3D-Printed Raney-Cu POCS as Promising New Catalysts for Methanol Synthesis - Poller, Maximilian J.; Renz, Christina; Wolf, Torsten; Körner, Carolin; Wasserscheid, Peter; Albert, Jakob (Catalysts, 2022)
Simultaneous generation and activation of Raney-type periodic open cellular structures (POCS) is a highly promising approach for generating novel structured methanol synthesis catalysts. In detail, we produced stable and highly active POCS from a Cu50Al50 alloy by additive manufacturing via Powder Bed Fusion by Electron Beam (PBF-EB) and activated them via selective leaching of aluminum in a sodium hydroxide/sodium zincate solution. The Raney-type Cu structures possessed catalytic methanol productivities of up to 2.2 g(MeOH)g(np-Cu) h(-1) (PBF-EB sticks) and 1.9 g(MeOH)g(np-Cu) h(-1) (PBF-EB POCS), respectively. Moreover, it was found that besides the nanoporous layer thickness, an optimum Zn/Cu ratio of 0.3-0.4 can also by adjusted by the leaching conditions.
CRIS-Team WoS Importer:2022-11-04

A 3D Printed Bone Tissue Engineering Scaffold Composed of Alginate Dialdehyde-Gelatine Reinforced by Lysozyme Loaded Cerium Doped Mesoporous Silica-Calcia Nanoparticles - Monavari, Mahshid; Medhekar, Rucha Shirish; Nawaz, Qaisar; Monavari, Mehran; Fuentes Chandia, Miguel Angel; Homaeigohar, Shahin; Boccaccini, Aldo R. (Macromolecular Bioscience, 2022)
A novel biomaterial comprising alginate dialdehyde-gelatine (ADA-GEL) hydrogel augmented by lysozyme loaded mesoporous cerium doped silica-calcia nanoparticles (Lys-Ce-MSNs) is 3D printed to create bioactive scaffolds. Lys-Ce-MSNs raise the mechanical stiffness of the hydrogel composite scaffold and induce surface apatite mineralization, when the scaffold is immersed in simulated body fluid (SBF). Moreover, the scaffolds can co-deliver bone healing (Ca and Si) and antioxidant ions (Ce), and Lys to achieve antibacterial (and potentially anticancer) properties. The nanocomposite hydrogel scaffolds can hold and deliver Lys steadily. Based on the in vitro results, the hydrogel nanocomposite containing Lys assured improved pre-osteoblast cell (MC3T3-E1) proliferation, adhesion, and differentiation, thanks to the biocompatibility of ADA-GEL, bioactivity of Ce-MSNs, and the stabilizing effect of Lys on the scaffold structure. On the other hand, the proliferation level of MG63 osteosarcoma cells decreased, likely due to the effect of Lys. Last but not least, cooperatively, alongside gentamicin (GEN), Lys brought about a proper antibacterial efficiency to the hydrogel nanocomposite scaffold against gram-positive and gram-negative bacteria. Taken together, ADA-GEL/Lys-Ce-MSN nanocomposite holds great promise for 3D printing of multifunctional hydrogel bone tissue engineering (BTE) scaffolds, able to induce bone regeneration, address infection, and potentially inhibit tumor formation and growth.
CRIS-Team WoS Importer:2022-07-29

Absorption medium and method for absorption of CO2 from a gas mixture, wherein the medium comprises water, an amine and an organic salt. - Schraven, A.; Schwab, P.; Salomon, T.; Schneider, R.; Rolker, J.; Willy, B.; Zehnacker, O.; Seiler, M.; Bahlmann, Matthias; Schulz, Peter; Wasserscheid, Peter (2015)
The invention relates to absorption medium and process for the absorption of CO2 from a gas mixt. The absorption of CO2 from a gas mixt. by bringing the gas mixt. in contact with an absorption medium, which contains water, 20 to 60 wt.% of amine and 0.01 to 0.1 mol/kg org. salts comprising a cation having quaternary nitrogen or phosphorus atom and an anion having a carbon-bonded, non-sterically hindered primary or secondary amino group, enables a high wt.-based CO2 absorption capacity in the cyclic operation of absorption and desorption. Bis(hydroxyethyl)dimethylammonium β-alaninate was prepd. by the reaction of bis(hydroxyethyl)dimethylammonium hydroxide with β-alanine and showed to be suitable as said org. salt for CO2 absorption. [on SciFinder(R)]
Keywords: amino acid salt absorbent carbon dioxide absorption

Absorption medium and process for the absorption of CO2 from a gas mixture. - Schraven, Alexander; Schwab, Peter; Salomon, Thomas; Schneider, Rolf; Rolker, J.; Willy, Benjamin; Zehnacker, Oliver; Seiler, Matthias; Bahlmann, Matthias; Schulz, Peter; Wasserscheid, Peter (2014)
The invention relates to absorption medium and process for the absorption of CO2 from a gas mixt. The absorption of CO2 from a gas mixt. by bringing the gas mixt. in contact with an absorption medium, which contains water, 20 to 60 wt.% of amine and 0.01 to 0.1 mol/kg org. salts comprising a cation having quaternary nitrogen or phosphorus atom and an anion having a carbon-bonded, non-sterically hindered primary or secondary amino group, enables a high wt.-based CO2 absorption capacity in the cyclic operation of absorption and desorption. Bis(hydroxyethyl)dimethylammonium β-alaninate was prepd. by the reaction of bis(hydroxyethyl)dimethylammonium hydroxide with β-alanine and showed to be suitable as said org. salt for CO2 absorption. [on SciFinder(R)]
Keywords: amino acid salt absorbent carbon dioxide absorption

Accelerating Oxygen-Reduction Catalysts through Preventing Poisoning with Non-Reactive Species by Using Hydrophobic Ionic Liquids - Zhang, Guirong; Munoz, Macarena; Etzold, Bastian (Angewandte Chemie International Edition, 2016)
Developing cost-effective electrocatalysts for the oxygen reduction reaction (ORR) is a prerequisite for broad market penetration of low-temperature fuel cells. A major barrier stems from the poisoning of surface sites by nonreactive oxygenated species and the sluggish ORR kinetics on the Pt catalysts. Herein we report a facile approach to accelerating ORR kinetics by using a hydrophobic ionic liquid (IL), which protects Pt sites from surface oxidation, making the IL-modified Pt intrinsically more active than its unmodified counterpart. The mass activity of the catalyst is increased by three times to 1.01 A mg-1Pt@0.9 V, representing a new record for pure Pt catalysts. The enhanced performance of the IL-modified catalyst can be stabilized after 30 000 cycles. We anticipate these results will form the basis for an unprecedented perspective in the development of high-performing electrocatalysts for fuel-cell applications.
EAM Import::2019-03-13

Acidic ionic liquids for n-alkane isomerization in a liquid-liquid or slurryphase reaction mode - Meyer, Carolin; Hager, Veit; Geburtig, Denise; Kohr, Carina; Haumann, Marco; Wasserscheid, Peter (DGMK International Conference on Catalysis - Innovative Applications in Petrochemistry and Refining, 2011)
Highly acidic ionic liquid (IL) catalysts offer the opportunity to convert n-alkanes at very low reaction temperatures. The results of IL catalyzed isomerization and cracking reactions of pure n-octane are presented. Influence of IL composition, [C C Im]Cl / AlCl / H SO and [C C Im]Cl / AlCl / 1-chlorooctane, on catalyst activity and selectivities to branched alkanes was investigated. Acidic chloroaluminate IL catalysts form liquid-liquid biphasic systems with unpolar organic product mixtures. Thus, recycling of the acidic IL is enabled by simple phase separation in the liquid-liquid biphasic reaction mode or the IL can be immobilized on an inorganic support with a large specific surface area. These supported ionic liquid phase (SILP) catalysts offer the advantage to get a macroscopically heterogeneous system while still preserving all benefits of the homogeneous catalyst which can be used for the slurry-phase n-alkane isomerization. The interaction of the solid support and acidic IL influences strongly the catalytic activity.

A comparative study of the desilication of channel- and cage-like zeolites - Shahid, Ameen; Inayat, Alexandra; Avadhut, Yamini; Hartmann, Martin; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2022)
Zeolites are very important catalysts in the chemical industry, but their intrinsic narrow micropore system often restricts the mass transport of reactant and product molecules. These mass transport limitations can be overcome by introducing a second larger pore system (meso-/macropores) into the zeolite crystals. Over the past decade, desilication of zeolites has emerged as a simple post-synthetic process to implement mesoporosity into zeolites. Here we present the investigation of the inﬂuence of framework topology on the formation of mesoporosity by the desilication process. For this purpose, the desilication behaviour of a channel-like system (ZSM-5/MFI-type) and a cage-like system (SSZ-13/CHA-type) are compared. It has been found that cage-like zeolite (SSZ-13) is more susceptible to the desilication process. The desilication of SSZ-13 zeolite resulted in drastic reduction of microporosity and crystallinity, while the microporosity and crystallinity of ZSM-5 gradually decreased with desilication time. By systematically studying the inﬂuence of various desilication parameters (e.g. treatment time, temperature and alkaline concentration), it has been found that there exists a direct correlation between the extraction of silicon and mesoporosity formation for the channel-like zeolite (ZSM-5) whereas in case of cage-like zeolite (SSZ-13) no direct correlation has been found.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Alkaline post treatment; Desilication; Hierarchy; Pore topology; SSZ-13; Zeolites; ZSM-5

A convenient method to access long-chain and functionalised mixed methylphosphonate esters and their application in the synthesis of ionic liquids. - Sachnov, Swetlana; Schulz, Peter; Wasserscheid, Peter (Chemical Communications, 2011)
Phosphonate monoester long-chain and functionalized ammonium ionic liqs. were prepd. by a two-step process, comprising SN2 alkylation of Me methylphosphonate monoester and reaction of the mixed neutral diester (R1O)(MeO)P(O)R2 with a 1-R-imidazole, resulting in preferential Me transfer and formation of the ionic liqs., 1-R-3-methylimidazolium (RMIM) salts [RMIM]+[(R1O)MePO2]- (R = Et, R1 = CH2CN, CH2CO2Me, Bu, C8H17). Some salts were prepd. also by R1 transfer to methylimidazole from sym. phosphonate diesters (R1O)2P(O)R2 [R1 = C8H17, Me(OCH2CH2)3, C12H25, Bu; R2 = Me, Ph]. The resulting ionic liqs. can be obtained in pure form, free of chloride and water. [on SciFinder(R)]
Keywords: ionic liq imidazolium phosphonate alkyl functionalized long chain prepn; unsym phosphonate diester imidazole alkylation methylation prepn ionic liq; quaternization alkylimidazole prepn ionic liq phosphonate long chain monoester; nitrile carboxylate functionalized phosphonate monoester imidazolium salt ionic liq

Acrylic Acid Synthesis from Lactide in a Continuous Liquid-Phase Process - Kadar, Julian; Heene-Würl, Nina; Nagengast, Jens; Kehrer, Matthias; Taccardi, Nicola; Wasserscheid, Peter; Collias, Dimitris; Dziezok, Peter; Hahn, Simon; Albert, Jakob (ACS Sustainable Chemistry & Engineering, 2019)
Synthesis of bulk chemicals from biogenic resources is gaining increasing interest in industry and academia. In the present study, we demonstrate the continuous production of acrylic acid (AA) from biogenic lactide in a liquid-phase reaction using the ionic liquid tetrabutylphosphonium bromide as reaction medium and 2-bromopropionic acid as acid catalyst precursor. We here present a ﬁrst continuous setup for AA production from LA derivatives in the liquid phase on a 10 L scale. The process operates at 200 °C and leads to AA yields of 72% in industrially relevant space−time−yields of up to 50 g/(h·L). We demonstrate continuous operation over 6 h time-on-stream, eﬃcient product isolation and successful catalyst recycling.<br
Keywords: Lactide; Liquid phase; Acrylic acid; Continuous process; Miniplant; Upscaling

Additively manufactured Raney-type Copper catalyst for methanol synthesis - Heßelmann, Christina; Wolf, Torsten; Galgon, Florian; Körner, Carolin; Albert, Jakob; Wasserscheid, Peter (Catalysis: Science and Technology, 2020)
We describe a novel approach to prepare cellular RANEY (R)-type catalysts by combining additive manufacturing (AM) of a Cu-Al alloy followed by selective leaching of Al with aqueous NaOH solutions. Three-dimensional cellular geometries of Cu-70Al were fabricated by laser-metal-deposition (LMD). After activation by an optimized leaching process, highly active and selective catalytic structures for CO hydrogenation to methanol were obtained.
CRIS-Team WoS Importer:2020-01-17

Additive manufacturing meets reaction engineering - Novel Raney® copper catalyst structures for methanol synthesis - Heßelmann, Christina; Wolf, T.; Körner, Carolin; Albert, J.; Wasserscheid, P. (DGMK Tagungsbericht, 2019)
In the current work, we present a new, interdisciplinary approach between reaction engineering and additive manufacturing to produce a structured Raney copper catalyst. Currently, structured catalysts are being developed by coating a carrier structure with the catalytically active species. This procedure involves several process steps, like multiple coating, impregnation, calcination, and catalytic activation. With our new top-down approach, periodic open cellular structures (POCS) will be additively manufactured by selective electron beam melting from a commercial CuAl alloy. The catalyst structure is activated by the principal of Raney®, where part of the aluminum is leached out with sodium hydroxide. For maintaining high stability, just the external surface is activated by alkali leaching, whereas the unreacted CuAl core will improve the heat-transfer of the catalyst structure (s. Figure 1). Our new innovative catalyst structures are interesting for exothermic gas-phase reactions (e.g. methanol synthesis) due to their physical properties. The catalytically active nanoporous copper layer contacts the remaining CuAl core directly. Therefore the heat of reaction can be optimally dissipated. In our work, we will investigate the leaching of additive produced simple rods, which correspond to the dimensions of the strut size of typical POCS. We want to find out optimal leaching conditions for highly active and stable Raney-Cu rods. The leaching reaction is investigated by measuring the Al concentration in the solution. Moreover, we will measure the active copper surface area with N2O decomposition. CT measurements will examine the thickness of the nanoporous layer. Catalytic tests for methanol synthesis of simple additive manufactured Raney Cu cylinders show promising results. Based on the knowledge gained in the leaching study, complex catalyst structures will also be activated and tested in the CO hydrogenation to methanol.
CRIS-Team Scopus Importer:2021-04-20

Additive manufacturing of interpenetrating periodic open cellular structures (interPOCS) with in operando adjustable flow characteristics - Do, Giang; Geißelbrecht, Michael; Schwieger, Wilhelm; Freund, Hannsjörg (Chemical Engineering and Processing, 2020)
Structured catalyst supports and structured reactors offer interesting features to address heat and mass transport challenges in catalytic processes. The present work addresses the unique role of so-called interpenetrating periodic open cellular structures (interPOCS) as a geometrically flexible system enabling in operando adjustment of fluid flow characteristics. The interPOCS studied in this work consist of an interwoven structure of two POCS with a defined offset, each based on a diamond unit cell. The specific surface area and porosity, as the structures’ influential morphology parameters, were derived as a function of cell size and strut thickness, respectively. Both, POCS and interPOCS of different geometrical parameters were designed via computer-aided design, fabricated by fused deposition modeling and geometrically characterized. The influence of the structure offset and the geometrical dimension on the pressure drop was investigated in detail. From experimental data, the coefficients of an Ergun-type pressure drop correlation were fitted and a two cavity channel model was established to describe the dependency of the pressure drop on the offset position. The possibility of the structure shift in interPOCS represents a highly interesting and versatile option for in operando adjustment in catalytic processes.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Additive manufacturing; Flexible flow control; Flow field; Periodic open cellular structures (POCS); Pressure drop; Structured reactor

Adsorption Device Based on a Langatate Crystal Microbalance for High Temperature High Pressure Gas Adsorption in Zeolite H-ZSM-5. - Ding, Wenjin; Baracchini, G; Klumpp, Michael; Schwieger, Wilhelm; Dittmeyer, Roland (Journal of Visualized Experiments, 2016)
We present a high-temperature and high-pressure gas adsorption measurement device based on a high-frequency oscillating microbalance (5 MHz langatate crystal microbalance, LCM) and its use for gas adsorption measurements in zeolite H-ZSM-5. Prior to the adsorption measurements, zeolite H-ZSM-5 crystals were synthesized on the gold electrode in the center of the LCM, without covering the connection points of the gold electrodes to the oscillator, by the steam-assisted crystallization (SAC) method, so that the zeolite crystals remain attached to the oscillating microbalance while keeping good electroconductivity of the LCM during the adsorption measurements. Compared to a conventional quartz crystal microbalance (QCM) which is limited to temperatures below 80 °C, the LCM can realize the adsorption measurements in principle at temperatures as high as 200-300 °C (i.e., at or close to the reaction temperature of the target application of one-stage DME synthesis from the synthesis gas), owing to the absence of crystalline-phase transitions up to its melting point (1,470 °C). The system was applied to investigate the adsorption of CO2, H2O, methanol and dimethyl ether (DME), each in the gas phase, on zeolite H-ZSM-5 in the temperature and pressure range of 50-150 °C and 0-18 bar, respectively. The results showed that the adsorption isotherms of these gases in H-ZSM-5 can be well fitted by Langmuir-type adsorption isotherms. Furthermore, the determined adsorption parameters, i.e., adsorption capacities, adsorption enthalpies, and adsorption entropies, compare well to literature data. In this work, the results for CO2 are shown as an example.

Adsorption Motifs and Molecular Orientation at the Ionic Liquid/Noble Metal Interface: [C(2)C(1)Im][NTf2] on Pt(111) - Hohner, Chantal; Fromm, Lukas; Schuschke, Christian; Taccardi, Nicola; Xu, Tao; Wasserscheid, Peter; Görling, Andreas; Libuda, Jörg (Langmuir, 2021)
In solid catalysts with ionic liquid layers (SCILLs), ionic liquid (IL) thin films are used to modify the activity and selectivity of catalytic materials. In this work, we investigated the adsorption behavior of the IL 1-ethyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide [C(2)C(1)Im][NTf2] on Pt(111) by combining experimental and theoretical studies. Under ultrahigh vacuum (UHV) conditions, the IL was deposited onto a Pt(111) single crystal surface by physical vapor deposition (PVD) at different surface temperatures (200, 300, and 400 K). The adsorption process was monitored by in situ infrared reflection absorption spectroscopy (IRAS). Complementary to the IRAS studies, we performed density functional theory (DFT) calculations and analyzed the adsorption motifs and orientation of the IL ions. In total, we calculated four different systems: (a) [C(2)C(1)Im](+) and [NTf2](-) ions in the gas phase; [NTf2](-) anions in (b) small (4 x 4) and (c) large (6 x 6) Pt(111) supercells; and (d) a complete ion pair of [C(2)C(1)Im][NTf2] in a (6 x 6) Pt(111) supercell. Based on DFT, we simulated IR spectra and compared them to the experimental data. Our results suggest that the binding motif and orientation of the IL is strongly dependent on the actual IL coverage. In the monolayer (ML), [NTf2](-) interacts strongly with the metal surface and adopts a specific orientation in which it interacts with the Pt surface via the SO2 groups. Also the [C(2)C(1)Im](+) cations adopt a preferential orientation up to coverages of 1 ML. Upon transition to the multilayer region, the specific orientation of the ions is gradually lost.
CRIS-Team WoS Importer:2021-11-12

Advanced and In-Situ Electron Microscopy Investigation of Phase Composition and Phase Transformation in Ga-Rh Liquid Metal Catalysts - Wu, Mingjian; Grabau, Mathias; Taccardi, Nicola; Papp, Christian; Steinrück, Hans-Peter; Wasserscheid, Peter; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

A feasible way to remove the heat during adsorptive methane storage - Gütlein, Stefan; Burkard, Christoph; Zeilinger, Johannes; Niedermaier, Matthias; Klumpp, Michael; Kolb, Veronika; Jess, Andreas; Etzold, Bastian (Environmental Science & Technology, 2015)
Methane originating from biogas or natural gas is an attractive and environmentally friendly alternative to gasoline. Adsorption is seen as promising storage technology, but the heat released limits fast filling of these systems. Here a lab scale adsorptive methane storage tank, capable to study the temperature increase during fast filling, was realized. A variation of the filling time from 1 h to 31 s, showed a decrease of the storage capacity of 14% and temperature increase of 39.6 °C. The experimental data could be described in good accordance with a finite element simulation solving the transient mass, energy, and impulse balance. The simulation was further used to extrapolate temperature development in real sized car tanks and for different heat pipe scenarios, resulting in temperature rises of approximately 110 °C. It could be clearly shown, that with heat conductivity as solei mechanism the heat cannot be removed in acceptable time. By adding an outlet to the tank a feed flow cooling with methane as heat carrier was realized. This setup was proofed in simulation and lab scale experiments to be a promising technique for fast adsorbent cooling and can be crucial to leverage the full potential of adsorptive methane gas storage.
CRIS-Team Scopus Importer:2023-08-15

A future energy supply based on Liquid Organic Hydrogen Carriers (LOHC) - Teichmann, Daniel; Arlt, Wolfgang; Wasserscheid, Peter; Freymann, Raymond (Energy and Environmental Science, 2011)
This contribution describes a concept for the establishment of a competitive energy distribution network based on Liquid Organic Hydrogen Carrier (LOHC) compounds. These compounds are characterized by the fact that they can be loaded and un-loaded with considerable amounts of hydrogen in a cyclic process. This concept links the technical challenge of storing temporary and local energy over-production from regenerative sources with the vision of a sustainable, hydrogen-based mobility. The proposed LOHC compounds have many physico-chemical similarities to diesel. Thus, LOHCs could make use of the existing energy infrastructure (e.g. tank ships, storage tanks or fueling stations) and enable a slow and step-wise replacement of the existing hydrocarbon fuels by alternative LOHC fuels. We consider LOHCs as an attractive way to provide wind and solar energy for mobility applications in the form of liquid energy carrying molecules of similar energy storage densities and manageability as today's fossil fuels.

Aggregation behaviour of chiral ionic liquids - Schulz, Peter; Schneiders, Karola; Wasserscheid, Peter (Tetrahedron-Asymmetry, 2009)
The diastereomeric ionic liquid (IL) (1R,2S)-ephedrinium (RS)-methoxytrifluorophenylacetate 1 was synthesized and its aggregation behavior and diastereomeric interaction were investigated using two independent methods. The aggregation number of the IL in methylene chloride was determined by diffusion ordered NMR spectroscopy. Furthermore the concentration dependence of the signal split of the two diastereomeric ILs (1R,2S)-ephedrinium (R)-methoxytrifluorophenylacetate and (1R,2S)-ephedrinium (S)-methoxytrifluorophenylacetate was measured and could be linked to the aggregation number. © 2009 Elsevier Ltd. All rights reserved.

Aggregation Models of Potential Cyclical Trimethylsulfonium Dicyanamide Ionic Liquid Clusters - Carper, W. Robert; Langenwalter, Kevin; Nooruddin, Naveed S.; Kullman, Michael J.; Gerhard, Dirk; Wasserscheid, Peter (Journal of Physical Chemistry B, 2009)
Raman and infrared spectra of trimethylsulfonium dicyanamide [(CH3)3SN(CN)2] are reported and accurately reproduced by DFT methods (B3LYP and B3PW91), MP2, and MP3, and to a lesser extent by the RHF method. The (CH3)3SN(CN)2 ionic liquid forms two isomeric dimers that are of cyclic structure, one of which is 13 kcal/mol lower in energy than the other. Both isomeric cyclic pairs (versions 1 and 2), [(CH3)3SN(CN)2]2, have the potential to further combine and form a common structure containing four pairs of (CH3)3SN(CN)2. This structure can then conceivably undergo a stacking procedure to form extended ionic liquid nanotubes of eight ionic liquids, [(CH3)3SN(CN)2]8. The possible formation of gas phase ionic liquid clusters of two, four, and eight trimethylsulfonium dicyanamide ionic liquids is supported by highly exergonic free energy changes obtained from B3LYP/(6-311+G(d,p)) density functional calculations.

A Highly Stable Bimetallic Transition Metal Phosphide Catalyst for Selective Dehydrogenation of n-Heptane - Stöber, Robert; Mai, Florian; Oshin, Sebastian; Körner, Andreas; Hutzler, Andreas; Schühle, Patrick (ChemCatChem, 2022)
In this work, we demonstrate RuP2-MoP catalysts being highly stable and selective for the dehydrogenation of long-chain alkanes like n-heptane. Compared to a monometallic MoP catalyst, the bimetallic system substantially increases n-heptene selectivity from 40 % towards 80 %. This effect can be traced back to a reduced surface acidity, suppressing the competitive hydrogenolysis reaction. The active transition metal phosphide is, furthermore, compared to its phosphorous-free RuMo-counterpart. As revealed by STEM-EDX investigations, incorporation of phosphorous results in the formation of separated metal phosphide clusters instead of an intermetallic alloy. In the dehydrogenation of n-heptane the phosphorous modification clearly avoids catalyst deactivation and maintains the high n-heptene selectivity. X-ray diffraction, elemental analysis and STEM-EDX further reveal that catalyst coking and the formation of less active molybdenum carbide phases is effectively suppressed by phosphorous incorporation, making RuP2-MoP an attractive system for selective dehydrogenation of long-chain alkanes.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Alkane dehydrogenation; Coking resistance; Heterogeneous catalysis; Molybdenum catalyst; Transition metal phosphides

Alcohol-Activated Vanadium-Containing Polyoxometalate Complexes in Homogeneous Glucose Oxidation Identified with 51V-NMR and EPR Spectroscopy - Wesinger, Stefanie; Mendt, Matthias; Albert, Jakob (ChemCatChem, 2021)
Alcoholic solvents, especially methanol, show an activating affect for heteropolyacids in homogenously catalysed glucose transformation reactions. In detail, they manipulate the polyoxometalate-based catalyst in a way that thermodynamically favoured total oxidation to CO2 can be completely supressed. This allows a nearly 100 % carbon efficiency in the transformation reaction of glucose to methyl formate in methanolic solution at mild reaction conditions of 90 °C and 20 bar oxygen pressure. By using powerful spectroscopic tools like 51V-NMR and continuous wave EPR we could unambiguously prove that the vanadate-methanol-complex[VO(OMe)3]n is responsible for the selectivity shift in methanolic solution compared to the aqueous reference system.
CRIS-Team Scopus Importer:2021-06-25
Keywords: EPR spectroscopy; Keggin polyoxometalates; NMR spectroscopy; solvent effect; vanadium redox chemistry

Alkali hydroxide-modified Ru/γ-Al2O3 catalysts for ammonia decomposition - Bajus, Stephanie; Agel, Friederike; Kusche, Matthias Manfred; Ní Bhriain, Nollaig; Wasserscheid, Peter (Applied Catalysis A-General, 2016)
We herein present an easy approach to increase drastically the catalytic activity of Ru/ extgreekg-Al2O3 catalysts in ammonia decomposition by surface modification with alkali hydroxides. The best activities have been achieved by a catalyst modification with lithium hydroxide in a Li/Al ratio of 1.7. In contrast, coatings with potassium and caesium hydroxide caused mass transfer limitations in the catalytic material already at low amounts (ratios alkali/Al <0.2–0.3). MAS ssNMR and XRD studies indicate the in-situ formation of alkali aluminates resulting in a basic modification of the support.
EAM Import::2019-03-13
Keywords: Ammonia decomposition; Ruthenium; Alkali doping; Support modification; Lithium aluminate

Alkyl chain length-dependent surface reaction of dodecahydro-N-alkylcarbazoles on Pt model catalysts - Gleichweit, Christoph; Amende, Maximilian; Bauer, Udo; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Müller, Michael; Koch, Marcus; Bachmann, Philipp; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Chemical Physics, 2014)
The concept of liquid organic hydrogen carriers (LOHC) holds the potential for large scale chemical storage of hydrogen at ambient conditions. Herein, we compare the dehydrogenation and decomposition of three alkylated carbazole-based LOHCs, dodecahydro-N-ethylcarbazole (H-NEC), dodecahydro-N- propylcarbazole (H-NPC), and dodecahydro-N-butylcarbazole (H -NBC), on Pt(111) and on AlO-supported Pt nanoparticles. We follow the thermal evolution of these systems quantitatively by in situ high-resolution X-ray photoelectron spectroscopy. We show that on Pt(111) the relevant reaction steps are not affected by the different alkyl substituents: for all LOHCs, stepwise dehydrogenation to NEC, NPC, and NBC is followed by cleavage of the C-N bond of the alkyl chain starting at 380-390 K. On Pt/AlO, we discern dealkylation on defect sites already at 350 K, and on ordered, (111)-like facets at 390 K. The dealkylation process at the defects is most pronounced for NEC and least pronounced for NBC. © 2014 AIP Publishing LLC.

A microelectrode study of triiodide diffusion coefficients in mixtures of room temperature ionic liquids, useful for dye-sensitised solar cells - Wachter, Philipp; Schreiner, Christian; Zistler, Markus; Gerhard, Dirk; Wasserscheid, Peter; Gores, Heiner J. (Microchimica Acta, 2008)
The diffusion coefficients of triiodide in binary mixtures of ionic liquids at 25 +/- 0.05 degrees C were determined via steady-state cyclic voltammetry at platinum disk microelectrodes in five different electrolyte systems, all representing potential ionic liquid based electrolytes for dye-sensitised solar cells. These electrolytes were composed of iodine, 1-methyl-3-propylimidazolium iodide (acting as iodide source) and a second lower viscous ionic liquid, namely 1-ethyl-3-methylimidazolium dicyanamide, 1-ethyl-3-methylimidazolium tetrafluoroborate or 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) and were investigated either at fixed ionic liquid composition and varying iodine concentration or at fixed iodine concentration and varying 1-methyl-3-propylimidazolium iodide content. To check and optimise our measurement set-up, four Pt disk microelectrodes with four different electrode radii (0.3-5 mu m) were tested at a well known system (ferrocene/tetraethylammonium tetrafluoroborate/acetonitrile solutions). The radius of each electrode was controlled by scanning electron microscopy at the beginning and during the work.
Keywords: microelectrode; diffusion coefficient; ionic liquids; non-Stokesian transport behaviour

Amino-functionalized silica materials for carbon dioxide capture - Schwieger, Wilhelm; Abbo, Hanna; Piet, Marvin; Titinchi, Salam; Bolland, Olav (ASME 2015 9th International Conference on Energy Sustainability, ES 2015, collocated with the ASME 2015 Power Conference, the ASME 2015 13th International Conference on Fuel Cell Science, Engineering and Technology, and the ASME 2015 Nuclear Forum, 2015)
Amine-functionalized mesoporous silica has attracted much attention as a promising chemical sorbent for capturing carbon dioxide. It has the combination of several features viz., high adsorption capacity, high selectivity toward CO, fast kinetics, mild conditions for desorption and should be stable under operating conditions. In this study, a chemical grafting route has been developed to synthesize mesoporous adsorbents with amines functionalization for CO capture. The initial silylation step was achieved by grafting of different silane linkers (3-aminopropyl)-trimethoxysilane (APS) and 3-chloropropyl)-trimethoxysilane (CPS) via direct condensation and hydrolysis reaction. After silylation the CPS-supports was reacted with tris(2-aminoethyl)amine (TREN) to introduce the amine group to increase the adsorptive capabilities for these sorbents. The synthesized sorbents were characterized by N2 adsorption/desorption, XRD, FTIR and HR-SEM. The adsorption capacities of the modified solid sorbents show a significant enhancement in their adsorption capacity by 3-4 times higher than that of the parent materials which indicate the affirmative impact of amines for CO adsorption after grafting.
Keywords: Adsorption capacity; Carbon capture; Mesoporous adsorbents; Silylation

A multimodular pseudoheterogeneous model framework for optimal design of catalytic reactors exemplified by methanol synthesis - Kaiser, Markus; Freund, Hannsjörg (Chemical Engineering Science, 2019)
Model-based design of chemical reactors via dynamic optimization can be performed using a recently developed approach called Multi-Level Reactor Design (MLRD). As a start, the MLRD method, its extensions and applications over the last ten years are reviewed compactly. In the main part of this contribution, a further extension to the model framework applied within this method allowing for the rigorous consideration of intrapellet transport processes in heterogeneously catalyzed systems is introduced. Accordingly, a system of coupled differential equations describing the mass and energy balance of both, reactor and catalyst pellet is set up. Balance equations are kept strictly distinguished from kinetic approaches, leaving the latter to be easily exchangeable. This leads to a multimodular model structure used to incorporate different models for diffusion flux, heat transport and pressure drop. The type of the extended model structure is "pseudoheterogeneous", i.e., the domain in which chemical reactions take place is shifted from a commonly applied pseudohomogeneous mixed phase to the catalyst interior while a solid phase on reactor scale is not modelled. Applying the extended and modularized method to methanol synthesis as a case study reveals considerable concentration and temperature gradients inside the catalyst. These are neglected implicitly in pseudohomogeneous approaches which can lead to a violation of the allowed range of operating conditions for a given catalyst. The extended MLRD model framework using a pseudoheterogeneous model overcomes this drawback and allows for apparatus independent reactor design while meeting process specific constraints in both the bulk gas and the catalyst phase. Further, a systematic investigation applying 27 combinations of diffusion flux, heat transport and pressure drop models reveals that a certain performance can be reached with any combination, while the deduced reactor design differs significantly. (C) 2019 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-07-02

An Adaptive Self-Healing Ionic Liquid Nanocomposite Membrane for Olefin-Paraffin Separations. - Pitsch, Fee; Krull, Florian Felix; Agel, Friederike; Schulz, Peter; Wasserscheid, Peter; Melin, Thomas; Wessling, Matthias (Advanced Materials, 2012)
The presented nanocomposite membrane is intrinsically safe, highly permeable as well as highly selective by employing the anhyd. functionalized ionic liq. [Ag(olefin)x]+[Tf2N]-. Its transport properties with respect to propylene/propane sepn. factor qual. correspond to the predicted selective propylene transport, which is based on mixed-gas soly. and diffusion coeff. measurements in the ionic liq. [on SciFinder(R)]
Keywords: silver triflimide membrane propylene propane sepn

An advanced method to manufacture hierarchically structured carbide-derived carbon monoliths - Fey, Tobias; Zierath, Bodo; Kern, Andreas; Greil, Peter; Etzold, Bastian (Carbon, 2014)
The preparation of carbide-derived carbon (CDC) monoliths with a hierarchically structure in the mu m and pm range is presented. Basis is the manufacturing of porous cellular SiC ceramics based on a biomorphous approach with pm porosity and subsequent conformal conversion to CDC by reactive extraction with chlorine. The SiC ceramics can be sintered at low temperatures and short times (1500 degrees C, 2 h) compared to classical preparation methods. The SiC ceramics show a macro pore volume (1-10 mu m channel size) of 0.56 ml g(-1), which corresponds to 1.5 ml g(-1) in the resulting CDC. The final carbon material exhibits an additional nano pore volume of 0.525 ml g(-1) with a mean slit pore size of 0.86 nm. Mechanical stabilities of the highly porous CDC are excellent (bending strength 2.1 +/- 0.2 MPa, corrected Weibull modulus 8.7, characteristic strength 2.2 MPa and Youngs modulus 10.0 +/- 0.5 GPa). The reactive extraction of the carbide monoliths shows very high reaction rates, approx. two dimensions faster (95x) compared to non-porous samples. Thus the manufacturing of the structured carbide and CDC can be performed at lower costs. (C) 2013 Elsevier Ltd. All rights reserved.

Analysis and optimal design of an ethylene oxide reactor - Peschel, Andreas; Karst, Florian; Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering Science, 2011)
In this work, a recently proposed multi-level reactor design methodology (Peschel et al., 2010) is extended and applied for the optimal design of an ethylene oxide reactor. In a first step, the optimal reaction route is calculated taking various process intensification concepts into account. The potential of each reaction concept can be efficiently quantified, which is the economic basis for the design of advanced reactors. Based on these results, a promising concept is further investigated and a technical reactor is designed. As an extension to the design method, reactor design criteria for external and internal heat and mass transfer limitations are directly included in the optimization approach in order to design the catalyst packing. The derived reactor concept is investigated with a detailed 2D reactor model accounting for radial concentration and temperature gradients in addition to a radial velocity profile.The example considered in this work is the production of ethylene oxide which is one of the most important bulk chemicals. Due to the high ethylene costs, the selectivity is the main factor for the economics of the process. A membrane reactor with an advanced cooling strategy is proposed as best technical reactor. With this reactor design it is possible to increase the selectivity of the ethylene epoxidation by approximately 3% compared to an optimized reference case. © 2011 Elsevier Ltd.
Keywords: Chemical reactors; Design; Elementary process functions; Ethylene oxide; Optimization; Process intensification

Analysis of evaporation and thermal decomposition of ionic liquids by thermogravimetrical analysis at ambient pressure and high vacuum - Heym, Florian; Etzold, Bastian; Kern, Christoph; Jess, Andreas (Green Chemistry, 2011)
Ionic liquids (ILs) are widely discussed as alternative green solvents not only because of their unique chemical properties, but also because of their extremely low vapour pressure and – at least in some cases – relatively high thermal stability. Two complementary methods are analyzed and compared to determine both the rate constant of decomposition and the vapour pressure of four ILs: (1) thermogravimetrical analysis at ambient pressure (TGap) with an overflow of inert gases, and (2) high vacuum (HV) experiments with a magnetic suspension balance (MSB). At ambient pressure, [EMIM][MeSO3] and [EMIM][CF3SO3] decompose without a significant contribution of evaporation, which leads to the rate constant of thermal degradation. For both ILs, the vapour pressure can only be determined at HV by the MSB, because the evaporation rate is then higher than the decomposition rate. For the relatively volatile ILs [EMIM][NTf2] and [BMIM][NTf2] the vapour pressure can be derived both by the MSB at HV as well as by TGap. General strategies to determine the volatility and stability of ILs and criteria for the maximum operation temperature with regard to decomposition and evaporation are presented. © 2011 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-08-15

Analysis of reaction mixtures of perhydro-dibenzyltoluene using two-dimensional gas chromatography and single quadrupole gas chromatography - Modisha, Phillimon M.; Jordaan, Johan H. L.; Bösmann, Andreas; Wasserscheid, Peter; Bessarabov, Dmitri (International Journal of Hydrogen Energy, 2018)
Energy storage via liquid organic hydrogen carrier (LOHC) systems has gained significant attention in recent times. A dibenzyltoluene (DBT) based LOHC offers excellent properties which largely solve today's hydrogen storage challenges. Understanding the course of the dehydrogenation reaction is important for catalyst and process optimization. Therefore, reliable and exact methods to determine the degree of hydrogenation (doh) are important. We here present other possible techniques, namely: comprehensive two-dimensional gas chromatography coupled with time of flight mass spectrometry (2D-GC-TOF-MS) and single quadrupole-mass spectrometry gas chromatogram system (GC-SQ-MS). The 2D-GC-TOF-MS results indicate that isomer fractions lose three molecules of hydrogen, as follows: H18-DBT, H12-DBT, H6-DBT and H0-DBT, and the doh decreases with an increase in dehydrogenation temperature. 1H NMR and GC-SQ-MS were employed as additional analytical techniques. The GC-SQ-MS was also used to analyse decomposition products that result from thermal cracking of reaction mixture molecules.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Dehydrogenation; Dibenzyltoluene; Hydrogen storage; Liquid organic hydrogen carrier (LOHC); Time-of-flight mass spectrometry; Two-dimensional gas chromatography

Analysis of the flow field and pressure drop in fixed-bed reactors with the help of lattice Boltzmann simulations - Zeiser, Thomas; Steven, Martin; Freund, Hannsjörg; Lammers, Peter; Brenner, Gunter; Durst, Franz; Bernsdorf, Jörg (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2002)
The pressure drop of technical devices is a crucial property for their design and operation. In this paper, we show how the results of lattice Boltzmann simulations can be used in science and engineering to improve the physical understanding of the pressure drop and the flow inhomogeneities in porous media, especially in sphere-packed fixed-bed reactors with low aspect ratios. Commonly used pressure drop correlations are based on simplified assumptions such as the capillary or tortuosity model, which do not reflect all hydrodynamic effects. Consequently, empirical correlations for certain classes of media have been introduced in the past to bridge the gap between the models and the experimental findings. As is shown in this paper by the detailed analysis of the velocity field in the void space of packed beds, the pressure drop is due to more complex hydrodynamics than considered in the above-mentioned models. With the help of lattice Boltzmann simulations, we were able to analyse the different contributions to the total dissipation, namely shear and deformation of the fluid, for different geometries over a wide range of Reynolds numbers. We further show that the actual length of the flow paths changes considerably with the radial and circumferential position.

An appraisal of the heat transfer properties of metallic open-cell foams for strongly exo-/endo-thermic catalytic processes in tubular reactors - Bianchi, Enrico; Heidig, Tobias; Visconti, Carlo Giorgio; Groppi, Gianpiero; Freund, Hannsjörg; Tronconi, Enrico (Chemical Engineering Journal, 2012)
We assess the heat transfer properties of open-cell foams, i.e. cellular materials made of interconnected struts, in view of their use as catalyst carriers. Metallic foams made of FeCrAlY and aluminum with 89-95% porosities and 10-40 PPI (pores per linear in.) pore densities were investigated. Geometrical measurements of all samples were performed using optical microscopy. X-ray micro-computed tomography techniques were applied for a detailed morphological characterization of selected samples. Heat transfer data were collected in heating and cooling flow experiments, under operating conditions expected to involve conductive as well as both convective and radiative heat exchange, using N-2 flow rates from 15 to 35 NI min(-1) in the 400-800 K T-range. The effective radial and axial conductivities and the wall heat transfer coefficient were estimated from the measured steady-state temperature profiles. The estimates of the effective radial conductivity were between 0.3 W m(-1) K-1 and 0.9 W m(-1) K-1 for FeCrAlY samples with similar to 95% porosity, while they increased up to 7.7 W m(-1) K-1 for aluminum samples with similar to 89% porosity. The latter value is comparable with or higher than typical effective radial thermal conductivities in technical packed bed reactors. The role of heat conduction in the foam solid matrix was also analyzed by solving the Laplace heat diffusion equation in a 3D mesh of foam samples virtually reconstructed by micro-computed tomography. It was found that the conductive mechanism is the dominant contribution to the effective radial conductivity for both FeCrAlY and Al foams. In the case of highly conductive materials, such as Al, the convective and radiative contributions are essentially negligible, and the wall coefficient (h(w)) becomes the controlling heat transfer parameter. The estimates of the wall heat transfer coefficient exhibit an inverse dependency on the foam cell size, but are unaffected by changes in the porosity and in the fabrication material of the foams. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Metallic foams; Sponges; Catalyst support; Effective radial conductivity; Process intensification; Heat transfer

A new analytical approximation to the extended Brinkman equation - Maußner, Johannes; Pietschak, Alexander; Freund, Hannsjörg (Chemical Engineering Science, 2017)
Keywords: Reactor optimization; Heat transfer; Radial flow profile; Fixed bed reactors; Brinkman equation

A new class of double alkyl-substituted, liquid crystalline imidazolium ionic liquids - A unique combination of structural features, viscosity effects, and thermal properties - Wang, Xinjiao; Heinemann, Frank Wilhelm; Yang, Mei; Melcher, Berthold Ulrich; Fekete, Melinda; Mudring, Anja-Verena; Wasserscheid, Peter; Meyer, Karsten (Chemical Communications, 2009)
1,3-Didodecylimidazolium salts have been prepared as first representatives of a new class of ionic liquid crystals (ILCs), showing thermotropic liquid crystalline behaviour in an extended temperature range below 70 °C. Remarkably strong non-Newtonian viscosity behaviour was found for the liquid-crystalline state of these ILCs. © 2009 The Royal Society of Chemistry.

A New Class of Task-Specific Imidazolium Salts and Ionic Liquids and Their Corresponding Transition-Metal Complexes for Immobilization on Electrochemically Active Surfaces - Seidl, Vera; Romero Cordero, Angel Heriberto; Heinemann, Frank Wilhelm; Scheurer, Andreas; Vogel, Carola; Unruh, Tobias; Wasserscheid, Peter; Meyer, Karsten (Chemistry - A European Journal, 2022)
Adding to the versatile class of ionic liquids, we report the detailed structure and property analysis of a new class of asymmetrically substituted imidazolium salts, offering interesting thermal characteristics, such as liquid crystalline behavior, polymorphism or glass transitions. A scalable general synthetic procedure for N-polyaryl-N’-alkyl-functionalized imidazolium salts with para-substituted linker (L) moieties at the aryl chain, namely [LPhmImHR]+ (L=Br, CN, SMe, CO2Et, OH; m=2, 3; R=C12, PEGn; n=2, 3, 4), was developed. These imidazolium salts were studied by single-crystal X-ray diffraction (SC-XRD), NMR spectroscopy and thermochemical methods (DSC, TGA). Furthermore, these imidazolium salts were used as N-heterocyclic carbene (NHC) ligand precursors for mononuclear, first-row transition metal complexes (MnII, FeII, CoII, NiII, ZnII, CuI, AgI, AuI) and for the dinuclear Ti-supported Fe-NHC complex [(OPy)2Ti(OPh2ImC12)2(FeI2)] (OPy=pyridin-2-ylmethanolate). The complexes were studied concerning their structural and magnetic behavior via multi-nuclear NMR spectroscopy, SC-XRD analyses, variable temperature and field-dependent (VT-VF) SQUID magnetization methods, X-band EPR spectroscopy and, where appropriate, zero-field 57Fe Mössbauer spectroscopy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: carbene ligands; electronic structure; ionic liquids; solid-state structure; thermal properties

A new concept for the global distribution of solar energy: energy carrying compounds - Müller, Benjamin; Arlt, Wolfgang; Wasserscheid, Peter (Energy and Environmental Science, 2011)
A new concept for storage and superregional transport of solar energy from the earth's desert belt is proposed. The concept is based on solid alkaline earth metal compounds, showing an energy-rich and an energy-lean state which are used in an energy distribution cycle. The concept is evaluated with regard to overall solar-to-electricity efficiency and benchmarked by the overall efficiency of the DESERTEC concept. For a scenario assuming that the current share of electricity production from lignite coal in Germany is replaced by the here proposed concept, the CO(2) mitigation potential is calculated. The assessment shows that the proposed concept can compete with the benchmark and even shows high potential for optimization.

A new heat transfer correlation suited for the design of fixed-bed reactors via numerical optimization - Pietschak, Alexander; Dixon, Anthony G.; Freund, Hannsjörg (Chemical Engineering Science, 2020)
A new correlation to account for the radial heat transfer in fixed-beds modeled via a 2D pseudo-homogeneous approach is presented in this contribution. Compared to state-of-the-art heat transfer correlations, no points of discontinuity are included in the definition of the new heat transfer correlation. This enables a direct application of gradient-based solution algorithms for the reactor design via numerical optimization. The presented heat transfer correlation is based on individually considering the influence of the radial velocity profile and radial bed voidage profile in the fixed-bed on the heat transfer. The predictive performance of the presented heat transfer correlation is benchmarked against the state-of-the-art heat transfer correlation proposed by Winterberg et al. for both, spherical and cylindrical shaped particles, based on an evaluation of a broad measurement data basis from literature heat transfer experiments.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Catalytic fixed-bed; Heat transfer; Numerical optimization; Reactor design; Transport phenomena

A New Process for Azeotropic Mixture Separation by Phase Behavior Tuning Using Pressurized Carbon Dioxide - Ye, Kongmeng; Freund, Hannsjörg; Sundmacher, Kai (Industrial & Engineering Chemistry Research, 2013)
A fundamental approach to separate azeotropic mixtures by tuning the phase behavior using pressurized CO2 as a tunable solvent was studied. Following this new process concept, two process variants were put forward to separate aqueous pressure-insensitive and pressure-sensitive azeotropic mixtures. The two process variants were studied in process simulations, and the potential was evaluated by comparison with a conventional pressure-swing distillation process for the acetonitrile water system. The new process shows significant potential to reduce the separation costs by 30.5% up to 68.9% for a broad variety of mixtures with water fractions in the range of 0.1 <= x(H2O) <= 0.9. Thus, these results clearly indicate that the novel fundamental separation approach is a promising alternative to conventional processes for the separation of azeotropic mixtures.

An improved method to measure the rate of vaporisation and thermal decomposition of high boiling organic and ionic liquids by thermogravimetrical analysis - Heym, Florian; Etzold, Bastian; Kern, Christoph; Jess, Andreas (Physical Chemistry Chemical Physics, 2010)
The vapour pressure and the thermal stability of liquids are important material properties. For high boiling organic and ionic liquids (ILs), the determination of these properties is laborious and it is not easy to discriminate between evaporation and thermal decomposition. In this work, a simple but accurate method is presented to determine the parameters of decomposition and evaporation by thermogravimetrical analysis (TGA). The mass transfer coefficient was calculated based on a new correlation for the Sherwood number for cylindrical crucibles in overflow of a carrier gas. This correlation is valid for any diameter-to-height ratio and for any filling degree of the crucible and was derived from numerical simulations and proven by experiments with hexadecane, dodecane, and anthracene. The TGA analysis of two ILs was conducted. [EMIM][EtSO4] decomposes at ambient pressure without a measurable contribution of evaporation. To the contrary, [BMIM][NTf2] is relatively volatile. The vapour pressure of [BMIM][NTf2] and the kinetics of decomposition of both ILs were determined. © 2010 the Owner Societies.
CRIS-Team Scopus Importer:2023-08-15

An investigation of the conformational behavior of a chlorinated hydrocarbon, 1,1,2-trichloroethane, adsorbed in zeolites by Raman spectroscopy - Wang, Haiyan; Schwieger, Wilhelm; Huang, Yining (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2015)
The conformational behavior of 1,1,2-trichloroethane (TCE) adsorbed in two representative zeolites (silicalite-1 and zeolite L) was investigated by Fourier transform (FT)-Raman spectroscopy in combination with thermogravimetric analysis (TGA) and powder X-ray diffraction (XRD). The results indicate that the conformational properties of the TCE molecules inside a zeolitic host are strongly influenced by both the framework topology and the existence of charge balancing cations. When TCE is adsorbed inside completely siliceous silicalite-1, the population of the trans conformer increases significantly relative to pure liquid. Adsorption of TCE also induces a phase transition from the monoclinic to orthorhombic crystal system in the framework of silicalite-1 at high loading levels. At low loading, the TCE molecules are adsorbed inside the channels of silicalite-1. When at high loading levels, TCE molecules reside at both the channel intersection as well as the midsection of the channels. For zeolite L, the presence of an extra-framework cation shows a strong influence on TCE conformation. The strong interaction of the cation with the large dipole moment of the gauche isomer leads to a large increase in the gauche population. Raman data provide direct evidence that the cations in the framework interact much more strongly with the gauche isomer than the trans isomer.
Keywords: 1; 1; 2-trichloroethane; conformation; Raman spectroscopy; zeolites; adsorption

An operando DRIFTS-MS study of NH3 removal by supported ionic liquid phase (SILP) materials - Kaftan, Andre; Klefer, Heiko; Haumann, Marco; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg (Separation and Purification Technology, 2017)
A novel gas purification material using a supported ionic liquid phase (SILP) has been investigated for removal of NH3 from ambient gas streams (1500 ppm NH3 in Ar). The SILP material is made of a thin film of an imidazolium based ionic liquid and a dissolved copper metal complex ([C(2)C(1)Im]Cl/CuC1(2)), which were dispersed in the pores of a silica 100 support. Diffuse reflection infrared Fourier transform spectroscopy (DRIFTS) was used to investigate the irreversible absorption from a 1500 ppm NH3 gas stream and to identify species formed upon physisorption and chemisorption of ammonia. Additionally, temperature-programmed DRIFTS combined with in situ mass spectrometry were used to evaluate the reversibility and regenerability of the system. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Infrared spectroscopy; Online mass spectrometry; Ammonia absorption; Ionic liquid

A Novel Reactive Distillation Process for the Indirect Hydration of Cyclohexene to Cyclohexanol Using a Reactive Entrainer - Steyer, Frank; Freund, Hannsjörg; Sundmacher, Kai (Industrial & Engineering Chemistry Research, 2008)
In the conventional process for cyclohexanol production, large amounts of energy are consumed and a considerable quantity of side products is formed. In addition, the process is inherently unsafe. The alternative process of cyclohexene direct hydration requires large amounts of catalyst to overcome kinetic limitations. This publication shows the feasibility of a new route from cyclohexene to cyclohexanol by means of reactive distillation using formic acid as a reactive entrainer. This allows overcoming kinetic limitations with moderate amounts of catalyst and makes large-scale cyclohexanol production by reactive distillation an interesting alternative. The suggested coupled reactive distillation process allows producing cyclohexanol in an inherently safe and energetically advantageous way without incurring significant amounts of side products.

An Overview of Mutual Solubility of Ionic Liquids and Water Predicted by COSMO-RS - Zhou, Teng; Chen, Long; Ye, Yinmei; Chen, Lifang; Qi, Zhiwen; Freund, Hannsjörg; Sundmacher, Kai (Industrial & Engineering Chemistry Research, 2012)
To properly screen and use ionic liquids (ILs) as environmental-friendly solvents in chemical reactors and separation processes, the knowledge of their solubilities with water is essential. In the present work, mutual solubilities of 1500 ILs (50 cations, 30 anions) with water at 298.15 K were predicted by using the conductor-like screening model for real solvents (COSMO-RS) as a thermodynamic model. On the basis of the COSMO-RS calculations, the influence of the types of anion and cation, side chain modifications and substituent groups on the mutual solubility with water was extensively analyzed. The data obtained can be used for the prescreening of Its as solvent candidates. Moreover, to understand the intrinsic solubility behavior in detail, different types of molecular interactions between ILs and water in solution were compared on the basis of the determination of multiple water-IL interaction energies from COSMO-RS computation. The results confirm that hydrogen bonding interactions between anions and water molecules have the dominant influence on the solubility. Finally, for the purpose of fast solubility estimation and solvent selection, COSMO-RS derived molecular descriptors which indicate the strength of anionic HB acceptors were calculated for typical anions and anion families.

Antioxidant mesoporous Ce-doped bioactive glass nanoparticles with anti-inflammatory and pro-osteogenic activities - Zheng, Kai; Torre, Elisa; Bari, Alessandra; Taccardi, Nicola; Cassinelli, Clara; Morra, Marco; Fiorilli, Sonia; Vitale-Brovarone, Chiara; Iviglia, Giorgio; Boccaccini, Aldo R. (Materials Today Bio, 2020)
Mesoporous bioactive glass nanoparticles (MBGNs) are emerging biomaterials for bone repair/regeneration, considering their favorable pro-osteogenic and proangiogenic activities. To further improve their therapeutic effects, the endowment of MBGNs with additional antioxidant properties is of particular interest to target oxidative stress related to bone remodeling and diseases. To this end, we developed antioxidant cerium-containing MBGNs (Ce-MBGNs) (particle size of 100–300 ​nm) by using a postimpregnation strategy to incorporate Ce, through which the shape, pore structure, and dispersity of the nanoparticles were preserved. The incorporated amount of Ce could be tailored by adjusting the concentration of the Ce precursor solution. When impregnated at a relatively low temperature (20 ​°C), Ce-MBGNs containing either 1.8 or 2.8 ​mol% of Ce were produced, while the formation of by-product cerium oxide nanoparticles (nanoceria) could be avoided. In both developed Ce-MBGNs, the concentration of Ce4+ was higher than that of Ce3+, while the relative molar percentage of Ce4+ was similar (∼74%) in both Ce-MBGNs. The obtained Ce-MBGNs were evidenced to be non-cytotoxic against fibroblasts at the concentration of 1 ​mg/mL. Moreover, the incorporation of Ce into MBGNs significantly reduced the expression of oxidative stress–related genes in macrophages (J774a.1). Particularly in the presence of pro-oxidation agents, Ce-MBGNs could downregulate the expression of oxidative stress–related genes in comparsion with the polystyrene plates (control). When cultured with Ce-MBGNs, the expression of proinflammatory-related genes in macrophages could also be downregulated in comparsion with MBGNs and the control. Ce-MBGNs also exhibited pro-osteogenic activities through suppressing pro-osteoclastogenic responses. The obtained results highlight the great potential of the developed Ce-MBGNs in a variety of biomedical applications, particularly in treating bone defects under inflammatory conditions, considering their antioxidant, anti-inflammatory, and pro-osteogenesis activities.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Anti-inflammatory; Antioxidant; Bioactive particles; Cerium; Pro-osteogenesis; Surface modification

A path to a dynamic hydrogen storage system using a liquid organic hydrogen carrier (LOHC): Burner-based direct heating of the dehydrogenation unit - Bollmann, Jonas; Schmidt, Nikolas; Beck, Dominik; Preuster, Patrick; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (International Journal of Hydrogen Energy, 2022)
Keywords: Dynamic heat supply; Hydrogen storage; Dehydrogenation; LOHC; Porous media burner

Application of In2O3-catalysts for Slurry Phase Hydrogenation of CO2 to Methanol: Influence of reaction conditions, support and catalyst preparation - Schühle, Patrick; Reichenberger, S.; Marzun, G.; Albert, Jakob (DGMK Tagungsbericht, 2019)
To reduce greenhouse gas emissions the development of novel storage and transport technologies for renewable produced electrical power is necessary. In comparison to conventional energy, renewables are highly dependent on the availability of primary energy sources like wind and sunlight. One concept to overcome this challenge is to convert electrical to chemical energy, e.g. by electrolysis of water to hydrogen and oxygen in an electrolysis cell. Yet storage and transport of hydrogen is a challenging task requiring the subsequent conversion to base chemicals like methanol. Due to the deactivation of the industrial Cu/ZnO/Al2O3-catalysts by stoichiometrically produced water [1], novel water resistant catalysts for the CO2 hydrogenation to methanol are required. Recently, it has been shown that heterogeneous In2O3-catalysts supported on semiconductor metal oxides presents a promising alternative [2], but require further catalyst development. In this work we follow two different synthesis approaches, namely wet-chemical impregnation and laser-based catalyst preparation. The latter represents a novel technique to individually study the catalytic activity in terms of nanoparticle purity, functional properties (size, morphology, oxidation state) and support properties (e.g. defect densities) [3]. Nanoparticles are synthesized by scalable pulsed laser ablation in a liquid under surfactant-free conditions and subsequent adsorption in chosen weight loading, onto various oxidic support materials. Due to subsequent processing, nanoparticle properties (e.g. nanoparticle size) are adjusted independently of the nanoparticle load or the used support [3]. Furthermore, the gained nanocatalyst is active without high temperature calcination further maintaining preadjusted support properties (e.g. defect structure of dopant distribution). To quantify the activity of the catalysts for methanol synthesis a slurry reactor with suspended catalyst in a high boiling liquid phase was used. Advantages of this concept are the applicability of catalysts in the size of nanometers without inducing high pressure drops. To examine the influence of the catalyst morphology on the catalytic performance, several analytical techniques were used. The Indium-loading of the catalyst was checked by ICP-OES. BET-sorption measurements and CO2-TPD were applied for the characterization of the catalyst supports concerning their total surface area and CO2 binding capacity. Via XPS measurement the oxidation state of the Indium-and Zirconia-species were analysed before and after the reaction. Furthermore, the catalyst surface was examined by electron microscopy and XRD.
CRIS-Team Scopus Importer:2021-04-20

Application of supported ionic liquid phase catalyst systems in the hydroformylation of olefin-containing mixtures to aldehyde mixtures with high portion of nonbranched aldehydes. - Franke, Robert; Brausch, Nicole; Fridag, Dirk; Christiansen, Andrea; Becker, Marc; Wasserscheid, Peter; Haumann, Marco; Jakuttis, Michael; Werner, Sebastian; Schönweiz, Andreas (2012)
The subject of the present invention is a catalyst with increased durability based on compn. of (a) an inert, porous substrate, (b) an ionic liq., (c) Rh, (d) a phosphorus-contg. org. ligand, (e) at least an org. amine. A further the subject of the present invention is a procedure for the hydroformylation of olefin-contg. hydrocarbon mixts. to aldehyde mixts. whereby: (a) the water content of the olefin-contg. hydrocarbon mixt. is adjusted to ≤20 ppm, (b) the content of multifunctional unsatd. compds. in the olefin-contg. hydrocarbon mixt. is adjusted continually to ≤3000 ppm, (c) the mol. ratio of org. amines to phosphorus-contg. ligands is ≥4:1; and (d) the mol. ratio of phosphorus-contg. org. ligand to Rh is ≥10:1. A typical catalyst consists of silica support, rhodium acetylacetonate dicarbonyl, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, 6,6'-[[3,3'-di-tert-butyl-5,5'-dimethoxy[1,1'-biphenyl]-2,2'-diyl]bis(oxy)]bis[dibenzo[d,f][1,3,2]dioxaphosphepin] and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and a typical reaction feed contains 1-butene, isobutene, cis-2-butene, trans-2-butene, n-butane, and isobutane, with the product being n-pentanal. [on SciFinder(R)]
Keywords: ionic liq rhodium phosphorus ligand amine catalyst supported hydroformylation; tertiary butyldimethoxy biphenyldiylbisoxybis dibenzodioxaphosphepin catalyst hydroformylation butene pentanal manuf; hydroformylation olefin catalyst unbranched aldehyde manuf; butene hydroformylation pentanal manuf catalyst; silica support hydroformylation catalyst butene pentanal manuf; rhodium acetylacetonatedicarbonyl catalyst hydroformylation butene pentanal manuf; ethylmethylimidazolium fluoromethanesulfonylimide catalyst hydroformylation butene pentanal manuf

Aqueous-phase reforming of xylitol over Pt/C and Pt/TiC-CDC catalysts: catalyst characterization and catalytic performance - Kirilin, Alexey V.; Hasse, Benjamin; Tokarev, Anton V.; Kustov, Leonid M.; Baeva, Galina N.; Bragina, Galina O.; Stakheev, Aleksandr Yu.; Rautio, Anne-Riikka; Salmi, Tapio; Etzold, Bastian; Mikkola, Jyri-Pekka; Murzin, Dmitry Yu. (Catalysis: Science and Technology, 2014)
The aqueous phase reforming (APR) of xylitol was studied over five Pt/C catalysts. The correlation between physico-chemical properties of the catalysts and catalytic performance was established. The Pt/C catalysts have different textural properties as well as different mean Pt cluster sizes and surface acidity. The average Pt cluster size was investigated by means of CO chemisorption as well as by TEM. The reaction was found to be structure sensitive and TOF linearly increases with increasing average Pt cluster size in the studied domain. The catalysts which possess higher surface acidity favoured higher rates of hydrocarbon production. On the contrary the Pt/C materials with lower acidities generated hydrogen with high selectivity and TOF.
EAM Import::2019-03-13

Arrangement and method for operating hydrogen filling stations. - Arlt, Wolfgang; Wasserscheid, Peter (2013)
The present application relates to an arrangement for the advantageous construction of a hydrogen filling station. A particular chem. compd. class, called liq. org. hydrogen carrier (LOHC), is dehydrogenated to a and the hydrogen formed is pressurized by compression in the tank of a vehicle during refueling. LOHC compds. store, per L, almost double the amt. of hydrogen compared to a 700 bar tank, but are themselves stored at ambient temp. and pressure. In embodiments, N-ethylcarbazole, N-(1-Propyl)carbazole or N-isopropylcarbazole, preferably N-ethylcarbazole, is used as LOHC in its energy-poor form. The energy-rich LOHC may be at least partially produced at the site of the service station by by renewably produced electricity, water electrolysis and hydrogenation. [on SciFinder(R)]
Keywords: hydrogen filling station liq org hydrogen carrier vehicle refueling

Arrangement and method for storing energy in buildings and supplying energy to buildings. - Arlt, Wolfgang; Wasserscheid, Peter (2013)
This patent relates to an arrangement for supplying energy to buildings, comprising at least one external connection for providing an elec. current, at least one electrolyzer for producing H from H2O using the elec. current from the connection, at least one 1st chem. reactor for at least partially hydrating at least one substrate with an extended π-conjugated system using the H formed in the electrolyzer, at least one storage tank for storing the substrate which is at least partially hydrated in the 1st chem. reactor, at least one 2nd chem. reactor for at least partially dehydrating the at least partially hydrated substrate produced in the 1st chem. reactor and stored in the storage tank releasing H, and at least one fuel cell for oxidn. of the H released in the 2nd chem. reactor so as to release energy. The present invention likewise relates to a method for supplying energy using this arrangement, wherein the energy is used for heating or cooling the building. In the case where the building does not have a requirement for either heat or cold, a thermal store can be added. The financial gain is achieved as a result of the thermal store and the storage of elec. current. [on SciFinder(R)]
Keywords: arrangement energy storage supply building hydrogen power

Arrangement and method for supplying energy to buildings. - Arlt, Wolfgang; Wasserscheid, Peter (2013)
The application relates to an arrangement for supplying energy to detached buildings, comprising: ≥1 energy-generating installation, in particular a photovoltaic installation, for providing an elec. current, ≥1 electrolyzer for producing hydrogen from water using the elec. current from the energy-generating installation, ≥1 first chem. reactor for at least partially hydrating ≥1 substrate with an extended n-conjugated system using the hydrogen formed in the electrolyzer, ≥1 storage tank for storing the substrate hydrated at least partially in the first chem. reactor, ≥1 second chem. reactor for at least partially dehydrating the at least partially hydrated substrate which was produced in the first chem. reactor and stored in the storage tank with the release of hydrogen, and ≥1 fuel cell for the oxidn. of the hydrogen released in the second chem. reactor with the release of energy. The invention likewise relates to a method for supplying energy using this arrangement. [on SciFinder(R)]
Keywords: energy supply arrangement building

Arrangement and process for autonomous supply of electricity over hydrogen. - Arlt, Wolfgang; Wasserscheid, Peter (2013)
The application concerns an arrangement for autonomous supply of electricity over hydrogen including: making an elec. current available from a regenerative source; making hydrogen of water using an electrolyzer and elec. current from that as a renewable energy source; the formed hydrogen is supplied from the chem. reactor by partial hydrogenation of the substrate; supplying the partly hydrogenated substrate from the chem. reactor into a storage; dehydrogenation into a second chem. reactor to release of hydrogen, and transformation of the hydrogen into elec. energy. [on SciFinder(R)]
Keywords: app autonomous electricity hydrogen hydrogenation dehydrogenation

A Scalable Preparation Method for SILP and SCILL Ionic Liquid Thin-Film Materials - Werner, Sebastian; Szesni, Normen; Kaiser, Melanie; Haumann, Marco; Wasserscheid, Peter (Chemical Engineering & Technology, 2012)
Supported ionic liquid phase (SILP) catalysts consist of a homogeneous catalyst that is dissolved in an ionic liquid and dispersed on a porous support material. This immobilization technique yields solid catalysts that can be applied in continuous gas phase processes. Recently, several successful applications have been presented that could possibly lead to a commercialization of this promising class of novel materials. The state-of-the-art preparation method uses an incipient wetness-type impregnation of the support material by a solution of catalyst, ionic liquid, and a helper solvent, followed by subsequent removal of the helper solvent in vacuo. Typically, this removal is carried out in a rotary evaporator, thus being limited in batch size. Similarly, the so-called supported catalysts with ionic liquid layer (SCILL) consist of an ionic liquid layer on top of a traditional heterogeneous catalyst, which can be prepared in a similar way. In this work, a novel preparation method for SILP catalysts is presented that is scalable for larger batches, as required for industrial use. Different types of support materials such as powders, spheres, agglomerates, and extrudates were successfully impregnated by the novel fluidized-bed impregnation method and the distribution of the ionic liquid and catalyst was analyzed by scanning electron microscopy with energy-dispersive X-ray spectroscopy measurements.
Keywords: Energy-dispersive X-ray spectroscopy; Film formation; Fluidized bed; Supported ionic liquid phase; Surface coating

A solid oxide fuel cell operating on liquid organic hydrogen carrier-based hydrogen – A kinetic model of the hydrogen release unit and system performance - Peters, Roland; Deja, Robert; Fang, Qingping; Nguyen, Van Nhu; Preuster, Patrick; Blum, Ludger; Wasserscheid, Peter; Stolten, Detlef (International Journal of Hydrogen Energy, 2019)
In this paper, a kinetic model for the catalytic dehydrogenation of perhydro dibenzyltoluene (H18-DBT), a well-established Liquid Organic Hydrogen Carrier (LOHC) compound, is presented. Kinetic parameters for hydrogen release at a Pt on alumina catalyst in a temperature range between 260 °C and 310 °C are presented. A Solid Oxide Fuel Cell (SOFC) system model was coupled to the hydrogen release from H18-DBT in order to validate the full sequence of LOHC-bound hydrogen-to-electric power. A system layout is described and investigated according to its transient operating behavior and its efficiency. We demonstrate that the maximum efficiency of LOHC-bound hydrogen-to-electricity is 45% at full load, avoiding any critical conditions for the system components.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Future energy systems; Heat integration; Hydrogen storage; LOHC; Off-grid energy supply; SOFC

Assemblies of Mesoporous FAU-Type Zeolite Nanosheets - Inayat, Alexandra; Knoke, Isabel; Spiecker, Erdmann; Schwieger, Wilhelm (Angewandte Chemie International Edition, 2012)
Holey sheets: Nanosheet assemblies of FAU-type zeoliteX with intracrystalline mesopores are prepared (see picture). This material is synthesized by soft-templating and combines micro, meso, and macropores in a hierarchically interconnected manner.
Keywords: hierarchy; mesoporous materials; nanosheets; soft templating; zeolites

Assessment of Periodic Open Cellular Structures for Enhanced Heat Conduction in Catalytic Fixed-Bed Reactors - Schwieger, Wilhelm; Freund, Hannsjörg; Bianchi, Enrico (Advanced Engineering Materials, 2015)
In this paper, the effective heat conductivity of periodic open cellular structures (POCS) is investigated by means of a systematic numerical study. 3D geometries of different configurations were considered, representing the unit cell volume of the modular POCS. Special emphasis is put on the strut morphology, i.e. the strut cross sectional shape and the distribution of the solid material along the strut. At the same porosity, the optimal designed structures show a higher effective heat conductivity than conventional open-cell solid foams with random cell geometry. This possibility to exceed the effective thermal conductivity of state-of-the-art open-cell foams by optimization of their geometrical properties is an interesting novel aspect of high relevance regarding their application in catalytic reactors.

A study of silicalite-1 and Al-ZSM-5 membrane synthesis on stainless steel supports - Mabande, Godwin; Pradhan, G; Schwieger, Wilhelm; Hanebuth, M; Dittmeyer, Roland; Selvam, Thangaraj; Zampieri, Alessandro; Baser, Hasan-Hüseyin; Herrmann, Ralph (Microporous and Mesoporous Materials, 2004)
Silicalite-1 and Al-ZSM-5 membranes were prepared by combining one-step in situ seeding with one secondary membrane growth step. For membranes prepared under similar conditions, Al-ZSM-5 membrane growth was found to be considerably slower than Silicalite-1 growth leading to a significantly higher preferred axial orientation of the Silicalite-1 membranes. H(2)/SF(6) single gas permeation measurements revealed that for both membrane types a correlation existed between the H(2)/SF(6) ideal perm-selectivities and the zeolite layer thickness. Above a certain thickness the defect density is independent of layer thickness. However, Al-ZSM-5 membrane perm-selectivities were higher, despite lower membrane thicknesses and comparable hydrogen permeation rates. For example, room temperature ideal H(2)/SF(6) perm-selectivities of about 136 and 65 were measured for a 7.5 mum thick Al-ZSM-5 and a 45 mum thick Silicalite-1 membrane, respectively. Comparison to literature data revealed that the membranes were of good quality. Moreover, reproducibility of the membrane synthesis procedure proved to be good. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: MFI membrane; single gas permeation; seeding; stainless steel support

A survey of pendant donor-functionalised (N, O) phosphine ligands for Cr-catalysed ethylene tri- and tetramerisation - Suttil, James A.; Wasserscheid, Peter; McGuiness, David S.; Gardiner, Michael G.; Evans, Stephen J. (Catalysis: Science and Technology, 2014)
chromium and both triethylaluminium (AlEt3) and methylaluminoxane (MAO) co-catalysts. Hydrazine based ligands containing an N-H functionality [PN(NH)P], analogous to Rosenthal's previously reported PNPNH system, show selectivity towards 1-hexene and 1-octene formation in conjunction with AlEt3, and act as PNP tetramerisation analogues when MAO is employed. PNP ligands containing non-protic pendant donor moieties generally show poor activity and selectivity when AlEt3 is employed as an activator, however when MAO is used good activities and selectivities are achieved. n-Propylcyclopentane and 2-propenylcyclopentane, and higher homologues, are produced during catalysis when oxygen is the donor atom. The formation of such products is discussed with respect to the generation of methylenecyclopentane and methylcyclopentane by PNP based tetramerisation catalysts. Simple phosphine ligands containing O-H functionalisation are also explored and it was shown that the catalyst selectivity is highly dependent on both the activator and structural features of the ligand employed.

Asymmetric hydrogenation catalysis via ion-pairing in chiral ionic liquids. - Wagner, Valentin; Schulz, Peter; Wasserscheid, Peter (Journal of Molecular Liquids, 2014)
The relevant interactions between the org. ions of ionic liqs. (ILs) include van der Waals forces, hydrogen bonding and Coulombic interactions. In solns. these interactions lead to the formation of aggregates. Depending on the strength of the interactions and the concn. of the IL in the solvent, different aggregates are formed with ion-pairs being the dominant species at low concns. A probe for investigating these interactions is the enantioselectivity of a reaction carried out on a prochiral ion in presence of its chiral counter-ion. As asym. induction requires structurally well-defined interactions, the induced enantioselectivity can be correlated to ion aggregate formation. Depending on the substrate IL concn. an enantioselectivity of up to 94% was realized. The catalytic results were linked to the probability of the ion pair formation as evidenced by DOSY-NMR measurements and dielec. relaxation spectroscopy. The expansion of this principle to chiral ionic liqs. that can be easily decompd. to chiral building blocks of synthetic relevance led to the development of two approaches: (a) the application of an IL substrate consisting of a chiral cation and a keto-functionalized, prochiral carboxylate counter-ion allowing for the synthesis of chiral esters in the sequence of IL hydrogenation and esterification, and (b) reversible binding of a prochiral substrate to the cation of an IL with a chiral, enantiopure anion allowing the synthesis of neutral chiral building blocks in a sequence of binding, hydrogenation and splitting. The latter approach was tested for two ILs based on the hydroxyl-functionalized cation cholinium to which a prochiral keto functionalized carboxylic acids was reversibly attached via esterification. The hydrogenation of such prochiral ester cation in the presence of enantiopure anions resulted in ee of up to 63%. [on SciFinder(R)]
Keywords: chiral ionic liq prepn asym hydrogenation catalysis ion pairing

Asymmetric hydrogenation of methyl pyruvate in the continuous gas phase using Supported Ionic Liquid Phase (SILP) catalysis - Schneider, Martin; Haumann, Marco; Wasserscheid, Peter (Journal of Molecular Catalysis A-Chemical, 2013)
Based on the recently reported asymmetric hydrogenation of methyl acetoacetate in a continuous-flow, gas phase reaction using Supported Ionic Liquid Phase (SILP) catalysis, this study deals with the even more challenging asymmetric reduction of the alpha-keto ester methyl pyruvate. Different support materials, ligands and ionic liquids were screened to identify an optimized Ru-based SILP catalyst. With Ru-BINAP dissolved in the ionic liquids 3-hydroxypropylpyridinium bis(trifluoromethylsulfonyl)imide on silica 100, stable catalyst performance could be obtained for more than 50 h time-on-stream. At 95 degrees C and with a residence time in the reactor of less than 3 s a stable product yield of 80-84% was obtained with moderate but stable enantiomeric excess of 26-30%. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Asymmetric hydrogenation; Gas phase; Methyl pyruvate; Supported catalyst; SILP catalyst; Ionic liquid

Attenuated Total Reflection Infrared Difference Spectroscopy (ATR-IRDS) for Quantitative Reaction Monitoring - Kiefer, Johannes; Cöngevel, Melek A.; Roth, Daniel; Obert, Katharina; Wasserscheid, Peter; Leipertz, Alfred (Applied Spectroscopy, 2012)
Monitoring of chemical reactors is key to optimizing yield and efficiency of chemical transformation processes. Aside from tracking pressure and temperature, the measurement of the chemical composition is essential in this context. We present an infrared difference spectroscopy approach for determining the reactant (cyclooctene) and product (cyclooctane) concentrations during a catalytic hydrogenation reaction in the solvent cyclohexane, which is present in large excess. Subtracting the spectrum of the pure solvent from the reactor mixture spectra yields infrared (IR) spectra, which can ultimately be evaluated using a curve-fitting procedure based on spectral soft modeling. An important feature of our evaluation approach is that the calibration only requires recording the pure component spectra of the reactants, products, and solvent. Hence, no time-consuming preparation of mixtures for calibration is necessary. The IR concentration results are in good agreement with gas chromatography measurements.
Keywords: Attenuated total reflection spectroscopy; ATR; Fourier transform infrared spectroscopy; FT-IR; Hydrogenation; Difference spectroscopy; Quantitative measurement; Catalysis

Author Correction: Isolated Rh atoms in dehydrogenation catalysis (Scientific Reports, (2023), 13, 1, (4458), 10.1038/s41598-023-31157-y) - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Correction to: Scientific Reports, published online 17 March 2023 The original version of this Article contained an error in the spelling of the author Nicola Taccardi, which was incorrectly given as Nicola Tacardi. The original Article has been corrected.
CRIS-Team Scopus Importer:2023-06-30

Axially chiral phosphites as ligands in enantioselective rhodium-catalyzed hydrogenation. - Agel, Friederike (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)
Keywords: axially chiral phosphite ligand enantioselective rhodium catalyzed hydrogenation

Basische Festkörperkatalysatoren für die Nutzung nachwachsender Rohstoffe: Die Bedeutung von Textur- und Oberﬂächeneigenschaften in der p-Cymen-Synthese - Inayat, Alexandra (Cuvillier Verlag, 2014)
Basische Festkörperkatalysatoren können eine Vielzahl von Reaktionen katalysieren, die für die Umwandlung nachwachsender Rohstoffe in bisher aus Erdöl gewonnene Chemikalien relevant sind. In der vorliegenden Arbeit wurde die Dehydroisomerisierung von Limonen zu p-Cymen als Modellreaktion für die Umsetzung der in Pflanzen enthaltenen Monoterpene in aromatische Wertprodukte betrachtet. Anhand dieser Reaktion wurde der Einfluss der Oberflächen- und Textureigenschaften basischer Katalysatoren auf ihre katalytische Performance untersucht. Der Schwerpunkt der Arbeit lag auf der Herstellung der entsprechenden basischen Festkörperkatalysatoren. Als Materialklassen wurden schichtförmige Zn/Al-Mischoxide und Kalium-ausgetauschter Zeolith X ausgewählt. Bei Zeolith X wurde die Textur durch Erzeugung von zusätzlicher intrakristalliner Mesoporosität mit Hilfe des Organosilan-Templates TPHAC verändert. Die Änderung der Oberflächenzusammensetzung bei den Mischoxiden erfolgte durch Variation des Bruchkantengehaltes, des Zn/Al-Molverhältnisses sowie durch partielle Entmischung der Mischoxidstruktu

Beneficial effects of liquid crystalline phases in solid-state dye-sensitized solar cells - Costa, Ruben Dario; Werner, Fabian; Wang, Xinjiao; Grönninger, Philipp; Feihl, Sebastian; Kohler, Florian; Wasserscheid, Peter; Hibler, Susanne; Beranek, Radim; Meyer, Karsten; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
Two novel double-alkyl functionalized imidazolium ionic liquid crystals have successfully been utilized to demonstrate the benefits of the liquid crystalline phase on the ssDSSC performance. In particular, a good balance between dye regeneration and hole transport is only realized in the liquid crystalline phase. Devices that employ a single component ionic liquid based electrolyte show a remarkably stable efficiency during 1000 h under outdoor operation temperature conditions and 1 sun illumination. Two novel double-alkyl functionalized imidazolium ionic liquid crystals have successfully been utilized to demonstrate the benefits of the liquid crystalline phase on the ssDSSC performance. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Benzyltoluene/dibenzyltoluene-based mixtures as suitable liquid organic hydrogen carrier systems for low temperature applications - Jorschick, Holger; Geißelbrecht, Michael; Eßl, Melanie; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2020)
In this contribution we propose mixtures of the two LOHC systems benzyltoluene (H0-BT)/perhydro benzyltoluene (H12-BT) and dibenzyltoluene (H0-DBT)/perhydro dibenzyltoluene (H18-DBT) as promising hydrogen storage media for technical applications at temperatures below ambient. The mixing of the two LOHC systems provides the advantage of a reduced viscosity of the hydrogen-rich system, for example a 20 wt% addition of H12-BT to H18-DBT reduces the viscosity at 10 °C by 80%. Interestingly, it is also found that the dehydrogenation of such mixture provides a hydrogen release productivity that is 12–16% higher compared to pure H18-DBT dehydrogenation under otherwise identical conditions. This enhanced rate is attributed to a combination of reduced hydrogen partial pressure in the reactor (due to the higher H12-BT vapor pressure), preferred H12-BT dehydrogenation (due to faster H12-BT diffusion) and effective transfer hydrogenation between the two LOHC systems.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Benzyltoluene; Dehydrogenation; Dibenzyltoluene; Hydrogen storage; Hydrogenation; LOHC systems

Benzyltoluene/perhydro benzyltoluene - pushing the performance limits of pure hydrocarbon liquid organic hydrogen carrier (LOHC) systems - Ruede, Timo; Dürr, Stefan; Preuster, Patrick; Wolf, Moritz; Wasserscheid, Peter (Sustainable Energy & Fuels, 2022)
LOHC technologies enable safe and efficient hydrogen logistics using the existent fuel infrastructure. This study presents benzyltoluene (H0-BT)/perhydro benzyltoluene (H12-BT) as a highly attractive technical LOHC system. Compared with the well-established LOHC systems toluene/methylcyclohexane and dibenzyltoluene (H0-DBT)/perhydro dibenzyltoluene (H18-DBT), the H0-BT/H12-B system combines high volumetric storage density and excellent robustness in hydrogenation/dehydrogenation cycles with low viscosity for easy handling under colder operation conditions. Herein, we report repeated hydrogenation and dehydrogenation cycles in semi-continuous operation at 290 degrees C with a commercial Pt on alumina catalyst and technical quality LOHC material. Reaction rates for both hydrogen uptake and release are generally found higher compared to those of the DBT-based LOHC system under identical reaction conditions. Side-product formation is very low during cycling the H0-BT/H12-BT system and can be traced back to a very low activity towards deep dehydrogenation forming the cyclisation product methylfluorene in four different regioisomers. Furthermore, we present the experimentally determined hydrogenation/dehydrogenation equilibrium of H0-BT/H12-BT in the temperature range between 220 and 360 degrees C and for total pressures of 1 and 9 bar(abs).
CRIS-Team WoS Importer:2022-03-11

Binary Diffusion Coefficients for Mixtures of Ionic Liquids [EMIM][N(CN)(2)), [EMIM][NTf2], and [HMIM][NTf2] with Acetone and Ethanol by Dynamic Light Scattering (DLS) - Rausch, Michael Heinrich; Hopf, Lisa; Heller, Andreas; Leipertz, Alfred; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2013)
Mutual diffusivities for binary mixtures of the ionic liquids (ILs) [EMIM] [N(CN)(2)] (1-ethyl-3-methylimidazolium dicyanimide), [EMIM] [NTf2] (1-ethyl-3-methylimidazolium bis-(trifluoromethylsulfonyl)imide), and [HMIM] [NTf2] (1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) with acetone and ethanol were studied in dependence on composition in the temperature range from 283.15 to 323.15 K, applying dynamic light scattering (DLS). The influence of experimental parameters on the achievable uncertainties was analyzed to ensure the acquisition of accurate data in adequate measurement times. For all probed systems, increasing binary diffusion coefficients were found for increasing temperatures. The systematic variation of anion and cation of the investigated ILs as well as a comparison with the literature data demonstrates the considerable influence of different ions on the resulting binary diffusion coefficients. Mutual diffusivities were found to be lower for the mixtures with ethanol than for those with acetone, which could be related to the formation of hydrogen bonds between ethanol and the ions. Most of the investigated IL solvent mixtures show increasing binary diffusion coefficients with increasing solvent concentration. For the mixtures of [EMIM][NTf2] with ethanol, however, a minimum of the mutual diffusivities was found in the ethanol mole fraction range from 0.7 to 0.8, which may hint at the vicinity of a critical demixing point. The viscosity of the pure ILs turned out to be no reliable indicator for the mutual diffusivity in mixtures with the same solvent.

Binary Diffusion Coefficients of the Liquid Organic Hydrogen Carrier System Dibenzyltoluene/Perhydrodibenzyltoluene - Heller, Andreas; Rausch, Michael Heinrich; Schulz, Peter; Wasserscheid, Peter; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2016)
Liquid organic hydrogen carrier (LOHC) systems constitute a very promising concept for future hydrogen storage and logistics. The concept builds on the conversion of excess renewable energy to hydrogen via electrolysis followed by reversible catalytic hydrogenation/dehydrogenation of a diesel-like organic carrier molecule. For an ideal design of the catalytic process, insight into reaction mechanisms and kinetics but also precise knowledge on mass transport properties are necessary. In the present study, binary diffusion coefficients in selected binary LOHC mixtures with five different compositions of perhydrodibenzyltoluene (H-18-LOHC) and dibenzyltoluene (LOHC) were measured by dynamic light scattering (DLS). The compositions were defined by mixing appropriate amounts of LOHC and H-18-LOHC to realize different hydrogenation degrees of the LOHC. Binary diffusion coefficients were investigated over a temperature range from (264 to 571) K with an absolute uncertainty of (3 to 25) %. Moreover, an empirical equation describing the binary diffusion coefficients of all five mixture compositions over the complete temperature range with a root-mean-square deviation of less than 3 % was established. It was observed that the binary diffusion coefficient is independent of the hydrogenation degree of LOHC at temperatures above 430 K. For lower temperatures, the binary diffusion coefficient increases with decreasing degree of hydrogenation.

Binary Mixtures of Proton-Conducting Ionic Liquids as Electrolytes for Medium-Temperature Polymer Electrolyte Membrane Fuel Cells - Suo, Yanpeng; Hou, Hui; Lin, Jingjing; Chen, Yingzhen; Liu, Chang; Wang, Ce; Schulz, Peter; Wippermann, Klaus; Korte, Carsten (Journal of Physical Chemistry C, 2021)
In this study, physicochemical and electrochemical characterization of mixtures of proton-conducting ionic liquids (PILs) is reported for potential future use as a novel electrolyte in polymer electrolyte membrane fuel cells operable at 100-120 °C. By blending two PILs, 2-sulfoethyl-methyl-ammonium triflate [2-Sema][TfO] and diethyl-methyl-ammonium triflate [Dema][TfO], exhibiting different cation acidities and different oxygen diffusivities/solubilities, it was apparent that the superior physicochemical and electrochemical properties of both PILs can be favorably combined. Improved thermal stability of the blend, compared to neat [2-Sema][TfO], was observed. The viscosity of the mixtures decreased when increasing the fraction of [Dema][TfO], which led to increased proton conductivity and oxygen transmission coefficients, that is, D × c. In combination with the highly acidic [2-Sema]+ cations, which served as strong proton donors for the oxygen reduction reaction (ORR), it led to an increase in the ORR limiting current density at cell potentials relevant for fuel cell operation.
CRIS-Team Scopus Importer:2021-10-29

Binder-free formed ZSM-5 based on porous glasses through in-situ crystallization: Preparation, properties, and catalytic testing - Schwieger, Wilhelm; Rauscher, Marcus; Schwab, Andreas (Chemie Ingenieur Technik, 2010)

Binder-free ZSM-5-Shaped Body on the Basis of porous Glass by in situ Cristallization: Preparation, Properties and catalytic Testing - Rauscher, Marcus; Schwab, Andreas; Schwieger, Wilhelm (Chemie Ingenieur Technik, 2010)

Bio-based materials: general discussion - Albert, Jakob; Huber, George; Argyropoulos, Dimitris; Matharu, Avtar; Bitter, Harry; Stevens, Christian; Herou, Servann; Wilson, Karen; Clark, James; Pant, Deepak; Cabrera-Rodríguez, Carlos I.; Samec, Joseph (Faraday Discussions, 2017)

Biodegradable nanostructures: Degradation process and biocompatibility of iron oxide nanostructured arrays - Yang, Yuyun; Zhou, Juncen; Detsch, Rainer; Taccardi, Nicola; Heise, Svenja; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Materials Science and Engineering C, 2018)

Biogenic formic acid as a green hydrogen carrier - Preuster, Patrick; Albert, Jakob (Energy Technology, 2018)
Formic acid (FA) is an important platform chemical that has numerous applications in the chemical, agricultural and leather industry. So far, FA is exclusively produced from fossil raw materials using either carbonylation of methanol or acidolysis of formates. In this contribution, sustainable and environmentallyfriendly approaches to produce biogenic FA from biomass (e.g. OxFA-process) are presented and combined with different approaches for the catalytic decomposition of bio-based FA solutions. Several homogeneous and heterogeneous approaches for the catalytic decomposition of aqueous FA to hydrogen and CO2 are compared for their applicability. Moreover, their technical application in fuel cells or as energy storage vector respectively hydrogen storage molecule are discussed.

Biomass oxidation to formic acid in aqueous media using polyoxometalate catalysts – boosting FA selectivity by in-situ extraction - Albert, Jakob; Wasserscheid, Peter; Reichert, Jenny; Jess, Andreas; Brunner, Birgit (Energy and Environmental Science, 2015)
Herein, we report a remarkable finding that biomass oxidation to formic acid (FA) in water–organic biphasic reaction systems is far more selective than the same reaction in a monophasic aqueous media. While literature claims that the yield of FA from carbohydrates and biomass is limited to less than 68%, even for simple substrates such as glucose or glycerol, we demonstrate in this study that FA yields of up to 85% can be obtained from glucose. Using our biphasic reaction protocol, even raw lignocellulosic biomass, such as beech wood, leads to FA yields of 61%. This is realized by applying polyoxometalate H8PV5Mo7O40 as a homogeneous catalyst, oxygen as the oxidant and water as the solvent in the presence of a long-chain primary alcohol as an in-situ extracting agent. The new, liquid–liquid biphasic operation opens a highly effective way to produce pure FA, a liquid syngas equivalent, from wood in a robust, integrated, and low-temperature process.

Bis-polyethylene glycol-functionalized imidazolium ionic liquids: A multi-method approach towards bulk and surface properties - Seidl, Vera; Bosch, Michael; Paap, Ulrike; Livraghi, Mattia; Zhai, Ziwen; Wick, Christian; Koller, Thomas Manfred; Wasserscheid, Peter; Maier, Florian; Smith, Ana-Suncana; Bachmann, Julien; Steinrück, Hans-Peter; et al. (Journal of Ionic Liquids, 2022)
Adding to the versatile class of ionic liquids, we report a new series of hydrophilic polyethylene glycol-functionalized room-temperature ionic liquids, offering interesting thermo- and electrochemical behavior as well as remarkable surface properties. A scalable and generally applicable synthetic procedure for the preparation of N,N’-bis(polyethylene glycol)imidazolium salts, generally abbreviated as [(mPEGn)2Im][A] (n = 2‒6, A = I‒, OMs‒, PF6‒, NTf2‒) was developed. These ionic liquids were studied concerning their thermo- and electrochemical properties, such as phase transition behavior, decomposition temperature, viscosity, and density, as well as electrical conductivity and electrochemical stability, using i.a. differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV). Additionally, the surface properties were investigated by angle-resolved X-ray photoelectron spectroscopy (ARXPS) and the pendant drop method. olecular dynamics simulations complement the studies and provide insight into the molecular structure of the ionic liquids and their specific orientation at the liquid-vacuum interface.<br

Boosting performance of low temperature fuel cell catalysts by subtle ionic liquid modification - Zhang, Guirong; Munoz Garcia, Macarena; Etzold, Bastian (ACS Applied Materials and Interfaces, 2015)
High cost and poor stability of the oxygen reduction reaction (ORR) electrocatalysts are the major barriers for broad-based application of polymer electrolyte membrane fuel cells. Here we report a facile and scalable approach to improve Pt/C catalysts for ORR, by modification with small amounts of hydrophobic ionic liquid (IL). The ORR performance of these IL-modified catalysts can be readily manipulated by varying the degree of IL filling, leading to a 3.4 times increase in activity. Besides, the IL-modified catalysts exhibit substantially enhanced stability relative to Pt/C. The enhanced performance is attributed to the optimized microenvironment at the interface of Pt and electrolyte, where advantages stemming from an increased number of free sites, higher oxygen concentration in the IL and electrostatic stabilization of the nanoparticles develop fully, at the same time that the drawback of mass transfer limitation remains suppressed. These findings open a new avenue for catalyst optimization for next-generation fuel cells.
EAM Import::2019-03-13

Boosting power density of hydrogen release from LOHC systems by an inverted fixed-bed reactor design - Kadar, Julian; Gackstatter, Felix; Ortner, Florian; Wagner, Lisa; Willer, Miriam; Preuster, Patrick; Wasserscheid, Peter; Geißelbrecht, Michael (International Journal of Hydrogen Energy, 2024)
Hydrogen storage and transportation in form of charged Liquid Organic Hydrogen Carrier (LOHC) systems is attractive as these hydrocarbon-based carrier molecules can provide hydrogen using the existing infrastructure for fossil fuels. For hydrogen release on board of heavy-duty vehicles, however, the limited volumetric power density of the hydrogen release units was so far seen as a critical factor. Herein, we show that the power density achieved in perhydro benzyltoluene dehydrogenation in a classical fixed-bed dehydrogenation reactor can be doubled by applying an inverted multi-tubular reactor with upstream LOHC flow and hydrogen release in the reactor housing and crossflow heating through perpendicular heating tubes. The resulting power densities of up to 0.76kWH2-LHV L−1reactor-outside (with respect to the total reactor housing), and 2.34kWH2-LHV L−1reactor-inside (with respect to inner reactor volume) bring on-board hydrogen release of LOHC-bound hydrogen much closer to technical reality. This very impressive increase in power density is mainly due to the fact, that the inverted arrangement of catalyst bed and heat transfer tubes offers a much higher catalyst volume per reactor volume compared to a classical fixed-bed reactor.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Dehydrogenation; Heat transfer; Hydrogen storage; LOHC; Perhydro benzyltoluene

Boosting the Activity in Supported Ionic Liquid-Phase-Catalyzed Hydroformylation via Surface Functionalization of the Carbon Support - Weiß, Alexander; Munoz, Macarena; Haas, Alexander; Rietzler, Florian; Steinrück, Hans-Peter; Haumann, Marco; Wasserscheid, Peter; Etzold, Bastian (ACS Catalysis, 2016)
Supported ionic liquid phase (SILP) catalysts are comprised of a thin ionic liquid film containing a homogeneous transition metal complex that is supported on a highly porous substrate. The application of functionalized activated carbon as a support material for SILP catalysts in a continuous gas-phase propene hydroformylation reaction reveals that the surface properties of the carbon support have a significant influence on the catalytic performance. The catalytic activity of the pristine activated carbon-based SILP catalysts was found to be negligibly small (TOF4h = 3.5 h(-1)) in contrast to that of common oxidic supports such as silica (TOF4h = 15 h(-1)) or alumina. By amine functionalization of the carbon support surface, a dramatic increase in catalytic activity could be observed outperforming the tested oxidic supports by an order of magnitude. A distinct relationship between increased nitrogen content and the point of zero charge of the support and the catalytic activity could be observed. The largest activity increase (TOF4h = 105 h(-1)) was found for functionalized activated carbon SILP catalysts featuring a high point of zero charge and a high nitrogen content. Despite the fact that aldol formation is catalyzed by a base, the respective alcohol was the only detectable byproduct in the reactions.
Keywords: hydroformylation; supported ionic liquid phase; surface functionalization; amino groups; activated carbon

Boosting the activity of hydrogen release from liquid organic hydrogen carrier systems by sulfur-additives to Pt on alumina catalysts - Auer, Franziska; Blaumeiser, Dominik; Bauer, Tanja; Bösmann, Andreas; Szesni, Normen; Libuda, Jörg; Wasserscheid, Peter (Catalysis: Science and Technology, 2019)
Liquid organic hydrogen carrier (LOHC) systems are a promising alternative for energy storage and transport. The development of an active and selective LOHC-dehydrogenation catalyst is therefore of great importance. In this study we present a modification procedure of Pt/Al2O3 catalysts with a sulfur containing compound that results in improved activity as well as in reduced side product formation. Here, it appears that the right amount of applied sulfur species is crucial to reach the described effects. The optimum value depends on the support surface area and the molar ratio of sulfur to surface platinum. Mechanistic studies of the sulfur modification by infrared spectroscopy (DRIFTS) with adsorbed CO revealed that preferentially low coordinated defect sites (edges or corner/apex Pt atoms) are blocked by sulfur compounds and that these are the ones responsible for side reactions. The sulfur species were found to modify the electronic properties of Pt and this facilitates the desorption of the aromatic dehydrogenation products.
CRIS-Team Scopus Importer:2019-07-16

Boron containing magnetic nanoparticles for neutron capture therapy - an innovative approach for specifically targeting tumors - Tietze, Rainer; Unterweger, Harald; Dürr, Stephan; Lyer, Stefan; Canella, Lea; Kudejova, Petra; Wagner, Franz M.; Petry, Winfried; Taccardi, Nicola; Alexiou, Christoph (Applied Radiation and Isotopes, 2015)
The selective delivery of (10)B into the tumor tissue remains to be further improved for successful and reliable Boron Neutron Capture Therapy applications. Magnetic Drug Targeting using intraarterially administered superparamagnetic nanoparticles and external magnetic fields already exhibited convincing results in terms of highly efficient and selective drug deposition. Using the same technique for the targeted (10)B delivery is a promising new approach. Here, systematic irradiation experiments of phantom cubes containing different concentrations of boron and nanoparticles as well as varying three-dimensional arrangements have been performed.
EVALuna2:19923

Boron-containing MFI-type zeolites with a hierarchical nanosheet assembly for lipase immobilization - Marthala, Venkata; Urmoneit, Lynn; Zhou, Zhou; Machoke, Albert; Schmiele, Martin; Unruh, Tobias; Schwieger, Wilhelm; Hartmann, Martin (Dalton Transactions, 2017)
Hierarchical nanosheet assemblies of boron-containing MFI-type zeolites were successfully synthesized using bifunctional surfactant molecules under static conditions. With the optimized Si/B = 50 in the synthesis gel, a material with high specific surface area (483 m2 g(-1)) and a maximum pore size of 6.5 nm suitable for lipase encapsulation was obtained.

Brønsted acidic SILP-based catalysts with H3PMo12O40 or H3PW12O40 in the oxidative desulfurization of fuels - Bryzhin, A. A.; Gantman, Mikhail; Buryak, A. K.; Tarkhanova, I. G. (Applied Catalysis B-Environmental, 2019)
In this manuscript novel heterogeneous catalysts for fuel desulfurization via peroxide oxidation are reported. The obtained catalysts combine high catalytic activity and stability with perfect synthetic availability, their composition and structure were ascertained. The catalysts represent supported ionic liquid phases (SILPs): Brønsted acidic ILs, namely 4-(3′- ethylimidazolium)-butanesulfonate, with two heteropolyacids (HPA) (sulfated ionic liquid protonated by H3PMo12O40 or H3PW12O40). Silica and γ-Al2O3 were used as support materials. These compositions ensure higher stability of heteropolyanions and make the catalyst stable over several successive oxidation cycles. The most active catalyst based on phosphomolybdic acid provides a high conversion rate for thiophene, thioanisole, and dibenzothiophene (turn over frequency of about 150–1200 h−1 per mole of HPA). Another important benefit of the reported systems is the desulfurization of diesel fuel with a very high efficiency (residual amount of sulfur <10 ppm) under mild conditions.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Catalytic oxidative desulfurization; Hydrogen peroxide; Phosphomolybdic and phosphotungstic heteropolyacids; Supported ionic liquid phase

Building concept inspired by raspberries: From microporous zeolite nanocrystals to hierarchically porous assemblies - Klumpp, Michael; Zeng, L.T.; Al-Thabaiti, Shaeel A.; Weber, Alfred P.; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2016)
Hierarchically porous zeolites offer great potential in catalytic and sorptive processes due to the enhanced mass transport properties by the increased diffusivity of the molecules from the bulk phase to the final active sites or sorption sites, respectively. In this contribution we present a simple, 3-step bottom-up preparation route yielding binder-free spherical zeolite material exhibiting a hierarchical pore system. This process consists of zeolite synthesis, aggregation and recrystallization. In this contribution, the process is demonstrated on silicalite-1 (MFI-type zeolite) as a model system. The aggregation process was realized by special spray drying of a complete reaction mixture containing pre-synthesized nanocrystals. The spray drying process results in spherical aggregates which contain amorphous silica species originating from the unconverted part of the zeolite synthesis mixture and which are acting as an intermediate binder. Steam-assisted crystallization was then applied to convert these amorphous species into crystalline zeolite enabling the overall process to utilize 100% of the initial silicon from the zeolite synthesis mixture. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Hierarchical porosity; Nanozeolite; Steam-assisted crystallization; Aggregation; Spray drying

Burner-heated dehydrogenation of a liquid organic hydrogen carrier (LOHC) system - Bollmann, Jonas; Mitländer, Kerstin; Beck, Dominik; Schühle, Patrick; Bauer, Florian; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (International Journal of Hydrogen Energy, 2023)
For a hydrogen-based economy, safe and efficient hydrogen storage is essential. Compared to other chemical hydrogen storage technologies, such as ammonia or methanol, liquid organic hydrogen carrier (LOHC) systems allow for a reversible storage of hydrogen while being easy to handle in a diesel-like manner. In our contribution, we describe for the first time the successful utilization of the exhaust gas enthalpy of a porous media burner to directly supply the dehydrogenation heat for a kW-scale dehydrogenation of the hydrogen-rich LOHC compound perhydro dibenzyltoluene (H18-DBT). Our setup demonstrates the dynamics of the dehydrogenation unit at a realized maximum hydrogen power of 3.9 kWth, based on the lower heating value of the released hydrogen. For the intended applications with fluctuating hydrogen demand, e.g. a hydrogen refueling station (HRS) or stationary heating in buildings, a dynamic hydrogen supply from LOHC is important. Methane, e.g. from a biogas plant, is utilized in our scenario as a fuel source for the burner. Hydrogen is released within 30 min after cold start of the system. The dehydrogenation unit exhibits a power density relative to the reactor volume of about 0.5 kWtherm l−1 based on the lower heating value of the hydrogen and a catalyst productivity of up to 0.65 gH2 gPt−1 min−1 for hydrogen release from H18-DBT. An analysis of the by-products and reaction intermediates shows low by-product formation (e.g. maximum 0.6 wt.-% for high boilers and 0.9 wt.- % for low boilers) and uniform distribution of intermediates after the reaction. Thus, a relatively homogeneous temperature distribution and a uniform LOHC flow in the reaction zone can be assumed. Our findings illustrate the dynamics (heating rates of about 10 K min−1) and performance of direct heating of a release unit with a burner and represent a significant step towards LOHC-based hydrogen provisioning systems at technically relevant scales.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Dehydrogenation; Dynamic heat supply; Hydrogen storage; LOHC; Porous media burner

Butane Oxidation to Maleic Anhydride over a VPO Catalyst Following the Riser Regenerator Approach - Freund, Hannsjörg; et al. (Studies in Surface Science and Catalysis, 2001)

Capturing spatially resolved kinetic data and coking of Ga-Pt Supported Catalytically Active Liquid Metal Solutions during propane dehydrogenation in situ - Wolf, Moritz; Raman, Narayanan; Taccardi, Nicola; Horn, Raimund; Haumann, Marco; Wasserscheid, Peter (Faraday Discussions, 2020)
Supported liquid phase catalysis has great potential to unify the advantages from both, homogeneous and heterogeneous catalysis. Recently, we reported Supported Catalytically Active Liquid Metal Solutions (SCALMS) as a new class of liquid phase catalysts. SCALMS enable high temperature application due to the high thermal stability of liquid metals when compared to supported molten salts or ionic liquids. The highly dynamic liquid metal/gas interface of SCALMS allows for catalysis over single atoms of an active metal atom within a matrix of liquid gallium. In the present study, kinetic data is acquired along the catalyst bed in a compact profile reactor during propane dehydrogenation over gallium-platinum SCALMS. The reactor design allows for analysis of the temperature and gas phase composition along the catalyst bed with a high spatial resolution using a sampling capillary inside the reactor. The concentration profiles suggest enhanced deactivation of the catalyst at the end of the bed with a deactivation front moving from the end to the beginning of the catalyst bed over time on stream. Only minor amounts of side products, formed via cracking of propane, were identified supporting previously reported high selectivity of SCALMS during alkane dehydrogenation. The acquired data is supported by in situ high-resolution thermogravimetry coupled with mass spectrometry to monitor the activity and coking behaviour of SCALMS during propane dehydrogenation. The results strongly suggest an enhanced formation of coke over Al2O3-supported SCALMS when compared to SiO2 as support material.<br

Capturing the interconnectivity of water-induced oxidation and sintering of cobalt nanoparticles during the Fischer-Tropsch synthesis in situ - Wolf, Moritz; Fischer, Nico; Claeys, Michael (Journal of Catalysis, 2019)
Keywords: Magnetometer; Model catalyst; Deactivation; Fischer-Tropsch synthesis; Water; Oxidation; Sintering; Cobalt catalyst

Carbide-derived carbon with hollow core structure and its performance as catalyst support for methanol electro-oxidation - Ariyanto, Teguh; Kern, Andreas; Etzold, Bastian; Zhang, Guirong (Electrochemistry Communications, 2017)
New hollow core particles of mesoporous/graphitic carbon were successfully prepared from carbon core-shell particles, through selective removal of the core. Electrocatalysts prepared by dispersing platinum on these hollow core materials showed remarkably high dispersion. The combination of high dispersion with short pore diffusion length allowed to obtain high mass specific activity in methanol electro-oxidation (ca. 390 A gPt − 1), along with excellent long-term stability. These novel carbon nanostructures show great promise as Pt catalyst support for methanol oxidation.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; Fuel cells; Hollow core particles; Methanol electro-oxidation; Pt electrocatalysts

Carbon Dioxide Capture by an Amine Functionalized Ionic Liquid: Fundamental Differences of Surface and Bulk Behavior - Niedermaier, Inga; Bahlmann, Matthias; Papp, Christian; Kolbeck, Claudia; Wei, Wei; Krick Calderon, Sandra; Grabau, Mathias; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of the American Chemical Society, 2014)
Carbon dioxide (CO2) absorption by the amine-functionalized ionic liquid (IL) dihydroxyethyl dimethylammonium taurinate at 310 K was studied using surface- and bulk-sensitive experimental techniques. From near-ambient pressure X-ray photoelectron spectroscopy at 0.9 mbar CO2, the amount of captured CO2 per mole of IL in the near-surface region is quantified to similar to 0.58 mol, with similar to 0.15 mol in form of carbamate dianions and similar to 0.43 mol in form of carbamic acid. From isothermal uptake experiments combined with infrared spectroscopy, CO2 is found to be bound in the bulk as carbamate (with nominally 0.5 mol of CO2 bound per 1 mol of IL) up to similar to 2.5 bar CO2, and as carbamic acid (with nominally 1 mol CO2 bound per 1 mol IL) at higher pressures. We attribute the fact that at low pressures carbamic acid is the dominating species in the near-surface region, while only carbamate is formed in the bulk, to differences in solvation in the outermost IL layers as compared to the bulk situation.

Carbon Dioxide-Free Hydrogen Production with Integrated Hydrogen Separation and Storage - Dürr, Stefan; Müller, Michael; Jorschick, Holger; Helmin, Marta; Bösmann, Andreas; Palkovits, Regina; Wasserscheid, Peter (Chemsuschem, 2017)
An integration of CO2-free hydrogen generation through methane decomposition coupled with hydrogen/methane separation and chemical hydrogen storage through liquid organic hydrogen carrier (LOHC) systems is demonstrated. A potential, very interesting application is the upgrading of stranded gas, for example, gas from a remote gas field or associated gas from off-shore oil drilling. Stranded gas can be effectively converted in a catalytic process by methane decomposition into solid carbon and a hydrogen/methane mixture that can be directly fed to a hydrogenation unit to load a LOHC with hydrogen. This allows for a straight-forward separation of hydrogen from CH4 and conversion of hydrogen to a hydrogen-rich LOHC material. Both, the hydrogen-rich LOHC material and the generated carbon on metal can easily be transported to destinations of further industrial use by established transport systems, like ships or trucks.
Keywords: hydrogen storage; hydrogenation; liquid organic hydrogen carriers; methane decomposition; upgrading

Carbon Nanohorn-based electrolyte for Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Casillas Pacheco, Ruben; Kohler, Florian; Wasserscheid, Peter; Prato, Maurizio; Guldi, Dirk Michael (Energy and Environmental Science, 2014)
For the first time, carbon nanohorns were implemented into solid-state electrolytes for highly efficient solid-state and quasi-solid-state DSSCs. They feature an effective catalytic behavior towards the reduction of I3- and enhance the I3- diffusivity into the electrolyte. In a final device, solar cells with 7.84% efficiency at room temperature were achieved. As a matter of fact, this is the highest reported efficiency for nanocarbon-based electrolytes up to date.

Catalyst activation and influence of the oil matrix on the extractive oxidative desulfurization using aqueous polyoxometalate solutions and molecular oxygen - Bertleff, Benjamin; Claußnitzer, Johannes; Korth, Wolfgang; Wasserscheid, Peter; Jess, Andreas; Albert, Jakob (Energy & Fuels, 2018)
Our contribution describes the oxidative desulfurization of dibenzothiophene (DBT) from model oils using an aqueous H8PV5Mo7O40 (HPA-5) catalyst solution and molecular oxygen as the oxidant. In contrast to common oxidative desulfurization (ODS) protocols, the organic sulfur compound DBT is oxidized to water-soluble compounds, such as sulfuric acid (50–55%), sulfoacetic acid (20–25%), and sulfobenzoic acid (25–30%), which are extracted in situ into the aqueous catalyst phase. We describe the activating effect of oxalic acid on the ODS performance of the catalyst and propose a mechanism for the catalyst activation. Moreover, we report on the influence of various organic solvents, i.e., n-alkanes and aromatics, on the oxidative DBT removal. Remarkably, the rate of DBT oxidation and removal enhances with an increasing chain length of the alkane matrix, whereas aromatic compounds in the oil matrix inhibit the desulfurization rate. Moreover, we demonstrate that the aqueous catalyst phase can be reused at least 5 times without loss in catalytic performanc

Catalyst recycling in monophasic Pt-catalyzed hydrosilylation reactions using ionic liquids - Taccardi, Nicola; Fekete, Melinda; Berger, Markus; Stanjek, Volker; Schulz, Peter; Wasserscheid, Peter (Applied Catalysis A-General, 2011)
The technical relevant Pt-catalyzed hydrosilylation of allyl chloride with trichlorosilane was investigated in a monophasic reaction system containing an ionic liquid (IL) additive. ILs screening allowed us to identify the liquid 1-decyl-3-methylimidazolium bis(trifloromethanesulfonyl)amide ([DMIM][NTf2]) as the best additive for such process. This IL combined complete miscibility with reactants as long as chemical and thermal robustness. After the reaction, the hydrosilylation product (3-chloropropyl)trichlorosilane was distilled off and the residual IL/catalyst solution could be reused. In such a way, a final TON of 14,200 was achieved over 10 reaction/distillation cycles without any loss of catalytic activity. The ability of [DMIM][NTf2] to prevent catalyst decomposition was deeper investigated and it was found that even with a Pt loading as high as 9500 ppm, the IL acted as protective/stabilizing agent for the catalyst during the thermally stressing product distillation.

Catalyst system for steam reforming of methanol. - Bösmann, Andreas; Enzenberger, Florian; Maaß, Hans-Jürgen; Wasserscheid, Peter (2012)
A catalyst system for steam reforming of methanol includes a porous catalyst support at the surface of which catalytically active centers are arranged, as well as a salt melt contg. inorg. cations and org. anions which covers at least a part of the surface and the catalytically active centers. The catalyst support can be carbon, titania, alumina, silica, and/or zirconia. The catalytically active centers can consist of Pt, Pd, Ru, Rh, Ir, Cu, and/or Zn. The salt melt can contain Li+, Na+, K+, Cs+, Mg2+, Ca2+, Ba2+, Al3+, Sc3+, and La3+ as cations. The anions of the salt melt can be ions of the general formula R1-COO-, R2-SO3-, R3-O-SO3-, R4-PO4-R5-, and (R6-SO2-)2N- with R1, R2, R3, R4, R5, and R6 being the same or different aliph., alicyclic, or arom. C1-30 hydrocarbon rests the H atoms of which may be substituted by F atoms, hydroxy groups, or carboxylate groups. [on SciFinder(R)]
Keywords: catalyst system steam reforming methanol salt melt porous support

Catalytically activated stainless steel plates for the dehydrogenation of perhydro dibenzyltoluene - Solymosi, Thomas Andrew; Auer, Franziska; Dürr, Stefan; Preuster, Patrick; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2021)
Hydrogen storage and transport via Liquid Organic Hydrogen Carriers (LOHC) is gaining increasing attention. In this study, we present catalytically activated stainless steel plates as a promising alternative to the commonly used pellet catalysts for the dehydrogenation of perhydro dibenzyltoluene (H18-DBT). These plate catalysts promise better heat transport to the active sites. For improved performance, we modified our Pt/alumina plate catalysts by using i) platinum sulfite impregnation and ii) post-treatment with (NH4)2SO4. Post-treatment with (NH4)2SO4 resulted in a less active catalyst with lower formation of high-boiling side products compared to the S-free plate catalyst. Catalysts prepared with platinum sulfite showed both >35% higher activities and 90% reduction in high-boiler formation compared to the S-free plate catalysts. Our findings pave the way for the development of catalytically activated heat transfer plates that would allow the incorporation of LOHC dehydrogenation units into the geometry of future high temperature fuel cell stacks.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Dehydrogenation; LOHC; Perhydro dibenzyltoluene; Plate catalysts; Selective poisoning

Catalytic hydrogenation using ionic liquids as catalyst phase - Wasserscheid, Peter; Schulz, Peter (Wiley-VCH Verlag GmbH, 2007)
This chapter contains sections titled: Introduction to Ionic Liquids Homogeneous Catalyzed Hydrogenation in Biphasic Liquid-Liquid Systems Homogeneous Catalyzed Hydrogenation in Biphasic Ionic Liquid/Supercritical (sc)CO2 System Supported Ionic Liquid Phase Catalysis Conclusion
Keywords: ionic liquids; chloroaluminate salts; transition-metals; olefins; hydrogenation

Catalytic low-temperature dehydration of fructose to 5-hydroxymethylfurfural using acidic deep eutectic solvents and polyoxometalate catalysts - Körner, Sam; Albert, Jakob; Held, Christoph (Frontiers in Chemistry, 2019)

Catalytic production of hydrogen from glucose and other carbohydrates under exceptionally mild reaction conditions - Taccardi, Nicola; Assenbaum, Daniel; Berger, Markus; Bösmann, Andreas; Enzenberger, Florian; Woelfel, Rene; Neuendorf, Stephanie; Göke, Volker; Schödel, Nicole; Maaß, Hans-Jürgen; Kistenmacher, Hans; Wasserscheid, Peter (Green Chemistry, 2010)
A catalytic reaction system for the production of hydrogen from sugars and even water-insoluble biomass like cellulose is presented. The reaction system is based on an ionic liquid that has the role to dissolve the carbohydrate feedstock and a ruthenium catalyst. As hydrogen dissolves in this media at very low level, hydrogen consuming side reactions have been hindered, leading to a gaseous product mixture consisting mainly of hydrogen and carbon dioxide. Investigations with isotopic labelling suggest a reaction sequence in which glucose first thermally decomposes to formic acid followed by Ru-catalyzed decomposition of the latter to hydrogen and CO_2.

Catalytic SILP Materials - Riisager, Anders; Fehrmann, Rasmus; Haumann, Marco; Wasserscheid, Peter (Topics in Organometallic Chemistry, 2008)
The principle of catalytic SILP materials involves surface modification of a porous solid material by an ionic liquid coating. Ionic liquids are salts with melting points below 100°C, generally characterized by extremely low volatilities. In the examples described in this paper, the ionic liquid coating contains a homogeneously dissolved Rh-complex and constitutes a uniform, thin film, which itself displays the catalytic reactivity in the system. Continuous fixed-bed reactor technology has been applied successfully to demonstrate the feasibility of catalytic SILP materials for propene hydroformylation and methanol carbonylation.

Catalytic test reactions for the evaluation of hierarchical zeolites - Hartmann, Martin; Machoke, Albert; Schwieger, Wilhelm (Chemical Society Reviews, 2016)
Hierarchical zeolites have received increasing attention in the last decade due to their outstanding catalytic performance. Several types of hierarchical zeolites can be prepared by a large number of different techniques. Hierarchical zeolites combine the intrinsic catalytic properties of conventional zeolites and the facilitated access and transport in the additional meso-or macropore system. In this tutorial review, we discuss several test reactions that have been explored to show the benefit of the hierarchical pore system with respect to their suitability to prove the positive effects of hierarchical porous zeolites. It is important to note that positive effects on activity, stability and less frequently selectivity observed for hierarchically structured catalysts not necessarily are only a consequence of the additional meso-or macropores but also the number, strength and location of active sites as well as defects and impurities. With regard to these aspects, the test reaction has to be chosen carefully and potential changes in the chemistry of the catalyst have to be considered as well. In addition to the determination of conversion, yield and selectivity, we will show that the calculation of the activation energy and the determination of the Thiele modulus and the effectiveness factor are good indicators of the presence or absence of diffusion limitations in hierarchical zeolites compared to their parent materials.

Cellulose-Based Ionogels for Paper Electronics - Thiemann, Stefan; Sachnov, Swetlana; Pettersson, Fredrik; Bollström, Roger; Österbacka, Ronald; Wasserscheid, Peter; Zaumseil, Jana (Advanced Functional Materials, 2014)
A new class of biofriendly ionogels produced by gelation of microcellulose thin films with tailored 1-ethyl-3-methylimidazolium methylphosphonate ionic liquids are demonstrated. The cellulose ionogels show promising properties for application in flexible electronics, such as transparency, flexibility, transferability, and high specific capacitances of 5 to 15 extgreekmF cm-2. They can be laminated onto any substrate such as multilayer-coated paper and act as high capacitance dielectrics for inorganic (spray-coated ZnO and colloidal ZnO nanorods) and organic (poly[3-hexylthiophene], P3HT) electrolyte-gated field-effect transistors (FETs), that operate at very low voltages (<2 V). Field-effect mobilities in ionogel-gated spray-coated ZnO FETs reach 75 cm2 V-1 s-1 and a typical increase of mobility with decreasing specific capacitance of the ionogel is observed. Solution-processed, colloidal ZnO nanorods and laminated cellulose ionogels enable the fabrication of the first electrolyte-gated, flexible circuits on paper, which operate at bending radii down to 1.1 mm.

Cetyltrimethylammonium bromide-silica membrane for seawater desalination through pervaporation - Singh, Puyam S.; Chaudhri, Sanjay G.; Kansara, Ankit M.; Schwieger, Wilhelm; Selvam, Thangaraj; Reuß, Stephanie; Aswal, Vinod K. (Bulletin of Materials Science, 2015)
A simple preparation of mesostructured cetyltrimethylammonium bromide (CTAB)-silica membrane is reported. It effectively desalinates seawater to pure water through pervaporation separation process. The membrane thickness was of nanometer-length-scale obtained by deposition of CTAB-silica colloids on porous polysulfone support. Scanning electron microscopy (SEM), atomic force microscopy (AFM) and transmission electron microscopy (TEM) studies were performed to characterize the membrane while the structure of the colloids in coating solution was probed by small-angle neutron scattering (SANS). The prepared membranes exhibited excellent salt rejection efficiency of 99.9% in desalination of synthetic seawater of 40,000 ppm NaCl by pervaporation at 25(a similar to)C. The pure water flux was in the range of 1-2.6 kg m(-2) h depending upon the membrane configuration and thickness. The flux could be greatly enhanced by operating the process at higher temperatures of 40-80(a similar to)C but it was at the cost of decreased salt-rejection efficiency. The initial rejection efficiency and flux of the membrane was found to be restored upon cooling the membrane back to room temperature.
Keywords: Seawater desalination; cetyltrimethylammonium bromide-silica membrane; pervaporation

Ce-, Zr-containing oxide layers formed by plasma electrolytic oxidation on titanium as catalysts for oxidative desulfurization - Tarkhanova, I. G.; Bryzhin, A. A.; Gantman, Mikhail; Yarovaya, T. P.; Lukiyanchuk, I.; Nedozorov, P. M.; Rudnev, V. S. (Surface & Coatings Technology, 2019)
Mixed cerium-zirconum-titanum oxide layers: CeOx + TiO2, CeOx + ZrO2 + TiO2, ZrO2 + TiO2 - on titanium were formed by plasma electrolytic oxidation technique in the electrolytes with different ratio of Ce(SO4)(3): Zr (SO4)(2) and investigated by the complex of physical-chemical methods. Their activity was studied in the peroxide oxidation of sulfur compounds (thiophene, thioanizole and dibenzothiophene) and the desulfurization of diesel fuel. Element and phase composition of the PEO-coated samples affect their catalytic activity. ZrO2 + TiO2 + CeOx systems with the largest content of zirconium showed the highest catalytic activity in oil desulfurization. Their catalytic activity correlates with the presence of the double oxides ZrTiO4 and Ti2ZrO6 in the coating composition. The decrease in the activity of catalysts when they are used in consecutive cycles can be accounted for by the etching of the coatings in the area of the pores. This drawback one can overcome by the addition of an ionic liquid namely 4-(3'-ethylimidazolium)-butanesulfonate, which increases not only the activity, but also the stability of the catalysts. Under these conditions, the structure and activity of the catalyst did not change significantly over several reaction cycles. The combination of PEO treatment and deposition of the ionic liquid allowed one not only to oxidize model substrates, but also carry out the desulfurization of diesel fuel to a residual sulfur content of less than 10 ppm.
CRIS-Team WoS Importer:2019-04-02

CFD-calculation of flow, dispersion and reaction in a catalyst filled tube by Lattice Boltzmann method - Zeiser, Thomas; Lammers, Peter; Klemm, Elias; Li, Yong-Wang; Bernsdorf, Jörg; Brenner, Gunter (Chemical Engineering Science, 2001)
The behaviour of a reacting, viscous flow inside the complex geometry of a fixed-bed reactor has been studied by means of a lattice Boltzmann automata (LBA). In particular, two tasks have been investigated in detail. The geometrical structures of the fixed bed have been generated with a Monte-Carlo method. This allows to simulate very efficiently the placement of randomly packed spheres in a cylinder and to obtain detailed information of statistical properties, such as the voidage distribution. This geometrical information is the base for the subsequent numerical flow simulation using a lattice Boltzmann automata. This approach allows to predict the local fluid velocity distribution in the bed as well as the transport and reactions of chemical species taking into account the effect of heterogeneous catalysis. Thus, detailed information can be provided for the diffusion/dispersion effects around catalytic particles and ensembles of spheres. It is shown that this approach allows to improve the understanding of the underlying transport and reaction phenomena in these reactors and to obtain a reliable database for their operating behaviour and design. (C) 2001 Elsevier Science Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2001.tech.ITC.stmmec.cfdcal
Keywords: computational fluid dynamics; lattice Boltzmann automata; packed structure; void fraction; velocity profile; detailed simulation

CFD calculations of flow, dispersion and chemical reactions in fixed bed tubular reactors using the lattice Boltzmann method - Freund, Hannsjörg; Zeiser, Thomas; et al. (High Performance Scientific and Engineering Computing, Lecture Notes in Computational Science and Engineering, 2002)
Detailed 3-D simulations are required to correctly predict the coupled behaviour of flow and mass transport in chemical reactors with e-asymmetry. These simulations can be of great technical and economical interest as the reactor performance and safety during operation are significantly influenced by the local flow behaviour. One particular interesting example are randomly filled tubular fixed bed reactors with small tube-to-particle diameter ratios. New numerical methods such as the lattice Boltzmann approach together with the increasing computational power can provide detailed insight into the flow and transport processes in complex geometries. The present paper demonstrates the applicability of this approach by investigating complex flows and showing first results of the inhomogeneities in the 3-D flow of reacting species in a tubular fixed bed reactor.

Challenging the scope of continuous, gas-phase reactions with supported ionic liquid phase (SILP) catalysts-Asymmetric hydrogenation of methyl acetoacetate - Öchsner, Eva; Schneider, Martin; Meyer, Carolin; Haumann, Marco; Wasserscheid, Peter (Applied Catalysis A-General, 2011)
In the last years Supported Ionic Liquid Phase (SILP) catalysis has attracted growing interest for continuous gas phase reactions. The concept combines in a unique manner the advantages of traditional homogeneous and heterogeneous catalysis by making use of the extremely low vapor pressure of an ionic liquid film on support. In this way, continuous gas phase reactions with macroscopically solid but microscopically homogeneous catalyst materials have been successfully realized. However—so far—continuous gas-phase SILP catalysis has only been demonstrated for reactions with relatively simple selectivity problems (such as, regioselectivity, chemoselectivity). This study demonstrates the successful application of a SILP catalyst in continuous gas phase asymmetric hydrogenation. The hydrogenation of methyl acetoacetate (MAA) is presented using an immobilized dibromo[3-(2,5-(2R,5R)-dimethylphospholanyl-1)-4-di-o-tolylphosphino-2,5-dimethylthio-phene]-ruthenium (Ru1Br2) catalyst.

Characterisation of DSSC-electrolytes based on 1-ethyl-3-methylimidazolium dicyanamide: Measurement of triiodide diffusion coefficient, viscosity, and photovoltaic performance - Wachter, Philipp; Zistler, Markus; Schreiner, Christian; Berginc, Marko; Krasovec, Ursa Opara; Gerhard, Dirk; Wasserscheid, Peter; Hinsch, Andreas; Gores, Heiner J. (Journal of Photochemistry and Photobiology A-Chemistry, 2008)
A comprehensive characterisation of an ionic liquid based electrolyte for dye-sensitised solar cells (DSSC) was performed by determination of triiodide diffusion coefficients, viscosities and photovoltaic performances. The electrolyte, consisting of 1-ethyl-3-methylimidazolium dicyanamide, 1-methyl-3-propylimidazolium iodide (MPII), and iodine, was examined at varying ionic liquid molar ratio and fixed iodine concentration, as well as at fixed ionic liquid molar ratio and varying iodine concentration. All measurements were conducted at controlled temperature over a broad temperature range to analyse the electrolyte properties in view of thermal stress of the DSSC during later practical application. The triiodide diffusion coefficient increases with decreasing MPII concentration or increasing temperature, caused by decreasing electrolyte viscosity. Additionally, strong non-Stokesian behaviour over the whole ionic liquid mixing range was found, decreasing at higher temperatures. Photovoltaic measurements showed that the DSSC efficiency is limited by triiodide diffusion at low temperatures and low iodine concentrations whereas at high temperatures it is limited by recombination processes, leading to a maximum for DSSC efficiency at a certain temperature. The exchange between diffusion limitation of DSSC efficiency and limitation by recombination and therefore the maximum for DSSC efficiency is shifted to lower temperatures by increasing iodine concentration. © 2007 Elsevier B.V. All rights reserved.
Keywords: Diffusion coefficients; Dye-sensitised solar cell; Ionic liquid electrolyte; Photovoltaic performance

Characterization of Biogenic Silica Generated by Thermo Chemical Treatment of Rice Husk - Alyosef, Hallah Ahmad; Eilert, Andre; Welscher, Julia; Ibrahim, Suzan S.; Denecke, Reinhard; Schwieger, Wilhelm; Enke, Dirk (Particulate Science and Technology, 2013)
This study presents two routes to produce amorphous silica from an Egyptian rice husk under conditions optimized for least environmental impact and low cost. The first route includes thoroughly washing of the husk sample with water, dry milling and leaching with citric acid. The leaching process was applied in two stages, that is, at 323K for 180min and then at 353K for 60min. After washing and drying, the leached sample was subjected to a heat treatment in a muffles furnace at four sequential steps. The second route includes all the previously mentioned steps, except the citric acid leaching. The final products were characterized using x-ray fluorescence analysis, carbon content analysis, x-ray diffraction, differential thermal analysis, nitrogen adsorption, mercury intrusion, and scanning electron microscopy. The results show that the citric acid leaching has many advantages with respect to silica yield and porosity as well.
Keywords: leaching; porosity; rice husk (RH); rice husk ash (RHA); sequential burning

Characterization of nanoporous monoliths using nitrogen adsorption and positronium annihilation lifetime spectroscopy - Inayat, Alexandra; Enke, Dirk; Thraenert, Stefan; Krause-Rehberg, Reinhard; et al. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2010)
The characterization of nanoporous materials is essential for their application as model systems. In this study, nanoporous glass monoliths with a pore diameter below 10 nm were used as model system to compare the pore size analysis performed via nitrogen adsorption and positronium annihilation lifetime spectroscopy (PALS). For determination of pore size distribution via nitrogen sorption, B.J.H. method and DFT method were used. By applying positronium annihilation lifetime spectroscopy as independent characterization technique, DFT method was validated to provide more realistic results for the pore size distribution of the model materia

Charging a Liquid Organic Hydrogen Carrier System with H2/CO2 Gas Mixtures - Jorschick, Holger; Bösmann, Andreas; Preuster, Patrick; Wasserscheid, Peter (ChemCatChem, 2018)
Liquid Organic Hydrogen Carrier (LOHC) systems have attracted growing attention in recent years as efficient way to store and transport hydrogen in the existing infrastructures for liquid fuels. This contribution highlights the additional feature that hydrogenation of the LOHC compound dibenzyltoluene with technical relevant H2/CO2 gas mixtures (up to 30 % CO2) gives access to hydrogen purification and hydrogen storage in one single process step. Alumina supported Rh and Pd catalysts proved to be especially suitable for this task. The rhodium catalysts enabled efficient aromatics hydrogenation in the temperature range of 120 °C to 150 °C with moderate methane formation (CH4/CO2<0.1 at 150 °C). The palladium catalyst showed the lowest selectivity to methane formation (CH4/CO2<0.1 at 270 °C) and promising hydrogenation activity at temperatures above 200 °C even in the presence of CO and CO2.
CRIS-Team Scopus Importer:2023-03-29
Keywords: carbon dioxide; gas solubility; hydrogen separation; Hydrogen storage; hydrogenation

Charging a Liquid Organic Hydrogen Carrier with Wet Hydrogen from Electrolysis - Jorschick, Holger; Bulgarin, Alexander; Alletsee, Lukas; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (ACS Sustainable Chemistry & Engineering, 2019)
In this contribution we explore the combination of hydrogen production via electrolysis with subsequent storage of the hydrogen via catalytic hydrogenation of the LOHC compound dibenzyltoluene (H0-DBT) without hydrogen drying. The objective is to investigate the influence of water on the performance of Pt, Pd, Rh, and Ru (all alumina-supported) catalysts in the hydrogenation of H0-DBT. Our study shows that H0-DBT can be readily and fully hydrogenated even in the presence of a large excess of water, i.e., through the use of a water-saturated LOHC-phase. The hydrogenation activity of the ruthenium catalyst is hardly affected by water, while a slight decrease in hydrogenation activity was found in the presence of water for the applied Rh, Pt, and Pd catalyst. We conclude that wet hydrogen may be utilized in charging the LOHC compound H0-DBT, and thus, energy and drying equipment for producing dry hydrogen can be saved in the production of the hydrogen-rich carrier perhydro dibenzyltoluene (H18-DBT).
CRIS-Team WoS Importer:2019-03-15

Chemical and (Photo)-Catalytical Transformations in Photonic Crystal Fibers - Schmidt, Matthias; Cubillas, Ana Maria; Taccardi, Nicola; Euser, Tijmen; Cremer, Till; Maier, Florian; Steinrück, Hans-Peter; Russell, Philip St. John; Wasserscheid, Peter; Etzold, Bastian (ChemCatChem, 2013)
The concept of employing photonic crystal fibers for chemical and (photo)-catalytical transformations is presented. These optofluidic microdevices represent a versatile platform where light and fluids can interact for spectroscopic or photoactivation purposes. The use of photonic crystal fibers in chemistry and sensing is reviewed and recent applications as catalytic microreactors are presented. Results on homogeneous catalysis and the immobilization of homogeneous and heterogeneous catalysts in the fiber channels are discussed. The examples demonstrate that combining catalysis and the excellent light guidance of photonic crystal fibers provides unique features for example, for photocatalytic activation and quantitative photospectroscopic reaction analysis. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Chemical Recycling of Waste Polypropylene via Thermocatalytic Pyrolysis over HZSM-5 Catalysts - Inayat, Amer; Inayat, Alexandra; Schwieger, Wilhelm; Klemencova, Katerina; Lestinsky, Pavel (Chemical Engineering & Technology, 2023)
The present work deals with the chemical recycling of waste polypropylene via thermocatalytic pyrolysis over HZSM-5 zeolite catalysts. The main aim was to systematically investigate the influence of reactor configuration, zeolite acidity, polypropylene wastes, obtained from different sources, as well as catalyst regeneration on the product distribution. It was demonstrated that the reactor configuration and the acid site density of HZSM-5 catalysts strongly influence the product yields and distributions. The different types of polypropylene waste, on the other hand, showed a comparatively small yet noticeable effect on the product distribution. Moreover, it was demonstrated that the HZSM-5 catalysts exhibit good regeneration capacity during regeneration-reaction cycles.
CRIS-Team WoS Importer:2023-04-14

Chemical utilization of hydrogen from fluctuating energy sources - Catalytic transfer hydrogenation from charged Liquid Organic Hydrogen Carrier systems - Geburtig, Denise; Preuster, Patrick; Bösmann, Andreas; Müller, Karsten; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2016)
Liquid Organic Hydrogen Carrier (LOHC) systems offer a very attractive way for storing and distributing hydrogen from electrolysis using excess energies from solar or wind power plants. In this contribution, an alternative, high-value utilization of such hydrogen is proposed namely its use in steady-state chemical hydrogenation processes. We here demonstrate that the hydrogen-rich form of the LOHC system dibenzyltoluene/perhydro-dibenzyltoluene can be directly applied as sole source of hydrogen in the hydrogenation of toluene, a model reaction for large-scale technical hydrogenations. Equilibrium experiments using perhydro-dibenzyltoluene and toluene in a ratio of 1:3 (thus in a stoichiometric ratio with respect to H) yield conversions above 60%, corresponding to an equilibrium constant significantly higher than 1 under the applied conditions (270 °C).
Keywords: Dehydrogenation; Dibenzyltoluene; Hydrogen storage; Hydrogenation; Liquid Organic Hydrogen Carrier; Transfer hydrogenation

Chirality Transfer in Imidazolium Camphorsulfonate Ionic Liquids through Ion Pairing Effects - Schneiders, Karola; Bösmann, Andreas; Schulz, Peter; Wasserscheid, Peter (dvanced Synthesis & Catalysis, 2009)
The paper describes our studies on ion pair interactions in ionic liquids (IL) using an asymmetric hydrogenation reaction as probe. Three different ionic liquids carrying prochiral keto-functionalized cations were hydrogenated in the presence of their chiral, enantiomerically pure counter-ion using an achiral heterogeneous ruthenium catalyst. For the hydrogenation of N-(3′-oxobutyl)-N-methylimidazolium camphorsulfonate (2), N-(3′-oxobutyl)imidazolium camphorsulfonate (4) and N-(5′-oxohexyl)-N-methylimidazolium camphorsulfonate (6) we found a strong dependency of the enantiomeric excess (ee in the cation) on the polarity of the solvent, the concentration of the IL and the structure of the IL. The highest ee values of up to 94% were found for the hydrogenation of 2 in ethanol. Interestingly, we observed that the ee (and consequently the strength of ion pair interaction) had a pronounced maximum for a certain concentration of the IL in the solvent depending on the nature of the solvent and on the substrate. Remarkably, the concentration leading to the maximum ee could be rationalized by independent determination of the degree of dissociation which was obtained by a combination of diffusion-ordered NMR spectroscopy and conductivity measurements.

Chirality transfer in mandelate ionic liquids through ion pairing effects - Sachnov, Swetlana; Schneiders, Karola; Schulz, Peter; Wasserscheid, Peter (Tetrahedron-Asymmetry, 2010)
Ion pairing in [N-(3′-oxohexyl)-N-methylimidazolium][(R)-mandelate] was probed as a function of its concentration in ethanol and compared to the corresponding [(S)-camphorsulfonate] ionic liquid. The applied methodologies comprised asymmetric hydrogenation with ee monitoring as well as independent diffusion-ordered NMR and conductivity measurements.

Chitosan Containing Supported Ionic Liquid Phase Materials for CO2 Absorption - Pohako-Esko, Kaija; Bahlmann, Matthias; Schulz, Peter; Wasserscheid, Peter (Industrial & Engineering Chemistry Research, 2016)
Here we present novel CO2 sorbents based on chitosan ionogels. The powder sorbents called inverse supported ionic liquid phase (SILP) materials were prepared by dissolving chitosan in various ionic liquids (ILs) followed by encapsulation of the ionogel droplets with nanoporous fumed silica. CO2 absorption was determined at 40 degrees C in the range of 200 to 5500 mbar. At 1 bar, absorption capacities of these materials were 0.1-0.8 mol kg(-1); at 5 bar, values of 0.2-1.5 mol kg(-1) were reached. A comparison of inverse SILP materials with and without chitosan dissolved in the applied IL indicated that the presence of chitosan increased the CO2 absorption efficiency of the materials. The aim of the study was also to compare the CO2 absorption in pure chitosan and chitosan dissolved in ILs. It was found that dissolution increases the absorption capacity of chitosan about 10 times.

Chlorination of titanium carbide for the processing of nanoporous carbon: A kinetic study - Becker, Philipp; Glenk, Friedrich; Kormann, Martina; Popovska, Nadejda; Etzold, Bastian (Chemical Engineering Journal, 2010)
Nanoporous carbon synthesized via the chlorination of titanium carbide at temperatures above 400 °C shows a good performance, e.g. for gas storage or electrochemical applications. In this work the influence of the temperature and of the chlorine concentration on the reaction rate and the development of the porous structure during the course of the reaction was studied. The synthesis follows a Langmuir–Hinshelwood approach regarding chlorine, which can be simplified to a power law rate with the order of 0.71, and the specific surface area is created mainly in the last 10% of conversion.
EAM Import::2019-03-13

Chloroalkylsulfonate ionic liquids by ring opening of sultones with organic chloride salts - Paape, Natalia; Wei, Wei; Bösmann, Andreas; Kolbeck, Claudia; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter; Schulz, Peter (Chemical Communications, 2008)
An efficient route to prepare ionic liquids with chloroalkylsulfonate anions is presented; the synthesis proceeds in a one-step ring-opening reaction of sultones with an organic chloride salt and provides a very attractive access to new anion functionalised ionic liquids. © The Royal Society of Chemistry.

Chloroorganic impurities in technical-grade benzyltoluene – Influence on its use as LOHC compound and removal strategies - Henseler, J.; Rullo, F.; Mitländer, Kerstin; Johner, N.; Wolf, P.; Schühle, Patrick; Geißelbrecht, M.; Wasserscheid, P. (International Journal of Hydrogen Energy, 2024)
The benzyltoluene (H0-BT)/perhydro benzyltoluene (H12-BT) LOHC system is very attractive for large-scale hydrogen storage and transportation applications due to its fuel-like handling and excellent technical availability. H0-BT is applied in industrial quantities since the 1960′ies as heat trafer fluid and is technically produced by a Friedel-Crafts alkylation of chlorobenzene and toluene. However, the current production route leads to minor impurities of chloroorganic compounds in technical H0-BT that were found to severely harm the performance in the catalytic hydrogenation to H12-BT, i.e. in the hydrogen charging process of the respective LOHC storage cycle. Our contribution deals with three aspects of this practically highly relevant topic: a) It discloses the previously unknown chemical structure of the relevant chloroorganic impurities; b) it develops a process for their removal by adsorption and/or hydrodechlorination using a commercial Ni/SiO2–Al2O3 material, and c) it determines the performance difference of the so-purified H0-BT samples and H0-BT samples containing the relevant chloroorganic compounds in the catalytic hydrogenation of H0-BT to H12-BT.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Benzyltoluene; Catalyst poisoning; Chloroorganic compounds; Hydrodechlorination; Hydrogenation; Impurities; LOHC

Chromium catalyzed tetramerization of ethylene in a continuous tube reactor-Proof of concept and kinetic aspects - Kuhlmann, Sven; Paetz, Caspar; Hägele, Christian; Blann, Kevin; Walsh, Richard; Dixon, John T.; Scholz, Judith; Haumann, Marco; Wasserscheid, Peter (Journal of Catalysis, 2009)
Highly selective processes for the tri- and tetramerization of ethylene offer an interesting alternative to conventional ethylene oligomerization processes that are constrained by yielding mathematical distributions of linear α-olefins. This inherent lack of selectivity often makes it difficult for full slate producers to respond to changing market demands in each product segment. This is the first known report on the continuous tri- and tetramerization of ethylene in a continuous plug flow tubular reactor. Standard run times of 10 h and a catalyst comprising Cr(acac), 1,2-dimethylpropyl-bis(diphenylphosphino)amine ligand and the aluminum-based activator MMAO-3A was used. Activities exceeding 3,700,000 g/(g h) and combined selectivities for 1-hexene and 1-octene of more than 90% were achieved. The influence of temperature, catalyst concentration, and ethylene concentration in the reactor on reaction rate (catalyst activity) and selectivity has also been investigated. In addition, supporting kinetic studies were performed in a semi-batch reactor setup with the aim to explain the influence of ethylene concentration on product selectivity found in the continuous runs. It was found that the reaction orders in ethylene for 1-hexene and 1-octene are different, with 1-octene formation being significantly more sensitive to ethylene concentration. © 2008.
Keywords: Chromium; Continuous oligomerization; Ethylene; Homogeneous catalysis; Linear α-olefins

[cis-(1,3-diene) 2W(CO) 2] complexes as MOCVD precursors for the deposition of thin tungsten - Tungsten carbide films - Jipa, Ilona; Heinemann, Frank Wilhelm; Schneider, Andreas; Popovska, Nadejda; Siddiqi, M. Aslam; Siddiqui, Rehan A.; Atakan, B.; Marbach, Hubertus; Papp, Christian; Steinrück, Hans-Peter; Zenneck, Ulrich (Chemical Vapor Deposition, 2010)
Tungsten - tungsten carbide thin films are deposited by metal-organic (MO)CVD on silica-coated silicon wafers using [cis-(1,3-butadiene) W(CO) ] and [cis-(1,3-cyclohexadiene) W(CO) ], respectively, as tunable precursor complexes. The compounds are prepared through photochemical ligand exchange reactions from [W(CO) ] and fully characterized, including X-ray structure determination and detailed differential thermal analysis (DTA)/thermogravimetry (TG) investigations. Gas-phase diffusion coefficients and the vapor pressure of the compounds are calculated. The MOCVD experiments are performed in a vertical cold-wall reactor and the exhaust gas is analyzed by gas chromatography (GC). X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), atomic force microscopy (AFM), and scanning electron microscopy (SEM) measurements are utilized for film characterization. Consequences of the high oxophilicity of freshly formed tungsten surfaces, consecutive surface reactions of the complex ligands, film growth, and film properties are discussed. Inside the layers, tungsten carbide is identified as the main component. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

CO2 as a Viscosity Index Improver for Wind Turbine Oils - Pohrer, Benjamin; Zürcher, Manuel; Westerholt, Antje; Bösmann, Andreas; Siebert, Daniel; Völkl, Johannes; Holweger, Walter; Wehrum, Natalie; Arlt, Wolfgang; Wasserscheid, Peter; Schlücker, Eberhard (Industrial & Engineering Chemistry Research, 2015)
A high viscosity index (VI) is crucial for lubricants in industrial gearboxes exposed to changing load or weather conditions. Especially in the field of wind turbine oil, viscosity indices of 150 or higher are demanded to reduce power losses and ensure reliability at the same time. In this context, the use of dissolved CO2 to improve viscositytemperature behavior has been investigated for task-specific, halogen-free ionic liquids and benchmarked against poly(alpha-olefins). By measuring the viscosity and density of the lubricants with dissolved CO2, it was proven that the VI can be increased significantly, even at moderate pressures. In addition, measurements and simulation on CO2 solubility and studies on corrosion and tribology under CO2 pressure are presented.

CO2 Capture by Novel Supported Ionic Liquid Phase Systems Consisting of Silica Nanoparticles Encapsulating Amine-Functionalized Ionic Liquids. - Romanos, George Em.; Schulz, Peter; Bahlmann, Matthias; Wasserscheid, Peter; Sapalidis, Andreas; Katsaros, Folios K.; Athanasekou, Chrysoula P.; Beltsios, Konstantinos; Kanellopoulos, N. K. (Journal of Physical Chemistry C, 2014)
The authors report novel supported ionic liq. (IL) phase systems, described as "inverse" SILPs, consisting of micron size IL droplets within an envelope of silica nanoparticles. These novel IL-in-air powders, produced by an easily scalable phase inversion process, are stable up to 60°C and 30 bar and are proposed as a means to confront the major drawbacks of conventional SILPs for gas sepn. SILPs are usually formed by filling the channels of nanoporous materials with the IL phase. In case the core space of the pores remains open, such conventional SILPs exhibit lack of gas absorption specificity, while complete pore filling leads to diffusivity that is very low compared with that for corresponding bulk ILs; the latter drop is largely due to the high tortuosity of the pore network of the support. The inverse SILPs prepd. in this work exhibited promising CO2/N2 sepn. performance that had reached the value of 20 at absorption equil. and enhanced CO2 absorption capacity of 1.5-3 mmol g-1 at 1 bar and 40°C. Moreover, the CO2 absorption kinetics were very fast compared with conventional SILP systems and to simultaneous N2 absorption; the CO2/N2 selectivity at the short times of the transient stage of absorption had reached values in excess of 200. [on SciFinder(R)]
Keywords: carbon dioxide capture silica nanoparticle encapsulated ionic liq; nitrogen carbon dioxide sepn supported amine functionalized ionic liq

CO2-hydrogenation to methanol using indium-based catalysts in slurry and fixed-bed reactors - Schühle, Patrick (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)

Coating of Pd/C catalysts with Lewis-acidic ionic liquids and liquid coordination complexes – SCILL induced activity enhancement in arene hydrogenation - Lijewski, Martin; Hogg, James M.; Swadzba-Kwasny, Malgorzata; Wasserscheid, Peter; Haumann, Marco (RSC Advances, 2017)
New solid catalysts with ionic liquid layer (SCILLs) were prepared by the coating of heterogeneous Pd/C catalysts with a thin film of acidic liquid: a known chloroaluminate ionic liquid (IL), [BMIM]Cl/AlCl3, and a recently developed liquid coordination complex (LCC), urea/AlCl3. Both coatings improved the activity of Pd/C catalyst against toluene hydrogenation; at lower temperatures (40 °C) the IL-SCILL performed better, whereas at 80 °C the LCC-SCILL gave higher conversion. A thin film of ionic liquid proved to be sufficient to increase activity, while larger volumes of ionic liquid resulted in a decrease in activity due to pore blocking and hence mass transport limitations. Kinetic investigations in batch mode revealed a zero order with respect to toluene concentration, a first order in hydrogen pressure, and activation energy of 64.7 kJ mol-1 for the Pd/C catalyst. The SCILL catalysts had slightly lower values of 53.1 kJ mol-1 for [BMIM]Cl/AlCl3 and 61.4 kJ mol-1 for urea/AlCl3, respectively.
EAM Import::2019-03-13

Cobalt mixed oxides deposited on the SiC open-cell foams for nitrous oxide decomposition - Klegova, A.; Inayat, A.; Indyka, P.; Gryboś, J.; Sojka, Z.; Pacultová, K.; Schwieger, Wilhelm; Volodarskaja, A.; Kuśtrowski, P.; Rokicińska, A.; Fridrichová, D.; Obalová, L. (Applied Catalysis B-Environmental, 2019)
Supported Co3O4 and Co4MnAlOx mixed oxides were prepared by deposition on the SiC open-cell foams by wet impregnation and suspension methods and characterized by AAS, BET, XRD, SEM, TEM, TPR-H2, XPS and nitrogen adsorption methods. Prepared supported catalysts as well as active phase Co3O4 and Co4MnAlOx in grain form prepared from parent solutions were tested for nitrous oxide decomposition. Catalytic activity of grain active phase was governed by methods of preparation; Co3O4 and Co4MnAlOx prepared by suspension method were significantly more active than those from solutions for impregnation method. Suspension method provided active phase with higher surface areas and sites with better reducibility, both of these factors contributed to higher N2O conversions. In contrast to this, N2O conversions over supported catalysts were dependent more on chemical composition of active phase than on method of preparation. Both catalysts containing Co4MnAlOx mixed oxide revealed higher conversion of N2O than catalysts containing Co3O4. STEM analysis of the most active Co4MnAlOx prepared by suspension method showed (i) segregation of Co3O4 nanocrystals of cuboctahedral shape containing (100) and (111) facets (this segregation was confirmed also by XPS and TPR-H2) and (ii) Co-Mn-Al oxide nanoparticles with very small un-faceted grains assembled into elongated fiber-like agglomerates were observed by STEM.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Cobalt mixed oxide; N; Open-cell foam; SiC; Supported catalyst

Coke Formation during Propane Dehydrogenation over Ga−Rh Supported Catalytically Active Liquid Metal Solutions - Wolf, Moritz; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2020)
Supported Catalytically Active Liquid Metal Solutions (SCALMS) were recently described as a new class of heterogeneous catalysts, where the catalytic transformation takes place at the highly dynamic interface of a liquid alloy. Their application in alkane dehydrogenation has been claimed to be superior to classical heterogeneous catalysts, because the single atom nature of Rh dissolved in liquid Ga hinders the formation of significant amounts of coke, e. g. by oligomerisation of carbon fragments and excessive dehydrogenation. In the present study, we investigate the coking behaviour of Ga−Rh SCALMS during dehydrogenation of propane in detail by means of high-resolution thermogravimetry. We report that the application of Ga−Rh SCALMS indeed limits the formation of coke when compared to the Ga-free Rh catalyst, in particular when relating coke formation to the catalytic performance. Furthermore, the formed coke has been shown to be highly reactive during temperature programmed oxidation in 21 % O2/He with onset temperatures of approx. 150 °C enabling a regeneration of the Ga−Rh SCALMS system under mild conditions. The activation energy of the oxidation lies in the lower range of values reported for spent cracking catalysts. Monitoring the formation of coke and performance of SCALMS in situ via thermogravimetry coupled with mass spectrometry revealed the continuous formation of coke, which becomes the only process affecting the net weight change after a certain time on stream.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Coke; Dehydrogenation; Gallium; SCALMS; TPO

Combined dynamic operation of PEM fuel cell and continuous dehydrogenation of perhydro-dibenzyltoluene - Geiling, Johannes; Steinberger, Michael; Ortner, Florian; Seyfried, Roman; Nuss, Andreas; Uhrig, Felix; Lange, Christopher; Oschsner, Richard; Wasserscheid, Peter; März, Martin; Preuster, Patrick (International Journal of Hydrogen Energy, 2021)
Hydrogen storage in liquid organic hydrogen carriers (LOHC) such as the substance system dibenzyltoluene/perhydro-dibenzyltoluene (H0/H18-DBT) offers a promising alternative to conventional methods. In this contribution, we describe the successful demonstration of the dynamic combined operation of a continuously operated LOHC reactor and a PEM (polymer exchange membrane) fuel cell. The fuel cell was operated stable with fluctuating hydrogen release from dehydrogenation of H18-DBT over a total period of 4.5 h, reaching electrical stack powers of 6.6 kW. The contamination with hydrocarbons contained in the hydrogen after activated carbon filtering did not result in any detectable impairment or degradation of the fuel cell. The proposed pressure control algorithm based on a proportional integral (PI) controller proved to be a robust and easy-to-implement approach to enable the dynamic combined operation of LOHC dehydrogenation and PEM fuel cell.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Control algorithm; Dynamic operation; Hydrogen purification; Hydrogen storage; LOHC; PEM fuel cell

Combining autoclave and LCWM reactor studies to shed light on the kinetics of glucose oxidation catalyzed by doped molybdenum-based heteropoly acids - Voß, Dorothea; Ponce, Sebastian; Wesinger, Stefanie; Etzold, Bastian J.M.; Albert, Jakob (RSC Advances, 2019)
In this work we combined kinetic studies for aqueous-phase glucose oxidation in a high-pressure autoclave setup with catalyst reoxidation studies in a liquid-core waveguide membrane reactor. Hereby, we investigated the influence of Nb- and Ta-doping on Mo-based Keggin-polyoxometalates for both reaction steps independently. Most importantly, we could demonstrate a significant increase of glucose oxidation kinetics by Ta- and especially Nb-doping by factors of 1.1 and 1.5 compared to the classical HPA-Mo. Moreover, activation energies for the substrate oxidation step could be significantly reduced from around 80 kJ mol-1 for the classical HPA-Mo to 61 kJ mol-1 for the Ta- and 55 kJ mol-1 for the Nb-doped species, respectively. Regarding catalyst reoxidation kinetics, the doping did not show significant differences between the different catalysts.
CRIS-Team Scopus Importer:2019-10-01

Combining cost-efficient biomass fractionation and selective biomass oxidation to formic acid - the new POM-ionosolv concept - Bukowski, Anna; Rafat Said, Aida; Brandt-Talbot, Agi; Albert, Jakob (ChemPlusChem, 2020)

Comparative evaluation of heat transfer correlations with different fluid property considerations for fixed-bed reactor modeling - Pietschak, Alexander; Maußner, Johannes; Dixon, Anthony G.; Freund, Hannsjörg (International Journal of Heat and Mass Transfer, 2020)
Catalytic fixed-bed reactors are well established and frequently used in the chemical industry. Full-scale catalytic fixed-bed reactors are commonly described via pseudo-homogeneous continuum models. The heat transfer is accounted for by correlations that have been predominately fitted under the assumption of constant fluid properties. As a result of chemical reactions taking place, the fluid composition and the temperature in the fixed-bed depend on the spatial position. The resulting system specific non-uniformity of the fluid properties should be taken into account during modeling. The effect of different approaches to consider the fluid properties in the bed on the predictive performance of selected heat transfer correlations is evaluated on a broad range of experimental heat transfer data obtained from the literature. Correlations from both the αw- and the λr(r)-heat transfer models were selected. Although the selected correlations have been fitted under the assumption of constant fluid properties, the predictive performance was improved for all correlations if radial and axial variations of the fluid properties were taken into account. The impact on the resulting temperature field is illustrated based on a case study. In addition, the predictive performances of the selected heat transfer correlations are compared to one another over a broad range of tube-to-particle diameter ratios and Reynolds numbers. A clear superiority of the λr(r)-correlation proposed by Winterberg et al. was identified.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Catalytic fixed-bed; Fixed-bed reactor simulation; Fluid properties; Heat transfer; Model evaluation; Pseudo-homogeneous models

Comparing Different Synthesis Procedures for Carbide-Derived Carbon-Based Structured Catalyst Supports - Knorr, Tilman; Schwarz, Aaron; Etzold, Bastian (Chemical Engineering & Technology, 2014)
Different approaches were analyzed to combine the tuneable micropore structure of carbide-derived carbons with a foam-like secondary porosity. The resulting structured catalyst supports were characterized in detail and applied in the model reaction of ethene hydrogenation. Preparation methods studied were dip-coating using polytetrafluoroethylene as binder on cellular metal structures, a chemical vapor deposition coating of the metal structures with thin carbide layers and subsequent conversion to carbide-derived carbon, and the partial or full conversion of carbide foams to carbon/carbide composites. For the binder method, optimal parameters for stable slurry preparation as well as for calcination of the slurry were obtained. It could further be demonstrated that the conversion of carbide foams into carbon/carbide composites leads to an appreciation between decreasing mechanical strength and increasing specific surface area.
EAM Import::2019-03-13

Comparison between phosphine and NHC-modified Pd catalysts in the telomerization of butadiene with methanol - A kinetic study combined with model-based experimental analysis - Völkl, Lisa; Recker, Sebastian; Niedermaier, Matthias; Kiermaier, Stephan; Strobel, Vinzent; Maschmeyer, Dietrich; Cole-Hamilton, David; Marquardt, Wolfgang; Wasserscheid, Peter; Haumann, Marco (Journal of Catalysis, 2015)
The telomerization of butadiene with methanol was investigated in the presence of different palladium catalysts modified either with triphenylphosphine (TPP) or 1,3-dimesityl-imidazol-2-ylidene (IMes) ligand. When pure butadiene was used as substrate, a moderate selectivity for the Pd-TPP catalyst toward the desired product 1-methoxy-2,7-octadiene (1-Mode) of around 87% was obtained, while the IMes carbene ligand almost exclusively formed 1-Mode with 97.5% selectivity. The selectivity remained unchanged when the pure butadiene feed was replaced by synthetic crack-C-4 (sCC(4)), a technical feed of 45 mol% butadiene and 55 mol% inerts (butenes and butanes). The TPP-modified catalyst showed a lower reaction rate, which was attributed to the expected dilution effect caused by the inerts. Surprisingly, the IMes-modified catalyst showed a higher rate with sCC(4) compared to the pure feed. By means of a model-based experimental analysis, kinetic rate equations could be derived. The kinetic modeling supports the assumption that the two catalyst systems follow different kinetic rate equations. For the Pd-TPP catalyst, the reaction kinetics were related to the Jolly mechanism. In contrast, the Jolly mechanism had to be adapted for the Pd-IMes catalyst as the impact of the base seems to differ strongly from that for the Pd-TPP catalyst. The Pd-IMes system was found to be zero order in butadiene at moderate to high butadiene concentrations and first order in base while the nucleophilicity of the base is influenced by the methanol amount resulting in a negative reaction order for methanol. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Telomerization; NHC ligand; TPP ligand; Palladium; Reaction kinetics; Model-based kinetic analysis

Competition of Acetone Reduction and Hydrogen Evolution on Pt Single Crystal Electrodes in the Absence and Presence of the Ionic Liquid [C2C1Im][OTf] - Kastenmeier, Maximilian; Franz, Evanie; Waidhas, Fabian; Yang, Tian; Taccardi, Nicola; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2023)
In heterogeneous catalysis, ionic liquids (ILs) are used as chemical modifiers to control selectivity. In our work, we aim to apply the same concept to electrocatalytic systems. We studied two competing reactions on low index platinum (111), (100), and (110) single crystal electrodes, namely, the hydrogen evolution reaction (HER) and the acetone reduction reaction. We used the IL [C2C1Im][OTf] dissolved in the supporting electrolyte (0.1 M HClO4) as chemical modifier. In our study, we combined cyclic voltammetry (CV), electrochemical infrared reflection absorption spectroscopy (EC-IRRAS), and differential electrochemical mass spectrometry (DEMS). On all three surfaces, the HER is the predominant reaction at potentials below 0.00 VRHE. While Pt(100) and Pt(111) show no or very low activity toward the reduction of acetone, the Pt(110) surface is active for this reaction in a potential window between 0.08 and 0.00 VRHE. We identified propane to be the main product of acetone reduction. Additionally, we observed the formation of adsorbed COads. In the presence of low concentrations of the IL (0.001 M), acetone reduction is fully suppressed and the activity for HER increases. We assign these effects to the specific adsorption of the IL, which blocks the adsorption sites for sterically more demanding acetone, while the coadsorbate layer remains permeable for the sterically less demanding hydrogen formation. Our results illustrate the potential of ionic liquids to act as molecular filters, which block a specific reaction channel.
CRIS-Team Scopus Importer:2023-12-15

Complementary Mass Transport Investigations in Open-Cell Foams: Full-Field Computational Fluid Dynamics Simulation with Random-Walk Microscopic Particle Tracking and Methane Nuclear Magnetic Resonance Displacement Measurements - Sadeghi, Mehrdad; Brix, Andreas; Trunk, Sebastian; Pesch, Georg R.; Freund, Hannsjörg; Thöming, Jorg (Transport in Porous Media, 2024)
Numerical simulation can provide detailed understanding of mass transport within complex structures. For this purpose, numerical tools are required that can resolve the complex morphology and consider the contribution of both convection and diffusion. Solving the Navier–Stokes equations alone, however, neglects self-diffusion. This influences the simulated displacement distribution of flow especially in porous media at low Péclet numbers (Pe < 16) and in near-wall regions where diffusion is the dominant mechanism. To address this problem, this study uses μCT-based computational fluid dynamics (CFD) simulations in OpenFOAM coupled with the random-walk particle tracking (PT) module disTrackFoam and cross-validated experimentally using pulsed-field gradient (PFG) nuclear magnetic resonance (NMR) measurements of gas flow within open-cell foams (OCFs). The results of the multi-scale simulations—with a resolution of 130–190 µm—and experimental PFG NMR data are compared in terms of diffusion propagators, which are microscopic displacement distributions of gas flows in OCFs during certain observation times. Four different flow rates with Péclet numbers in the range of 0.7–16 are studied in the laminar flow regime within 10 and 20 PPI OCFs, and axial dispersion coefficients were calculated. Cross-validation of PFG NMR measurements and CFD-PT simulations revealed a very good matching with integral differences below 0.04%, underpinning the capability of both complementary methods for multi-scale transport analysis.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Cross-validation; Diffusion propagator; Dispersion coefficient; disTrackFOAM; Near-wall diffusion; Pore-scale CFD simulations; Pulsed-field gradient NMR; Self-diffusion

Complementary Molecular Dynamics and X-ray Reflectivity Study of an Imidazolium-Based Ionic Liquid at a Neutral Sapphire Interface - Brkljaca, Zlatko; Klimczak, Michael; Milicevic, Zoran; Weißer, Matthias; Taccardi, Nicola; Wasserscheid, Peter; Smith, David M.; Magerl, Andreas; Smith, Ana-Suncana (Journal of Physical Chemistry Letters, 2015)
Understanding the molecular-level behavior of ionic liquids (ILs) at IL–solid interfaces is of fundamental importance with respect to their application in, for example, electrochemical systems and electronic devices. Using a model system, consisting of an imidazolium-based IL ([C2Mim][NTf2]) in contact with a sapphire substrate, we have approached this problem using a complementary combination of high-resolution X-ray reflectivity measurements and atomistic molecular dynamics (MD) simulations. Our strategy enabled us to compare experimental and theoretically calculated reflectivities in a direct manner, thereby critically assessing the applicability of several force-field variants. On the other hand, using the best-matching MD description, we are able to describe the nature of the model IL–solid interface in appreciable detail. More specifically, we find that characteristic interactions between the surface hydroxyl groups and donor and acceptor sites on the IL constituents have a dominant role in inducing a multidimensional layering profile of the cations and anions.

Comprehensive thermodynamic study of substituted indoles/perhydro indoles as potential liquid organic hydrogen carrier system - Safronov, Sergey P.; Vostrikov, Sergey V.; Samarov, Artemiy A.; Wasserscheid, Peter; Müller, Karsten; Verevkin, Sergey P. (Fuel, 2023)
Indole has been proposed as a Liquid Organic Hydrogen Carrier (LOHC) component. Its hydrogenation leads to octahydro indole, which can subsequently release hydrogen again in an endothermic, catalytic dehydrogenation reaction. This reaction requires high temperatures due to limitations by the reaction equilibrium. It is therefore interesting to find derivatives of the carrier molecules with lower enthalpies of reaction, which corresponds to a higher equilibrium constant. In this study, methyl and phenyl substituted derivatives of indole have been examined. Vapor pressures and enthalpies of vaporisation/sublimation have been measured. The standard molar enthalpies of formation in the gas phase have been calculated using quantum chemistry. The liquid phase standard molar enthalpies of formation were derived and used for calculating reaction enthalpies. The results show that methylation lowers the enthalpy of reaction for dehydrogenation. The reduction is not very pronounced in case of single methylation (up to 3.1 kJ mol−1/H2), but can be increased by manifold methylation (e.g. 4.6 kJ mol−1/H2 in case of 2,3-dimethyl-H8-indole). Substitution of indole with a phenyl group leads to a corresponding hydrogenated counterpart, that can only be dehydrogenated partially under mild conditions. This is due to the fact that the reducing effect of the nitrogen atom on enthalpy of reaction is only effective in the indole system itself, while the cyclohexyl ring has similar dehydrogenation properties to homocyclic LOHCs.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Enthalpy of formation; Enthalpy of vaporisation; Indole derivatives; LOHC; Quantum-chemical calculations; Vapour pressure measurements

Concentration of apple juice using CO(2 )gas hydrate technology to higher sugar contents - Claßen, Timo; Jäger, Michael; Loekman, Soebiakto; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Innovative Food Science & Emerging Technologies, 2020)
This paper describes the application of CO2-hydrate technology for the concentration of apple juice towards industrially relevant levels. Assays were carried out in a stirred autoclave at 1-2 degrees C and 35 bars with rediluted apple concentrate in the range of 11 degrees Bx to 40 degrees Bx. A hydraulic pellet press was used to separate the hydrate from the concentrate, resulting in an almost complete sugar recovery. It was found that apple juice can be concentrated to 45 degrees Bx and beyond using this technique. Maximum hydrate conversion of up to 30% was achieved at an average concentration rate of 2.5-3 degrees Bx/h. Furthermore, an optimal juice to crystallizer volume ratio of 35% was found. The investigations also revealed the juice composition to interfere with the hydrate formation process to some extend. In the assays with constant water content, no decrease in the hydrate formation rate was observed until 30 degrees Bx. From this concentration onwards, however, the hydrate yield decreased steadily and amounted to only 15% M 40 degrees Bx.
CRIS-Team WoS Importer:2020-09-25

Continuous catalytic Friedel-Crafts acylation in the biphasic medium of an ionic liquid and supercritical carbon dioxide. - Zayed, Firas; Greiner, Lasse; Schulz, Peter; Lapkin, Alexei; Leitner, Walter (Chemical Communications, 2008)
Immobilization of catalytically-active metal salts in ionic liqs., with extn. by supercrit. carbon dioxide, affords continuous Friedel-Crafts acylation, with in situ-recycling of the catalyst. [on SciFinder(R
Keywords: acylation catalyst recycling supercrit carbon dioxide ionic liq

Continuous gas-phase desulfurisation using supported ionic liquid phase (SILP) materials - Kohler, Florian; Roth, Daniel; Kuhlmann, Esther; Wasserscheid, Peter; Haumann, Marco (Green Chemistry, 2010)
Supported ionic liquid phase (SILP) materials have been developed for a continuous gas cleaning process. The technology is exemplified for the desulfurisation of a model gas stream consisting of 500 ppmwtn-butyl mercaptan in n-heptane vapour to levels of mercaptan below 5 ppmwt. By varying the ionic liquid structure, acidity and loading, [C12MIM]Cl/SnCl2 (XSnCl2 = 0.50) on alumina in an ionic liquid loading of 20 vol% of the support's pore volume was identified as a particularly suitable gas sorption system. Breakthrough experiments demonstrate desulfurisation performance of up to 130 h time-on-stream, and the suitability of the system for loading/unloading cycles in a pressure and temperature swing operation mode.

Continuous Gas-Phase Hydroaminomethylation using Supported Ionic Liquid Phase Catalysts - Schneider, Martin; Lijewski, Martin; Woelfel, Rene; Haumann, Marco; Wasserscheid, Peter (Angewandte Chemie International Edition, 2013)
Keywords: amine formation; hydroaminomethylation; hydroformylation; ionic liquids; supported catalysts

Continuous Gas-Phase Hydroformylation of a Highly Diluted Technical C4 Feed using Supported Ionic Liquid Phase Catalysts - Haumann, Marco; Jakuttis, Michael; Franke, Robert; Schönweiz, Andreas; Wasserscheid, Peter (ChemCatChem, 2011)
The concept of supported ionic liquid phase (SILP) catalysis has been established in recent years by our group and others. Its application in continuous catalytic gas-phase processes provides a very attractive way to bridge the gap between homogeneous and heterogeneous catalysis. In this contribution, we extend SILP hydroformylation catalysis to reactions with a highly diluted, technical C4 feed containing 1.5 % 1-butene, 28.5 % 2-butenes, and 70 % of inert n-butane. To obtain the desired product, n-pentanal, the Rh-biphephos catalyst system was immobilized in the SILP system to allow for consecutive isomerization/hydroformylation activity. The resulting SILP catalyst material converted up to 81 % of the reactive butenes, with a residence time of 155s in the reactor. An n-pentanal selectivity greater than 92% was realized for more than 500h time-on-stream in the continuous gas-phase reaction. Post-reaction NMR studies revealed no significant loss of the phosphite ligand through ligand oxidation during the reaction.

Continuous gas-phase hydroformylation of but-1-ene in a membrane reactor by supported liquid-phase (SLP) catalysis - Logemann, Morten; Marinkovic, Jakob Maximilian; Schörner, Markus; Garcia-Suarez, Eduardo Jose; Hecht, Corinna; Franke, Robert; Wessling, Matthias; Riisager, Anders; Fehrmann, Rasmus; Haumann, Marco (Green Chemistry, 2020)
Process intensification is a cornerstone to achieve a significant reduction in energy consumption and CO(2)emissions in the chemical industry. In this context, a monolithic membrane reactor combining homogeneous catalytic gas-phase hydroformylation of but-1-ene within situproduct removal is here presented. The homogeneous supported ionic liquid-phase (SILP) catalyst consists of a Rh-biphephos complex dissolved in 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C(2)C(1)Im][NTf2] and immobilized on a mesoporous silicon carbide monolith. The resulting monolith is catalytically active and selective towards linear aldehyde formation, but the accumulation of aldehyde products and high boilers in the ionic liquid leads to slow catalyst deactivation. This accumulation is suppressed when bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate is used as alternative solvent, where only marginal aldehyde accumulation and aldol formation occur. A polydimethylsiloxane (PDMS) membrane coating of the monolith increases the aldehyde-alkene ratio by an enrichment factor of 2.2 in the permeate gas compared to the retentate gas from the reactor simplifying further downstream processing. The monolithic membrane reactor loaded with SILP or SLP catalysts presents a scalable, versatile platform to achieve process intensification for diverse hydroformylation reactions as well as related gas-phase reactions.
CRIS-Team WoS Importer:2020-09-18

Continuous gas-phase isopropylation of toluene and cumene using highly acidic Supported Ionic Liquid Phase (SILP) catalysts - Joni, Joni; Haumann, Marco; Wasserscheid, Peter (Applied Catalysis A-General, 2010)
Continuous gas-phase Friedel-Crafts isopropylation of toluene and cumene has been investigated using acidic Supported Ionic Liquid Phase (SILP) materials as the catalyst. Detailed kinetic studies in a multi-stage tubular reactor revealed that reactant's water content and the aromatic-to-alkene ratio are the most relevant influencing factors for the catalyst stability and selectivity in these reactions. Based on this insight, our process optimization led to the first highly stable, highly active and selective SILP-type acidic catalyst system for gas-phase aromatic alkylation. We anticipate that this concept offers great potential for more sustainable Friedel-Crafts alkylation processes.

Continuous Gas-Phase Synthesis of Oxymethylene Dimethyl Ethers Using Supported Ionic Liquid Phase Catalysts - Aubermann, Manfred; Haumann, Marco; Wisser, Dorothea; Wasserscheid, Peter (ACS Sustainable Chemistry & Engineering, 2022)
Acidic supported ionic liquid phase catalysts were investigated for the synthesis of oxymethylene dimethyl ethers (OMEs). The application of OME1 and trioxane for the gas-phase synthesis of higher OMEs and in particular the generation of OMEn with n higher than 3 was successfully demonstrated. Raising the pressure led to an increase in the conversion of OME1 and to higher selectivity for higher molecular weight OMEs. Furthermore, a correlation between the ionic liquid's acidity and the catalytic activity was shown with higher acidity leading to higher conversion of trioxane and OME1. Moreover, successful long-term operation for more than 200 h time on stream has been demonstrated with good catalyst system stability.
CRIS-Team Scopus Importer:2022-06-17
Keywords: acid catalysis; continuous process; immobilization; oligomerization; supported ionic liquids

Continuous Purification of Gases Using SILP Materials - Klefer, Heiko; Roth, Daniel; Eckle, Ilsebill; Schrage, Christian; Böhringer, Bertram; Haumann, Marco; Wasserscheid, Peter (Chemie Ingenieur Technik, 2014)
Supported ionic liquid phase (SILP) materials consist of a porous solid that is coated with a thin film of an ionic liquid. The application of such hybrid materials in adsorptive gas cleaning processes is described using own experiments and recent literature. Examples using metal oxides and spherical carbon adsorbents as supports are discussed and the application of SILP materials in foam structures is presented. SILP materials benefit in adsorption processes in a particular manner from the special properties of ionic liquids. Using the liquid salt in an immobilized form allows for a large gas-liquid exchange area and a very high degree of ionic liquid utilization.
Keywords: Adsorption; Foam structure; Gas cleaning; Ionic liquid; Porous materials; Pressure drop

Continuous Transesterification with Acidic Ionic Liquids as Homogeneous Catalysts. - Kuschnerow, Jan C.; Titze-Frech, Karin; Schulz, Peter; Wasserscheid, Peter; Scholl, Stephan (Chemical Engineering & Technology, 2013)
Ionic liqs. (ILs) are recyclable acid catalysts for transesterification reactions. In the present study, different acidic ILs were examd. in this reaction, with special focus on their recyclability. Furthermore, the IL-catalyzed transesterification reaction was realized in continuous operation. A miniplant reactor with tech. representative design and operating characteristics was used for this study. The applied rig has a vol. of 5 L and an external thermosyphon reboiler. The miniplant reactor can be operated in batch and in continuous mode. ILs functionalized with a sulfonic acid group were found to be the most suitable IL catalysts for the transesterification reactions under investigation. Using these ILs, reaction rates as high as for H2SO4 could be realized. Moreover, the IL catalyst was demonstrated to be active for at least 1000 h of operation time. [on SciFinder(R)]
Keywords: transesterification acidic ionic liq homogeneous catalyst

Controlled doping of carbon catalyst supports by atomic replacement via gasification-assisted heteroatom doping - Herold, Felix; Imhof, Timo; Roumeliotis, Paul; Schühle, Patrick; Ledendecker, Marc; Rønning, Magnus (Carbon, 2023)
Due to a set of unique properties, carbon materials are applied as supports for metal-based catalysts in a wide variety of established and emerging (electro-)catalytical transformations. By introducing heteroatoms such as N, S and P into carbon supports, metal-support interactions can be tuned, enabling an optimization of catalyst performance in terms of activity, selectivity and stability. However, the exact impact of carbon heteroatom doping on catalyst performance remains often poorly understood, as the effects are inseparable from the clustered influence of other support properties such as texture and nanostructure. In this context, we present gasification-assisted heteroatom doping (GAHD) as a novel, broadly applicable post synthesis approach to exchange carbon surface atoms against heteroatoms while retaining the properties of the parental carbon. Employing GAHD, N, S and P doping of carbons with widely varying properties could be achieved, allowing, for example, incorporation of up to 13.1 wt-% S into an activated carbon at a change of specific surface area of only 4.4%. As a proof-of-concept, comparable N, S and P doped carbon nanofiber supports were used to prepare Pt-based electrocatalysts for the oxygen reduction reaction and probe the influence of the heteroatom dopants on their stability by accelerated stress tests in different potential regimes. In this context, P and S doped supports were found to exhibit a high degree of interaction with Pt, providing increased degradation resistance compared to N and non-doped support.
CRIS-Team Scopus Importer:2023-03-24

Controlled synthesis of core-shell carbide-derived carbons through in situ generated chlorine - Ariyanto, Teguh; Zhang, Guirong; Riyahi, Farshad; Gläsel, Jan-Sebastian; Etzold, Bastian (Carbon, 2017)
Core-shell porous carbon represents an innovative concept for optimizing performances of carbon materials in a wide range application. Here, a novel route to produce carbons with spatially varying pore and microstructure is presented. Following the carbide-derived carbon method, a homogeneous and adjustable shell generation is achieved through mixing a limited amount of solid chlorine precursors with titanium carbide raw material. Chlorine is released in situ when reaching approx. 600 °C and consumed subsequently directly, resulting in the aspired materials. Various characterization methods proved that the amount of solid chlorine precursor directly adjusts the share of the shell for the core-shell material, while a range of 5–80% was studied. The amorphous, microporous shell can be converted to a mesoporous and graphitic shell (crystal sizes 20 nm), through a subsequent vacuum annealing, allowing to control the properties of the carbon shell. The carbon core results after a subsequent second chlorination step, where directly gaseous chlorine is used. The materials were characterized in detail after every step of this novel route. Adjusting the share between mesoporous/graphitic shell and microporous/amorphous core for these new materials is of interest in applications where competing processes like mass transfer and surface interaction need to be optimized.
CRIS-Team Scopus Importer:2023-08-15

CO Permeability and Wetting Behavior of Ionic Liquids on Pt(111): An IRAS and PM-IRAS Study from Ultrahigh Vacuum to Ambient Pressure - Blaumeiser, Dominik; Schuschke, Christian; Fromm, Lukas; Taccardi, Nicola; Schötz, Simon; Eschenbacher, Roman; Bühlmeyer, Hanna; Xu, Tao; Bauer, Tanja; Wasserscheid, Peter; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2021)
Solid catalysts with ionic liquid layers (SCILLs) show improved performance as compared to ionic liquid (IL)-free catalysts. To realize the beneficial IL-induced modification, the IL layer should be stable under reaction conditions but also permeable for gaseous reactants entering through the IL phase. Herein, we applied (polarization modulation-) infrared reflection absorption spectroscopy ((PM-)IRAS) to investigate the CO permeability of model SCILL systems. We investigated three different IL model systems prepared by physical vapor deposition (PVD) in ultrahigh vacuum (UHV) on atomically clean Pt(111), namely, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([C4C1Pyr][NTf2]), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2C1Im][NTf2]), and 1-butyl-1-methylpyrrolidinium trifluoromethanesulfonate ([C4C1Pyr][OTf]). The adsorption geometries of the anions depend on the surface structure, IL coverage, and precoverage of CO. At room temperature, IL multilayers of randomly oriented species grow on top of strongly adsorbed wetting layers. Upon heating, a partial wetting transition induces the coexistence of an IL wetting monolayer film with three-dimensional droplets. Gas-phase CO does not permeate through IL multilayers, while it penetrates the IL wetting monolayer leading to mixed IL/CO films. The partial dewetting transition and the permeability differ drastically with the temperature and IL. Consequently, the morphology of the IL films could be a factor that determines the catalytic behavior of SCILLs to a significant extent.
CRIS-Team Scopus Importer:2021-08-06

Correlating Gasoline Spray Propagation in Constant Volume Chamber and Optically Accessible Engines - Welß, Richard; Seeger, Jan; Deinhard, Bianca; Wensing, Michael (COMODIA 2017 Int. Conference, 2017)

Correlative 3D characterization of hierarchical zeolite structures linking nano X-ray tomography and 360° electron tomography - Drobek, Dominik; Apeleo Zubiri, Benjamin; Wirth, Janis; Englisch, Silvan; Weissenberger, Tobias; Schwieger, Wilhelm; Spiecker, Erdmann (European Microscopy Congress 2020, 2021)
In catalysis, the available total surface area for active sites is of utmost importance and the intraparticle pore space of a single particle has to be designed accordingly. In addition, the interparticle pore space, determining the packing density of a particle network, is also critical for catalytic applications. MFI-type zeolite particles exhibit such a structured pore system and can serve as support frameworks for catalytic applications. Applying multiscale Nano-X-ray tomography (Nano-CT) and 360° electron tomography (ET) reveals the complex morphology of a single MFI-type zeolite particle and even larger agglomerations of these particles can be analyzed in detail [1].
Keywords: 360° electron tomography; 3D; correlative microscopy; hierarchial material; nano X-ray tomography

Correlative 3D-Characterization of Liquid Metal Catalysts (LMC) utilizing X-ray and Analytical Electron Microscopy - Wirth, Janis; Englisch, Silvan; Wiktor, Christian; Taccardi, Nicola; Wasserscheid, Peter; Spiecker, Erdmann (Microscopy & Microanalysis 2018, 2018)
X-ray microscopy (XRM) allows non-destructive 3D investigations of materials across multiple length scales. At the University of Erlangen-Nürnberg a high-resolution XRM/NanoCT instrument (ZEISS Xradia 810 Ultra) has been recently installed and put into operation. The instrument uses Fresnel zone plate optics to achieve 3D resolutions down to 50 nm and can be equipped with a Zernike phase ring enabling phase contrast in addition to standard absorption contrast imaging. While the latter is well suited to image materials containing regions of sufficiently different densities the former can be employed to study weakly absorbing materials and to discriminate materials exhibiting similar densities. Due to the high resolution capabilities and flexible contrast the ZEISS Xradia 810 Ultra can be combined with Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) techniques for correlative 3D studies of functional materials. In this contribution we report correlative 3D studies of Pd-Ga liquid metal catalysts which have been recently shown outstanding performance in alkane dehydrogenation and, in particular, high resistance against coking [1]. Such liquid metal catalysts exhibit a complex material structure featuring a molecularly defined, catalytically active liquid film/droplet layer adsorbed on meso- or macroporous silica. High-resolution 3D characterization across different length scales is required to gain deeper insight into the structure and microscopic mechanisms of the catalyst system. SEM imaging (Fig. 1a) and corresponding Energy- Dispersive X-ray Spectroscopy (EDXS) analysis (not shown) reveal the presence of larger Ga-rich particles on the surface of the porous silica but do not allow to clarify to which extend Ga and Pd is incorporated in the bulk of the porous network. By combining absorption and phase contrast imaging in the XRM the metal droplets and the macroporous silica network can be independently resolved. Tomographic reconstruction enables non-destructive characterization of the 3D distribution of metal droplets in the porous network structure (Fig. 1b). In order to study the composition of individual metal droplets inside the porous network site-specific sample preparation has to be combined with high-resolution analytical TEM techniques. Fig. 1c) exemplarily shows a Scanning Transmission Electron Microscopy (STEM) image of a mesoporous silica network containing a single Pd-Ga particle. The corresponding EDXS mapping clearly shows that the particle has a bimetallic structure with Pd-rich and Ga-rich parts occurring in direct contact to each other. Currently, we perform in situ TEM experiments in order to reveal phase transformations and melting behavior of such bimetallic particles upon heating to typical process temperatures of 500 °C

Correlative 3D nanotomography and in situ transmission electron microscopy studies on supported catalytically active liquid metal solutions - Wirth, Janis; Apeleo Zubiri, Benjamin; Wu, Mingjian; Englisch, Silvan; Drobek, Dominik; Taccardi, Nicola; Wasserscheid, Peter; Spiecker, Erdmann (European Microscopy Congress 2020, 2021)
Liquid metal catalysts (LMC) are intermetallic compounds of low-melting main group elements (e.g. Ga, In) with a small percentage of catalytically active transition metal elements (e.g. Pt, Pd, Rh). These compounds possess complex intermetallic phases in solid state and become highly dynamic in liquid form. Liquid metal solutions show a superior activity, robust performance and selectivity in dehydrogenation reactions [1]. At typical process temperatures around 500°C, it is conceivable that the large surface/volume ratio of nanodroplets, supported in the open meso-/macroporous scaffold, provide a huge number of active sites, which are intrinsically robust to coke formation and degradation due to the highly dynamic nature of the liquid metal alloy. Therefore, structural information including phase stability, local composition and wetting behavior of the nanoalloys inside/on the scaffold as well as the degradation behavior are indispensable to capture the full picture of the catalytic performance. Such microscopic insights are hardly accessible with macroscopic catalytic tests and require a combination of surface science, scattering and high-resolution imaging/analytical techniques, if possible, in situ, in operando or in conditions close to it [2]. In this study, we applied analytical and in situ transmission electron microscopy (TEM) in combination with correlative tomography techniques to contribute to a comprehensive characterization of LMC systems. This is required to unravel the complex pore morphology and the spatial distribution and composition of individual alloy droplets containing the catalytically active sites and, furthermore, to reveal and understand microscopic changes occurring at realistic catalytic process temperatures. Firstly, we report on a correlative three-dimensional (3D) characterization across different length scales of Pd-Ga supported catalytically active liquid metal solutions (SCALMS), which exhibit a complex material structure featuring a molecularly defined, catalytically active liquid droplet layer adsorbed on macroporous silica templates. X-ray nanotomography (Nano-CT) allows non-destructive 3D investigations of materials across multiple length scales. The ZEISS Xradia 810 Ultra laboratory instrument uses Fresnel zone plate optics to achieve 3D resolutions down to 50 nm and can be equipped with a Zernike phase ring enabling phase contrast imaging, which is beneficial to study weakly absorbing materials and porous structures. We used phase contrast Nano-CT large-field of view (LFOV) and multiple region-of-interest (ROI) high-resolution (HR) imaging mode to reconstruct the macroporous silica support and, at the same time, the positions of larger Pd-Ga droplets inside a LMC sample (Figure 1). Figure 1c shows evenly distributed droplets inside the scaffold, which is important for a uniform catalytic performance. For correlative 3D studies at higher resolution using 360° electron tomography (ET), we prepared a pillar sample via focused ion beam (FIB) milling out of the Nano-CT sample (Figure 2a). We used a Fischione model 2050 on-axis rotation tomography holder inside a FEI Titan Themis 300 transmission electron microscope to acquire tilt series of projections with a 180° tilt-angle range to investigate the spatial distribution of Pd and Ga inside the porous silica network at higher resolution (Figure 2). Complementary selected area electron diffraction (SAED) and scanning TEM (STEM) energy-dispersive X-ray spectroscopy (EDXS) enable to distinguish between Ga- and Pd-rich phases (Figure 2b). Both Nano-CT and 360° ET allow investigating the pore interconnectivity and the pore size distribution by applying the maximum sphere inscription (MSI) algorithm [3] to the 3D reconstructions (Figure 2c,d). A precise knowledge of these parameters are of utmost importance since they highly influence the gas diffusion properties in porous catalyst supports. In addition to scale-bridging 3D analyses of the porous network and the position of the nanodroplets, we applied advanced and in situ TEM methods using a Gatan Heating Holder (Model 652) to Ga-Rh nanoparticles as a model LMC deposited on SiNx membranes simulating realistic process temperatures (Figure 3) [2]. The analyses reveal a typical two-phase microstructure comprised of amorphous nanoparticles with laminate-shaped Rh-rich crystalline precipitates. In situ SAED upon heating clearly reveals the melting of the crystalline precipitates at a temperature of 500 ºC, which is in accordance with complementary X-ray photoelectron spectroscopy (XPS) studies. These experiments help to explore the temperature-dependent phase behavior and thus the phase diagram of the Ga-Rh system in the low Rh concentration regime, which is not yet safely established. Moreover, for bimetallic nanoparticles thermodynamic properties like phase stability and melting may be altered by surface effects due to the small particle size. The investigation of such size effects are expected to be key to understand the relationship between superior catalytic performance on the one hand and preparation and process conditions on the other hand.<br
Keywords: 360° electron tomography; correlative microscopy; in situ transmission electron microscopy; liquid metal catalysts; nano X-ray tomography

Correlative Laboratory Nano-CT and 360° Electron Tomography of Macropore Structures in Hierarchical Zeolites - Apeleo Zubiri, Benjamin; Wirth, Janis; Drobek, Dominik; Englisch, Silvan; Przybilla, Thomas; Weissenberger, Tobias; Schwieger, Wilhelm; Spiecker, Erdmann (Advanced Materials Interfaces, 2020)
Hierarchical pore structures exhibit morphological features on several length scales, which govern important materials properties in catalysis, such as catalytic activity, diffusivity or selectivity. Correlative tomography offers unique opportunities for a comprehensive and scale-bridging 3D characterization of such complex pore morphologies, which is crucial to further optimize materials design and synthesis routines. This study explores the capabilities of correlative 360° electron tomography (ET) and lab-based nano X-ray computed tomography (Nano-CT) enabling 3D analyses of volumes of up to (60 µm)³ with down to nm resolution, as demonstrated for zeolite particles with embedded macropores. By first applying the two techniques to the same particle the higher resolution and fidelity of ET are used to improve the segmentation of pore space in the Nano-CT reconstruction. Extended statistical relevance and access to interparticle pore space are obtained from reconstructions of larger particle agglomerates, using the large-field-of-view mode of the Nano-CT. The presented correlative approach enables real space analyses of important pore characteristics for comparison with complementary pore characterization techniques. Moreover, by investigating samples from different stages of the synthesis, 360°-ET and Nano-CT provide unique insights into the formation mechanism of porous materials, as demonstrated for the steam-assisted crystallization of the macroporous zeolite particles.
CRIS-Team Scopus Importer:2020-10-16
Keywords: 360° electron tomography; correlative microscopy; hierarchical pore structure; nano X-ray tomography; phase contrast Nano-CT

Corrigendum to “Seasonal storage and alternative carriers: A flexible hydrogen supply chain model” [Appl. Energy 200 (2017)290–302](S0306261917305457)(10.1016/j.apenergy.2017.05.050) - Reuß, M.; Grube, T.; Robinius, M.; Preuster, Patrick; Wasserscheid, Peter; Stolten, D. (Applied Energy, 2019)
Unfortunately, we must admit that we discovered an error in our previous calculation. The work that we presented had an error related to the GH2 truck-supplied fuel station. In our script, we highlighted that the model includes additional trailer costs at the fuelling station under the assumption that the trailer serves as low pressure storage. Unfortunately, the model did not factor this cost into the fueling station's cost as intended, and thereby underestimated the specific cost of hydrogen for gaseous trailer-supplied fueling stations by 0.34€/kWh. This influences the costs noted in to Figs. 6–9 and 14. The new figures are shown below: Fig. 6. Hydrogen cost at the fuelling station regarding the full supply chain (Electrolysis, seasonal storage, transportation, fuelling station)for transport = storage. [Figure presented]Regarding the surface diagram from Fig. 6, it became obvious that the gaseous truck transportation is increasing in cost compared to the previously submitted picture. This leads to a smaller area in which the gas truck is the cheapest option. The pipeline is now the cheapest solution for high demand at ∼50 km distance. Fig. 7. Hydrogen costs for pathways without conversion between storage and transportation modules at 250 km distance and 50 t/day hydrogen demand. [Figure presented]Fig. 8. Hydrogen cost at the fuelling station regarding the full supply chain (Electrolysis, seasonal storage, transport, fuelling station). [Figure presented]With regard to Fig. 8, the option LOHC tank, GH2 truck, is no longer visible on the surface plot. Due to the increased fuel station cost, this combination is no longer cost-competitive. Fig. 9. Cost comparison of pathways without seasonal GH2-Tanks at 250 km distance and 50 t/day hydrogen demand. [Figure presented]With regard to Fig. 9, the truck-supplied fuel station with GH2 cavern is now more expensive than LOHC trucks, as well as LH2 trucks with GH2 caverns. The changes in Fig. 14 are similar to Fig. 9. Fig. 14. Comparison of different heat sources for LOHC stations at 250 km and 50 t/day hydrogen demand. [Figure presented]These amendments will not affect the main conclusions of the paper. The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2019-05-28

Co-solvent intensification effect on aromatic alcohol oxidation - Chen, Long; Chen, Lifang; Ye, Yinmei; Qi, Zhiwen; Freund, Hannsjörg; Sundmacher, Kai (Catalysis Communications, 2012)
Solvent intensification for aromatic alcohol oxidation was performed by experimentally extensive screening. A co-solvent mixture of[Omim]Cl and toluene was found to significantly intensify this class of reactions with high conversion of alcohols (>90%) and high selectivity to their aldehydes (>90%). The intensification effect can be jointly attributed to the interaction of [Omim]Cl with the catalyst WO3 surface, which enhances its catalytic reactivity, and to the aqueous-organic biphasic formation by toluene, which inhibits the over-oxidation of aromatic alcohols. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Oxidation; Aromatic alcohols; Co-solvent; Ionic liquids; Intensification effect

Coupled ptychography and tomography algorithm improves reconstruction of experimental data - Kahnt, Maik; Becher, Johannes; Brueckner, Dennis; Fam, Yakub; Sheppard, Thomas; Weissenberger, Tobias; Wittwer, Felix; Grunwaldt, Jan-Dierk; Schwieger, Wilhelm; Schroer, Christian G. (Optica, 2019)
Three-dimensional (3D) x-ray microscopy by ptychographic tomography requires elaborate numerical reconstructions. We describe a coupled ptychography-tomography reconstruction algorithm and apply it to an experimental ptychographic x-ray computed tomography data set of a catalyst particle. Compared to the traditional sequential algorithm, in which ptychographic projections are reconstructed to serve as input for subsequent tomographic reconstruction, the coupled ptychography-tomography algorithm reconstructs the 3D volume with higher spatial resolution over a larger field of view. Coupling the data from different projections improves the overall reconstruction, and the ptychographic sampling in individual projections can be coarsened beyond the point of overlap between neighboring scan points, still leading to stable reconstructions. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-11-01

Coupled ptychography and tomography reconstruction of experimental data - Kahnt, Maik; Becher, Johannes; Brueckner, Dennis; Fam, Yakub; Sheppard, Thomas; Weissenberger, Tobias; Wittwer, Felix; Grunwaldt, Jan-Dierk; Schwieger, Wilhelm; Schroer, Christian G. (ACTA CRYSTALLOGRAPHICA A-FOUNDATION AND ADVANCES, 2021)
CRIS-Team WoS Importer:2022-04-01

Covalent incorporation of aminated nanodiamond into an epoxy polymer network - Mochalin, Vadym N.; Neitzel, Ioannis; Etzold, Bastian; Peterson, Amy; Palmese, Giuseppe; Gogotsi, Yury (ACS nano, 2011)
Outstanding mechanical and optical properties of diamond nanoparticles in combination with their biocompatibility have recently attracted much attention. Modification of the surface chemistry and incorporation into a polymer is required in many applications of the nanodiamond. Nanodiamond powder with reactive amino groups (∼20% of the number of surface carbon atoms in each 5 nm particle) was produced in this work by covalent linking of ethylenediamine to the surface carboxyl groups via amide bonds. The synthesized material was reacted with epoxy resin, yielding a composite, in which nanodiamond particles are covalently incorporated into the polymer matrix. The effect of amino groups grafted on the nanodiamond on the curing chemistry of the epoxy resin was analyzed and taken into consideration. Covalently bonded nanodiamond-epoxy composites showed a three times higher hardness, 50% higher Young's modulus, and two times lower creep compared to the composites in which the nanodiamond was not chemically linked to the matrix. Aminated nanodiamond produced and characterized in the present study may also find applications beyond the composites, for example, as a drug, protein, and gene delivery platform in biology and medicine, as a solid support in chromatography and separation science, and in solid state peptide synthesis. © 2011 American Chemical Society.
CRIS-Team Scopus Importer:2023-08-15
Keywords: amination; epoxy; hardness; nanocomposites; nanodiamond; surface chemistry; Young's modulus

Cu carbonyls enhance the performance of Ru-based SILP water-gas shift catalysts: a combined in situ DRIFTS and DFT study - Blaumeiser, Dominik; Stepic, Robert; Wolf, Patrick; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Bauer, Tanja; Libuda, Jörg (Catalysis: Science and Technology, 2020)
Ru-based supported ionic liquid phase (SILP) catalysts efficiently promote the water-gas shift reaction (WGSR). The addition of CuCl further improves the performance. This is attributed to the formation of labile Cu carbonyl species, which act as CO shuttles in the ionic liquid (IL) phase. We apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) to monitor the formation of these Cu carbonyls in an imidazolium-based SILP system. To aid the identification of the relevant Cu carbonyls, we perform density functional theory (DFT) calculations. In the present study, we investigate [Ru(CO)(3)Cl-2](2)/CuCl/[C(4)C(1)C(1)Im]Cl/Al2O3 and CuCl/[C(4)C(1)C(1)Im]Cl/Al2O3 with various CuCl : IL ratios. The relevant Cu carbonyls are identified as neutral CuCl monomers and dimers, as well as monoanionic monomers and dimers. Moreover, we demonstrate that the ratio of the individual Cu carbonyl species depends on the CuCl : IL ratio.
CRIS-Team WoS Importer:2020-01-17

Cu-releasing bioactive glass/polycaprolactone coating on Mg with antibacterial and anticorrosive properties for bone tissue engineering - Yang, Yuyun; Zheng, Kai; Liang, Ruifang; Mainka, Astrid; Taccardi, Nicola; Roether, Judith; Detsch, Rainer; Goldmann, Wolfgang; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Biomedical Materials, 2017)
Copper (Cu)-containing bioactive glass nanoparticles (Cu-BGNs) were introduced in polycaprolactone (PCL) coating systems to improve the bioactivity, antibacterial property, and corrosion resistance of vulnerable magnesium matrices under physiological conditions. The influence of different amounts of Cu-BGNs in PCL coatings was thoroughly investigated determining the wettability, electrochemical properties, and antibacterial effects against Staphylococcus carnosus and Escherichia coli, as well as their cyto-compatibility. Cu-BGNs were observed randomly scattered in PCL coatings. Increasing concentration of Cu-BGNs resulted in slightly decreasing water contact angle, and reducing anti-corrosion properties of the Cu-BGNs composite coatings. Yet higher Cu-BGNs content in coatings led to more calcium phosphate formation on the surface after 7 days of immersion in DMEM, which was confirmed by FTIR and XPS. The growth of S. carnosus and E. coli was inhibited by Cu2+ ion released from Cu-BGN coatings. In addition, both direct and indirect cyto-compatibility experiments showed that the viability and proliferation of MG-63 cells on Cu-BGN coatings were highly increased compared to pure magnesium; however, an additional increase of Cu-BGNs concentration showed a slight decrease of cell proliferation and cell activity. In summary, Cu-BGN/PCL composite coatings impart magnesium-based biomaterials antibacterial and anticorrosive properties for clinical applications.
EVALuna2:13499

CVD diamond coating of steel on a CVD-TiBN interlayer - Bareiss, Christian; Hackl, Gerrit; Popovska, Nadejda; Rosiwal, Stefan; Singer, Robert (Surface & Coatings Technology, 2006)
Adherent and homogeneous diamond films were deposited on 41Cr4 steel substrates employing chemical vapor deposited (CVD) TiBN interlayers. The suitability of CVD-TiBN interlayers for diamond deposition was investigated. The CVD intermediate layers showed excellent barrier properties against the diffusion of iron from the bulk substrate to the surface and against diffusion of carbon from gas phase during diamond deposition. Various growth conditions for interlayers affect their thickness and composition. For these samples different shares in the phases TiB2 and TiN were analyzed by XRD. The diamond coating onto the TiBN interlayer showed very good adhesion. The measured Raman spectra proved high compressive stresses in the diamond film with a high diamond quality. Sandblasting tests indicated an enormous improvement of the erosion resistance after diamond deposition on 41Cr4 substrates with a 5 mu m intermediate layer of TiBN. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: diamond properties and application; diamond on steel; CVD-TiBN interlayer; adhesion

Cyclic metalla-allyl-carboxylates as model complexes for the butadiene-carbon dioxide coupling at nickel(0) - Schulz, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2002)

Cyclic thiouronium ionic liquids: Physicochemical properties and their electronic structure probed by X-ray induced photoelectron spectroscopy - Taccardi, Nicola; Niedermaier, Inga; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Chemistry - A European Journal, 2012)
Radiography of a structure skeleton: Cyclic thiouronium ionic liquids have been synthesized and characterized in such a way that the straightforward introduction of three different alkyl substituents at the cation has been realized. X-ray induced photoelectron spectroscopy studies indicated a significant electronic contribution of the free electrons at the sulfur to stabilize the cationic charge, leading to structures with peculiar physicochemical properties (see figure). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Das Neue geschieht an den Grenzflächen. - Schlücker, Eberhard; Müller, Georg; Wasserscheid, Peter (Chemie Ingenieur Technik, 2005)
UnivIS-Import:2015-03-09:Pub.2005.tech.ITC.prozma.dasneu

Deducing kinetic constants for the hydrodechlorination of 4-chlorophenol using high adsorption capacity catalysts - Munoz Garcia, Macarena; Kaspereit, Malte; Etzold, Bastian (Chemical Engineering Journal, 2016)
Employing high surface area supports for catalytic hydrodechlorination can result in pronounced, adsorption of reactants, intermediates and products. The influence of these sorption processes on the activity and selectivity upon 4-chlorophenol (4-CP) hydrodechlorination in aqueous solution has been studied using four commercial Pd/Al2O3 and Pd/AC catalysts at ambient pressure within the temperature range of 20-40 degrees C ([4-CP](0) = 0.78-2.90 mmol L-1, [catalyst] = 1 g L-1, 50 N mL H-2 min(-1)). The adsorption capacity of the catalysts was independently evaluated. The Al2O3-based catalyst did not show any significant adsorption of those species whereas the activated carbon materials presented in all cases high uptakes (e.g. up to 2.4 mmol(4-CP) g(cat)(-1)). In order to deduce true kinetic constants also for these catalysts, a kinetic model was developed, which accounts for the consecutive reaction and sorption processes in parallel. This expanded model resulted in a reasonable fit, can thus be used for comparison of different catalysts regardless their sorption capacity and allows predicting successfully the selectivity to the reaction products. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Catalytic hydrodechlorination; Adsorption; Kinetic model; 4-Chlorophenol; Pd; Activated carbon

Dehydrogenation mechanism of liquid organic hydrogen carriers: Dodecahydro-N-ethylcarbazole on Pd(111) - Amende, Maximilian; Schernich, Stefan; Sobota, Marek; Nikiforidis, Ioannis; Hieringer, Wolfgang; Assenbaum, Daniel; Gleichweit, Christoph; Drescher, Hans-Jörg; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; Wasserscheid, Peter; et al. (Chemistry - A European Journal, 2013)
Dodecahydro-N-ethylcarbazole (H-NEC) has been proposed as a potential liquid organic hydrogen carrier (LOHC) for chemical energy storage, as it combines both favourable physicochemical and thermodynamic properties. The design of optimised dehydrogenation catalysts for LOHC technology requires a detailed understanding of the reaction pathways and the microkinetics. Here, we investigate the dehydrogenation mechanism of H-NEC on Pd(111) by using a surface-science approach under ultrahigh vacuum conditions. By combining infrared reflection-absorption spectroscopy, density functional theory calculations and X-ray photoelectron spectroscopy, surface intermediates and their stability are identified. We show that H-NEC adsorbs molecularly up to 173 K. Above this temperature (223 K), activation of C-H bonds is observed within the five-membered ring. Rapid dehydrogenation occurs to octahydro-N-ethylcarbazole (H-NEC), which is identified as a stable surface intermediate at 223 K. Above 273 K, further dehydrogenation of H -NEC proceeds within the six-membered rings. Starting from clean Pd(111), C-N bond scission, an undesired side reaction, is observed above 350 K. By complementing surface spectroscopy, we present a temperature-programmed molecular beam experiment, which permits direct observation of dehydrogenation products in the gas phase during continuous dosing of the LOHC. We identify H-NEC as the main product desorbing from Pd(111). The onset temperature for H-NEC desorption is 330 K, the maximum reaction rate is reached around 550 K. The fact that preferential desorption of H -NEC is observed even above the temperature threshold for H -NEC dehydrogenation on the clean surface is attributed to the presence of surface dehydrogenation and decomposition products during continuous reactant exposure. © 2013 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dehydrogenation of Dodecahydro-N-ethylcarbazole on Pd/Al2O3 Model Catalysts - Sobota, Marek; Nikiforidis, Ioannis; Amende, Maximilian; Sanmartίn Zanón, Beatriz; Staudt, Thorsten; Höfert, Oliver; Lykhach, Yaroslava; Papp, Christian; Hieringer, Wolfgang; Laurin, Mathias; Assenbaum, Daniel; Wasserscheid, Peter; et al. (Chemistry - A European Journal, 2011)
To elucidate the dehydrogenation mechanism of dodecahydro-N-ethylcarbazole (H-12-NEC) on supported Pd catalysts, we have performed a model study under ultra high vacuum (UHV) conditions. H-12-NEC and its final dehydrogenation product, N-ethylcarbazole (NEC), were deposited by physical vapor deposition (PVD) at temperatures between 120 K and 520 K onto a supported model catalyst, which consisted of Pd nanoparticles grown on a well-ordered alumina film on NiAl(110). Adsorption and thermally induced surface reactions were followed by infrared reflection absorption spectroscopy (IRAS) and high-resolution X-ray photoelectron spectroscopy (HR-XPS) in combination with density functional theory (DFT) calculations. It was shown that, at 120 K, H-12-NEC adsorbs molecularly both on the Al2O3/NiAl(110) support and on the Pd particles. Initial activation of the molecule occurs through C-H bond scission at the 8a- and 9a-positions of the carbazole skeleton at temperatures above 170 K. Dehydrogenation successively proceeds with increasing temperature. Around 350 K, breakage of one C-N bond occurs accompanied by further dehydrogenation of the carbon skeleton. The decomposition intermediates reside on the surface up to 500 K. At higher temperatures, further decay to small fragments and atomic species is observed. These species block most of the absorption sites on the Pd particles, but can be oxidatively removed by heating in oxygen at 600 K, fully restoring the original adsorption properties of the model catalyst.
Keywords: density functional calculations; IR spectroscopy; liquid organic hydrogen carriers; photo-electron spectroscopy; supported catalysts

Dehydrogenation of dodecahydro-N-ethylcarbazole on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Chemsuschem, 2013)
Sloshing hydrogen: Liquid organic hydrogen carriers are high-boiling organic molecules, which can be reversibly hydrogenated and dehydrogenated in catalytic processes and are, therefore, a promising chemical hydrogen storage material. One of the promising candidates is the pair N-ethylcarbazole/perhydro- N-ethylcarbazole (NEC/H-NEC). The dehydrogenation and possible side reactions on a Pt(111) surface are evaluated in unprecedented detail. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dehydrogenation of perhydro-N-ethylcarbazole under reduced total pressure - Kiermaier, Stephan; Lehmann, Daniel; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2021)
Liquid organic hydrogen carrier (LOHC) systems represent a promising storage option for hydrogen produced from renewable electricity by water electrolysis. Regarding the efficiency of the endothermal hydrogen release reaction, this technology greatly benefits from a direct heat integration with the waste heat of the energetic use of the released hydrogen, e. g. in a fuel cell. To enable such beneficial set-up, the reaction temperature of hydrogen release must be below the operation temperature of the applied fuel cell which calls for both low temperature dehydrogenation catalysis and high temperature fuel cell operation. This paper demonstrates that such combination may be suitable if reduced pressure dehydrogenation of perhydro-N-ethylcarbazole (H12-NEC) is combined with hydrogen electrification in a high temperature polymer electrolyte membrane fuel cell (HT-PEMFC). Dehydrogenation reactions of H12-NEC were carried out between 160 °C and 200 °C applying different hydrogen partial pressures in the dehydrogenation unit to mimic the effect of a sucking fuel cell operation mode, i.e. the reduction of hydrogen partial pressure in the dehydrogenation unit caused by the fuel cell operation. Our kinetic analysis reveals that a dehydrogenation temperature of 180 °C combined with 500 mbar hydrogen partial pressure represent, for example, a suitable parameter set for efficient hydrogen release.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Dehydrogenation; Fuel cell; Hydrogen partial pressure; LOHC; N-ethylcarbazole

Dehydrogenation of the liquid organic hydrogen carrier system 2-methylindole/2-methylindoline/2-methyloctahydroindole on Pt(111) - Bachmann, Philipp; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Eschenbacher, Roman; Hemauer, Felix; Scheuermeyer, Marlene; Bösmann, Andreas; Büttner, Miriam; Neiß, Christian; Görling, Andreas; et al. (Journal of Chemical Physics, 2019)
Among other N-heterocycles, indole and its substituted derivatives, such as methylindoles, are considered promising Liquid Organic Hydrogen Carriers (LOHCs) for the storage of renewable energy. We used X-ray photoelectron spectroscopy (XPS), temperature programmed desorption (TPD), and density-functional theory (DFT) to investigate the low temperature adsorption and consecutive dehydrogenation reaction during heating of 2-methylindole, 2-methylindoline, and 2-methyloctahydroindole on Pt(111) and their viability as the LOHC system. In the photoemission experiments, for all Hx-2-methylindoles, we find deprotonation at the NH bond starting between 240 and 300 K, resulting in a 2-methylindolide species. Simultaneously or before this reaction step, the dehydrogenation of 2-methyloctahydroindole via 2-methylindoline and 2-methylindole intermediates is observed. For 2-methyloctahydroindole, we also find π-allyl intermediates above 230 K. Starting at ∼390 K, decomposition of the remaining 2-methylindolide species takes place under the conditions of our surface science experiments. DFT calculations give insight into the relative energies of the various species, reaction intermediates, and their isomers both in the gas phase and on the Pt(111) surface.
CRIS-Team Scopus Importer:2019-10-22

Dehydrogenation of the Liquid Organic Hydrogen Carrier System Indole/Indoline/Octahydroindole on Pt(111) - Bachmann, Philipp; Schwarz, Matthias; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Nascimento Silva, Thais; Mohr, Susanne; Hohner, Chantal; Scheuermeyer, Marlene; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Physical Chemistry C, 2018)
Indole derivatives are considered as promising liquid organic hydrogen carriers for renewable energy storage. Using X-ray photoelectron spectroscopy, temperature-programmed desorption, and infrared reflection absorption spectroscopy, we investigated low-temperature adsorption and dehydrogenation during heating of indole, indoline, and octahydroindole on Pt(111). For all three molecules, we find deprotonation of the NH bond above 270 K, accompanied with dehydrogenation of indoline and octahydroindole via an indole intermediate, resulting in an indolide species above 300 K. For octahydroindole, we also find a side reaction yielding small amounts of a pi-allyl species between 170 and 450 K. Above 450 K, decomposition of the remaining indolide species takes place.

Densification of Silica Spheres: A New Pathway to Nano-Dimensioned Zeolite-Based Catalysts - Machoke, Albert; Apeleo Zubiri, Benjamin; Leonhardt, Rainer; Marthala, Venkata; Schmiele, Martin; Unruh, Tobias; Hartmann, Martin; Spiecker, Erdmann; Schwieger, Wilhelm (Chemistry - A European Journal, 2017)
Nanosized materials are expected to play a unique role in the development of future catalytic processes. Herein, pre-prepared and geometrically well-defined amorphous silica spheres are densified into silica-rich zeolites with nanosized dimensions. After the densification, the obtained nanosized zeolites exhibit the same spherical morphology like the starting precursor but characterized by a drastically reduced size, higher density, and high crystallinity. The phase transformation into crystalline zeolite material and the densification effect are achieved through a well-controlled steam-assisted treatment of the larger precursor particles so that the transformation process proceeds always towards the center of the spheres, just like a shrinking process. Furthermore, this procedure is applicable also to commercially available silica particles, as well as aluminum-containing systems (precursors) leading to acidic nano-catalysts with improved catalytic performance.
Keywords: catalytic cracking; crystallization; heterogeneous catalysis; nanoparticles; silica-rich zeolites

Density and surface tension of ionic liquids - Kolbeck, Claudia; Lehmann, Julia; Lovelock, Kevin; Cremer, Till; Paape, Natalia; Wasserscheid, Peter; Fröba, Andreas Paul; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry B, 2010)
We measured the density and surface tension of 9 bis[(trifluoromethyl) sulfonyl]imide ([Tf N] )-based and 12 1-methyl-3- octylimidazolium ([C C Im] )-based ionic liquids (ILs) with the vibrating tube and the pendant drop method, respectively. This comprehensive set of ILs was chosen to probe the influence of the cations and anions on density and surface tension. When the alkyl chain length in the [C C Im][Tf N] series (n) 1, 2, 4, 6, 8, 10, 12) is increased, a decrease in density is observed. The surface tension initially also decreases but reaches a plateau for alkyl chain lengths greater than n) 8. Functionalizing the alkyl chains with ethylene glycol groups results in a higher density as well as a higher surface tension. For the dependence of density and surface tension on the chemical nature of the anion, relations are only found for subgroups of the studied ILs. Density and surface tension values are discussed with respect to intermolecular interactions and surface composition as determined by angle-resolved X-ray photoelectron spectroscopy (ARXPS). The absence of nonvolatile surface-active contaminants was proven by ARXPS. © 2010 American Chemical Society.

Der Erlanger OxFA-Prozess - Albert, Jakob (SVH-Südwestdeutscher Verlag für Hochschulschriften, 2016)

Design of optimal multiphase reactors exemplified on the hydroformylation of long chain alkenes - Peschel, Andreas; Hentschel, Benjamin; Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering Journal, 2012)
In summary, the proposed methodology is suited for the design of tailor-made superior multiphase reactors. For the example process, namely the hydroformylation of long chain linear alkenes, a new reactor concept was derived, leading to a significantly higher selectivity compared to conventional reactor concepts. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Multiphase reactor; Design; Optimization; Hydroformylation; Process intensification; Elementary process functions

Detailed 3D-simulations of single phase reacting flow in randomly packed beds with low aspect ratios - Freund, Hannsjörg Dieter; Klemm, Elias; Emig, Gerhard; Zeiser, Thomas; Brenner, Gunter; Durst, Franz (Chemie Ingenieur Technik, 2001)
UnivIS-Import:2015-03-09:Pub.2001.tech.ITC.stmmec.detail

Detailed geometrical analysis of statistical activity variations in diluted catalyst beds - Ganzer, Gunnar; Daniel, Andreas; Freund, Hannsjörg (Chemical Engineering Research & Design, 2019)
In multitubular fixed bed reactors for heterogeneously catalyzed, highly exothermic gas phase reactions the catalyst bed is usually diluted with inert particles for improving the heat management. To help balancing the heat generation and heat removal out of the reactor by catalyst bed dilution, the active and inert particles have to be mixed as well as possible. Otherwise, the thermal stability of the reactor cannot be guaranteed and, e.g., catalyst deactivation or thermal runaway may take place because of the formation of local hotspots. Since loading a mixture of active and inert particles into a reactor tube inherently is a statistical process, fluctuations in local activity cannot be avoided. We have analyzed this phenomenon in detail based on numerically generated 3-dimensional randomly packed beds of spheres. The statistical process of loading a mixture of particles into a reactor tube was mimicked by a random number based approach. The simulations show that activity variations are evenly distributed along the axial direction, whereas in radial direction the fluctuations become larger towards the tube center. The synthetic packed beds provide detailed information about the packed bed structure, which has been used to identify accumulations of active particles in local clusters. This evaluation reveals significant non-idealities compared to the assumption of a uniform activity profile, e.g., clusters of up to 20 active particles could be observed. Especially for highly diluted beds and/or low D/d ratios typical for highly exothermic reactions this aspect should be kept in mind during process development and design.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Catalyst bed dilution; Fixed bed reactors; Geometrical analysis; Hotspot formation; Randomly packed beds; Statistical activity variations

Detailed investigation of liquid distribution and holdup in periodic open cellular structures using computed tomography - Littwin, Giulia; von Beyer, Markus; Freund, Hannsjörg (Chemical Engineering and Processing, 2021)
Periodic open cellular structures (POCS) show great potential for process intensification in catalytic reactors due to their favorable properties regarding heat transfer, pressure drop and liquid distribution. In multiphase applications, POCS can be employed as multifunctional catalyst carrier with integrated liquid distribution function for enhancing the performance of heterogeneously catalyzed reactions. This applies particularly to trickle bed reactors where a uniform liquid distribution is of great importance. In this contribution, the liquid distribution of three POCS of different unit cell geometry is investigated using a custom-made computed tomography scanner with high spatial resolution. POCS with the Kelvin, diamond and DiaKel unit cell, respectively, were manufactured via fused deposition modeling out of acrylonitrile butadiene styrene. The liquid distribution was examined in dependence of the unit cell as well as for different liquid and gas flow rates. The three POCS show different behavior for the liquid distribution and holdup within the structures. POCS with Kelvin and DiaKel unit cell geometry show a higher liquid holdup as well as a more uniform liquid distribution compared to diamond unit cell POCS. Also, the liquid filling between the individual POCS that are stacked in the column is dependent on the unit cell.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Computed tomography; Liquid distribution; Liquid holdup; Multiphase system; POCS; Trickle bed reactor

Detailed Investigation of the Mechanism of Rh-Diphosphite Supported Ionic Liquid Phase (SILP)-Catalyzed 1-Butene Hydroformylation in the Gas Phase via Combined Kinetic and Density Functional Theory (DFT) Modeling Studies - Walter, Simon; Spohr, Hanna; Franke, Robert; Hieringer, Wolfgang; Wasserscheid, Peter; Haumann, Marco (ACS Catalysis, 2017)
A detailed kinetic investigation of the gas-phase continuous hydroformylation of 1-butene has been carried out. The supported ionic liquid phase (SILP) catalyst was based on a Rh-diphosphite, the ionic liquid [EMIM][NTf2), and silica support material. Based on the established Wilkinson mechanism, the hyperbolic rate expressions were used to fit the experimental results. While the hydroformylation could be modeled with high accuracy, the hydrogenation and isomerization trends could not be reproduced by the given rate expressions. An alternative reaction mechanism was developed and allowed an excellent fit of experimental data by the new reaction rate expressions. Initial steps of the mechanism were studied using density functional theory (DFT) calculations.
Keywords: hydroformylation; hydrogenation; isomerization; supported ionic liquid phase (SILP); kinetic modeling; density functional theory (DFT)

Detailed kinetic investigations on the selective oxidation of biomass to formic acid (OxFA process) using model substrates and real biomass - Albert, Jakob; Reichert, Jenny (ACS Sustainable Chemistry & Engineering, 2017)
A detailed kinetic analysis of the selective catalytic oxidation of different biogenic model substrates to formic acid (OxFA process) is presented using two different polyoxometalate catalysts, HPA-2 (H5PV2Mo10O40) and HPA-5 (H8PV5Mo7O40). By using high oxygen pressures (30-60 bar) and temperatures of 80-90 °C in aqueous solution, we were able to investigate the rate-determining substrate oxidation step catalyzed by the oxidized form of the polyoxometalates (POMs) by keeping the concentration of the catalytic active species constant. Under these conditions, kinetic parameters like effective reaction order and reaction rate constants could be determined by the differential method for model substrates like glucose, fructose, sorbitol, and gluconic acid. Furthermore, kinetic experiments using the two different catalysts showed a different behavior for various functionalities within the carbon framework of the substrate with the tendency of higher reaction rates with the HPA-5 catalyst. This effect was more pronounced for disaccharides like cellobiose and sucrose than for monosaccharides. Finally, a detailed kinetic study for water-insoluble biomasses like beech and spruce wood showed differences in formic acid (FA) formation and product selectivities depending on the composition of the wood in terms of their ratios of lignin, cellulose, and hemicellulose.

Detailed kinetic study of cumene isopropylation in a liquid-liquid biphasic system using acidic chloroaluminate ionic liquids. - Joni, Joni; Schmitt, Daniel; Schulz, Peter; Lotz, T. J.; Wasserscheid, Peter (Journal of Catalysis, 2008)
A kinetic study of cumene isopropylation has been carried out using the acidic ionic liq. 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl)/AlCl3 (molar ratio 1:2) as the catalyst phase in a semi-batch liq.-liq. biphasic reaction system. Kinetic models representing the alkylation reaction network have been established based on reaction temp. and propylene partial pressure variations. By comparing the results of the kinetic models with the measured concns. in the liq. org. phase, the importance of the different product solubilities in the acidic ionic liq. became evident. Correction of the product concns. in the org. phase based on a COSMO-RS calcn. of the relative product solubilities in the acidic ionic liq. [EMIM][Al2Cl7] gave a remarkably good prediction of the reaction kinetics by the kinetic model. These findings demonstrate the suitability of COSMO-RS to predict the relative solubilities of different arom. compds. in highly reactive catalytic systems. [on SciFinder(R)]
Keywords: cumene isopropylation kinetics biphasic system acidic chloroaluminate ionic liq

Detailed numerical investigations of the in operando adjustable flow field in a diamond unit cell-based interpenetrating periodic open cellular structure (interPOCS) - Trunk, Sebastian; Freund, Hannsjörg (Chemical Engineering and Processing, 2024)
In the field of heterogeneous catalysis, additively manufactured so-called Periodic Open Cellular Structures (POCS) applied as catalyst supports have demonstrated their advantages over conventional randomly packed bed reactors in terms of heat management and pressure drop (Busse et al., 2018; Inayat et al., 2016). Since the internal flow field and the pressure drop are mainly influenced by the geometrical properties of the unit cell (unit cell type, strut diameter and cell size), the resulting transport characteristics of the structure is already determined during the design phase of the unit cell (Horneber, 2015). By inserting one POCS based on a diamond unit cell (offset structure) into the cavities of a second diamond cell structure (fix structure), a completely new type of so-called interpenetrating Periodic Open Cellular Structures (interPOCS) is formed which allows for an in operando adjustment of the global and local morphological properties of the structure (Do et al., 2017; Do et al., 2020). With detailed, spatially resolved computational fluid dynamics (CFD) simulations using the open source toolbox OpenFOAM® (Weller et al., 1998) and an additional in-house random-walk particle tracking implementation called disTrackFoam (Trunk et al., 2021), we systematically investigated the local and global flow characteristics within the interPOCS in dependency of the relative positioning of the fixed and offset structure. The obtained results show that this highly adjustable structure allows for a broad variation of flow characteristics in a chemical reactor without changing the system's periphery. This study demonstrates that interPOCS represent a completely new application of additively manufactured catalyst support structures enabling highly flexible in operando tuning of the flow field and mass transport in a heterogeneously catalyzed reactor system.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Adjustable flow conditions; Flexibility; InterPOCS; OpenFOAM®; Process intensification; Structured catalysts

Detailed simulation of transport processes in fixed-beds reactors - Emig, Gerhard; Zeiser, Thomas; Freund, Hannsjörg; et al. (Industrial & Engineering Chemistry Research, 2005)
UnivIS-Import:2015-03-09:Pub.2005.zwiss.rrze.zensys.detail

Determination of Glucose and Cellobiose Dissolved in the Ionic Liquid 1-Ethyl-3-Methylimidazolium Acetate Using Fourier Transform Infrared Spectroscopy - Kiefer, Johannes; Obert, Katharina; Fries, Jürgen; Bösmann, Andreas; Wasserscheid, Peter; Leipertz, Alfred (Applied Spectroscopy, 2009)
The conversion of biogenic carbohydrate feedstock to chemicals or energy equivalents is a promising approach to solve the problem of limited fossil fuel reserves. Some concepts to accomplish these transformations are based on ionic liquids (ILs) due to their ability to dissolve biopolymers, such as cellulose, and even complex biopolymer mixtures, such as wood. However, concerning control of such conversions, a reliable tool for process analytics is required. In this paper we demonstrate the applicability of Fourier transform infrared (FT-IR) spectroscopy to perform quantitative concentration measurements of glucose and cellobiose as two examples of carbohydrates dissolved in the room-temperature ionic liquid [EMIM][OAc] (1-ethyl-3-methylimidazolium acetate). For this purpose, binary mixtures in the range 0-20 wt% have been studied. A previously developed method for the data analysis, which was based on the Beer-Lambert relation, has been universalized by employing empirical correlations between the measured quantity (i.e., extinction) and the carbohydrate concentration. In the entire spectral range under investigation (500-4000 cm(-1)) numerous individual wave-numbers have been identified, allowing quantitative measurements with high accuracy and precision.
Keywords: Carbohydrates; Ionic liquid; Glucose; Cellobiose; Infrared spectroscopy; IR spectroscopy; Fourier transform infrared spectroscopy; FT-IR spectroscopy; Quantitative measurements

Determination of hydrogen loading in the carrier system diphenylmethane/dicyclohexylmethane by depolarized Raman spectroscopy - Jander, Julius Hans; Kerscher, Manuel; Li, Shao; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
During the processes of hydrogenation or dehydrogenation of liquid organic hydrogen carriers (LOHCs), knowledge of the current degree of hydrogenation (DoH) is often essential. The present study shows that depolarized Raman spectroscopy allows the accurate determination of the DoH of the model LOHC system diphenylmethane (H0-DPM)/dicyclohexylmethane (H12-DPM) at temperatures up to 573 K. Using two independent experimental setups and binary mixtures of H0- and H12-DPM, a temperature-independent calibration factor could be obtained by analyzing Raman bands characteristic for the aromatic and aliphatic carbon rings. The successful transfer of the calibration to technical mixtures is validated by DoH measurements of samples from deliberately stopped hydrogenation reactions containing also the intermediate cyclohexylphenylmethane (H6-DPM) and of pure H6-DPM. Here, the average absolute deviation of the DoHs obtained by depolarized Raman spectroscopy from those measured analytically is 0.018, which demonstrates the applicability of the method at arbitrary and process-relevant temperatures.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Degree of hydrogenation; Depolarized Raman spectroscopy; Diphenylmethane; In-situ process monitoring; LOHC

Determination of Solubility of GaN in Ammonobasic Systems - Schwieger, Wilhelm; Baser, Hasan-Hüseyin (Ammonothermal Synthesis and Crystal Growth of Nitrides, 2021)
In this study, the solubility of GaN in the ammonobasic MNH2–GaN–NH3 (M = Na, K) systems in the temperature range of 350–550 °C was studied. The target value for the ammonia filling degree was 45% and 55% for mineralizers NaNH2 and KNH2, respectively. The mineralizer concentration was varied at all temperatures from 1 M to 3 M, in respect to the liquid ammonia. It has been found that the solubility of GaN with NaNH2 as a mineralizer increases slightly with increasing temperature in the range 400–600 °C, but is generally very low. A dependence of solubility on mineralizer concentration was not observed. An increase in the ammonia filling degree from 45% to 55% only slightly increased the solubility of GaN. The use of KNH2 as a mineralizer brought an enormous increase in the solubility of GaN. Here, 7 times higher solubilities than those for NaNH2 were observed. A retrograde solubility behavior of GaN in the temperature range 400–550 °C was determined for KNH2 as a mineralizer. In the range of 350–400 °C the solubility showed a positive temperature dependence. The maximum solubility was reached at 400 °C. The solubility of GaN at 400 °C was found three times higher than at 550 °C.
CRIS-Team Scopus Importer:2021-03-05

Determining the specific surface area of ceramic foams: The tetrakaidecahedra model revisited - Inayat, Amer; Freund, Hannsjoerg; Zeiser, Thomas; Schwieger, Wilhelm; Freund, Hannsjörg (Chemical Engineering Science, 2011)
Silicon carbide foams were characterized with respect to their specific surface area as well as their morphological parameters including strut diameter, window diameter and open porosities. Image analysis, computed tomography, He-pycnometry and mercury intrusion were used for characterization purposes. State-of-the-artcorrelations (based on different geometrical models for foam structures) for the estimation of the specific surface area were applied and evaluated. Based on the tetrakaidecahedron geometry and different strut morphologies of the foams, new correlations for the specific surface area were developed and successfully validated by comparison with both, own and external experimental data. With the new correlations it is possible to estimate the specific surface area of ceramic foams by using only two measured parameters, namely the window diameter and the open porosity. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Foam; Catalyst support; Strut morphology; Specific surface area; Tetrakaidecahedra model; Correlation

Development and characterization of a low-NOx partially premixed hydrogen burner using numerical simulation and flame diagnostics - Schmidt, Nikolas; Müller, Marcel; Preuster, Patrick; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (International Journal of Hydrogen Energy, 2023)
The utilization of hydrogen as a fuel in free jet burners faces particular challenges due to its special combustion properties. The high laminar and turbulent flame velocities may lead to issues in flame stability and operational safety in premixed and partially premixed burners. Additionally, a high adiabatic combustion temperature favors the formation of thermal nitric oxides (NO). This study presents the development and optimization of a partially premixed hydrogen burner with low emissions of nitric oxides. The single-nozzle burner features a very short premixing duct and a simple geometric design. In a first development step, the design of the burner is optimized by numerical investigation (Star CCM+) of mixture formation, which is improved by geometric changes of the nozzle. The impact of geometric optimization and of humidification of the combustion air on NOx emissions is then investigated experimentally. The hydrogen flame is detected with an infrared camera to evaluate the flame stability for different burner configurations. The improved mixture formation by geometric optimization avoids temperature peaks and leads to a noticeable reduction in NOx emissions for equivalence ratios below 0.85. The experimental investigations also show that NOx emissions decrease with increasing relative humidity of combustion air. This single-nozzle forms the basis for multi-nozzle burners, where the desired output power can flexibly be adjusted by the number of single nozzles.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Flame stability; Hydrogen burner; Lean combustion; Low-NO; Premixed combustion

Development and characterization of a low-NOx partially premixed hydrogen burner using numerical simulation and flame diagnostics - Schmidt, Nikolas; Müller, Marcel; Preuster, Patrick; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (International Journal of Hydrogen Energy, 2023)
Keywords: Lean combustion; Low-NOx; Flame stability; Hydrogen burner; Premixed combustion

Development and characterization of magnetic iron oxide nanoparticles with a cisplatin-bearing polymer coating for targeted drug delivery - Unterweger, Harald; Tietze, Rainer; Janko, Christina; Zaloga, Jan; Lyer, Stefan; Dürr, Stephan; Taccardi, Nicola; Goudouri, Ourania Menti; Hoppe, Alexander; Eberbeck, Dietmar; Schubert, Dirk W.; Boccaccini, Aldo R.; et al. (International Journal of Nanomedicine, 2014)
A highly selective and efficient cancer therapy can be achieved using magnetically directed superparamagnetic iron oxide nanoparticles (SPIONs) bearing a sufficient amount of the therapeutic agent. In this project, SPIONs with a dextran and cisplatin-bearing hyaluronic acid coating were successfully synthesized as a novel cisplatin drug delivery system. Transmission electron microscopy images as well as X-ray diffraction analysis showed that the individual magnetite particles were around 4.5 nm in size and monocrystalline. The small crystallite sizes led to the superparamagnetic behavior of the particles, which was exemplified in their magnetization curves, acquired using superconducting quantum interference device measurements. Hyaluronic acid was bound to the initially dextran-coated SPIONs by esterification. The resulting amide bond linkage was verified using Fourier transform infrared spectroscopy. The additional polymer layer increased the vehicle size from 22 nm to 56 nm, with a hyaluronic acid to dextran to magnetite weight ratio of 51:29:20. A maximum payload of 330 μg cisplatin/mL nanoparticle suspension was achieved, thus the particle size was further increased to around 77 nm with a zeta potential of -45 mV. No signs of particle precipitation were observed over a period of at least 8 weeks. Analysis of drug-release kinetics using the dialysis tube method revealed that these were driven by inverse ligand substitution and diffusion through the polymer shell as well as enzymatic degradation of hyaluronic acid. The biological activity of the particles was investigated in a nonadherent Jurkat cell line using flow cytometry. Further, cell viability and proliferation was examined in an adherent PC-3 cell line using xCELLigence analysis. Both tests demonstrated that particles without cisplatin were biocompatible with these cells, whereas particles with the drug induced apoptosis in a dose-dependent manner, with secondary necrosis after prolonged incubation. In conclusion, combination of dextran-coated SPIONs with hyaluronic acid and cisplatin represents a promising approach for magnetic drug targeting in the treatment of cancer.

Development and evaluation of a new particle tracking solver for hydrodynamic and mass transport characterization of porous media - A case study on periodic open cellular structures - Trunk, Sebastian; Brix, Andreas; Freund, Hannsjörg (Chemical Engineering Science, 2021)
The detailed understanding of local mass transport characteristics in porous catalyst supports is essential for the evaluation of their performance in reaction engineering applications. This applies particularly for the development and assessment of novel concepts such as additively manufactured periodic open cellular structures (POCS). A major drawback of the frequently used Eulerian based mass transport simulation methods is their tendency to overestimate molecular diffusion due to artificial numerical diffusion, especially in the range of high Peclet numbers (boundary-layer dispersion and pure mechanical dispersion regime) that is often encountered in industrial applications.
CRIS-Team WoS Importer:2021-07-30

Development of a new pressure drop correlation for open-cell foams based completely on theoretical grounds: Taking into account strut shape and geometric tortuosity - Inayat, Amer; Klumpp, Michael; Lämmermann, Markus; Freund, Hannsjörg; Schwieger, Wilhelm (Chemical Engineering Journal, 2016)
Owing to their outstanding geometry and material related properties, open-cell foams as structured packing in reactors, columns or heat exchangers offer clear advantages over their traditional counterparts. For the reliable and efficient design of such systems, an accurate knowledge or prediction of the pressure drop is of fundamental importance, as it plays an important economic role in situations involving high space velocities (high Reynolds numbers). The state-of-the-art pressure drop correlations for open-cell foams are not predictive as they tend to show large deviations from measured data. These deviations are observed mainly due to empirical coefficients in the correlations that have been fitted to a particular data set, but without theoretical meaning these coefficients cannot be extrapolated to other foam structures. In addition, the incorporation of inappropriate definitions (originating from misinterpretation or negligence of important aspects) of the structural and geometrical parameters of foams can also induce a considerable error. In this paper, using the notion of geometric tortuosity and starting from the basic Hagen-Poiseuille equation, a generalized pressure drop correlation for open-cell foams is developed which is based completely on theoretical grounds. The correlation is validated for a wide range of open porosities, pore sizes and materials and its applicability for different working fluids is demonstrated. Furthermore, the definitions of structural and geometrical parameters (as mentioned, these are crucial for pressure drop correlations but are sometimes misinterpreted or neglected) of open-cell foams are reviewed. A consensus on these definitions and their incorporation into the pressure drop correlations is proposed. Consequently, with the proposed correlation, pressure drop in open-cell foams can be predicted by knowing only two structural parameters: the open porosity and the window diameter.
Keywords: Correlation; Foam; Porosity; Pressure drop; Tetrakaidecahedron model; Tortuosity

Development of a Structured Reactor System for CO2 Methanation under Dynamic Operating Conditions - Albert, Jakob; Stiegler, Thomas; Wasserscheid, Peter; Meltzer, Katharina; Tremel, Alexander; Baldauf, Manfred (Energy Technology, 2019)
In our contribution we propose the use of an additively manufactured rack-type reactor for CO2 methanation under dynamic operation conditions. In detail, we report CO2 methanation using an additively manufactured structured reactor (catalyst: 2.5 wt.-% Ru/Al2O3/MgO). The dynamic operation was simulated by changing the reactant flow rates (loads) based on the operation strategy of an electrolyzer connected to a wind farm. Due to the high heat conductivity of the metallic structures, temperature hotspots related to load variations can be avoided efficiently. In our test rig, these structured reaction systems reached equilibrium CO2-conversions with only minor axial temperature gradients for various loads and thus offer high potential for the dynamic operation of exothermic gas-phase processes. <br
Keywords: Dynamic operation; CO2 methanation; structured reactor; structured catalyst

Development of a structured reactor system for CO2 valorisation under dynamic operating conditions - Stiegler, Thomas; Meltzer, K.; Tremel, A.; Baldauf, M.; Wasserscheid, Peter; Albert, Jakob (DGMK Tagungsbericht, 2019)
In our contribution we propose the use of an additively manufactured rack-type reactor for CO2 methanation under dynamic operation conditions. In detail, we report CO2 methanation using an additively manufactured structured reactor (catalyst: 2.5 wt.-% Ru/Al2O3/MgO). The dynamic operation was simulated by changing the reactant flow rates (loads) based on the operation strategy of an electrolyzer connected to a wind farm. Due to the high heat conductivity of the metallic structures, temperature hotspots related to load variations can be avoided efficiently. In our test rig, these structured reaction systems reached equilibrium CO2-conversions with only minor axial temperature gradients for various loads and thus offer high potential for the dynamic operation of exothermic gas-phase processes.
CRIS-Team Scopus Importer:2021-04-20

Development of a Supported Ionic Liquid Phase (SILP) Catalyst for Slurry-Phase Friedel-Crafts Alkylations of Cumene - Joni, Joni; Haumann, Marco; Wasserscheid, Peter (dvanced Synthesis & Catalysis, 2009)
A supported ionic liquid phase (SILP) catalyst material has been developed based on a silica support coated with an acidic chloroaluminate ionic liquid. Compared to the results in a liquid-liquid biphasic reaction these materials showed in the isopropylation of cumene a clearly different selectivity which was found to be related to a reduction of the ionic liquid's acidity by the untreated silica support. By pretreating the support with a defined amount of ionic liquid for neutralization and removal of surface hydroxy groups, a well defined, very active and also very selective SILP catalyst for slurry phase Friedel–Crafts alkylation was obtained.

Development of Novel Mesoporous Silica-Based Bioactive Glass Scaffolds with Drug Delivery Capabilities - Philippart, Anahi; Boccardi, Elena; Pontiroli, Lucia; Beltrán, Ana Maria; Inayat, Alexandra; Vitale-Brovarone, Chiara; Schwieger, Wilhelm; Spiecker, Erdmann; Boccaccini, Aldo R. (Advances in Science and Technology, 2014)
Novel silica-based bioactive glasses were successfully prepared by the sol-gel method. The optimized glass composition for fabrication of the scaffolds was (in mol.%) 60% SiO2 – 30% CaO - 5% Na2O - 5% P2O5 (60S30C5N5P). This composition was confirmed to develop a thick hydroxycarbonate apatite (HCA) layer in Simulated Body Fluid (SBF) after 7 days, as revealed by Fourier Transform Infrared Spectroscopy (FTIR), indicating the bioactive character of the scaffolds. The mesoporous nature of the glass structure allows the load of tetracycline and a sustained release of the drug in PBS during 7 days was measured.
Keywords: Mesoporous material; Bioactive glasses; sol-gel; drug delivery; Scaffolds; Bone Tissue Engineering

Dewatering of ionic liquids in a falling film evaporator - Wellner, Niels; Siebeneck, Karl; Ramunno, Monique; Wasserscheid, Peter; Scholl, Stephan (Chemie Ingenieur Technik, 2011)
Experimental investigations on the dewatering of ionic liquids (IL) in a single falling film evaporator were carried out. Depending on the process conditions, such as heating temperature and process pressure, a minimum water content of 0.2 wt-% (2000 ppm) was achieved using batch mode. Assuming that these water contents represent equilibrium state at constant temperatures and pressures, vapor pressure curves of different IL-water mixtures were obtained and from these the required heat for evaporation could be estimated. During the dewatering process viscosity was monitored online and proved to be a sufficient and reliable indicator for dewatering progress. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Dewatering; Falling film evaporator; Ionic liquids

Dicyclohexylmethane as a Liquid Organic Hydrogen Carrier: A Model Study on the Dehydrogenation Mechanism over Pd(111) - Amende, Maximilian; Gleichweit, Christoph; Xu, Tao; Höfert, Oliver; Koch, Marcus; Wasserscheid, Peter; Steinrück, Hans-Peter; Papp, Christian; Libuda, Jörg (Catalysis Letters, 2016)
Abstract: We have studied the dehydrogenation of the liquid organic hydrogen carrier (LOHC) dicyclohexylmethane (DCHM) to diphenylmethane (DPM) and its side reactions on a Pd(111) single crystal surface. The adsorption and thermal evolution of both DPM and DCHM was measured in situ in ultrahigh vacuum (UHV) using synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (HR-XPS). We found that after deposition at 170 K, the hydrogen-lean DPM undergoes C-H bond scission at the methylene bridge at 200 K and, starting at 360 K, complete dehydrogenation of the phenyl rings occurs. Above 600 K, atomic carbon incorporates into the Pd bulk. For the hydrogen-rich DCHM, the first stable dehydrogenation intermediate, a double π-allylic species, forms already at 190 K. Until 340 K, further dehydrogenation of the phenyl rings and of the methylene bridge occurs, yielding the same intermediate that is formed upon heating of DPM to this temperature, that is, DPM dehydrogenated at the methylene bridge. The onset for the complete dehydrogenation of this intermediate occurs at a much higher temperature than after adsorption of DPM. This behavior is mainly attributed to coadsorbed hydrogen from DCHM dehydrogenation. The results are discussed in comparison to our previous study of DPM and DCHM on Pt(111) revealing strong material dependencies. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Liquid organic hydrogen carrier; Model catalysis; X-ray photoelectron spectroscopy

Die Helmholtz-Energie-Allianz "Energieeffiziente Chemische Mehrphasenprozesse" - Hampel, Uwe; Dittmeyer, Roland; Patyk, Andreas; Wetzel, Thomas; Lange, Ruediger; Freund, Hannsjörg; Schwieger, Wilhelm; Gruenewald, Marcus; Schlueter, Michael; Petasch, Uwe (Chemie Ingenieur Technik, 2013)
Energieeffizienz ist ein wesentlicher Baustein nachhaltigen Wirtschaftens und unabdingbare Voraussetzung zur Erreichung aktueller klimapolitischer Ziele. Die von der Helmholtz-Gemeinschaft Deutscher Forschungszentren geförderte Energie-Allianz chemische Mehrphasenprozessebündelt Kompetenzen und Forschungsaktivitäten im Bereich der chemischen Verfahrenstechnik mit dem Ziel der Weiterentwicklung von Entwurfs- und Auslegungsmethoden, numerischen und experimentellen Techniken sowie neuer Messeverfahren zur Effizienzsteigerung chemischer Mehrphasenprozesse.
EAM Import::2019-03-13

Diffusion of gold nanoparticles in porous silica monoliths determined by dynamic light scattering - Wu, Wenchang; Cui, Junwei; Sultan, Umair; Gromotka, Lukas; Malgaretti, Paolo; Damm, Cornelia; Harting, Jens; Vogel, Nicolas; Peukert, Wolfgang; Inayat, Alexandra; Fröba, Andreas Paul (Journal of Colloid and Interface Science, 2023)
Hypothesis: The applicability of the dynamic light scattering method for the determination of particle diffusivity under confinement without applying refractive index matching was not adequately explored so far. The confinement effect on particle diffusion in a porous material which is relevant for particle chromatography has also not yet been fully characterized. Experiments: Dynamic light scattering experiments were performed for unimodal dispersions of 11-mercaptoundecanoic acid-capped gold nanoparticles. Diffusion coefficients of gold nanoparticles in porous silica monoliths were determined without limiting refractive index matching fluids. Comparative experiments were also performed with the same nanoparticles and porous silica monolith but applying refractive index matching. Findings: Two distinct diffusivities could be determined inside the porous silica monolith, both smaller than that in free media, showing a slowing-down of the diffusion processes of nanoparticles under confinement. While the larger diffusivity can be related to the slightly slowed-down diffusion of particles in the bulk of the pores and in the necks connecting individual pores, the smaller diffusivity might be related to the diffusion of particles near the pore walls. It shows that the dynamic light scattering method with a heterodyne detection scheme can be used as a reliable and competitive tool for determining particle diffusion under confinement.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Confinement; Diffusion; Dynamic light scattering; Gold nanoparticles; Porous material

Diffusivities in Binary Mixtures of [AMIM][NTf2] Ionic Liquids with the Dissolved Gases H2, He, N2, CO, CO2, or Kr Close to Infinite Dilution - Klein, Tobias; Piszko, Maximilian; Lang, Maren; Mehler, Julian; Schulz, Peter; Rausch, Michael Heinrich; Giraudet, Cédric; Koller, Thomas Manfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2020)
Ionic liquids (ILs) are interesting working fluids in many areas of chemical and energy engineering such as gas separation, catalysis, or energy storage. For the optimum design of related processes and apparatuses, the diffusion coefficient of gases dissolved in ILs is necessary, yet is often only known for a few selected gases. In this work, the thermal and mutual diffusivities in binary mixtures consisting of the gases hydrogen, helium, nitrogen, carbon monoxide, carbon dioxide, or krypton dissolved in the homologous series of the ILs [EMIM][NTf2], [HxMIM][NTf2], or [DcMIM][NTf2] were investigated by dynamic light scattering (DLS) and equilibrium molecular dynamics (EMD) simulations for temperatures between (298 and 423) K at conditions close to infinite dilution of the dissolved gas. Here, the Fick diffusion coefficient determined by DLS can be compared with the self-diffusion coefficient of the dissolved gases predicted by EMD simulations. For the latter, selected force fields (FFs) for the ILs available in literature were tested, for which the most suitable FF was modified by scaling the partial charges of all atoms with an IL-specific factor using experimental data for density, viscosity, and the self-diffusion coefficient of the pure ILs. On the basis of the modified FF, agreement of the calculated gas self-diffusion coefficients and the experimental Fick diffusion coefficients with an average absolute relative deviation of 12% was found. The Fick diffusion coefficient increases with decreasing molecular weight of the dissolved gas, with the exception of hydrogen and helium, which show an inverse behavior. In contrast to the trends observed for binary mixtures of the above gases dissolved in n-alkanes or 1-alcohols of varying alkyl chain length, the diffusion coefficients of the mixtures with the different ILs investigated in this study were found to be not significantly affected by the solvent viscosity.
CRIS-Team Scopus Importer:2020-07-24

Dimerization of ethene in a fluidized bed reactor using Ni-based Supported Ionic Liquid Phase (SILP) catalysts - Kohler, Florian; Gärtner, Konstantin; Hager, Veit; Haumann, Marco; Sternberg, Michelle; Wang, Xinjiao; Szesni, Normen; Meyer, Karsten; Wasserscheid, Peter (Catalysis: Science and Technology, 2014)
The complexes [(mall)Ni(dppanis)][SbF6] (mall = methallyl, dppanis = (2-methoxyphenyl)diphenylphosphine) 1, [(mall)Ni(PPh3OC10)][SbF6] (PPh3OC10 = (2-decyloxyphenyl)diphenylphosphine) 2, and [(mall)Ni(PPh3OdiMePh)][SbF6] (PPh3OdiMePh = (2-(2,6-dimethylphenoxy)phenyl)diphenylphosphine) 3 were immobilized as Supported Ionic Liquid Phase (SILP) catalysts and applied for the tandem dimerization/isomerization of ethylene to 2-butene in a fluidized bed reactor. The better heat removal in the fluidized bed improves the catalyst stability and allows for a more detailed investigation of the deactivation mechanism. Based on kinetic studies, a second order deactivation mechanism is proposed, in which two nickel complexes dimerize if the supply of ethene is insufficient.

Dimethyl ether/CO2 - a hitherto underestimated H2 storage cycle - Schühle, Patrick; Stöber, Robert; Semmel, M.; Schaadt, A.; Szolak, R.; Thill, S.; Alders, M.; Hebling, C.; Wasserscheid, Peter; Salem, O. (Energy and Environmental Science, 2023)
Large amounts of renewable energy will have to be stored and transported in the future. For this task, chemical hydrogen storage technologies are particularly suitable. In this paper, we show that the DME/CO2 storage cycle is especially promising for point-to-point transport of renewable hydrogen over long distances. Surprisingly, this technology has been neglected so far, as DME has been mostly discussed as a fuel substitute for internal combustion engines while the back transport of CO2 has not been considered in this context. Our study reveals that the similarity of the physico-chemical properties of DME and CO2 enables back-shipping of CO2 after hydrogen release in the same vessel that is used to transport DME. This leads to an overall technology that shows in our analysis considerable potential to outperform ammonia or methanol, which are intensively discussed as hydrogen vectors today. The proposed cycle is characterised in particular by comparatively high energy efficiency, reduced mass flows per ton of delivered hydrogen, lower water consumption at the hydrogen production site and lower toxicological risks.
CRIS-Team Scopus Importer:2023-08-11

Direct oxidation of benzene to phenol over hierarchical ZSM-5 zeolites prepared by sequential post synthesis modification - Shahid, Ameen; Lopez Orozco, Sofia; Marthala, Venkata; Hartmann, Martin; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2017)
Hierarchical zeolites were prepared by post synthesis treatments of commercial ZSM-5 zeolite (Sit Al = 13) involving alkali treatment, acid treatment, steam treatment, combination of acid-alkali treatments, and combination of steam-acid-alkali treatments. Various characterization techniques were employed to investigate the influence of each post synthesis treatment step on the structure, composition, porosity, acidity and iron species of the samples. The catalytic activity and selectivity of the post modified samples were also measured in the direct oxidation of benzene to phenol using nitrous oxide as an oxidising agent. The combination of steam-acid-alkali treatments of ZSM-5 zeolite exhibiting low Si/Al ratio lead to significant high level of mesoporosity with considerable preserved amount of microporosity that was not possible to achieve by the other treatment methods outlined above. ESR results reveal the homogeneous distribution of iron species when commercial MFI zeolite containing low amount of iron was steam treated. The modified iron species were not significantly altered by subsequent acid and alkali treatments, while the alkali treatment heals the destructed part of the zeolite that was produced by steam and acid treatments. These modifications in the pore structure and iron species led to excellent catalytic performance in the direct oxidation of benzene to phenol using nitrous oxide. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Hierarchical zeolite; Post synthesis modification; Direct oxidation of benzene; Iron species

Direct synthesis of non-breathing MIL-53(Al)(ht) from a terephthalate-based ionic liquid as linker precursor - Fischer, Marcus; Schwegler, Johannes; Paula, Carolin; Schulz, Peter; Hartmann, Martin (Dalton Transactions, 2016)
An organic imidazolium salt of terephthalic acid has been utilized as a linker precursor for the synthesis of an aluminum-based metal organic framework (MOF) with MIL-53(ht) structure. This material shows the predicted porosity in terms of nitrogen and hydrogen sorption without exhibiting the breathing effect typical for MIL-53 (Al) materials.

Dry reforming of methane over gallium-based supported catalytically active liquid metal solutions - Wolf, Moritz; de Oliveira, Ana; Taccardi, Nicola; Maisel, Sven; Heller, Martina; Khan Antara, Sharmin; Soegaard, Alexander; Felfer, Peter; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter (Communications Chemistry, 2023)
Gallium-rich supported catalytically active liquid metal solutions (SCALMS) were recently introduced as a new way towards heterogeneous single atom catalysis. SCALMS were demonstrated to exhibit a certain resistance against coking during the dehydrogenation of alkanes using Ga-rich alloys of noble metals. Here, the conceptual catalytic application of SCALMS in dry reforming of methane (DRM) is tested with non-noble metal (Co, Cu, Fe, Ni) atoms in the gallium-rich liquid alloy. This study introduces SCALMS to high-temperature applications and an oxidative reaction environment. Most catalysts were shown to undergo severe oxidation during DRM, while Ga-Ni SCALMS retained a certain level of activity. This observation is explained by a kinetically controlled redox process, namely oxidation to gallium oxide species and re-reduction via H2 activation over Ni. Consequentially, this redox process can be shifted to the metallic side when using increasing concentrations of Ni in Ga, which strongly suppresses coke formation. Density-functional theory (DFT) based ab initio molecular dynamics (AIMD) simulations were performed to confirm the increased availability of Ni at the liquid alloy-gas interface. However, leaching of gallium via the formation of volatile oxidic species during the hypothesised redox cycles was identified indicating a critical instability of Ga-Ni SCALMS for prolonged test durations.
CRIS-Team Scopus Importer:2023-10-27

Dynamic equilibria in supported ionic liquid phase (SILP) catalysis: in situ IR spectroscopy identifies [Ru(CO)xCly]n species in water gas shift catalysis - Bauer, Tanja; Stepic, Robert; Wolf, Patrick; Kollhoff, Fabian; Karawacka, Weronica; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Libuda, Jörg (Catalysis: Science and Technology, 2018)
Ru-based supported ionic liquid phase (SILP) systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). While previous studies suggest that Ru-carbonyl species play an important role in the mechanism, detailed knowledge on the catalytically active species is still missing. To identify these carbonyl complexes, we apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT). Investigations of an as-prepared [R(CO)3Cl2]2/ [C4C1C1Im]Cl/Al2O3 catalyst indicate splitting of the dimer induced by Cl−. Subsequently, an equilibrium between several [R(CO)xCly]n species is established, in which the IL serves as an effectively infinite Cl− reservoir. We find that the major species in the system freshly-prepared from [R(CO)3Cl2]2 is indeed [R(CO)3Cl3]−. A smaller amount of [R(CO)2Cl3]− and chloride-rich species [R(CO)2Cl4]2− or [RuCOCl4]2− are also found in the SILP. Similar Ru-carbonyl species are observed during carbonylation of RuCl3/ [C4C1C1Im]Cl/Al2O3, another potential WGSR catalyst. The response of [Ru(CO)3Cl2]2/[C4C1C1Im]Cl/Al2O3 to heating and/or CO dosing was probed in situ and the results confirm the presence of the equilibrium proposed above.
Keywords: SILP catalysis; in situ IR spectroscopy; [Ru(CO)xCly]n species

Dynamic power supply by hydrogen bound to a liquid organic hydrogen carrier - Fikrt, André; Brehmer, Richard; Milella, Vito-Oronzo; Müller, Karsten; Bösmann, Andreas; Preuster, Patrick; Alt, Nicolas; Schlücker, Eberhard; Wasserscheid, Peter; Arlt, Wolfgang (Applied Energy, 2017)

Dynamics of liquid-liquid systems based on linear thermodynamics of irreversible processes - Imam, Rayees Ahamed; Freund, Hannsjörg; Sundmacher, Kai (Computers & Chemical Engineering, 2011)
The use of non-equilibrium models for integrated processes involving liquid-liquid systems has increased in recent years. These processes often exhibit complex dynamic behavior. These dynamical systems still pose many open questions, e. g. with regard to the sources of multiple steady states (MSS). This article analyzes the effect of mass transfer on the MSS of these systems. A generalized non-equilibrium modeling approach based on linear thermodynamics of irreversible processes (LTIP) is presented, and the dynamics of the system is studied systematically. It is shown that the non-linearity present in even the simplest nonideal activity model acts as a source for MSS. The parameters that affect the solubility, e. g. temperature, can play a critical role on the existence of MSS in the system. A geometrical visualization of the MSS is also illustrated. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Phase splitting; Multiple steady states; Liquid-liquid system; Non-equilibrium model; Bifurcation analysis

Dynamic Viscosity of Tetracyanoborate- and Tricyanomethanide-Based Ionic Liquids by Dynamic Light Scattering - Bi, Shengshan; Koller, Thomas Manfred; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (Industrial & Engineering Chemistry Research, 2015)
Low-viscosity ionic liquids (ILs) based on the anions [B(CN)(4)](-) (tetracyanoborate) and [C(CN)(3)](-) (tricyanomethanide) are currently discussed as alternative working fluids for various applications. The dynamic viscosity of such ILs carrying [1-alky1-MIM](+) (1-alkyl-3-methylimidazolium) cations was investigated via determination of the translational particle diffusion coefficient by dynamic light scattering (DLS). The long-term stability of suspensions of different particles in the ILs, their particle diameters, and the influence of laser power on the measured particle diffusion coefficient for Semi-transparent ILs were studied. For temperatures from 283 to 353 K at atmospheric pressure, the dynamic viscosity of the four pure ILs forming stable suspensions was obtained with an uncertainty of less than 5% (k = 2) and agrees with literature. Absorption of CO2 at pressures up to 0.87 MPa induced a distinct decrease in the dynamic viscosity. Differences between the viscosities of the different systems can be explained by varying strength of molecular interactions.

Economic comparison of different electric fuels for energy scenarios in 2035 - Runge, Philipp; Sölch, Christian; Albert, Jakob; Wasserscheid, Peter; Zöttl, Gregor; Grimm, Veronika (Applied Energy, 2019)
Electric fuels (e-fuels) enable CO2-neutral mobility and are therefore an alternative to battery-powered electric vehicles. This paper compares the cost-effectiveness of Fischer-Tropsch diesel, methanol and Liquid Organic Hydrogen Carriers. The production costs of those fuels are to a large part driven by the energy-intensive electrolytic hydrogen production. In this paper, we apply a multi-level electricity market model to calculate future hourly electricity prices for various electricity market designs in Germany for the year 2035. We then assess the economic efficiency of the different fuels under various future market conditions. In particular, we use the electricity price vectors derived from an electricity market model calibrated for 2035 as an input for a mathematical model of the entire process chain from hydrogen production and chemical bonding to the energetic utilization of the fuels in a vehicle. Within this model, we perform a sensitivity analysis, which quantifies the impact of various parameters on the fuel production cost. Most importantly, we consider prices resulting from own model calculations for different energy market designs, the investment cost for the electrolysis systems and the carbon dioxide purchase price. The results suggest that the use of hydrogen, which is temporarily bound to Liquid Organic Hydrogen Carriers, is a favorable alternative to the more widely discussed synthetic diesel and methanol.<br
Keywords: Sector coupling; Electricity markets; Electric fuels; Hydrogen utilization; LOHC; Mobility

Economic comparison of electric fuels for heavy duty mobility produced at excellent global sites-a 2035 scenario - Runge, Philipp; Sölch, Christian; Albert, Jakob; Wasserscheid, Peter; Zöttl, Gregor; Grimm, Veronika (Applied Energy, 2023)
The transformation of economies worldwide towards climate neutrality will require not only renewable electricity but also climate-neutral energy carriers such as hydrogen and its derivatives. The production cost of electric fuels (e-fuels) are to a large extent driven by the energy-intensive electrolytic water splitting. The option of producing e-fuels in highly industrialized countries, as Germany, competes with production at international locations, with excellent conditions for renewable energies and thus very low levelized cost of green hydrogen and its derivatives. In this paper, we examine the economic efficiency of various imported e-fuels that are under consideration in different scenarios for the year 2035: Fischer-Tropsch diesel, methanol, and hydrogen transported as cryogenic liquid or in form of liquid organic hydrogen carriers. We develop a mathematical model that covers the entire process chain, from the production of the e-fuels at various excellent locations worldwide to the energetic utilization of the fuels in a heavy duty vehicle. We find that the choice of production site has a major impact on the mobility cost using the respective fuels. Under the selected boundary conditions and assumptions, methanol, cryogenic hydrogen, and liquid organic hydrogen carriers are the most favourable options for all seven locations examined. Which e-fuel is cheapest varies with the production site. Especially in case of diesel, the levelized cost of electricity determined by the full load hours of the applied renewable energy source have a huge impact. An LOHC-based system is shown to be less dependent on electricity source compared to other technologies due to its comparatively low electricity consumption. The length of the transportation route and the price of the filling station infrastructure, however, increase mobility cost for LOHC and LH2</sub
Keywords: Electric Fuels; Hydrogen Utilization; Hydrogen Import; LOHC; Mobility

Effective chirality transfer in ionic liquids through ion-pairing effects. - Schulz, Peter; Bösmann, Andreas; Wasserscheid, Peter; et al. (Angewandte Chemie International Edition, 2007)
Since every reaction at a prochiral ion must take place in close proximity to its counterion, it should be possible to transfer chiral information between the ions of an ionic liq. Indeed, the hydrogenation of a prochiral, keto-functionalized cation was found to proceed in the presence of (R)-camphorsulfonate in up to 80% ee. [on SciFinder(R)]
Keywords: chirality transfer ionic liq ion pairing

Effectiveness of catalyst passivation techniques studied in situ with a magnetometer - Wolf, Moritz; Fischer, Nico; Claeys, Michael (Catalysis Today, 2016)
Keywords: Passivation; Magnetometer; Oxide layer; Fischer-Tropsch catalyst; Cobalt catalyst

Effective n-octane isomerization under exceptionally mild conditions using a novel class of superacidic ionic liquids - Meyer, Carolin; Wasserscheid, Peter (Chemical Communications, 2010)
Superacidic chloroaluminate ionic liquids of the general formula [cation]Cl/AlCl(3)[X(AlCl(3)) > 0.5] + H(2)SO(4) effectively isomerize n-octane to form branched liquid hydrocarbon isomers. Due to the highly acidic character of the ionic liquid the reaction proceeds under extremely mild conditions in a liquid-liquid biphasic reaction mode leading to a minimum of undesired cracking side-reactions.

Effect of acid treatment on the chemical composition and the structure of Egyptian diatomite - Alyosef, Hallah Ahmad; Ibrahim, Suzan; Welscher, Julia; Inayat, Alexandra; Eilert, Andre; Denecke, Reinhard; Schwieger, Wilhelm; Muenster, Tom; Kloess, Gert; Einicke, Wolf-Dietrich; Enke, Dirk (International Journal of Mineral Processing, 2014)
In this study Egyptian diatomaceous earth from Kasr El-Sagha locality in El Fayium province, Egypt was used. A highly purified diatomite has been prepared successfully by using a two stage process. In the first stage, samples of Egyptian diatomite were subjected to several mechanical techniques (attrition scrubbing and hydrocyclone classification) to remove most of the accompanied gangue minerals like inorganic carbonate, silica sand, and clay. The fraction with a particle size of -45 mu m was then submitted to a thermo-chemical treatment. This second stage started with a calcination of the diatomite samples at 1023 K for 1 h. Three modified forms of diatomite were then prepared by hot acidification of the calcined diatomite samples with aqua regia (5 M HCl + 5 M HNO3), 5 M sulphuric acid or 5 M hydrochloric acid. The refined products were characterized by X-ray diffraction, X-ray fluorescence, low temperature nitrogen adsorption, mercury intrusion and scanning electron microscopy. Silica materials with high purity (>96 wt.% SiO2) and an accessible and interconnected mesopore structure could be obtained. Additionally, all samples displayed a large amount of macropores of about 1 mu m diameter and a broad distribution of larger interstitial macropores. The treatment with hydrochloric acid led to products with a specific surface area between 120 and 150 m(2) g(-1) and 63 wt.% of amorphous phase. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Diatomite; Acid modification; Purity; Pore structure of amorphous biogenic; silica products

Effect of ball milling on the structural and textural features of MCM-41 mesoporous material - Abu-Zied, Bahaa M.; Schwieger, Wilhelm; Asiri, Abdullah M. (Microporous and Mesoporous Materials, 2015)
This paper reports on the ball-milling process and its influence on the structural, textural and morphological features of mesoporous MCM-41 material. MCM-41 and the as-milled products were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), N-2-adsorption, a field emission scanning electron microscope (FE-SEM) and a thermogravimetric analysis (TGA). The XRD showed that the mechanical treatment of MCM-41 in a ball mill leads to a gradual crystallinity loss with time until 2 h, and complete crystallinity loss was observed after 4 h of ball milling. N-2 sorption measurements revealed a sharp surface area decrease as well as mesoporosity loss accompanying the milling process. The FE-SEM investigation demonstrated severe damage of the spherical morphology of MCM-41 upon milling for 8 h. Moreover, it was found that these structural, textural and morphological changes strongly affected the water content of the milled MCM-41 material. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: MCM-41; Ball milling; Mesoporous material; Texture analysis

Effect of Conversion, Temperature and Feed Ratio on In2O3/In(OH)3 Phase Transitions in Methanol Synthesis Catalysts: A Combined Experimental and Computational Study - Kampe, Philipp; Wesner, Anne; Schühle, Patrick; Hess, Franziska; Albert, Jakob (ChemPlusChem, 2023)
Catalytic hydrogenation of CO2 to methanol has attracted lots of attention as it makes CO2 useable as a sustainable carbon source. This study combines theoretical calculations based on the dummy catalytic cycle model with experimental studies on the performance and degradation of indium-based model catalysts for methanol synthesis. In detail, the reversibility of phase transitions in the In2O3/In(OH)3 system under industrial methanol synthesis conditions are investigated depending on conversion, temperature and feed ratio. The dummy catalytic cycle model predicts a peculiar degradation behavior of In(OH)3 at 275 °C depending on the water formed either by methanol synthesis or the competing reverse water-gas-shift reaction. These results were validated by dedicated experimental studies confirming the predicted trends. Moreover, X-ray diffraction and thermogravimetric analysis proved the ensuing phase transition between the indium species. Finally, the validated model is used to predict how hydrogen drop out will affect the stability of the catalyst and derive practical strategies to prevent irreversible catalyst degradation.
CRIS-Team Scopus Importer:2023-09-22
Keywords: catalyst degradation; CO; dummy catalytic cycle; indium; methanol synthesis

Effect of excess silicate on the structure formation and textural properties of MTS materials - Inayat, Alexandra; Kuhnt, Andreas; Schwieger, Wilhelm; Einicke, Wolf-Dietrich; Kullmann, Jens; Enke, Dirk (Journal of Porous Materials, 2011)
The synthesis of micellar templated silica (MTS) materials has been conducted with different SiO2/CTAB molar ratios for two different cetyltrimethylammoniumbromide (CTAB) concentrations of 0.02 and 0.07 M to examine the structure formation for cubic (SBA-1) as well as for hexagonal (SBA-3) surfactant arrangement in acidic reaction medium with increasing silicate excess. Reaction products were analyzed with X-ray diffraction, N-2 physisorption and TG-MS. It was found that an increase of the silicate concentration leads to the formation of additional silica gel in the resulting MTS material, which causes not only a decrease of specific surface area and pore volume, but also of the mesopore diameter. The latter effect is explained by a proposed embedding theory. Furthermore, with increasing silicate content in the synthesis mixture a phase transformation from hexagonal to cubic pore arrangement was found for the CTAB concentration of 0.07 M and the maximum SiO2/CTAB molar ratio for ordered pore arrangement has been determined.
Keywords: Micellar templated silica (MTS); Silicate excess; SBA-1; SBA-3; Pore arrangement; Textural properties

Effect of microwave power on the thermal genesis of Co3O4 nanoparticles from cobalt oxalate micro-rods - Schwieger, Wilhelm; Abu-Zied, Bahaa M.; Bawaked, S. M.; Kosa, S. A. (Applied Surface Science, 2015)
This study focuses on investigating the influence of microwave power (MWP) change on the morphology and size of Co3O4 nanoparticles (NPs), which was obtained from the thermal decomposition of cobalt oxalate precursor. The oxalate precursor was prepared via the microwave-assisted route in the presence of cetyltrimethylammonium bromide (CTAB) employing an MWP of 280 and 700W. Physicochemical properties of the prepared solids were characterized by means of X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and thermogravimetry-differential thermal analyses (TGA-DTA). The results obtained indicated that the applied MWP has a crucial effect in controlling the morphology and the size of CoC2O4 center dot 2H(2)O as well as Co3O4 NPs. Acicular- and rod-like morphologies of both phases were obtained employing an MWP of 280 and 700W during the preparation, respectively. Further, both the prepared Co3O4 nanoneedles and nanorods are composed of net-like structure of interconnected nanocapsules. Moreover, although all the routes led to the same phase, additional difference existed in terms of surface Co2+ and hydroxyl-carbonate concentrations. Lower MWP favors high Co2+ and low cobalt hydroxyl-carbonate surface concentrations. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Co3O4; Spinel oxide; Microwave-assisted synthesis; Nanomaterials

Effect of Pr, Sm, and Tb Doping on the Morphology, Crystallite Size, and N2O Decomposition Activity of Co3O4 Nanorods - Abu-Zied, Bahaa M.; Bawaked, Salem M.; Kosa, Samia A.; Schwieger, Wilhelm (Journal of Nanomaterials, 2015)
Cobalt(II, III) oxide, Co3O4, is a promising catalyst for nitrous oxide direct decomposition. In this paper we report effect of doping with some rare earth (RE) elements (Pr, Sm, and Tb) on the morphology and crystallite size of Co3O4 nanorods. The various precursors (RE/Co oxalates) were prepared via the microwave assisted method and subsequent calcination. The decomposition pathway of these precursors was followed using thermogravimetric analysis (TGA). Based on thermal analysis results, Pr-, Sm-, and Tb-doped Co3O4 samples were obtained via the calcination in static air at 500 degrees C for their oxalate precursors. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and hydrogen temperature programmedreduction (H-2-TPR) were used to characterize the RE-doped cobalt oxide catalysts. The activity of the prepared catalysts was investigated for N2O direct decomposition and compared with that of the undoped Co3O4 catalyst. It was shown that the promoted Co3O4 catalysts revealed higher activity compared to the unpromoted one. The dependence of the activity on both the catalysts particle size and the reduction behaviour was discussed.

Effect of some rare earth oxides doping on the morphology, crystallite size, electrical conductivity and N2O decomposition activity of CuO catalyst - Schwieger, Wilhelm; Bawaked, S. M.; Kosa, S. A.; Abu-Zied, Bahaa M. (International Journal of Electrochemical Science, 2016)
The present work presents the results of direct catalytic decomposition of nitrous oxide over CuO and its Pr-, Sm- and Tb-promoted catalysts. These catalysts were prepared by the microwave assisted precipitation method, using oxalic acid as precipitant, and subsequent calcination at 500 °C. X-ray diffraction (XRD) was used for identification of the composition of the dried oxalate precursors and their calcination products. Thermogravimetric analysis (TGA) was used to follow up the thermal stability of the prepared precursors. The obtained catalysts were characterized by Fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), transmission electron microscopy, electrical conductivity and (TEM) H temperature programmed reduction (H-TPR). An enhancement effect of the added rare earth elements was observed during NO decomposition over the prepared catalysts Assessment of the de-NO activity was discussed based on the electrical conductivity as well as the H-TPR results.
Keywords: CuO catalyst; Greenhouse gases; N2O decomposition; Nitrous oxide; RE promotedCuO

Effect of the degree of hydrogenation on the viscosity, surface tension, and density of the liquid organic hydrogen carrier system based on diphenylmethane - Schmidt, Patrick; Kerscher, Manuel; Klein, Tobias; Jander, Julius Hans; Bioucas, Francisco; Rüde, Timo; Li, Shao; Stadelmaier, Monika; Hanyon, Samantha; Fathalla, Ramy; Bösmann, Andreas; Preuster, Patrick; et al. (International Journal of Hydrogen Energy, 2022)
For the efficient design of hydrogenation and dehydrogenation processes, a comprehensive database for the viscosity, surface tension, and density of mixtures of the diphenylmethane-based liquid organic hydrogen carrier system and the pure intermediate cyclohexylphenylmethane measured by complementary optical and conventional methods and calculated by molecular dynamics simulations at process-relevant temperatures up to 623 K is presented. The simulations employ self-developed force fields including a new one for cyclohexylphenylmethane and reveal surface enrichment and orientation effects influencing the surface tension. Relatively simple correlation and prediction approaches yield accurate representations as function of temperature and degree of hydrogenation (DoH) of the mixtures with average absolute relative deviations (AARD) of 0.07% for the density and 2.9% for the surface tension. Application of the extended hard sphere theory considering the presented accurate density data allows capturing the highly nonlinear DoH-dependent behavior of the dynamic viscosity with an AARD of 2.9%. (c) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density; Experiment; LOHC mixtures; Modeling; Surface tension; Viscosity

Effect of the Motion Pattern on the Turbulence Generated by an Active Grid - Herbert, Meike; Skeledzic, Tanja; Lienhart, Hermann; Ertunc, Özgür (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2021)
In the field of turbulence research, many experiments are performed using turbulence generated under reproducible conditions. In the past mostly static grids having a fixed blockage were adopted, but in order to generate turbulence with high intensity and high turbulence Reynolds numbers, so called active grids can be used. Therefore, an experimental study has been carried out to investigate the effect of the motion pattern on the turbulence generated by an active grid with individually controllable paddles in the wind tunnel. Measurements were performed using the hot-wire technique. In comparison to former experiments, modifications of the active grid had been made concerning the arrangement of the paddles. The results show that the homogeneity of the turbulence could be improved using the modified grid. Turbulence Reynolds numbers could reach values up to 540. In order to produce even higher integral time scales or higher turbulence Reynolds numbers, synchronous movement of adjacent paddles was tested but did not show the intended improvements. In this paper, the results of the experimental study are presented in more detail.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Active grid; Experimental study; Turbulence

Effect of the structure and morphology of natural, synthetic and post-processed graphites on their dispersibility and electronic properties - Kozhemyakina, Nina; Eigler, Siegfried; Inayat, Alexandra; Schwieger, Wilhelm; Hirsch, Andreas; Dinnebier, Robert E. (Fullerenes Nanotubes and Carbon Nanostructures, 2013)
Twenty-two different graphite grades of the families natural, synthetic, intercalated, expanded, amorphous, and turbostratic graphite, as well as platelets and activated carbon, were analyzed on their dispersibility in N-methylpyrrolidone, cyclohexylpyrrolidone and water-sodium cholate solution. They were characterized for their properties (grain size, density, purity, surface area, pH in water) and morphology. Thermogravimetric analysis, Raman spectroscopy studies, and electrical conductivity measurements were also used. XRPD followed by a Rietveld refinement provided information on the amounts of the rhombohedral (3R) and hexagonal (2H) phases for the crystalline part of the material and the interlayer distances. The properties of graphites favoring better dispersibility are: small grain size and bulk density, neutral pH in water. The electrical conductivity in inversely proportional to the Raman D-band intensity and is highest for the graphites with shortest interlayer spacing. The D-, G- and 2D-bands in the Raman spectra of graphites are in an exponential relation. © 2013 Copyright Taylor and Francis Group, LLC.

Effects of Nd-, Pr-, Tb- and Y-doping on the structural, textural, electrical and N2O decomposition activity of mesoporous NiO nanoparticles - Abuzied, Bahan Mohamed; Bawaked, Salem M.; Kosa, Samia A.; Ali, T.T.; Schwieger, Wilhelm; Aqlan, F.M. (Applied Surface Science, 2017)
Recently, nickel oxide, NiO, promoted with various dopants showed an interesting activity behavior in N2O direct decomposition. In this paper, the activity of a series of rare earth (Nd, Pr, Tb and Y) doped NiO catalysts was investigated for this reaction. These catalysts have been prepared by the calcination of their corresponding oxalate mixtures, which have been synthesized via the microwave-assisted precipitation route using oxalic acid as precipitant. Characterization of the obtained catalysts was carried out by using various physico-chemical techniques including TGA, FT-IR, XRD, FE-SEM, TEM, TPR, XPS and electrical conductivity. The results obtained revealed the nanocrystalline nature of the prepared catalysts. Moreover, the presence of the various dopants has led to a noticeable decrease of the NiO crystallites size, mesoporosity development and an increase of its surface area and pore volume. There is a substantial activity increase upon doping NiO with the various rare earth oxides. Such activity increase is associated with the structural modifications as well as the electrical conductivity increase of these catalysts. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Greenhouse gas; Nitrous oxide; Mesoporous RE-NiO; N2O decomposition; Promoted-NiO; Rare earth oxides

Efficient calculation of constraint back-offs for optimization under uncertainty: A case study on maleic anhydride synthesis - Maußner, Johannes; Freund, Hannsjörg (Chemical Engineering Science, 2018)
In the present work we propose an efficient and general algorithm for optimization under uncertainty based on the work of Srinivasan et al. (2003). We use specialized cubature rules to speed up the uncertainty propagation step which results in a significant reduction of the overall computational effort. The approach is illustrated by studying the optimal design of a fixed bed reactor for the synthesis of maleic anhydride from raffinate II feedstock, where the amount of n-butane and n-butenes in the feed is assumed to be uncertain. Applying the algorithm results in a robustified reactor design which shows significantly less temperature constraint violations and runaway conditions while still satisfying reactor performance criteria such as minimally required conversion and maximum allowable pressure drop.
Keywords: Reaction engineering; Reactor optimization; Maleic anhydride; Optimization under uncertainty; Cubature rules

Efficient hydrogen release from perhydro-N-ethylcarbazole using catalyst-coated metallic structures produced by selective electron beam melting - Peters, Willi; Eypasch, Martin; Frank, T.; Schwerdtfeger, Jan; Körner, Carolin; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2015)
A particularly suitable reactor concept for the continuous dehydrogenation of perhydro-N-ethylcarbazole in the context of hydrogen and energy storage applications is described. The concept addresses the fact that dehydrogenation is a highly endothermic gas evolution reaction. Thus, for efficient dehydrogenation a significant amount of reaction heat has to be provided to a reactor that is essentially full of gas. This particular challenge is addressed in our study by the use of a catalyst-coated (Pt on alumina), structured metal reactor obtained by selective electron beam melting. The so-obtained reactor was tested both as a single tube set-up and as a Hydrogen Release Unit (HRU) with ten parallel reactors. In stationary operation, the HRU realized a hydrogen release capacity of 1.75 kW(therm) (960 W-el in a subsequent fuel cell) with up to 1.12 g(H2) min(-1) g(Pt)(-1) and a power density of 4.32 kW(el) L-1 of HRU reactor.

Electrochemical characterization of 1-ethyl-3-methylimidazolium thiocyanate and measurement of triiodide diffusion coefficients in blends of two ionic liquids - Zistler, Markus; Schreiner, Christian; Wachter, Philipp; Wasserscheid, Peter; Gerhard, Dirk; Gores, Heiner J. (International Journal of Electrochemical Science, 2008)
According to literature, binary mixtures of ionic liquids (ILs) such as 1-methyl-3-propylimidazolium iodide (MPII) as an iodide source and another IL of low viscosity such as 1-ethyl-3- methylimidazolium thiocyanate (EMISCN) may be used to increase the diffusion coefficients of redox-active species (I-/I3 -). As dye-sensitized solar cells (DSCs) are diffusion limited a better performance may result with blends when compared to cells based on MPII alone. In order to learn more about EMISCN and its blends with MPII, we electrochemically characterized this IL and measured diffusion coefficients of triiodide in binary mixtures containing EMISCN by polarization and impedance studies at thin layer cells with a distance between Pt-electrodes of about 30 to 40 μm. The electrochemical windows of the used ILs were measured by cyclic voltammetry (CV) and compared to those of other ILs, recently investigated by us. © 2008 by ESG.
Keywords: Cyclic voltammetry; Diffusion measurement; Dye-sensitized solar cell; Electrochemical stability; Ionic liquids

Electrochemically Triggered Energy Release from an Azothiophene-Based Molecular Solar Thermal System - Franz, Evanie; Kunz, Anne; Oberhof, Nils; Heindl, Andreas H.; Bertram, Manon; Fusek, Lukáš; Taccardi, Nicola; Wasserscheid, Peter; Dreuw, Andreas; Wegner, Hermann A.; Brummel, Olaf; Libuda, Jörg (Chemsuschem, 2022)
Molecular solar thermal (MOST) systems combine solar energy conversion, storage, and release in simple one-photon one-molecule processes. Here, we address the electrochemically triggered energy release from an azothiophene-based MOST system by photoelectrochemical infrared reflection absorption spectroscopy (PEC-IRRAS) and density functional theory (DFT). Specifically, the electrochemically triggered back-reaction from the energy rich (Z)-3-cyanophenylazothiophene to its energy lean (E)-isomer using highly oriented pyrolytic graphite (HOPG) as the working electrode was studied. Theory predicts that two reaction channels are accessible, an oxidative one (hole-catalyzed) and a reductive one (electron-catalyzed). Experimentally it was found that the photo-isomer decomposes during hole-catalyzed energy release. Electrochemically triggered back-conversion was possible, however, through the electron-catalyzed reaction channel. The reaction rate could be tuned by the electrode potential within two orders of magnitude. It was shown that the MOST system withstands 100 conversion cycles without detectable decomposition of the photoswitch. After 100 cycles, the photochemical conversion was still quantitative and the electrochemically triggered back-reaction reached 94 % of the original conversion level.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Electrochemistry; Energy Storage; Photochemistry; Photoswitches; Solar Thermal Fuels

Electrophoretic co-deposition of chitosan and graphene oxide results in antibacterial coatings for medical applications - Metze, Anke-Lisa; Pishbin, Fatemehsadat; Ryan, Mary P.; Seuß, Sigrid; Diba, Mani; Shaffer, Milo S P; Boccaccini, Aldo R. (Key Engineering Materials, 2015)
Chitosan - graphene oxide (GO) composite coatings intended for antibacterial applications were obtained by cathodic electrophoretic deposition (EPD) on stainless steel. The coatings were characterized using SEM, FTIR, contact angle and roughness measurements and by antibacterial studies against E.coli. The coating was observed to consist of a polymer matrix with embedded, agglomerated graphene oxide sheets. A decrease in bacteria cell viability of at least 50 % was measured on the chitosan - GO surface in comparison to uncoated stainless steel.
Keywords: Antibacterial; Chitosan; Electrophoretic deposition; Graphene oxide

Electrophoretic Deposition of Boehmite on Additively Manufactured, Interpenetrating Periodic Open Cellular Structures for Catalytic Applications - Do, Giang; Stiegler, Thomas; Fiegl, Markus; Adler, Lucas; Körner, Carolin; Bösmann, Andreas; Freund, Hannsjörg Dieter; Schwieger, Wilhelm; Wasserscheid, Peter (Industrial & Engineering Chemistry Research, 2017)
Our contribution demonstrates that the combination of additive manufacturing and electrophoretic deposition offers great potential for the future manufacturing of tailor-made catalytic structures for continuous flow applications. A new protocol for the controlled and homogeneous coating of both electrodes of interpenetrating porous open cell structures (interPOCS) with layers of boehmite is presented. Moreover, it has been found that by applying different coating voltages in an electrophoretic deposition (EPD) process, the properties of the obtained coating can be fine-tuned with respect to layer thickness, density, and porosity. This offers very interesting options for optimizing the catalysis-relevant properties from two sides by the use of the special interPOCS support design and by adjusting the coating through the parameters of the EPD coating process.

Elucidating activating and deactivating effects of carboxylic acids on polyoxometalate-catalysed three-phase liquid–liquid-gas reactions - Poller, Maximilian J.; Bönisch, Simon; Bertleff, Benjamin; Raabe, Jan Christian; Görling, Andreas; Albert, Jakob (Chemical Engineering Science, 2022)
Three-phase liquid–liquid gas reactions are promising strategies to combine highly active and selective homogeneous-catalysed oxidation reactions with in-situ product isolation. Several approaches like the three-phasic oxidation of biomass to formic acid (OxFA process) or the three-phasic extraction-coupled oxidative desulfurization (ECODS process) of fuels have been developed. Hereby, an aqueous polyoxometalate (POM) catalyst solution in combination with molecular oxygen as oxidant is used. However, contrary effects on the oxidation performance of the POM-catalyst were observed for different carboxylic acids as reaction products or intermediates. By using model calculations employing Density-Functional Theory (DFT) in combination with magnetic and optical spectroscopy, we could explain the experimental observations that oxalic acid activates the POM catalyst and therefore promotes its oxidation performance while acetic and especially formic acid form stable complexes with the active centres and therefore inhibit the oxidation activity. These findings greatly improve the understanding of POM-acid complexes and their effect on the catalytic performance.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Catalyst activation/deactivation; Density-functional calculations; Polyoxometalates; Spectroscopic investigations; Three-phase liquid–liquid-gas reactions

Elucidating the ionic liquid distribution in monolithic SILP hydroformylation catalysts by magnetic resonance imaging - Marinkovic, Jakob Maximilian; Benders, Stefan; Garcia-Suarez, Eduardo J.; Weiß, Alexander; Gundlach, Carsten; Haumann, Marco; Küppers, Markus; Blümich, Bernhard; Fehrmann, Rasmus; Riisager, Anders (RSC Advances, 2020)
Monolithic silicon carbide supported ionic liquid-phase (SILP) Rh-catalysts have very recently been introduced for gas-phase hydroformylation as an important step toward industrial upscaling. This study investigates the monolithic catalyst system in combination with different impregnation procedures with non-invasive magnetic resonance imaging (MRI). The findings were supported by X-ray microtomography (micro-CT) data of the monolithic pore structure and a catalytic performance test of the catalyst system for 1-butene gas-phase hydroformylation. MRI confirmed a homogeneous impregnation of the liquid phase throughout the full cross-section of the cylindrical monoliths. Consistent impregnations from one side to the other of the monoliths were achieved with a stabilizer in the system that helped preventing inhomogeneous rim formation. External influences relevant for industrial application, such as long-term storage and temperature exposure, did not affect the homogeneous liquid-phase distribution of the catalyst. The work elucidates important parameters to improve liquid-phase catalyst impregnation to obtain efficient monolithic catalysts for industrial exploitation in gas-phase hydroformylation as well as other important industrial processes.
CRIS-Team Scopus Importer:2020-06-09

Enduring liquid repellency through slippery ionic liquid-infused organogels - Salbaum, Tobias; Galvan, Yaraset; Haumann, Marco; Wasserscheid, Peter; Zarraga, Ramon; Vogel, Nicolas (Journal of Materials Chemistry A, 2021)
Lubricant-infused repellent coatings provide efficient repellency against contamination as the lubricant avoids direct contact between the surface and any contaminant to be repelled. Here, we address two mechanisms that potentially cause failure of the coating by loss of the liquid lubricant, and present a strategy for long-lasting coatings. We use ionic liquids as lubricants with extremely low vapor pressure. These are confined to the underlying substrate by means of functionalized polymeric gel that matches the chemical structure of the ionic liquids and thereby maximizes their molecular interactions. We use pentafluorophenol-based active ester polymers to provide a versatile platform that allows a convenient post-synthetic functionalization of the polymer network. The matching functional groups to efficiently bind a desired ionic liquid can thus be introduced via their amine-functionalized analogues, which we demonstrate for imidazole- and phosphonium-based molecules. We copolymerize benzophenone methacrylate for surface attachment and gel formation in one step. At 85 °C the surface and repellency properties remained constant for several months, outperforming thick, swollen PDMS films as the gold standard of lubricant-infused coatings.
CRIS-Team Scopus Importer:2021-02-26

Energetics of Technical Integration of 2-Propanol Fuel Cells: Thermodynamic and Current and Future Technical Feasibility - Braun, Katharina; Wolf, Moritz; de Oliveira, Ana; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon; Weiß, Lukas; Wensing, Michael (Energy Technology, 2022)
2-Propanol/acetone is a promising liquid organic hydrogen carrier system for fuel cell reactions. Herein, six different concepts for a 2-propanol/acetone fuel cell system are evaluated in MATLAB simulation with respect to their thermodynamic integration and technical feasibility. Four of the concepts use a direct 2-propanol fuel cell while the other two first release molecular hydrogen from 2-propanol and subsequently use a hydrogen fuel cell. The presented liquid phase 2-propanol fuel cell concept is thermodynamically feasible but cannot be realized technically using commercial Nafion membranes, due to membrane dissolution by the 2-propanol/acetone/water fuel mixture. Gaseous 2-propanol fuel cells imply a high heating requirement for the evaporation of the fuel. A direct high-temperature fuel cell using 2-propanol is thermodynamically feasible because there is less water in the overall system but is not technically feasible because of the esterification of phosphoric acid. A very interesting option is the conversion of gaseous 2-propanol to pressurized hydrogen in an electrochemical pumping step followed by a hydrogen fuel cell, because here the waste heat of a sufficiently hot hydrogen fuel cell can drive the 2-propanol evaporation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: 2-propanol fuel cell system; balance of plant; energy balancing; system integration; technical integration

Energieversorgung über flüssige Wasserstoffträger - Arlt, Wolfgang; Wasserscheid, Peter (Chemie Ingenieur Technik, 2012)

Energy storage in residential and commercial buildings via Liquid Organic Hydrogen Carriers (LOHC) - Teichmann, Daniel; Stark, Katharina; Müller, Karsten; Zöttl, Gregor; Wasserscheid, Peter; Arlt, Wolfgang (Energy and Environmental Science, 2012)
This contribution proposes the usage of Liquid Organic Hydrogen Carriers (LOHC) for the establishment of a decentralised energy storage network. Due to the continually increasing amount of renewable energy within the power grid, in particular in countries of the European Union, a huge demand for storage capacities develops that can hardly be met by large-scale systems alone. Because of their high storage density and good manageability LOHC substances permit the local storage of excess energy in residential and commercial buildings. Following the approach of a CHP system ('combined heat and power' or more precisely a 'combined heat and storage' system), thermal losses from the storage processes can be used for heating (and cooling) purposes in order to increase the overall efficiency. An evaluation of the economic feasibility identifies possible approaches to generate income from storage operation. The usage of exhaust heat for heating proves to significantly support the business case by providing a considerable financial contribution that is usually not exploitable for centralised storage units. © 2012 The Royal Society of Chemistr
WiSo-Import:2015-03-26:5048

Enhanced Activity and Selectivity in Catalytic Methanol Steam Reforming by Basic Alkali Metal Salt Coatings - Kusche, Matthias Manfred; Enzenberger, Florian; Bajus, Stephanie; Niedermeyer, Heiko Jannes; Bösmann, Andreas; Kaftan, Andre; Laurin, Mathias; Libuda, Jörg; Wasserscheid, Peter (Angewandte Chemie International Edition, 2013)
Pt on alumina catalysts can be used for converting methanol and water into hydrogen and carbon dioxide, for applications such as hydrogen storage. Both the activity and selectivity could be enhanced by coating these materials with a thin layer of a molten salt mixture of Li/K/Cs acetate. Potassium doping was indentified by DRIFTS measurements to be an important factor for the boost in catalyst performance.

Enhanced activity and selectivity in n-octane isomerization using a bifunctional SCILL catalyst - Meyer, Carolin; Hager, Veit; Schwieger, Wilhelm; Wasserscheid, Peter (Journal of Catalysis, 2012)
Bifunctional Solid Catalyst with Ionic Liquid Layer (SCILL) systems are presented and applied in the skeleton isomerization of n-octane in a slurry-phase reaction mode. It is demonstrated that Pt on silica, coated with a thin film of acidic chloroaluminate ionic liquid exhibits remarkable catalytic performance under mild conditions in the presence of hydrogen. Interestingly, both selectivity and activity of n-octane isomerization increase in these systems as a function of hydrogen pressure. This does not only suggest a hydrogenation activity of the catalytic Pt-centers embedded in the strongly Lewis acidic ionic liquid but also a significant increase in the proton acidity in this system as a function of the hydrogen pressure.

Enhancing aromatics and olefins yields in thermo-catalytic pyrolysis of LDPE over zeolites: Role of staged catalysis and acid site density of HZSM-5 - Inayat, Amer; Inayat, Alexandra; Schwieger, Wilhelm; Sokolova, Barbora; Lestinsky, Pavel (Fuel, 2022)
The present work deals with the thermo-catalytic pyrolysis of LDPE (low-density polyethylene) in lab-scale one- and two-stage test rigs over HZSM-5 catalysts featuring different acid site densities. In the first part of this work, the influence of catalyst-to-feed ratio and temperature (in conjunction with the acid site density of HZSM-5) on the product distribution was studied with an aim to identify the optimum operating conditions for the enhanced production of aromatics and light olefins. For this purpose, one-stage thermo-catalytic pyrolysis was performed in which catalysts were mixed with LDPE pellets for in-situ catalysis. In the one-stage catalytic pyrolysis, the catalyst sample with the highest acid site density gave the highest concentration of aromatics (ca. 55%) in the pyrolysis oil with a mono-aromatics fraction of over 50% that consisted mainly of BTEX (benzene, toluene, ethylbenzene and xylenes) compounds. The highest C2-C4 olefins concentration (ca. 65%) in the pyrolysis gas was obtained when the sample with the lowest acid site density was used. In the two-stage catalytic pyrolysis (ex-situ catalysis), the concentration of aromatics in the pyrolysis oil reached over 77% with a mono-aromatics fraction of ca. 72% that contained mainly BTEX compounds, when the most acidic catalyst was used. When the catalyst with the lowest number of strong acid sites was employed, the high content of C2-C4 olefins in the pyrolysis gas remained almost independent of the reactor configuration. These findings might provide important new insights for the chemical recycling of plastic wastes.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Chemical recycling; Polyethylene; Pyrolysis; Thermo-catalytic process; Waste management; Zeolite catalyst

Enhancing task specific ionic liquids' thermal stability by structural modification. - Schulz, Peter; Bösmann, Andreas; Wasserscheid, Peter (Monatshefte für Chemie, 2007)
Thermal retro-Michael decompn. of task specific ionic liqs. (TSILs) was efficiently suppressed by hydrogenation of the oxobutyl side chain yielding a hydroxy-functionalized TSIL. [on SciFinder(R)]
Keywords: task specific ionic liq thermal decompn suppression hydrogenation

Enhancing the feasibility of Pd/C-catalyzed formic acid decomposition for hydrogen generation - catalyst pretreatment, deactivation, and regeneration - Kosider, Axel; Blaumeiser, Dominik; Schötz, Simon; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter; Libuda, Jörg; Bauer, Tanja (Catalysis: Science and Technology, 2021)
Formic acid decomposition (FAD) generates H-2 at low temperatures. However, many known catalyst systems suffer from deactivation due to competing side reactions during FAD. In this work, we focus on the origins of the deactivation of Pd catalysts but also on protocols which allow for reactivation of this precious metal catalyst. We combined batch experiments with results from in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). We find that CO adsorbates block catalytic sites and deactivate the Pd catalyst. Oxidative treatment lifts this inhibition. Additionally, our results show that oxidative pretreatment activates the Pd catalyst, whereas reduction leads to a catalyst which is essentially inactive for FAD.
CRIS-Team WoS Importer:2021-05-28

Environmental and health impact assessment of Liquid Organic Hydrogen Carrier (LOHC) systems - challenges and preliminary results - Markiewicz, M.; Zhang, Y. Q.; Bösmann, Andreas; Brückner, Nicole; Thöming, J.; Wasserscheid, Peter; Stolte, S. (Energy and Environmental Science, 2015)
Liquid Organic Hydrogen Carrier (LOHC) systems offer a very attractive way to store and transport hydrogen, a technical feature that is highly desirable to link unsteady energy production from renewables with the vision of a sustainable, CO2-free, hydrogen-based energy system. LOHCs can be charged and discharged with considerable amounts of hydrogen in cyclic, catalytic hydrogenation and dehydrogenation processes. As their physico-chemical properties are very similar to diesel, today's infrastructure for liquid fuels can be used for their handling thus greatly facilitating the step-wise transition from today's fossil system to a CO2 emission free energy supply for both, stationary and mobile applications. However, for a broader application of these liquids it is mandatory to study in addition to their technical performance also their potential impact on the environment and human health. This paper presents the first account on the toxicological profile of some potential LOHC structures. Moreover, it documents the importance of an early integration of hazard assessment in technology development and reveals for the specific case of LOHC structures the need for additional research in order to overcome some challenges in the hazard assessment for these liquids.

Ethene/Ethane and Propene/Propane Separation via the Olefin and Paraffin Selective Metal-Organic Framework Adsorbents CPO-27 and ZIF-8 - Böhme, Ulrike; Barth, Benjamin; Paula, Carolin; Kuhnt, Andreas; Schwieger, Wilhelm; Mundstock, Alexander; Caro, Juergen; Hartmann, Martin; Hartmann, Martin (Langmuir, 2013)
Two types of metal-organic frameworks (MOFs) have been synthesized and evaluated in the separation of C-2 and C-3 olefins and paraffins; Whereas Co-2(dhtp) (=Co-CPO-27 = Co-MOF-74) and Mg-2(dhtp) show an adsorption selectivity for the olefins ethene and propene over the paraffins ethane and propane, the zeolitic imidazolate framework ZIF-8 behaves in the opposite way and preferentially adsorbs the alkane. Consequently, in break-through experiments, the olefins or paraffins, respectively, can be separated.

Ethene-induced temporary inhibition of grubbs metathesis catalysts - Scholz, Judith; Loekman, Soebiakto; Szesni, Normen; Hieringer, Wolfgang; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter (dvanced Synthesis & Catalysis, 2011)
Grubbs-type catalysts were immobilized in form of supported ionic liquid phase (SILP) materials and applied in the gas-phase cross-metathesis of various substrates in order to study the effect of ethene on catalyst activity and stability in detail. From our theoretical and experimental findings we suggest that ethene causes temporary inhibition effects due to a reversible shift of ruthenium complexes from the productive catalytic cycle towards unproductive, dormant ruthenium species. By avoiding the presence of ethene, constant catalytic activity and selectivity for more than 20 days of continuous operation could be realized. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Ethylene to 2-butene in a continuous gas phase reaction using silp-type cationic nickel catalysts - Scholz, Judith; Hager, Veit; Wang, Xinjiao; Kohler, Florian; Sternberg, Michelle; Haumann, Marco; Szesni, Normen; Meyer, Karsten; Wasserscheid, Peter (ChemCatChem, 2014)
Owing to shifting market demands, it is important to convert ethylene to propylene. One attractive way to achieve this conversion is the dimerization of ethylene to 1-butene, followed by isomerization to 2-butene and subsequent metathesis of 2-butene/ethylene olefin. Our contribution focuses on combining the first two steps. Herein, we report a highly selective tandem dimerization/isomerization of ethylene to 2-butene catalyzed by homogeneously dissolved cationic nickel complexes. These catalysts can be efficiently immobilized by using the supported ionic liquid phase technology. Such supported ionic liquid phase materials have been tested under continuous gas phase conditions and demonstrated attractive catalytic performance with respect to both catalyst stability and productivity after the optimization of support, ionic liquid, ligand, and process parameters. The limited thermal stability of the nickel complexes and olefin condensation at too low temperatures require a careful thermal management of the fixed-bed reactor. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Evaluation of a method for micro-defect sealing in ZSM-5 zeolite membranes by chemical vapor deposition of carbon - Simon, A.; Richter, H.; Reif, Benjamin; Schülein, Christa Marion; Sanwald, Dirk; Schwieger, Wilhelm (Separation and Purification Technology, 2019)
This work presents a systematic study on closing micro-defects in zeolite membranes using chemical vapor deposition of carbon. For chemical vapor deposition (CVD), different carbon sources, dwell times and temperatures were applied. The zeolite membranes used in this study were fabricated by hydrothermal syntheses on the inner surface of porous ceramic substrates in single channel geometry. The quality of the membranes was characterized by permporometry, single gas permeation measurements and microstructural techniques (e.g. electron microscopy).
CRIS-Team WoS Importer:2019-05-03

Evaluation of a novel reactor concept for the process intensification and intelligent heat management in the hydrogenation and dehydrogenation of Liquid Organic Hydrogen Carriers - Preuster, Patrick; Wagner, Lisa; Nuß, Andreas; Geiling, Johannes; Steinberger, Michael; Bösmann, Andreas; Wasserscheid, Peter (21st World Hydrogen Energy Conference 2016, WHEC 2016, 2016)

Evaluation of Different Process Concepts for the Indirect Hydration of Cyclohexene to Cyclohexanol - Imam, Rayees Ahamed; Freund, Hannsjörg; Guit, Rudolf P. M.; Fellay, Celine; Meier, Robert J.; Sundmacher, Kai (Organic Process Research & Development, 2013)
An indirect hydration process route for the production of cyclohexanol was proposed by Steyer et al., which uses formic acid as a reactive entrainer (Steyer, F.; Freund, H.; Sundmacher, K. Ind. Eng. Chem. Res. 2008, 47, 9581-9587; Steyer, F.; Sundmacher, K. Ind. Eng. Chem. Res. 2007, 46, 1099-1104). This route overcomes several limitations of the conventional Asahi process for cyclohexene hydration to cyclohexanol (Steyer, F.; Sundmacher, K. Ind. Eng.,Chem. Res. 2007, 46, 1099-1104; Mitsui, O.; Fukuoka, Y. Process for producing cyclic alcohol. U.S. Patent 4,588,846, 1986; Ishida, H. Catal. Sure. Jpn. 1997, 1, 241-246; Ishida, H.; Fukuoka, Y.; Mitsui, O.; Mono, M. Liquid-Phase Hydration of Cyclohexane with Highly Silicious Zeolities. In Zeolites and Microporous Crystals: Proceedings of the International Symposium on Zeolites and Microporous Crystals, Nagoya, August 22-25, 1993; Hattori, T., Yashima, T., Eds.; Studies in Surface Science and Catalysis, Vol. 83; Elsevier: Tokyo, NY, 1994; pp 473-480). A coupled-column reactive distillation process concept, developed earlier in our group (Kumar, R.; Katariya, A.; Freund, H.; Sundmacher, K. Org. Process Res. Dee. 2011, 15, 527-529; Katariya, A.; Freund, H.; Sundmacher, K. Ind. Eng. Chem. Res, 2009, 48, 9534-9545; Freund, H.; Katariya, A.; Kumar, R.; Steyer, F.; Sundmacher, K. DGMK Tagungsber. 2007, 2, 237-239), is feasible, but the energy consumption is very high, and the process concept is limited by multiple steady states with a narrow operating window. There is a need to develop other promising process options. In this direction the present work analyses different process concepts and discusses in detail the challenges involved. Various process options were developed and analyzed. Dedicated experiments were carried out in order to ensure the validity of the kinetic model at a wide range of process conditions. Long-time batch experiments provided an accurate estimation of the heat of formation of cyclohexylformate. The developed process concepts are compared and evaluated with respect to the benchmark Asahi process. As an important indicator of the economic viability, the energy consumption is analyzed.

Evaluation of Industrially Applied Heat-Transfer Fluids as Liquid Organic Hydrogen Carrier Systems - Brückner, Nicole; Obesser, Katharina; Bösmann, Andreas; Teichmann, Daniel; Arlt, Wolfgang; Dungs, Jennifer; Wasserscheid, Peter (Chemsuschem, 2014)
Liquid organic hydrogen carrier (LOHC) systems offer a very attractive method for the decentralized storage of renewable excess energy. In this contribution, industrially well-established heat-transfer oils (typically sold under trade names, e.g., Marlotherm) are proposed as a new class of LOHC systems. It is demonstrated that the liquid mixture of isomeric dibenzyltoluenes (m.p. -39° to -34°C, b.p. 390°C) can be readily hydrogenated to the corresponding mixture of perhydrogenated angenated to the corresponding mixture of perhydrogenated an-alogues by binding 6.2 wt% of H2. The liquid H2 -rich form can be stored and transported similarly to diesel fuel. It readily undergoes catalytic dehydrogenation at temperatures above 260°C, which proves its applicability as a reversible H2 carrier. The presented LOHC systems are further characterized by their excellent technical availability at comparably low prices, full registration of the H2-lean forms, and excellent thermal stabilities.

Evaluation of the ionic liquids 1-alkyl-3-methylimidazolium hexafluorophosphate as a solvent for the extraction of benzene from cyclohexane: (Liquid plus liquid) equilibria - Zhou, Teng; Wang, Ziyun; Chen, Lifang; Ye, Yinmei; Qi, Zhiwen; Freund, Hannsjörg; Sundmacher, Kai (Journal of Chemical Thermodynamics, 2012)
In the catalytic hydrogenation of benzene to cyclohexane, the separation of unreacted benzene from the product stream is inevitable and essential for an economically viable process. In order to evaluate the separation efficiency of ionic liquids (ILs) as a solvent in this extraction processes, the ternary (liquid + liquid) equilibrium of 1-alkyl-3-methylimidazolium hexafluorophosphate, [C(n)mim][PF6] (n = 4, 5, 6), with benzene and cyclohexane was studied at T = 298.15 K and atmospheric pressure. The reliability of the experimentally determined tie-line data was confirmed by applying the Othmer-Tobias equation. The solute distribution coefficient and solvent selectivity for the systems studied were calculated and compared with literature data for other ILs and sulfolane. It turns out that the benzene distribution coefficient increases and solvent selectivity decreases as the length of the cation alkyl chain grows, and the ionic liquids [C(n)mim][PF6] proved to be promising solvents for benzene-cyclohexane extractive separation. Finally, an NRTL model was applied to correlate and fit the experimental LLE data for the ternary systems studied. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Benzene/cyclohexane separation; Ionic liquid [C(n)mim][PF6]; (Liquid plus liquid) equilibria; NRTL correlation

Evaluations of Concepts for the Integration of Fuel Cells in Liquid Organic Hydrogen Carrier Systems - Müller, Karsten; Thiele, Simon; Wasserscheid, Peter (Energy & Fuels, 2019)
Liquid organic hydrogen carrier (LOHC) systems store hydrogen through covalent bonds. As the release of H2 from the LOHC carrier is an endothermic process, clever heat and system integration of this critical step with the exothermic fuel cell operation is highly desirable. The aim of this study is the evaluation of different configurations of this sequence. The results allow decisions on efficient process options. With respect to energy efficiency, the worst case is electric heating for providing the LOHC dehydrogenation heat. Most favorable, in contrast, is full heat integration between a high-temperature fuel cell and the dehydrogenation unit. Partial combustion of hydrogen for heat provision represents an attractive choice. Alternatively, hydrogen transfer to a CO2-free, organic fuel cell is another interesting option. This includes transfer hydrogenation, for example, conversion of acetone to isopropanol, followed by direct conversion of the latter in a fuel cell. While hydrogen combustion-driven dehydrogenation promises high overall power densities, the hydrogen transfer to an organic fuel represents a very efficient technology.
CRIS-Team Scopus Importer:2019-10-15

Expanding the scope of biogenic substrates for the selective production of formic acid from water-insoluble and wet waste biomass - Albert, Jakob; Wasserscheid, Peter (Green Chemistry, 2015)
The selective oxidation of complex, water-insoluble and wet biomasses from second and third generation to formic acid including effective catalyst recycling is reported. Additionally, the relevance and limits of potential contaminants are illustrated by different experimental approaches. By using a very robust homogeneous polyoxometalate catalyst in aqueous solution, molecular oxygen as oxidant and an acid as solubilizer, it is possible to convert different lignocellulosic and algae feedstock into formic acid and pure carbon dioxide. The applied green oxidation system benefits from its low reaction temperature (below 100 °C) and its very selective nature. Furthermore, catalyst recycling over three batches has been successfully carried ou

Experimental assessment of the degree of hydrogen loading for the dibenzyl toluene based LOHC system - Müller, Karsten; Aslam, Rabya; Fischer, Armin; Stark, Katharina; Wasserscheid, Peter; Arlt, Wolfgang (International Journal of Hydrogen Energy, 2016)
Liquid Organic Hydrogen Carriers allow for storing hydrogen with high density at ambient conditions. In the LOHC hydrogen storage process, a significant number of different partially and fully hydrogenated species occur on the reaction pathway from the hydrogen-lean to the hydrogen-rich form of the LOHC system. In order to access the amount of hydrogen stored in the carrier system, ways of measuring the degree of hydrogenation are required. A number of physical properties can be correlated with the degree of hydrogenation. However, there are different mixtures of hydrogenated, partly hydrogenated and dehydrogenated derivatives which result in an identical degree of hydrogenation but different properties. In this contribution we report on attempts to correlate physico-chemical properties and spectroscopic data to the degree of hydrogenation of the dibenzyl toluene system by using density, viscosity, refractive index, UV–VIS and Raman spectroscopy measurements. The most reliable correlations were found for density or refractive index.
Keywords: Fuel gauge; Hydrogen storage; LOHC; Online measurement; Organic hydrides

Experimental determination of the hydrogenation/dehydrogenation - Equilibrium of the LOHC system H0/H18-dibenzyltoluene - Dürr, Stefan; Zilm, S.; Geißelbrecht, Michael; Müller, Karsten; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2021)
Liquid organic hydrogen carrier (LOHC) systems store hydrogen through a catalyst-promoted exothermal hydrogenation reaction and release hydrogen through an endothermal catalytic dehydrogenation reaction. At a given pressure and temperature the amount of releasable hydrogen depends on the reaction equilibrium of the hydrogenation/dehydrogenation reaction. Thus, the equilibrium composition of a given LOHC system is one of the key parameters for the reactor and process design of hydrogen storage and release units. Currently, LOHC equilibrium data are calculated on the basis of calorimetric data of selected, pure hydrogen-lean and hydrogen-rich LOHC compounds. Yet, real reaction systems comprise a variety of isomers, their respective partially hydrogenated species as well as by-products formed during multiple hydrogenation/dehydrogenation cycles. Therefore, our study focuses on an empirical approach to describe the temperature and pressure dependency of the hydrogenation equilibrium of the LOHC system H0/H18-DBT under real life experimental conditions. Because reliable measurements of the degree of hydrogenation (DoH) play a vital role in this context, we describe in this contribution two novel methods of DoH determination for LOHC systems based on 13C NMR and GC-FID measurements.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Degree of hydrogenation; Equilibrium; Hydrogen storage; Hydrogenation; LOHC

Experimental investigation, modeling and scale-up of hydrophilic vapor permeation membranes: Separation of azeotropic dimethyl carbonate/methanol mixtures - Holtbrügge, Johannes; Wierschem, Matthias; Steinrücken, Simon; Voß, Dorothea; Parhomenko, Lubow; Lutze, Philip (Separation and Purification Technology, 2013)
The separation of azeotropic mixtures is a challenging task that is currently performed by special distillation processes, such as heteroazeotropic, extractive or pressure-swing distillation. In recent years, membrane materials that are used to separate different combinations of chemical compounds have constituted an energy-efficient and competitive alternative to special distillation processes. Vapor permeation is a promising type of membrane separation processes which enables to overcome limitations caused by the thermodynamic phase equilibrium. This characteristic facilitates the separation of azeotropic mixtures. However, the membrane needs to be large to handle high throughputs or to achieve high purities. Thus, the use of membranes in combination with established unit operations in so-called membrane-assisted separation processes is advantageous. Nevertheless, in addition to the reliable selection of a suitable membrane polymer for a given design task, a model-based scale-up is still challenging and complicates the design of said membrane separations. These disadvantages limit the application of vapor permeation in the chemical industry. Therefore, the aim of this paper is to enable scale-up by systematically identifying the influence of vapor permeation operating parameters at two different experimental scales with a scale-up factor of 50. Based on these experiments, a rigorous model was developed using experimental data from lab-scale to predict the separation characteristics in pilot-scale. These findings were validated against experimental data from this scale. In this work, the separation of dimethyl carbonate and methanol showing a low-boiling azeotrope with high methanol content was used as a case study. The separation of these two compounds is of significant interest because valuable dimethyl carbonate is usually produced from methanol feedstocks, thus necessitating the separation of both components.
Keywords: Azeotropic separation; Lab-scale; Pilot-scale; PERVAP™; Solution-diffusion model

Experimental investigation of gas-liquid distribution in periodic open cellular structures as potential catalyst supports - Lämmermann, Markus; Schwieger, Wilhelm; Freund, Hannsjörg (Catalysis Today, 2016)
Radial and axial liquid distribution was measured in a packed column of 500 mm length and 100 mm inner diameter under various gas- and liquid superficial velocities to achieve trickle flow regime. Liquid maldistribution was determined using a liquid collector at the outlet consisting of 21 collection zones of equal area. In this work, as packings inside the column, periodic open cellular structures (POCS) were manufactured and applied. Such POCS can be used as structured catalyst support and/or liquid distributor. The hydrodynamic behavior of packings with Kelvin cell, Diamond cell and a hybrid combination of both unit cells was studied to identify unit cells with high potential for achieving homogeneous liquid distribution over the entire reactor cross-section. The liquid superficial velocity had a strong influence on the liquid distribution, while an increasing gas flow rate did not change the flow patterns. Kelvin cell packings tend to distribute the liquid towards the center whereas Diamond cell packings predominantly spread the fluid towards the rim. As a consequence of these observations, in this work a novel POCS structure is proposed: The combination of Kelvin and Diamond unit cells, called hybrid DiaKel unit cell. With POCS consisting of this unit cell type, a significantly improved liquid distribution can be achieved. Thus, this structure features high potential as liquid distributor and/or catalyst support in gas-liquid reaction systems.

Experimental investigations on current and temperature imbalances among parallel-connected lithium-ion cells at different thermal conditions - Fill, Alexander; Mader, Tobias; Schmidt, Tobias; Avdyli, Arber; Kopp, Mike; Birke, Kai Peter (Journal of Energy Storage, 2022)
In this article the influence of Cell to Cell Variances (CtCV) and the thermal design of the battery on electrical and thermal cell imbalances are experimentally investigated for different cell configurations. Measurements with six cell groups are conducted, four cell groups with two parallel cells holding different CtCV and one cell group each with three and four parallel cells. In order to emulate different thermal conditions within a battery, the cells are separated locally and clamped between temperature-controllable aluminum plates. Due to this setup different conditions and battery system components can be emulated, such as insulation material, an adjacent cell or the battery housing. Asides from full discharge/charge cycles with constant current, the relaxation behavior and isolated selective current pulses are considered. It is found that the current inhomogeneity is superimposed by two effects: the voltage source difference ΔUsc and the reciprocal resistance ratio R2/(R1+R2), with the resistance of cell 1 R1 and cell 2 R2. The full discharge/charge cycles with constant current leading to a build up of ΔUsc acting against the resistance ratio. In case of subsequent relaxation, only ΔUsc is effective, since the resistance term is multiplied by the battery current IBatt. By applying an inversely directed pulse, ΔUsc and R2/(R1+R2) act in the same direction.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Current and temperature imbalance; Current distribution; Lithium-ion battery; Parallel-connected cells

Experimental simulation of methane hydrate extraction at high pressure conditions: Influence of the sediment bed - Rodríguez Agudo, José; Park, Jinyoung; Luzi, Giovanni; Williams, Marc; Rauh, Cornelia; Wierschem, Andreas; Delgado, Antonio (Journal of Physics: Conference Series, 2017)
Being a clean alternative to other fossil fuels, Methane Hydrate (MH) is currently considered as one of the most important potential sources for hydrocarbon fuels [1]. In addition, the high energy density of MH and its stability at higher temperatures as compared to LNG (Liquefied Natural Gas) makes MH a potential greener method for energy transportation. At the same time, the low thermodynamic stability of MH strongly questions the future exploitation of gas hydrate deposits, turning its extraction into a possible geohazard [2]. Fluctuations in pressure, temperature, salinity, degree of saturation or sediment bed properties may cause methane gas release from the water lattice. We experimentally study the influence of the sediment bed geometry during formation-dissociation of MH. For this purpose, MH is synthesized within regular substrates in a 93 cm3 high pressure vessel. The regular substrates are triangular and quadratic arrangements of identical glass spheres with a diameter of 2 and 5 mm, respectively. MH formation within regular substrate reduces the possibility of spontaneous nucleation to a unique geometrical configuration. This fact permits us to characterize the kinetics of MH formation-dissociation as a function of the sediment bed geometry. Preliminary experimental results reveal a strong dependence of MH formation on the geometry of the regular substrate. For instance, under the same pressure and temperature, the kinetics of MH production is found to change by a factor 3 solely depending on the substrate symmetry, i.e. triangular or quadrati

Explaining the role of vanadium in homogeneous glucose transformation reactions using NMR and EPR spectroscopy - Albert, Jakob; Mendt, Matthias; Mozer, Michael; Voß, Dorothea (Applied Catalysis A-General, 2019)
Keywords: Keggin polyoxometalates Biomass transformation EPR spectroscopy NMR spectroscopy Vanadium redox chemistry

Exploring the role of the catalytic support sorption capacity on the hydrodechlorination kinetics by the use of carbide-derived carbons - Munoz, Macarena; Zhang, Gui Rong; Etzold, Bastian (Applied Catalysis B-Environmental, 2017)
This work aims at evaluating the effect of the catalytic support sorption capacity on the hydrodechlorination (HDC) process. Carbide-derived carbons (CDCs) have been selected for such goal as their high purity and tunable pore structure makes them a suitable carbon model material. CDCs were synthesized from TiC by chlorination at different extraction temperatures (800–1300 °C) in order to selectively modify their pore structure and crystallinity. Afterwards, the catalysts were produced using a three step process of sulfuric acid treatment, ion-adsorption of palladium precursor and gas phase reduction. Pd/TiC-CDC (1% wt.) catalysts were tested in the HDC of 4-chlorophenol (4-CP) in both aqueous and organic phases under ambient conditions (30 °C, 1 atm, [4-CP]0 = 2.9 mmol L−1, [Pd-TiC-CDC] = 1 g L−1, 50 N mL H2 min−1). The experimental results were successfully fitted by an expanded kinetic model which accounts for consecutive reaction and sorption processes in parallel, allowing to deduce true HDC kinetic constants. The sorption capacity of the support was found to determine the HDC rates in aqueous phase. In this sense, those catalysts showing the highest surface areas and lowered ordered structures led to higher HDC rates, confirming that a high surface density of 4-CP onto the catalyst surface enhances significantly the HDC reaction. The optimum catalyst (Pd/TiC-CDC-1000) led to the complete conversion of 4-CP in 15 min at a HDC rate of 4.1 × 10−2 L s−1 gcat−1.
CRIS-Team Scopus Importer:2023-08-15
Keywords: 4-Chlorophenol; Adsorption; Carbide-derived carbon; Catalytic hydrodechlorination; Pd

Extraction coupled oxidative desulfurization of fuels to sulfate and water-soluble sulfur compounds using polyoxometalate catalysts and molecular oxygen - Albert, Jakob; Wasserscheid, Peter; Bertleff, Benjamin; Claußnitzer, Johannes; Korth, Wolfgang; Jess, Andreas (ACS Sustainable Chemistry & Engineering, 2017)
Our contribution demonstrates a new way of fuel desulfurization, namely selective oxidation of organic S-compounds present in fuels to water-soluble sulfur compounds followed by in situ extraction of the latter into an aqueous phase. Different from common oxidative desulfurization (ODS) processes, we demonstrate a technique that converts sulfur compounds in fuel to a large extent to sulfate (60–70%) using oxygen as the oxidant and an aqueous H8PV5Mo7O40 (HPA-5) solution as the catalyst phase. Other water-soluble desulfurization products are sulfoacetic acid (SAA) with a share of 10–20%, 2-sulfobenzoic acid (2-SBA), and 2-(sulfooxy)benzoic acid (2-SOBA), the latter two with a share of <10%. The new desulfurization method has been optimized for removing benzothiophene from isooctane, giving the best results with a degree of desulfurization of 99% applying 120 °C, 20 bar oxygen pressure, and 1000 rpm of 6 h reaction time using a volume water/oil ration of 10/1. Furthermore, we also successfully demonstrated the desulfurization of a domestic fuel oil with 973 ppmw sulfur content with a degree of desulfurization of 28% under nonoptimized conditions.

Fabrication and pressure drop behavior of novel monolithic structures with zeolitic architectures - Schwieger, Wilhelm; Thangaraj, Thangaraj; Warmuth, Franziska; Warnick, Karl-Georg; Klumpp, Michael; Lodes, Matthias; Körner, Carolin (Chemical Engineering Journal, 2016)
Novel monolithic structures with zeolitic [sodalite (SOD), Linde-Type A (LTA) and faujasite (FAU)-type] architectures having well-defined pores, cages and channels are successfully fabricated by selective electron beam melting (SEBM) using Ti-6Al-4V powder. The open porosities of the monoliths are 92.87% (SOD), 94.64% (LTA) and 95.67% (FAU), respectively. Although the porosity of the FAU monolith is relatively higher than the other two monoliths (SOD and LTA), but exhibits higher normalized pressure drop due to its inherent pore tortuosity (supercages interconnected by 12-ring channels in all three dimensions). This represents a significant step forward for the design and development of innovative structured supports and/or reactors with desired porosities and pressure drop characteristics.
Keywords: Monoliths; Pressure drop; SEBM; Structured supports/reactors; Zeolitic architecture

Fabrication of 1,2-dichlorobenzene sensor based on mesoporous MCM-41 material - Abu-Zied, Bahaa M.; Alam, M. M.; Asiri, Abdullah M.; Schwieger, Wilhelm; Rahman, Mohammed M. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2019)
Recently, mesoporous silicas with uniform pore diameters and ordered pore systems showed promising performances in sensing applications. The present paper was performed to develop a novel 1,2-dichlorobenzene chemical sensor based on mesoporous MCM-41 material, which exhibited a good performance at room temperature. The prepared MCM-41 was characterized using XRD, FT-IR, FE-SEM, TEM, EDX and XPS techniques. The obtained results revealed the spherical nature of the prepared MCM-41 with a good structural order and high specific area. A thin layer of synthesized MCM-41 was deposited on glassy carbon electrode (GCE). By using the fabricated working electrode for the chemical sensor, it was practically applied to detect 1,2-dichlorobenzene (1,2-DCB) successively by an electrochemical approach in phosphate buffer phase. The proposed 1,2-DCB chemical sensor has been exhibited good sensitivity (0.7468 mu A mu M-1 cm(-2)), wide linear dynamic range (0.089 nM-8.9 mM), low detect limit (13.0 +/- 0.65 pM), and short response time (14.0 s). This novel 1,2-DCB chemical sensor based on MCM-41 might be reliable and promisingly approach for the detection of 1,2-DCB for the safety of environment and healthcare fields in a broad scales.
CRIS-Team WoS Importer:2019-02-21

Fabrication of gold-nanoshell/polycaprolactonecomposite films with high electrical conductivity - Naseri, Shiva; Diba, Mani; Golkar, Saeedeh; Boccaccini, Aldo R.; Klupp Taylor, Robin (Materials Letters, 2014)
Gold nanoshells on 1.1 μm diameter silica cores were produced via a seeded growth approach and their quality evaluated using optical measurements. The particles were combined with polycaprolactone to produce a flexible biocompatible composite film with high conductivity (1.51 S cm-1) and relatively low effective gold loading (16.86 wt%) in comparison with other reports in the literature. The morphology of the composite was shown to comprise nanoshell-filled pores percolating a polymer-rich matrix. The obtained films have potential for biomedical applications such as in patches for cardiac tissue engineering, combining biocompatibility, flexibility and electrical conductivity. © 2014 Elsevier B.V.
Keywords: Conductivity; Metal nanoshells; Nanocomposite; Plasmon resonance; Polycaprolactone

Facile synthesis of a tricyclohexylphosphine-stabilized η3-allyl-carboxylato Ni(II) complex and its relevance in electrochemical butadiene carbon dioxide coupling. - Schulz, Peter; Dinjus, Eckhard; Walter, Olaf (Applied Organometallic Chemistry, 2005)
With the reaction of bis(1,5-cyclooctadiene)nickel(0) and trans-penta-2,4-dienoic acid in the presence of tricyclohexylphosphine, a new more general method was developed to synthesize cyclic π3-allyl-carboxylato Ni(II) complexes, which are known to be intermediates in the C-C coupling of butadiene and CO2. The cyclic π3-allyl-carboxylato Ni(II) complex obtained was tested as a mediator in the electrochem. coupling reaction of butadiene and CO2. The authors also demonstrate the dependency on the coordination sphere by using Pt instead of Ni as the metal center; [Pt(cod)2], trans-penta-2,4-dienoic acid and PMe3 gave an oxaplatinacyclopentanone whereas [Pt(cod)2], hexa-2,4-dienoic acid and PCy3 gave [trans-(Cy3P)2PtH(O2CCH:CHCH:CHMe)]. The crystal and mol. structures of the (Cy3P)Ni(CH2CH:CHCH2CO2) chelate were detd. by x-ray crystallog. [on SciFinder(R)]
Keywords: pentadienoic acid coordinative oxidative addn nickel platinum; allyl carboxylato nickel complex prepn structure; electrochem coupling butadiene carbon dioxide nickel complex catalysis; crystal structure nickel phosphine complex pentadienoic acid radical anion; mol structure nickel phosphine complex pentadienoic acid radical anion; metallacycle oxaplatinacyclopentanone prepn; hexadienoato platinum hydrido phosphine complex prepn

Fast production of monolithic carbide-derived carbons with secondary porosity produced by chlorination of carbides containing a free metal phase - Schmirler, Martina; Knorr, Tilman; Fey, Tobias; Lynen, Arthur; Greil, Peter; Etzold, Bastian (Carbon, 2011)
Hierarchical structured carbide-derived carbons (CDC) are produced by high temperature chlorination of silicon carbides containing free silicon (Si/SiC). The influence of free silicon in the precursor carbide on the resulting pore and carbon structure and production rate is studied. The two phases - free silicon and silicon carbide - of Si/SiC gives the possibility to synthesize a monolithic carbon with the typical microporous character and narrow pore size distribution combined with larger voids in the micrometer range, while the carbon structure itself stays unchanged. The study revealed that using Si/SiC material increases the production rate for carbide-derived carbons dramatically, due to higher reactive surface area and lower mass transfer limitations, which allows for the time effective production of larger monoliths. (C) 2011 Elsevier Ltd. All rights reserved.

Fast synthesis of optimal chemical reactor networks based on a universal system representation - Xie, Mingquan; Freund, Hannsjörg (Chemical Engineering and Processing, 2018)
We propose a new approach for the synthesis of optimal chemical reactor networks based on the concept of elementary process functions [1] and dynamic optimization. This approach is capable of incorporating process intensification options at an early design stage. Only one single differential equation is required to describe the mass balance of the whole reactor system along the reaction route. This equation contains terms describing mass fluxes from outside the reactor system and mass fluxes which flow between different positions of the reaction route. We demonstrate that different reactor types and different reactor connections can be represented by such a formulation. After solving an optimization problem using such a model, optimal profiles of state variables and fluxes are obtained. Based on these profiles, the optimal reactor system is determined. After the presentation of the theoretical background and the derivation of the new approach, it is illustrated in case studies and validated by comparison with literature results. The advantages of this new approach presented in our contribution are its simplicity in description and implementation, universality in representing different reactor types and networks, and the potential to consider different intensification and integration options at an early design stage.
Keywords: Reactor design; Process design; Optimization; Reactor network; Process intensification

Fifteen Years of Supported Ionic Liquid Phase-Catalyzed Hydroformylation: Material and Process Developments - Marinkovic, Jakob Maximilian; Riisager, Anders; Franke, Robert; Wasserscheid, Peter; Haumann, Marco (Industrial & Engineering Chemistry Research, 2019)
This review describes the development of supported ionic liquid phase (SILP) materials as novel hydroformylation catalysts. Ligandmodified rhodium catalysts can be immobilized in a thin film of ionic liquid, which itself is dispersed on a porous material. The solid SILP catalysts have been improved with respect to activity, selectivity, and stability. In addition, their applicability in continuous gas-phase processes opens new opportunities for improved chemical production routes.
CRIS-Team WoS Importer:2019-03-08

Flows due to pressure induced dissociation-formation of gas hydrates - Rodríguez Agudo, José; Kwon, Sinyoung; Saur, Roland; Loekman, Soebiakto; Luzi, Giovanni; Rauh, Cornelia; Wierschem, Andreas; Delgado, Antonio (IOP Conference Series: Materials Science and Engineering, 2017)
During the last decade, Gas Hydrates (GH) have attracted the interest of the scientific community for engineering applications. Carbon dioxide hydrate (CO2H), for instance, may play an important role for capture and sequestration methods in order to reduce global climate change. Despite the extensive literature, the transport phenomena involved during CO2H formation are not yet fully understood. CO2 transfer from gas or liquid phase to the bulk of water is expected to happen not only by molecular diffusion but also driven by natural convective currents induced by CO2 dissolution in water. Using particle tracer methods, we experimentally characterize the flow velocity of the bulk of water during CO2H formation. For that purpose, CO2H is grown inside an optical cell with a volume of 12 mL at various pressures and temperatures. Due to CO2 dissolution, convection currents are noticed prior to hydrate formation. Our experimental results point to a significant correlation between this process and the subsequent hydrate formation. Two well-differentiated hydrate growth patterns were observed depending on the hydrate induction time and the corresponding CO2 concentration distribution inside water. For long induction times, CO2 can be provided from the water phase resulting in rapid growth. Short induction times resulted in slow growth at the interface creating a solid barrier accompanied by a significant drop in the flow velocity. In some cases, the hydrate layer appeared to be unstable and convection could restar

Flue gas cleaning with alternative processes and reaction media - Rasmussen, Soren Birk; Huang, Jun; Riisager, Anders; Hamma, Hind; Rogez, Jacquez; Winnick, J.; Wasserscheid, Peter; Fehrmann, Rasmus (15th International Symposium on Molten Salts - 210th ECS Meeting, 2007)
Alternative methods to the traditional industrial NO and SO flue gas cleaning processes working at lower temperatures and/or leading to useful products are desired. In this work we present our latest results regarding the use of molten ionic media in electrocatalytic membrane separation, ionic liquid reversible absorption and supported ionic liquid deNOx catalysis. Further development of the methods will hopefully make them suitable for installation in different positions in the flue gas duct as compared to the industrial methods available today. copyright The Electrochemical Society.

Flüssige Wasserstoffträger für ein Nachhaltiges Energiesystem - Teichmann, Daniel; Arlt, Wolfgang; Wasserscheid, Peter (ATZ - Automobiltechnische Zeitschrift, 2012)

Food technological potentials of CO2 gas hydrate technology for the concentration of selected juices - Seidl, Pia; Loekman, Soebiakto; Sardogan, Miray; Voigt, Erik; Claßen, Timo; Ha, Jawon; Luzi, Giovanni; Sevenich, Robert; Rodríguez Agudo, José; Rauh, Cornelia; Delgado, Antonio (High Pressure Research, 2019)
CO2 gas hydrate technology seems to be a gentle way to concentrate juices, especially comparing to evaporation processes which achieve high levels of concentration and is furthermore energetically favorable in contrast to freeze concentration processes. CO2 can form gas hydrates at around 30–80 bar and 274–283 K. For evaluating this new technology, it is not only important to know the phase equilibrium lines of commercial juices like apple and orange juices but also how the application of e.g. a bubble column affects the gas hydrate formation and separation from the concentrated product. In order to support the experimental outcome, numerical modeling seems suitable to understand the physical background of this novel concentration technology. This includes the simulation of temperature, velocity, pressure and concentration fields using finite volume technique. All three work packages combined will lead to a better understanding of the behavior of gas hydrate technology used to concentrate liquid foo
Keywords: Fruit juice; hydrate technology; food technology; gas hydrate; carbon dioxide/CO2 clathrate; CO2 hydrate

Formation and Surface Behavior of Pt and Pd Complexes with Ligand Systems Derived from Nitrile-functionalized Ionic Liquids Studied by XPS - Hemmeter, Daniel; Paap, Ulrike; Taccardi, Nicola; Mehler, Julian; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2022)
We studied the formation and surface behavior of Pt(II) and Pd(II) complexes with ligand systems derived from two nitrile-functionalized ionic liquids (ILs) in solution using angle-resolved X-ray photoelectron spectroscopy (ARXPS). These ligand systems enabled a high solubility of the metal complexes in IL solution. The complexes were prepared by simple ligand substitution under vacuum conditions in defined excess of the coordinating ILs, [C3CNC1Im][Tf2N] and [C1CNC1Pip][Tf2N], to immediately yield solutions of the final products. The ILs differ in the cationic head group and the chain length of the functionalized substituent. Our XPS measurements on the neat ILs gave insights in the electronic properties of the coordinating substituents revealing differences in donation capability and stability of the complexes. Investigations on the composition of the outermost surface layers using ARXPS revealed no surface affinity of the nitrile-functionalized chains in the neat ILs. Solutions of the formed complexes in the nitrile ILs showed homogeneous distribution of the solute at the surface with the heterocyclic moieties preferentially orientated towards the vacuum, while the metal centers are rather located further away from the IL/vacuum interface.
CRIS-Team Scopus Importer:2022-10-28
Keywords: catalysis; ionic liquids; organometallic chemistry; surface science; X-ray photoelectron spectroscopy

Formic acid-based Fischer-Tropsch synthesis for green fuel production from wet waste biomass and renewable excess energy - Albert, Jakob; Jess, A.; Kern, C.; Pöhlmann, F.; Glowienka, K.; Wasserscheid, Peter (DGMK Tagungsbericht, 2018)
Growing concerns about global warming have created a world-wide interest in new concepts for sustainable and biomass-based future energy supplies. A main interest of related research efforts is to provide liquid transportation fuels from biomass waste or non-edible biomass resources as competing use of agricultural products for feeding people or animals against its conversion to fuels is increasingly inacceptable in the light of a still growing global population. While the production of hydrocarbons by Fischer-Tropsch synthesis (FTS) is a widely recognized, yet technically quite complex way to transform biomass via syngas (mostly from biomass gasification) into liquid fuels, we here present an alternative route transforming biomass first into formic acid (FA) followed by syngas formation by decomposition of FA and finally FTS using regenerative hydrogen (or if needed H2 from the stored FA) to balance the C:H ratio. The new method builds on the recently developed, selective oxidation of biomass to formic acid using Keggin-type polyoxometalates as homogeneous catalysts, oxygen as the oxidant and water as the solvent. This method is able to transform a wide range of complex and wet biomass mixtures into FA as the sole liquid product at mild reaction conditions (90 °C, <10 bar O2). We propose to convert FA with hydrogen from water electrolysis - the electrolysis step producing also the oxygen for the biomass oxidation to FA - to green hydrocarbon fuels using a typical Co-based FT catalyst.
CRIS-Team Scopus Importer:2023-03-29

Formic Acid-Based Fischer-Tropsch Synthesis for Green Fuel Production from Wet Waste Biomass and Renewable Excess Energy - Albert, Jakob; Wasserscheid, Peter; Jess, Andreas; Kern, Christoph; Pöhlmann, Ferdinand; Glowienka, Kevin (ACS Sustainable Chemistry & Engineering, 2016)
While the production of hydrocarbons by Fischer-Tropsch synthesis (FTS) is a widely recognized, yet technically quite complex way to transform biomass via syngas (mostly from biomass gasification) into liquid fuels, we here present an alternative route transforming biomass first into formic acid (FA) followed by syngas formation by decomposition of FA and finally FTS using regenerative hydrogen (or if needed H2 from the stored FA) to balance the C:H ratio. The new method builds on the recently developed, selective oxidation of biomass to formic acid using Keggin-type polyoxometalates of the general formula (H3+x[PVxMo12-xO40]) as homogeneous catalysts, oxygen as the oxidant, and water as the solvent. This method is able to transform a wide range of complex and wet biomass mixtures into FA as the sole liquid product at mild reaction conditions (90 °C, 20-30 bar O2). We propose to convert FA with hydrogen from water electrolysis–the electrolysis step producing also the oxygen for the biomass oxidation to FA–to green hydrocarbon fuels using a typical Co-based FT catalyst.

From Meso to Macro: Controlling Hierarchical Porosity in Supraparticle Powders - Sultan, Umair; Götz, Alexander; Schlumberger, Carola; Drobek, Dominik; Bleyer, Gudrun; Walter, Teresa; Loewer, Erik; Peuker, Urs Alexander; Thommes, Matthias; Spiecker, Erdmann; Apeleo Zubiri, Benjamin; Inayat, Alexandra; et al. (Small, 2023)
A drying droplet containing colloidal particles can consolidate into a spherical assembly called a supraparticle. Such supraparticles are inherently porous due to the spaces between the constituent primary particles. Here, the emergent, hierarchical porosity in spray-dried supraparticles is tailored via three distinct strategies acting at different length scales. First, mesopores (<10 nm) are introduced via the primary particles. Second, the interstitial pores are tuned from the meso- (35 nm) to the macro scale (250 nm) by controlling the primary particle size. Third, defined macropores (>100 nm) are introduced via templating polymer particles, which can be selectively removed by calcination. Combining all three strategies creates hierarchical supraparticles with fully tailored pore size distributions. Moreover, another level of the hierarchy is added by fabricating supra-supraparticles, using the supraparticles themselves as building blocks, which provide additional pores with micrometer dimensions. The interconnectivity of the pore networks within all supraparticle types is investigated via detailed textural and tomographic analysis. This work provides a versatile toolbox for designing porous materials with precisely tunable, hierarchical porosity from the meso- (3 nm) to the macroscale (≈10 µm) that can be utilized for applications in catalysis, chromatography, or adsorption.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adsorption; hierarchy; porous materials; self-assembly; supraparticles; tomography

From molecules to materials: The cluster of excellence "engineering of Advanced Materials" at Friedrich-Alexander University of Erlangen-Nuremberg - Peukert, Wolfgang; Wasserscheid, Peter; Hirsch, Andreas (Advanced Materials, 2011)
Engineering of Advanced Materials - Hierarchical Structure Formation for Functional Devices (EAM) focus on the development of advanced materials with properties customized on the nano and mesoscale. The EAM network comprises scientists from different departments including Applied Mathematics, Chemical Engineering, Chemistry, Computer Science, Electrical Engineering, Materials Science, and Mechanical Engineering and Physics. The development of EAM has been encouraged by the acquisition of world-class scientific instruments. These include an FEI Titan 80-300 transmission electron microscope enhancing an aberration corrector to enable the high resolution imaging of nanomaterials in unprecedented clarity. The instrument also includes a full suite of state of the art spectroscopic and tomographic techniques. EAM is also focusing on hybrid electronic systems which exploit the advantages of both organic and inorganic materials.

Functionalization of oxide surfaces through reaction with 1,3-dialkylimidazolium ionic liquids - Schernich, Stefan; Laurin, Mathias; Lykhach, Yaroslava; Steinrück, Hans-Peter; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Taccardi, Nicola; Matolin, Vladimir; Wasserscheid, Peter; Libuda, Jörg (Journal of Physical Chemistry Letters, 2013)
Practical applications of ionic liquids (ILs) often involve IL/oxide interfaces, but little is known regarding their interfacial chemistry. The unusual physicochemical properties of ILs, including their exceptionally low vapor pressure, provide access to such interfaces using a surface science approach in ultrahigh vacuum (UHV). We have applied synchrotron radiation photoelectron spectroscopy (SR-PES) to the study of a thin film of the ionic liquid [CCIm][TfN] prepared in situ in UHV on ordered stoichiometric CeO(111) and partially reduced CeO . On the partially reduced surface, we mostly observe decomposition of the anion. On the stoichiometric CeO(111) surface, however, a layer of surface-anchored organic products with high thermal stability is formed upon reaction of the cation. The suggested acid-base reaction pathway may provide well-defined functionalized IL/solid interfaces on basic oxides. © 2012 American Chemical Society.

Functional nickel complexes of N-heterocyclic carbene ligands in pre-organized and supported thin film materials - Wang, Xinjiao; Sobota, Marek; Kohler, Florian; Morain, Bruno; Melcher, Berthold Ulrich; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg; Meyer, Karsten (Journal of Materials Chemistry, 2012)
Nickel(ii) complexes with double alkyl chain functionalized N-heterocyclic carbene (NHC) ligands, [NiCl (C MIM) ] and [NiCl (C C IM) ], where C MIM = 1-dodecyl-3-methylimidazolin-2-ylidene (1) and C C IM = 1,3-didodecylimidazolin-2-ylidene (2), have been prepared and fully characterized by H NMR, C NMR, and CHN elemental analyses. Furthermore, we have developed a system, in which double long alkyl chain derivatized Ni-NHC complexes are dissolved in the related ionic liquid crystalline 1,3-didodecylimidazolium tetrafluoroborate, [C C IM][BF ], to form pre-organized structures for enhanced reactivity. Remarkably, differential scanning calorimetry, polarized optical microscopy, and temperature-programmed IR reflection absorption spectroscopy performed on a mixture of 10 wt% Ni complexes in [C C IM][BF ] demonstrate that this system retains an ionic liquid crystalline phase; even after immobilization onto a silica-100 support with pore filling α = 1. © 2012 The Royal Society of Chemistry.

Gallium-rich Pd-Ga phases as supported liquid metal catalysts - Taccardi, Nicola; Grabau, Mathias; Debuschewitz, Jonas; Distaso, Monica; Brandl, Marco; Hock, Rainer; Maier, Florian; Papp, Christian; Erhard, Jannis; Neiß, Christian; Peukert, Wolfgang; Görling, Andreas; et al. (Nature chemistry, 2017)
A strategy to develop improved catalysts is to create systems that merge the advantages of heterogeneous and molecular catalysis. One such system involves supported liquid-phase catalysts, which feature a molecularly defined, catalytically active liquid film/droplet layer adsorbed on a porous solid support. In the past decade, this concept has also been extended to supported ionic liquid-phase catalysts. Here we develop this idea further and describe supported catalytically active liquid metal solutions (SCALMS). We report a liquid mixture of gallium and palladium deposited on porous glass that forms an active catalyst for alkane dehydrogenation that is resistant to coke formation and is thus highly stable. X-ray diffraction and X-ray photoelectron spectroscopy, supported by theoretical calculations, confirm the liquid state of the catalytic phase under the reaction conditions. Unlike traditional heterogeneous catalysts, the supported liquid metal reported here is highly dynamic and catalysis does not proceed at the surface of the metal nanoparticles, but presumably at homogeneously distributed metal atoms at the surface of a liquid metallic phas

Ga-Ni supported catalytically active liquid metal solutions (SCALMS) for selective ethylene oligomerization - Sogaard, Alexander; De Oliveira, Ana Luiza; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter (Catalysis: Science and Technology, 2021)
Non-precious metal supported catalytically active liquid metal solutions exhibit attractive performance in ethylene oligomerization. It is found for the Ga-Ni system on silica that the performance depends strongly on the applied Ga/Ni ratio. Ga-rich systems forming liquid alloys exhibit a far higher Ni-based catalytic activity than solid intermetallic compounds or Ni nanoparticles.
CRIS-Team WoS Importer:2021-11-26

GaPt Supported Catalytically Active Liquid Metal Solution Catalysis for Propane Dehydrogenation-Support Influence and Coking Studies - Raman, Narayanan; Wolf, Moritz; Heller, Martina; Heene-Würl, Nina; Taccardi, Nicola; Haumann, Marco; Felfer, Peter; Wasserscheid, Peter (ACS Catalysis, 2021)
Supported catalytically active liquid metal solutions (SCALMS) of Pt in Ga (2 at.-% Pt) were studied in the temperature range of 500 to 600 °C for propane dehydrogenation. A facile synthesis procedure using ultrasonication was implemented and compared to a previously reported organo-chemical route for gallium deposition. The procedure was applied to synthesize GaPt-SCALMS catalyst on silica (SiO2), alumina (Al2O3), and silicon carbide (SiC) to investigate the effect of the support material on the catalytic performance. The SiC-based SCALMS catalyst showed the highest activity, while SiO2-based SCALMS showed the highest stability and lowest cracking tendency at higher temperatures. The selectivity toward propene for the SiO2-based catalyst remained above 93% at 600 °C. The catalysts were analyzed for coke content after use by temperature-programmed oxidation (TPO) and Raman spectroscopy. While the SiC- and SiO2-supported SCALMS systems showed hardly any coke formation, the Al2O3-supported systems suffered from pronounced coking. SEM-EDX analyses of the catalysts before and after reaction indicated that no perceivable morphological changes occur during reaction. The SCALMS catalysts under investigation are compared with supported Pt and supported GaPt solid-phase catalyst, and possible deactivation pathways are discussed.
CRIS-Team Scopus Importer:2021-11-19
Keywords: coking; dehydrogenation; gallium; platinum; SCALMS; supported liquid catalysis

Ga-Pt supported catalytically active liquid metal solutions (SCALMS) prepared by ultrasonication - influence of synthesis conditions on n-heptane dehydrogenation performance - Oshin, Sebastian; Al-Shaibani, Asem; Taccardi, Nicola; Sultan, Umair; Inayat, Alexandra; Vogel, Nicolas; Haumann, Marco; Wasserscheid, Peter (Catalysis: Science and Technology, 2023)
Supported catalytically active liquid metal solution (SCALMS) materials represent a recently developed class of heterogeneous catalysts, where the catalytic reaction takes place at the highly dynamic interface of supported liquid alloys. Ga nuggets were dispersed into nano-droplets in propan-2-ol using ultrasonication followed by the addition of Pt in a galvanic displacement reaction - either directly into the Ga/propan-2-ol dispersion (in situ) or consecutively onto the supported Ga droplets (ex situ). The in situ galvanic displacement reaction between Ga and Pt was studied in three different reaction media, namely propan-2-ol, water, and 20 vol% water containing propan-2-ol. TEM investigations reveal that the Ga-Pt reaction in propan-2-ol resulted in the formation of Pt aggregates on top of Ga nano-droplets. In the water/propan-2-ol mixture, the desired incorporation of Pt into the Ga matrix was achieved. The ex situ prepared Ga-Pt SCALMS were tested in n-heptane dehydrogenation. Ga-Pt SCALMS synthesized in pure alcoholic solution showed equal dehydrogenation and cracking activity. Ga-Pt SCALMS prepared in pure water, in contrast, showed mainly cracking activity due to oxidation of Ga droplets. The Ga-Pt SCALMS material prepared in water/propan-2-ol resulted in high activity, n-heptene selectivity of 63%, and only low cracking tendency. This can be attributed to the supported liquid Ga-Pt alloy where Pt atoms are present in the liquid Ga matrix at the highly dynamic catalytic interfac
Keywords: Binary alloys; Dehydrogenation; Drops; Heptane; Liquid metals; Platinum alloys; Substitution reactions; Cracking activity; Ex situ; Galvanic displacement reactions; matrix; Metal solutions; n-Heptanes; Nano-droplets; Performance; Synthesis conditions; Ultra-sonication; Catalysis

Gas-Phase Hydroformylation Using Supported Ionic Liquid Phase (SILP) Catalysts - Influence of Support Texture on Effective Kinetics - Schörner, Markus; Rothgängel, Philipp; Mitländer, Kerstin; Wisser, Dorothea; Thommes, Matthias; Haumann, Marco (ChemCatChem, 2021)
The supported ionic liquid phase (SILP) concept, which included thin films of ionic liquid dispersed onto porous support surfaces, was applied for the gas-phase hydroformylation of but-1-ene catalyzed by Rh-bpp (bpp=biphephos ligand) complexes. The support material silica was carefully pre-treated by a hydrothermal procedure to induce textural changes concerning the pore size. Starting with a mean pore size of 3 nm these could be enlarged by almost a factor of 10 up to 27 nm. Different particle size fractions having the same pore size of 10 +/- 1 nm were investigated regarding the hydroformylation activity. A clear limitation by pore diffusion can be found for particles larger than 500 mu m in diameter. The limitation could be minimized by enlarging the pore size. To support the data, dimensionless numbers and criteria were calculated, including Thiele-modulus, Mears, and Weisz-Prater. All data support the assumption that limitation occurs around 500 mu m particle size if 10 nm pores are present.
CRIS-Team WoS Importer:2021-08-27

Gas-phase oxycarbonylation of methanol for the synthesis of dimethyl carbonate using copper-based Supported Ionic Liquid Phase (SILP) catalysts - Schneider, Martin; Haumann, Marco; Stricker, Marion; Sundermeyer, Jörg; Wasserscheid, Peter (Journal of Catalysis, 2014)
Catalyst systems for the gas-phase oxycarbonylation of methanol often suffer from low catalyst activities and strong catalyst deactivation. In this work, the continuous gas-phase oxycarbonylation of methanol was realized by using Supported Ionic Liquid-Phase (SILP) catalysts. Copper(I) bromide dissolved in various ionic liquids and dispersed on Polymer-Based Spherical Activated Carbon (PBSAC) as supporting material was found to be an active catalyst. The poor activity and stability of copper halide catalysts reported in literature was substantially increased by the presence of ionic liquids. In particular, trioctylmethylammonium bromide in combination with a basic salt additive increased the activity of the CuBr catalyst and led to comparatively stable SILP catalyst operation reaching a total turnover number of 600 over 50 h time-on-stream.

Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie International Edition, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be adhered selectively to specific oxide surfaces.
Keywords: chemical anchoring; cobalt oxide; ester functionalization; ionic liquids; vapor deposition

Gluing ionic liquids to oxide surfaces: Chemical anchoring of functionalized ionic liquids by vapor deposition onto cobalt(II) oxide // Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Ph. D. Maria Julia; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be ``glued'' selectively specific oxide surfaces.
EAM Import::2019-03-13

Greening the esterification between isosorbide and acetic acid - Inayat, Alexandra; van Assche, Alexander; Clark, James H.; Farmer, Thomas J. (Sustainable Chemistry and Pharmacy, 2018)
This contribution deals with the investigation of greener conditions for the preparation of 2,5-diacetyl-isosorbide from the bio-based substances isosorbide and acetic acid. The influence of solvent, catalyst and reactant ratio on the course of the isosorbide conversion and selectivity to 2,5-diacetyl-isosorbide as well as to the intermediate 2-acetyl-isosorbide is examined. It was found that the conventionally used solvent toluene can be substituted by the greener solvent n-propyl acetate. Additionally, the homogeneous acid catalyst p-toluene sulfonic acid can be replaced by the heterogeneous catalyst Amberlyst-15, resulting in an easier isolation of the desired 2,5-diacetyl-isosorbide, this being an important precursor for the vasodilatory drug isosorbide-5-nitrat

Green organic synthesis in ionic liquids. - Wasserscheid, Peter; Joni, Joni (Handbook of Green Chemistry, 2010)
A review. Green org. synthesis in ionic liqs. is reviewed. [on SciFinder(R)]
Keywords: green synthesis ionic liq solvent catalyst review

Halide-Free Synthesis and Tribological Performance of Oil-Miscible Ammonium and Phosphonium-Based Ionic Liquids - Westerholt, Antje; Weschta, Martin; Bösmann, Andreas; Tremmel, Stephan; Korth, Yasmin; Wolf, Marcus J.; Schlücker, Eberhard; Wehrum, Natalie; Lennert, Angela; Uerdingen, Marc; Holweger, Walter; Wartzack, Sandro; et al. (ACS Sustainable Chemistry & Engineering, 2015)
Due to their low vapor pressures, nonflammability, high thermal stabilities, and excellent tribological properties ionic liquids (ILs) are highly attractive lubricant base oils and additives. However, for practical applications of ILs in lubrication, two requirements are often limiting, the required miscibility with standard mineral oils (≥5 wt %) and the complete absence of corrosive halide ions in the ionic liquid. Moreover, the need for full compatibility with standard oil additives reduces the number of potential IL-based lubricant additives even further. In this contribution, an economic halide-free synthesis route to oil-miscible ionic liquids is presented, and very promising tribological properties of such ILs as base oil or additive are demonstrated. Therefore, sliding tests on bearing steel and XPS analysis of the formed surface films are shown. Corrosion test results of different bearing metals in contact with our halide-free ILs and (salt) water prove their applicability as real life lubricants. In the sustainable chemistry and engineering context, we present a halide-free design approach for ionic performance chemicals that may contribute to significant energy savings due to their enhanced lubrication properties.
Keywords: Halide-free; Ionic liquid; Lubrication; Noncorrosive; Oil-miscible; XPS

Heat transfer performance of structured catalytic reactors packed with metal foam supports: Influence of wall coupling - Razza, S.; Heidig, Tobias; Bianchi, Enrico; Groppi, G.; Schwieger, Wilhelm; Tronconi, E.; Freund, Hannsjörg (Catalysis Today, 2016)
Based on previous lab-scale heat transfer experiments performed in a test tube filled with metallic foams, extensive simulations of conjugated heat transfer were performed to systematically investigate the role of different coupling scenarios between the foam structure and the tube wall, using a 3D scanned foam geometry to enable the comparison of simulation results with experiments. The goal of this analysis is to gain insight into the prominent role of the wall coupling for radial heat transfer in a structured catalytic reactor packed with metal foams as catalyst supports. In the current numerical investigation the focus is on the characterization of the contact area between the foam and the reactor wall. Starting from perfect contact between the two, the contact area was decreased by selecting randomly some boundary spots of the foam and considering them as adiabatic. Moreover, the local distribution of the adiabatic struts was restricted to regions near the reactor inlet to additionally investigate the influence of the local distribution of the adiabatic struts at same overall contact areas. Eventually, all the contacts between the foam and the reactor wall were considered adiabatic as the other limiting case, wherein heat transfer at the foam/wall interface was governed solely by convection. The numerical analysis revealed that even if only a limited fraction of the struts have a direct contact with the tube wall, the heat transfer rate is significantly enhanced in comparison to the adiabatic case. In analogy with the previous experimental study, the numerical investigation was carried out for two different gases, nitrogen and helium, in order to address the influence of the thermal conductivity of the fluid phase. For further experimental verification, additional heat transfer measurements were performed for the case of a foam directly sintered to the tube in order to realize a perfect contact between foam and wall.

Heat transfer properties of metal foam supports for structured catalysts: Wall heat transfer coefficient - Bianchi, Enrico; Heidig, Tobias; Visconti, Carlo Giorgio; Groppi, Gianpiero; Freund, Hannsjörg; Tronconi, Enrico (Catalysis Today, 2013)
In this work we investigate the heat transfer within single phase tubular reactors packed with open-cell metal foams. Special focus is on the role of the coupling between the foam packing and the reactor tube wall. Steady-state heat transfer experiments were carried out in a tube of 28 mm inner diameter packed with different open-cell foams using N-2 or He at a flow rate ranging from 15 to 35 Nl/min. The foam samples were made of either FeCrAlY or aluminum with porosities in the range of 89-95% and pore densities ranging from 10 to 40 PPI (nominal pores per linear inch). For this purpose, axial and radial temperature profiles along the tested foam samples and along the tube wall were collected in heating and cooling runs within a temperature range from 400 to 800 K. The effective radial and axial conductivity and the wall heat transfer coefficient were then estimated for each run by nonlinear regression, using a 2D pseudo-homogeneous heat transfer model. The collected data allowed deriving a correlation for the wall heat transfer coefficient as a function of the process conditions and of the foam structural properties. Complementary to these experimental investigations, a numerical study in a 3D geometry of a foam sample reconstructed from X-ray micro-computed tomography data was carried out in order to analyze the heat transfer process close to the wall. For this, the conjugated heat transfer in both the solid and the fluid phase was investigated by finite volume analysis for selected experimental conditions. Both experiments and simulations confirm that the wall heat transfer resistance depends strongly on the gas conductivity and on the foam geometry, but more weakly on the flow velocity. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Metal foams; Sponges; Heat transfer; Process intensification; Optimized supports; Structured reactors

Heterogeneous Catalysts SILP with Phosphotungstic Acid for Oxidative Desulfurization: Effect of Ionic Liquid - Bryzhin, A. A.; Buryak, A. K.; Gantman, Mikhail; Zelikman, V. M.; Shilina, M. I.; Tarkhanova, I. G. (Kinetics and Catalysis, 2020)
Abstract: SILP (supporting ionic liquid phase) catalysts for peroxide thiophene oxidation were obtained on silica gel, they included imidazole cations with sulfonic acid group and phosphotungstate anions. The composition of the active phase and the surface structure of the catalysts are characterized by a set of modern physicochemical methods, including mass spectrometry using the SALDI technique. It was found that the organic cation structure affects the stability of heteropolyanions, decomposition processes in the SILP and the catalytic properties of the samples. SILP catalysts are effective in desulfurization of the diesel fraction and provide fuel with an S content of less than 10 ppm.
CRIS-Team Scopus Importer:2020-10-16
Keywords: diesel desulfurization; hydrogen peroxide; phosphotungstic heteropolyacid; SILP catalysts; thiophene oxidation

Hierarchically-Ordered Materials - Hartmann, Martin; Schwieger, Wilhelm; Thommes, Matthias (Advanced Materials Interfaces, 2021)

Hierarchically-Ordered Materials - Hartmann, Martin; Schwieger, Wilhelm; Thommes, Matthias (Advanced Materials Interfaces, 2021)
CRIS-Team Scopus Importer:2021-03-05

Hierarchically-Ordered Zeolites: A Critical Assessment - Hartmann, Martin; Thommes, Matthias; Schwieger, Wilhelm (Advanced Materials Interfaces, 2021)
Hierarchically-ordered zeolites have received increasing attention in the last 15 years due to their outstanding properties, which are explored in catalytic reaction with industrial relevance. Up to now, a large number of different synthetic strategies have been reported that allow to introduce an additional meso- or macropore system in addition to the intrinsic microporosity of classical zeolites. Thus, hierarchical zeolites combine the intrinsic (catalytic) properties of conventional zeolites with facilitated access and transport via the additional pore system. In this critical review, the various synthesis pathways reported so far are evaluated, several physico-chemical methods required for in-depth characterization of the hierarchical pore system are discussed, and selective applications that are or potentially will be of technical relevance are introduced. The present review provides a critical analysis of the present achievements and discusses future opportunities and challenges for the research on hierarchically-ordered zeolite in particular with respect to their industrial use.
CRIS-Team Scopus Importer:2021-03-05
Keywords: advanced characterization; catalysis; hierarchically-ordered materials; porous materials; separation

Hierarchically-structured porous materials: from basic understanding to applications - Hartmann, Martin; Schwieger, Wilhelm (Chemical Society Reviews, 2016)
No abstract available for this article

Hierarchical MFI type zeolites with intracrystalline macropores: The effect of the macropore size on the deactivation behaviour in the MTO reaction - Weissenberger, Tobias; Reiprich, Bastian; Machoke, Albert; Klühspies, Katharina; Bauer, Juergen; Dotzel, Ralf; Casci, John L.; Schwieger, Wilhelm (Catalysis: Science and Technology, 2019)
Hierarchically structured ZSM-5 catalysts have been prepared using different sized mesoporous silica particles as the sacrificial template, resulting in zeolite crystals with different sized intracrystalline macropores but very similar zeolitic characteristics such as crystallinity, chemical composition, and acidic and textural properties. This set of catalysts was used to investigate the effect of intracrystalline macropores on the deactivation behaviour of ZSM-5 catalysts in the conversion of methanol to olefins (MTO). The catalytic tests showed that the incorporation of macropores was very beneficial in improving the catalyst lifetime in the MTO reaction. This improved performance was correlated to the reduced coke formation during the reaction, likely a result of the enhanced transport of reactants and products in the zeolite crystals due to the well-interconnected macropores. Also worth mentioning is the effect of the dimensions of the additional macropores on the rate of coke formation. Increasing the macropore size by a factor of two led to a decrease in coke formation and consequently a two times longer catalyst lifetime.
CRIS-Team Scopus Importer:2019-07-02

Hierarchical ZSM-5 Catalysts: The Effect of Different Intracrystalline Pore Dimensions on Catalyst Deactivation Behaviour in the MTO Reaction - Weissenberger, Tobias; Machoke, Albert; Bauer, Juergen; Dotzel, Ralf; Casci, John L.; Hartmann, Martin; Schwieger, Wilhelm (ChemCatChem, 2020)
Abstract: We present the effect of different combinations of intracrystalline pore systems in hierarchical ZSM-5 zeolites on their performance as MTO catalysts. We prepared ZSM-5 zeolites with additional intracrystalline mesoporous, intracrystalline macropores and a novel ZSM-5 type zeolite with intracrystalline meso and macropores. The catalytic results showed that both used catalysts with mesopores and macropores exhibited three times longer catalyst lifetime compared to a conventional catalyst. However, TGA analysis of the deactivated catalysts showed much larger coke content in the mesoporous catalyst than in the macroporous catalyst. Consequently, macropores predominantly led to reduced coke formation rate while additional mesopores predominantly enhanced the resistance against deactivation by coke. Combining both intracrystalline meso and macropores in one catalyst lead to a tenfold increase in catalyst lifetime. Besides the effect on the catalyst lifetime there was also a strong effect of the additional pore systems on the selectivity of the catalysts. The catalysts containing mesopores showed reduced selectivity to short chain olefins and increased selectivity to larger hydrocarbons in comparison to the catalysts without a mesopores system.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Heterogeneous catalysis; hierarchical materials; Mesoporous materials; nanostructures; Zeolites

Hierarchy concepts: classification and preparation strategies for zeolite containing materials with hierarchical porosity - Schwieger, Wilhelm; Machoke, Albert; Weissenberger, Tobias; Inayat, Amer; Selvam, Thangaraj; Klumpp, Michael; Inayat, Alexandra (Chemical Society Reviews, 2016)
'Hierarchy' is a property which can be attributed to a manifold of different immaterial systems, such as ideas, items and organisations or material ones like biological systems within living organisms or artificial, man-made constructions. The property 'hierarchy' is mainly characterised by a certain ordering of individual elements relative to each other, often in combination with a certain degree of branching. Especially mass-flow related systems in the natural environment feature special hierarchically branched patterns. This review is a survey into the world of hierarchical systems with special focus on hierarchically porous zeolite materials. A classification of hierarchical porosity is proposed based on the flow distribution pattern within the respective pore systems. In addition, this review might serve as a toolbox providing several synthetic and post-synthetic strategies to prepare zeolitic or zeolite containing material with tailored hierarchical porosity. Very often, such strategies with their underlying principles were developed for improving the performance of the final materials in different technical applications like adsorptive or catalytic processes. In the present review, besides on the hierarchically porous allzeolite material, special focus is laid on the preparation of zeolitic composite materials with hierarchical porosity capable to face the demands of industrial application.

High-density risers as reactor system for benzene synthesis by non-oxidative dehydroaromatization of methane - fluid-dynamic investigations - Hensler, Timo; Zhang, Yingxue; Mleczko, Leslaw; Assmann, Jens; Bellinghausen, Rainer; Schwieger, Wilhelm; Wirth, Karl-Ernst (11th International Conference on Fluidized Bed Technology, CFB 2014, 2014)
As a precursor for synthesis of dyes, polymers, fuel additives and various solvents benzene has become an indispensable base chemical in a large field of industrial processes. To date the industrial benzene demand is covered in large part by benzene which is extracted from crude oil. However, scarcity of oil resources accompanied by increasing prices for oil derived chemicals necessitates the development of alternative processes to satisfy the market's benzene demand. The presented work deals with the development of a reactor model for benzene synthesis by non-oxidative dehydroaromatization of methane. Based on model calculations a riser reactor operated at high solids concentrations has been found to allow for most efficient operation. Together with the model experimental data are presented in order to evaluate the fluid-dynamic feasibility of the suggested flow condition within a pilot plant scale circulating fluidized bed. Experimental data show that stable operation can be achieved at cross-section averaged solids concentrations up to 30 vol.%.

Highly dispersed Pd nanoparticles within silica: Synthesis and characterization - Ofili, Ifeanyi Jimmy; Steinrück, Hans-Peter; Schwieger, Wilhelm; Ramakrishnan, Ayyappan; Dumbuya, K.; Gottfried, Michael (Applied Clay Science, 2011)
Well dispersed and homogeneously distributed Pd nanoparticles within a silica matrix were synthesized by a two stage process: (1) intercalation of palladium tetrammine ions into the layered aluminium-free silicate Na ilerite followed by (2) a self-reduction of the complex through decomposition of the tetrammine ligands by calcination at 550°C for 5h under N or air. Samples calcined in N predominantly contained nanoparticles of metallic Pd, while calcination in air led largely to the formation of PdO, as confirmed by XPS and supported by XRD and TGA. Thus, the Pd/PdO loading in the silica can be selectively tuned through this method. The intercalates were characterized by standard methods such as XRD, TGA, ICP and TEM. TGA of the intercalates indicated that the stabilization of the palladium tetrammine complex was enhanced by intercalation into Na ilerite. Based on ICP analysis, the Pd loadings in the intercalates were estimated to be about 18mass-%, which was also in agreement with the results from TGA. TEM revealed that the Pd/PdO nanoparticles were well dispersed in the silica matrix with an average particle size of approximately 8-10nm after calcination in air. © 2010 Elsevier B.V.

Highly durable spray-coated plate catalyst for the dehydrogenation of perhydro benzyltoluene - Nathrath, Phillip; Raed Ramzi, Yousuf; Bierling, Markus; Thiele, Simon; Wasserscheid, Peter; Schühle, Patrick (Catalysis: Science and Technology, 2024)
In this study, we introduce a new spray coating technique to produce porous catalytic layers for the dehydrogenation of hydrogen carriers. The composition of the sol-gel composite dispersion is adjusted by a design of experiments (DoE) approach in order to reach excellent spraying processability, high coating stability, and a high coating load. In this way, coatings with remarkably high thicknesses of up to 500 μm, good durability, and decent adherence on stainless steel substrates were achieved. Furthermore, the precise adjustment of the coating loads and thicknesses of the highly porous γ-alumina catalyst support coating is demonstrated using the developed approach. Coating of different line-of-sight geometries, e.g., corrugated plates, is also shown. The coated plates have been impregnated with platinum and tested in the highly endothermic dehydrogenation of perhydro benzyltoluene. Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX) revealed an increasing penetration depth of platinum into the coating layer with higher platinum loadings. For the dehydrogenation reaction, high surface related productivities of 0.8 mgH2 min−1 cm−2 using a platinum loading of 3.7 wt% were reached, and the coatings proved completely mechanically stable under these hydrogen release conditions.
CRIS-Team Scopus Importer:2024-02-09

Highly Effective Propane Dehydrogenation Using Ga-Rh Supported Catalytically Active Liquid Metal Solutions - Raman, Narayanan; Maisel, Sven; Grabau, Mathias; Taccardi, Nicola; Debuschewitz, Jonas; Wolf, Moritz; Wittkämper, Haiko; Bauer, Tanja; Wu, Mingjian; Haumann, Marco; Papp, Christian; Görling, Andreas; et al. (ACS Catalysis, 2019)
Our contribution demonstrates that rhodium, an element that has barely been reported as an active metal for selective dehydrogenation of alkanes becomes a very active, selective, and robust dehydrogenation catalyst when exposed to propane in the form of single atoms at the interface of a solid-supported, highly dynamic liquid Ga-Rh mixture. We demonstrate that the transition to a fully liquid supported alloy droplet at Ga/Rh ratios above 80, results in a drastic increase in catalyst activity with high propylene selectivity. The combining results from catalytic studies, X-ray photoelectron spectroscopy, IR-spectroscopy under reaction conditions, microscopy, and density-functional theory calculations, we obtained a comprehensive microscopy picture of the working principle of the Ga-Rh supported catalytically active liquid metal solution.
CRIS-Team Scopus Importer:2019-10-18
Keywords: alkane; alkene; catalysis; dehydrogenation; gallium; rhodium

Highly Effective Pt-Based Water-Gas Shift Catalysts by Surface Modification with Alkali Hydroxide Salts - Kusche, Matthias Manfred; Bustillo, Karen; Agel, Friederike; Wasserscheid, Peter (ChemCatChem, 2015)
Herein, we describe an economical and convenient method to improve the performance of Pt/alumina catalysts for the water-gas shift reaction through surface modification of the catalysts with alkali hydroxides according to the solid catalyst with ionic liquid layer approach. The results are in agreement with our findings reported earlier for methanol steam reforming. This report indicates that alkali doping of the catalyst plays an important role in the observed catalyst activation. In addition, the basic and hygroscopic nature of the salt coating contributes to a significant improvement in the performance of the catalyst. During the reaction, a partly liquid film of alkali hydroxide forms on the alumina surface, which increases the availability of H2O at the catalytically active sites. Kinetic studies reveal a negligible effect of the KOH coating on the rate dependence of CO and H2O partial pressures. TEM studies indicate an agglomeration of the active Pt clusters during catalyst preparation; restructuring of Pt nanoparticles occurs under reaction conditions, which leads to a highly active and stable system over 240 h time on stream. Excessive pore fillings with KOH introduce a mass transfer barrier as indicated in a volcano-shaped curve of activity versus salt loading. The optimum KOH loading was found to be 7.5 wt%.
Keywords: electron microscopy; heterogeneous catalysis; ionic liquids; platinum; water-gas shift reaction

Highly efficient and selective C-H activation in gallium-containing molten-salt systems. - Wasserscheid, Peter; Weiss, Tobias; Agel, Friederike; Werth, Christiane; Jess, Andreas; Forster, Rüdiger (Angewandte Chemie International Edition, 2007)
Isobutane was prepd. with high selectivity from CH4 via chloromethane reaction with Ga0 suspended in a molten-salt or ionic liq. medium, without catalysts. The molten-salt medium comprises AlCl3, LiCl, [Me3NCH2C6H5]Cl. During the reaction, hydrogen and GaI and GaIII chlorogallate species are formed. The latter can be electrochem. reduced back to Ga0 in a subsequent step. The chlorine liberated in this Ga0 regeneration can be used for the synthesis of chloromethane feedstock from methane. [on SciFinder(R)]
Keywords: methane reaction gallium chloromethane route isobutane prepn molten salt; aluminum chloride trimethylbenzylammonium chloromethane reaction medium

Highly efficient and selective C-H-activation in gallium containing molten salt systems: Toward a fundamentally new route for CH4 valorization. - Wasserscheid, Peter; Weiss, Tobias; Agel, Friederike (Abstracts of Papers, 236th ACS National Meeting, Philadelphia, PA, United States, August 17-21, 2008, 2008)
Rational and efficient conversion of methane to more useful higher hydrocarbons is an important topic in natural gas utilization. Today, methane activation is mostly carried out in an indirect way via transformation of methane to syngas (a mixt. of CO and hydrogen) which then is converted into higher hydrocarbons by Fischer-Tropsch synthesis or via methanol. A true alternative for indirect methane conversion is the use of chloromethane as the activated intermediate. In our labs. chloromethane has been found to react with Ga(0) suspended in an ionic liq./molten salt medium with very high selectivities (up to 97% of gaseous products) to isobutane. During the reaction hydrogen and anionic chlorogallate species of Ga(I) and Ga(III) are formed. The latter can be regenerated to Ga(0) electrochem. in a subsequent step using the molten salt medium as electrolyte. The chlorine liberated in the Ga(0) regeneration can be applied for the synthesis of the chloromethane feedstock from methane thus making this new reaction the potential key-step of a fundamentally new process chain for methane valorization. [on SciFinder(R)]

Highly efficient, low-temperature hydrogen release from perhydro-benzyltoluene using reactive distillation - Geißelbrecht, Michael; Mrusek, Stephan; Mueller, K.; Preuster, P.; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2020)
The need to supply significant amounts of heat at the high temperature level required thermodynamically for cycloalkane dehydrogenation has so far been seen as the main hurdle to bring the otherwise highly attractive Liquid Organic Hydrogen Carrier (LOHC) technology to broad technical use. The LOHC technology promises infrastructure-compatible storage and transport of hydrogen in chemically bound form,e.g.for long-term energy storage, global energy logistics and heavy-duty mobility. Our contribution shows that hydrogen release from the hetero-atom free, pure hydrocarbon LOHC compound perhydro-benzyl toluene is possible at temperatures down to 200 degrees C, if the operation is carried out in a reactive distillation column under reduced pressure. Such low temperature dehydrogenation of hydrocarbon-based LOHC systems facilitates heat integration with waste heat sources and the energetic use of the released hydrogen considerably, and this will greatly enhance the attractiveness of LOHC-based hydrogen storage for many applications.
CRIS-Team WoS Importer:2020-10-02

Highly enantioselective Ru-catalyzed asymmetric hydrogenation of β-keto ester in ionic liquid/methanol mixtures - Öchsner, Eva; Schneiders, Karola; Junge, Kathrin; Beller, Matthias; Wasserscheid, Peter (Applied Catalysis A-General, 2009)
The enantioselective hydrogenation of methyl acetoacetate (MAA) was studied in detail using a ruthenium-monodentate binaphthophosphepine complex in a homogeneous solution formed by different ionic liquids and methanol. Remarkably, ionic liquid additives did not only open an attractive way for catalyst recycling in repetitive batch-mode but also led to significantly increased catalytic activity compared to pure methanol. Enantioselectivities up to 95% have been achieved in mixed ionic liquid/methanol systems which are comparable to the values obtained in pure methano

Highly Selective Aromatic Alkylation of Phenol and Anisole by Using Recyclable Brønsted Acidic Ionic Liquid Systems - Titze-Frech, Karin; Ignatiev, Nikolai; Uerdingen, Marc; Schulz, Peter; Wasserscheid, Peter (European Journal of Organic Chemistry, 2013)
A highly efficient ionic liq. catalyst system for selective alkylation of phenol and anisole with alkenes is described. By using Bronsted acidic triflate ionic liqs. contg. the SO3H group attached to the cation, it was possible to recycle the catalyst and reuse it after a simple workup procedure. Moreover, selectivity towards the monoalkylated products e. g., I, was improved to 93 % by using a biphasic system. [on SciFinder(R)]
Keywords: alkyl phenol alkyl anisole prepn; phenol anisole alkene alkylation ionic liq catalyst

Highly selective synthesis of acrylic acid from lactide in the liquid phase - Nagengast, Jens; Hahn, Simon; Taccardi, Nicola; Kehrer, Matthias; Kadar, Julian; Collias, Dimitris; Dziezok, Peter; Wasserscheid, Peter; Albert, Jakob (ChemSusChem, 2018)
A new reaction system for the highly selective, hydrobromic acid catalyzed conversion of lactide into acrylic acid under mild conditions is reported. The applied liquid reaction system consists of a temperature‐stable bromide‐containing ionic liquid and 2‐bromopropionic acid as a source of dry HBr, with no volatile organic solvent being used. This allows for the in situ removal of the formed acrylic acid, leading to an unmatched acrylic acid selectivity of over 72 % at full lactide conversion. Accounting for leftover reaction intermediates on the way to acrylic acid, which could be recycled in an elaborate continuous process, the proposed reaction system shows potential for acrylic acid yields well above 85 % in the liquid phase. This opens new avenues for the effective conversion of biogenic lactic acid (e.g., obtained by fermentation from starch) to acrylic acid. The resulting bio‐acrylic acid is a highly attractive product for, for example, the diaper industry, where we expect consumers to be especially sensitive to aspects of sustainability.

Highly Selective Synthesis of Methanol from Glucose in a Two‐Step Process - Haagen, Vera; Schörner, Markus; Albert, Jakob; Franken, Tanja; Schühle, Patrick (Chemie Ingenieur Technik, 2022)

High performance direct organic fuel cell using the acetone/isopropanol liquid organic hydrogen carrier system - Hauenstein, Pascal; Seeberger, Dominik; Wasserscheid, Peter; Thiele, Simon (Electrochemistry Communications, 2020)
Liquid Organic Hydrogen Carrier (LOHC) systems offer a very interesting option for hydrogen storage in the existing infrastructure for common fuels. Technically most attractive is the direct use of LOHC-bound hydrogen in a low-temperature PEM fuel cell. Here, the isopropanol/acetone LOHC system is suggested to produce electricity from a condensable liquid without CO2 emissions. A high-performance direct isopropanol fuel cell using a vaporizer and a commercial fuel cell test system is demonstrated. For the first time backpressure is used to enhance the performance. The self-fabricated GDEs combined with a Nafion composite membrane achieved a power density of 203 mW cm−2 for Isopropanol/Air operation at 300 kPa absolute and 85 °C. By increasing the operation temperature to 100 °C a peak power density of 254 mW cm−2 is achieved, exceeding the highest reported values for isopropanol fuel cells operated with air by over 80%. The observed increase in performance can be attributed to the higher reaction rate of the electrooxidation of isopropanol at the anode side during pressurized conditions and to the reduced acetone-poisoning of the Pt-Ru catalyst at elevated temperatures.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Backpressure; Direct isopropanol fuel cells; LOHC; Organic fuel cells; Temperature

High selectivity of TiC-CDC for CO2/N2 separation - Silvestre-Albero, Ana; Rico-Frances, Soledad; Rodriguez-Reinoso, Francisco; Kern, Andreas; Klumpp, Michael; Etzold, Bastian; Silvestre-Albero, Joaquin (Carbon, 2013)
A series of carbide-derived carbons (CDC) have been prepared starting from TiC and using different chlorine treatment temperatures (500–1200 °C). Contrary to N2 adsorption measurements at -196 °C, CO2 adsorption measurements at room temperature and high pressure (up to 1 MPa) together with immersion calorimetry measurements into dichloromethane suggest that the synthesized CDC exhibit a similar porous structure, in terms of narrow pore volume, independently of the temperature of the reactive extraction treatment used (samples synthesized below 1000 °C). Apparently, these carbide-derived carbons exhibit narrow constrictions were CO2 adsorption under standard conditions (0 °C and atmospheric pressure) is kinetically restricted. The same accounts for a slightly larger molecule as N2 at a lower adsorption temperature (-196 °C), i.e. textural parameters obtained from N2 adsorption measurements on CDC must be underestimated. Furthermore, here we show experimentally that nitrogen exhibits an unusual behavior, poor affinity, on these carbide-derived carbons. CH4 with a slightly larger diameter (0.39 nm) is able to partially access the inner porous structure whereas N2, with a slightly smaller diameter (0.36 nm), does not. Consequently, these CDC can be envisaged as excellent sorbent for selective CO2 capture in flue-gas streams.
EAM Import::2019-03-13

High-yielding Sandmeyer reaction on immobilized Cu(I)/Cu(II)-based catalysts - Tarkhanova, Irina; Gantman, Mikhail; Sigeev, Alexander; Maslakov, Konstantin; Zelikman, Vladimir; Beletskaya, Irina (Mendeleev Communications, 2018)

Homogeneously-catalysed hydrogen release/storage using the 2-methylindole/2-methylindoline LOHC system in molten salt-organic biphasic reaction systems - Soegaard, Alexander; Scheuermeyer, Marlene; Bösmann, Andreas; Wasserscheid, Peter; Riisager, Anders (Chemical Communications, 2019)
Ir-Complex catalysed hydrogen release/storage using a 2-methylindole/2-methylindoline Liquid Organic Hydrogen Carrier (LOHC) system is shown to be effective in a temperature range of 120 to 140 8C. In the form of a liquid-liquid biphasic reaction systemwithmolten [PPh4][NTf2] as catalyst immobilisation phase, the applied cationic Ir-complex can be easily separated and recycled enabling a small amount of ionic catalyst solution to store/release a large amount of hydrogen.
CRIS-Team WoS Importer:2019-02-27

Homogeneous ruthenium-based water–gas shift catalysts via supported ionic liquid phase (SILP) technology at low temperature and ambient pressure - Werner, Sebastian; Szesni, Normen; Fischer, Richard; Haumann, Marco; Wasserscheid, Peter (Physical Chemistry Chemical Physics, 2009)
Novel ruthenium-based supported ionic liquid phase (SILP) catalysts for the water–gas shift (WGS) reaction are reported which, compared to classical low temperature shift systems, operate at much lower temperatures and even at ambient pressure.

Hydrogenation of aromatic and heteroaromatic compounds-a key process for future logistics of green hydrogen using liquid organic hydrogen carrier systems - Jorschick, Holger; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (Sustainable Energy & Fuels, 2021)
This review deals with the chemical storage of green hydrogen in the form of Liquid Organic Hydrogen Carrier (LOHC) systems. LOHC systems store hydrogen by an exothermal catalytic hydrogenation reaction that converts the hydrogen-lean compounds of the LOHC system to their hydrogen-rich counterparts. All compounds of a technically suitable LOHC system are liquids and this offers the advantage of simple logistics of chemically bound hydrogen in the existing infrastructure for fuels. On demand, hydrogen can be released from the hydrogen-rich LOHC molecule in an endothermal catalytic dehydrogenation at low hydrogen pressure (typically below 5 bar). Our contribution deals first with available sources of green hydrogen for a future hydrogen economy and then describes established technical processes to produce clean hydrogen from technically hydrogen-rich gas mixtures. Subsequently, the review focuses on the hydrogenation of aromatic and heteroaromatic compounds as the key step of the LOHC-based hydrogen storage cycle. Special emphasis is given to the hydrogen-charging of hydrogen-lean LOHC compounds with various gas mixtures demonstrating that such a Mixed Gas Hydrogenation (MGH) process offers the technical potential to selectively extract hydrogen in a chemically bound form that enables very efficient hydrogen logistics. In this way, low cost hydrogen sources can be connected to high value hydrogen application, e.g. hydrogen filling stations for clean mobility applications, to enable a future hydrogen economy.
CRIS-Team Scopus Importer:2021-03-19

Hydrogenation of liquid organic hydrogen carrier systems using multicomponent gas mixtures - Jorschick, H.; Vogl, M.; Preuster, P.; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2019)
The cost of industrial hydrogen production and logistics, and the purity of hydrogen produced from different technologies are two critical aspects for the success of a future hydrogen economy. Here, we present a way to charge the Liquid Organic Hydrogen Carrier (LOHC) dibenzyltoluene (H0-DBT) with industrially relevant, CO2- and CO-containing gas mixtures. As only hydrogen binds to the hydrogen-lean carrier molecule, this process step extracts hydrogen from the gas mixture and binds it selectively to the carrier. Pd on alumina has been identified as the most promising catalyst system for successfully hydrogenating H0-DBT using model gas mixtures resembling the compositions produced in methane reforming and in industrial coke production (up to 50% CO2 and 7% CO). Up to 80% of the hydrogen present in the feedstock mixture could be extracted during the LOHC hydrogenation process. 99.5% of the reacting hydrogen was selectively bound to the H0-DBT LOHC compound. The purity of hydrogen released from the resulting perhydro dibenzyltoluene previously charged with the hydrogen-rich gas mixture proved to be up to 99.99 mol%.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Carbon monoxide; Hydrogen separation; Hydrogen storage; Hydrogenation; LOHC systems; Stranded gas

Hydrogenation of the liquid organic hydrogen carrier compound dibenzyltoluene – reaction pathway determination by 1H NMR spectroscopy - Do, Truong Giang; Preuster, Patrick; Aslam, Rabya; Bösmann, Andreas; Müller, Karsten; Arlt, Wolfgang; Wasserscheid, Peter (Reaction Chemistry & Engineering, 2016)
The catalytic hydrogenation of the LOHC compound dibenzyltoluene (H0-DBT) was investigated by 1H NMR spectroscopy in order to elucidate the reaction pathway of its charging process with hydrogen in the context of future hydrogen storage applications. Five different reaction pathways during H0-DBT hydrogenation were considered including middle-ring preference (middle-side-side, MSS), side-middle-side order of hydrogenation (SMS), side-ring preference (SSM), simultaneous hydrogenation of all three rings without intermediate formation and statistical hydrogenation without any ring preference. Detailed analysis of the 1H NMR spectra of the H0-DBT hydrogenation over time revealed that the reaction proceeds with a very high preference for the SSM order at temperatures between 120 °C and 200 °C and 50 bar in the presence of a Ru/Al2O3-catalyst. HPLC analysis supported this interpretation by confirming an accumulation of H12-DBT species prior to full hydrogenation to H18-DBT with middle ring hydrogenation as the final step.

Hydrogen, chemically stored - Papp, Christian; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter (Nachrichten aus der Chemie, 2014)

Hydrogen extraction from methane-hydrogen mixtures from the natural gas grid by means of electrochemical hydrogen separation and compression - Mrusek, Stephan; Blasius, Marco; Morgenroth, Frank; Thiele, Simon; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2023)
One interesting option to store and transport hydrogen in the future is to blend it into the natural gas grid. In this paper, we present technological insights regarding electrochemical hydrogen separation and compression (EHC/S), a technology that enables extraction of compressed and purified hydrogen from such blends. Our contribution discusses two use cases, namely i) hydrogen separation to recover purified hydrogen under pressure, and ii) hydrogen removal to protect downstream methane consumers from excessive hydrogen levels. Our experimental work with a laboratory scale EHC/S centers on efficiency aspects. We show that at low hydrogen contents in dry feed gas, gas humidification causes relevant thermal energy consumption, that cannot be provided by EHC/S waste heat. We also show that hydrogen recovery is restricted by mass transport if the residence time in the EHC device is too short. Simultaneous hydrogen separation and compression from 5% hydrogen in methane is demonstrated yielding hydrogen at 6 bara at the cathode.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Electrochemical hydrogen compression; Electrochemical hydrogen separation; Hydrogen purification; Hydrogen storage; Natural gas grid

Hydrogen production from wet biomass via a formic acid route under mild conditions - Kroll, Fabian; Schörner, Markus; Schmidt, Matthias; Kohler, Florian T.U.; Albert, Jakob; Schühle, Patrick (International Journal of Hydrogen Energy, 2024)
Renewable Hydrogen is a key building block for a sustainable energy economy. An attractive resource for its production is waste biomass. This contribution analyses a promising new Biomass-to-H2 two-step approach, consisting of (1) biomass oxidation to formic acid and methyl formate in the so-called OxFA-Process and (2) hydrogen generation by dehydrogenation or decarbonylation of these intermediates. This contribution explains a novel hydrogen production concept and compares three distinct process routes for their efficient implementation. By using Aspen Plus® V12 the process was designed and optimized to achieve maximum hydrogen yield. An economic analysis allowed to compare the different characteristics of each process concept and to select the most promising option. The chosen concept was subject to a detailed cost and sensitivity analysis showing that this new route has high potential and competitiveness for hydrogen production from waste biomass.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Biomass oxidation; Decentral production; Formic acid; Hydrogen; Technoeconomic analysis

Hydrogen solubility, interfacial tension, and density of the liquid organic hydrogen carrier system diphenylmethane/dicyclohexylmethane - Jander, Julius Hans; Schmidt, Patrick; Giraudet, Cédric; Wasserscheid, Peter; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2021)
In the present study, physico-chemical properties of the liquid organic hydrogen carrier (LOHC) system diphenylmethane/dicyclohexylmethane in the presence of dissolved hydrogen are presented for temperatures up to 523 K and pressures up to 10 MPa. Solubility of hydrogen, interfacial tension, and liquid density were measured by the isochoric saturation method, the pendant-drop method, and vibrating-tube method, respectively, which are realized in two experimental setups. The solubility of hydrogen increases with increasing temperature and pressure. For the fully hydrogenated dicyclohexylmethane, it is about 50% higher than for the non-hydrogenated diphenylmethane and similar to that of a mixture from a deliberately stopped hydrogenation process containing also partially hydrogenated cyclohexylphenylmethane. While the interfacial tension decreases slightly with increasing hydrogen pressure at constant temperature, the density remains approximately constant. The latter properties obtained for different mixtures with similar degree of hydrogenation show that the influence of the presence of cyclohexylphenylmethane is small.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Density; Dissolved hydrogen; Interfacial tension; LOHC systems; Solubility

Hydrogen Storage in a Pressure Swing Reactor – Development of a Continuous Reactor Design. - Dürr, Stefan; Wagner, Lisa; Preuster, Patrick; Wasserscheid, Peter (1st INTERNATIONAL YOUNG PROFESSIONALS CONFERENCE ON PROCESS ENGINEERING (YCOPE 2019), 2019)
Hydrogen storage via reversible catalytic hydrogenation and dehydrogenation of Liquid Organic Hydrogen Carrier (LOHC) molecules such as dibenzyltoluene, has outgrown laboratory scale setups. LOHC storage systems now are commercially available and prove to be a safe and practical solution for hydrogen storage. [1] A state of the art LOHC-system intended for hydrogen transport comprises separate hydrogenation and dehydrogenation units: One at the site of hydrogen production and another one on the site of hydrogen demand. However, it was recently shown that both reactions can be implemented in a simple one-reactor setup using only one Pt-catalyst. [2,3] Consequently, given an adequately high temperature, the reaction mode can be set to hydrogenation or dehydrogenation by applying the appropriate pressure. This provides for a highly dynamic, more cost- and energy efficient plant design for scenarios in which no transport is intended. Moving from semi-batch to continuous mode offers several advantages such as more efficient noble metal use and separate scaling of capacity and maximum input/output rate of hydrogen. In this flow-battery-like setup, capacity solely depends on tank size while maximum hydrogen flow is determined by reactor design. Thus the combination of a compact, high-performance reactor and cost-effective, refillable tanks allows highly flexible solutions for a variety of hydrogen storage and supply scenarios. To account for the reaction enthalpies of both reactions our oneReactor concept is based on a shell-and-tube heat exchanger design. Multiple catalyst containing, vertical tube reactors are employed in co- or counter-current trickle-bed mode. Since frequent change from hydrogenation to dehydrogenation mode and varying reaction times lead to differing feed compositions, a liquid loop is applied to obtain a more stable mode of operation. In this poster presentation we show the feasibility of the oneReactor-concept as well as first experimental results. Furthermore examples of system integration in both energy-storage and hydrogen supply will be discussed. [1] Preuster, P., et al. (2017). “Liquid Organic Hydrogen Carriers (LOHCs): “Toward a Hydrogen-Free Hydrogen Economy,” ACCOUNTS OF CHEMICAL RESEARCH 50 (1): 74-85 [2] Jorschick, J., et al. (2017). “Hydrogen Storage Using a Hot Pressure Swing Reactor,” ENERGY & ENVIRONMENTAL SCIENCE 10 (1): 1652-1659 [3] Jorschick, J., et al. (2018). “Operational Stability of a LOHC-based Hot Pressure Swing Reactor for Hydrogen Storage,” ENERGY TECHNOLOGY 10.1002/ente.201800499, (early access) </

Hydrogen Storage: Thermochemical Studies of N-Alkylcarbazoles and Their Derivatives as a Potential Liquid Organic Hydrogen Carriers - Emel'Yanenko, Vladimir N.; Varfolomeev, Mikhail A.; Verevkin, Sergey P.; Stark, Katharina; Müller, Karsten; Müller, Michael; Bösmann, Andreas; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Physical Chemistry C, 2015)
Although N-ethylcarbazole is considered as a most promising potential liquid organic hydrogen carriers (LOHC) substance, a major drawback for stationary and particularly mobile applications is its high melting point of 343 K. Study of other possible N-alkylcarbazole-derivatives having lower melting points but keeping a high storage density is of practical importance. This contribution presents thermochemical properties (enthalpy of formation, enthalpy of vaporization, enthalpy of sublimation, and fusion enthalpy) for N-alkylcarbazoles (with alkyl = isopropyl, n-propyl, and n-butyl) derived from experiments in order to investigate the applicability of the carbazole derivatives as potential LOHCs. Additionally, high-level quantum chemical calculations were applied to determine molar enthalpies of formation of the gaseous carbazole derivatives and thus validated the experimental findings. Using a combination of the quantum-chemical calculations with vaporization enthalpy data measured in this work, the standard molar liquid phase enthalpies of formation were derived for alkylcarbazole derivatives. Results of this study were applied for thermodynamic analysis of the liquid-phase reversible hydrogenation/dehydrogenation processes with N-alkylcarbazoles.

Hydrogen storage using a hot pressure swing reactor - Jorschick, Holger; Preuster, Patrick; Dürr, Stefan; Seidel, Alexander; Müller, Karsten; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2017)
Our contribution demonstrates that hydrogen storage in stationary Liquid Organic Hydrogen Carrier (LOHC) systems becomes much simpler and significantly more efficient if both, the LOHC hydrogenation and the LOHC dehydrogenation reaction are carried out in the same reactor using the same catalyst. The finding that the typical dehydrogenation catalyst for hydrogen release from perhydro dibenzyltoluene (H18-DBT), Pt on alumina, turns into a highly active and very selective dibenzyltoluene hydrogenation catalyst at temperatures above 220 °C paves the way for our new hydrogen storage concept. Herein, hydrogenation of H0-DBT and dehydrogenation of H18-DBT is carried out at the same elevated temperature between 290 and 310 °C with hydrogen pressure being the only variable for shifting the equilibrium between hydrogen loading and release. We demonstrate that the heat of hydrogenation can be provided at a temperature level suitable for effective dehydrogenation catalysis. Combined with a heat storage device of appropriate capacity or a high pressure steam system, this heat could be used for dehydrogenation.

Hydrogen Storage via Pressure Swing Reaction – Development and Advantages of Continuous Reactor Design - Dürr, Stefan; Wagner, Lisa; Steinberger, Michael; Geiling, Johannes; Preuster, Patrick; Oechsner, Richard; Wasserscheid, Peter (Integration of Sustainable Energy Conference, Nürnberg, 2018)

Hydrogen Storage via Pressure Swing Reaction – from Batch to Continuous Reactor Design - Dürr, Stefan; Wagner, Lisa; Preuster, Patrick; Wasserscheid, Peter (World Hydrogen Energy Conference, 2018)

Identification of Reaction Pathways and Kinetic Modeling of Olefin Interconversion over an H-ZSM-5 Catalyst - Warnecke, Felix; Lin, Lin; Haag, Stephane; Freund, Hannsjörg (Industrial & Engineering Chemistry Research, 2020)
Kinetic investigations with a commercial H-ZSM-5 catalyst were performed to enable the modeling of the interconversion reactions of olefins in a temperature range from 420 to 490 degrees C. Different olefin feedstocks ranging from C2 up to C7 were investigated using a Berty-type reactor. Additional mixed olefin feedstock experiments were performed to obtain improved information about the bimolecular reaction pathways. The experiments include a wide range of conversions to cover the full range of typical industrial process conditions. The reaction pathways and the rate law approach of olefin cracking were analyzed systematically to identify a suitable and comprehensive model structure. A lumped kinetic model with 11 interconversion reactions based on a Langmuir-Hinshelwood-Hougen-Watson approach is found to be the best trade-off between accuracy and model complexity. The comparison between the model and experiments demonstrates that the kinetic model can predict the olefin behavior with a high accuracy for mixed as well as single olefin feedstock. A detailed kinetic model for the formation of side products has also been derived but will be discussed separately in another publication on hydrogen transfer on H-ZSM-5. Compared to existing kinetic models, the kinetic model proposed in this work shows distinct advantages because of the use of mixed feedstock, the widest range of conversions investigated so far, the use of a gradient-free and isothermal Berty-type reactor, and high-performance online gas chromatography analytics.
CRIS-Team WoS Importer:2020-08-07

Immobilization of a selective Ru-pincer complex for low temperature methanol reforming–Material and process improvements - Schwarz, Christian; Agapova, Anastasiya; Junge, Henrik; Haumann, Marco (Catalysis Today, 2020)
A homogeneous Ru-pincer complex was immobilized by the supported liquid phase (SLP) technique and tested in continuous gas-phase steam reforming of methanol. Variations of catalyst composition (liquid phase, base and catalyst loading) as well as process parameters (temperature, flow rate) were carried out. High activity was obtained when ionic liquids were used for catalyst immobilization. However, better stability was obtained in the absence of ionic liquids using pure KOH.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Catalyst immobilization; Hydrogen production; Low temperature catalysis; Methanol reforming; Pincer complex; Ruthenium; Supported liquid phase (SLP)

Immobilization of Aspergillus sp. laccase on hierarchical silica MFI zeolite with embedded macropores - Tocco, Davide; Wisser, Dorothea; Fischer, Marcus; Schwieger, Wilhelm; Salis, Andrea; Hartmann, Martin (Colloids and Surfaces B: Biointerfaces, 2023)
Laccase from Aspergillus sp. (LC) was immobilized on functionalized silica hierarchical (microporous-macroporous) MFI zeolite (ZMFI). The obtained immobilized biocatalyst (LC#ZMFI) was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (ATR-FTIR), N2 adsorption/desorption isotherms, solid-state NMR spectroscopy and thermogravimetric analysis (TGA) confirming the chemical anchoring of the enzyme to the zeolitic support. The optimal pH, kinetic parameters (KM and Vmax), specific activity, as well as both storage and operational stability of LC#ZMFI were determined. The LC#ZMFI KM and Vmax values amount to 10.3 µM and 0.74 µmol·mg−1 min−1, respectively. The dependence of specific activity on the pH for free and immobilized LC was investigated in the pH range of 2–7, The highest specific activity was obtained at pH = 3 for both free LC and LC#ZMFI. LC#ZMFI retained up to 50 % and 30 % of its original activity after storage of 21 and 30 days, respectively. Immobilization of laccase on hierarchical silica MFI zeolite allows to carry out the reaction under acidic pH values without affecting the support structure.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Enzyme activity; Enzyme immobilization; Hierarchical porous materials; Laccase; Zeolite

Immobilized catalytically active composition for hydroformylation of olefin-containing mixtures. - Dyballa, Katrin M.; Franke, Robert; Hahn, Hanna; Becker, Marc; Schönweiz, Andreas; Debuschewitz, Jonas; Walter, Simon; Woelfel, Rene; Haumann, Marco; Wasserscheid, Peter; Kaftan, Andre; Laurin, Mathias; et al. (2014)
Compn. used as a catalyst for hydroformylation of olefinically unsatd. hydrocarbon mixts. comprises a metal complex, esp. an Rh complex having a phosphine or phosphite ligand, on an inert porous carrier, and is loaded for the purposes of the hydroformylation with the aldol byproduct of the desired aldehyde, in the manner of an application of the "Supported Liq. Phase" (SLP) concept. Thus, aldol ( 2-Methylpent-2-enal) doping leads to increasing yield of propanal as a product of hydroformylation of ethylene with H2 and CO on a solid catalyst consisting of acetylacetonatodicarbonylrhodium supported on Trisopor 423. [on SciFinder(R)]
Keywords: immobilized hydroformylation catalyst olefin aldehyde

Immobilized Ru-Pincer Complexes for Continuous Gas-Phase Low-Temperature Methanol Reforming-Improving the Activity by a Second Ru-Complex and Variation of Hydroxide Additives - Schwarz, Christian; Kraus, Dominik; Alberico, Elisabetta; Junge, Henrik; Haumann, Marco (European Journal of Inorganic Chemistry, 2021)
Ru-pincer complexes were immobilized as supported liquid phase (SLP) materials to allow the methanol reforming reaction as continuous gas phase process. Under reaction conditions, the liquid phase forms from the hydroxide coating. Several hydroxides were screened and CsOH showed highest activity compared to the standard KOH coating. The well-known Ru-pincer complex carbonylchlorohydrido [bis(2-di-i-propylphosphinoethyl)amine]ruthenium(II) is limited in catalyzing the final step of the methanol reforming. Addition of a second complex, having a methylated backbone in the pincer-ligand, could overcome these limitations. Significant enhancement of the overall catalytic activity was observed.
CRIS-Team WoS Importer:2021-05-28

Impact of catalyst loading, ionomer content, and carbon support on the performance of direct isopropanol fuel cells - Hauenstein, Pascal; Mangoufis Giasin, Iosif; Seeberger, Dominik; Wasserscheid, Peter; Mayrhofer, Karl; Katsounaros, Ioannis; Thiele, Simon (Journal of Power Sources Advances, 2021)
Liquid Organic Hydrogen Carriers (LOHC) offer a promising solution for hydrogen storage in the existing infrastructure for conventional fuels. Within this framework, the isopropanol/acetone couple as a light-LOHC system is used to generate electricity in a direct isopropanol fuel cell (DIFC). This work focuses on the impact of catalyst loading, ionomer content and catalyst support on the performance of DIFCs. We achieve a performance rise from 95 mW cm-2 to 219 mW cm-2 under air operation by increasing the anode catalyst loading from 0.5 mg cm-2 to 4 mg cm-2, which can be attributed to the increased abundance of active catalyst sites with higher loadings. In contrast, we find that the cathode loading for the oxygen reduction reaction (ORR) plays a minor role in the performance of DIFCs. Therefore, the cathode loading can be minimized to decrease the total amount of platinum-group metals and, consequently, to save cost. It was also found that an ionomer content of 30% on the anode side is optimal. Additionally, different carbon supports were investigated, where advanced high surface area carbon support showed superior performance to Vulcan with an increase of 20% in power density, motivating the development of new carbon supports for DIFCs.
CRIS-Team Scopus Importer:2021-07-30
Keywords: 2-propanol fuel cell; Carbon support; Catalyst loading; Direct isopropanol fuel cells; Ionomer content; LOHC; Organic fuel cells

Impact of Gd-, La-, Nd- and Y-doping on the textural, electrical conductivity and N2O decomposition activity of CuO catalyst - Schwieger, Wilhelm; Abu-Zied, Bahaa M.; Bawaked, Salem M.; Kosa, Samia A. (International Journal of Electrochemical Science, 2016)
In this paper, a series of rare earth (Gd, La, Nd, and Y) doped CuO catalysts have been successfully prepared by using the microwave assisted co-precipitation method and tested for NO direct decomposition. The decomposition pathway of the catalysts precursors was followed up using thermogravimetric analysis (TGA). Several physico-chemical techniques were used in the characterization of the obtained catalysts including XRD, FT-IR, FE-SEM, TEM, N adsorption, XPS, and H-TPR. Structural analysis revealed the formation of nanocrystalline monoclinic CuO as a major phase in all the prepared catalysts together with minor amount of the rare earth oxides. FE-SEM and TEM observations revealed the smaller crystallites sized of the rare earth-containing catalysts compared to the bare CuO one. All the rare earth-doped CuO catalysts showed higher activity and improved electrical conductivity compared to the bare CuO. The activity enhancement of the added rare earth oxides were discussed in terms of the electrical conductivity as well as the structural characterization results.
Keywords: CuO catalyst; Electrical conductivity; Greenhouse gases; N2O decomposition; Nitrous oxide; Rare earth promoted-CuO

Improved activity and stability of lipase immobilized in cage-like large pore mesoporous organosilicas - Zhou, Zhou; Inayat, Alexandra; Schwieger, Wilhelm; Hartmann, Martin; Hartmann, Martin (Microporous and Mesoporous Materials, 2012)
Lipase from Thermomyces lanuginosus has been immobilized in different mesoporous organosilicas (PMOs) containing ethane and benzene groups with large cage-like pores. The immobilization of lipase as well as the application of these catalysts in hydrolysis and transesterification reactions is studied in detail. The results show that the structural properties of the support employed have a significant influence on the adsorption capacity. In general, materials with high specific surface areas and pore volumes show high adsorption capacity. However, in the case of monolayer adsorption, the hydrophobicity of the surface has a significant impact on the adsorption efficiency due to strong hydrophobic interactions. Furthermore, the transesterification of vinyl propionate with 1-butanol catalyzed by immobilized lipase was studied. The influence of lipase loading, the effect of water content in the reaction mixture and the influence of different solvents were investigated. The results show that lipase immobilized in the most hydrophobic material (LPbenzene) exhibits excellent catalytic performance, which is attributed to the enhanced interfacial activity of lipase due to the interaction between lipase and the hydrophobic surface of the material. In order to further disclose the influence of the hydrophobic surface on the lipase activity, ATR-FTIR spectroscopy was used to study the secondary structure of lipase immobilized on different supports. The results confirm that a structural transition of entrapped lipase to the open-lid conformation takes place on LPbenzene, which shows that the observed increase in enzymatic activity is triggered by interfacial activation of lipase. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cage-like PMOs; Lipase; Transesterification; IR spectroscopy

Improvement of hydrogen storage capacity of aminoborane/ionic liquid systems by ionic liquids with functional groups. - Assenbaum, Daniel; Gerhard, Dirk; Schulz, Peter; Wasserscheid, Peter (Chemie Ingenieur Technik, 2009)

Improving control of carbide-derived carbon microstructure by immobilization of a transition-metal catalyst within the shell of carbide/carbon core shell structures - Ariyanto, Teguh; Gläsel, Jan-Sebastian; Kern, Andreas; Zhang, Guirong; Etzold, Bastian (Beilstein Journal of Nanotechnology, 2019)
Carbon materials for electrical energy devices, such as battery electrodes or fuel-cell catalysts, require the combination of the contradicting properties of graphitic microstructure and porosity. The usage of graphitization catalysts during the synthesis of carbide-derived carbon materials results in materials that combine the required properties, but controlling the microstructure during synthesis remains a challenge. In this work, the controllability of the synthesis route is enhanced by immobilizing the transition-metal graphitization catalyst on a porous carbon shell covering the carbide precursor prior to conversion of the carbide core to carbon. The catalyst loading was varied and the influence on the final material properties was characterized by using physisorption analysis with nitrogen as well as carbon dioxide, X-ray diffraction, temperature-programmed oxidation (TPO), Raman spectroscopy, SEM and TEM. The results showed that this improved route allows one to greatly vary the crystallinity and pore structure of the resulting carbide-derived carbon materials. In this sense, the content of graphitic carbon could be varied from 10-90 wt % as estimated from TPO measurements and resulting in a specific surface area ranging from 1500 to 300 m(2)g(-1).
CRIS-Team WoS Importer:2019-02-21

Improving the fractionated catalytic oxidation of lignocellulosic biomass to formic acid and cellulose by using design of experiments - Voß, Dorothea; Pickel, Heike; Albert, Jakob (ACS Sustainable Chemistry & Engineering, 2019)
Keywords: Biomass fractionization; selective catalytic oxidation; Formic acid; Lignocellulose; Design of experiments

Improving the Performance of Supported Ionic Liquid Phase Catalysts for the Ultra-Low-Temperature Water Gas Shift Reaction Using Organic Salt Additives - Wolf, Patrick; Wick, Christian; Mehler, Julian; Blaumeiser, Dominik; Schötz, Simon; Bauer, Tanja; Libuda, Jörg; Smith, David; Smith, Ana-Suncana; Haumann, Marco (ACS Catalysis, 2022)
The water gas shift reaction (WGSR) is catalyzed by supported ionic liquid phase (SILP) systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs). These systems work at very low temperatures, that is, between 120 and 160 °C, as compared to >200 °C in the conventional process. To improve the performance of this ultra-low-temperature catalysis, we investigated the influence of various additives on the catalytic activity of these SILP systems. In particular, the application of methylene blue (MB) as an additive doubled the activity. Infrared spectroscopy measurements combined with density functional theory (DFT) calculations excluded a coordinative interaction of MB with the Ru complex. In contrast, state-of-the-art theoretical calculations elucidated the catalytic effect of the additives by non-covalent interactions. In particular, the additives can significantly lower the barrier of the rate-determining step of the reaction mechanism via formation of hydrogen bonds. The theoretical predictions, thereby, showed excellent agreement with the increase of experimental activity upon variation of the hydrogen bonding moieties in the additives investigated.
CRIS-Team Scopus Importer:2022-06-03
Keywords: electronic interaction; methylene blue; ruthenium; supported ionic liquid phase; water gas shift reaction

Improving the performance of supported ionic liquid phase (SILP) catalysts for the ultra-low-temperature water-gas shift reaction using metal salt additives - Wolf, Patrick; Aubermann, Manfred; Wolf, Moritz; Bauer, Tanja; Blaumeiser, Dominik; Stepic, Robert; Wick, Christian; Smith, David M.; Smith, Ana-Suncana; Wasserscheid, Peter; Libuda, Jörg; Haumann, Marco (Green Chemistry, 2019)
Supported ionic liquid phase (SILP) catalyst systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs) catalyze the water-gas shift reaction (WGSR) at very low temperatures, i.e., between 120 and 160 °C. One limiting factor of the SILP WGS technology is the low solubility of CO in most ILs. To overcome this issue, we study the influence of different transition metal chloride additives on the activity of Ru-based WGS SILP catalysts. CuCl as the additive was found to enhance the activity by almost 30%. This increase in activity peaks at a CuCl addition of 4 M as a result of the interplay between the increasing CO uptake in the ionic liquid film as evidenced by means of CO sorption and thermogravimetry, and the increasing, unfavorable ionic liquid acidity at too high CuCl concentrations. The respective chlorocuprate species were identified by means of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT) calculations. We attribute the enhanced catalytic performance to cuprate ions that act as CO shuttles within the ionic liquid film.
CRIS-Team Scopus Importer:2019-09-27

Incorporation of Boron in Mesoporous Bioactive Glass Nanoparticles Reduces Inflammatory Response and Delays Osteogenic Differentiation - Zheng, Kai; Fan, Yuqian; Torre, Elisa; Balasubramanian, Preethi; Taccardi, Nicola; Cassinelli, Clara; Morra, Marco; Iviglia, Giorgio; Boccaccini, Aldo R. (Particle & Particle Systems Characterization, 2020)
Mesoporous bioactive glass nanoparticles (MBG) are multifunctional building blocks for tissue regeneration and nanomedicine applications. Incorporation of biologically active ions can endow MBG with additional functionalities toward promoted therapeutic effects. Here, boron is incorporated into MBG by using a sol–gel approach. The concentration of boron incorporated is controllable by tuning the amount of boron precursor. Two types of boron-doped MBG, namely 10B- and 15B-MBG (5.8 and 6.5 mol% of B2O3, respectively) are synthesized. Boron incorporation does not significantly influence the particle morphology. All synthesized particles exhibit a sphere-like shape with a size ranging from 100 to 300 nm. 10B- and 15B-MBG show large specific surface area (346 and 320 m² g−1, respectively) and pore volume. Both boron-doped MBG exhibit remarkable in vitro bioactivity and noncytotoxicity. Boron incorporation is shown to reduce the inflammatory response linked to macrophages as indicated by downregulated expression of pro-inflammatory genes. However, boron incorporation delays the osteogenic differentiation in osteoblasts as indicated by the downregulated expression of pro-osteogenic genes. The results demonstrate the promising potential of using boron-doped MBG to modulate inflammatory response for bone regeneration under inflammatory conditions, as shown in this study for the first time.
CRIS-Team Scopus Importer:2020-06-09
Keywords: bioactive glasses; bioactivity; boron; inflammatory response; osteogenic activity

In-depth characterisation of metal-support compounds in spent Co/SiO2 Fischer-Tropsch model catalysts - Wolf, Moritz; Gibson, E.; Olivier, E.; Neethling, J.; Catlow, C. R. A.; Fischer, Nico; Claeys, Michael (Catalysis Today, 2019)
Keywords: Cobalt catalyst; TEM; XANES; Cobalt silicate; Metal-support compound

Influence of carboxylate anions on phase behavior of choline ionic liquid mixtures - Elhi, Fred; Gantman, Mikhail; Nurk, Gunnar; Schulz, Peter; Wasserscheid, Peter; Aabloo, Alvo; Põhako-Esko, Kaija (Molecules, 2020)
Mixing ionic liquids is a suitable strategy to tailor properties, e.g., to reduce melting points. The present study aims to widen the application range of low-toxic choline-based ionic liquids by studying eight binary phase diagrams of six different choline carboxylates. Five of them show eutectic points with melting points dropping by 13 to 45 ◦C. The eutectic mixtures of choline acetate and choline 2-methylbutarate were found to melt at 45 ◦C, which represents a remarkable melting point depression compared to the pure compounds with melting points of 81 (choline acetate) and 90 ◦C (choline 2-methylbutarate), respectively. Besides melting points, the thermal stabilities of the choline salt mixtures were investigated to define the thermal operation range for potential practical applications of these mixtures. Typical decomposition temperatures were found between 165 and 207 ◦C, with choline lactate exhibiting the highest thermal stability.
CRIS-Team Scopus Importer:2020-04-21
Keywords: Choline; Differential scanning calorimetry; Eutectic mixture; Ionic liquid; Phase diagram

Influence of different anions on the surface composition of ionic liquids studied using ARXPS - Kolbeck, Claudia; Cremer, Till; Lovelock, Kevin; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry B, 2009)
Angle-resolved X-ray photoelectron spectroscopy has been used to study the influence of different types of anions on the surface composition of ionic liquids (ILs). We have investigated nine ILs with the same cation, 1-octyl-3-methylimidazolium [CCIm], but very different anions. In all cases, an enrichment of the cation alkyl chains is found at the expense of the polar cation head groups and the anions in the first molecular layer. This enhancement effect decreases with increasing size of the anion, which means it is most pronounced for the smallest anions and least pronounced for the largest anions. A simple model is proposed to explain the experimental observations. © 2009 American Chemical Society.

Influence of different substituents on the surface composition of ionic liquids studied using ARXPS - Lovelock, Kevin; Kolbeck, Claudia; Cremer, Till; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry B, 2009)
Angle resolved X-ray photoelectron spectroscopy has been used to study the surface composition of various nonfunctionalized and functionalized 1,3-dialkylimidazolium ionic liquids. For [C C Im][Tf N] (where n ) 2-16), an enrichment of the aliphatic carbon was observed for longer chains (n ≥ 4). Enrichment of the aliphatic carbon also occurs for alkyl chains attached to the anion, as observed for [C C Im][OcOSO ]. Oligo(ethyleneglycol)ether (PEG) functionalities in the cation lead to a surface composition close to bulk stoichiometry and thus a loss in enrichment of the chains. This effect is attributed to attractive interactions between the oxygen atoms on the cation to the hydrogen atoms on the imidazolium ring for [Et(EG) MIm][Tf N] and [Me(EG) MIm][Tf N]. © 2009 American Chemical Society.

Influence of dissolved hydrogen on the viscosity and interfacial tension of the liquid organic hydrogen carrier system based on diphenylmethane by surface light scattering and molecular dynamics simulations - Kerscher, Manuel; Klein, Tobias; Preuster, Patrick; Wasserscheid, Peter; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
In hydrogenation and dehydrogenation processes of liquid organic hydrogen carriers (LOHCs), molecular hydrogen (H2) is present, but its influence on the thermophysical properties of the LOHC compounds is still hardly known. This study provides experimental results from surface light scattering and predictions from molecular dynamics simulations on the influence of dissolved H2 on the liquid viscosity, interfacial tension, and liquid density of the LOHC system based on diphenylmethane at varying degree of hydrogenation, process-relevant temperatures up to 573 K, and pressures up to 7 MPa. First-time measurements of the viscosity of bicyclic hydrocarbon compounds in the presence of dissolved H2 at saturation conditions reveal a negligible effect of pressure. The interfacial tension decreases independently of the LOHC composition by about 6% at 7 MPa. The simulations can adequately represent the effect of H2 on the interfacial tension and evidence a weak enrichment of H2 at the interface.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Density; Dissolved hydrogen; Interfacial tension; LOHC systems; Pressure; Viscosity

Influence of gas impurities on the hydrogenation of CO2to methanol using indium-based catalysts - Schühle, Patrick; Schmidt, Maximilian; Schill, Leonhard; Riisager, Anders; Wasserscheid, Peter; Albert, Jakob (Catalysis: Science and Technology, 2020)
In this study, the performance of an In2O3/ZrO2 catalyst for hydrogenation of CO2 to methanol is reported in the presence of typical impurities of industrial CO2 feed gas streams. Experiments were performed with defined amounts of SO2, H2S, NO2, NH3 and hydrocarbons purposely added to the reaction mixture under industrially relevant conditions (225-275 °C, 50 bar total pressure, H2 : CO2 = 3 : 1). Comparative studies-with and without added impurities-further relate the observed effects to the behaviour of the commercial Cu/ZnO/Al2O3 methanol catalyst under identical treatments. Elemental analysis was used to determine the amount of sulphur, nitrogen and carbon residing on the catalyst after poisoning and after methanol synthesis. Moreover, temperature programmed desorption (TPD), temperature programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS) allowed identifying potential catalyst poisons formed on the catalyst surface. This work discloses that H2S and SO2 impurities led to drastic deactivation of the In2O3/ZrO2 catalyst (due to indium sulfide and -sulphate formation), while NH3, NO2 and hydrocarbon impurities have no major effect on the methanol production.
CRIS-Team Scopus Importer:2020-11-27

Influence of Resolution of Rasterized Geometries on Porosity and Specific Surface Area Exemplified for Model Geometries of Porous Media - Heidig, Tobias; Zeiser, Thomas; Freund, Hannsjörg (Transport in Porous Media, 2017)
Rasterized representations of geometrical structures are commonplace in science and engineering. They are used in analysis and design of complex geometrical structures; however, the introduced errors for volume and surface estimation are often not considered in detail. To provide insight and information on these effects, in this study model geometries of porous media (simple cubic, body-centered cubic, face-centered cubic) are used to investigate the influence of resolution (voxels per length) on volume and surface approximation. The numerically obtained results are compared with analytical solutions for porosity and specific surface area. Small deviations from the real volume are found for the rasterized geometry at reasonable resolution. For the estimated surface area, in contrast, when using marching cubes considerable deviations from the analytically calculated surface area are found even at relatively fine resolutions. These findings are especially important for the use of rasterized voxel data as input for engineering correlations to estimate characteristic physical transport properties such as pressure drop or effective heat transport.

Influence of statistical activity variations in diluted catalyst beds on the thermal reactor behavior: Derivation of an a priori criterion - Ganzer, Gunnar; Freund, Hannsjörg (Chemical Engineering Science, 2020)
Catalyst bed dilution by mixing active and inert particles is common practice for highly exothermic gas phase reactions for balancing the heat generation and heat removal out of the reactor tubes. The predicted reactor performance is commonly calculated assuming a perfectly mixed bed. However, loading a particle mixture into a reactor tube is an inherently statistical process, and thus fluctuations in local activity cannot be avoided which can lead to the formation of local hotspots. We have analyzed the influence of non-uniform activity profiles on the reactor behavior by simulation studies using 1- and 2-dimensional reactor models. Based on the results, an a priori criterion using dimensionless numbers was derived for the prediction of maximum temperature variations. The general applicability has been successfully proven for several reaction systems and process conditions. The derived correlation allows for considering the non-idealities at an early stage of reactor and process development.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Catalyst bed dilution; Hotspot formation; Reactor analysis; Reactor modeling; Reactor stability; Statistical activity variations

Influence of substituents and functional groups on the surface composition of ionic liquids - Kolbeck, Claudia; Niedermaier, Inga; Deyko, Alexey; Lovelock, Kevin; Taccardi, Nicola; Wei, Wei; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2014)
We have performed a systematic study addressing the surface behavior of a variety of functionalized and non-functionalized ionic liquids (ILs). From angle-resolved X-ray photoelectron spectroscopy, detailed conclusions on the surface enrichment of the functional groups and the molecular orientation of the cations and anions is derived. The systems include imidazolium-based ILs methylated at the C2 position, a phenyl-functionalized IL, an alkoxysilane-functionalized IL, halo-functionalized ILs, thioether- functionalized ILs, and amine-functionalized ILs. The results are compared with the results for corresponding non-functionalized ILs where available. Generally, enrichment of the functional group at the surface is only observed for systems that have very weak interaction between the functional group and the ionic head groups. Scratching the surface: The surface behavior of various functionalized ionic liquids (ILs) is studied by angle-resolved X-ray photoelectron spectroscopy and conclusions on surface-enrichment effects and molecular orientation of cations and anions are derived (see figure; Im=imidazolium, Tf=trifluoromethanesulfonyl). Overall, surface enrichment is only observed for functional groups that interact weakly with the ionic head groups. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Influence of support texture and reaction conditions on the accumulation and activity in the gas-phase aldol condensation of n-pentanal on porous silica - Schörner, Markus; Kämmerle, Stefanie; Wisser, Dorothea; Baier, Benjamin; Hartmann, Martin; Thommes, Matthias; Franke, Robert; Haumann, Marco (Reaction Chemistry & Engineering, 2022)
In this work, the continuous gas-phase aldol condensation reaction of n-pentanal was investigated on silica supports. Since high aldol formation can lead to deactivation by pore blocking, the reaction is important to improve continuous gas-phase hydroformylation processes. Aldehyde conversion was monitored depending on the surface acidity. The spent catalysts were analyzed by thermogravimetric analysis (TGA) to evaluate the accumulation of substrate and product inside the pores. The pore size was altered using hydrothermal treatment. The obtained supports were analyzed using N-2-sorption, mercury pore intrusion/extrusion, point-of-zero-charge measurements, temperature programmed desorption measurements (CO2 and NH3), and Si-29 MAS NMR. A variation of reaction duration, pressure, and temperature was carried out. The influence of the silica texture on activity and accumulation was investigated using different particle size fractions and median pore diameters. In larger pores, the total volume-based accumulation was lower compared to the one in smaller pores. At the same time, the aldol was enriched compared to n-pentanal in the condensed liquid inside the pore network.
CRIS-Team WoS Importer:2022-09-02

Influence of Surfactant-Mediated Interparticle Contacts on the Mechanical Stability of Supraparticles - Wang, Junwei; Kang, Eunsoo; Sultan, Umair; Merle, Benoit; Inayat, Alexandra; Graczykowski, Bartlomiej; Fytas, George; Vogel, Nicolas (Journal of Physical Chemistry C, 2021)
Colloidal supraparticles are micron-scale spherical assemblies of uniform primary particles, which exhibit emergent properties of a colloidal crystal, yet exist as a dispersible powder. A prerequisite to utilize these emergent functionalities is that the supraparticles maintain their mechanical integrity upon the mechanical impacts that are likely to occur during processing. Understanding how the internal structure relates to the resultant mechanical properties of a supraparticle is therefore of general interest. Here, we take the example of supraparticles templated from water/fluorinated oil emulsions in droplet-based microfluidics and explore the effect of surfactants on their mechanical properties. Stable emulsions can be generated by nonionic block copolymers consisting of a hydrophilic and fluorophilic block and anionic fluorosurfactants widely available under the brand name Krytox. The supraparticles formed in the presence of both types of surfactants appear structurally similar, but differ greatly in their mechanical properties. While the nonionic surfactant induces superior mechanical stability and ductile fracture behavior, the anionic Krytox surfactant leads to weak supraparticles with brittle fracture. We complement this macroscopic picture with Brillouin light spectroscopy that is very sensitive to the interparticle contacts for subnanometer-thick adsorbed layers atop of the nanoparticle. While the anionic Krytox does not significantly affect the interparticle bonds, the amphiphilic nonionic surfactant drastically strengthens these bonds to the point that individual particle vibrations are not resolved in the experimental spectrum. Our results demonstrate that seemingly subtle changes in the physicochemical properties of supraparticles can drastically impact the resultant mechanical propertie
Keywords: Ductile fracture; Emulsification; Fracture mechanics; Nonionic surfactants; Ostwald ripening; Physicochemical properties; Colloidal crystals; Emergent functionality; Emergent property; Internal structure; Interparticle contacts; Mechanical impacts; Mechanical integrity; Micron scale; Primary particles; Spherical assembly; Mechanical stability

Influence of the counterion on the synthesis of ZnO mesocrystals under solvothermal conditions - Klupp Taylor, Robin; Distaso, Monica; Taccardi, Nicola; Wasserscheid, Peter; Peukert, Wolfgang (Chemistry - A European Journal, 2011)
Polymers and coordinating solvents have been shown to serve as templating agents to assist the precipitation of ZnO nanoparticles and address their morphology. In this work we show for the first time that a difference in the coordination strength between the polymer (poly-N-vinylpyrrolidone (PVP)) and the two Zn precursor salts (nitrate and acetate) is able to promote or suppress the formation of mesocrystalline structures and even more importantly to tune their three-dimensional organization. On the basis of FTIR and C NMR spectroscopic studies, we propose that not only the polymer (PVP) but also the solvent (DMF) play a key role as directing agents. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: NMR spectroscopy; optical properties; oriented attachment; poly-N-vinylpyrrolidone; ZnO mesocrystals

Influence of the Inter-structural Gap between the Combustion Zone and the Flame Trap on the Properties of the dual Layer Porous Burners in Operation - Jovicic, Vojislav; Friedmann, Eva; Zbogar-Rasic, Ana; Regensburger, Christoph; Delgado, Antonio (Proceedings of the 7th European Combustion Meeting, 2015)
UnivIS-Import:2017-11-06:Pub.2015.tech.ITC.stmmec.influe

Influence of the nanoparticle size on hydrogen release and side product formation in liquid organic hydrogen carrier systems with supported platinum catalysts - Auer, Franziska; Hupfer, Alexander; Bösmann, Andreas; Szesni, Normen; Wasserscheid, Peter (Catalysis: Science and Technology, 2020)
Liquid organic hydrogen carrier (LOHC) systems represent a promising option for hydrogen storage and transport in chemically bound and infrastructure-compatible form. For multiple use of the carrier liquid in repetitive hydrogenation/dehydrogenation cycles, the applied dehydrogenation catalyst has to provide a combination of high productivity and excellent selectivity. In this study, we demonstrate that the catalytic performance of an alumina supported Pt catalyst in the dehydrogenation of perhydro-dibenzyltoluene (H18-DBT) is strongly dependent on the mean Pt nanoparticle size. With reference to the available Pt surface atoms, unmodified Pt nanoparticles have been found to show a maximum in dehydrogenation productivity for Pt particle sizes between 1.95 and 2.70 nm, while the undesired high-boiler formation peaks around 1.5 nm. Furthermore, we show that the exact knowledge of the Pt nanoparticle size makes surface modification with sulphur compounds much more effective. Smaller nanoparticles that exhibit a large share of low-coordinated Pt atoms require a larger amount of sulphur to block the undesired by-product formation caused by these sites. Treated with an optimal amount of sulphur, the maximum Pt-based productivity of the catalyst increases by a factor of 2.8 with a simultaneous reduction of the high-boiler formation by 40%.
CRIS-Team WoS Importer:2020-10-23

Influencing the Product Distribution in Citral Hydrogenation Using Ionic Liquid Modified Cu Catalysts - Naicker, Letisha; Schörner, Markus; Kremitzl, Daniel; Friedrich, Holger B.; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2022)
This work shows the effect of selected ionic liquids on the catalytic performance of a Cu/Al2O3 catalyst towards citral hydrogenation. The Cu/Al2O3 was prepared using a combination of wet impregnation and strong electrostatic interaction technique. The catalyst was coated with three ionic liquids, namely: [C4C1Pyrr][OTf], [C2C1C1Im][NTf2], and [C2C1Im][NTf2] resulting in Cu-based SCILL catalysts (solid catalyst with an ionic liquid layer). The fresh and used SCILL catalysts were characterized using FT-IR spectroscopy and thermal gravimetric analysis. All Cu-SCILL catalysts were stable throughout the liquid-phase reactions with no leaching of ionic liquid being detectable by means of TGA. All ionic liquids investigated prevented the formation of undesired isopulegol compared to the 30 % isopulegol selectivity obtained over the bare Cu/Al2O3 catalyst. The Cu-SCILL (coated with 15 wt% [C2C1Im][NTf2]) increased the selectivity towards geraniol and nerol by 340 %.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Citral; Copper; Ionic liquid; SCILL; Selective Hydrogenation

Infrared Spectroscopy of a Wilkinson Catalyst in a Room-Temperature Ionic Liquid - Kiefer, Johannes; Obert, Katharina; Himmler, Simone; Schulz, Peter; Wasserscheid, Peter; Leipertz, Alfred (ChemPhysChem, 2008)
Homogeneous catalysis in room-temperature ionic liquids (ILs) constitutes a most interesting field of research with high potential in technical applications. As concerns the hydrogenation of unsaturated hydrocarbons, Wilkinson's compound RhCl(PPh_3)_3 represents a catalyst that provides high selectivity and activity. Herein, we demonstrate the application of infrared spectroscopy to the quantitative analysis of the Wilkinson catalyst in the IL 1-ethyl-3-methylimidazolium acetate ([EMIM][OAc]). Our study demonstrates for the first time the quantitative, accurate and reproducible determination of the concentration of a rhodium catalyst by means of IR spectroscopy and, moreover, allows the investigation of intermolecular interactions. Spectral features, located mainly in the fingerprint region of the IR spectrum, are identified revealing the influence of the dissolved catalyst on the IL's vibrational structure. In particular, the ring-bending mode of the imidazolium ring shows a frequency shift as a function of catalyst concentration, probably due to hydrogen-bond formation between the IL cation and the Rh complex. The results show the potential of IR spectroscopy both for application as a quick process control technology in catalytic processes and as a tool for better understanding of IL–catalyst interactions.
Keywords: IR spectrum Wilkinson catalyst ionic liq ethylmethylimidazolium acetate

Insights into the redox kinetics of vanadium substituted heteropoly acids through liquid core waveguide membrane microreactor studies - Albert, Jakob; Ponce, Sebastian; Drochner, Alfons; Trabold, Michael; Etzold, Bastian (Chemical Engineering Journal, 2019)
A liquid core waveguide membrane microreactor is a novel concept that allows in situ spectroscopy to be carried out in an optical microreactor, while enabling a very high gas-to-liquid mass transfer. The potential of this reactor concept to derive kinetics in gas/liquid reactions is demonstrated using the heteropoly acids catalyzed oxidation of biomass to formic acid (the ‘OxFA process’). For vanadium-substituted, Keggin-type heteropoly acids, the kinetics of the reduction and reoxidation step of the catalyst cycle was deduced using in situ UV/Vis spectroscopy. Reduction was studied from 40 to 80 °C: a strong dependency of the reduction kinetics was deduced. In combination with additional cyclic voltammetry and EPR characterization, it can be assumed that two active centers promote this reaction, while the existence and proportions of both types depends on the degree of vanadium substitution. The rapid mass transfer allowed transient response experiments to be carried out for the reoxidation step, which was studied up to 150 °C. Switching from anaerobic to aerobic conditions, an even stronger dependency of the reoxidation kinetics on the degree of vanadium substitution was revealed.<br
Keywords: Anaerobic aerobic oxidation; Biomass oxidation; Optical microreactors; OxFA process; Heteropoly acids; Membrane microreactors

Insights into the surface composition and enrichment effects of ionic liquids and ionic liquid mixtures - Maier, Florian; Cremer, Till; Kolbeck, Claudia; Lovelock, Kevin; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2010)
A systematic study of ionic liquid surfaces by angle resolved X-ray photoelectron spectroscopy (ARXPS) is presented. By reviewing recent and presenting new results for imidazolium-based ionic liquids (ILs), we discuss the impact of chemical differences on surface composition and on surface enrichment effects. (1) For the hydrophilic ethylene glycol (EG) functionalised ILs [Me(EG)MIm][TfN], [Et(EG)MIm][TfN] and [Me(EG)MIm][TfN], which vary in the number of ethylene glycol units (from 1 to 3), we find that the surface composition of the near-surface region is in excellent agreement with the bulk composition, which is attributed to attractive interactions between the oxygen atoms on the cation to the hydrogen atoms on the imidazolium ring. (2) For [CC Im][TfN] (where n = 1-16), i.e. ILs with an alkyl chain of increasing length, an enrichment of the aliphatic carbons is observed for longer chains (n > 2), at the expense of the polar cation head groups and the anions in the first molecular layer, both of which are located approximately at the same distance from the outer surface. (3) To study the influence of the anion on the surface enrichment, we investigated ten ILs [CC Im][X] with the same cation, but very different anions [X] . In all cases, surface enrichment of the cation alkyl chains is found, with the degree of enrichment decreasing with increasing size of the anion, i.e., it is most pronounced for the smallest anions and least pronounced for the largest anions. (4) For the IL mixture [CC Im][TfN] and [CCIm][Tf N] we find a homogeneous distribution in the outermost surface region with no specific enrichment of the [CCIm] cation. © 2010 the Owner Societies.

In Situ Heterogeneous Catalysis Monitoring in a Hollow-Core Photonic Crystal Fiber Microflow Reactor - Cubillas, Ana Maria; Schmidt, Matthias; Euser, Tijmen G.; Taccardi, Nicola; Unterkofler, Sarah; Russell, Philip St. John; Wasserscheid, Peter; Etzold, Bastian (Advanced Materials Interfaces, 2014)
A novel process for uniform deposition of noble-metal catalyst nanoparticles on the inner core wall of a hollow-core photonic crystal fiber is presented. The resulting continuous flow microreactor enables heterogeneous catalysis reactions on extremely low (sub- extgreekmL) sample volumes. Strikingly, the excellent single mode transmission properties of the HC-PCF are preserved after the deposition process, allowing sensitive in situ spectroscopy measurements over unprecedented length scales of up to 50 cm.

In-situ monitoring of homogeneously catalysed reactions using raman spectroscopy inside hollow-core photonic crystal fibres - Schorn, Florian; Aubermann, Manfred; Zeltner, Richard; Wasserscheid, Peter; Haumann, Marco; Joly, Nicolas (Optics InfoBase Conference Papers, 2020)
We monitor the reaction of an acid with an alcohol inside a hollow-core photonic crystal fibre using Raman spectroscopy. The method uses tiny amount of chemicals and allows precise measurement of the activation energy.
CRIS-Team Scopus Importer:2020-11-13

In Situ Multimodal 3D Chemical Imaging of a Hierarchically Structured Core@Shell Catalyst - Sheppard, T.; Price, S.W.T; Benzi, F.; Baier, Sina; Klumpp, Michael; Dittmeyer, Roland; Schwieger, Wilhelm; Grunwaldt, J.D. (Journal of the American Chemical Society, 2017)
A Cu/ZnO/Al2O3@ZSM-5 core@shell catalyst active for one-step conversion of synthesis gas to dimethyl ether (DME) was imaged simultaneously and in situ using synchrotron-based micro X-ray fluorescence (mu-XRF), X-ray diffraction (mu-XRD), and scanning transmission X-ray microscopy (STXM) computed tomography (CT) with micrometer spatial resolution. An identical sample volume was imaged stepwise, first under oxidizing and reducing atmospheres (imitating calcination and activation processes); and then under model reaction conditions for DME synthesis (H-2:CO:CO2 ratio of 16:8:1, up to 250 degrees C). The multimodal imaging methods offered insights into the active metal structure and speciation within the catalyst, and allowed imaging of both the catalyst core and zeolite shell in a single acquisition. Dispersion of nanosized. Cu species was observed in the catalyst core during reduction, with formation of a metastable Cu+ phase at the core-shell interface. Under DME reaction conditions at 1 bar, the coexistence of Cu-0 in the active catalyst core together with partially oxidized Cu species was unraveled. The zeolite shell and core-shell interface remained stable under all conditions, preserving the bifunctional nature of the catalyst. These observations are inaccessible using standard bulk techniques like X-ray absorption spectroscopy (XAS) and XRD, demonstrating the potential of multimodal in situ X-ray CT for characterization of hierarchically designed materials, which stand to benefit tremendously from such 3D spatially resolved measurements.

In-situ thermal activation of carbide-derived carbon - Schmirler, Martina; Glenk, Friedrich; Etzold, Bastian (Carbon, 2011)
Microporous carbons attract high interest due to their application as a medium for gas storage, catalyst support or electrode material in lithium ion batteries or supercapacitors. Carbide-derived carbons (CDC) produced by halogenation of carbides exhibit a narrow pore size distribution and a tunable pore and microstructure by choosing the appropriate carbide precursor and chlorination temperature. However, the pore volume is limited by the amount of metal in the carbide structure, and the variation of pore size by varying the process conditions is not possible for all carbides. With an in-situ thermal activation in CO_2 parallel to the chlorination, the porosity of the CDC materials can be further increased. This improved carbide-derived carbon process also allows producing novel pore structures which vary in the meso- to micropore ratio from the outside to the center of the particle. Thereby also the boarder case of shell-like carbon structures showing different pore size distributions in the shells can be produced. For this in-situ activation and chlorination of carbides the influence of the processing, the concentration of CO_2 and activation time on the pore structure of CDC was studied.
EAM Import::2019-03-13

In situ ultrasonic diagnostic of zeolite X crystallization with novel (hierarchical) morphology from coal fly ash - Musyoka, Nicholas M.; Petrik, Leslie F.; Hums, Eric; Baser, Hasan-Hüseyin; Schwieger, Wilhelm (Ultrasonics, 2014)
In this paper the applicability of an in situ ultrasonic diagnostic technique in understanding the formation process of zeolite X with a novel morphology was demonstrated. The complexity of the starting fly ash feedstock demands independent studies of the formation process for each type of zeolite since it is not known whether the crystallization mechanism will always follow the expected reaction pathway. The hierarchical zeolite X was noted to follow a solution phase-mediated crystallization mechanism which differs from earlier studies of the zeolite A formation process from unaged, clear solution extracted from fused fly ash. The use of the in situ ultrasonic monitoring system provided sufficient data points which enabled closer estimation of the time of transition from the nucleation to the crystal growth step. In order to evaluate the effect of temperature on the resulting in situ attenuation signal, synthesis at three higher temperatures (80, 90 and 94 degrees C) was investigated. It was shown, by the shift of the US-attenuation signal, that faster crystallization occurred when higher temperatures were applied. The novel hierarchical zeolite X was comprised of intergrown disc-like platelets. It was further observed that there was preferential growth of the disc-shaped platelets of zeolite X crystals in one dimension as the synthesis temperature was increased, allowing tailoring of the hierarchical morphology. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: In situ ultrasonic; Hierarchical zeolite X; Fly ash

In situ ultrasonic measurements: a powerful tool to control the synthesis of zeolites from coal fly ash - Hums, Eric; Baser, Hasan-Hüseyin; Schwieger, Wilhelm (Research on Chemical Intermediates, 2016)
An in situ ultrasonic diagnostic technique was applied to monitoring the hydrothermal synthesis of zeolite A and X of clear solution extracted from alkaline fused class F coal fly ash. In this context, kinetic evaluations based on in situ ultrasonic diagnostic data displayed an important approach to study the synthesis process. The impact on nucleation and crystal growth was demonstrated by variation of a few relevant parameters such as reaction temperature, amount of water, NaO and ageing time, including templated colloidal synthesis mixtures as model solution. To complement the kinetic analysis, ex situ techniques such as ICP, X-ray diffraction, scanning electron microscopy and dynamic light scattering were used to investigate liquid phase and reaction products extracted from the reaction mixture during the synthesis.
Keywords: Coal fly ash; Colloidal synthesis; In situ; Kinetics; Sodalite; Ultrasound; Zeolite A; X

In-situ ultrasonic methods for monitoring the hydrothermal synthesis of LTA-type zeolite from colloidal solutions - Baser, Hasan-Hüseyin; Thangaraj, Thangaraj; Herrmann, Ralph; Ofili, Ifeanyi Jimmy; Schwieger, Wilhelm (Studies in Surface Science and Catalysis, 2007)
In the present study, we report the successful use of ultrasound device as a real-time, in situ diagnostic tool for monitoring the crystallization progress of zeolite A from homogeneous colloidal solutions with the composition 0.4 Na(2)O : 10 SiO(2) : 1.4 Al(2)O(3) : 16 (TMA)(2)O: 650 H(2)O. The results demonstrate that there exist good correlation between the crystallisation progress of zeolite A in terms of yield and the attenuated ultrasonic signal. It is also revealed that the kinetic information like activation energy of crystallisation reaction could be easily calculated from the measured ultrasonic signals data. In the studied case, activation energy of Ca. 30 kJ/mol was obtained.

In situ ultrasonic monitoring of zeolite A crystallization from coal fly ash - Baser, Hasan-Hüseyin; Schwieger, Wilhelm; Hums, Eric; Musyoka, Nicholas M.; Petrik, Leslie F. (Catalysis Today, 2012)
In this study, high phase purity of zeolite A was prepared from coal fly ash precursors. The molar regime of both the clear solution extract and unseparated fly ash slurry was adjusted to achieve the right composition for zeolite A crystallization. The formation process for zeolite A from coal fly ash precursors was monitored in detail using an in situ ultrasonic system and was complemented by use of ex situ techniques such as XRD, FTIR, SEM and FTIR. The findings from both the in situ ultrasonic monitoring process and ex situ techniques clearly contributed significantly in unmasking the formation process of zeolite A from coal fly ash compared to previous studies reported in the literature. The study also enriches the existing body of literature by deeply investigating the gel-solution-crystal interactions starting from this complex feedstock. Comparable ultrasonic signals were generated when both clear and unseparated fly ash based precursor solutions were used during the zeolite synthesis process. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: In situ; Ultrasound; Coal fly ash; Zeolite A; Mechanism; Ageing process

In-situ ultrasound study of the kinetics of formation of zeolites Na-A and Na-X from coal fly ash - Hums, Eric; Musyoka, Nicholas M.; Baser, Hasan-Hüseyin; Inayat, Alexandra; Schwieger, Wilhelm (Research on Chemical Intermediates, 2015)
The kinetics of synthesis of zeolites Na-A and Na-X from fused South African class F coal fly ash were studied by using an ultrasound device as a real-time, in-situ diagnostic tool. Ex-situ techniques, for example XRD, ICP, and SEM, were used to complement the results of the kinetic study. Reaction rate, reaction order, and activation energy of crystallization processes in clear solution extracted from fused fly ash were calculated on the basis of ultrasound signal data recorded at different crystallization temperatures. Zeolite Na-X and zeolite Na-A crystals were both obtained without ageing. The zeolite Na-X sample showed contaminations of zeolite P and sodalite depending on the synthesis temperature. For zeolite Na-A the impact of ageing on the process of formation was also studied.
Keywords: In-situ; Ultrasound; Coal fly ash; Kinetics; Zeolite Na-A; Zeolite Na-X

Installation and process for reservoirs of hydrogen energy. - Bösmann, Andreas; Preuster, Patrick; Schmidt, Matthias; Teichmann, Daniel; Wasserscheid, Peter; Arlt, Wolfgang (2015)
An installation for reservoirs of energy comprises a H prodn. unit for producing H, a H storage device for reservoirs the carrier loaded by H with a load unit for loading a carrier with the H produced in the H prodn. unit and with an unloading unit for the discharge of the H of, a heat prodn. unit for producing heat and a heat storage unit for reservoirs by the heat prodn. unit produced heat, whereby the heat storage unit is connected with the unloading unit for making available heat. [on SciFinder(R)]
Keywords: installation reservoir hydrogen energy

Intensification of heat transfer in catalytic reactors by additively manufactured periodic open cellular structures (POCS) - Busse, Corinna; Freund, Hannsjörg; Schwieger, Wilhelm (Chemical Engineering and Processing, 2018)
Cellular structures are considered as alternative catalyst carrier with high potential for process intensification of catalytic reactors due to their remarkable combination of beneficial properties: high specific surface area, low pressure drop and adjustable heat transfer properties. In this contribution, the potential for heat transfer intensification of a new generation of cellular structures, so-called periodic open cellular structures (POCS), is investigated. These structures are produced via additive manufacturing which provides two major advantages. First, highly regular structures can be obtained with perfect reproducibility, which makes them ideal model systems for systematic investigations. Second, the design flexibility of the manufacturing techniques enables an innovative approach for structure optimization. Such optimization, however, requires a detailed understanding of the geometry-transport interaction. In this regard, the first advantage is exploited here to examine in detail the influence of each relevant property of the structure (material, morphology, wall coupling) on the heat transfer. These findings, along with newly derived correlations, enlarge the toolbox for the design of POCS for catalytic applications. Furthermore, POCS can now be designed and optimized a priori according to the needs of the given application. This adds a new degree of freedom to the process intensification approach regarding equipment optimization.
Keywords: Catalyst support; Heat transfer; Additive manufacturing; Metal foam; Periodic open cellular structures

Intensification of load flexible fixed bed reactors by optimal design of staged reactor setups - Fischer, Konrad; Freund, Hannsjörg (Chemical Engineering and Processing, 2020)
The dynamic and load flexible operation of fixed bed reactors has recently gained considerable interest for processes where large fluctuations of the feed flow rate are expected. Load flexibility poses new challenges regarding the reactor design and operation in comparison to the conventional steady state operating mode. These challenges can be managed by a more conservative reactor design, but it creates a performance gap between conventional and load flexible reactors. The intensification of load flexible wall-cooled fixed bed reactors is approached using the methanation of carbon dioxide as case study. An optimization problem is formulated which bases on the simultaneous optimization of the reactor design and several steady state operating points within a desired load range. The identified staged reactor setup with a catalyst dilution profile tolerates large variations of the flow rate up to 80 % and shows a significant improvement of the load flexible reactor performance. A considerable potential of a split and bypass of the feed stream to other stages is identified, which enables an adaption of the axial flow field according to the current load level. The feasibility of the identified setup for the dynamic operation is successfully verified by dynamic simulation of different operating scenarios.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Carbon dioxide methanation; Catalyst dilution profile; Dynamic operation; Feed distribution; Model-based reactor optimization; Wall-cooled tubular reactor

Interaction between Ionic Liquids and a Pt(111) Surface Probed by Coadsorbed CO as a Test Molecule - Eschenbacher, Roman; Schuschke, Christian; Bühlmeyer, Hanna; Taccardi, Nicola; Wasserscheid, Peter; Bauer, Tanja; Xu, Tao; Libuda, Jörg (Journal of Physical Chemistry Letters, 2021)
We used temperature-programmed infrared reflection absorption spectroscopy (TP-IRAS) to study the desorption behavior of CO on Pt(111) coadsorbed with four kinds of ionic liquids (ILs), namely 1-butyl-1-methyl-pyrrolidinium-bis(trifluoromethylsulfonyl)imide ([C4C1Pyr][NTf2]), 1-ethyl-3-methyl-imidazolium-bis(trifluoromethylsulfonyl)imide ([C2C1Im][NTf2]), 1-butyl-1-methyl-pyrrolidinium-trifluoro-methanesulfonate ([C4C1Pyr][OTf]), and 1-butyl-1-methyl-pyrrolidinium-hexafluorophosphate ([C4C1Pyr][PF6]). We found that CO desorbs earlier from a Pt(111) surface with coadsorbed ILs than without. In addition, the CO desorption temperature varies between different types of coadsorbed ILs, which follows the order: [C4C1Pyr][PF6] (365 K) > [C4C1Pyr][NTf2] (362 K) > [C2C1Im][NTf2] (352 K) > [C4C1Pyr][OTf] (348 K). We ascribe the difference in CO desorption temperature to the different interaction strength between ILs and the Pt(111) surface. A stronger IL-Pt(111) interaction leads to a lower CO desorption temperature. We suggest that TP-IRAS experiments of CO coadsorbed with ILs can be a useful method to aid the characterization of the interaction strength between ILs and metal surfaces such as Pt(111).
CRIS-Team Scopus Importer:2021-11-05

Interaction of Ester-Functionalized Ionic Liquids with Atomically-Defined Cobalt Oxides Surfaces: Adsorption, Reaction and Thermal Stability - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (ChemPhysChem, 2017)
Hybrid materials consisting of ionic liquid (ILs) films on supported oxides hold a great potential for applications in electronic and energy materials. In this work, we have performed surface science model studies scrutinizing the interaction of ester-functionalized ILs with atomically defined Co3O4(111) and CoO(100) surfaces. Both supports are prepared under ultra-high vacuum (UHV) conditions in form of thin films on Ir(100) single crystals. Subsequently, thin films of three ILs, 3-butyl-1-methyl imidazolium bis(trifluoromethyl-sulfonyl) imide ([BMIM][NTf2]), 3-(4-methoxyl-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([MBMIM][NTf2]), and 3-(4-isopropoxy-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([IPBMIM][NTf2]), were deposited on these surfaces by physical vapor deposition (PVD). Time-resolved and temperature-programmed infrared reflection absorption spectroscopy (TR-IRAS, TP-IRAS) were applied to monitor insitu the adsorption, film growth, and thermally induced desorption. By TP-IRAS, we determined the multilayer desorption temperature of [BMIM][NTf2] (360 +/- 5K), [MBMIM][NTf2] (380K) and [IPBMIM][NTf2] (380K). Upon deposition below the multilayer desorption temperature, all three ILs physisorb on both cobalt oxide surfaces. However, strong orientation effects are observed in the first monolayer, where the [NTf2](-) ion interacts with the surface through the SO2 groups and the CF3 groups point towards the vacuum. For the two functionalized ILs, the [MBMIM](+) and [IPBMIM](+) interact with the surface Co2+ ions of both surfaces via the CO group of their ester function. A very different behavior is found, if the ILs are deposited above the multilayer desorption temperature (400K). While for [BMIM][NTf2] and [MBMIM][NTf2] a molecularly adsorbed monolayer film is formed, [IPBMIM][NTf2] undergoes a chemical transformation on the CoO(100) surface. Here, the ester group is cleaved and the cation is chemically linked to the surface by formation of a surface carboxylate. The IL-derived species in the monolayer desorb at temperatures around 500 to 550K.
Keywords: chemical anchoring; cobalt oxide; ionic liquids; IRAS; thermal stability

Interactions Between the Room-Temperature Ionic Liquid [C(2)C(1)Im][OTf] and Pd(111), Well-Ordered Al2O3, and Supported Pd Model Catalysts from IR Spectroscopy - Schernich, Stefan; Kostyshyn, Dmytro; Wagner, Valentin; Taccardi, Nicola; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2014)
The interactions between ionic liquids and their supports determine many of their applications. The adsorption of the ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C2C1Im][OTf] on Pd(111), ordered Al2O3/NiAl(110), and Pd nanoparticles supported on Al2O3/NiAl(110) was investigated under ultrahigh vacuum (UHV) conditions using time-resolved infrared reflection absorption spectroscopy (TR-IRAS). On Pd, the [OTf]- anion stands up with its CF3 group directed toward the vacuum, whereas the anion is less clearly oriented on the oxide. We also find that strong interactions of the IL with the Pd result in migration of the IL from the oxide to the metal nanoparticles.

Interactions of imidazolium-based ionic liquids with oxide surfaces controlled by alkyl chain functionalization - Schernich, Stefan; Laurin, Mathias; Lykhach, Yaroslava; Tsud, Nataliya; Sobota, Marek; Skala, Tomas; Prince, Kevin C.; Taccardi, Nicola; Wagner, Valentin; Steinrück, Hans-Peter; Matolin, Vladimir; Wasserscheid, Peter; et al. (ChemPhysChem, 2013)
From a different angle: Thin films of functionalized ionic liquids are deposited on cerium oxides following a surface science approach. The functionalization of the alkyl chain changes its orientation with respect to the surface plane from normal to parallel. This then leads to a different surface chemistry at higher temperatures. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Interface Controls Spontaneous Crystallization in Thin Films of the Ionic Liquid [C2C1Im][OTf] on Atomically Clean Pd(111) - Schernich, Stefan; Wagner, Valentin; Taccardi, Nicola; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Langmuir, 2014)
A total of 5-30 monolayer thick films of the ionic liquid (IL) [C2C1Im][OTf] were vaporized in vacuo onto an atomically clean Pd(111) single crystal surface at 220 K. Time- and temperature-resolved infrared reflection-absorption spectroscopy reveals growth, interactions with the metallic support, and the macroscopic phase behavior of the layer. At 220 K, the IL layer first grows in the form of a glassy phase. Crystallization of the IL was witnessed above a critical thickness of about 10 monolayers. On the basis of the known bulk crystal structure of the IL, we suggest the formation of well-oriented checkerboard-like crystalline film structures on the surface. The preferential orientation manifested by the crystal phase with regard to the macroscopic metallic surface is attributed to strong interactions between anionic headgroups and the metal.

Interface of Ionic Liquids and Carbon: Ultrathin [C1C1Im][Tf2N] Films on Graphite and Graphene - Rietzler, Florian; Nagengast, Jens; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2015)
We investigated the initial adsorption behavior and growth of thin films of ionic liquid (IL) [CCIm][TfN] on highly ordered pyrolytic graphite (HOPG) and on a full and a fractional graphene layer on Ni(111). We found that the initial adsorption behavior and growth strongly depended on the underlying substrate. On HOPG, the IL forms an initial wetting layer with a coverage of 0.5 ML and anions and cations next to each other in direct contact with the substrate. On a complete graphene layer on Ni(111), the wetting layer has twice the thickness with alternately oriented ion pairs next to each other. On top of these wetting layers, further IL growth occurs in 3D islands, with the island formation being less pronounced on the graphene layer. On the fractional graphene layer on Ni(111), initial IL adsorption preferentially occurs on bare Ni surface areas, with anions on top of cations, followed by 3D island growth on both the bare and the graphene-covered surface regions.

Interface properties and physicochemical characterization of the low-temperature molten salt Li/K/Cs acetate - Deyko, Alexey; Bajus, Stephanie; Rietzler, Florian; Bösmann, Andreas; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2013)
The surface of macroscopic films of the ternary molten salt mixture Li KCs[OAc] has been investigated by angle-resolved X-ray photoelectron spectroscopy (XPS) as a function of temperature. With increasing temperature a preferential depletion of K is observed by ∼40%. From temperature programmed desorption we find that the onset for the cation desorption follows the order Cs, K, and Li, with activation energies of 125, 148, and 157 kJ mol, respectively; the corresponding value for the [OAc] anion is 147 kJ mol, which is, within the margin of error, identical to the average of the value found for the cations. Ultrathin films of the molten salt deposited on a Au(111) surface by physical vapor deposition show preferential enrichment of Cs, in line with the lower activation energy and thus higher desorption rate of Cs[OAc] from the ternary mixture. Angle-resolved XPS of the molten salt/gold interface demonstrates that the first molten salt monolayer grows in a layer-by-layer growth, followed by three-dimensional island growth at higher coverages. © 2013 American Chemical Society.

Internal Structure of Nanometer-Sized Droplets Prepared by Antisolvent Precipitation - Schuldes, Isabel; Noll, Dennis; Schindler, Torben; Zech, Tobias; Götz, Klaus; Appavou, Marie Sousai; Boesecke, Peter; Steiniger, Frank; Schulz, Peter; Unruh, Tobias (Langmuir, 2019)
Antisolvent precipitation (AP) is a low-cost and less-invasive preparation alternative for organic nanoparticles compared to top-down methods such as high-pressure homogenization or milling. Here we report on particularly small organic nanoparticles (NPs) prepared by AP. It has been found for various materials that these NPs in their liquid state exhibit a significant degree of molecular order at their interface toward the dispersion medium including ubiquinones (coenzyme Q10), triglycerides (trimyristin, tripalmitin), and alkanes (tetracosane). This finding is independent of the use of a stabilizer in the formulation. While this is obviously a quite general interfacial structuring effect, the respective structural details of specific NPs systems might differ. Here, a detailed structural characterization of very small liquid coenzyme Q10 (Q10) NPs is presented as a particular example for this phenomenon. The Q10 NPs have been prepared by AP in the presence of two different stabilizers, sodium dodecyl sulfate (SDS) and pentaethylene glycol monododecyl ether (C12E5), respectively, and without any stabilizer. The NPs' size is initially analyzed by photon correlation spectroscopy (PCS). The SDS-stabilized Q10 NPs have been studied further by differential scanning calorimetry (DSC), small-angle X-ray and neutron scattering (SAXS, SANS), wide-angle X-ray scattering (WAXS), and cryogenic transmission electron microscopy (CryoTEM). A simultaneous analysis of SAXS and contrast variation SANS studies revealed the molecular arrangement within the interface between the NPs and the dispersion medium. The Q10 NPs stabilized by SDS and C12E5, respectively, are small (down to 19.9 nm) and stable (for at least 16 months) even when no stabilizer is used. The SDS-stabilized Q10 NPs reported here, are therewith, to the best of our knowledge, the smallest organic NPs which have been reported to be prepared by AP so far. In particular, these NPs exhibit a core-shell structure consisting of an amorphous Q10 core and a surrounding shell, which is mainly composed of oriented Q10 molecules and aligned SDS molecules. This structure suggests a significant amphiphilic behavior and a rather unexpected stabilizing role of Q10 molecules.
CRIS-Team Scopus Importer:2019-10-22

Intramolecular crossover from unconventional diamagnetism to paramagnetism of palladium ions probed by soft X-ray magnetic circular dichroism - Smekhova, Alevtina; Schmitz, Detlef; Izarova, Natalya V.; Stuckart, Maria; Shams, S. Fatemeh; Siemensmeyer, Konrad; de Groot, Frank M.F.; Kögerler, Paul; Schmitz-Antoniak, Carolin (Communications Chemistry, 2020)
The case of palladium(II) ions in molecular polyoxopalladates highlights the importance of accounting not only for nearest neighbour atoms or ions in order to understand, model or predict magnetic characteristics. Here, using site-specific soft X-ray magnetic circular dichroism (XMCD), the effects of different bond lengths, delocalization of 4d electrons, and 4d spin-orbit coupling on the electronic and magnetic properties are investigated and three different states identified: Conventional diamagnetism in a square-planar O4 coordination environment, paramagnetism caused by four additional out-of-plane oxygen anions, and an unusual diamagnetic state in the diamagnetic/paramagnetic crossover region modified by significant mixing of states and facilitated by the substantial 4d spin-orbit coupling. The two diamagnetic states can be distinguished by characteristic XMCD fine structures, thereby overcoming the common limitation of XMCD to ferro-/ferrimagnetic and paramagnetic materials in external magnetic fields. The qualitative interpretation of the results is corroborated by simulations based on charge transfer multiplet calculations and density functional theory results.
CRIS-Team Scopus Importer:2020-08-07

Inverse gas chromatography for determining the dispersive surface energy of porous silica - Rückriem, Michael; Inayat, Alexandra; Enke, Dirk; Glaeser, Roger; Einicke, Wolf-Dietrich; Rockmann, Rico (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2010)
Inverse gas chromatography (IGC) is a modern technique for the characterization of porous materials, which provides thermodynamic parameters of the solids. Porous glass beads, silica gels and ordered mesoporous materials were used as model systems to study correlations between the dispersive part of the surface energy and the surface chemistry of porous materials. The surface chemistry of silica was controlled via thermal treatment and reaction with 1,1,1,3,3,3-hexamethyldisilazane (HMDS) or 3-amino-propyltriethoxysilane (3-APTS). The dependency of the surface energy on the various modifications was investigated in this study. Furthermore, the impact of microstructure on the dispersive surface energy was determined by a comparative study of the ordered mesoporous materials MCM-41, SBA-15 and SBA-1

Investigation of High-Temperature and High-Pressure Gas Adsorption in Zeolite H-ZSM-5 via the Langatate Crystal Microbalance: CO2, H2O, Methanol, and Dimethyl Ether - Ding, Wenjin; Klumpp, Michael; Li, Hui; Schygulla, Ulrich; Pfeifer, Peter; Schwieger, Wilhelm; Haas-Santo, Katja; Dittmeyer, Roland (Journal of Physical Chemistry C, 2015)
The adsorption of gases CO2, H2O, methanol, and dimethyl ether (DME) in zeolite H-ZSM-5 in the temperature range of 50-150 degrees C and pressure range of 0-18 bar has been investigated using a high-temperature, high-frequency oscillating microbalance (langatate crystal microbalance, LCM). The determined adsorption data are needed to validate a detailed simulation model, which is meant to assist in the optimization of the preparation of bifunctional core shell catalysts for one-stage DME synthesis from syngas. Compared to the conventional quartz crystal microbalance (QCM) which is limited to temperatures below 80 degrees C, LCM can be used at higher temperatures, i.e., at or close to the reaction temperature of one-stage DME synthesis (200-300 degrees C), owing to the absence of crystalline-phase transitions up to its melting point (1470 degrees C). Zeolite H-ZSM-5 crystallites have been synthesized on the langatate crystal by steam-assisted crystallization (SAC). The loaded H-ZSM-5 (Si/Al molar ratio 100) on the langatate crystal has been confirmed and characterized with X-ray diffraction (XRD), wavelength-dispersive X-ray spectroscopy (WDX), and scanning electron microscopy (SEM). The adsorption experiments showed that the adsorption of CO2, methanol, and DME in H-ZSM-5 is fitted well by the single site Langmuir model, while the dual-site Langmuir model is needed for the adsorption of H2O in H-ZSM-5. The determined adsorption parameters, i.e., adsorption capacities, adsorption enthalpies, and adsorption entropies, compare well to literature data.

Investigation of the Concepts to Increase the Dew Point Temperature for Thermal Energy Recovery from Flue Gas, Using Aspen® - Fedorova, Nataliia; Aziziyanesfahani, Pegah; Jovicic, Vojislav; Zbogar-Rasic, Ana; Khan, Muhammad Jehanzaib; Delgado, Antonio (Energies, 2019)
Thermal energy of flue gases (FG) dissipating from industrial facilities into the environment, constitute around 20% of the total dissipated thermal energy. Being part of the FG, water vapour carries thermal energy out of the system in the form of the latent heat, which can be recovered by condensation, thus increasing the overall efficiency of an industrial process. The limiting factor in this case is the low dew point temperature (usually 40–60 °C) of the water vapour in the FG. The increase of the dew point temperature can be achieved by increasing the water content or pressure. Taking these measures as a basis, the presented work investigated the following concepts for increasing the dew point temperature: humidification of the flue gas using water, humidification using steam, compression of the FG and usage of the steam ejector. Modelling of these concepts was performed using the commercial software Aspen®. The humidification of the FG using water resulted in the negligible increase in the dew point (3 °C). Using steam humidification the temperatures of up to 92 °C were reached, while the use of steam ejector led to few degrees higher dew point temperatures. However, both concepts proved to be energy demanding, due to the energy requirements for the steam generation. The FG compression enabled the achievement of a 97 °C dew point temperature, being both energy-efficient and exhibiting the lowest energy cos
Keywords: thermal energy recovery; flue gas; dew point temperature; condensation; Aspen®

Investigations on catalyst stability and product isolation in the extractive oxidative desulfurization of fuels using polyoxometalates and molecular oxygen - Bertleff, Benjamin; Claußnitzer, Johannes; Goebel, Rebecca; Korth, Wolfgang; Skiborowski, Mirko; Wasserscheid, Peter; Jess, Andreas; Albert, Jakob (ChemCatChem, 2018)
Our contribution adds important new insight to the recent finding that polyoxometalate catalysts, such as H8PV5Mo7O40 (HPA‐5), are very effective catalysts in the extractive oxidative desulfurization of fuels using molecular oxygen. Our contribution focuses on aspects of catalyst stability and deactivation caused by the accumulation of acidic products and intermediates, i.e. sulfuric acid, formic acid, acetic acid, sulfoacetic acid or 2‐sulfobenzoic acid. These compounds reduce the pH value of the aqueous catalyst phase during the course of the desulfurization reaction. At lower pH values, the higher V‐substituted species rearrange to lower V‐substituted species and VO2+. This rearrangement is responsible for a decreasing activity in extractive oxidative desulfurization. We show that formic acid, acetic acid, sulfoacetic acid and 2‐sulfobenzoic acid block active sites of the catalyst. Oxalic acid, in contrast, has been found to exert a remarkable positive effect on catalyst activity. The feasibility of catalyst recycling and efficient isolation of the decomposition products is demonstrated using four commercially available organic solvent nanofiltration membranes.

In vitro cytocompatibility and antibacterial studies on biodegradable Zn alloys supplemented by a critical assessment of direct contact cytotoxicity assay - Watroba, Maria; Bednarczyk, Wiktor; Szewczyk, Piotr K.; Kawalko, Jakub; Mech, Krzysztof; Grünewald, Alina; Ünalan, Irem; Taccardi, Nicola; Boelter, Gabriela; Banzhaf, Manuel; Hain, Caroline; Bala, Piotr; et al. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2022)
In vitro cytotoxicity assessment is indispensable in developing new biodegradable implant materials. Zn, which demonstrates an ideal corrosion rate between Mg- and Fe-based alloys, has been reported to have excellent in vivo biocompatibility. Therefore, modifications aimed at improving Zn's mechanical properties should not degrade its biological response. As sufficient strength, ductility and corrosion behavior required of load-bearing implants has been obtained in plastically deformed Zn-3Ag-0.5Mg, the effect of simultaneous Ag and Mg additions on in vitro cytocompatibility and antibacterial properties was studied, in relation to Zn and Zn-3Ag. Direct cell culture on samples and indirect extract-based tests showed almost no significant differences between the tested Zn-based materials. The diluted extracts of Zn, Zn-3Ag, and Zn-3Ag-0.5Mg showed no cytotoxicity toward MG-63 cells at a concentration of <= 12.5%. The cytotoxic effect was observed only at high Zn2+ ion concentrations and when in direct contact with metallic samples. The highest LD50 (lethal dose killing 50% of cells) of 13.4 mg/L of Zn2+ ions were determined for the Zn-3Ag-0.5Mg. Similar antibacterial activity against Escherichia coli and Staphylococcus aureus was observed for Zn and Zn alloys, so the effect is attributed mainly to the released Zn2+ ions exhibiting bactericidal properties. Most importantly, our experiments indicated the limitations of water-soluble tetrazolium salt-based cytotoxicity assays for direct tests on Zn-based materials. The discrepancies between the WST-8 assay and SEM observations are attributed to the interference of Zn2+ ions with tetrazolium salt, therefore favoring its transformation into formazan, giving false cell viability quantitative results.
CRIS-Team WoS Importer:2022-09-02

Ionic liquid based model catalysis: Interaction of [BMIM][Tf2N] with Pd nanoparticles supported on an ordered alumina film - Sobota, Marek; Schmid, Martin; Happel, Markus; Amende, Maximilian; Maier, Florian; Steinrück, Hans-Peter; Paape, Natalia; Wasserscheid, Peter; Laurin, Mathias; Gottfried, Michael; Libuda, Jörg (Physical Chemistry Chemical Physics, 2010)
Towards a better understanding of novel catalytic materials consisting of supported noble metal catalysts modified by an ionic liquid (IL) film, we have performed a study under ultrahigh-vacuum (UHV) conditions. The model surface consists of Pd nanoparticles grown in UHV on an ordered alumina film on NiAl(110). Thin films of the room temperature IL 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][TfN] are deposited onto this surface by means of physical vapor deposition (PVD). The interaction of the IL with clean and CO-covered Pd/AlO/NiAl(110) at 300 K and the thermal behavior of the deposited IL films on Pd/AlO /NiAl(110) are investigated by time-resolved infrared reflection absorption spectroscopy (TR-IRAS) and X-ray photoelectron spectroscopy (XPS). At 300 K, the IL adsorbs molecularly both onto the Pd particles and onto the alumina. The IR spectra suggest that the [TfN] anions interact with Pd sites preferentially via the sulfonyl groups. CO pre-adsorbed on the Pd particles is partially displaced by the IL, even at 300 K, and only the part of CO adsorbed onto hollow sites on (111) facets of the Pd particles remains in place. Upon heating to temperatures higher than the desorption temperature of the IL (>400 K), molecular desorption of the IL competes with decomposition. The decomposition products, atomic species and small fragments, remain preferentially adsorbed onto the Pd nanoparticles and strongly modify their surface properties. Most of the decomposition products originate from the [BMIM] cations, whereas the [TfN] anions desorb for the most part. © 2010 the Owner Societies.

Ionic-Liquid-Infused Nanostructures as Repellent Surfaces - Galvan, Yaraset; Phillips, Katherine R.; Haumann, Marco; Wasserscheid, Peter; Zarraga, Ramon; Vogel, Nicolas (Langmuir, 2018)
In order to prepare lubricant-infused repellent coatings on silica nanostructures using low vapor pressure ionic liquids as lubricants, we study the wetting behavior of a set of imidazolium-based ionic liquids with different alkyl side chains as a function of the applied surface functionalities. We take advantage of the structural color of inverse opals prepared from a colloidal coassembly technique to study the infiltration of ionic liquids into these nanoporous structures. We find that the more hydrophobic ionic liquids with butyl and hexyl side chains can completely infiltrate inverse opals functionalized with mixed self-assembled monolayers composed of imidazole groups and aliphatic hydrocarbon chains, which we introduce via silane chemistry. These molecular species reflect the chemical nature of the ionic liquid, thereby increasing the affinity between the liquid and solid surface. The mixed surface chemistry provides sufficiently small contact angles with the ionic liquid to infiltrate the nanopores while maximizing the contact angle with water. As a result, the mixed monolayers enable the design of a stable ionic liquid/solid interface that is able to repel water as a test liquid. Our results underline the importance of matching chemical affinities to predict and control the wetting behavior in complex, multiphase systems
Keywords: Coating materials; Salts; Liquids; Wetting; Solvents

Ionic liquid-ionic liquid biphasic systems. - Gerhard, Dirk; Fick, Friedrich; Wasserscheid, Peter (Molten Salts Ionic Liq., [EuChem Conf.], 21st, 2010)
New examples of ionic liq.-ionic liq. biphasic systems are presented and their phase compn. was detd. The synthesis of the target compds. had been achieved previously (ionic liqs.) and in this study, two ionic liqs. [i.e., 3-ethyl-1-methyl-1H-imidazolium Et sulfate [C2mim][EtOSO3] and Methyltrioctylammonium bis(trifluoromethanesulfonyl)imide [N1888][NTf2]] were mixed with THF, 1-hexene and 1-octene, resp. For selected combinations, the ion distribution in the two liq. phases was detd. and the usefulness of these systems in sepn. applications was described. [on SciFinder(R)]
Keywords: ionic liq biphase system; Tego IL IMS ionic liq biphase system THF alkene

Ionic Liquid-Modified Electrocatalysts: The Interaction of [C1C2Im][OTf] with Pt(1 1 1) and its Influence on Methanol Oxidation Studied by Electrochemical IR Spectroscopy - Brummel, Olaf; Faisal, Firas; Bauer, Tanja; Pohako-Esko, Kaija; Wasserscheid, Peter; Libuda, Jörg (Electrochimica Acta, 2016)
Ionic liquids (ILs) have recently been proposed as modifying agents to tune the selectivity and the activity of electrocatalysts. In order to explore the origin of IL-induced effects on electrocatalytic reactions, we have investigated (i) the interaction of [CCIm][OTf]-water mixtures with Pt(1 1 1) single crystal electrodes and (ii) the influence of [CCIm][OTf] on methanol oxidation in acidic aqueous solution using cyclic voltammetry (CV) and electrochemical IR spectroscopy. We show that [CCIm][OTf] interacts strongly with the Pt(1 1 1) surface in the potential range from -0.2 V to 0.65 V, leading to partial blocking of the surface, partial suppression of hydrogen adsorption, and partial suppression of OH formation. The interaction of the IL with Pt occurs in this potential range via specific adsorption of the [OTf] anions which bind to Pt(1 1 1) via the SO group in a tilted adsorption geometry. The adsorption process is largely reversible as a function of the electrode potential, but shows a complex kinetics and becomes very slow at high IL coverage. Also, [CCIm][OTf] has a strong effect on the electro-oxidation of methanol in acidic solution. Adsorption of [OTf] leads to partial blocking of the indirect oxidation pathway to CO. The onset potential for CO oxidation is found to be shifted to more positive values indicating hindered access of HO to the electrode surface. CO and the [CCIm][OTf] form a mixed co-adsorption layer which is characterized by a strongly red-shifted CO stretching band. The effect is assigned to an IL-induced ligand effect in the mixed adsorbate layer and suggests that the direct modification of active centers by surface-bound IL species plays an important role in IL-modified electrocatalytic materials.
Keywords: carbon monoxide; electrochemical IR spectroscopy; Ionic liquids; methanol oxidation; platinum

Ionic-Liquid-Modified Hybrid Materials Prepared by Physical Vapor Codeposition: Cobalt and Cobalt Oxide Nanoparticles in [C(1)C(2)Im][OTf] Monitored by In Situ IR Spectroscopy - Mehl, Sascha; Bauer, Tanja; Brummel, Olaf; Pohako-Esko, Kaija; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Langmuir, 2016)
The synthesis of ionic-liquid-modified nanomaterials has, attracted much attention recently. In this study we explore the potential to prepare such systems in an ultraclean fashion by physical vapor codeposition (PVCD). We codeposit metallic cobalt and the room-temperature ionic liquid (IL) 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C(1)C(2)Im][OTf] simultaneously onto a Pd(111) surface at 100 K. This process is performed under ultrahigh-vacuum (UHV) conditions in the presence of CO, or in the presence of O-2 and CO. We use time-resolved (TR) and temperature-programmed (TP) infrared reflection absorption spectroscopy (IRAS) to investigate the formation and stability of the IL-modified Co deposits in situ during the PVD-based synthesis. CO is used as a probe molecule to monitor the growth. After initial growth of flat Co films on Pd(111), multilayers of Co nanoparticles (NPs) are formed. Characteristic shifts and intensity changes are observed in the vibrational bands of both CO and the IL, which originate from the electric field at the IL/Co interface (Stark effect) and from specific adsorption of the [OTf](-) anion. These observations indicate that the Co aggregates are stabilized by mixed adsorbate shells consisting of CO and [OTf](-). The CO coverage on the Co particle decreases with increasing temperature, but some CO is preserved up to the desorption temperature of the IL (370 K). Further, the IL shell suppresses the oxidation of the Co NPs if oxygen is introduced in the PVCD process. Only chemisorbed oxygen is formed at oxygen partial pressures that swiftly lead to formation of Co3O4 in the absence of the IL (5 X 10(-6) mbar O-2). This chemisorbed oxygen is found to destabilize the CO ligand shell. The oxidation of Co is not suppressed if IL and Co are deposited sequentially under otherwise identical conditions. In this case we observe the formation of fully oxidized cobalt oxide particles.

Ionic Liquids as Operating Fluids in High Pressure Applications - Predel, Tim; Schlücker, Eberhard; Wasserscheid, Peter; Arlt, Wolfgang; et al. (Chemical Engineering & Technology, 2007)
During the past years a growing number of scientists and engineers have investigated ionic liquids because of their outstanding advantages in several areas. Their unique physical properties and specific chemical behavior make these liquids very interesting for new and innovative applications. For commercial implementation ionic liquids have to meet a number of requirements. For use in high pressure applications they should have a low compressibility, an adjustable gas solubility and a superior lubricating ability. A screening of the relevant parameters was conducted in several experimental setups built for these purposes. Most of these parameters were also examined under long term conditions with regard to real process conditions and safety guarantee in possible high pressure applications. A major application is the compression of oxygen using ionic liquid as operating fluid. Besides, there are many more applications where the superior chemical and physical properties of ionic liquids are of high potential benefit. © 2007 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.prozma.ionicl_0
Keywords: Chemical stability; Compressibility; Corrosion; Ionic liquids

Ionic Liquids as Solvent Probes for NMR Cryoporometry. - Schulz, Peter (ChemPhysChem, 2010)
The cryoporosimetry expt. was conducted with controlled pore glass (CPG) of pore diams. 50.2 nm, 101 nm, 197.18 nm, 427.56 nm and 517.89 nm. The resoln. was still good enough to resolve a melting-point shift of -0.15 K for ionic liq. confined in pores with a pore radius of 427.56 nm because of the high value of Kc. The m.p. shift of the ionic liq. in pores of 517.89 nm diam. can not be detd. any more with a temp. resoln. of 0.05 K. It was interesting to note that, for 1-ethyl-3-Me imidazolium [EMIM] bis(trifluoromethylsulfonyl)imide [NTf2], higher melting temps. for bulk ionic liq. than the values known from literature were found. The detected m.p. of [EMIM] tetrafluoroborate [BF4] was well correlated with published data. It can be concluded that the ionic liqs. are suitable as a solvent probe for cryoporometry. [on SciFinder(R)]
Keywords: NMR cryoporometry ionic liq solvent probe

Ionic Liquids for Chloromethane/Isobutane Distillative Separation: Express Screening - Mokrushin, Vladimir; Mokrushina, Liudmila; Arlt, Wolfgang; Assenbaum, Daniel; Wasserscheid, Peter; Petri, Martin; Wewers, Wolfgang (Chemical Engineering & Technology, 2010)
The present study centres on room-temperature ionic liquids (ILs) as entrainers in extractive distillation of chloromethane/isobutane mixtures. The binary system, chloromethane/isobutene, is an azeotropic system. In this study, IL entrainers are shown to be able to break the azeotrope and, thus, assure the separation in the whole range of chloromethane/isobutane ratios. ILs formed from different cations and anions are considered and their influence on chloromethane/isobutane separation is explored. Among the ILs studied, those containing the trifluoromethanesulfonate ([CF(3)SO(3)](-)) or tricyanomethanide ([C(CN)(3)](-)) anion are demonstrated to exhibit an enhanced potential for chloromethane/isobutane separation compared to the corresponding ILs based on the bis(trifluoromethylsulfonyl)imide ([Tf(2)N](-)) anion. Moreover, the ILs enclosing these anions are cheaper than those with the [Tf(2)N](-) anion. Thus, the separation ability, solubility of chloromethane/isobutane mixtures, and costs of IL entrainers can be adjusted by the right choice of cations and anions.
Keywords: Chloromethane-isobutane mixture; COSMO-RS; Express screening experiments; Extractive distillation; Headspace chromatography; Ionic liquids

Ionic Liquids for Electrolyte-Gating of ZnO Field-Effect Transistors - Thiemann, Stefan; Sachnov, Swetlana; Porscha, S.; Wasserscheid, Peter; Zaumseil, Jana (Journal of Physical Chemistry A, 2012)
We investigate the influence of the chemical structure of a range of imidazolium-based ionic liquids (IL) on their properties as electrolytes and the device characteristics of electrolyte-gated field-effects transistors (FETs) based on spray-deposited polycrystalline zinc oxide (ZnO). We find a decrease of electron field-effect mobility that correlates with the capacitance of the ionic liquids and not only with the size of the IL-cation. The device stability depends significantly on testing conditions. While they are reasonably stable in nitrogen, ZnO-FETs degrade rapidly in ambient air due to absorption of water by the IL and the resulting ZnO surface reactions. Replacement of the most acidic hydrogen atom of the imidazolium cation and surface passivation of ZnO with hexamethyldisilazane improve environmental stability.

Ionic Liquids for Propene-Propane Separation - Mokrushin, Vladimir; Assenbaum, Daniel; Paape, Natalia; Gerhard, Dirk; Mokrushina, Liudmila; Wasserscheid, Peter; Arlt, Wolfgang; Kistenmacher, Hans; Neuendonf, Stephanie; Göke, Volker (Chemical Engineering & Technology, 2010)
This paper presents an extensive study on the feasibility of ionic liquids (IL) for the extractive distillation of propene-propane mixtures. A new experimental method for express screening of non-volatile entrainers was elaborated. A series of ILs and their mixtures were screened at ambient temperature and low pressures. The screening results show that every tested IL turns a low boiler propene into a high boiler and the alkene-to-alkane separation factor can be as low as 0.28. The solubility and separation efficiency can be tuned by adjusting the chemical structures of the ions forming the IL. It was found that shortening of the alkyl substituents of the imidazolium ions leads to a decrease in capacity and to an increase in the separation factor. Interestingly, ILs containing nitrile functionalities in either the cation or the anion showed, in our experiments, enhanced separation ability combined with still good capacities. From our thermodynamic measurements, [EMIM] [ [B(CN)(4)] was proved to be the most promising candidate. Binary mixtures of ILs were also tested and resulted in separation factors and capacities between the values for the individual ILs. For the most promising candidates, also autoclave measurements at elevated temperatures and pressures were carried out. These experiments indicate that the separation ability decreases with growing temperature and loading. In general, our study definitely proves the high potential of ILs to act as entrainers in the extractive distillation of propene-propane mixtures or for the separation of any other low-boiling alkene-alkane mixture.
Keywords: Express screening experiments; Extractive distillation; Headspace chromatography; Ionic liquids; Propene - propane mixtures

Ionic liquid silver salt complexes for propene/propane separation - Agel, Friederike; Pitsch, Fee; Krull, Florian Felix; Schulz, Peter; Wessling, Matthias; Melin, Thomas; Wasserscheid, Peter (Physical Chemistry Chemical Physics, 2010)
Properties of the room-temperature liquid complex salt [Ag(propene)x][Tf2N] have been studied to probe its suitability for acting as active separation layer in immobilised liquid membrane (ILM) concepts for propane/propene separation. The pressure/temperature range of complex formation has been determined and the thermal properties of Ag[Tf2N] and [Ag(propene)x][Tf2N] have been studied by DSC (differential scanning calorimetry) and TGA (thermogravimetric analysis) measurements. Pressure dependent measurements of solubility and diffusivity showed that the observed membrane selectivity is dominated by the solubility selectivity. The self-diffusion coefficient of propene is always smaller compared to propane as propene is temporarily bound to the silver ion in the [Ag(propene)x][Tf2N] ionic liquid.

Ionic Liquids in Catalysis - Wasserscheid, Peter; Steinrück, Hans-Peter (Catalysis Letters, 2015)
Ionic liquids (ILs), salts with melting points below 100 °C, represent a fascinating class of liquid materials typically characterized by an extremely low vapor pressure. Besides their application as new solvents or as electrolytes for electrochemical purposes, there are two important concepts of using ILs in catalysis: Liquid–liquid biphasic catalysis and IL thin film catalysis. Liquid–liquid biphasic catalysis enables either a very efficient manner to apply catalytic ILs, e.g. in Friedel–Crafts reactions, or to apply ionic transition metal catalyst solutions. In both cases, phase separation after reaction allows an easy separation of reaction products and catalyst re-use. One problem of liquid–liquid biphasic catalysis is mass transfer limitation. If the chemical reaction is much faster than the liquid–liquid mass transfer the latter limits the overall reaction rate. This problem is overcome in IL thin film catalysis where diffusion pathways and thus the characteristic time of diffusion are short. Here, Supported Ionic Liquid Phase (SILP) and Solid Catalyst with Ionic Liquid Layer (SCILL) are the two most important concepts. In both, a high surface area solid substrate is covered with a thin IL film, which contains either a homogeneously dissolved transition metal complex for SILP, or which modifies catalytically active surface sites at the support for SCILL. In each concept, interface phenomena play a very important role: These may concern the interface of an IL phase with an organic phase in the case of liquid–liquid biphasic catalysis. For IL thin film catalysis, the interfaces of the IL with the gas phase and with catalytic nanoparticles and/or support materials are of critical importance. It has recently been demonstrated that these interfaces and also the bulk of ILs can be investigated in great detail using surface science studies, which greatly contributed to the fundamental understanding of the catalytic properties of ILs and supported IL materials. Exemplary results concerning the IL/vacuum or IL/gas interface, the solubility and surface enrichment of dissolved metal complexes, the IL/support interface and the in situ monitoring of chemical reactions in ILs are presented.
Keywords: Heterogeneous catalysis; Catalysis; Homogeneous catalysis; Green chemistry; Evaporation; Methodology and Phenomena; XPS; Spectroscopy and General Characterisation; Ionic liquids; Preparation and Materials

Ionic Liquids in Chemical Engineering - Werner, Sebastian; Haumann, Marco; Wasserscheid, Peter (Annual Review of Chemical and Biomolecular Engineering, 2010)
The development of engineering applications with ionic liquids stretches back to the mid-1990s when the first examples of continuous catalytic processes using ionic liquids and the first studies of ionic liquid–based extractions were published. Ever since, the use of ionic liquids has seen tremendous progress in many fields of chemistry and engineering, and the first commercial applications have been reported. The main driver for ionic liquid engineering applications is to make practical use of their unique property profiles, which are the result of a complex interplay of coulombic, hydrogen bonding and van der Waals interactions. Remarkably, many ionic liquid properties can be tuned in a wide range by structural modifications at their cation and anion. This review highlights specific examples of ionic liquid applications in catalysis and in separation technologies. Additionally, the application of ionic liquids as working fluids in process machines is introduced.

Ionic liquids in electrocatalysis - Zhang, Guirong; Etzold, Bastian (Journal of Energy Chemistry, 2016)
The performance of an electrocatalyst, which is needed e.g. for key energy conversion reactions such as hydrogen evolution, oxygen reduction or CO2 reduction, is determined not only by the inherent structure of active sites but also by the properties of the interfacial structures at catalytic surfaces. Ionic liquids (ILs), as a unique class of metal salts with melting point below 100 °C, present themselves as ideal modulators for manipulations of the interfacial structures. Due to their excellent properties such as good chemical stability, high ionic conductivity, wide electrochemical windows and tunable solvent properties the performance of electrocatalysts can be substantially improved through ILs. In the current minireview, we highlight the critical role of the IL phase at the microenvironments created by the IL, the liquid electrolyte, catalytic nanoparticles and/or support materials, by detailing the promotional effect of IL in electrocatalysis as reaction media, binders, and surface modifiers. Updated exemplary applications of IL in electrocatalysis are given and moreover, the latest developments of IL modified electrocatalysts following the ``Solid Catalyst with Ionic Liquid Layer (SCILL)'' concept are presented.
EAM Import::2019-03-12

Ionic liquids in mechanical engineering - Schlücker, Eberhard; Wasserscheid, Peter (Chemie Ingenieur Technik, 2011)
Ionic liquids (ILs) offer many possibilities for improving the properties of machines that rely on lubricants or operating liquids. The studies presented here showed that different ionic liquids are suitable to, e.g., make high pressure processes more efficient and reduce fuel consumption of combustion engines. It is shown that ionic liquids can increase the performance for all machines with lubricants or operating liquids. The only obstacle to the widespread use of ionic liquids in the machine technology is the potential corrosivity of ILs that generally prohibits the use of conventional materials. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Combustion engines; Ionic liquids; Pumps; Vacuum technology

Ionic Liquids in Refinery Desulfurization: Comparison between Biphasic and Supported Ionic Liquid Phase Suspension Processes - Kuhlmann, Esther; Haumann, Marco; Jess, Andreas; Seeberger, Andreas; Wasserscheid, Peter (Chemsuschem, 2009)
The desulfurization of fuel compounds in the presence of ionic liquids is reported. For this purpose, the desulfurization efficiency of a variety of imidazolium phosphate ionic liquids has been tested. Dibenzothiophene/dodecane and butylmercaptan/decane mixtures were used as model systems. Single-stage extractions reduced the sulfur content from 500ppm to 200ppm. In multistage extractions the sulfur content could be lowered to less than 10ppm within seven stages. Regeneration of the ionic liquid was achieved by distillation or re-extraction procedures. Supported ionic liquid phase (SILP) materials, obtained by dispersing the ionic liquid as a thin film on highly porous silica, exhibited a significantly higher extraction performance owing to their larger surface areas, reducing the sulfur content to less than 100ppm in one stage. Multistage extraction with these SILP materials reduced the sulfur level to 50ppm in the second stage. The SILP technology offers very efficient utilization of ionic liquids and circumvents mass transport limitations because of the small film thickness and large surface area, and allows application of the simple packed-bed column extraction technique.

Ionic liquid "solutions" for catalytic transformations. - Wasserscheid, Peter (VDI-Berichte, 2008)
There are many good reasons to study ionic liqs. as solvents for catalytic transformations. Besides the advantage of their extremely low vapor pressure, their tuneable soly. and coordination properties are of special interest as they allow a systematic optimization of ionic liq.-org. biphasic as well as supported ionic liq. phase (SILP) catalysis. But which catalytic reaction should be optimized using the ionic liq. approach. This paper highlights important aspects making catalysis in ionic liqs. more or less promising. It turns out that ionic liq. and catalyst stability under reaction conditions and ease of product isolation from the ionic liq. are among the most important pre-requisites to make catalysis in ionic liqs. a success. [on SciFinder(R)]
Keywords: ionic liq soln catalytic transformations

Ion speciation driving chirality transfer in imidazolium-based camphorsulfonate ionic liquid solutions - Huang, Mian-Mian; Schneiders, Karola; Schulz, Peter; Wasserscheid, Peter; Weingaertner, Hermann (Physical Chemistry Chemical Physics, 2011)
The underlying principle of the chirality transfer in imidazolium-based camphorsulfonate ionic liquids is rationalized by linking catalytic results from the hydrogenation of [N-(3′-oxobutyl)-N-methylimidazolium] [(+)-camphorsulfonate] to [N-(3′-hydroxybutyl)-N-methylimidazolium] [(+)-camphorsulfonate] in tetrahydrofuran with electrolyte theory by the help of dielectric relaxation spectroscopy. Using this approach we are able to explain why the maximum of the enantiomeric excess of the hydrogenation reaction in tetrahydrofuran is found at a medium concentration of 0.15 mol L-1, whereas it declines at both, lower and higher concentrations. Dielectric spectra in the concentration range between 0.05 and 1.0 mol L-1 reveal a solute mode due to dipolar ion pairs and larger dipolar ion clusters. They verify that at very low concentrations the ionic liquid ions are fully solvated with an increasing tendency to form neutral ion pairs with increasing concentration. Already at 0.025 mol L-1 the degree of dissociation reaches a minimum reflecting a maximum of neutral ion pair formation. With increasing ionic liquid concentration ordered ion clusters are formed by two and more ion pairs. At high concentrations these clusters collapse by dilution in the excess ionic liquid and the defined ion contact necessary for the chirality transfer is lost to a great extent.

Isolated Rh atoms in dehydrogenation catalysis - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Tacardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Isolated active sites have great potential to be highly efficient and stable in heterogeneous catalysis, while enabling low costs due to the low transition metal content. Herein, we present results on the synthesis, first catalytic trials, and characterization of the Ga9Rh2 phase and the hitherto not-studied Ga3Rh phase. We used XRD and TEM for structural characterization, and with XPS, EDX we accessed the chemical composition and electronic structure of the intermetallic compounds. In combination with catalytic tests of these phases in the challenging propane dehydrogenation and by DFT calculations, we obtain a comprehensive picture of these novel catalyst materials. Their specific crystallographic structure leads to isolated Rhodium sites, which is proposed to be the decisive factor for the catalytic properties of the systems.
CRIS-Team Scopus Importer:2023-03-31

Isomerisation of 1,4-dichlorobenzene using highly acidic alkali chloroaluminate melts. - Meßner, Julia; Schulz, Peter; Taccardi, Nicola; Kuhlmann, Sven; Wasserscheid, Peter (Chemical Communications, 2014)
The isomerization reaction of 1,4-dichlorobenzene leading to the thermodynamically favored and tech. desired 1,3-dichlorobenzene has been studied comparing highly acidic chloroaluminate melts with org. imidazolium and alkali metal ions. Interestingly, the inorg. melts show much higher reactivity and full recyclability if small AlCl3 losses are compensated and the reaction is carried out under slight HCl pressure. [on SciFinder(R)]
Keywords: dichlorobenzene isomerization acidic alkali chloroaluminate melt

Key factors for the direct growth of zeolite faujasite (FAU) on metallic aluminum surface - Chanda, Rajesh; Selvam, Thangaraj; Avadhut, Yamini; Kuhnt, Andreas; Herrmann, Ralph; Hartmann, Martin; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2018)
Zeolite faujasite (FAU) is widely used as a catalyst and adsorbent in many industrial catalytic and separation applications. The high water adsorption capacity of zeolite FAU makes it an attractive adsorbent material for the heat pump and heat storage applications. However, highly alkaline condition, which is required for the synthesis of zeolite FAU, is a challenge to achieve FAU/aluminum composites via a direct, reactive coating approach. In this contribution, a reactive coating method to fabricate zeolite FAU based aluminum composites is presented. The impact of important synthesis paramaters on the formation of such composites is discussed based on thorough characterization (such as XRD, SEM, MAS NMR, N-2- and water-sorption) of the coated FAU layer (the composite) and so-called excess powder, formed parallel in the reaction solution. Along with the comprehensive study of zeolite FAU formation as a coating layer, preliminary results of the fabricated composites in potential heat pump application are presented as well.
Keywords: Zeolite; Crystal growth; Coating; Heat pump; Thin film

Kinetic Modeling of the Partial Oxidation of Propylene to Acrolein: A Systematic Procedure for Parameter Estimation Based on Non-isothermal Data - Ganzer, Gunnar; Freund, Hannsjörg (Industrial & Engineering Chemistry Research, 2019)
Based on non-isothermal experiments in an integral pilot scale reactor, the heterogeneously catalyzed gas phase oxidation of propylene to acrolein was investigated at industrial relevant process conditions. From an extensive experimental data set both reaction scheme and reaction rates were derived. Beside the main components propylene, oxygen, acrolein and water, the proposed reaction network includes a variety of side products. The reaction rates were modeled by a semi-mechanistical approach given by Mars and van Krevelen. Based on a two-dimensional, pseudohomogeneous reactor model, the kinetic parameters were estimated successfully by introducing a systematic procedure for a stepwise determination using different regions with different characteristics to estimate the pre-exponential factors and activation energies individually, i. e. separated from each other. The model is able to predict the data included in the parameter estimation and independent data measured at different process conditions as well. Furthermore, it provides reliable results for an industrial plant.<br

Kinetic modelling of reactions for the synthesis of 2-methyl-5-ethyl pyridine - Moioli, Emanuele; Schmid, Leo; Wasserscheid, Peter; Freund, Hannsjörg (Reaction Chemistry & Engineering, 2021)
The kinetics of the acid catalyzed reactions of acetaldehyde ammonia trimer (AAT) and paraldehyde (para) to 2-methyl-5-ethyl pyridine (MEP) in the presence of an acid catalyst were investigated systematically. A reaction model has been developed based on experimental data. With full characterisation of side products it is possible to describe the reaction as a polymerisation and to understand the different reactivity of AAT and para, respectively. A kinetic model to describe the formation of MEP and the side products was developed using operando Raman spectroscopy. The model, involving four main reactions, is able to describe the formation of MEP and side products and incorporates the effects of reactant concentration, temperature and promoter concentration. This model is an important step that allows for further process intensification and evaluation of each of the two reaction routes.
CRIS-Team WoS Importer:2021-05-28

Kinetics of tri-phase extractive oxidative desulfurization of benzothiophene with molecular oxygen catalyzed by HPA-5 - Claußnitzer, Johannes; Bertleff, Benjamin; Korth, Wolfgang; Albert, Jakob; Wasserscheid, Peter; Jess, Andreas (Chemical Engineering & Technology, 2019)
The triphasic, aerobic, extractive desulfurization of benzothiophene (BT) using an aqueous H8[PV5Mo7O40] solution as catalyst and O2 as oxidant was investigated. A time-resolved analysis of all reaction products in the gas, organic and aqueous phase, is given. The organic sulfur in BT is mainly converted to sulfuric acid (SSA > 60 %). Mass transport limitations can be excluded and an activation energy of BT oxidation of 90 ± 8 kJ mol-1 was determined. The reaction orders are 1 with regard to BT, and 0.5 both for HPA-5 and O2. Calculated data derived from this mechanism with a power law kinetic approach show good agreement to the experimental data for conversions below 60 %. At higher BT conversions, significant deviations are found suggesting that acidic products formed in the BT oxidation affect the catalyst and therefore the initial kinetics of the BT oxidatio
Keywords: aerobic extractive oxidative desulfurization; kinetic model; benzothiophene; polyoxometalates; sulfate

Kinetic Study of the Asymmetric Hydrogenation of Methyl Acetoacetate in the Presence of a Ruthenium Binaphthophosphepine Complex - Öchsner, Eva; Etzold, Bastian; Junge, Kathrin; Beller, Matthias; Wasserscheid, Peter (dvanced Synthesis & Catalysis, 2009)
The asymmetric hydrogenation of methyl acetoacetate (MAA) in methanol using dibromobis(S)-4-phenyl-4,5-dihydro-3H-dinaphtho[2,1-c: 1′,2′-e]phosphepine-ruthenium was studied in detail. For the determination of the reaction network, data from kinetic experiments were compared to different possible reaction networks using the kinetic software Presto Kinetics. The simulation was optimised to describe the reaction accurately with a minimal set of process parameters and reaction equations. For the best model the reaction orders, collision factors and activation energy of all reaction steps were determined. Additionally, the influence of reaction temperature and hydrogen pressure on the enantiomeric excess (ee) of the reaction was studied. It was found that high reaction temperatures and high hydrogen pressures result in increasing enantioselectivities.

KOH-promoted Pt/Al2O3 catalysts for water gas shift and methanol steam reforming: An operando DRIFTS-MS study - Kaftan, Andre; Kusche, Matthias Manfred; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg (Applied Catalysis B-Environmental, 2017)
The performance of KOH-modified Pt/AlO catalysts has been investigated under the conditions of the water-gas shift (WGS) reaction and methanol steam reforming (MSR) with diffuse reflectance infrared Fourier-transform spectroscopy (DRIFTS) coupled with online quadrupole mass spectrometry (QMS). We demonstrate that both the activity and the selectivity are enhanced in comparison to the uncoated catalyst by applying a thin coating of KOH. By means of IR spectroscopy, we were able to follow the formation of surface species on two different types of catalysts. During reaction, primarily formates are observed on the uncoated catalyst while a film of hydroxides and carbonates is observed on the KOH-coated sample. Additionally, the vibrational bands of CO adsorbed on Pt suggest a strong modification of the electronic structure of the Pt particles by K-coadsorption, leading to a weakening C[sbnd]O bond and a strengthening of the Pt[sbnd]C bond. As a result, we observe an increased selectivity to CO on the KOH modified system.
Keywords: Infrared spectroscopy; Methanol steam reforming; Online mass spectrometry; Platinum; Water-gas shift

Laser-Generated InOx/ZrO2Catalysts for CO2Hydrogenation: Role of in Situ Fragmentation and Ripening Control - Lau, Kinran; Schühle, Patrick; Liang, Shun Xing; De Kock, Florian; Albert, Jakob; Reichenberger, Sven (ACS Applied Energy Materials, 2021)
It is desirable to reduce the reliance on fossil fuels and to develop alternative methods to yield valuable chemicals. CO2 hydrogenation to methanol is a promising approach, where In2O3/ZrO2 catalysts have attracted increasing attention due to their high selectivity and stability. However, the activity of indium-based catalysts is very susceptible to the preparation method, which is typically wet impregnation. Here, we explore a laser-based synthesis route to prepare InOx/ZrO2 catalysts of varying indium size and load. The respective particle sizes were either adjusted by in situ fragmentation with a more (ns-VIS-laser) or less (ns-IR-laser) efficient laser wavelength or by using micromolar concentrations of phosphate as an electrostatic stabilizer. The InOx colloids were subsequently deposited onto ZrO2 Our results demonstrate that the pulsed laser ablation with ns-IR-laser pulses yielded larger ∼45 nm crystalline cuboid InOx supported on zirconia. The frequency-doubled ns-VIS-pulses on the other hand caused an augmented in situ fragmentation during ablation, which led to catalysts with spherical ∼14 nm InOx particles with a significantly higher degree of amorphousness. Further size quenching and increased amorphous content of the InOx nanoparticles were observed when micromolar concentrations of phosphates were additionally present during ablation. After supporting the InOx nanoparticles onto ZrO2, the laser-generated catalysts were found to perform equally well as their wet-chemically prepared counterparts for methanol synthesis in a slurry phase, although crystalline In species performed slightly better in the catalytic reaction. In conclusion, in situ fragmentation does not only provide opportunities for independent studies of size and composition but also ripening control and structural modifications such as amorphization.
CRIS-Team Scopus Importer:2021-10-29
Keywords: amorphous nanoparticles; laser ablation in liquid; methanol synthesis; size quenching; slurry reaction

Layer-by-Layer Oxidation for Decreasing the Size of Detonation Nanodiamond - Etzold, Bastian; Neitzel, Ioannis; Kett, Manfred; Strobl, Florian; Mochalin, Vadym N.; Gogotsi, Yury (Chemistry of Materials, 2014)
Diamond nanoparticles attract much attention as they combine outstanding mechanical properties with biocompatibility and are available in large quantities. Control and tunability of the particle size is very important for any nanomaterial. Although oxidation can burn carbon and lead to a particle size decrease, this technique could not be successfully employed for nanodiamond size reduction on the nanoscale. In this work, two commercial nanodiamond powders are used to demonstrate separation of the oxidation reaction into two steps (i) the oxygen chemisorption and (ii) the CO and/or CO2 desorption. This allows for an effective control of the oxidation process. In situ thermogravimetric analysis suggests that the oxidation is thermodynamically rather than kinetically controlled, and that the carbon burn off can be adjusted by repeating chemisorption/desorption steps to remove carbon layer after layer. Small-angle X-ray scattering (SAXS) characterization of the diamond nanoparticles showed a continuous size decrease from 5.2 to 4.8 nm during 15 layer-by-layer (LbL) oxidation cycles, in contrast to average particle size increase observed in the case of continuous oxidation in air. In accordance with the size decrease after LbL oxidation, the specific surface area (SSA) of the nanopowders increased.
EAM Import::2019-03-12

Layer-like FAU-type zeolites: A comparative view on different preparation routes - Reiprich, Bastian; Weissenberger, Tobias; Schwieger, Wilhelm; Inayat, Alexandra (Frontiers of Chemical Science and Engineering, 2020)
The creation of intergrown layer-like zeolite crystals is one route to form hierarchical zeolites. Faujasite-type (FAU-type) zeolites are among the industrially most important zeolites and the implementation of hierarchical porosity is a promising way to optimise their catalytic and adsorptive performance. After a short general survey into routes for the preparation of hierarchical pore systems in FAU, we will review the currently existing strategies for the synthesis of FAU with layer-like morphology. Those strategies are mainly based on the presence of morphology modifying agents in the synthesis mixture. However, a very recent approach is the synthesis of layer-like FAU-type zeolite crystals assembled in an intergrown manner in the absence of such additives, just by finely adjusting the crystallization temperature. This additive-free preparation route for layer-like FAU, which appears very attractive from an ecological as well as economic point of view, is highlighted in this review. Concluding, a comparison, including powder X-ray diffraction, scanning and transmission electron microscopy, nitrogen physisorption and elemental analysis, between conventional FAU and three layer-like FAU obtained by different synthesis routes was carried out to show the structural, morphological and textural differences and similarities of these materials. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-01-21
Keywords: FAU; hierarchical zeolite; layer-like morphology

Layer-like zeolite x as catalyst in a knoevenagel condensation: The effect of different preparation pathways and cation exchange - Grass, Jan-Paul; Klühspies, Katharina; Reiprich, Bastian; Schwieger, Wilhelm; Inayat, Alexandra (Catalysts, 2021)
This study is dedicated to the comparative investigation of the catalytic activity of layer-like Faujasite-type (FAU) zeolite X obtained from three different synthesis routes (additive-free route, Li2 CO3 route, and TPOAC route) in a liquid-phase Knoevenagel condensation of benzaldehyde and ethyl cyanoacetate to ethyl trans-α-cyanocinnamate. It is shown that the charge-balancing cations (Na+ and K+) and the morphological properties have a strong influence on the apparent reaction rate and degree of conversion. The highest initial reaction rate could be found for the layer-like zeolite X synthesised by the additive-free route in the potassium form. In most cases, the potassium-exchanged zeolites enabled higher maximum conversions and higher reaction rates compared to the zeolite X catalysts in sodium form. However, very thin crystal plates (below 100 nm thickness), similar to those obtained in the presence of TPOAC, did not withstand the multiple aqueous ion exchange procedure, with the remaining coarse crystals facilitating less enhancement of the catalytic activity.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Heterogeneous catalysis; Ion exchange; Knoevenagel condensation; Layer-like zeolites; Morphological modification; Zeolite X

LCA in Process Development: Case Study of the OxFA-Process - Rauch, Simon; Piepenbreier, Frank; Voß, Dorothea; Albert, Jakob; Hartmann, Martin (Progress in Life Cycle Assessment, 2019)
In the context of environmental problems and resource depletion, the chemical industry is challenged with the substitution of fossil feedstock by renewable resources. To reduce the probability of unexpected environmental impacts by new processes using various sources of biomass, LCA methods can provide support for process development. The investigated OxFA-process, which converts biomass into formic acid, is a typical representative for these next generation processes. However, at an early development stage, data gaps have to be handled. In this study, scientific literature, process simulation and generic data have been used to identify the catalyst, compressed air and energy consumptions as those process components are the ones that significantly influence the environmental footprint of the whole process. Hereby starting points for an effective process optimization are shown and different scenarios for process implementation are compared. Furthermore, a first estimation of the competitiveness with the state-of-the-art process was attempted. Despite some data inaccuracies and required estimations, it is fair to assume that the OxFA-process is an ecological reasonable alternative.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Biomass; Formic acid; Life cycle assessment; OxFa process

Leveraging gigawatt potentials by smart heat-pump technologies using ionic liquids - Wasserscheid, Peter; Seiler, Matthias (Chemsuschem, 2011)
One of the greatest challenges to science in the 21 st century is the development of efficient energy production, storage, and transformation systems with minimal ecological footprints. Due to the lack of efficient heat-transformation technologies, industries around the world currently waste energy in the gigawatt range at low temperatures (40-80°C). These energy potentials can be unlocked or used more efficiently through a new generation of smart heat pumps operating with novel ionic liquid (IL)-based working pairs. The new technology is expected to allow revolutionary technical progress in heat-transformation devices, for example, significantly higher potential efficiencies, lower specific investments, and broader possibilities to incorporate waste energy from renewable sources. Furthermore, due to drastically reduced corrosion rates and excellent thermal stabilities of the new, IL-based working pairs, the high driving temperatures necessary for multi-effect cycles such as double- or triple-effect absorption chillers, can also be realized. The details of this novel and innovative heat-transformation technology are described. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: absorption; crystallization; energy conversion; green chemistry; ionic liquids

Ligand Effects at Ionic Liquid-Modified Interfaces: Coadsorption of [C(2)C(1)lm][OTf] and CO on Pd(111) - Bauer, Tanja; Mehl, Sascha; Brummel, Olaf; Pohako-Esko, Kaija; Wasserscheid, Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2016)
Thin films of ionic liquids (ILs) can be used to tune the activity and selectivity of heterogeneous catalysts and electrocatalysts (solid catalysts with IL layer, SCILL). In several cases it has been found that these IL layers have a strong beneficial effect on the selectivity. To explore the molecular origin of this phenomenon, we have performed a model study on ultrahigh-vacuum conditions. We have investigated the coadsorption of CO and the room-temperature IL [CCIm][OTf] (1-ethyl-3-methylimidazolium trifluoromethanesulfonate) on Pd(111) by time-resolved infrared reflection-absorption spectroscopy, temperature-programmed reflection absorption spectroscopy, and temperature-programmed desorption. We find that the [OTf] anion adsorbs specifically to the Pd(111) surface via the SO group, thereby adopting a well-defined orientation with the molecular axis oriented perpendicular to the surface. At higher IL coverage, unspecific but oriented adsorption occurs, before the orientation is successively lost in the multilayer region. Upon coadsorption of [CCIm][OTf] on a CO-saturated Pd(111) surface at 300 K (θ = 0.5) a well-defined coadsorption layer is formed without any loss of adsorbed CO and with very similar CO site occupation. In the coadsorption layer [OTf] is specifically adsorbed between the CO with a molecular orientation perpendicular to the surface. Thus, a dense and homogeneous coadsorption layer is formed in which Pd surface atoms are simultaneously coordinated to both CO and [OTf] ions. From this compressed layer, CO desorbs with peak temperature at 410 K (heating rate, 3.3 K/s). Above this temperature, a low-coverage coadsorption phase of CO and surface-adsorbed IL resides, with little influence of the IL on the CO desorption temperature (peak temperature, 470 K). Coadsorption of the IL gives rise to a pronounced red shift of the CO stretching frequency in the order of 50 cm. The effect originates from the electrostatic interfacial field (Stark effect) generated by the coadsorbed IL and, at high coverage, possibly from additional short-range interactions. The results show that ILs form dense and well-defined mixed phases with strongly adsorbing reactants such as CO, in which a specifically adsorbed carpet of IL anions directly modifies the active surface sites by ligand-like effects.

Ligand Effects in SCILL Model Systems: Site-Specific Interactions with Pt and Pd Nanoparticles - Sobota, Marek; Happel, Markus; Amende, Maximilian; Paape, Natalia; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Advanced Materials, 2011)
Ionic liquids (ILs), such as [BMIM][Tf_2N], on well-defined SCILL model catalysts are able to replace weakly adsorbed CO. On Pt, on-top CO remains adsorbed under the ionic liquid layer, but its IR signal red-shifts by over 30 cm-1. IL–adsorbate interactions are mediated by the noble metal and similar to ligands.

Ligand effects on the surface composition of Rh-containing ionic liquid solutions used in hydroformylation catalysis - Kolbeck, Claudia; Paape, Natalia; Cremer, Till; Schulz, Peter; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Chemistry - A European Journal, 2010)
The chemical surface composition of Rh-containing ionic liquid solutions has been studied by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Rh-tppts complexes of high relevance for multiphase hydroformylation catalysis showed remarkable surface activity, whereas non-tppts containing systems showed Rh depleting from the surface (tppts=tris(3-sodium sulfonatophenyl)phosphine). © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Ligand-Modified Rhodium Catalysts on Porous Silica in the Continuous Gas-Phase Hydroformylation of Short-Chain Alkenes-Catalytic Reaction in Liquid-Supported Aldol Products - Schönweiz, Andreas; Debuschewitz, Jonas; Walter, Simon; Woelfel, Rene; Hahn, Hanna; Dyballa, Katrin M.; Franke, Robert; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2013)
Ligand-modified Rh complexes were physically adsorbed on the surface of porous silica. The resulting materials were subjected to the continuous gas-phase hydroformylation of C-2 and C-4 alkenes. The ligands used for catalyst modification were bidentate phosphorus ligands known from the literature, namely, sulfoxantphos (1) and a benzopinacol-based bulky diphosphite 2. The tested catalyst materials were active and, in particular, selective as in comparable homogeneous liquid-phase experiments. Long-term stability experiments over 1000h on stream showed minor deactivation. A significant increase in the catalyst mass after the reaction was detected by weighing and thermogravimetric analysis. By using headspace-GC-MS, the mass increase could be attributed to high-boiling compounds, which are formed insitu during the catalytic reaction itself and accumulate inside the pores of the support. Evidence is given that the initially physisorbed catalyst complexes dissolve in the high-boiling aldol side-products, which are suitable solvents for the active catalyst species and provide a liquid-phase environment held by capillary forces on the support.
Keywords: aldol reaction; hydroformylation; immobilization; rhodium; supported liquid

Ligands for catalytic reactions in ionic liquids. - Schulz, Peter (Wiley-VCH Verlag GmbH & Co. KGaA, 2008)
A review focusing on chiral, phosphorus-based ligands for transition-metal-catalyzed reactions in ionic liqs. [on SciFinder(R)]
Keywords: review phosphorus ligand prepn asym catalyst ionic liq

Liquid-Liquid Biphasic, Platinum-Catalyzed Hydrosilylation of Allyl Chloride with Trichlorosilane using an Ionic Liquid Catalyst Phase in a Continuous Loop Reactor - Hofmann, Norbert; Bauer, Andreas; Frey, Thomas; Auer, Marco; Stanjek, Volker; Schulz, Peter; Taccardi, Nicola; Wasserscheid, Peter (dvanced Synthesis & Catalysis, 2008)
The platinum-catalyzed hydrosilylation of allyl chloride with trichlorosilane was investigated in an ionic liquid-organic biphasic reaction mode. After an ionic liquid screening and repetitive batch mode experiments, the process was realized in a continuous mode using a loop reactor concept with integrated continuous separation and recycling of the ionic liquid catalyst phase. The continuous reactor could be operated for 48h at constant activity and selectivity without addition of platinum indicating that platinum leaching into the product phase was far below 1ppm. Enhanced selectivity for the product trichloro(3-chloropropyl)silane (compared to the state-of-the art) and the possibility to use simple platinum tetrachloride (PtCl_4) as platinum source are further attractive features of this new ionic liquid-based process concept.

Liquid Organic Hydrogen Carriers as an efficient vector for the transport and storage of renewable energy - Teichmann, Daniel; Arlt, Wolfgang; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2012)
This contribution proposes the usage of Liquid Organic Hydrogen Carriers (LOHC) for the storage and subsequently the transport of renewable energy. It is expected that a significant share of future energy consumption will be satisfied with the import of energy coming from regions with high potential for renewable generation, e.g. the import of solar power from Northern Africa to Europe. In this context the transport of energy in form of chemical carriers is proposed supplementary to electrical transmission. Because of their high storage density and good manageability under ambient conditions Diesel-like LOHC substances could be transported within the infrastructure that already exists for the handling of liquid fossil fuels (e.g. oil tankers, tank trucks, pipelines, etc.). A detailed assessment of energy consumption as well as of transport costs is conducted that confirms the feasibility of the concept. Copyright (c) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen storage; renewable energy; Energy transport; LOHC; Liquid hydrogen carriers; Feasibility study

Liquid organic hydrogen carriers (LOHCs): Toward a hydrogen-free hydrogen economy - Preuster, Patrick; Papp, Christian; Wasserscheid, Peter (Accounts of Chemical Research, 2017)
The need to drastically reduce CO2 emissions will lead to the transformation of our current, carbon-based energy system to a more sustainable, renewable-based one. In this process, hydrogen will gain increasing importance as secondary energy vector. Energy storage requirements on the TWh scale (to bridge extended times of low wind and sun harvest) and global logistics of renewable energy equivalents will create additional driving forces toward a future hydrogen economy. However, the nature of hydrogen requires dedicated infrastructures, and this has prevented so far the introduction of elemental hydrogen into the energy sector to a large extent. Recent scientific and technological progress in handling hydrogen in chemically bound form as liquid organic hydrogen carrier (LOHC) supports the technological vision that a future hydrogen economy may work without handling large amounts of elemental hydrogen. LOHC systems are composed of pairs of hydrogen-lean and hydrogen-rich organic compounds that store hydrogen by repeated catalytic hydrogenation and dehydrogenation cycles. While hydrogen handling in the form of LOHCs allows for using the existing infrastructure for fuels, it also builds on the existing public confidence in dealing with liquid energy carriers. In contrast to hydrogen storage by hydrogenation of gases, such as CO2 or N2, hydrogen release from LOHC systems produces pure hydrogen after condensation of the high-boiling carrier compounds. This Account highlights the current state-of-the-art in hydrogen storage using LOHC systems. It first introduces fundamental aspects of a future hydrogen economy and derives therefrom requirements for suitable LOHC compounds. Molecular structures that have been successfully applied in the literature are presented, and their property profiles are discussed. Fundamental and applied aspects of the involved hydrogenation and dehydrogenation catalysis are discussed, characteristic differences for the catalytic conversion of pure hydrocarbon and nitrogen-containing LOHC compounds are derived from the literature, and attractive future research directions are highlighted. Finally, applications of the LOHC technology are presented. This part covers stationary energy storage (on-grid and off-grid), hydrogen logistics, and on-board hydrogen production for mobile applications. Technology readiness of these fields is very different. For stationary energy storage systems, the feasibility of the LOHC technology has been recently proven in commercial demonstrators, and cost aspects will decide on their further commercial success. For other highly attractive options, such as, hydrogen delivery to hydrogen filling stations or direct-LOHC-fuel cell applications, significant efforts in fundamental and applied research are still needed and, hopefully, encouraged by this Account.

Liquid Organic Hydrogen Carriers: Surface Science Studies of Carbazole Derivatives - Papp, Christian; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter (Chemical Record, 2014)
We review recent results towards a molecular understanding of the adsorption and dehydrogenation of carbazole-derived liquid organic hydrogen carriers on platinum and palladium single crystals and on Al2O3-supported Pt and Pd nanoparticles. By combining synchrotron-based high-resolution X-ray photoelectron spectroscopy, infrared reflection-absorption spectroscopy, advanced molecular beam methods and temperature-programmed desorption spectroscopy, detailed insights into the reaction mechanism are obtained. On Pt(111), dehydrogenation of perhydro-N-ethylcarbazole, H-12-NEC, starts with activation of the hydrogen atoms at the pyrrole unit, yielding H-8-NEC as the first stable reaction intermediate at approximate to 340K, followed by further dehydrogenation to NEC at approximate to 380K. Above 390K, dealkylation starts, yielding carbazole as an undesired byproduct. On small supported Pt particles, the dealkylation sets in at lower temperatures, due to the higher reactivity of low-coordinated sites, while on larger particles with (111) facets a reactivity as on the flat surface is observed. Carbazole derivatives with ethyl, propyl and butyl chains show an overall very similar reactivity, both on Pt(111) and on Pt nanoparticles. When comparing the dealkylation behavior of H-12-NEC on Pt(111) and Pt nanoparticles to that on Pd(111) and Pd nanoparticles, we find a higher reactivity for the Pd systems.
Keywords: dehydrogenation; liquid organic hydrogen carriers; platinum; renewable resources; surface chemistry

Liquid silver tris(perfluoroethyl)trifluorophosphate salts as new media for propene/propane separation - Pliquett, Daniel; Schulz, Peter; Heinemann, Frank Wilhelm; Bause, Angela; Wasserscheid, Peter (Physical Chemistry Chemical Physics, 2016)
A series of silver tris(perfluoroethyl) trifluorophosphate (Ag[FAP]) complexes with various ligands (acetonitrile ACN, chloroacetonitrile Cl-ACN, acrylonitrile acryl-CN, pyridine py, ethylenediamine en and propene C3H6) have been synthesized starting from Ag[NO3] and K[FAP] using three different routes. Physicochemical properties as well as crystal structures ([Ag(ACN)(2/4)][FAP], [Ag(py) 2][FAP]) were determined and the suitability of such Ag salts for propene/propane separation processes was investigated. The investigated silver complexes exhibit either low melting points or form liquid complexes when contacted with gaseous propene at 30 degrees C. This makes them promising separation materials for both liquid membranes and absorber fluids due to their high silver content and significant propene capacity. Single (iGSC) and mixed (NMR) gas solubilities as well as diffusion coefficients (PFG-NMR) of propene and propane were determined to predict the theoretical selectivity of solubility, membrane selectivity, capacity and transport properties of the silver salts according to the solution diffusion model. A strong influence of the number and type of ligands on chemical complexation, physicochemical properties and separation performance has been observed.

Long-alkyl-chain-derivatized imidazolium salts and ionic liquid crystals with tailor-made properties - Wang, Xinjiao; Sternberg, Michelle; Kohler, Florian; Melcher, Berthold Ulrich; Wasserscheid, Peter; Meyer, Karsten (RSC Advances, 2014)
A series of new 1,3-dialkylimidazolium salts with the general formula [CCIM][A] (for n = 12; A = PF, OTf, NTf; for n = 10, 14, 16, and 18; A = BF, ClO) has been synthesized. The [CCIM][A] salts are ionic liquids at room temperature, whereas all [CCIM][BF] and [CCIM][ClO] (n = 10, 14, 16, 18) salts demonstrate a liquid crystalline phase at elevated temperatures that have a large mesophase window, which varies from 10 to 80 °C with increasing alkyl chain length. In particular, [CCIM][BF] shows liquid crystalline behavior at room temperature and therefore is potentially suitable for application as a pre-organized reaction medium in synthesis and catalysis. Viscosity studies of [CC IM][BF] and the corresponding perchlorate salt demonstrate strong non-Newtonian viscosity behavior for the liquid crystalline state of these ionic liquids. © 2014 The Royal Society of Chemistry.

Low melting Li/K/Cs acetate salt mixtures as new ionic media for catalytic applications - first physico-chemical characterization - Bajus, Stephanie; Deyko, Alexey; Bösmann, Andreas; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Dalton Transactions, 2012)
In order to expand the temperature limits of Supported Ionic Liquid Phase (SILP) or Solid Catalyst with Ionic Liquid Layer (SCILL) systems to higher operation temperatures, the mixture of lithium acetate, potassium acetate, and caesium acetate (molar ratio of 0.2/0.275/0.525) has been studied in detail. Physico-chemical properties of the bulk melt are reported together with stability data of the modern salt on various solid support materials showing attractive properties for many potential high temperature applications. © 2012 The Royal Society of Chemistry.

Low-Temperature Synthesis of Oxides in Ionic Liquids: Ozone-Mediated Formation of Co3O4 Nanoparticles Monitored by In Situ Infrared Spectroscopy - Bauer, Tanja; Agel, Friederike; Blaumeiser, Dominik; Maisel, Sven; Görling, Andreas; Wasserscheid, Peter; Libuda, Jörg (Advanced Materials Interfaces, 2019)
For most functional oxides, structure-selective synthesis is the key for the task-specific production of nanomaterials. Herein, the low-temperature synthesis in ionic liquids (ILs) is an attractive strategy to produce nanomaterials which are not accessible otherwise is described. In this study, a bench-scale synthesis route toward Co3O4 by applying O3 on the molecular precursor Co2(CO)8 in IL medium is reported. The Co3O4 nanoparticles (NPs) are characterized by infrared (IR) spectroscopy, X-ray diffraction (XRD), and transmission electron microscopy (TEM). This protocol yields Co3O4 with good crystallinity and narrow size distribution. In addition to conventional materials characterization, a new experimental approach is described in which the material synthesis in situ by IR reflection absorption spectroscopy (IRAS) (in situ IRAS) is followed. The in situ approach provides additional information on the growth mechanisms and kinetics and confirms that O3 treatment of Co2(CO)8 in IL exclusively yields pure Co3O4 without the formation of byproducts or intermediates.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Co; cobalt oxide; ionic liquids; IR spectroscopy; ozone

Macrokinetic effects in perhydro-N-ethylcarbazole dehydrogenation and H2 productivity optimization by using egg-shell catalysts - Peters, Willi; Seidel, Alexander; Herzog, Stefan; Bösmann, Andreas; Schwieger, Wilhelm; Wasserscheid, Peter (Energy and Environmental Science, 2015)
This contribution deals with pore diffusion influences on the dehydrogenation kinetics of perhydro-N-ethylcarbazole (H12-NEC). The reaction is of high interest in the context of hydrogen storage in the N-ethylcarbazole (NEC)/perhydro-N-ethylcarbazole (H12-NEC) Liquid Organic Hydrogen Carrier (LOHC) system. The hydrogen content of H12-NEC is 5.8 wt% and total dehydrogenation releases for each mL of H12-NEC more than 600 mL of H-2. Further optimization of H12-NEC dehydrogenation catalysis requires a better understanding of the role of mass transfer effects. Pore diffusion effects have been studied by preparing egg-shell catalysts (Pt/gamma-alumina layer on alpha-alumina core) of different active layer thicknesses (24 -88 mu m). It has been found that even at very thin catalyst layers (24 mu m) the kinetic regime is limited to 235 degrees C, thus pore diffusion effects the dehydrogenation in almost all commercial catalysts strongly.

Magnesium-Containing Bioactive Glasses for Biomedical Applications - Diba, Mani; Tapia, Felipe; Boccaccini, Aldo R.; Strobel, Leonie (International Journal of Applied Glass Science, 2012)
The importance of Mg in the human body, its key role in bone tissue development, in addition to its application to improve and modify physical, thermal, and mechanical properties of bioactive silicate glasses, make Mg a very interesting element as a component of bioactive glasses for medical applications. Although Mg is a typical element in the composition of numerous developed bioactive glasses, the analysis of the literature reveals that further research is required to gain comprehensive understanding about the effects of MgO on bioactive glass structure and properties. This article presents a comprehensive overview of the field of Mg-containing bioactive glasses discussing available compositions and summarizing existing knowledge on effects of MgO on glass properties. The biomedical applications of several developed glasses are discussed highlighting the distinct effects of Mg in relevant areas, such as bioactivity and cell response, and focusing on the most common applications for these glasses, such as bone cements, bioactive coatings, and scaffolds for bone tissue engineering. The effect of Mg on bone development is discussed and avenues for future research in the field are proposed, emphasizing the need to investigate unstudied properties of (already developed) Mg-containing glass compositions, such as angiogenesis-stimulating action and the effect on osteoclast functions, to develop new Mg-containing bioactive glasses as well as to make products of different shape designs such as nanoparticles, fibers, and complex porous structures. © 2012 The American Ceramic Society and Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.magnes

Magnesium-containing bioactive polycrystalline silicate-based ceramics and glass-ceramics for biomedical applications - Diba, Mani; Goudouri, Ourania Menti; Tapia, Felipe; Boccaccini, Aldo R. (Current Opinion in Solid State & Materials Science, 2014)
With improvement of orthopaedic technologies for bone replacement and regeneration, there is an increasing need for materials with superior properties. Mg-containing silicate ceramics and glass-ceramics have been shown to be bioactive and exhibit various advantages for biomedical applications. This review paper is intended to summarize and discuss the most relevant studies carried out in the field of Mg-containing bioactive silicate ceramics and glass-ceramics. © 2014 Elsevier Ltd. All rights reserved.
Keywords: Bioactive materials; Ceramics; Glass-ceramics; Magnesium; Silicate

Materials with Hierarchical Porosity Enhance the Stability of Infused Ionic Liquid Films - Galvan, Yaraset; Bauernfeind, Johannes; Wolf, Patrick; Zarraga, Ramon; Haumann, Marco; Vogel, Nicolas (ACS Omega, 2021)
Defined surface functionalities can control the properties of a material. The layer-by-layer method is an experimentally simple yet very versatile method to coat a surface with nanoscale precision. The method is widely used to either control the chemical properties of the surface via the introduction of functional moieties bound to the polymer or create nanoscale surface topographies if one polymeric species is replaced by a colloidal dispersion. Such roughness can enhance the stability of a liquid film on top of the surface by capillary adhesion. Here, we investigate whether a similar effect allows an increased retention of liquid films within a porous surface and thus potentially increases the stability of ionic liquid films infused within a porous matrix in the supported ionic liquid-phase catalysis. The complex geometry of the porous material, long diffusion pathways, and small sizes of necks connecting individual pores all contribute to difficulties to reliably coat the required porous materials. We optimize the coating process to ensure uniform surface functionalization via two steps. Diffusion limitations are overcome by force-wetting the pores, which transports the functional species convectively into the materials. Electrostatic repulsion, which can limit pore accessibility, is mitigated by the addition of electrolytes to screen charges. We introduce nanoscale topography in microscale porous SiC monoliths to enhance the retention of an ionic liquid film. We use gamma-Al2O3 to coat monoliths and test the retention of 1-butyl-2,3-dimethylimidazolium chloride under exposure to a continuous gas stream, a setup commonly used in the water-gas shift reaction. Our study showcases that a hierarchical topography can improve the stability of impregnated ionic liquid films, with a potential advantage of improved supported ionic liquid-phase catalysis.
CRIS-Team WoS Importer:2021-09-03

Measurement and Prediction of the Thermal Conductivity of Ionic Liquids - Rausch, Michael Heinrich; Krzeminski, Kamil; Assenbaum, Daniel; Wasserscheid, Peter; Leipertz, Alfred; Fröba, Andreas Paul (Chemie Ingenieur Technik, 2011)
Thermal conductivities of seven ionic liquids (ILs) based on the cation [EMIM] (1-ethyl-3-methylimidazolium) and four ILs based on the anion [NTf(2)] (bis(trifluoromethylsulfonyl)imide) were measured for temperatures between 0 and 80 degrees C using a guarded parallel plate instrument. With the corresponding data, a simple relation between thermal conductivity, molar mass, and density of the ILs at constant temperature was found, representing a convenient tool for the estimation of the thermal conductivities of arbitrary ILs.
Keywords: Ionic liquids; Stationary parallel plate instrument; Thermal conductivity

Measurement and Prediction of the Thermal Conductivity of Tricyanomethanide- and Tetracyanoborate-Based Imidazolium Ionic Liquids - Koller, Thomas Manfred; Schmid, Stefan; Sachnov, Swetlana; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Thermophysics, 2014)
The thermal conductivity of ten ionic liquids (ILs) based on the anions [C(CN)(3)](-) (tricyanomethanide) and [B(CN)(4)](-) (tetracyanoborate) carrying a homologous series of the [alkyl-MIM](+) (1-alkyl-3-methylimidazolium) cations [EMIM](+) (ethyl), [BMIM](+) (butyl) [HMIM](+) (hexyl), [OMIM](+) (octyl), [DMIM](+) (decyl) was measured by a steady-state guarded parallel-plate instrument in the temperature range between (283.15 and 353.15) K at atmospheric pressure with a total uncertainty of 5 % (k = 2). Furthermore, the refractive index required for data evaluation and the density, which is an important property in the developed prediction method for the thermal conductivity, were determined. In general, the measured thermal conductivities of the probed ILs decrease with increasing temperature and increasing alkyl-chain length of the cation. Regarding the influence of the anion, somewhat smaller values for the [B(CN)(4)](-)-based ILs compared to the [C(CN)(3)](-)-based ILs carrying the same cation are observed. Our previously developed simple prediction method for the thermal conductivity of ILs at 293.15K using only information on the molar mass and the density could be improved. By the combination of this approach with the temperature dependence of the density, an extended empirical correlation additionally describing the temperature dependence of the thermal conductivity of ILs is recommended. This correlation represents all experimental thermal-conductivity data in the literature with a standard deviation of less than 7 %.
Keywords: Density; Ionic liquids; Parallel-plate method; Prediction; Refractive index; Thermal conductivity

Measurement of diffusion coefficients of gaseous alkenes in ionic liquids by NMR spectroscopy. - Melcher, Berthold Ulrich; Schulz, Peter (Chemie Ingenieur Technik, 2009)

Measurement of Hydrogen Solubility in Potential Liquid Organic Hydrogen Carriers - Aslam, Rabya; Müller, Karsten; Müller, Michael; Koch, Marcus; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Chemical and Engineering Data, 2016)
Liquid organic hydrogen carriers (LOHC) are potential compounds that can facilitate chemical energy storage and hydrogen logistics using reversible hydrogenation. For the process development, the physical solubility of hydrogen in potential LOHCs is required. In this work, solubility of hydrogen in the potential LOHC systems toluene/methylcyclohexane, N-ethylcarbazole/perhydro-N-ethylcarbazole, and dibenzyltoluene/perhydrodibenzyltoluene was measured using the static isochoric saturation method. The data were measured at low pressures up to 10 bar within the temperature range of (293 to 373) K. Hydrogen solubility in hydrogenated forms of the LOHCs was found to be higher compared to the dehydrogenated forms. Solubility in all substances increased with increasing temperature within the whole temperature range under consideration. The temperature dependency of the Henry coefficient of hydrogen in the solvents was correlated using the Benson and Krause correlation.

Measurement of Minute Liquid Volumes of Chiral Molecules Using In-Fiber Polarimetry - Schorn, Florian; Essert, Arabella; Zhong, Yu; Abdullayev, Sahib; Castiglione, Kathrin; Haumann, Marco; Joly, Nicolas (Analytical Chemistry, 2023)

Measuring and predicting the extraction behaviour of biogenic formic acid in biphasic aqueous/organic reaction mixtures - Albert, Jakob; Veith, Heiner; Voges, Matthias; Held, Christoph (ACS Omega, 2017)
The distribution coefficients and selectivities required for extraction purposes were predicted with a thermodynamic equation of state for the ternary system formic acid/water/extraction solvent. These predictions were validated with experimental data from the literature and experimental data from the oxidation of biomass to formic acid process measured in this work. Extraction solvents discussed in this work are 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, 1-decanol, ethyl n-butyl ether, diisopropyl ether, di-n-butyl ether, benzyl formate, and heptyl formate. The considered temperature ranged from 273 to 363 K under atmospheric pressure. Perturbed-chain statistical associating fluid theory (PC-SAFT) was used for prediction purposes applying an approach as simple as possible and as complex as necessary to achieve trustworthy data for selecting the best extraction solvent. Using PC-SAFT allowed identifying 1-hexanol as the most promising solvent out of the 11 extraction agents. The predicted data were in good agreement with the experimental distribution coefficients and the selectivities, which are very sensitive to experimental uncertaintie

Measuring average rheological quantities of cell monolayers in the linear viscoelastic regime - Dakhil, Haider; Gilbert, Daniel; Malhotra, Deepika; Limmer, Anja; Engelhardt, Hannes; Amtmann, Anette; Hansmann, Jan; Hübner, Holger; Buchholz, Rainer; Friedrich, Oliver; Wierschem, Andreas (Rheologica Acta, 2016)
During the last decades, the rheology of cells has been studied almost entirely in single cells. While cell-to-cell variation is typically very large and most studies were carried out in the nonlinear viscoelastic regime, we quantify average linear viscoelastic cell properties like storage and loss moduli and normal stress in monolayers of different cell types showing that murine 3T6 fibroblasts, human fibroblasts, and HeLa cells differ considerably in their storage modulus. To this end, we modified a commercial rheometer to set up a parallel-disk configuration at gap widths of a few micrometers and optically detected the cell concentration in the gap. This enables studying the linear viscoelastic behavior of the cells and permits quantifying the impact of drugs affecting the cytoskeleton or the extracellular matrix connection. Thus, due to its high-content approach, without the need of treating the samples in the rheometer, this envisions the use of this method as a fast diagnostic tool. The method also allows for quantitatively studying of the impact of pre-stress on the storage and loss moduli of the cells.
Keywords: Cell rheology; Linear viscoelasticity; Narrow-gap rheometry; Parallel-disk configuration; Cell monolayer; Biochemical treatment; Pre-stress; Primary cells; Cell lines

Mechanism of the Water–Gas Shift Reaction Catalyzed by Efficient Ruthenium-Based Catalysts: A Computational and Experimental Study - Stepic, Robert; Wick, Christian; Strobel, Vinzent; Berger, Daniel; Vucemilovic-Alagic, Natasa; Haumann, Marco; Wasserscheid, Peter; Smith, Ana-Suncana; Smith, David M. (Angewandte Chemie International Edition, 2019)
Supported ionic liquid phase (SILP) catalysis enables a highly efficient, Ru-based, homogeneously catalyzed water-gas shift reaction (WGSR) between 100 °C and 150 °C. The active Ru-complexes have been found to exist in imidazolium chloride melts under operating conditions in a dynamic equilibrium, which is dominated by the [Ru(CO) 3 Cl 3 ] − complex. Herein we present state-of-the-art theoretical calculations to elucidate the reaction mechanism in more detail. We show that the mechanism includes the intermediate formation and degradation of hydrogen chloride, which effectively reduces the high barrier for the formation of the requisite dihydrogen complex. The hypothesis that the rate-limiting step involves water is supported by using D 2 O in continuous catalytic WGSR experiments. The resulting mechanism constitutes a highly competitive alternative to earlier reported generic routes involving nucleophilic addition of hydroxide in the gas phase and in solution.
CRIS-Team Scopus Importer:2019-08-16
Keywords: ab initio calculations; reaction mechanisms; ruthenium; supported catalysts; water–gas shift reaction

Mechanistic studies on the formation of Pt(II) hydroformylation catalysts in imidazolium-based ionic liquids - Illner, Peter; Zahl, Achim; Puchta, Ralph; van Eikema Hommes, Nico; Wasserscheid, Peter; van Eldik, Rudi (Journal of Organometallic Chemistry, 2005)
The kinetics of the formation of the active species cis-[Pt (PPh)Cl(SnCl)] and cis-[Pt (PPh)(SnCl)] from the hydroformylation catalyst precursor cis-[Pt(PPh )Cl] in the presence of SnCl, was studied in two different imidazolium-based ionic liquids. A large range of different chlorostannate melts consisting of 1-butyl-3-methyl-imidazolium cations and [SnCl] anions with varying molar fraction of SnCl, were prepared and characterized by H and Sn NMR. The observed chemical shifts point to major changes in the composition of the anionic species within the melt. The second ionic liquid employed, viz., 1-butyl-3-methyl-imidazolium-bis(trifluormethylsulfonyl)amide was prepared in a colorless quality that enabled its application in kinetic studies. The concentration and temperature dependence of the substitution of Cl by [SnCl] to yield cis-[Pt(PPh )Cl(SnCl)], could be studied in detail. Theoretical (DFT) calculations were employed to model the reaction progress and to resolve the role of the ionic liquid in the activation of the catalyst. The available results are presented and a plausible mechanism for the formation of the catalytically active species is suggested. © 2005 Elsevier B.V. All rights reserved.

Melting Points of Potential Liquid Organic Hydrogen Carrier Systems Consisting of N-Alkylcarbazoles - Stark, Katharina; Keil, Philipp; Schug, Sebastian; Müller, Karsten; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Chemical and Engineering Data, 2016)

Mesoporous and Graphitic Carbide-Derived Carbons as Selective and Stable Catalysts for the Dehydrogenation Reaction - Gläsel, Jan-Sebastian; Diao, Jiangyong; Feng, Zhenbao; Hilgart, Markus; Wolker, Thomas; Su, Dang Sheng; Etzold, Bastian (Chemistry of Materials, 2015)
Dehydrogenation of ethylbenzene to styrene is one of the most important catalytic processes in chemical industry. While it was demonstrated that nanocarbons like nanotubes, nanodiamond, or nanographite show high performance, especially selectivity, these powders give rise to handling problems, high pressure drop, hampered heat and mass transfer, and unclear health risks. More common macroscopic carbon materials like activated carbons show unsatisfying selectivity below 80%. In this study, mesoporous, graphitic, and easy to handle carbon powders were synthesized on the basis of the reactive extraction of titanium carbide in a novel temperature regime. This resulted in extraordinary properties like a mean pore diameter of up to 8 nm, pore volumes of up to 0.90 mL g-1, and graphite crystallite sizes exceeding 25 nm. Exceptional styrene selectivities of up to 95% were observed for materials synthesized above 1300 °C and pretreated with nitric acid. Furthermore, the long-term stability of these non-nanocarbon catalysts could be demonstrated for the first time during 120 h of time-on-stream. (Figure Presented).
CRIS-Team Scopus Importer:2023-08-15

Metal-organic frameworks constructed with 1, 2, 4-triazol-1-ylacrylic acid ligand: Syntheses and crystal structures - Fischer, Nina; Inayat, Alexandra; Schwieger, Wilhelm; Burzlaff, Nicolai (Journal of Coordination Chemistry, 2010)
Synthesis of a triazole-based N, O ligand, 1, 2, 4-triazol-1-yl)acrylate (ta) is described. The coordination of this new ligand is studied by the reaction of K[ta] (3) with zinc(II), manganese(II), cobalt(II), iron(II), and magnesium(II). The ligand favors the formation of metal-organic frameworks (MOFs) apart from magnesium(II). Single-crystal X-ray diffraction analyses reveal MOF structures for [Mn(ta) ] (4), [Fe(ta) ] (5), [Co(ta)2(H O) ] (6), and [Zn(ta) ] (7). © 2010 Taylor & Francis.
Keywords: Ligand design; Metal-organic frameworks; Triazole; N; O ligand

Methanol Steam Reforming Promoted by Molten Salt-Modified Platinum on Alumina Catalysts - Kusche, Matthias Manfred; Agel, Friederike; Ní Bhriain, Nollaig; Kaftan, Andre; Laurin, Mathias; Libuda, Jörg; Wasserscheid, Peter (Chemsuschem, 2014)
We herein describe a straight forward procedure to increase the performance of platinum-on-alumina catalysts in methanol steam reforming by applying an alkali hydroxide coating according to the "solid catalyst with ionic liquid layer" (SCILL) approach. We demonstrate by diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and temperature-programmed desorption (TPD) studies that potassium doping plays an important role in the catalyst activation. Moreover, the hygroscopic nature and the basicity of the salt modification contribute to the considerable enhancement in catalytic performance. During reaction, a partly liquid film of alkali hydroxides/carbonates forms on the catalyst/alumina surface, thus significantly enhancing the availability of water at the catalytically active sites. Too high catalyst pore fillings with salt introduce a considerable mass transfer barrier into the system as indicated by kinetic studies. Thus, the optimum interplay between beneficial catalyst modification and detrimental mass transfer effects had to be identified and was found on the applied platinum-on-alumina catalyst at KOH loadings around 7.5 mass%.
Keywords: catalyst characterization; heterogeneous catalysis; methanol reforming; molten salts; platinum

Method for inertization of oxygen-sensitive heterogeneous catalysts using ionic liquids. - Ehrig, Martin; Gerhard, Dirk; Medved, Mitja; Obert, Katharina; Wasserscheid, Peter (2008)
Treating surfaces of oxygen-sensitive heterogeneous catalysts and insensitive towards oxygen heterogeneous catalysts, esp. pyrophoric nickel Raney hydrogenation catalysts with ionic liqs. makes them insensitive against reactions with oxygen. Thus, mixing 2 wt. parts nickel Raney hydrogenation catalysts (keeped in water in anaerobic conditions) with 3 wt. parts 1-butyl-3-methylimidazolium bistrifluoromethylsulfonylimide followed by removing water in a rotor evaporator at 50 mbar and 50° gave a catalyst for hydrogenation 2,3-dimethyl-1,3-butadiene, which is practically insensitive to oxygen. [on SciFinder(R)]
Keywords: treating surface oxygen sensitive heterogeneous catalyst raney nickel catalyst; ionic liq treating surface oxygen sensitive heterogeneous catalyst

Method for manufacturing menthol by hydrogenation of thymol to menthone and hydrogenation on menthone to menthol. - Dreisbach, Claus; Jentsch, Jörg-Dietrich; Heuer, Lutz; Wasserscheid, Peter; Rittsteiger, Anne; Mechelhoff, Martin (2014)
The invention presents a process for prodn. of 2-isopropyl-5-Me cyclohexanol (D, L-menthol) by hydrogenation of thymol to menthone and following hydrogenation to D, L-menthol. [on SciFinder(R)]
Keywords: menthol prodn process catalyst thymol hydrogenation menthone intermediate

Method for preparation of mononitrated aromatic compounds in ionic liquids. - Schlenk, Stefan; Wasserscheid, Peter; Rijksen, Christiaan; Noti, Christian; Hanselmann, Paul (2012)
The invention discloses a method for prepn. of mononitrated arom. compds. in a liq.-liq. biphasic solvent system with aq. nitric acid as one phase and ionic liqs. (ILs) as the second phase, wherein the nitric acid is continuously exchanged during the reaction, or the water, that is generated during the reaction, is removed by addn. of NO2 and an oxidizing agent (oxygen or air) during the reaction. The ionic liq. is selected from the group consisting of nitrate, hydrogen sulfonate, methanesulfonate, 1,1,2,2,tetrafkuoroethanesulfonate and trifluoromethanesulfonate of N+R1R2R3R4 [R1 and R2 are identical or different and independently from each other C1-14-alkyl; R3 is C4-14-alkyl; R4 is C4-14-alkyl or C1-14-alkyl-SO3H; with the proviso, that the total no. of carbons in R1, R2, R3 and R4 is at least 16; and, with proviso, that if R1 and R2 are C1-2-alkyl then R3 and R4 are C10-14-alkyl] and P+R1R2R3R4. Thus, PhMe was nitrated with aq. HNO3 in Bu4N+NO3- to give 39% 2-, 3-, and 4-nitrotoluene (1:0.09:0.64). [on SciFinder(R)]
Keywords: mononitrated arom compd prepn; benzene deriv nitration nitric acid ionic liq; nitrogen dioxide nitration arom compd oxidizing agent ionic liq

Method for producing aldehydes from alkanes and synthesis gas. - Franke, Robert; Hahn, Hanna; Quandt, Thomas; Wasserscheid, Peter; Haumann, Marco; Walter, Simon (2015)
A method for producing aldehydes from alkanes and synthesis gas comprises a) dehydrating at least one alkane in the presence of a heterogeneous catalyst to produce at least one alkene, b) conversion of the alkene or the alkenes from step a) with hydrogen and carbon monoxide in the presence of a heterogeneous catalyst comprising a solid substrate material which supports an ionic liq. which contains a catalyst including at least one transition metal and at least one ligand. Thus, obtaining pentanal by dehydrogenating and hydroformylating butane at 850° and normal pressure implemented in a dehydrogenation reactor made of Alloy 600 having length 650 mm and inner diam. 10 mm and contg. 10 g a hydrogenation catalyst such as Cr2O3 and CrO3 supported on alumina followed by hydroformylation step implemented in a hydroformylation reactor at 450° and pressure 50 bar in the presence of 3 g a SILP catalyst prepd. from Rh(CO)2acac, 2,2'-(3,3'-Di-tert-butyl-5,5'-dimethoxybiphenyl-2,2'-diyl)bis(oxy)bis(4,4,5,5-tetraphenyl-1,3,2-dioxaphospholane) as a ligand and EMIM NTF2 as an ionic liq. and supported Kieselgel 100 takes place with selectivity >99%. [on SciFinder(R)]
Keywords: producing aldehyde alkane synthesis gas pentanal

Method for removing chromium from material containing collagen and chromium. - Reiners, Jürgen; Kuhlmann, Sven; Rabe, Volker; Hufschmidt, Jan; Westerholt, Antje; Bösmann, Andreas; Wasserscheid, Peter (2015)
The invention relates to a method for removing chromium from material contg. collagen and chromium, preferably leather contg. chromium, with the use of an extractant, wherein the extractant is a compd. of the formula K+A-, or a mixt. of a compds. of the formula K+A-, where K+ is a cation selected from ammonium, iminium, phosphonium and sulfonium; and A- is an anion selected from phosphate, phosphonate, phosphinate, borate, sulfate, sulfonate, amide, imide, carbene, carboxylate and carbonate, preferably selected from phosphate, phosphonate, phosphinate, thiophosphate, thiophosphonate, and thiophosphinate. [on SciFinder(R)]
Keywords: ionic liq extractant leather extn chromium removal

Method for the isomerization of substituted aromatic substances using a molten metal salt. - Kuhlmann, Sven; Weber, Hans-Martin; Böger, Uwe; Wasserscheid, Peter; Schlenk, Stefan; Meßner, Julia (2013)
A method for the isomerization of substituted arom. substances such as, an example, p-dichlorobenzene comprises isomerization at 100 - 220° in the presence of a mixt. of molten salts comprising AlCl3, AlBr3 and GaCl3 with chlorides of Li, K, Naor Cs at ratios (1:1) - (10:1). Thus, mixing in a glass autoclave at 170° 20 mol.% AlCl3 with 10 mol.% LiCl, adding 250 g p-dichlorobenzene, stirring 4 h at 170° gave a mixt. contg. 53% m-dichlorobenzene, 44% p-dichlorobenzene and 3% o-dichlorobenzene. [on SciFinder(R)]
Keywords: isomerization substituted arom substance molten metal salt

Methodology for the Design of Optimal Chemical Reactors Based on the Concept of Elementary Process Functions - Peschel, Andreas; Freund, Hannsjörg; Sundmacher, Kai (21st International Symposium on Chemical Reaction Engineering, 2010)
In this contribution, a methodology for the optimal design of chemical reactors based on the best reaction route in the thermodynamic state space is proposed. This route is obtained by tracking a fluid element on its way through the reactor and manipulating the fluxes into this element. Instead of choosing the reactor design a priori and optimizing the free parameters of the chosen reactor setup, an innovative reactor design is developed based on the optimal flux profiles. Besides classical reactor concepts, this methodology is suited to investigate the potential of different process intensification options such as integration of reaction, cooling and separation in a single apparatus, or the application of high interface areas for heat and mass transfer. The methodology is exemplarily illustrated for the development of a new SO(2) oxidation reactor. The residence time as an example for a meaningful objective is minimized, and a reduction of 69% compared to the optimized technical reference case is achieved.

Methylated [(arene)(1,3-cyclohexadiene)Ru(0)] complexes as low-melting MOCVD precursor complexes with a controlled follow-up chemistry of the ligands - Jipa, Ilona; Danova, Katia; Popovska, Nadejda; Siddiqi, M. Aslam; Siddiqui, Rehan A.; Atakan, B.; Cremer, Till; Maier, Florian; Marbach, Hubertus; Steinrück, Hans-Peter; Heinemann, Frank Wilhelm; Zenneck, Ulrich (Journal of Materials Chemistry, 2011)
[(Benzene)(2-methyl-1,3-cyclohexadiene)Ru(0)] (1), [(1,3-cyclohexadiene) (toluene)Ru(0)] (2), and [(methyl-cyclohexadiene)(toluene)Ru(0)] (3, mixture of isomers) have been prepared and tested as new metal organic ruthenium precursor complexes for chemical vapor deposition (MOCVD) with favorable properties. 1 is a low-melting precursor complex (mp = 29 °C) and the isomeric mixture 3 forms a liquid at room temperature. X-ray diffraction studies of single crystals of complexes 1 and 2 are characteristic for true Ru(0) π-complexes without molecular structure peculiarities or significant intermolecular interactions in the solid state, which could hinder undecomposed evaporation. Differential thermal analysis (DTA), differential scanning calorimetry (DSC) and vapor pressure data qualify the compounds as almost ideal MOCVD precursors. Thin ruthenium films have been deposited successfully on silicon wafers and substrate temperatures between 200 and 450 °C in inert gas atmospheres. Film growth and properties were evaluated by scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and four-point probe conductivity measurements. All films consist of polycrystalline metallic ruthenium with a low surface roughness. © The Royal Society of Chemistry 2011.

Methylated [(benzene)(1,3-butadiene)Ru0] derivatives as novel MOCVD precursors with favorable properties - Jipa, Ilona; Siddiqi, M. Aslam; Siddiqui, Rehan A.; Atakan, Burak; Marbach, Hubertus; Cremer, Till; Maier, Florian; Steinrück, Hans-Peter; Danova, Katia; Popovska, Nadejda; Heinemann, Frank Wilhelm; Zenneck, Ulrich (Chemical Vapor Deposition, 2011)
[(Benzene)(2-methyl-1,3-butadiene)Ru] (1), [(benzene)(2,3- dimethyl-1,3-butadiene)Ru] (2), and [(2,3-dimethyl-1,3-butadiene) (toluene)Ru] (3) are prepared and tested as new metal-organic (MO) ruthenium precursor complexes with favorable deposition properties for the CVD of thin ruthenium films. X-ray diffraction (XRD) studies of single crystals of the complexes are characteristic for true Ru π-complexes without molecular structure peculiarities or significant intermolecular interactions in the solid state, which can hinder undecomposed evaporation. Differential thermal analysis (DTA) and vapor pressure data qualify the compounds as almost ideal MOCVD precursors. Thin ruthenium films are deposited successfully on silicon wafers at substrate temperatures between 200 and 400°C in a nitrogen gas atmosphere. X-ray photoelectron spectroscopy (XPS), four-point probe conductivity measurements, and atomic force microscopy (AFM) are used to characterize the films. All films consist of polycrystalline metallic ruthenium with a low surface roughness. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

MFI Type Zeolite Aggregates with Nanosized Particles via a Combination of Spray Drying and Steam-Assisted Crystallization (SAC) Techniques - Machoke, Albert; Arias, Aurina Martinez; Baracchini, Giulia; Rubin, Michael; Baser, Hasan-Hüseyin; Weissenberger, Tobias; Dittmeyer, Roland; Weber, Alfred; Hartmann, Martin; Schwieger, Wilhelm (Catalysts, 2023)
Hydrothermal synthesis is the state-of-the-art technique for the preparation of zeolites and related porous solids. However, when it comes to the preparation of nanosized zeolites, this technique is limited by low yields, separation problems and high amounts of waste. In this work, we utilized the strengths of a combination of spray drying and steam-assisted crystallization (SAC), also known as dry gel conversion, to reduce these problems. At spray drying temperatures between 300 and 400 degrees C, it was possible to convert all the amorphous material via SAC into zeolite particles without extra addition of template. Kinetic studies of SAC revealed that about 4 to 8 days are needed to achieve the formation of a 100% crystalline product. The newly formed crystalline phase was crystallized on the surface of the nanosized zeolites and led to a slight increase in the primary particle size while the macroscopic morphology of the spray-dried aggregates was preserved. This work demonstrates that the combination of spray drying and SAC are useful tools in supplementing the hydrothermal synthesis of nanosized zeolites.
CRIS-Team WoS Importer:2023-04-14
Keywords: spray drying; steam-assisted crystallization; zeolites

MFI-type zeolites from natural materials: a comparative study of MFI-type zeolites generated from different diatomite species (part I) - Alyosef, Hallah Ahmad; Roggendorf, Hans; Schneider, Denise; Inayat, Alexandra; Welscher, Julia; Schwieger, Wilhelm; Münster, Tom; Kloess, Gert; Ibrahim, Suzan S.; Enke, Dirk (Journal of Porous Materials, 2016)
A new one step approach for the preparation of MFI-type zeolites through direct trans-formation of pre-modified diatomite is reported. Two diatomite species modified by calcination and acid treatment were used as silica and alumina sources. The progress of the transformation was investigated by analyzing samples after different crystallization times at 453 K. Tetrapropylammonium hydroxide was utilized for the first time as bi-functional molecule for silica dissolution in diatomite and structure directing agent during zeolite formation. In this way, the use of an additional alkaline source, such as sodium hydroxide, for silica dissolution was not necessary. The applied diatomite samples contained amorphous silica in combination with impurities like feldspar, anatase and quartz. This allowed the systematic investigation of the influence of modification procedure, amorphous silica content and crystalline impurities of the different diatomite samples on the direct transformation in MFI-type zeolites. During the transformation process, the feldspar was totally dissolved. The quartz content was reduced to <10 wt% in the final products as compared with the modified diatomite starting material. X-ray diffraction, nitrogen adsorption, scanning electron microscopy and optical emission spectroscopy were used to characterize these materials.
Keywords: Amorphous silica; MFI-type zeolite; Modified diatomite; Quartz; Silica source

MFI-type (ZSM-5) zeolite-filled TiO2 nanotubes for enhanced photocatalytic activity - Paramasivam, Indhumati; Avhale, Abhijeet; Inayat, Amer; Bösmann, Andreas; Schmuki, Patrik; Schwieger, Wilhelm (Nanotechnology, 2009)
The present work demonstrates enhanced photocatalytic activity for zeolite-filled TiO2 nanotubes. ZSM-5 zeolite nanocrystals were grown on and into a TiO2 nanotubular skeleton (TiNT/ZSM-5) by multi-step hydrothermal synthesis consisting of in situ seeding and multiple in situ crystallization (MISC). The resulting zeolite nanocrystals were in the range of a few nanometers and they adhere well to the nanotubular inner walls. After crystallization, the photocatalytic activity of this zeolite-filled nanotube catalyst system was compared with neat anatase TiO2 nanotube (TiNT) and with calcined ZSM-5 powder. The results show for TiNT/ZSM-5 a highly enhanced efficiency for the decomposition of acetophenone (used as an aromatic model organic pollutant).

Micro/Macroporous System: MFI-Type Zeolite Crystals with Embedded Macropores - Machoke, Albert; Beltran, Ana M.; Inayat, Alexandra; Winter, Benjamin; Weissenberger, Tobias; Kruse, Nadine; Guettel, Robert; Spiecker, Erdmann; Schwieger, Wilhelm; Spiecker, Erdmann (Advanced Materials, 2015)
Zeolite crystals with an embedded and interconnected macropore system are prepared by using mesoporous silica particles as a silica source and as a sacrificial macroporogen. These novel hierarchical zeolite crystals are expected to reduce diffusion limitations in all zeolite-catalyzed reactions, especially in the transformation of larger molecules like in the catalytic cracking of polymers and the conversion of biomass.

Mikrowellenheizung und Ultraschallmonitoring in der Zeolithsynthese - Schwieger, Wilhelm; Schmachtl, M.; Scharf, Oliver; Herrmann, Ralph; Kim, J.; Grill, W.; Stenzel, C.; Schertlen, R.; Venot, Y. (Innovative Energieträger in der Verfahrenstechnik II, 2001)
UnivIS-Import:2015-03-09:Pub.2001.tech.ITC.LTCIR.mikrow_4

Minkowski Tensor Shape Analysis of Cellular, Granular and Porous Structures - Peukert, Wolfgang; Schröder-Turk, Gerd; Mickel, Walter; Kapfer, Sebastian; Klatt, Michael; Schaller, Fabian; Hoffmann, Matthias; Kleppmann, Nicola; Inayat, Amer; Armstrong, Patrick; Hug, Daniel; Reichelsdorfer, Martin; et al. (Advanced Materials, 2011)
Predicting physical properties of materials with spatially complex structures is one of the most challenging problems in material science. One key to a better understanding of such materials is the geometric characterization of their spatial structure. Minkowski tensors are tensorial shape indices that allow quantitative characterization of the anisotropy of complex materials and are particularly well suited for developing structure-property relationships for tensor-valued or orientation-dependent physical properties. They are fundamental shape indices, in some sense being the simplest generalization of the concepts of volume, surface and integral curvatures to tensor-valued quantities. Minkowski tensors are based on a solid mathematical foundation provided by integral and stochastic geometry, and are endowed with strong robustness and completeness theorems. The versatile definition of Minkowski tensors applies widely to different types of morphologies, including ordered and disordered structures. Fast linear-time algorithms are available for their computation. This article provides a practical overview of the different uses of Minkowski tensors to extract quantitative physically-relevant spatial structure information from experimental and simulated data, both in 2D and 3D. Applications are presented that quantify (a) alignment of co-polymer films by an electric field imaged by surface force microscopy; (b) local cell anisotropy of spherical bead pack models for granular matter and of closed-cell liquid foam models; (c) surface orientation in open-cell solid foams studied by X-ray tomography; and (d) defect densities and locations in molecular dynamics simulations of crystalline coppe
Keywords: geometric; statistic; spatial; anisotropy; shape; morphology; crystal

Mixtures of ionic liquids with lewis acids as catalysts. - Wasserscheid, Peter; Metlen, Andreas; Brausch, Nicole (2005)
Ionic liqs. useful as catalysts in Lewis acid-catalyzed reactions, comprises a mixt. of one or more triflate or bis(trifluoromethylsulfonyl)imide salt(s) with one or more Lewis acid(s), wherein the total of the molar contents of the Lewis acid(s) in the mixt. is from about 0.01-98%. [on SciFinder(R)]
Keywords: ethylmethylpyridinium bistrifluoromethylsulfonylimide aluminum chloride friedel crafts acylation catalyst

Model-Based Analysis of a Liquid Organic Hydrogen Carrier (LOHC) System for the Operation of a Hydrogen-Fired Gas Turbine - Dennis, Jason; Bexten, Thomas; Petersen, Nils; Wirsum, Manfred; Preuster, Patrick (Journal of Engineering For Gas Turbines and Power-Transactions of the Asme, 2021)
One of the main challenges currently hindering the transition to energy systems based on renewable power generation is grid stability. To compensate for the volatility of wind- and solar-based power generation, storage facilities able to adapt to seasonal and short-term differences in energy production and demand are required. Liquid organic hydrogen carriers (LOHCs) represent a viable method of chemically binding elemental hydrogen, offering opportunities for large-scale and safe energy storage. In times of energy shortage, flexible and dispatchable power generation technologies such as gas turbines can be fueled by hydrogen stored in this manner. Hydrogen can be released from its liquid carrier via an endothermic dehydrogenation reaction using waste heat provided by the gas turbine. This gaseous hydrogen can be supplied to the gas turbine combustion chamber using a hydrogen compressor. In this study, a steady-state model is developed in order to analyze the heat-integrated combination of a 7.7 MW hydrogen-fired gas turbine and a perhydrodibenzyltoluene (H18-DBT)/dibenzyltoluene (H0-DBT) LOHC system. For the best-performing parameter set, the effective storage density of the LOHC oil comes to 1.5 kWh/L. This value is situated in between that of compressed hydrogen at 350 bar (1.01 kWh/L) and liquid hydrogen (2.33 kWh/L). Concurrently, the corresponding energy required for hydrogen compression reduces the overall system efficiency to 22.00% (GT=30.15%). The resulting optimal electricity yield, being a product of these two values, amounts to 0.33 kWhel/L.
CRIS-Team Scopus Importer:2021-02-26

Model-Based Determination of the Optimal Reaction Route for Integrated Multiphase Processes - Hentschel, Benjamin; Freund, Hannsjörg; Sundmacher, Kai (Chemie Ingenieur Technik, 2014)
For the optimal reactor design, the knowledge of the optimal reaction route is crucial. Model-based methods are superior since in complex reactions the intuitive identification of the optimal reaction route is mostly impossible. Using the hydro-formylation of long chain olefins as an example, an optimal control-based method is presented which considers the possible recycling of chemical components in early stages of the design process. Thereby, not only the optimal reaction concept can be identified, but also requirements for the downstream separation processes can be derived.
Keywords: Dynamic optimization; Hydroformylation; Process design; Reactor design

Model-based development of optimal reaction concepts for plant wide process intensification - Peschel, Andreas; Jörke, Andreas; Freund, Hannsjörg; Sundmacher, Kai (Elsevier BV, 2012)
The oxygen based production of ethylene oxide, one of the most important bulk chemicals, is considered as an example. Here, advanced cooling and distributed dosing of oxygen is identified as best reaction concept from an economical and technological point of view. Applying this innovative reaction concept, the production costs of an average sized plant are reduced by 1.35 Mio /a, and the CO2 emissions are decreased by 2.7.10(4) t/a compared to an optimized reference case. This general method provides a first step towards more economical and greener processes.
Keywords: Reactor; design; optimization; ethylene oxide; process intensification

Model-Based Development of Optimal Reaction Concepts for Plant Wide Process Intensification - Peschel, Andreas; Jörke, Andreas; Freund, Hannsjörg; Sundmacher, Kai (Computer Aided Chemical Engineering, 2012)

Model-Based Identification and Experimental Validation of the Optimal Reaction Route for the Hydroformylation of 1-Dodecene - Hentschel, Benjamin; Kiedorf, Gregor; Gerlach, Martin; Hamel, Christof; Seide-Morgenstern, Andreas; Freund, Hannsjörg; Sundmacher, Kai (Industrial & Engineering Chemistry Research, 2015)
Previously developed kinetic and dynamic models of the hydroformylation of 1-dodecene in a thermomorphic multicomponent solvent system (TMS), consisting of DMF, n-decane, and hydroformylation products, were experimentally validated applying various operation modes, such as batch, semibatch, and perturbed batch operation. On the basis of experimentally obtained data, which cover a broad range of physical conditions, the parameters of the reaction kinetics were refined to give reliable model predictions as basis for rigorous process optimization. The improved model was used for dynamic optimization to obtain optimal trajectories (e.g., temperature and gas dosing fluxes versus reaction time), which maximize the selectivity to the desired linear aldehyde product. The predicted optimal trajectories were successfully validated in semibatch reactor experiments.

Model-based prediction of optimal conditions for 1-octene hydroformylation - Hentschel, Benjamin; Peschel, Andreas; Xie, Mingquan; Vogelpohl, Christina; Sadowski, Gabriele; Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering Science, 2014)
After fitting the PC-SAFT parameters to pure component data the model was used to study the influence of product formation on the solubilities of H-2 and CO. Finally, the reaction conditions were optimized in order to maximize the differential selectivity to the desired product n-nonanal. It is shown that the performance of the hydroformylation reaction system can be significantly increased by optimally controlling temperature, total pressure, and the amount of H-2 and CO in the gas phase. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: PC-SAFT; Multiphase systems; VLE; Simultaneous optimization; Hydroformylation; Reactor design

Model-Based Reactor Design Based on the Optimal Reaction Route - Freund, Hannsjörg; Peschel, Andreas; Sundmacher, Kai (Chemie Ingenieur Technik, 2011)
A novel methodology for the model-based design of chemical reactors is presented. The aim of the method is the identification of the optimal reaction route and its technical realization. As an important characteristic of this novel approach, at the beginning a fluid element is considered on an abstract level. The fluid element is tracked over the reaction time and its state is optimally adjusted at any time. The advantage of this approach is that at the early design stage no constraints owing to predefined apparatus specific limitations are narrowing the solution space. That way it is possible to quantify the maximum potential of the reaction system.
Keywords: Optimization; Process intensification; Reaction control; Reactor design

Model catalytic studies of liquid organic hydrogen carriers: Dehydrogenation and decomposition mechanisms of dodecahydro-n-ethylcarbazole on pt(111) - Amende, Maximilian; Gleichweit, Christoph; Werner, Kristin; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Papp, Christian; Koch, Marcus; Wasserscheid, Peter; Laurin, Mathias; Steinrück, Hans-Peter; et al. (ACS Catalysis, 2014)
Liquid organic hydrogen carriers (LOHC) are compounds that enable chemical energy storage through reversible hydrogenation. They are considered a promising technology to decouple energy production and consumption by combining high-energy densities with easy handling. A prominent LOHC is N-ethylcarbazole (NEC), which is reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H -NEC). We studied the reaction of H-NEC on Pt(111) under ultrahigh vacuum (UHV) conditions by applying infrared reflection-absorption spectroscopy, synchrotron radiation-based high resolution X-ray photoelectron spectroscopy, and temperature-programmed molecular beam methods. We show that molecular adsorption of H-NEC on Pt(111) occurs at temperatures between 173 and 223 K, followed by initial C-H bond activation in direct proximity to the N atom. As the first stable dehydrogenation product, we identify octahydro-N-ethylcarbazole (H -NEC). Dehydrogenation to H-NEC occurs slowly between 223 and 273 K and much faster above 273 K. Stepwise dehydrogenation to NEC proceeds while heating to 380 K. An undesired side reaction, C-N bond scission, was observed above 390 K. H-NEC and H-carbazole are the dominant products desorbing from the surface. Desorption occurs at higher temperatures than H-NEC formation. We show that desorption and dehydrogenation activity are directly linked to the number of adsorption sites being blocked by reaction intermediates. © 2014 American Chemical Society.

Model Catalytic Studies of Novel Liquid Organic Hydrogen Carriers: Indole, Indoline and Octahydroindole on Pt(111) - Schwarz, Matthias; Bachmann, Philipp; Nascimento Silva, Thais; Mohr, Susanne; Scheuermeyer, Marlene; Späth, Florian; Bauer, Udo; Düll, Fabian; Steinhauer, Johann; Hohner, Chantal; Döpper, Tibor; Noei, Heshmat; et al. (Chemistry - A European Journal, 2017)
Indole derivatives were recently proposed as potential liquid organic hydrogen carriers (LOHC) for storage of renewable energies. In this work, we have investigated the adsorption, dehydrogenation and degradation mechanisms in the indole/indoline/octahydroindole system on Pt(111). We have combined infrared reflection absorption spectroscopy (IRAS), X-ray photoelectron spectroscopy (XPS) and DFT calculations. Indole multilayers show a crystallization transition at 200 K, in which the molecules adopt a strongly tilted orientation, before the multilayer desorbs at 220 K. For indoline, a less pronounced restructuring transition occurs at 150 K and multilayer desorption is observed at 200 K. Octahydroindole multilayers desorb already at 185 K, without any indication for restructuring. Adsorbed monolayers of all three compounds are stable up to room temperature and undergo deprotonation at the NH bond above 300 K. For indoline, the reaction is followed by partial dehydrogenation at the 5-membered ring, leading to the formation of a flat-lying di-sigma-indolide in the temperature range from 330-390 K. Noteworthy, the same surface intermediate is formed from indole. In contrast, the reaction of octahydroindole with Pt(111) leads to the formation of a different intermediate, which originates from partial dehydrogenation of the 6-membered ring. Above 390 K, all three compounds again form the same strongly dehydrogenated and partially decomposed surface species.
Keywords: density functional theory; infrared reflection absorption spectroscopy; liquid organic hydrogen carrier; octahydroindole; X-ray photoelectron spectroscopy

Modeling of the Continuous Dehydrogenation of Perhydro-Dibenzyltoluene in a Cuboid Reactor - Geißelbrecht, Michael; Benker, Rachid; Seidel, Alexander; Preuster, Patrick (Energy Technology, 2024)
The use of the dibenzyltoluene/perhydro-dibenzyltoluene (H18–DBT) system as a liquid organic hydrogen carrier (LOHC) enables the safe and loss-free storage of hydrogen. The release of hydrogen from the LOHC is a catalytic reaction and requires ≈27% of the lower heating value of the released hydrogen in the form of heat neglecting heat losses. The high heat requirement makes it necessary to design chemical conversion units that both provide good heat input and accommodate the high gas release. Up to 1200 L of hydrogen is released from 1 L of LOHC under reaction conditions. In this work, a cuboid reactor for the release of hydrogen from H18–DBT is demonstrated. In the experiments, it is shown that evaporation has a significant effect on the reaction rate and thus the amount of hydrogen releases. Therefore, a kinetic model capable of accounting for the release rate and evaporation in the reactor is developed. The model is successfully validated and shows deviations of less than 15% between measured and modeled hydrogen flow in the entire range considered. Since the model considers this important interaction between evaporation and hydrogen release for the first time, it is suitable for optimizing the reactor used.
CRIS-Team Scopus Importer:2024-02-23
Keywords: cuboid reactors; hydrogen storage; LOHCs; modeling of dehydrogenation of perhydro-dibenzyltoluene

Modellgestützter Reaktorentwurf auf der Basis der optimalen Reaktionsführung - Freund, Hannsjörg (Jahrestreffen Reaktionstechnik, 2010)

Modelling (vapour plus liquid) and (vapour plus liquid plus liquid) equilibria of water (H2O) + methanol (MeOH) plus dimethyl ether (DME) plus carbon dioxide (CO2) quaternary system using the Peng-Robinson EoS with Wong-Sandler mixing rule - Ye, Kongmeng; Freund, Hannsjörg; Sundmacher, Kai (Journal of Chemical Thermodynamics, 2011)
The (vapour + liquid) equilibria (VLE) and (vapour + liquid + liquid) equilibria (VILE) binary data from literature were correlated using the Peng-Robinson (PR) equation of state (EoS) with the Wong-Sandler mixing rule (WS). Two group contribution activity models were used in the PRWS: UNIFAC-PSRK and UNIFAC-Lby. The systems were successfully extrapolated from the binary systems to ternary and quaternary systems. Results indicate that the PRWS-UNIFAC-PSRK generally displays a better performance than the PRWS-UNIFAC-Lby. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: PRWS; UNIFAC; VLE; VLLE; Dimethyl ether; Carbon dioxide; Anti-solvent

Model Studies on the Ozone-Mediated Synthesis of Cobalt Oxide Nanoparticles from Dicobalt Octacarbonyl in Ionic Liquids - Schuster, Ralf; Wähler, Tobias; Kettner, Miroslav; Agel, Friederike; Bauer, Tanja; Wasserscheid, Peter; Libuda, Jörg (ChemistryOpen, 2020)
Low-temperature synthesis in ionic liquids (ILs) offers an efficient route for the preparation of metal oxide nanomaterials with tailor-made properties in a water-free environment. In this work, we investigated the role of 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide [C4C1Pyr][NTf2] in the synthesis of cobalt oxide nanoparticles from the molecular precursor Co2(CO)8 with ozone. We performed a model study in ultra-clean, ultrahigh vacuum (UHV) conditions by infrared reflection absorption spectroscopy (IRAS) using Au(111) as a substrate. Exposure of the pure precursor to ozone at low temperatures results in the oxidation of the first layers, leading to the formation of a disordered CoxOy passivation layer. Similar protection to ozone is also achieved by deposition of an IL layer onto a precursor film prior to ozone exposure. With increasing temperature, the IL gets permeable for ozone and a cobalt oxide film forms at the IL/precursor interface. We show that the interaction with the IL mediates the oxidation and leads to a more densely packed CoxOy film compared to a direct oxidation of the precursor.
CRIS-Team Scopus Importer:2020-09-25
Keywords: cobalt oxide; ionic liquids; IR spectroscopy; low temperature synthesis; ozone

Modification of nitrogen doped carbon for SILP catalyzed hydroformylation of ethylene - Weiß, Alexander; Giese, Matthias; Lijewski, Martin; Franke, Robert; Wasserscheid, Peter; Haumann, Marco (Catalysis: Science and Technology, 2017)
We report the application of nitrogen doped carbon (NDC) materials as supports for the SILP catalyzed gas-phase hydroformylation of ethylene. The Rh-xantphos complex, dissolved in [EMIM][NTf2] and dispersed onto commercially available activated carbon yielded low activity. The incorporation of nitrogen functionalities into the surface was achieved via oxidation of the original carbon support followed by reduction with either urea or ammonia. SILP catalysts based on the so-obtained NDC materials provided higher activity in ethylene hydroformylation, while at the same time the formation of undesired aldol condensation products was low. Thus, the performance of the new SILP catalyst on NDC material represents a significant step ahead for a technically relevant, continuous catalytic operation with very high aldehyde selectivity.
CRIS-Team Scopus Importer:2023-03-29

Modifying the Electrocatalytic Selectivity of Oxidation Reactions with Ionic Liquids - Yang, Tian; Yang, Juntao; Deng, Xin; Franz, Evanie; Fromm, Lukas; Taccardi, Nicola; Liu, Zhi; Görling, Andreas; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Angewandte Chemie International Edition, 2022)
The "solid catalyst with ionic liquid layer" (SCILL) is an extremely successful new concept in heterogeneous catalysis. The idea is to boost the selectivity of a catalyst by its modification with an ionic liquid (IL). Here, we show that it is possible to use the same concept in electrocatalysis for the selective transformation of organic compounds. We scrutinize the electrooxidation of 2,3-butanediol, a reaction which yields two products, singly oxidized acetoin and doubly oxidized diacetyl. When adding the IL (1-ethyl-3-methyl-imidazolium trifluormethanesulfonate, [C(2)C(1)Im][OTf]), the selectivity for acetoin increases drastically. By in situ spectroscopy, we analyze the underlying mechanism: Specific adsorption of the IL anions suppresses the activation of water for the second oxidation step and, thus, enhances the selectivity for acetoin. Our study demonstrates the great potential of this approach for selective transformation of organic compounds.
CRIS-Team WoS Importer:2022-06-03

Monitoring of catalytic reactions in photonic crystal fiber - Cubillas, Ana Maria; Schmidt, Matthias; Scharrer, Michael; Euser, T. G.; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Hollow-core photonic crystal fiber (HC-PCF) offers several advantages for chemical analysis, for example, long optical pathlengths, sub-L sample volumes, close to 100% overlap between light and sample, and more compact systems for sensing [1-2] and photochemistry [3-4]. Here we compare the performance of a conventional cuvette-based UV-VIS system for monitoring of catalytic reactions with a system based on liquid-filled HC-PCF. We study the photo-Fenton catalytic reaction, which under visible light irradiation induces degradation of methylene blue dye (MB) in the presence of Fe2+ / H2O 2 [5]. © 2011 IEEE.
CRIS-Team Scopus Importer:2023-08-15

Monitoring of liquid-phase organic reactions by photoelectron spectroscopy - Kolbeck, Claudia; Niedermaier, Inga; Taccardi, Nicola; Schulz, Peter; Maier, Florian; Wasserscheid, Peter; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2012)
There are strings attached: After linking the reacting groups to head groups of ionic liquids to drastically lower the vapour pressures of the reactants, ordinary liquid-phase organic reactions can be monitored by in situ X-ray photoelectron spectroscopy. This approach is demonstrated for the nucleophilic substitution of an alkyl amine and an alkyl chloride moiety, which are attached to the cation and anion of ionic liquids, respectively. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Monodispersed lysozyme-functionalized bioactive glass nanoparticles with antibacterial and anticancer activities - Zheng, Kai; Lu, Miao; Liu, Yufang; Chen, Qiang; Taccardi, Nicola; Hueser, Norbert; Boccaccini, Aldo R. (Biomedical Materials, 2016)
In this study, highly monodispersed spherical bioactive glass nanoparticles (BGS) with a particle size of 408 ± 36 nm were synthesized using a modified Stöber method. The BGS was then functionalized with lysozyme (LY) via a simple electrostatic interaction routine under selected conditions. The LY-functionalized BGS (LY-BGS) exhibited monodispersity, spherical morphology and homogeneity in size. The incorporated content of LY could be tailored conveniently by adjusting the initial concentration of the LY precursor for functionalization. Hydroxyapatite (HA) formed on the LY-BGS after soaking in simulated body fluid (SBF) for 7 d, but the formation was retarded compared to the non-functionalized BGS. The LY-BGS showed antibacterial activity towards Gram-positive B. subtilis and >90% of the bacteria was killed within 24 h after culture with the LY-BGS at a concentration of 1 mg ml-1. The LY-BGS also showed cytotoxicity towards the human hepatocellular carcinoma (HepG2) cell line. In addition, the relative cytotoxicity increased with an increase in the concentration of the LY-BGS in contact with the cells. As a comparison, the LY-BGS exhibited reduced or no cytotoxicity towards human umbilical vein endothelial cells (HUVECs) at the same concentration with respect to the HepG2 groups. Notably, the relative cell viability of HepG2 was 45.9% after exposure to the LY-BGS at a concentration of 10 extgreekmg ml-1 for 24 h, while no decrease in relative viability for the HUVECs was observed under the same conditions. This cytotoxicity window between cancerous cells and healthy cells could be expected for cancer treatment. Furthermore, the antibacterial properties and the bioactivity of LY-BGS make it a promising material for biomedical applications, particularly in the treatment of bone defects caused by tumors.
Keywords: antibacterial activity; anticancer activity; bioactive glasses; lysozyme; nanocomposites

Monolithic SiC supports with tailored hierarchical porosity for molecularly selective membranes and supported liquid-phase catalysis - Portela, Raquel; Marinkovic, Jakob Maximilian; Logemann, Morten; Schörner, Markus; Zahrtman, Nanette; Eray, Esra; Haumann, Marco; García-Suárez, Eduardo J.; Wessling, Matthias; Ávila, Pedro; Riisager, Anders; Fehrmann, Rasmus (Catalysis Today, 2020)
Monolithic support materials with the mechanical resistance and thermal conductivity of SiC as well as tunable surface chemistry and textural properties were developed for their use in catalytic membrane reactors. After heat treatment, the extruded SiC monoliths have a monomodal distribution of macropores of a few μm in diameter depending on the particle size of the starting material. A macroporous, defect-free, smoother skin was applied onto the external wall using a solution of sub-micrometer SiC particles. These monoliths with skin could be coated successfully with molecularly selective membranes, and thus have application in membrane reactor processes. Finally, metal oxide nanoparticles were infiltrated into the macropores to modify the surface texture and chemistry, allowing the immobilization of liquid phase catalysts. The resulting multimodal distribution of pore sizes could be tuned by the choice of SiC and oxide particle sizes, number of wash-coats and calcination temperature. Mesopores created between nanoparticles had diameters of roughly 40 % of those of the nanoparticles. Small macropores, between 10−1000 nm, were also created, with bigger size and volume at higher calcination temperatures due to the metal oxide particles contraction. The developed materials were validated as support for PDMS membranes and for continuous gas-phase hydroformylation of 1-butene using Rh-diphosphite catalysts.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Catalysis; Hydroformylation; Molecularly selective membrane; Monolith; Porosity; Silicon carbide

MRI investigation and complementary numerical simulations of flow-through random bead packings with low aspect ratio - Zeiser, Thomas; Freund, Hannsjörg; et al. (Magnetic Resonance Imaging, 2005)
UnivIS-Import:2015-07-08:Pub.2005.tech.ITC.stmmec.mriinv

Multinary salt system for storing and transferring thermal energy. - Wasserscheid, Peter; Gladen, Henner; Medved, Mitja (2008)
A salt compn. contg. 10-55 wt.% KNO2, 15-35 wt.% NaNO2, and 10-35 wt.% LiNO3 or its aq. soln. is used for storing and/or transferring thermal energy. The compn. can further contain ≤ 10 wt.% Ca(NO3)2 and 30-50 wt.% KNO3. The compn. contains at least one of the following salts: NaNO3, Sr(NO3)2, Ba(NO3)2, RbNO3, or CsNO3. The aq. soln. contains ≥ 30 wt.% of the salt compn. and ≤ 70 wt.% water. [on SciFinder(R)]
Keywords: multinary salt system thermal energy storage transfer heat

Multi-objective reactor design under uncertainty: A decomposition approach based on cubature rules - Maußner, Johannes; Freund, Hannsjörg (Chemical Engineering Science, 2019)
Model-based strategies for chemical reactor design proved to be a reliable tool for the systematic design of resource and energy efficient chemical reactors. The adequacy and accuracy of the underlying model equations (e.g. reaction kinetics and kinetics for heat and mass transport) are crucial for the success of such design approaches. However, the models used in chemical engineering are typically based on experimental data and predictive expressions for the fundamental phenomena and thus the respective model parameters are inevitably subject to uncertainty. Therefore, consideration of parametric uncertainty in the design strategy is necessary to obtain reliable chemical reactor designs. Moreover, the design of chemical reactors involves almost always multiple conflicting objectives which poses an additional challenge. In the present work, we propose an efficient reactor design strategy to tackle the combined challenges of parametric uncertainty and multiple conflicting objectives. The approach combines a scalarization method with a cubature rule to efficiently determine robust compromise solutions. The cubature rule is used to approximate the first two statistical moments of the objectives and of all critical inequality constraints. The approximation of the statistical moments is performed separate from the optimization problem. This leads to an iterative approach with improved computational performance. The proposed approach is illustrated and compared to an existing approach from literature by studying three different reactor design case studies, namely the optimization of a batch, semi-batch and multi-tubular fixed-bed reactor. The results of the newly proposed reactor design approach and the existing method from literature are in very good agreement for all considered case studies. The advantage of the new approach is a significantly lower computational effort compared to the existing method. This is especially visible for the more complex case studies with a higher number of uncertain parameters. The advantage of the approach proposed in the present work is thus particularly relevant and important for the application to complex reactor design tasks such as, e.g., the design of polymerization reactors or multi-phase reactors.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Cubature rule; Maleic anhydride synthesis; Model-based reactor design; Multi-objective optimization; Optimization under uncertainty

Multiscale Chemical Process Design Exemplified for a PEM Fuel Cell Process - Karst, Florian; Freund, Hannsjörg; Maestri, Matteo; Sundmacher, Kai (Chemie Ingenieur Technik, 2014)
To maximize the utilization of limited energy and material resources, a new design methodology for chemical processes is proposed based on a multiscale optimization approach. The different levels of the process hierarchy are presented and design aspects are discussed. The methodology is further exemplified by considering a methane steam reforming process for operation of a proton exchange membrane fuel cell (PEMFC) in an automotive application. The method delivers an optimal technically feasible process based on an integrated steam reforming reactor, operated in autothermal mode.
Keywords: Methane Reforming; Micro Kinetic Model; Multiscale Process Design; Process Optimization

Multi-walled carbon nanotube-based composite materials as catalyst support for water-gas shift and hydroformylation reactions - Wolf, Patrick; Logemann, Morten; Schörner, Markus; Keller, Laura; Haumann, Marco; Wessling, Matthias (RSC Advances, 2019)
In times of depleting fossil fuel reserves, optimizing industrial catalytic reactions has become increasingly important. One possibility for optimization is the use of homogenous catalysts, which are advantageous over heterogeneous catalysts because of mild reaction conditions as well as higher selectivity and activity. A new emerging technology, supported ionic liquid phase (SILP), was developed to permanently immobilize homogeneous catalyst complexes for continuous processes. However, these SILP catalysts are unable to form freestanding supports by themselves. This study presents a new method to introduce the SILP system into a support made from multi-walled carbon nanotubes (MWCNT). In a first step, SILP catalysts were prepared for hydroformylation as well as low-temperature water-gas shift (WGS) reactions. These catalysts were integrated into freestanding microtubes formed from MWCNTs, with silica (for hydroformylation) or alumina particles (for WGS) incorporated. In hydroformylation, the activity increased significantly by around 400% when the pure MWCNT material was used as SILP support. An opposite trend was observed for WGS, where pure alumina particles exhibited the highest activity. A significant advantage of the MWCNT composite materials is the possibility to coat them with separation layers, which allows their application in membrane reactors for more efficient processes.
CRIS-Team Scopus Importer:2019-09-17

Mutual and Self-Diffusivities in Binary Mixtures of [EMIM][B(CN)(4)] with Dissolved Gases by Using Dynamic Light Scattering and Molecular Dynamics Simulations - Koller, Thomas Manfred; Heller, Andreas; Rausch, Michael Heinrich; Wasserscheid, Peter; Economou, Ioannis G.; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2015)
Ionic liquids (ILs) are possible working fluids for the separation of carbon dioxide (CO2) from flue gases. For evaluating their performance in such processes, reliable mutual-diffusivity data are required for mixtures of ILs with relevant flue gas components. In the present study, dynamic light scattering (DLS) and molecular dynamics (MD) simulations were used for the investigation of the molecular diffusion in binary mixtures of the IL 1-ethyl-3-methylimidazolium tetracyanoborate ([EMIM][B(CN)(4)]) with the dissolved gases carbon dioxide, nitrogen, carbon monoxide, hydrogen, methane, oxygen, and hydrogen sulfide at temperatures from 298.15 to 363.15 K and pressures up to 63 bar. At conditions approaching infinite dilution of a gas, the Fick mutual diffusivity of the mixture measured by DLS and the self-diffusivity of the corresponding gas calculated by MD simulations match, which could be generally found within combined uncertainties. The obtained diffusivities are in agreement with literature data for the same or comparable systems as well as with the general trend of increasing diffusivities for decreasing IL viscosities. The DLS and MD results reveal distinctly larger molecular diffusivities for [EMIM][B(CN)(4)]-hydrogen mixtures compared to mixtures with all other gases. This behavior results in the failure of an empirical correlation with the molar volumes of the gases at their normal boiling points. The DLS experiments also showed that there is no noticeable influence of the dissolved gas and temperature on the thermal diffusivity of the studied systems.

Mutual and Thermal Diffusivity of Binary Mixtures of the Ionic Liquids [BMIM][C(CN)(3)] and [BMIM][B(CN)(4)] with Dissolved CO2 by Dynamic Light Scattering - Rausch, Michael Heinrich; Heller, Andreas; Herbst, Jonas; Koller, Thomas Manfred; Bahlmann, Matthias; Schulz, Peter; Wasserscheid, Peter; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2014)
Ionic liqs. (ILs) are promising solvents for gas sepn. processes such as carbon dioxide (CO2) capture from flue gases. For the design of corresponding processes and app., thermophys. properties of ILs contg. dissolved gases are required. In the present study, it is demonstrated that with a single optical setup, mutual and thermal diffusivities as well as refractive indexes can be measured quasi-simultaneously for such mixts. Dynamic light scattering (DLS) from bulk fluids was applied to det. mutual and thermal diffusivities for mixts. of 1-butyl-3-methylimidazolium tricyanomethanide ([BMIM][C(CN)3]) or 1-butyl-3-methylimidazolium tetracyanoborate ([BMIM][B(CN)4]) with dissolved CO2 at temps. from 303.15 to 333.15 K and pressures between 2 and 26 bar in macroscopic thermodn. equil. Good agreement with literature data and only slight differences between the diffusivities measured for the two systems at the same temp. and comparable mole fractions of CO2 were found. Increasing mutual diffusivities with increasing mole fractions of CO2 are consistent with decreasing viscosities reported for other IL-CO2 mixts. in the literature and can be attributed to weakening of mol. interactions by the dissolved gas. For the conditions studied, no dependence of the thermal diffusivity on the temp. or the mole fraction of CO2 could be found. [on SciFinder(R)]
Keywords: mutual thermal diffusivity binary mixt ionic liq carbon dioxide; refractive index carbon dioxide dissolved ionic liq

Nano-casted N-Doped Carbon Created From a Task-Specific Protic Salt and Controlled Porous Glass - Singh, Varun; Gantman, Mikhail; Selvam, Thangaraj; Muenzer, Maximilian; Enke, Dirk; Schwieger, Wilhelm (Frontiers in Chemistry, 2019)
3-dimensionally interconnected macroporous carbons are versatile materials that can be used in catalysis, electrochemical devices, and separation technology. Herein, the synthesis of a nitrogen doped carbonaceous material with a well-defined nanoarchitecture via nano-casting is demonstrated. A novel carbon source, a task-specific protic salt, has been proposed to create nitrogen doped carbon by direct carbonization within the pores of controlled macroporous glass. After the removal of macroporous glass from the composite using an aqueous sodium hydroxide solution and upon further heat treatment, an oxidation resistant doped carbon with high nitrogen content (6 mass %) is obtained. The materials formed during the different stages of the nano-casting process exhibit interesting properties such as hierarchical porosity, very high nitrogen content (15 mass %), and increased oxidational stability. A combination of different properties to create tailor-made materials for different applications using this technique is possible.
CRIS-Team Scopus Importer:2019-12-31
Keywords: controlled porous glass; direct carbonization; macroporous carbon replica; N-doped carbon; nano-casting

Nanocrystalline Zeolite Tetraethylammonium-Beta Membrane for Preferential Sorption and Transport of CO2 over N2 - Singh, Puyam S.; Selvam, Thangaraj; Reuß, Stephanie; Avhale, Abhijeet; Lopez Orozco, Sofia; Schwieger, Wilhelm (Chemical Engineering & Technology, 2013)
CO2/N2 gas separation was performed over a nanocrystalline zeolite tetraethylammonium (TEA)-beta membrane prepared on a stainless-steel porous disc by repeated hydrothermal crystallization. Two to three consecutive hydrothermal syntheses were required to form a membrane comprised of a continuous and compact layer of zeolite beta nanocrystals on the support. The membrane TEA-BEA3 obtained by three consecutive syntheses, in which the membrane from two consecutive syntheses was used as support, exhibited the highest structural order. When the separation experiment was performed over this membrane without applying any external applied pressure, 100% selectivity of CO2 over N2 was observed. The separation was driven by differences in chemical potentials of the molecules generated only by the adsorption-desorption behavior of the gases into the membrane. The novel zeolite TEA-beta membrane provided promising results for the separation of small gas molecules due to the combined influence of diffusion and sorption selectivity.
Keywords: CO2/N-2 separation; Hydrothermal crystallization; Nanocrystalline zeolite; Tetraethylammonium-beta membrane

Nanostructured Encapsulated Catalysts for Combination of Fischer-Tropsch Synthesis and Hydroprocessing - Kruse, Nadine; Machoke, Albert; Schwieger, Wilhelm; Guettel, Robert (ChemCatChem, 2015)
Controlling the selectivity of Fischer-Tropsch synthesis in a single reaction step is highly desirable, but is a major challenge in heterogeneous catalysis. One approach is the application of bifunctional catalysts. However, to control the catalytic properties the morphology of the catalyst needs to be controlled on the nanoscopic scale. Herein, an innovative synthetic approach that allows the bottom-up construction of nanostructured bifunctional catalysts in a step-wise manner is described. The resulting material, which exhibits cobalt nanoparticles encapsulated inside a zeolite matrix, was proven to be active in the combined Fischer-Tropsch and cracking reaction, evidenced by a shift from waxy to liquid products. Consequently, the use of this novel approach was demonstrated in terms of material synthesis and catalytic applications.
Keywords: cracking; Fischer-Tropsch synthesis; heterogeneous catalysis; nanomaterials; zeolites

Natural Cuban zeolites for medical use and their histamine binding capacity - Selvam, Thangaraj; Schwieger, Wilhelm; Dathe, W. (Clay Minerals, 2014)
The work reported herein involves the characterization of natural zeolites from two different mines (San Andres and Tasajeras; Cuba) using XRD, SEM, TG-DTA, ICP and surface area measurements. In addition, the chemical composition of zeolites, the heavy metal and environmental organic toxins content, the ion exchange rates, stability under biological conditions using simulated body fluids as well as the binding capacity for histamine have been investigated with a view to using them as medical products. The investigated zeolites contain clinoptilolite and mordenite as major phases. Furthermore, the samples are apparently free from fibrous materials according to SEM observations. In particular, the San Andres zeolite binds remarkable amounts of histamine which are nearly irreversible under acidic (pH = 1; 12.4 mg/g) and neutral conditions (pH = 7; 15.7 mg/g), respectively. Thus, the San Andres sample may well be applied as a medical product due to its excellent binding capacity for histamine along with its remaining optimum physico-chemical characteristics.
Keywords: natural zeolite; clinoptilolite; mordenite; morphology; chemical composition; aluminium-leaching; ion-exchange; histamine uptake; medical product

n-Butane Carbonylation to n-Pentanal Using a Cascade Reaction of Dehydrogenation and SILP-Catalyzed Hydroformylation - Walter, Simon; Haumann, Marco; Wasserscheid, Peter; Hahn, Hanna; Franke, Robert (Aiche Journal, 2015)
A novel gas-phase process has been developed that allows direct two-step conversion of butane into pentanals with high activity and selectivity. The process consists of alkane dehydrogenation over a heterogeneous Cr/Al2O3 catalyst followed by direct gas-phase hydroformylation using advanced supported ionic liquid phase (SILP) catalysis. The latter step uses rhodium complexes modified with the diphosphite ligands biphephos (BP) and benzopinacol to convert the butane/butene mixture from the dehydrogenation step efficiently into aldehydes. The use of the BP ligand results in improved yields of linear pentanal because SILP systems with this ligand are active for both isomerization and hydroformylation. (c) 2014 American Institute of Chemical Engineers AIChE J, 61: 893-897, 2015
Keywords: catalysis; supported ionic liquids; dehydrogenation; hydroformylation; cascade reaction

Nematic suspension of a microporous layered silicate obtained by forceless spontaneous delamination via repulsive osmotic swelling for casting high-barrier all-inorganic films - Loch, Patrick; Schuchardt, Dominik; Algara-Siller, Gerardo; Markus, Paul; Ottermann, Katharina; Rosenfeldt, Sabine; Lunkenbein, Thomas; Schwieger, Wilhelm; Papastavrou, Georg; Breu, Josef (Science Advances, 2022)
Exploiting the full potential of layered materials for a broad range of applications requires delamination into functional nanosheets. Delamination via repulsive osmotic swelling is driven by thermodynamics and represents the most gentle route to obtain nematic liquid crystals consisting exclusively of single-layer nanosheets. This mechanism was, however, long limited to very few compounds, including 2:1-type clay minerals, layered titanates, or niobates. Despite the great potential of zeolites and their microporous layered counterparts, nanosheet production is challenging and troublesome, and published procedures implied the use of some shearing forces. Here, we present a scalable, eco-friendly, and utter delamination of the microporous layered silicate ilerite into single-layer nanosheets that extends repulsive delamination to the class of layered zeolites. As the sheet diameter is preserved, nematic suspensions with cofacial nanosheets of ≈9000 aspect ratio are obtained that can be cast into oriented films, e.g., for barrier applications.
CRIS-Team Scopus Importer:2022-06-03

New hybrid materials consisting of solid or liquid substrate with tin ultra pure ionic liquid film. - Cremer, Till; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (2009)
This invention claims new hybrid materials consisting of a solid or liq. substrate and an extremely thin film of an ultra-pure ionic liq., where the film thickness of the applied ionic liq. amts. to less than ten nanometers, preferably less then two nanometers. This extremely thin, ultra-pure film lends to the new hybrid materials with surprising and tech. interesting surface properties, different to substrate it self, different to substrate with a thicker film and different to substrate with a less pure film of the same ionic liq. This extremely thin ultra-pure film on solid or liq. substrate changes elec. cond., catalytic activity, optical, tribol., mech. properties, sensory and permeation/sepn. capability or stability against oxidn. by air of coated substrate. The ultra pure ionic liq. has a formula [A]n+[Y]n-, where A is quaternary ammonium, phosphonium, imidazolium, pyridinium, pyrazolium and triazolium cation, n= 1 or 2 and Y is an anion such as tetrafluoroborate, hexafluorophosphate, dicyanamide, tricyanomethid, tetracyano borate, halogenide or others which is applied at temp. of 30-400° under high vacuum over liq. or solid substrate kept at -200-350°. [on SciFinder(R)]
Keywords: substrate pure ionic liq nanoscale surface modification hybrid material

New ionic liquids based on anion functionalization. - Wasserscheid, Peter; Gerhard, Dirk; Himmler, Simone; Hörmann, S.; Schulz, Peter (Acs Symposium Series, 2007)
Various alkylsulfate imidazolium ionic liqs. were synthesized by quaternization of N-substituted imidazoles with di-Et sulfate followed by transesterification with primary alcs. The kinetics of the esterification step, concepts for scale-up and phys. properties of the products, such as viscosity and d., are presented. Two vinylsulfonate ionic liqs. were prepd. by ion exchange of imidazolium halides with sodium vinylsulfonate and their phys. properties (thermal stability, viscosity) and double bond transformations (hydrogenation and hydroformylation) were studied. [on SciFinder(R)]
Keywords: imidazolium ionic liq alkylsulfate vinylsulfonate prepn density viscosity stability

New route to biaryl phosphanes with axial chirality as ligands for enantioselective hydrogenations. - Drießen-Hölscher, Birgit; Kralik, Joachim; Agel, Friederike; Steffens, Christian; Hu, Chunhua (dvanced Synthesis & Catalysis, 2004)
The authors found a modular route for the synthesis of Cl-MeOBIPHEP ligands (I; R = Ph, p-FC6H4, xylyl, 2-furyl, 2,5-(MeO)2C6H3) via the corresponding biphenol that allows the authors to introduce several substituents without the necessity to sep. the enantiomers of each deriv. These new diphosphines were used to prepn. Ru(I)(O2CCF3)2 for use in the Ru-catalyzed enantioselective hydrogenation of di-Me itaconate with ee values up to 97%. [on SciFinder(R)]
Keywords: phosphinobiphenyl prepn complexation ruthenium; ruthenium phosphinobiphenyl complex prepn hydrogenation catalyst itaconate; crystal structure phosphinobiphenyl

NH3-SCR of NO with novel active, supported vanadium-containing Keggin-type heteropolyacid catalysts - Bukowski, Anna; Schill, Leonhard; Nielsen, David; Mossin, Susanne; Riisager, Anders; Albert, Jakob (Reaction Chemistry & Engineering, 2020)
Supported vanadium-substituted Keggin polyoxometalates (POMs) were applied as catalysts for the selective catalytic reduction of NO using NH3 as reductant (NH3-SCR). Interestingly, HPA-3 (H6PV3Mo9O40) was found to be the most active catalytic species, and TiO2 (anatase) the most promoting support for the SCR reaction in the temperature range 200-350 C. Moreover, 10 wt.% HPA 3 loading was found to be optimum resulting in nearly complete NO conversion at 350 °C. Characterization by several techniques, including N2-physisorption, NH3-TPD, FTIR, XPS and TEM showed distinctive structural HPA-3 support interactions explaining the beneficial interplay between both parts for the SCR reaction. Furthermore, different catalytically active surface species were identified at various reaction temperatures and SCR conditions by in-situ EPR spectroscopy. The study introduces a novel type of heterogeneous supported vanadium-based NH3-SCR catalysts comprising redox-active POMs, which so far mainly have been applied for homogeneously catalyzed reaction
Keywords: : DeNOx; selective catalytic reduction; polyoxometalates; EPR spectroscopy

Nickel catalyzed dimerization of propene in chloroaluminate ionic liquids: Detailed kinetic studies in a batch reactor - Eichmann, Marcus; Keim, Wilhelm; Haumann, Marco; Melcher, Berthold Ulrich; Wasserscheid, Peter (Journal of Molecular Catalysis A-Chemical, 2009)
The dimerization of propene in the presence of homogeneous nickel catalysts in acidic chloroaluminate ionic liquids has been investigated. The solubility of both substrate and products has been carefully determined in order to interpret kinetic findings. Detailed kinetic studies have indicated strong mass transport limitation of the overall reaction rate. The diffusion coefficient of propene in the ionic liquid has been determined from gas solubility measurements. This established method allowed the calculation of the Hatta number to be 4.9, indicating the severe mass transport limitation. For such fast biphasic reactions a loop reactor design is suggested.

NiMo and NiW Nanostructured Catalysts of Thiophene Oxidation, Obtained via Laser Electrodispersion - Bryzhin, A. A.; Tarkhanova, I. G.; Maslakov, K. I.; Nikolaev, S. A.; Gurevich, S. A.; Kozhevin, V. M.; Yavsin, D. A.; Gantman, Mikhail; Rostovshchikova, T. N. (Russian Journal of Physical Chemistry A, 2019)
New bimetallic catalysts based on Ni and Mo or W oxide nanoparticles deposited on alumina are obtained via the laser electrodispersion of tightly compacted binary mixtures of NiMo and NiW powders. SEM, TEM, and XPS show that both components of each pair are uniformly distributed over a carrier's surface in the form of nanoparticles of 4-7 nm in size. Metals on the catalyst's surface are predominantly in an oxidized state. The catalytic activity of NiMo/Al2O3 and NiW/Al2O3 pairs is compared using examples of the oxidation of thiophene and dibenzothiophene with hydrogen peroxide. High reagent conversion on such catalysts with ultra-low metal contents (<0.01 wt %) is maintained by continually repeating the process. Introducing a zwitterionic liquid with sulfo group into the reaction mixture results in additional improvement of catalyst efficiency.
CRIS-Team WoS Importer:2019-10-11

NMR Studies of the Dehydroxylation and Rehydroxylation (RHX) of Clays with Respect to the RHX Dating of Ceramic Materials - Avramovska, Marija; Freude, Dieter; Schwieger, Wilhelm; Song, Chen; Kärger, Jörg; Haase, Jürgen (Journal of Physical Chemistry C, 2021)
Monitoring the recombination of OH groups in a ceramic sample after firing, also known as rehydroxylation (RHX), was proposed as a way to determine the time elapsed since the firing of a ceramic material, thus providing archeologists with the only up-to-date known method for determining the age of fired ceramics directly. A nuclear magnetic resonance (NMR) study was performed in order to understand the RHX dating of ceramic materials in archeology. We perform MAS NMR investigations on four pure clay minerals and one mixed ceramic. We point out a large discrepancy between NMR measurements and TG in the obtained total concentration of hydrogen. We are able to differentiate and investigate the dynamics (by monitoring H/D exchange) of the three types of hydrogen species present in the samples: T0 (physisorbed), T1 (interlayer), and T2 (chemisorbed) water. We use H/D tracer exchange to monitor the mobility of hydrogen species and obtain the exchange time constants of T2 water, which is in the order of a few to 100 days. Interestingly, we find that H/D exchange time constants do not significantly depend on temperature. The slow exchange times of T2 water, in the order of days, can be compared with the diffusion time scales of T1 water (in the order of 100 s) obtained with tracer desorption and with T0 water (order of 100 ms) obtained by PFG MAS NMR measurements.
CRIS-Team Scopus Importer:2021-12-10

NMR Studies of the Rehydroxylation of Ceramic Materials with Respect to Rehydroxylation Dating - Avramovska, Marija; Freude, Dieter; Schwieger, Wilhelm; Fey, Tobias; Kärger, Jörg; Haase, Jürgen (Journal of Physical Chemistry C, 2023)
Monitoring the rehydroxylation (RHX) in ceramic samples after firing was introduced in archeology as the RHX dating in order to determine the time elapsed since the firing of a ceramic artifact. But the mechanisms of hydroxyl transport during the RHX mechanism are still largely unclear. The present study investigates hydroxyl groups of three at 800 °C fired ceramics upon hydrothermal treatment of the samples. The rehydroxylation of the ceramics between 600 and 200 °C results in an increase of less than a factor of 1.5 for most samples, whereas early studies showed that the decrease of the hydroxyl concentration is a factor of about 10 for the basic powder material in the dehydroxylation range 200-800 °C. A sieve fraction of 100-140 μm of ceramic materials crushed in a mortar was used for the magic-angle spinning (MAS) NMR experiments because larger particles and of course the fired cylinders (10 mm diameter) of the ceramic materials do not rotate at higher frequencies. The less accurate static NMR experiments (without MAS) on the ceramic pieces with 1 cm diameter did not show significant differences because the ceramic is porous. H/D tracer exchange experiments show that H/D exchange time constants do not significantly depend on temperature. Therefore, the hydroxyl transport mechanism cannot be described by an activation energy like for normal diffusion. We explain the transport of hydroxylation by a quantum Brownian diffusion of hydrogen atoms between hydroxyl groups and (opening of) constrained bonds in the near neighborhood.
CRIS-Team Scopus Importer:2023-11-10

Noble Metals on Anodic TiO2 Nanotube Mouths: Thermal Dewetting of Minimal Pt Co-Catalyst Loading Leads to Significantly Enhanced Photocatalytic H2 Generation - Nguyen, Nhat Truong; Altomare, Marco; Yoo, Jeong Eun; Taccardi, Nicola; Schmuki, Patrik (Advanced Energy Materials, 2016)
A technique is introduced to strongly reduce Pt use for photocatalytic hydrogen generation from TiO2 nanotubes. By site selectively depositing thin layers of Pt only at the ``mouth'' of the nanotubes, and with a subsequent thermal dewetting step, an outstanding photocatalytic improvement with minimal amounts of cocatalyst is achieved.
EAM Import::2019-03-08

Novel Inverse Supported Ionic Liquid Absorbents for Acidic Gas Removal from Flue Gas - Karousos, D. S.; Kouvelos, E.; Sapalidis, A.; Pohako-Esko, Kaija; Bahlmann, Matthias; Schulz, Peter; Wasserscheid, Peter; Siranidi, E.; Vangeli, O.; Falaras, P.; Kanellopoulos, N.; Romanos, G. Em. (Industrial & Engineering Chemistry Research, 2016)
This work reports on the astonishing high capacity of inverse supported ionic liquid absorbents, hereinafter denoted as "inverse SILPs" to remove acidic gases (SO2 and CO2) from flue gas streams. These nonconventional SILPs are easily prepared in the form of flowing powder via a phase inversion technique and consist of tiny ionic liquid (IL) droplets enclosed into an ultrathin, porous solid sleeve of pyrogenic silica nanoparticles. The CO2/N-2 and SO2/CO2 separation performance and regeneration efficiency of inverse SILPs developed from six different ILs and two IL/chitosan ionogels was examined via gravimetric CO2, N-2 absorption isotherms and via SO2, CO2, O-2 breakthrough curves from gas mixtures in fixed beds. The involved ILs varied from chemisorbing ones, composed of alkyl- or alkanol-ammonium cations and amino acid anions, to physisorbing ones including ether functionalized anions and 1-alky1-3-methylimidazolium cations. It is noteworthy that the best performing inverse SILP consisted of a very common IL, the 1-butyl-3-methylimidazolium chloride [BMIM] [Cl], the absorption capacity of which was slightly enhanced by dissolving 5 wt % of chitosan to form the respective ionogel. The material's performance was stable in repeated cycles of absorption and regeneration at 60 degrees C under helium flow, exhibiting SO2/CO2 selectivity of above 300, while the SO2 and CO2 absorption capacity was 1.6 and 0.6 mmol/g respectively at 25 degrees C, in a gas stream of 1 bar composed of 0.13 vol % SO2, 13 vol % CO2, 11.5 vol % O-2 and N-2 (balance).

Novel nanographene/porphyrin hybrids-preparation, characterization, and application in solar energy conversion schemes - Kießling, Daniel; Costa, Ruben Dario; Katsukis, Georgios; Malig, Jenny; Lodermeyer, Fabian; Feihl, Sebastian; Roth, Alexandra Marina; Wibmer, Leonie; Kehrer, Matthias; Volland, Michel; Wagner, Pawel; Wallace, Gordon G.; et al. (Chemical Science, 2013)
Four novel nanographene/porphyrin hybrids were prepared, characterized, and probed in solar energy conversion schemes. Exfoliation of graphite by means of immobilizing four different porphyrins onto the basal plane of graphene is accompanied by distinct electronic interactions in both the ground and the excited states. In the ground state, a strong loss in oscillator strength goes hand-in-hand with a notable broadening of the porphyrin transitions and, as such, attests to the shift of electron density from the electron donating porphyrins to nanographene. In the excited state, a nearly quantitative quenching of the porphyrin fluorescence is indicative of full charge transfer. The latter is corroborated by femtosecond transient absorption measurements, which reveal the generation of the one-electron oxidized radical cation of the porphyrins with absorption maxima at 490 and 625 nm in the visible region and conduction band electrons in nanographene with features at 890 and 1025 nm in the near infrared region. We have demonstrated the applicability of the new nanographene/porphyrin hybrids in, for example, solar cells. In this regard, the presence of flakes is crucial in terms of influencing the injection processes, preventing aggregation, and reducing recombination losses, which are commonly encountered in porphyrin-based DSSCs. © 2013 The Royal Society of Chemistry.

Novel open cell aluminum foams and their use as reactive support for zeolite crystallization - Barg, S.; Soltmann, C.; Schwab, Andreas; Koch, D.; Schwieger, Wilhelm; Grathwohl, G. (Journal of Porous Materials, 2011)
Open cell aluminum (Al) foams are developed in this work by a novel direct foaming process in which a low concentrated alkane phase is emulsified in a stabilized Al powder suspension. In this versatile technique, the porosity parameters are adjusted during foaming of the emulsified suspensions and the final stability is achieved by a thermal treatment above the melting temperature of Al. The thin oxide layers surrounding the Al particles and the ascertained percolation of the molten metal are essential in this stage. The efficiency of the processing route is demonstrated with the essential requisites for successful foaming and the final structural stability. Furthermore, open cell Al-foams/zeolite composites exhibiting a hierarchical porous structure (nano-and macroscale) are produced by hydrothermal synthesis of Faujasite-like zeolite on the surface of the developed AI-foams. Due to the advantageous properties of zeolite X in N(2) adsorption, the application of the composites for separation of N(2) from air is specially envisaged.
Keywords: Al foams; Highly porous materials; Zeolite

Nucleation as a rate-determining step in catalytic gas generation reactions from liquid phase systems - Solymosi, Thomas; Geißelbrecht, Michael; Mayer, Sophie; Auer, Michael; Leicht, Peter; Terlinden, Markus; Malgaretti, Paolo; Bösmann, Andreas; Preuster, Patrick; Harting, Jens; Thommes, Matthias; Vogel, Nicolas; et al. (Science Advances, 2022)
The observable reaction rate of heterogeneously catalyzed reactions is known to be limited either by the intrinsic kinetics of the catalytic transformation or by the rate of pore and/or film diffusion. Here, we show that in gas generation reactions from liquid reactants, the nucleation of gas bubbles in the catalyst pore structure represents an additional important rate-limiting step. This is highlighted for the example of catalytic hydrogen release from the liquid organic hydrogen carrier compound perhydro-dibenzyltoluene. A nucleation-inhibited catalytic system produces only dissolved hydrogen with fast saturation of the fluid phase around the active site, while bubble formation enhances mass transfer by more than a factor of 50 in an oscillating reaction regime. Nucleation can be efficiently triggered not only by temperature changes and catalyst surface modification but also by a mechanical stimulus. Our work sheds new light on performance-limiting factors in reactions that are of highest relevance for the future green hydrogen economy.

Numerical simulation of heat transfer in the near-wall region of tubular reactors packed with metal open-cell foams - Bianchi, Enrico; Groppi, Gianpiero; Schwieger, Wilhelm; Tronconi, Enrico; Freund, Hannsjörg (Chemical Engineering Journal, 2015)
A numerical investigation of the thermal transport processes in the near-wall region of a reactor packed with metal open-cell foams is presented in view of the development of externally-cooled tubular reactors packed with catalytically active foams. Two different aluminium open-cell foams were scanned by X-ray micro-computed tomography in order to generate the 3D models used in this study. The conjugated solid-fluid heat transfer problem is solved by finite volume analysis (FVA) for different flow rates and fluid properties (Peclet number range from 1 to 105). Predictive correlations for the wall heat transfer coefficient are derived according to different thermal coupling scenarios between the open-cell foam bed and the reactor wall. Such kind of systematic study and the proposed correlations that account for the gap size represent a novelty in the field of published literature on open-cell foams. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Metal open-cell foams; Sponges; Conjugated heat transfer; Wall heat transfer coefficient; Catalytic structured reactors; CFD

Numerical simulations of single phase reacting flows in randomly packed fixed-bed reactors and experimental validation - Durst, Franz; Zeiser, Thomas; Freund, Hannsjörg; et al. (Chemical Engineering Science, 2003)
Randomly packed fixed-bed reactors are widely used in the chemical process industries. Their design is usually based on pseudo-homogeneous model equations with averaged semi-empirical parameters. However, this design concept fails for low tube-to-particle diameter ratios (=aspect greater than ratios) where local phenomena dominate. The complete three-dimensional (3D) structure of the packing has therefore to be considered in order to resolve the local inhomogeneities. New numerical methods and the increase of computational power allow us to simulate in detail single phase reacting flows in such reactors, exclusively based on material properties and the 3D description of the geometry, thus without the use of semi-empirical data. The successive simulation steps (packing generation, fluid flow and species calculation) and their validation with experimental data are described in this paper. In order to synthetically generate realistic random packings of spherical particles, we apply a Monte-Carlo method. The subsequent numerical simulation of the 3D flow field and coupled mass transport of reacting species is done by means of lattice Boltzmann methods. The simulation results reveal that not only the local behaviour but also integral quantities like the pressure drop depend remarkably on the local structural properties of the packings, a feature which is neglected when using correlations with averaged values. © 2003 Elsevier Science Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.stmmec.numeri
Keywords: CFD simulation; Lattice Boltzmann methods; Monte-Carlo packing generation; Packed bed; Porosity profile; Voidage

One-Step Synthesis of MIL-53(Al)/Boehmite Composites - Schwegler, Johannes; Fischer, Marcus; Paula, Carolin; Schulz, Peter; Hartmann, Martin (Chemie Ingenieur Technik, 2017)
[EMIM][Hbdc]and [EMIM](2)[bdc] were synthesized and successfully used in a one-step synthesis procedure of MIL-53(Al)/boehmite composites with unusual properties. The breathing effect typically observed for MIL-53(Al) is not found and scanning electron microscopy confirms the presence of MIL-53 nanoparticles in a boehmite matrix. The completely different characteristics of this MIL-53 samples in comparison to hydrothermally synthesized MIL-53(Al) clearly demonstrate the tremendous influence of variations of the reagents used for the syntheses of metal-organic framework materials.
Keywords: Ionic liquids; Metal-organic framework; NMR spectroscopy

One-step synthesizable Lindqvist-isopolyoxometalates as promising new catalysts for selective conversion of glucose as a model substrate for lignocellulosic biomass to formic acid - Albert, Jakob; Streb, Carsten; Mehler, Julian; Tucher, Johannes; Kastner, Katharina (ChemistrySelect, 2016)

Online Monitoring of Microscale Liquid-Phase Catalysis Using in-Fiber Raman Spectroscopy - Schorn, Florian; Aubermann, Manfred; Zeltner, Richard; Haumann, Marco; Joly, Nicolas (ACS Catalysis, 2021)
We report on the use of hollow-core photonic crystal fibers to monitor the evolution of chemical reactions. The combination of tight confinement and long interaction length allows single-pass spectroscopic measurements using less than a microliter volume of chemicals with good accuracy. As a proof of principle, we used here nonlinear Raman spectroscopy for a reaction screening of the acidic catalyzed esterification of methanol and acetic acid.
CRIS-Team Scopus Importer:2021-07-02
Keywords: esterification; hollow-core photonic crystal fibers; in situ spectroscopy; microreactor; Raman

On the optimal design of load flexible fixed bed reactors: Integration of dynamics into the design problem - Fischer, Konrad; Freund, Hannsjörg (Chemical Engineering Journal, 2020)
The design of dynamically operated fixed bed reactors is a challenging task, especially for highly exothermic reactions. Fluctuations of process conditions such as inlet flow rate and composition can cause losses in product quality, wrong-way behavior or even a thermal runaway which damages reactor and catalyst. We present a methodology for the model-based design of dynamically operated, load flexible fixed bed reactors. Critical reactor dynamics are already considered during the reactor design and are integrated into the optimization problem. Instead of a steady state problem, the reactor is optimized for a worst case dynamic scenario. The optimization approach yields a design which allows for safe transitions from any flow rate to another within a pre-defined load range. The approach is introduced using the methanation of carbon dioxide as an important case study of high relevance for both research and society within the context of chemical energy storage of fluctuating renewable energy. A feasibility test demonstrates the safe reactor operation for a time horizon which includes a series of step-changes of the inlet flow rate as an approximation of a fluctuating hydrogen supply.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Carbon dioxide methanation; Dynamic operation; Model-based reactor optimization; Thermal runaway; Wall-cooled tubular reactor; Wrong-way behavior

Operando DRIFTS and DFT Study of Propane Dehydrogenation over Solid- and Liquid-Supported GaxPty Catalysts - Bauer, Tanja; Maisel, Sven; Blaumeiser, Dominik; Vecchietti, Julia; Taccardi, Nicola; Wasserscheid, Peter; Bonivardi, Adrian; Görling, Andreas; Libuda, Jörg (ACS Catalysis, 2019)
Supported catalytically active liquid metal solutions (SCALMS) represent a class of catalytic materials that have only recently been developed, but have already proven to be highly active, e.g., for dehydrogenation reactions. Previous studies attributed the catalytic activity to isolated noble metal atoms at the surface of a liquid and inert Ga matrix. In this study, we apply diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) with CO as a probe molecule to Ga/Al2O3, Pt/Al2O3, and Ga37Pt/Al2O3 catalysts, to investigate in detail the nature of the active Pt species. Comparison of CO adsorption on Pt/Al2O3 and Ga37Pt/Al2O3 shows that isolated Pt atoms are, indeed, present at the surface of the liquid SCALMS. Combining DRIFTS with online gas chromatography (GC), we investigated the Ga/Al2O3, Pt/Al2O3, and Ga37Pt/Al2O3 systems under operando conditions during propane dehydrogenation in CO/propane and in Ar/propane. We find that the Pt/Al2O3 sample is rapidly poisoned by CO adsorption and coke, whereas propane dehydrogenation over Ga37Pt/Al2O3 SCALMS leads to higher conversion with no indication of poisoning effects. We show under operando conditions that isolated Pt atoms are present at the surface of SCALMS during the dehydrogenation reaction. IR spectra and density-functional theory (DFT) suggest that both the Ga matrix and the presence of coadsorbates alter the electronic properties of the surface Pt species.
CRIS-Team WoS Importer:2019-04-23

Operational experience with a liquid organic hydrogen carrier (LOHC) system for bidirectional storage of electrical energy over 725 h - Geiling, Johannes; Wagner, Lisa; Auer, Franziska; Ortner, Florian; Nuß, Andreas; Seyfried, Roman; Stammberger, Florian; Steinberger, Michael; Bösmann, Andreas; Öchsner, Richard; Wasserscheid, Peter; Graichen, Knut; et al. (Journal of Energy Storage, 2023)
Hydrogen storage in liquid organic hydrogen carriers (LOHC) enables the utilization of renewable energy in different sectors. In this paper, we describe the operational experience with one single LOHC system for bidirectional electrical energy storage at the kW scale. The system includes a reactor for the hydrogenation and dehydrogenation of LOHC, as well as a fuel cell and an electrolyzer based on polymer electrolyte membrane (PEM) technology. The LOHC used is the substance pair dibenzyltoluene/perhydro-dibenzyltoluene. For dehydrogenation, the upflow operation with common discharge of liquid and gaseous product was found to be the preferred mode of operation. For hydrogenation, it was shown that stable operation is possible also with fluctuating hydrogen production from the electrolyzer. After operating the reactor for 725 h in the hot state, i.e., at temperatures above 150 ∘C, samples of the catalyst and LOHC were taken and analyzed. These showed no signs of serious degradation.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Catalyst; Hydrogen storage; Liquid organic hydrogen carrier (LOHC); Operation experience; PEM electrolyzer; PEM fuel cell

Operational stability of a LOHC-based hot pressure swing reactor for hydrogen storage - Jorschick, Holger; Dürr, Stefan; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (Energy Technology, 2018)
Apart from hydrogen logistics, stationary hydrogen storage applications using Liquid Organic Hydrogen Carrier (LOHC) systems are also of significant interest. In contrast to the traditional use of separate hydrogenation and dehydrogenation reactors, our so-called oneReactor technology offers the advantages of a simpler storage unit layout and high dynamics in switching from hydrogen charging to hydrogen release. Here we report repeated hydrogenation and dehydrogenation cycles with one batch of liquid carrier for LOHC stability tests under defined hydrogenation and dehydrogenation conditions. We demonstrate up to 13 hydrogenation/dehydrogenation cycles over a total of 405 h of operation including two long dehydrogenation sequences over weekends. In general, longer dehydrogenation runs, i.e. exposure of the LOHC to catalyst at low hydrogen pressure and elevated temperatures (> 280 °C), showed negative effects on both activity of the subsequent cycles and by-product formation. Concerning catalyst activity and hydrogen productivity, stable productivity was achieved (within 3 to 9 cycles) under all conditions tested. Longer hydrogenation runs led to significantly higher stability of the reaction system.
Keywords: hydrogen storage; LOHC systems; hydrogenation; dehydrogenation; platinum; stability

Optically Monitored Catalytic Photonic Crystal Fibre Microreactor - Cubillas, Ana Maria; Schmidt, Matthias; Euser, Tijmen G.; Etzold, Bastian; Taccardi, Nicola; Unterkofler, Sarah; Wasserscheid, Peter; Russell, Philip St. John (European Conference on Lasers and Electro-Optics, 2013)
Here we show that by depositing metallic catalyst nanoparticles in the core of the fibre, we can turn the HC-PCF into a catalytically active microreactor. As a proof-of-principle experiment, we investigated the well-known catalytic hydrogenation of azobenzene in a kagomé HC-PCF, whose core wall has been decorated with rhodium (Rh) catalyst nanoparticles. The reaction was monitored online by in-fibre absorption spectroscopy.

Optimal reaction concept and plant wide optimization of the ethylene oxide process - Peschel, Andreas; Jörke, Andreas; Sundmacher, Kai; Freund, Hannsjörg (22nd International Symposium on Chemical Reaction Engineering, 2012)
<h2 class="secHeading" id="author1" style="border: 0px; font-size: 18px; font-weight: 100; margin: 20px 0px 6px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; color: rgb(92, 92, 92); line-height: inherit; clear: both;"> Abstract <p id="sp010" style="border: 0px; font-size: 16px; margin: 0px 0px 9px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; word-spacing: -0.15ex; color: rgb(46, 46, 46); line-height: 23.68px;"> In this paper, a new method for the identification of the best reaction concept from an overall process point of view is proposed. Using this method the optimal reaction route is determined independent of existing apparatuses and the recycle affecting the reactor is fully considered. The reaction concept and the design parameters of the process are simultaneously optimized. For this purpose, a detailed model of the reaction system including reaction kinetics, thermodynamic relationships, and intrinsic boundaries such as explosion limits as well as a complete model of the downstream process is set up. The potential of different reaction concepts including innovative process intensification alternatives can easily be determined by comparison with an optimized reference case. <p id="sp015" style="border: 0px; font-size: 16px; margin: 0px 0px 9px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; word-spacing: -0.15ex; color: rgb(46, 46, 46); line-height: 23.68px;"> The example considered in this paper is the oxygen based ethylene oxide process, which is one of the most important chemical bulk processes. Sophisticated cooling in combination with distributed oxygen dosing along the reactor length is identified as best technical reaction concept with a potential of reducing the operating costs of an average sized plant by 1.35 Mio /a compared to an optimized reference case. In addition, the utility consumption is reduced, especially the consumption of electricity is decreased by 46.3%, and the overall CO2 emissions are cut by 8%. <p id="sp020" style="border: 0px; font-size: 16px; margin: 0px 0px 9px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; word-spacing: -0.15ex; color: rgb(46, 46, 46); line-height: 23.68px;"> In conclusion, the proposed method enables the predictive determination of the best reaction concept from an overall process point of view taking the full interconnections between the reaction concept and the process into account and considering highly innovative process intensification options. Thereby, this method provides a key stone for the development of more economical and more sustainable chemical reactors and processes of the future.
Keywords: Chemical reactors; Novel reactor technologies; Process intensification; Elementary process functions; Optimization; Design; Ethylene oxide

Optimal reactor design and operation taking catalyst deactivation into account - Xie, Mingquan; Freund, Hannsjörg (Chemical Engineering Science, 2018)
In this work, a new approach for taking catalyst deactivation into account in the early stage of reactor design is derived and exemplified by the ethylene oxide synthesis as an industrial relevant case study. In this process, the catalyst lifetime is much larger than the residence time of reactants. The operating conditions over the whole catalyst lifetime and the reactor configuration are simultaneously optimized. The objective of the mathematical optimization problem is the overall reactor performance such as the average selectivity over the catalyst lifetime. An optimal detailed design could be derived with advanced temperature control, giving rise to a higher average selectivity and potentially longer catalyst lifetime compared to the reference case. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Reactor design; Catalyst deactivation; Optimization; Process intensification; Modeling

Optimal Reactor Design for the Hydroformylation of Long Chain Alkenes in Biphasic Liquid Systems - Peschel, Andreas; Hentschel, Benjamin; Freund, Hannsjörg; Sundmacher, Kai (Computer Aided Chemical Engineering, 2011)

Optimization of the direct synthesis of dimethyl ether from CO2 rich synthesis gas: closing the loop between experimental investigations and model-based reactor design - Delgado Otalvaro, Nirvana; Kaiser, Markus; Delgado, Karla Herrera; Wild, Stefan; Sauer, Joerg; Freund, Hannsjörg (Reaction Chemistry & Engineering, 2020)
Reaction kinetic modeling, model-based optimization and experimental validation are performed for the direct synthesis of dimethyl ether from CO2 rich synthesis gas. Among these disciplines, experimental methods and models are aligned in a stringent way of action, i.e., the same setup and models are applied throughout the whole contribution. First, a lumped reaction kinetic model from the literature is modified and parametrized to fit a vast array of 240 data points measured in a laboratory fixed bed reactor. The data were acquired using a mechanical mixture of the commercial catalysts CuO/ZnO/Al2O3 and gamma-Al2O3. For this setup, a predictive model is derived and applied within dynamic model-based optimization. Here, the single-pass COx conversion serves as objective function while the operating conditions and composition of the mixed catalyst bed are the optimization variables. Finally, the optimization results obtained numerically are validated experimentally verifying the identified performance enhancement qualitatively. The remaining quantitative deviations yield valuable insights into model and methodological weaknesses or inaccuracies, closing the loop between kinetic investigations, model-based optimization and experimental validation.
CRIS-Team WoS Importer:2020-05-29

Optimization under uncertainty in chemical engineering: Comparative evaluation of unscented transformation methods and cubature rules - Maußner, Johannes; Freund, Hannsjörg (Chemical Engineering Science, 2018)
Keywords: Reactor optimization; Unscented transformation; Optimization under uncertainty; Reaction engineering; Cubature rule

Optimized Polymer Electrolyte Membrane Fuel Cell Electrode Using TiO2 Nanotube Arrays with Well-Defined Spacing - Özkan, Selda; Valle, Francesco; Mazare, Anca Valentina; Hwang, Imgon; Taccardi, Nicola; Zazpe, Raul; Macak, Jan M.; Cerri, Isotta; Schmuki, Patrik (ACS Applied Nano Materials, 2020)
TiO2-based catalyst supports in polymer electrolyte membrane fuel cells (PEMFCs) are widely investigated and provide an alternative to corrosion-susceptible carbon-based catalyst supports. For PEMFCs, designing a catalyst support material with an optimal geometry is of high importance to provide high catalyst dispersion, long-term operation, and efficient fuel cell performance. In this work, we report on the use of spaced (SP) TiO2 nanotubes (NTs) as catalyst support for the cathode electrode of PEMFCs. We construct a vertically aligned Pt-TiO2 NT catalyst layer on the Nafion membrane by a threestep process: (i) growth of self-organized TiO2 nanotubes with defined intertube spacing and detachment from the Ti substrate, (ii) Pt catalyst decoration on tube walls by atomic layer deposition (ALD) or photodeposition (PD), and (iii) decal transfer of the Pt-TiO2 catalyst layer onto Nafion to fabricate a membraneelectrode assembly (MEA) by hot pressing. Such an MEA configuration based on vertically aligned high aspect ratio spaced TiO2 nanotubes with Pt catalyst decoration delivers a significantly higher fuel cell performance, compared with close-packed (CP) TiO2 nanotubes. The key for this excellent performance is that TiO2 NTs with a regular interspacing on the Nafion polymer membrane enable highly dispersed Pt catalyst decoration and provide strongly enhanced mass transport in the interspaces.
CRIS-Team WoS Importer:2020-06-19

Ordering and phase transitions in ionic liquid-crystalline films - Sobota, Marek; Wang, Xinjiao; Fekete, Melinda; Happel, Markus; Meyer, Karsten; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (ChemPhysChem, 2010)
Watching phase transitions: Ordering processes and phase transitions in thin films of the liquid-crystalline ionic liquid 1,3-didodecylimidazolium tetrafluoroborate [CCIM][BF] on Pt(111) (see picture) are studied by means of temperature-dependent IR reflection absorption spectroscopy. The method allows in situ monitoring of the structural properties of liquid-crystalline supported ionic liquid phase (SILP) catalysts under reaction conditions. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Organic-free synthesis of layer-like FAU-type zeolites - Inayat, Alexandra; Schneider, Christopher; Schwieger, Wilhelm (Chemical Communications, 2015)
The formation of layer-like FAU-type zeolites was facilitated in the absence of any organic template. Instead, the addition of simple inorganic salts turned out to be an effective and easy to handle alternative to organic additives to induce morphological and even structural changes during zeolite crystallisation.

Organic reactions in ionic liquids studied by in situ XPS - Niedermaier, Inga; Kolbeck, Claudia; Taccardi, Nicola; Schulz, Peter; Li, Jing; Drewello, Thomas; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2012)
We demonstrate the application of in situ X-ray photoelectron spectroscopy (XPS) to monitor organic, liquid-phase reactions. By covalently attaching ionic head groups to the reacting organic molecules, their volatility can be reduced such that they withstand ultra high vacuum conditions. The applied method, which is new for the investigation of organic reactions, allows for following the fate of all elements present in the reaction mixtureexcept for hydrogenin a quantitative and oxidation-state-sensitive manner in one experiment. This concept is demonstrated for the alkylation of a tertiary amine attached to an imidazolium or phosphonium moiety by the anion 4-chlorobutylsulfonate ([ClC H SO ] ). In the course of the reaction, the covalently bound chlorine is converted to chloride and the amine to ammonium as reflected by the distinct shifts in the N 1s and Cl 2p binding energies. © 2012 Wiley-VCH Verlag GmbH& Co. KGaA, Weinheim.

Ortsaufgelöste Simulation des externen Stofftransports in komplexen Katalysatorträgergeometrien - Heidig, Tobias; Zeiser, Thomas; Schwieger, Wilhelm; Freund, Hannsjörg (Chemie Ingenieur Technik, 2014)
The design of tailor-made innovative catalyst support structures enables improved reactor performance by freely tunable fluid flow and mass transport characteristics. Numerical geometry generation, fluid flow simulation and particle tracking for mass transport investigation allow for the required understanding of the structure-transport relationship. Particle tracking, as simulation of the movement of many tracer particles, is costly. This article presents simulation methods including numeric and algorithmic challenges. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: CFD; Particle-Tracking; Stofftransport; Strukturierte Reaktoren; CFD; Mass transport; Particle tracking; Structured reactors

Ortsaufgelöste Simulation von Transportprozessen in durchströmten Festbetten - Freund, Hannsjörg (Shaker-Verlag, 2008)

Oxidative Depolymerization of Lignin in Ionic Liquids - Hildebrandt-Stärk, Kerstin; Taccardi, Nicola; Bösmann, Andreas; Wasserscheid, Peter (Chemsuschem, 2010)
Beech lignin was oxidatively cleaved in ionic liquids to give phenols, unsaturated propylaromatics, and aromatic aldehydes. A multiparallel batch reactor system was used to screen different ionic liquids and metal catalysts. Mn(NO_3)_2 in 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [EMIM][CF_3SO_3] proved to be the most effective reaction system. A larger scale batch reaction with this system in a 300mL autoclave (11g lignin starting material) resulted in a maximum conversion of 66.3 % (24h at 100 °C, 84×105Pa air). By adjusting the reaction conditions and catalyst loading, the selectivity of the process could be shifted from syringaldehyde as the predominant product to 2,6-dimethoxy-1,4-benzoquinone (DMBQ). Surprisingly, the latter could be isolated as a pure substance in 11.5 wt % overall yield by a simple extraction/crystallization process.

Packed Periodic Open Cellular Structures – an Option for the Intensification of Non-Adiabatic Catalytic Processes - Ambrosetti, Matteo; Groppi, Gianpiero; Schwieger, Wilhelm; Tronconi, Enrico; Freund, Hannsjörg (Chemical Engineering and Processing, 2020)
Conductive structured catalysts offer significant potential for the intensification of gas-solid catalytic processes owing to their enhanced heat transfer properties. A major drawback is the limited catalyst inventory. Recently, packed foams were proposed to overcome the catalyst inventory limitation. The effectiveness of this concept was proven at lab-scale for intensified reactors filled with small catalyst particles. When adopting commercial foams and industrial-scale catalyst pellets, however, poor packing efficiencies are expected, limiting the potential of this concept. Similarly to foams, Periodic Open Cellular Structures (POCS) grant high heat transfer rates thanks to substantial heat conduction in their solid matrix. Additively manufactured POCS additionally offer great design flexibility. This allows for using a wider range of pellet sizes. In this work, particle packed POCS are introduced and packing efficiencies are systematically studied. Pressure drop in packed POCS is also analyzed and a suitable correlation is proposed. The heat transfer associated with this innovative reactor solution is investigated by performing non-reactive heat transfer experiments. Based on these experiments, a predictive heat transfer model is established and successfully validated with experimental data. The enormous potential of packed POCS for process intensification is illustrated by a case study of a Sabatier pilot reactor.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Additive manufacturing; Heat transfer; Pressure drop; Process intensification; Structured catalysts

Palladium-Mediated Ethylation of the Imidazolium Cation Monitored In Operando on a Solid Catalyst with Ionic Liquid Layer - Bauer, Tanja; Hager, Veit; Williams, Marc; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Szesni, Normen; Wasserscheid, Peter; Haumann, Marco; Libuda, Jörg (ChemCatChem, 2017)
The ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate [EMIM][EtOSO] was supported on Pd-AlO to yield a solid catalyst with ionic liquid layer (SCILL) material. During the hydrogenation of ethene, it was found that ethene was incorporated into the imidazolium moiety in a reaction catalyzed by the palladium surface. The formation of 1,2-diethyl-3-methylimidazolium ethylsulfate was confirmed ex situ by means of NMR spectroscopy. Moreover, the reaction itself could be monitored in situ by diffuse reflection infrared Fourier transformation (DRIFT) spectroscopy. A reaction mechanism involving surface carbene species was proposed on the basis of the analytical data.
Keywords: carbenes; heterogeneous catalysis; ionic liquids; palladium; reaction mechanisms

Pd-catalyzed telomerization of butadiene and methanol with direct catalyst recycling using a liquid-ionic liquid biphasic, continuous process - Völkl, Lisa; Geburtig, Denise; Kiermaier, Stephan; Wasserscheid, Peter; Haumann, Marco (Chemical Engineering and Processing, 2016)
The telomerization of 1,3-butadiene with methanol in the presence of a phosphine modified palladium catalyst was investigated in liquid-ionic liquid biphasic systems. Suitable ionic liquids were pre-selected from computational a priori COSMO-RS screening and tested in a batch autoclave. The Pd leaching could be suppressed significantly when the ligand TPPTS was used instead of the monosulfonated ligand TPPMS. The two most promising ionic liquids [EMMIM][NTf] and [BMMIM][NTf] were used to immobilize the Pd-TPPTS catalyst in a continuous loop reactor with integrated separation. While the monosulfonated TPPMS ligand failed to efficiently immobilize the catalyst in the ionic liquid, the TPPTS ligand resulted in very good catalyst immobilization and a constant conversion was maintained for more than 200 h time-on-stream.
Keywords: Butadiene telomerization; Catalyst immobilization; Ionic liquid; Loop reactor; Palladium catalyst; TPPTS

Pd nanoparticle formation in ionic liquid thin films monitored by in situ vibrational spectroscopy - Mehl, Sascha; Toghan, Arafat; Bauer, Tanja; Brummel, Olaf; Taccardi, Nicola; Wasserscheid, Peter; Libuda, Jörg (Langmuir, 2015)
Ionic liquids (ILs) are flexible reaction media and solvents for the synthesis of metal nanoparticles (NPs). Here, we describe a new preparation method for metallic NPs in nanometer thick films of ultraclean ILs in an ultrahigh vacuum (UHV) environment. CO-covered Pd NPs are formed by simultaneous and by sequential physical vapor deposition (PVD) of the IL and the metal in the presence of low partial pressures of CO. The film thickness and the particle size can be controlled by the deposition parameters. We followed the formation of the NPs and their thermal behavior by time-resolved IR reflection absorption spectroscopy (TP-IRAS) and by temperature-programmed IRAS (TR-IRAS). Codeposition of Pd and [CCIm][OTf] in CO at 100 K leads to the growth of homogeneous multilayer films of CO-covered Pd aggregates in an IL matrix. The size of these NPs can be controlled by the metal fraction in the co-deposit. With increasing metal fraction, the size of the Pd NPs also increases. At very low metal content, small Pd carbonyl-like species are formed, which bind CO in on-top geometry only. Upon annealing, the [OTf] anion coadsorbs at the NP surface and partially displaces CO. Co-adsorption of CO and IL is indicated by a strong red-shift of the CO stretching bands. While the weakly bound on-top CO is mainly replaced below the melting transition of the IL, coadsorbate shells with bridge-bonded CO and IL are stable well above the melting point. Larger three-dimensional Pd NPs can be prepared by PVD of Pd onto a solid [CCIm][OTf] film at 100 K. Upon annealing, on-top CO desorbs from these NPs below 200 K. Upon melting of the IL film, the CO-covered Pd NPs immerse into the IL and again form a stable coadsorbate shell that consists of bridge-bonded CO and the IL.

PERFORMANCE OF BENZYLTOLUENE AS PURE HYDROCARBON LIQUID ORGANIC HYDROGEN CARRIER (LOHC) IN STORAGE CYCLES - Rüde, Timo; Preuster, Patrick; Wolf, Moritz; Wasserscheid, Peter (Proceedings of WHEC 2022 - 23rd World Hydrogen Energy Conference: Bridging Continents by H2, 2022)
This study presents benzyltoluene/perhydro benzyltoluene (H0-BT/H12-BT) as favourable liquid organic hydrogen carrier (LOHC) system for potential technical applications. LOHCs can enable safe and efficient hydrogen logistics using the existent fuel infrastructure. Compared with the well-established LOHC systems toluene/methylcyclohexane and dibenzyltoluene/perhydro dibenzyltoluene (H0-DBT/H18-DBT), the H0-BT/H12-BT system combines a similarly high volumetric storage density and excellent robustness in hydrogenation/dehydrogenation cycles with low viscosity for easy handling in colder operation conditions. Herein, we report repeated hydrogenation and dehydrogenation cycles of technical grade LOHCs in semi continuous operation at 290 °C with a commercial platinum on alumina catalyst (Pt/Al2O3). Reaction rates for both, hydrogen uptake and release, are generally found to be higher for H0-BT/H12-BT when compared to the DBT-based LOHC system at identical reaction conditions. By-product formation is low during cycling of the H0-BT/H12-BT system and only small amounts of the dehydrocyclisation products, such as methylfluorene species, are formed that can themselves act as hydrogen carrier.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Benzyltoluene; by-product formation; Chemical Hydrogen Storage; reaction rate; repeated storage cycles

Performance of Continuous Hydrogen Production from Perhydro Benzyltoluene by Catalytic Distillation and Heat Integration Concepts with a Fuel Cell - Rüde, Timo; Lu, Yanye; Anschuetz, Leon; Blasius, Marco; Wolf, Moritz; Preuster, Patrick; Wasserscheid, Peter; Geißelbrecht, Michael (Energy Technology, 2023)
The benzyltoluene-based liquid organic hydrogen carrier (LOHC) system enables the safe transport and loss-free storage of hydrogen. At least 26% of the lower heating value of the released hydrogen, however, has to be invested in form of heat to release the stored hydrogen. The low operation temperatures of catalytic distillation (CD) can facilitate waste heat integration to reduce external heat demand. Herein, the continuous hydrogen release from perhydro benzyltoluene via CD is demonstrated. It is revealed in the experimental results that this mode of operation leads to a high hydrogen release rate and very efficient noble metal catalyst usage at exceptionally mild conditions. The hydrogen-based productivity of platinum of 0.35 g(H2) g(Pt)(-1) min(-1) (0.7 kW(LHV_H2) g(Pt)(-1)) at a dehydrogenation temperature of only 267 degrees C is found to be nearly four times higher than for the conventional continuous liquid-phase dehydrogenation at the same temperature. Furthermore, simulation results of the CD process are described. The feasibility of a fully heat-integrated process for electricity generation from the released hydrogen via CD using waste heat from the fuel cell for the CD reboiler is demonstrated. The technical potential of coupling the H12-BT dehydrogenation by CD with high-temperature fuel cell operation is highlighted by the simulation.
CRIS-Team WoS Importer:2023-02-24

Periodic open-cell foams: Pressure drop measurements and modeling of an ideal tetrakaidecahedra packing - Inayat, Amer; Schwerdtfeger, Jan; Freund, Hannsjoerg; Körner, Carolin; Singer, Robert; Schwieger, Wilhelm; Freund, Hannsjörg (Chemical Engineering Science, 2011)
The applicability of the new correlation for a large range of porosities was examined by comparing the experimental and simulated friction factors for the porous media with both high (foam structure) and low porosities (packed beds) for a large range of the Reynolds number. It was demonstrated that the correlation can successfully predict the pressure drop of foam structures as well as packed beds. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Foam; Ideal structure; Pressure drop; Catalyst support; Tetrakaidecahedra model; SEBM

Periodic open cellular Raney-Copper-Catalysts fabricated via selective electron beam melting - Wolf, Torsten; Fu, Zongwen; Ye, Jihui; Heßelmann, Christina; Pistor, Julian; Albert, Jakob; Wasserscheid, Peter; Körner, Carolin (Advanced Engineering Materials, 2020)

Periodic open cellular structures (POCS) for intensification of multiphase reactors: Liquid holdup and two-phase pressure drop - Lämmermann, Markus; Horak, Giulia; Schwieger, Wilhelm; Freund, Hannsjörg (Chemical Engineering and Processing, 2018)
Structuring concepts for catalytic reactors provide promising options for process intensification on the process unit level [1,2] as they offer a better control on the occurring transport processes, e.g. on the fluid flow, species distribution, pressure drop and heat transfer. Process intensification aims at the realization of processes that are only limited by reaction kinetics, but not anymore on hydrodynamics [3]. For this reason, in multiphase reactors it is desirable to achieve good liquid distribution, advanced heat transport and low pressure drop, just to mention a few transport characteristics. In this regards, the use of periodic open cellular structures (POCS) is a recent and very promising structuring concept, as packings of these structures offer superior and adjustable properties (e.g. low pressure drop, high surface area, good liquid distribution, advanced heat transfer) [4-8].In this contribution, static and dynamic liquid holdup as well as single- and two-phase pressure drop was measured in POCS. These kinds of structures can be used as catalyst support in packed bed reactors, and also as liquid distributor for trickle-bed applications. The POCS investigated in this study were fabricated with different additive manufacturing methods (fused deposition modeling, stereolithography and selective electron beam melting) to study the influence of different materials (ABS, resin, Ti6Al/4V). For the description of the static liquid holdup, a modified Eotvos correlation, which takes the contact angle of the different materials into account, is proposed. Dynamic liquid holdup and two-phase pressure drop was modelled using an extension of the concept of hydrodynamic tortuosity proposed by Inayat et al. [8], and a modification of the relative permeability model introduced by Saez et al. [9]. Furthermore, equations for the geometric characterization of POCS consisting of different unit cell types, namely Diamond, Kelvin and the recently presented DiaKel hybrid cell [5] were derived. The window diameter of the used unit cells as well as the porosity has a strong influence on the liquid holdup and the pressure drop. By taking the contact angle into account the static liquid holdup can be calculated with good precision (errors smaller than 20%). The concept of geometric tortuosity and the relative permeability model also is applicable to predict the (two-) phase pressure drop and the dynamic liquid holdup in stacked packings of POCS segments of different unit cells and materials. Both, pressure drop and liquid holdup can be predicted a priori (i.e., without further fitting) with good precision using the correlations established in this work solely based on geometric properties of the packing.
Keywords: Two-phase pressure drop; Liquid holdup; Structured catalysts; Relative permeability model; Additive manufacturing

Periodic open cellular structures with ideal cubic cell geometry: Effect of porosity and cell orientation on pressure drop behavior - Klumpp, Michael; Inayat, Amer; Schwerdtfeger, Jan; Körner, Carolin; Singer, Robert; Freund, Hannsjörg; Schwieger, Wilhelm (Chemical Engineering Journal, 2014)
Periodic open cellular structures (POCS) with ideal cubic cell geometry (icPOCS) were manufactured via the selective electron beam melting technique (SEBM). Depending on the cell dimensions (cell length, strut diameter) and cell orientation in respect to the main axis of the cylindrical structures, the icPOCS investigated in this work exhibit different porosities and/or tortuosities. The structures were characterized with respect to their morphological and geometrical parameters such as strut and cell dimension, specific surface area, and porosity using different techniques (e.g., micro-computed tomography and helium pycnometry). Additionally, a model for the calculation of the specific surface area is presented which takes surface roughness into account. The model enables the determination of the specific surface area on the basis of only two geometrical parameters, i.e., the strut diameter and the cell length, which are both easy to determine for such highly regular open cellular structures. The pressure drop of the icPOCS was measured with air as working fluid. A correlation allowing for the prediction of the pressure drop of icPOCS was developed based on the Ergun equation in its basic form. The presented correlation reflects the porosity and cell orientation and is solely based on the geometric properties of the structures. As the correlation does not rely on the use of empirical fitting parameters it is fully predictive. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Open cellular structure; Pressure drop; Cell orientation; Specific surface area; SEBM

Perspective on the Use of Ultrasonic Monitoring for In Situ Diagnostics of Zeolite and MOF Crystallization - Ermer, Matthias; Reber, Rebecca; Baser, Hasan-Hüseyin; Fischer, Marcus; Schwieger, Wilhelm; Hartmann, Martin (Crystal Growth and Design, 2023)
The investigation and understanding of the underlying mechanisms for the crystallization of molecular sieve materials, such as metal-organic frameworks (MOFs) and zeolites, have received increasing interest in recent years. This is mainly because improvements of the corresponding equipment were made that are essential for in situ diagnostics. In contrast to classical techniques, such as X-ray diffraction and neutron scattering, nuclear magnetic resonance, or infrared and Raman spectroscopy, ultrasonic monitoring has not received proper attention. Thereby, especially for zeolites, important insights have been gained with this technique already. However, for MOFs, the number of publications dealing with in situ US monitoring is still limited. Therefore, this perspective gives an overview of the topic of in situ monitoring of crystallization of zeolites and MOFs and highlights the work that has been done so far by ultrasonic monitoring. Furthermore, we state benefits and current challenges for further establishing ultrasonic monitoring as a tool for the investigation of crystallization processes.
CRIS-Team Scopus Importer:2023-07-21

Phantom Studies of Neutron Capture of Boron Containing Magnetic Nanoparticles - Tietze, Rainer; Dürr, Stephan; Lyer, Stefan; Taccardi, Nicola; Wasserscheid, Peter; Canella, Lea; Wagner, Franz M.; Petry, Winfried; Alexiou, Christoph (Biomedizinische Technik, 2013)
The main burden that hinders the translation of neutron capture therapy drafts to human trials is the difficulty to deposit a sufficient amount of boron in the targeted tumour areas. Magnetic nanoparticles containing B-10 isotopes attempt to be enriched in tumour tissues selectively by the means of external magnetic fields to overcome these restrictions. First pilot measurements of the neutron depth penetration investigated the neutron flux density in dependence of depth, presence of boron and additional presence of iron oxide nanoparticles. These irradiation experiments on different phantoms evidenced no disturbing attenuation effects of the applied boron and the co-present nanoparticles in the samples.
EVALuna2:19968

Phase Transformations in Porous Materials Studied by in Situ Solid-State NMR Spectroscopy and in Situ X-ray Diffraction - Paula, Carolin; Wisser, Dorothea; Rangus, Mojca; Schwieger, Wilhelm; Hovestadt, Maximilian; Kriesten, Martin; Vanatalu, Kalju; Oss, Andres; Org, Mai-Liis; Samoson, Ago; Hartmann, Martin (Journal of Physical Chemistry C, 2020)
Studying complex processes in solid phases such as adsorption or phase transitions in situ is the best way to obtain detailed and realistic insights on a molecular level. Besides in situ X-ray diffraction techniques, magic angle spinning (MAS) solid-state NMR spectroscopy is one of the most powerful analytical techniques. The implementation of in situ and operando MAS NMR is however challenging and requires dedicated hardware. We introduce here a new 4.0 mm wide-bore probe that allows for a continuous and well-distributed flow of gaseous adsorbates or reactants through the packed sample, as well as uniform heating of the sample and spinning of the rotor at the magic angle. The combination of both in situ MAS NMR and in situ powder X-ray diffraction allowed us to obtain new insights into two phase transformation mechanisms in crystalline, porous materials, viz. that of aluminophosphate VPI-5 into AlPO4-8 and that of metal-organic frameworks from the MIL-53 family during water adsorption and desorption.
CRIS-Team Scopus Importer:2020-10-23

Photocatalytic methanol oxidation to formaldehyde in a continuous laboratory plant over Aeroxide P25 - Stubenrauch, Florian; Schörner, Markus; Bösmann, Andreas; Schühle, Patrick; Wasserscheid, Peter (Reaction Chemistry & Engineering, 2024)
We here report the photochemical synthesis of formaldehyde by gas phase methanol oxidation with oxygen in a sophisticated continuous laboratory setup. The commonly used benchmark photocatalyst Evonik Aeroxide P25 was applied in combination with a narrow peak UV-A LED light source. Prior to its use, the applied powder catalyst was immobilized with a simple spray coating technique to a steel plate support (300 mm × 130 mm × 20 mm). With this system, reaction engineering studies have been carried out to elaborate the dependencies of catalyst mass, irradiation, residence time and temperature on achieved conversions, selectivities, yields, reaction rates, and apparent quantum efficiencies. We found that catalyst load influences conversion in an extended plateau like manner. High irradiation and residence time benefit MeOH conversion while the selectivity for HCHO decreases with both parameters. Temperature showed an interesting influence, as it increases both conversion and selectivity, until desorption effects become dominating over 120 °C. Our work thus for the first time provides application relevant information for an industrial highly interesting reaction and a heavily researched model photocatalytic system that has so far been mainly studied under surface science conditions.
CRIS-Team Scopus Importer:2024-03-15

Photochemical Microreactors in Photonic Crystal Fibers - Cubillas, Ana Maria; Scharrer, Michael; Euser, Tijmen G.; Schmidt, Matthias; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (OSA Publishing, 2012)
Hollow-core photonic crystal fiber offers new possibilities for sensing and photochemistry applications. In this paper we review our recent achievements on liquid-phase photochemical microreactors using photonic crystal fibers and discuss our future prospects in this field.

Photochemistry in a soft-glass single-ring hollow-core photonic crystal fibre - Cubillas, Ana M.; Jiang, Xin; Euser, Tijmen G.; Taccardi, Nicola; Etzold, Bastian; Wasserscheid, Peter; Russell, Philip St. John (Analyst, 2017)
A hollow-core photonic crystal fibre (HC-PCF), guided by photonic bandgap effects or anti-resonant reflection, offers strong light confinement and long photochemical interaction lengths in a microscale channel filled with a solvent of refractive index lower than that of glass (usually fused silica). These unique advantages have motivated its recent use as a highly efficient and versatile microreactor for liquid-phase photochemistry and catalysis. In this work, we use a single-ring HC-PCF made from a high-index soft glass, thus enabling photochemical experiments in higher index solvents. The optimized light-matter interaction in the fibre is used to strongly enhance the reaction rate in a proof-of-principle photolysis reaction in toluene.
EAM Import::2019-03-12

Photochemistry in hollow-core photonic crystal fiber microreactors - Euser, Tijmen G.; Cubillas, Ana Maria; Jiang, X.; Unterkofler, Sarah; Etzold, Bastian; Wasserscheid, Peter; Jones, Anita C.; Sadler, Peter J.; Russell, Philip St. John (Laser Applications to Chemical, Security and Environmental Analysis, 2014)
Hollow-core photonic crystal fiber uniquely allows low-loss propagation of light in liquid-filled microchannels, thus enabling highly efficient photochemistry, photo-switching, and photocatalysis at optical powers that are five orders of magnitude lower than in conventional systems.

Photochemistry on soft-glass hollow-core photonic crystal fibre - Cubillas, Ana Maria; Jiang, X.; Euser, Tijmen G.; Taccardi, Nicola; Etzold, Bastian; Wasserscheid, Peter; Russell, Philip St. John (23rd International Conference on Optical Fibre Sensors, 2014)
Hollow-core photonic crystal fibre (HC-PCF) offers strong light confinement and long interaction lengths in an optofluidic channel. These unique advantages have motivated its recent use as a highly efficient and versatile microreactor for liquid-phase photochemistry and catalysis. In this work, we use a soft-glass HC-PCF to carry out photochemical experiments in a high-index solvent such as toluene. The high-intensity and strong confinement in the fibre is demonstrated to enhance the performance of a proof-of-principle photolysis reaction.

Photonic crystal fibres for chemical sensing and photochemistry - Cubillas, Ana Maria; Unterkofler, Sarah; Euser, Tijmen G.; Etzold, Bastian; Jones, Anita C.; Sadler, Peter J.; Wasserscheid, Peter; Russell, Philip St. John (Chemical Society Reviews, 2013)
In this review, we introduce photonic crystal fibre as a novel optofluidic microdevice that can be employed as both a versatile chemical sensor and a highly efficient microreactor.We demonstrate that it provides an excellent platform in which light and chemical samples can strongly interact for quantitative spectroscopic analysis or photoactivation purposes. The use of photonic crystal fibre in photochemistry and sensing is discussed and recent results on gas and liquid sensing as well as on photochemical and catalytic reactions are reviewed. These developments demonstrate that the tight light confinement, enhanced light-matter interaction and reduced sample volume offered by photonic crystal fibre make it useful in a wide range of chemical applications.

Physical vapor deposition of [EMIM][Tf2N]: A new approach to the modification of surface properties with ultrathin ionic liquid films - Cremer, Till; Killian, Manuela; Gottfried, Michael; Paape, Natalia; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2008)
Ultrathin films of the ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [EMIM][TfN], are prepared on a glass substrate by means of an in situ thermal-evaporation/condensation process under ultrahigh-vacuum conditions. By using X-ray photoelectron spectroscopy (XPS), it is demonstrated that the first layer of the IL film grows two dimensionally, followed by the three-dimensional growth of successive layers. The first molecular layer consists of a bilayer, with the [EMIM] cations in contact to the surface and the [TfN] anions at the vacuum side. The ultrathin IL films are found to be stable under ambient conditions. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Pillared HMCM-36 zeolite catalyst for biodiesel production by esterification of palmitic acid - Purova, Ralitsa; Narasimharao, Katabathini; Ahmed, Nesreen S. I.; Al-Thabaiti, Shaeel; Al-Shehri, Abdulmohsen; Mokhtar, Mohammed; Schwieger, Wilhelm (Journal of Molecular Catalysis A-Chemical, 2015)
Layered MWW zeolite has been studied for swelling/pillaring using CTAB and silica as swelling and pillaring reagents, respectively to synthesize pillared MCM-36 material. The swelling/pillaring efficiency was evaluated based on their X-ray diffraction, N-2-physisorption, scanning electron microscopy and FTIR spectra after pyridine adsorption as indicator for acidity measurements and catalytic potential. There was an overall decrease in acid site concentration due to incorporation of inert silica pillars. However, after ion exchange, mesoporous HMCM-36 zeolite with the highest BET surface area showed increased Bronsted and Lewis acid sites compared to the MCM-22, suggesting enhanced accessibility of acid sites for bulky reacting molecules. MCM-22 and MCM-36, as well as the ion exchanged HMCM-22 and HMCM36 samples were tested for esterification of palmitic acid with methanol. The HMCM-36 catalyst showed high activity in palmitic acid esterification with methanol. This catalyst can be readily separated from the reaction system for re-use for at least four cycles without losing any activity suggesting potential industrial applications in biodiesel synthesis. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Pillared HMCM-36; MCM-22(P); Biodiesel; Esterification; Palmitic acid

Polymer-Based Spherical Activated Carbon as Easy-to-Handle Catalyst Support for Hydrogenation Reactions - Klefer, Heiko; Munoz Garcia, Macarena; Modrow, Antje; Böhringer, Bertram; Wasserscheid, Peter; Etzold, Bastian (Chemical Engineering & Technology, 2016)
The application of polymer-based spherical activated carbon (PBSAC) as catalyst support offers unprecedented advantages in the handling of the catalyst in all stages of its application due to its superior fluid dynamic properties and dust-free character, minimizing post processing times and facilitating catalyst recycling. The preparation of PBSAC-based Pd catalysts has been addressed using PBSAC of different particle sizes and degrees of activation. Prior to Pd deposition, the support was oxidized in nitric and sulfuric acidic media under different operating conditions in order to introduce surface charges for the ion exchange. This method was successfully applied as, even for the mildest functionalization conditions, full deposition of Pd was achieved. The synthesized Pd-PBSAC catalysts were successfully employed in the hydrogenation of cinnamic acid achieving its complete conversion at an optimum effective rate constant of 0.122mkg s.
Keywords: Cinnamic acid; Hydrogenation; Palladium catalyst; Polymer-based spherical activated carbon

Porous Materials: Small Holes - big Effects - Schwieger, Wilhelm; Hartmann, Martin (Chemie Ingenieur Technik, 2010)

Porous materials: Small voids large effect - Schwieger, Wilhelm; Hartmann, Martin (Chemie Ingenieur Technik, 2010)

Potential Application of Innovative Gas Hydrate Technology in Fruit Juices Concentration Process - Loekman, Soebiakto; Claßen, Timo; Seidl, Pia; Luzi, Giovanni; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy, 2019)

Präparationsprinzipien mikroporöser Materialien: Vom building block zum hierarchisch aufgebauten porösen System - Schwieger, Wilhelm; Klumpp, Michael; Al-Thabaiti, Shaeel A.; Hartmann, Martin (Chemie Ingenieur Technik, 2016)
Mikroporöse Materialien sind lange bekannt und werden aufgrund ihrer einzigartigen sorptiven und katalytischen Eigenschaften mit weiterhin steigendem Interesse untersucht, zielgerichtet synthetisiert und potenziellen Anwendungen zugeführt. Obwohl gerade die Mikroporosität entscheidend zu den herausragenden Eigenschaften in Katalyse und Sorptionsprozessen beiträgt, so bremst sie auch die Geschwindigkeit vieler solcher Prozesse. Deshalb rückt die Entwicklung von Materialien mit hierarchisch aufgebauter Porosität zunehmend in den Fokus der Forschung. Dieser Artikel spannt den Bogen von der grundsätzlichen Beschreibung mikroporöser Materialien und ihrer Baueinheiten, über grundsätzliche Präparationsprinzipien bei deren Herstellung bis hin zu den neueren Entwicklungen im Bereich der zeolithischen Materialien mit hierarchischer Porosität.
EAM Import::2019-03-08

Predicting the Specific Surface Area and Pressure Drop of Reticulated Ceramic Foams Used as Catalyst Support - Inayat, Amer; Freund, Hannsjoerg; Schwab, Andreas; Zeiser, Thomas; Schwieger, Wilhelm; Freund, Hannsjörg (Advanced Engineering Materials, 2011)
Open-cell ceramic foams are attractive candidates as catalyst support owing to their remarkable heat and mass transfer characteristics. The accurate knowledge of the specific surface area and the pressure drop is a prerequisite for the reliable design of reactors with solid foam structures as internals. In this contribution, we propose a new correlation for the prediction of the pressure drop in reticulated ceramic foams using their predicted specific surface area. The correlation is based on an ideal tetrakaidecahedron geometry, which is the preferred representative geometry for reticulated foams. The validity of the correlation is demonstrated by experimental data of reticulated ceramic foams of different pores per inch (PPI), porosity, and material from the present study as well as from the open literature.

Prediction of multicomponent phase behavior of CO2-expanded liquids using CEoS/GE models and comparison with experimental data - Ye, Kongmeng; Freund, Hannsjörg; Xie, Zhuanzhuan; Subramaniam, Bala; Sundmacher, Kai (Journal of Supercritical Fluids, 2012)
Models utilizing cubic equation of state and excess Gibbs free energy-based mixing rules (CEoS/GE) were used for predicting the multicomponent VLE phase behavior involving CO2-expanded liquids. Four such models were selected out of 36 models (four CEoS in conjunction with nine mixing rules each) and evaluated with regard to their predictive capability using 14 systems, including 12 sub-systems (eight ternary systems, three quaternary systems and one quinary system) of 1-octene hydroformylation in CO2-expanded acetone (with the components H-2, CO, CO2, 1-octene, n-nonanal, and acetone), a CO2-expanded toluene ternary system and a CO2-expanded acetonitrile ternary system. Model discrimination was based on their relative abilities to predict experimental VLE data generated within this work (ternary, quaternary or quinary systems with various combinations of H-2, CO, CO2, 1-octene or n-nonanal) and from the literature. The results indicate that the CEoS/GE modeling approach is successful in predicting the phase behavior of the 14 investigated CO2-expanded liquid systems. The selected models are expected to be useful in the rational selection of CO2-expanded liquids and operating conditions (p & T) for optimal performance of reaction and/or separation units. (C) 2012 Elsevier BM. All rights reserved.
Keywords: CEoS/GE; CO2-expanded liquids; Phase behavior; VLE; Hydroformylation; Experimental VLE data

Preparation and characterization of ultrathin [Ru(CO) 3Cl 2] 2 and [BMIM][Tf 2N] films on Al 2O 3/NiAl(110) under UHV conditions - Sobota, Marek; Schernich, Stefan; Schulz, Hannes; Hieringer, Wolfgang; Paape, Natalia; Wasserscheid, Peter; Görling, Andreas; Laurin, Mathias; Libuda, Jörg (Physical Chemistry Chemical Physics, 2012)
Towards a better understanding of the interface chemistry of ionic liquid (IL) thin film catalytic systems we have applied a rigorous surface science model approach. For the first time, a model homogeneous catalyst has been prepared under ultrahigh vacuum conditions. The catalyst, di-μ- chlorobis(chlorotricarbonylruthenium) [Ru(CO) Cl ] , and the solvent, the IL 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][Tf N], have been deposited by physical vapor deposition onto an alumina model support [Al O /NiAl(110)]. First, the interaction between thin films of [Ru(CO) Cl ] and the support is investigated. Then, the ruthenium complex is co-deposited with the IL and the influence of the solvent on the catalyst is discussed. D O, which is a model reactant, is further added. Growth, surface interactions, and mutual interactions in the thin films are studied with IRAS in combination with density functional (DFT) calculations. At 105 K, molecular adsorption of [Ru(CO) Cl ] is observed on Al O /NiAl(110). The IRAS spectra of the binary [Ru(CO) Cl ] + [BMIM][Tf N] and ternary [Ru(CO) Cl ] + [BMIM][Tf N] + D O show every characteristic band of the individual components. Above 223 K, partial decomposition of the ruthenium complex leads to species of molecular nature attributed to Ru(CO) and Ru(CO) surface species. Formation of metallic ruthenium clusters occurs above 300 K and the model catalyst decomposes further at higher temperatures. Neither the presence of the IL nor of D O prevents this partial decomposition of [Ru(CO) Cl ] on alumina. © 2012 the Owner Societies.

Preparation and Potential Catalytic Applications of Hierarchically Structured Zeolites with Macropores - Weissenberger, Tobias; Machoke, Albert; Reiprich, Bastian; Schwieger, Wilhelm (Advanced Materials Interfaces, 2021)
Hierarchically structured zeolites can mitigate problems arising from the slow transport in the micropores, such as diffusion limitations. Hence, a manifold of different preparation methods for hierarchical zeolites have been developed over the years and the corresponding zeolites showed superior performance due to enhanced mass transport caused by higher diffusivities in the additional pore system and reduced diffusion path length in the micropores. The dimensions of the additional secondary “transport” pores in these materials is a major factor affecting their diffusion properties and consequently their catalytic performance. Interestingly almost all reports focus on the generation of additional mesopores and study of catalytic performance of mesoporous zeolites. Larger macropores with pore diameters of more than 50 nm, however, have some intrinsic advantages over mesopores that make them very attractive for catalytic applications. In the last years, methods for the preparation of zeolites and zeolite composites with additional macropores have been developed. These developments have brought about a novel and promising class of hierarchically structured materials; zeolites with macropores. This review gives an overview about different preparation routes for zeolites with inter or intra crystalline macropores as well as zeolite composites with macropores and summarizes the first studies regarding catalytic their performance.
CRIS-Team Scopus Importer:2021-02-05
Keywords: catalysts; hierarchical zeolites; hierarchically-ordered materials; macropores; zeolites

Preparation and use of sulfonium dicyanamides as ionic liquids for electrical applications. - Uerdingen, Marc; Gerhard, Dirk; Wasserscheid, Peter (2006)
Sulfonium dicyanamides (e.g., trimethylsulfonium dicyanamide) are prepd. (e.g., by the reaction of trimethylsulfonium iodide with sodium dicyanamide) and used as ionic liqs. in elec. applications (e.g., capacitors). [on SciFinder(R)]
Keywords: sulfonium dicyanamide ionic liq prepn; trimethylsulfonium dicyanamide ionic liq prepn

Preparation of atom probe tips from (nano)particles in dispersion using (di)electrophoresis and electroplating - Vorlaufer, Nora; Josten, Jan; Carl, Simon; Göbel, Erik; Soegaard, Alexander; Taccardi, Nicola; Spiecker, Erdmann; Felfer, Peter (Microscopy Research and Technique, 2023)
The behavior of catalytic particles depends on their chemical structure and morphology. To reveal this information, the characterization with atom probe tomography has huge potential. Despite progresses and papers proposing various approaches towards the incorporation of particles inside atom probe tips, no single approach has been broadly applicable to date. In this paper, we introduce a workflow that allowed us to prepare atom probe specimens from Ga particles in suspension in the size range of 50 nm up to 2 μm. By combining dielectrophoresis and electrodeposition in a suitable way, we achieve a near-tip shape geometry, without a time-consuming FIB lift-out. This workflow is a simple and quick method to prepare atom probe tips and allows for a high preparation throughput. Also, not using a lift-out allowed us to use a cryo-stage, avoiding melting of the Ga particles, while ensuring a mechanical stable atom probe tip. The specimen prepared by this workflow enable a stable measurement and low fracture rates.<br

Preparation of atom probe tips from (nano)particles in dispersion using (di)electrophoresis and electroplating - Vorlaufer, Nora; Josten, Jan; Carl, Simon; Göbel, Erik; Soegaard, Alexander; Taccardi, Nicola; Spiecker, Erdmann; Felfer, Peter (Microscopy Research and Technique, 2024)
The behavior of catalytic particles depends on their chemical structure and morphology. To reveal this information, the characterization with atom probe tomography has huge potential. Despite progresses and papers proposing various approaches towards the incorporation of particles inside atom probe tips, no single approach has been broadly applicable to date. In this paper, we introduce a workflow that allowed us to prepare atom probe specimens from Ga particles in suspension in the size range of 50 nm up to 2 μm. By combining dielectrophoresis and electrodeposition in a suitable way, we achieve a near-tip shape geometry, without a time-consuming FIB lift-out. This workflow is a simple and quick method to prepare atom probe tips and allows for a high preparation throughput. Also, not using a lift-out allowed us to use a cryo-stage, avoiding melting of the Ga particles, while ensuring a mechanical stable atom probe tip. The specimen prepared by this workflow enable a stable measurement and low fracture rates. Research Highlights: Enabling cryo-preparation of (nano)particles for the atom probe. Characterization of surface and bulk elemental distribution of GaPt model SCALMS.
CRIS-Team Scopus Importer:2024-02-16
Keywords: atom probe tomography; catalyst particles; cryo preparation; nanoparticles

Preparation of carbide-derived carbon supported platinum catalysts - Hasse, Benjamin; Gläsel, Jan-Sebastian; Kern, Andreas; Murzin, D. Yu.; Etzold, Bastian (Catalysis Today, 2014)
Well defined carbon supported catalysts are of interest to deduce structure activity relationships and for catalyst optimization. Carbide-derived carbons (CDC) are high purity porous carbons with tunable pore structure. The deposition of platinum on silicon and titanium carbide based CDC was studied, using a three step process of acid treatment, ion-adsorption of platinum precursor and gas phase reduction. The influence of the steps on the carbon support properties and possibility to control the platinum loading and resulting cluster size was determined. Most crucial is the acid treatment step, where oxygen groups are introduced. At a too high degree of functionalization (non-carbon content above 30 wt%), which can result for nitric acid treatment, the pore structure is heavily attacked. For sulfuric acid treatments non-carbon contents below 15 wt% and only minor changes in the pore structure were observed. The ion-adsorption technique could be successfully transferred to the CDC supports. For medium to high degrees of functionalization (non-carbon contents above 20 wt%) the full deposition of 2.5 wt% of platinum was achieved. By the choice of platinum precursor, the pH of impregnation and the temperature of reduction the platinum cluster size could be varied from 2.5 to 5.3 nm. Thus, important knowledge how to prepare tuned Pt/C catalysts based on CDC and the ion-adsorption technique could be deduced.
EAM Import::2019-03-08

Preparation of geometrically highly controlled Ga particle arrays on quasi-planar nanostructured surfaces as a SCALMS model system - Hofer, André; Taccardi, Nicola; Moritz, Michael; Wichmann, Christoph; Hübner, Sabine; Drobek, Dominik; Engelhardt, Matthias; Papastavrou, Georg; Spiecker, Erdmann; Papp, Christian; Wasserscheid, Peter; Bachmann, Julien (RSC Advances, 2023)
This study establishes a preparative route towards a model system for supported catalytically active liquid metal solutions (SCALMS) on nanostructured substrates. This model is characterized by a uniquely precise geometrical control of the gallium particle size distribution. In a SCALMS system, the Ga serves as a matrix material which can be decorated with a catalytically active material subsequently. The corresponding Ga containing precursor is spin-coated on aluminum based substrates, previously nanostructured by electrochemical anodization. The highly ordered substrates are functionalized with distinct oxide coatings by atomic layer deposition (ALD) independently from the morphology. After preparation of the metal particles on the oxide interface, the characterization of our model system in terms of its geometry parameters (droplet diameter, size distribution and population density) points to SiO2 as the best suited surface for a highly controlled geometry. This flexible model system can be functionalized with a dissolved noble metal catalyst for the application chosen.<br

Preparation of hollow mesoporous carbon spheres and their performances for electrochemical applications - Ariyanto, T.; Zhang, Guirong; Kern, Andreas; Etzold, Bastian (IOP Conference Series: Materials Science and Engineering, 2018)
Hollow carbon materials have received intensive attention for energy storage/conversion applications due to their attractive properties of high conductivity, high surface area, large void and short diffusion pathway. In this work, a novel hollow mesoporous material based on carbide-derived carbon (CDC) is presented. CDC is a new class of carbon material synthesized by the selective extraction of metals from metal carbides. With a two-stage extraction procedure of carbides with chlorine, firstly hybrid core-shell carbon particles were synthesized, i.e. mesoporous/graphitic carbon shells covering microporous/amorphous carbon cores. The amorphous cores were then selectively removed from particles by a careful oxidative treatment utilizing its low thermal characters while the more stable carbon shells remained, thus resulting hollow particles. The characterization methods (e.g. N2 sorption, Raman spectroscopy, temperature-programmed oxidation and SEM) proved the successful synthesis of the aspired material. In electric double-layer capacitor (EDLC) testing, this novel hollow core material showed a remarkable enhancement of EDLC's rate handling ability (75% at a high scan rate) with respect to an entirely solid-mesoporous material. Furthermore, as a fuel cell catalyst support the material showed higher Pt mass activity (a factor of 1.8) compared to a conventional carbon support for methanol oxidation without noticeably decreasing activity in a long-term testing. Therefore, this carbon nanostructure shows great promises as efficient electrode materials for energy storage and conversion systems.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; Electric-double layer capacitors; Hollow carbon spheres; Methanol oxidation

Preparation of ionic liquids and their application. - Wasserscheid, Peter; Paape, Natalia; Bösmann, Andreas; Schulz, Peter (2009)
The present invention relates to chem. compds. comprising of formula [X(CHRa)n-CH(Ra)SO3]- [X = F, Cl, Br, acyl; n = 1 - 3; Ra = H, C1-12 alkyl; Rb = C1-12], their prepn. and application. The chem. compds. are preferably ionic liqs. Compd. I was prepd. by addn. of the anion of 1-butyl-3-methylimidazolium chloride to 1,4-butane sulfone. [on SciFinder(R)]
Keywords: imidazolium chloride sultone anion addn; sulfonate imidazolium prepn ionic liq; tetraalkylammonium sulfonate prepn ionic liq

Preparation of isolated Co3O4 and fcc-Co crystallites in the nanometre range employing exfoliated graphite as novel support material - Wolf, Moritz; Fischer, Nico; Claeys, Michael (Nanoscale Advances, 2019)
The inert nature of graphitic samples allows for characterisation of rather isolated supported nanoparticles in model catalysts, as long as sufficiently large inter-particle distances are obtained. However, the low surface area of graphite and the little interaction with nanoparticles result in a challenging application of conventional preparation routes in practice. In the present study, a set of graphitic carbon materials was characterised in order to identify potential support materials for the preparation of model catalyst systems. Various sizes of well-defined Co3O4 nanoparticles were synthesised separately and supported onto exfoliated graphite powder, that is graphite after solvent-assisted exfoliation via ultrasonication resulting in thinner flakes with increased specific surface area. The stability of the supported nanoparticles during reduction to metallic cobalt in H-2 was monitored in situ by means of X-ray diffraction and smaller crystallite sizes were found to be harder to reduce than their larger counterparts. A low cobalt loading of 1 wt% was required to avoid aggregates in the parent catalyst, and this allowed for the preparation of supported cobalt nanoparticles which were resistant to sintering at reduction temperatures below 370 degrees C. The developed model catalysts are ideally suited for sintering studies of isolated nano-sized cobalt particles as the graphitic support material does not provide distinct metal-support interaction. Furthermore, the differently sized cobaltous particles in the various model systems render possible studies on structural dependencies of activity, selectivity, and deactivation in cobalt oxide or cobalt catalysed reactions.
CRIS-Team WoS Importer:2019-08-27

Preparation of ZSM-5 zeolite membranes by combined hydrothermal synthesis and electrophoretic deposition - Negishi, Hideyuki; Reuß, Stephanie; Schwieger, Wilhelm; Boccaccini, Aldo R. (Key Engineering Materials, 2015)
The preparation of a ZSM-5 zeolite membrane on porous stainless steel disk by hydrothermal synthesis with electrophoretic deposition (EPD) as a seeding method was investigated. Micron size ZSM-5 crystal powder was seeded by EPD on the support disk by using ZSM-5 powder dispersed in ethanol. The seeded amounts were easily controlled by the deposition time during EPD. The membrane after secondary growth had a low amount of zeolite in comparison with the in situ seeding method and the permeance of single gas such as He, N2 and CO was also low in comparison with that of the in situ seeding method.
Keywords: Electrophoretic deposition (EPD); Permeance; Secondary growth; Seeding; Zeolite membrane

Preparation Principles of Microporous Materials: From Building Blocks Towards Hierarchically Ordered Systems - Schwieger, Wilhelm; Klumpp, Michael; Al-Thabaiti, Shaeel A.; Hartmann, Martin (Chemie Ingenieur Technik, 2016)
Microporous materials are well known and due to their unique properties in sorptive and catalytic processes also of still growing interest in research with regards to, e.g., targeted material synthesis and potential application in novel processes. Though, it is their microporosity which is in the first place the responsible property for the outstanding performance in sorption and catalysis, it is also its small pore size which thwarts the kinetic of such processes. This discrepancy is therefore the main driving force for the ongoing development of hierarchically porous materials. This article gives a basic description of microporous materials and their building blocks in general as well as the underlying principles of their preparation and additionally gives a review on the field of recent developments with special focus on hierarchically porous zeolites.
Keywords: Building blocks; Core-shell; Hierarchy; Porous materials; Preparation principles

Pressurized hydrogen from charged liquid organic hydrogen carrier systems by electrochemical hydrogen compression - Mrusek, Stephan; Preuster, Patrick; Müller, Karsten; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2021)
We demonstrate that the combination of hydrogen release from a Liquid Organic Hydrogen Carrier (LOHC) system with electrochemical hydrogen compression (EHC) provides three decisive advantages over the state-of-the-art hydrogen provision from such storage system: a) The EHC device produces reduced hydrogen pressure on its suction side connected to the LOHC dehydrogenation unit, thus shifting the thermodynamic equilibrium towards dehydrogenation and accelerating the hydrogen release; b) the EHC device compresses the hydrogen released from the carrier system thus producing high value compressed hydrogen; c) the EHC process is selective for proton transport and thus the process purifies hydrogen from impurities, such as traces of methane. We demonstrate this combination for the production of compressed hydrogen (absolute pressure of 6 bar) from perhydro dibenzyltoluene at dehydrogenation temperatures down to 240 °C in a quality suitable for fuel cell operation, e.g. in a fuel cell vehicle. The presented technology may be highly attractive for providing compressed hydrogen at future hydrogen filling stations that receive and store hydrogen in a LOHC-bound manner.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Compression; Dehydrogenation; Heat integration; Hydrogen storage; Purity

Probing a gas/liquid acid-base reaction by X-ray photoelectron spectroscopy - Niedermaier, Inga; Taccardi, Nicola; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2013)
A mechanistic study: In a Brønsted acid/base reaction, gaseous triflic acid (OTfH) transfers its proton to the basic Cl anion of the ionic liquid [CCIm]Cl forming volatile HCl and the IL [CCIm][TfO]. This anion exchange reaction is monitored in the near-surface region quantitatively by X-ray photoelectron spectroscopy as a function of time (see picture; BE=binding energy). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Probing Mass Transfer in Mesoporous Faujasite-Type Zeolite Nanosheet Assemblies - Mehlhorn, Dirk; Inayat, Alexandra; Schwieger, Wilhelm; Valiullin, Rustem; Kärger, Jörg (ChemPhysChem, 2014)
Pulsed field gradient nuclear magnetic resonance (NMR) diffusion studies are performed by using cyclohexane to probe transport properties in a NaX-type zeolite with a hierarchical pore structure (house-of-cards-like assemblies of mesoporous nanosheets), which is compared with a purely microporous sample. With guest loadings chosen to ensure saturation of the micropores, and the meso- and macropores left essentially unoccupied, guest diffusion is shown to be enhanced by almost one order of magnitude, even at room temperature. Diffusivity enhancement is further increased with increasing temperature, which may, therefore, be unambiguously attributed to the contribution of mass transfer in the meso-and macropores.
Keywords: diffusion; hierarchical pore systems; nanostructures; nmr spectroscopy; zeolites

Process and catalyst for oligomerization of C3-C5 olefins in batch reactor. - Boeing, Christian; Maschmeyer, Dietrich; Winterberg, Markus; Buchholz, Stefan; Melcher, Berthold Ulrich; Haumann, Marco; Wasserscheid, Peter (2011)
The subject of this invention is use of a catalyst system for oligomerization of olefins where catalyst system consists of (a) a carrier substrate selected from silicon dioxide, aluminum oxide, magnesium oxide, zirconium oxide as well as their mixt., or carbon nano-tubes, (b) an ionic liq. such as 1-butyl-3-methylimidazoliumchloride and aluminum chloride, (c) a catalytic effective compn., contg. nickel such NiCl2(P[C6H5]3), (d)and an activator selected from Lewis acids with alkylating characteristic such as ethylaluminum dichloride. [on SciFinder(R)]
Keywords: short olefin oligomerization batch reactor selective dimerization process catalyst

Process for hydrosilylation of alkenes in ionic liquids in preparation of alkylchlorosilanes. - Bauer, A.; Frey, T.; Wasserscheid, Peter; Schulz, Peter; Hofmann, Norbert (2008)
Alkylchlorosilanes were prepd. by hydrosilylation of alkenes R8R9C:CR10R11 (2; R8-R11 = H, optionally halo-, amino-, alkoxy-, cyano- of isocyanato-substituted C1-18 hydrocarbyl, Cl, F, C1-18 alkoxy) by silanes HaSiR4-a (1; R = H, optionally halo C1-18 hydrocarbyl, C1-18 alkoxy; a = 1-3), preferably by chlorosilanes RcHdSiCl4-c-d (3; same R, c = 0-4, d = 1-3), catalyzed by transition metal complexes, preferably by platinum complexes dissolved in ionic liqs. [A+][Y-] (4; Y- = BArF4-, BF4-, P(C2F5)3F3-, SbF6-, AsF6-, fluorosulfonate, carboxylate, sulfonate, organyl sulfate, diorganyl phosphate, disulfonylimidate; A+ = tetraorganylammonium, tetraorganylphosphonium, imidazolium, pyridinium, pyrazolium, triazolium, picolinium, pyrrolidinium), optionally supported by high-porous silica. In an example, the silica-supported catalyst was prepd. by adsorption of a soln. of 0.7 mg of PtCl4 in 1.0 g of 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imidate on 5 g of granulated silica (0.2-0.5 mm particles) followed by reaction of 6.3 g of allyl chloride with 11.7 g of trichlorosilane at 100°, giving (trichloropropyl)trichlorosilane with 70% yield and 73% selectivity. In another example, the catalytic soln. of PtCl4 in 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imidate was reused three times with any loss of catalytic activity. [on SciFinder(R)]
Keywords: hydrosilylation ionic liq allyl chloride chloropropylsilane prepn improved process; silane halosilane prepn improved process hydrosilylation ionic liq

Process for the alkylation of arylamines. - Ladnak, Viktor; Ott, Lothar; Schlenk, Stefan; Wasserscheid, Peter (2011)
The present invention which provides an in situ process for prepg. of a catalytically active complex for the alkylation of arylamines, a catalytically active complex mixt. prepd. by said process, a method for sep. prepg. a defined catalytically active complex out of the mixt. of said in situ formed catalytically active complex, the use of said in situ or sep. prepd. catalytically active complex for the alkylation of arylamines, and a process in the alkylation of arylamines by using said in situ or sep. prepd. catalytically active complex and recycling said catalytically active complex in the reaction. [on SciFinder(R)]
Keywords: alkylation catalyst Friedel Crafts olefin arylamine

Process for the preparation of ionic liquids with alkyl sulfate and functionalized alkyl sulfate anions. - Wasserscheid, Peter; van Hal, Roy; Hilgers, Claus (2006)
The invention relates to a process for the prepn. of ionic liqs. of general formula (cation)(R'-O-SO3). The process includes the step of treating the compd. of formula (cation)(R-O-SO3) with an alc., or mixt. of different alcs., of the formula R'-OH optionally in the presence of a catalyst to form the desired ionic liq. and the byproduct R-OH, which is optionally removed during the reaction or after completion of the reaction. The compd. of formula (cation)(R-O-SO3) can be prepd. by alkylating a tertiary or arom. amine with a dialkylsulfate. [on SciFinder(R)]
Keywords: alkyl sulfate ionic liq; onium compd ionic liq

Processing and/or operating machine comprising an ionic liquid as the operating liquid. - Hilgers, Claus; Uerdingen, Marc; Wagner, Markus; Wasserscheid, Peter; Schlücker, Eberhard (2008)
The invention relates to a processing or working machine comprising a liq. as the operating liq. in which the invention is characterized in that an ionic liq. constitutes the operating liq. The invention also relates to the use of operating fluids in processing or working machines, in which an ionic liq. constitutes the operating liq. and is used, in particular, as a lubricating fluid, barrier fluid, sealing fluid, or a pressure transmission fluid. [on SciFinder(R)]
Keywords: machine oil transmission fluid ionic liq hydraulic

Processing of Biomorphic Si3N4 Ceramics by CVI-R Technique with SiCl4/H2/N2 System - Ghanem, Hanadi; Popovska, Nadejda; Gerhard, Helmut (Journal of the European Ceramic Society, 2007)
Biomorphic porous silicon nitride Si3N4 ceramics have been produced by chemical vapor infiltration (CVI) of carbonized paper preforms with silicon, followed by gas-solid chemical reaction (R) of nitrogen with the infiltrated silicon. The paper was first carbonized in inert atmosphere to obtain a biocarbon (Cb) template. In a second step, silicon tetrachloride in excess of hydrogen was used to infiltrate silicon into the pores of the Cb template and to deposit silicon onto the Cb fibers. Finally, a gas-solid chemical reaction between nitrogen and infiltrated silicon in a temperature range of 1300-1450 °C took place in N2 or N2/H2 atmosphere to form reaction bonded silicon nitride (RBSN) ceramics. After nitridation, the samples consist mainly of α-Si3N4 phase for thermal treatment below the melting point of silicon (1410 °C) or of β-Si3N4 phase and β-Si3N4/SiC-mixed ceramics for treatment at temperatures above. The crystalline phases α- and β-Si3N4 were identified by X-ray diffraction (XRD) analysis and the microstructure of these samples was investigated by scanning electron microscopy (SEM). Energy-dispersive X-ray analysis (EDX) was used to detect the presence of silicon, nitrogen, carbon and oxygen, whereas Raman spectroscopy was applied to identify the presence of Si and SiC. Using thermal gravimetric analysis (TGA), residual carbon was determined. It was found, that addition of 10% H2 to the nitridation gas at temperatures near the melting point of silicon allows to increase the conversion of Si as well as to control the exothermic nitridation reaction obtaining the preferable needle-like microstructure. © 2006 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.LTCIR.proces_8
Keywords: Chemical vapor infiltration (CVI); Fibers; Si; SiC; Structural application

Processing or working machine using an ionic liquid as the service fluid. - Hilgers, Claus; Uerdingen, Marc; Wagner, Markus; Wasserscheid, Peter; Schlücker, Eberhard (2006)
The invention relates to a processing or working machine using an ionic liq. as the service fluid. The invention also relates to the use of service fluids in processing or working machines. An ionic liq. is used esp. as a lubricating fluid, a hydraulic fluid, a sealing fluid, or a pressure transmission fluid. [on SciFinder(R)]
Keywords: ionic liq lubricant; hydraulic fluid ionic liq; sealing fluid ionic liq; transmission fluid ionic liq

Process intensification by model-based design of tailor-made reactors - Freund, Hannsjörg; Maußner, Johannes; Kaiser, Markus; Xie, Mingquan (Current Opinion in Chemical Engineering, 2019)
The most recent work in the field of model-based design of catalytic reactors with a special focus on the multi-level reactor design (MLRD) methodology is reviewed. The key idea of this method is to track a fluid element on its way through the — not yet specified — reactor and to optimize the reaction conditions along its way by providing the necessary material and energy fluxes. On the basis of these optimal flux profiles novel reactor concepts tailored to the needs of the reaction system can be derived and analyzed. Recent advances and extensions to handle the specifics of reaction systems with different complexity are presented. The MLRD approach enables the predictive determination of the best reaction concept considering highly innovative process intensification options. Thereby, this method provides a key stone for the development of more economical and more sustainable chemical reactors and processes of the future.
CRIS-Team Scopus Importer:2019-10-08

Process specific catalyst supports-Selective electron beam melted cellular metal structures coated with microporous carbon - Knorr, Tilman; Heinl, Peter; Schwerdtfeger, Jan; Körner, Carolin; Singer, Robert; Etzold, Bastian (Chemical Engineering Journal, 2012)
Cellular support structures of Ti-6Al-4V produced by selective electron beam melting were coated with microporous carbon using a combined chemical vapor deposition and carbide-derived carbon approach. The production method allows for a process specific design of the open cellular metal structure. High thermal and electrical conductivity of the metal substrate are combined with the high surface area of the carbon coating within the tailored catalyst support. The study shows that for a successful deposition of the microporous carbon a protective oxide layer on top of the metal structure is necessary. Samples were impregnated with platinum as active metal and successfully tested in the hydrogenation of ethene. © 2011 Elsevier B.V..
Keywords: Carbide-derived carbon; Catalysis; Chemical vapor deposition; Foams; Microporous carbon; Selective electron beam melting; Silicon carbide; Structured catalyst support; Ti-6Al-4V

Producing a dialkyl carbonate by oxidative carbonylation in the presence of a supported on a solid phase substrate copper-containing catalyst. - Sundermeyer, Jörg; Wasserscheid, Peter; Stricker, Marion; Melcher, Berthold Ulrich; Haumann, Marco (2012)
A method for producing a dialkyl carbonate comprises reacting alkanol with carbon monoxide and oxygen in the presence of a supported on a solid phase substrate copper-contg. catalyst having m.p. ≤120° (catalyst is present on the solid phase substrate under method conditions in a liq. state). A copper-contg. complex compd. belonging to the catalyst comprises at least one nitrogen compd. such as N-alkylimidazoles, N,N -dialkylamino pyridines, N-alkylpyrazoles or N alkylguanidines as an N-donor ligand and/or a quaternized nitrogen compd. as an org. cation. Thus, mixing 15 min 6.17 g [Cu(Im12)2][CuBr2] (Im12 = 1-dodecylimidazole rest) with 90 mL acetonitrile in the absence of oxygen, adding 10.5 g silica gel having particle size 0.063 - 0.20 mm and BET surface area 335 m2/g, stirring 15 min, heating under stirring to 50°, treating with ultrasound, them reducing pressure to 500 Pa gave after 45 min a catalyst powder used in oxidative carbonylation of methanol to di-Me carbonate exhibiting selectivity 83% by reacting 4 h at 120° at O2 pressure 3 bar and CO pressure 50 bar. [on SciFinder(R)]
Keywords: dialkyl carbonate manufg oxidative carbonylation copper contg catalyst

Producing high quality carbide-derived carbon from low quality byproducts stemming from SiC production - Ariyanto, Teguh; Mohd Laziz, Afiq; Gläsel, Jan-Sebastian; Zhang, Guirong; Garbes, Josef; Etzold, Bastian (Chemical Engineering Journal, 2016)
The utilization of carbide-derived carbons (CDCs) in a wide range of applications is obstructed due to relatively high production costs. In this study a possibility to reduce the costs of CDC synthesis by employing low quality SiC byproducts stemming from the ESK process is presented. While the crystallinity and impurity content differs for the different precursor qualities, the resulting CDC materials possess similar textural characteristics and carbon microstructures. Evaluation of intrinsic kinetic data reveals that the low grade precursors react faster during reactive extraction and can be best described by a power law approach. The CDC materials were further investigated with respect to their performance as electrode materials in Electric Double Layer Capacitors (EDLC). All SiC-CDCs display a comparable and excellent specific capacitance of approx. 115Fg-1. The results are demonstrating the promising utilization of CDC materials synthesized from low valuable SiC feedstock.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; ESK process; Kinetic study; Reactive extraction

Production of dispersions with small particle size from commercial indium tin oxide powder for the deposition of highly conductive and transparent films - Mahajeri, Mahdi; Schneider, Andreas; Baum, Marcus; Rechtenwald, T.; Voigt, Michael; Schmidt, Michael; Peukert, Wolfgang (Thin Solid Films, 2012)
Indium tin oxide (ITO) nanoparticle films for applications in printable electronics were prepared by dip-coating. The dispersion conditions (bead size, stabilizer concentration) strongly affect the particle size of the ITO suspensions and consequently determine the surface morphology of the ITO films. Deposition from ethanolic ITO suspensions with an extremely small particle size of 17 nm to 21 nm led to the formation of extremely smooth and spike-free ITO films with a typical root mean square surface roughness of 4.5 nm +/- 0.2 nm and a high optical transparency above 95%. The effect of annealing with forming gas and CO2 laser treatment on the electrical properties of the ITO films was investigated. Annealing with forming gas and CO2 laser treatment led to a temporary increase in the electrical conductivity of the ITO films by up to a factor of 10 and 6, respectively. Specific conductivities of up to 196 S cm(-1) were obtained for our ITO nanoparticle films under optimized conditions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide; Nanoparticles; Suspension; Conductivity; Laser treatment; Forming gas treatment

Production of lactic acid by fermentation and extraction using amines. - Schulze, Joachim; Tietz, Wolfgang; Wasserscheid, Peter; Bösmann, Andreas (2009)
The invention relates to a method for producing and isolating lactic acid, wherein the lactic acid is produced from a base material contg. carbohydrates by fermn. while adding ammonia, and the release of the lactic acid from the ammonia salt of the lactate occurs by adding a mineral acid, and the isolation of the lactic acid occurs by an extn. using an alkylated amine, and extn. preferably occurring at a pH value of 4.0 to 2.0, wherein a multi-phase mixt. is formed, which is split, whereupon the formed phase is either distd. using the lactate salt of the amine, wherein the lactic acid is obtained as a pure product, or the formed phase is thermally decompd. with the lactate salt of the amine, by means of which an oligolactide is obtained, which can be distd., wherein pure dilactide is obtained. The invention further relates to a device, by means of which said method can be carried out. [on SciFinder(R)]
Keywords: lactic acid fermn amine extn

Purity of hydrogen released from the Liquid Organic Hydrogen Carrier compound perhydro dibenzyltoluene by catalytic dehydrogenation - Bulgarin, Alexander; Jorschick, Holger; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2019)
While Liquid Organic Hydrogen Carrier (LOHC) systems offer a very promising way of infrastructure-compatible storage and transport of hydrogen, the hydrogen quality released from charged LOHC compounds by catalytic dehydrogenation has been a surprisingly rarely discussed topic to date. This contribution deals, therefore, with a detailed analysis of the hydrogen purity released from the hydrogen-rich Liquid Organic Hydrogen Carrier compound perhydro dibenzyltoluene (H18-DBT). We demonstrate, that high purity hydrogen (>99.999%) with carbon monoxide levels below 0.2 ppmv can be obtained from the dehydrogenation of H18-DBT if the applied H18-DBT had been carefully pre-dried and pre-purified prior to the dehydrogenation experiment. Indeed, the largest part of relevant impurities to comply with the hydrogen quality standard for fuel cells in road vehicles (ISO 14687-2) was found to originate from water and oxygenate impurities present in the applied, technical LOHC qualities.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Carbon monoxide; Hydrogen storage; LOHC systems; Oxygenates; Water

Quantitative analysis of alpha-D-glucose in an ionic liquid by using infrared spectroscopy - Kiefer, Johannes; Obert, Katharina; Bösmann, Andreas; Seeger, Thomas; Wasserscheid, Peter; Leipertz, Alfred (ChemPhysChem, 2008)
The applicability of infrared (IR) spectroscopy for quantitative concentration measurements in mixtures of carbohydrates and ionic liquids (ILs) is investigated. The compound 1-ethyl-3-methyl-imidazolium acetate, [EMIM][OAc] - an "enzyme-friendly" ionic liquid with great application potential in the dissolution of various biomass - is used as solvent in combination with alpha-D-glucose. Our study establishes a new way to monitor the concentration of sugars in ILs, thus providing a convenient method to follow the kinetics of, for example, enzymatic reactions in [EMIM][OAc]. As a first step; we present the IR spectrum of pure [EMIM][OAc] (this constitutes the first vibrational study of this particular IL). Although numerous lines overlap in the fingerprint region of the spectrum characteristic features can be assigned to the corresponding vibrational modes of both ions. Secondly, we study different mixtures of the IL with alpha-D-glucose (in the concentration range 0-20 mass % glucose) and analyze them by means of IR spectroscopy, followed by computational methods, thus demonstrating the great potential of this spectroscopic technique in quantitative measurements.
Keywords: biotechnology; carbohydrates; ionic liquids; IR spectroscopy; spectroscopic methods

Quantitative measurement of complex substances dissolved in an ionic liquid using IR spectroscopy and chemometrics - Kiefer, Johannes; Bösmann, Andreas; Wasserscheid, Peter (Technisches Messen, 2017)
In the past two decades, ionic liquids have found many applications as solvents for complex solutes. Prominent examples are the dissolution of biomass and carbohydrates as well as catalytically active substances. The chemical analysis of such solutions, however, is still a challenge due to the molecular complexity. In the present work, the use of infrared spectroscopy for quantifying the concentration of different solutes dissolved in an imidazolium-based ionic liquid is investigated. Binary solutions of glucose, cellubiose, and Wilkinson's catalyst in 1-ethyl-3-methylimidazolium acetate are studied as examples. For this purpose, different chemometric approaches (principal component analysis (PCA), partial least-squares regression (PLSR), and principal component regression (PCR)) for analyzing the spectra are tested. Principal component analysis was found to be suitable for classifying the different solutions. Both regression techniques were capable of deriving accurate concentration values. The performance of PLSR was slightly better than that of PCR for the same number of components.
CRIS-Team Scopus Importer:2023-03-29
Keywords: FTIR; Hauptkomponentenanalyse; Konzentrationsbestimmung; Regression

Rare Earth-Promoted Nickel Oxide Nanoparticles as Catalysts for N2O Direct Decomposition - Abu-Zied, Bahaa M.; Bawaked, S. M.; Kosa, S. A.; Schwieger, Wilhelm (Catalysts, 2016)
For this paper, a series of rare earth (Gd, La, Sm) promoted NiO catalysts were prepared by using the microwave-assisted precipitation method and tested for N2O direct decomposition. The obtained solids have been characterized by using various techniques. X-ray diffraction (XRD) results revealed that the incorporation of RE oxides into NiO significantly decreases its crystallite size. Field-emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations indicated that the addition of RE oxides swells the NiO particles yielding particles into a rice-like morphology. N-2 adsorption studies showed a sharp surface area increase as well as mesoporosity development accompanied the RE incorporation. It was found that the RE oxides significantly enhance the NiO activity.
Keywords: greenhouse gas; nitrous oxide; N2O decomposition; promoted-NiO; rare earth oxides

Reactions of a Polyhalide Ionic Liquid with Copper, Silver, and Gold - Lexow, Matthias; May, Benjamin; Taccardi, Nicola; Steinrück, Hans-Peter; Maier, Florian (ChemistryOpen, 2018)
Keywords: ionic liquids; corrosion; photoelectron spectroscopy; metal dissolution; surface analysis

Reactivation strategies for nucleation-inhibited catalyst beds in continuously operated gas-release reactions from liquids - Uhrig, Felix; Solymosi, Thomas; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2023)
In reactions that release gaseous products from liquids, heterogeneous, porous catalysts can be in an active or nucleation-inhibited state as has recently been shown by our group for batch dehydrogenation reactions. This paper investigates this practically highly relevant phenomenon now in a continuous tube reactor for the example of liquid organic hydrogen carrier (LOHC) dehydrogenation. A mechanical stimulus, increase in reaction temperature or decrease in residence time reactivates the inhibited catalyst bed. Furthermore, the experimental results indicate that the dehydrogenation reaction turns into a hydrogenation reaction for thermodynamic reasons as the catalyst bed cools down. Hydrogenation is responsible for the consumption of the gas phase and thus a liquid filling of the pellets, which causes the nucleation-inhibition. Our work reveals new aspects of nucleation-inhibition on catalyst beds and provides insights into the efficient operation of heterogeneous catalytic gas release reactions in which this phenomenon occurs.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Dehydrogenation; LOHC; Nucleation-inhibited catalyst; Reactivation

Reactivity and applications of layered silicates and layered double hydroxides - Selvam, Thangaraj; Inayat, Alexandra; Schwieger, Wilhelm (Dalton Transactions, 2014)
Layered materials, such as layered sodium silicates and layered double hydroxides (LDHs), are well-known for their remarkable adsorption, intercalation and swelling properties. Their tunable interlayers offer an interesting avenue for the fabrication of pillared nanoporous materials, organic-inorganic hybrid materials and catalysts or catalyst supports. This perspective article provides a summary of the reactivity and applications of layered materials including aluminium-free layered sodium silicates (kanemite, ilerite (RUB-18 or octosilicate) and magadiite) and layered double hydroxides (LDHs). Recent developments in the use of layered sodium silicates as precursors for the preparation of various porous, functional and catalytic materials including zeolites, mesoporous materials, pillared layered silicates, organic-inorganic nanocomposites and synthesis of highly dispersed nanoparticles supported on silica are reviewed in detail. Along this perspective, we have attempted to illustrate the reactivity and transformational potential of LDHs in order to deduce the main differences and similarities between these two types of layered materials.

Reactivity of a model SCILL: Influence of co-adsorbed [C2C1Im][OTf] on the dehydrogenation of dimethylamine on Pt(111) - Eschenbacher, Roman; Steffen, Julien; Farrugia, Karl; Taccardi, Nicola; Wasserscheid, Peter; Görling, Andreas; Libuda, Jörg (Surface Science, 2024)
Solid catalysts with ionic liquid layers (SCILLs) are heterogeneous catalysts whose selectivity is significantly improved by the application of a thin coating of an ionic liquid (IL). In this work, we studied the influence of the IL 1-ethyl-3-methyl-imidazolium-trifluormethansulfonate ([C2C1Im][OTf]) on the dehydrogenation of dimethylamine (DMA) on Pt(111) by surface science experiments under ultrahigh vacuum (UHV) conditions. We investigated the growth, thermal stability, and the dehydrogenation reaction of DMA on Pt(111) both in the presence and absence of [C2C1Im][OTf] by time-resolved and temperature-programmed infrared reflection absorption spectroscopy (IRAS) and density functional theory (DFT). We found that pre-adsorbed DMA has a strong influence on the interaction of [C2C1Im][OTf] with the Pt surface. The competition for the same adsorption sites leads to changes in the binding motif and binding angles of the IL. In the presence of the IL, the reaction temperature of DMA is shifted to higher temperature due to the same competition and blocking effects. Thus, the IL leads to an enhanced stability of DMA on the surface and influences the product spectrum of the dehydrogenation reaction at higher temperature.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Catalysis; Dehydrogenation; Infrared spectroscopy; Ionic liquid; SCILL

Reactor for the release of hydrogen from a liquid compound. - Eypasch, Martin; Zenner, Michael; Peters, Willi; Wasserscheid, Peter (2015)
The invention relates to a reactor for releasing hydrogen from a hydrogen-bearing, liq. compd., comprising a reactor vessel, which contains at least one body having a metal support structure, to which metal support structure a solid, highly porous coating is applied, which contains catalytically active substances for the release of hydrogen from the liq., hydrogen-bearing compd. The reactor is characterized in that the body having the metal support structure can be heated by means of Joule self-heating or induction heating. [on SciFinder(R)]
Keywords: reactor hydrogen release liq energy storage compd catalytic dehydrogenation; hydrogen storage release supply tubular reactor heating porous coating

Recommendations for the Production of Silicon Carbide-derived Carbon Based on Intrinsic Kinetic Data - Knorr, Tilman; Strobl, Florian; Glenk, Friedrich; Etzold, Bastian (Chemical Engineering & Technology, 2012)
Recommendations for mode of operation and critical dimensions regarding inner mass transfer limitation were deduced for the technical extraction of silicon from silicon carbide to produce nanoporous carbon (carbide-derived carbon, CDC). The recommendations are based on intrinsic kinetics derived from experimental data and reaction engineering simulation of the transient process (shrinking-core like mechanism). As the reaction takes place at 1000 °C under chlorine atmosphere, kinetic data as well as diffusion coefficients are extracted from integral conversion data in a lab scale reactor. The reaction rate dependency for varying chlorine concentrations is represented best by a Hougen-Watson type rate approach with dissociative adsorption of a reactant. From the experimental data the effective diffusion coefficient of chlorine in the resulting nanoporous carbon could also be derived to 4 · 10–8 m2s–1 at 1000 °C.
EAM Import::2019-03-13

Redox chemistry, solubility, and surface distribution of Pt(II) and Pt(IV) complexes dissolved in ionic liquids - Kolbeck, Claudia; Taccardi, Nicola; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Molecular Liquids, 2014)
An X-ray photoelectron spectroscopy (XPS) study of Pt(II) and Pt(IV) complexes dissolved in ionic liquids (ILs) revealed the occurrence of a rich redox chemistry, which is partly induced by X-ray radiation. Depending on the IL anion either a reduction of Pt(IV) to Pt(II) in the case of ethylsulfate ([EtOSO])-based ILs, or an oxidation of Pt(II) to Pt(IV) in the case of bis[(trifluoromethyl)sulfonyl]imide ([TfN] )-based ILs was observed upon X-ray irradiation. Moreover, surface enrichment or depletion effects of the Pt complexes were deduced from angle-resolved XPS (ARXPS) data; while the Pt complexes dissolved in imidazolium-based ILs tended to deplete from the surface, in pyrrolidinium-based solutions a surface enrichment of the Pt complexes was observed. © 2013 Elsevier B.V. All rights reserved.

Reduction of microkinetic reaction models for reactor optimization exemplified for hydrogen production from methane - Karst, Florian; Maestri, Matteo; Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering Journal, 2015)
Sustainable and efficient processes require optimal design and operating conditions. The determination of optimal process routes, however, is a challenging task. Either the models and underlying chemical reaction rate equations are not able to describe the process in a wide ranges of reaction conditions and thus limit the optimization space, or the models are too complex and numerically challenging to be used in dynamic optimization. To address this problem, in this contribution, a reduction technique for chemical reaction networks is proposed. It focuses on the sensitivity of the reaction kinetic model with respect to the removal of selected reaction steps and evaluates their significance for the prediction of the overall system behavior. The method is demonstrated for a C-1 microkinetic model describing methane conversion to syngas on Rh/Al2O3 as catalyst. The original and the reduced microkinetic model show excellent qualitative and quantitative agreement. Subsequently, the reduced kinetic model is used for the optimization of a methane reformer to produce a hydrogen rich gas mixture as feed for polymer electrolyte membrane (PEM) fuel cell applications. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: Microkinetic modeling; Reactor optimization; Reaction networks; Methane conversion; Process design

Reduction of the heat capacity in low-temperature adsorption chillers using thermally conductive polymers as heat exchangers material - Hinze, Moritz; Ranft, Florian; Drummer, Dietmar; Schwieger, Wilhelm (Energy Conversion and Management, 2017)
Keywords: Adsorption chillers; Fillers; Heat exchangers; Polymers

Regeneration of LOHC dehydrogenation catalysts: In-situ IR spectroscopy on single crystals, model catalysts, and real catalysts from UHV to near ambient pressure - Amende, Maximilian; Kaftan, Andre; Bachmann, Philipp; Brehmer, Richard; Preuster, Patrick; Koch, Marcus; Wasserscheid, Peter; Libuda, Jörg (Applied Surface Science, 2016)
The Liquid Organic Hydrogen Carrier (LOHC) concept offers an efficient route to store hydrogen using organic compounds that are reversibly hydrogenated and dehydrogenated. One important challenge towards application of the LOHC technology at a larger scale is to minimize degradation of Pt-based dehydrogenation catalysts during long-term operation. Herein, we investigate the regeneration of Pt/alumina catalysts poisoned by LOHC degradation. We combine ultrahigh vacuum (UHV) studies on Pt(111), investigations on well-defined Pt/AlO model catalysts, and near-ambient pressure (NAP) measurements on real core-shell Pt/AlO catalyst pellets. The catalysts were purposely poisoned by reaction with the LOHC perhydro-dibenzyltoluene (H18-MSH) and with dicyclohexylmethane (DCHM) as a simpler model compound. We focus on oxidative regeneration under conditions that may be applied in real dehydrogenation reactors. The degree of poisoning and regeneration under oxidative reaction conditions was quantified using CO as a probe molecule and measured by infrared reflection-absorption spectroscopy (IRAS) and diffuse reflectance Fourier transform IR spectroscopy (DRIFTS) for planar model systems and real catalysts, respectively. We find that regeneration strongly depends on the composition of the catalyst surface. While the clean surface of a poisoned Pt(111) single crystal is fully restored upon thermal treatment in oxygen up to 700 K, contaminated Pt/AlO model catalyst and core-shell pellet were only partially restored under the applied reaction conditions. Whereas partial regeneration on facet-like sites on supported catalysts is more facile than on Pt(111), carbonaceous deposits adsorbed at low-coordinated defect sites impede full regeneration of the Pt/AlO catalysts.
Keywords: Infrared spectroscopy; Liquid Organic Hydrogen Carrier; Materials gap; Model catalysis; Pressure gap; Real catalysis

Reliability of liquid organic hydrogen carrier-based energy storage in a mobility application - Uhrig, Felix; Kadar, Julian; Müller, Karsten (Energy Science and Engineering, 2020)
Liquid organic hydrogen carriers (LOHC) are a technology that allows storing hydrogen in a safe and dense manner by reversible chemical conversion. They constitute a very promising option for energy storage, transport, and release combined with electric power generation by fuel cells in large-scale applications like trains. In order to establish trains running on LOHC, it is mandatory to ensure the reliability of the system. This study evaluates various system configurations concerning reliability and resilience. The fault tree analysis method has been used to quantify the probability of failure. The S-P matrix was applied to assess the different failure modes in context of severity as well as their probability. The MTTF of the system can be more than doubled by introducing single redundancy for the fuel cell and the reactor, while more than two redundant components diminish the positive effect on reliability due to higher complexity. It is estimated that the systems full functionality is available for more than 97% of its operating time.
CRIS-Team Scopus Importer:2020-02-18
Keywords: energy system analysis; hydrogen storage; resilience; risk assessment

Renewable superabsorbent polymers (bio-SAP) enabled by renewable acrylic acid (bio-AA), produced via the dehydration of lactic acid or its derivatives - Collians, Dimitris; Godlewski, Jane; Velasquez, Juan; Dziezok, Peter; Kehrer, Matthias; Nagengast, Jens; Kadar, Julian; Taccardi, Nicola; Albert, Jakob; Wasserscheid, Peter (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2020-05-02

Repulsive Osmotic Delamination: 1D Dissolution of 2D Materials - Dudko, Volodymyr; Khoruzhenko, Olena; Weiss, Sebastian; Daab, Matthias; Loch, Patrick; Schwieger, Wilhelm; Breu, Josef (Advanced Materials Technologies, 2022)
2D materials have proved their potential in nearly every area of material science and chemistry. Unfortunately, large-scale production of nanosheets is not straightforward. Current methods suffer from low yield, uncontrollable defects, and requires a high-energy input. There is always a tradeoff between high quality and high yield. In this review, the alternative is highlighted to existing methods of 2D nanosheet production - 1D dissolution, historically known as osmotic swelling. As a thermodynamically driven, and therefore spontaneous, process it provides numerous benefits such as high aspect ratio and defect-free nanosheets with a quantitative yield. In this review, the theory behind this process is discussed, compare it with the existing methods, and highlight the key features that allow to extend 1D dissolution to different charged layered materials. Moreover, the applications in which nanosheets obtained by 1D dissolution proved to be advantageous due to their unique, processing-related features are discussed.
CRIS-Team WoS Importer:2022-11-25

Resilience of LOHC Based Energy Storage Systems - Rüde, Timo; Bösmann, Andreas; Preuster, Patrick; Wasserscheid, Peter; Arlt, Wolfgang; Müller, Karsten (Energy Technology, 2017)

Revealing the influence of the strength of coulomb interactions on the viscosity and interfacial tension of ionic liquid cosolvent mixtures - Fröba, Andreas Paul; Wasserscheid, Peter; Gerhard, Dirk; Kremer, Heiko; Leipertz, Alfred (Journal of Physical Chemistry B, 2007)
Within this work, viscosity and interfacial tension of selected ionic liquid cosolvent mixtures, [EMIM] [EtOSO(3)] (1-ethyl-3-methyl-immidazolium ethyl sulfate) with water and ethanol, were studied as a function of composition by surface light scattering (SLS) and the pendant drop method in a consistent manner, allowing a close insight into the nature of interactions. Here, we show that the viscosity behavior clearly reflects the bulk structure of the ionic liquid cosolvent mixtures and correlates to the fluid structure at the phase boundary. In contrast to former work, we found the viscosity of ionic liquid [EMIM][EtOSO(3)] to be decreasing the stronger by small amounts of the cosolvents and the lower their dielectric constant. Furthermore, two distinct trends for the dependence of the viscosity on the cosolvent concentration were resolved. These were assigned to ion-dipole interactions dominating in the salt-rich region and to dipole-dipole interactions in the diluted one. A crossover between both regions is reflected by the interfacial tension data, where it seems that up to a "critical" concentration almost no cosolvent is present at the phase boundary.

Reversible thermally induced phase transition in ordered domains of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin on Cu(111) - Steinrück, Hans-Peter; Stark, Michael Werner; Ditze, Stefanie; Thomann, Michael; Lungerich, Dominik; Jux, Norbert; Marbach, Hubertus (Surface Science, 2016)
We investigated the adsorption behavior of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin (CoTTBPP) on Cu(111) by scanning tunneling microscopy (STM). At room temperature (RT), the coverage dependent adsorption behavior follows an expected scheme: at low coverage step decoration is found, which evolves into supramolecular domains with a hexagonal order at higher coverage. Interestingly, upon cooling the sample to 180 K the occurrence of a clearly distinguishable coexisting herringbone phase is observed. Upon heating to RT again, the herringbone phase vanishes. Thus a temperature dependent, fully reversible phase transition was observed. High resolution STM micrographs allow for the determination of the intramolecular conformations which are different for the two supramolecular arrangements. In addition, we studied the bias voltage dependent appearance of the molecule in STM and assigned a dominant contribution of the central Co at negative bias voltages close to the Fermi edge to the occupied d orbital. Interestingly, the herringbone phase, which dominates at 180 K, exhibits a significantly higher molecular density than the monomodal hexagonal arrangement at RT, which is in line with the "normal" behavior of freezing substances.
Keywords: Bias voltage dependence; Intramolecular conformation; Porphyrin; Reversible phase transition; Scanning tunneling microscopy; Self-assembly

Review on the food technological potentials of gas hydrate technology - Claßen, Timo; Seidl, Pia; Loekman, Soebiakto; Rauh, Cornelia; Delgado, Antonio; Gatternig, Bernhard (Current Opinion in Food Science, 2019)
Gas hydrate technology has been known for a long time, but has only recently gained interest in food technology field. A major advantage for food technology applications are the gentle conditions under which products can be refined using gas hydrates, therefor not altering or damaging valuable product contents. This review discusses recent developments of hydrate applications for different areas of food technology for example concentration and purification processes, the preservation of foodstuff as well as novel product designs.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Gashydrate; Lebensmitteltechnologie; Fruchsaftkonzentration

Rhodium-Phosphite SILP Catalysis for the Highly Selective Hydroformylation of Mixed C4 Feedstocks - Jakuttis, Michael; Schönweiz, Andreas; Werner, Sebastian; Franke, Robert; Wiese, Klaus-Diether; Haumann, Marco; Wasserscheid, Peter (Angewandte Chemie International Edition, 2011)
The cat. that got the butene: Highly active and selective diphosphite ligands are applied for rhodium-catalyzed supported ionic liquid phase (SILP) hydroformylation and make it possible to form linear n-pentanal with exceptional selectivity from a mixed butene feedstock by combined isomerization and hydroformylation (see picture, vials 1–4 show typical SILP catalysts employed in this study.). The SILP catalyst is stable for more than 800h on stream.

Rigorous design of multiphase reactors: Identification of optimal conditions for mass transfer limited reactions - Xie, Mingquan; Freund, Hannsjörg (Chemical Engineering and Processing, 2018)
Multiphase reaction systems are often complex due to the interaction of reaction and transport processes. To design optimal reactors for such systems, a rigorous optimization is necessary. In this regard, this work proposes extensions of a reactor design methodology based on rigorous optimization. Each phase is represented by one fluid element, subject to different mass and energy fluxes. While the unlimited external fluxes are optimally provided along the reaction route, sensitivity analysis of the parameters related to the limited external fluxes is performed. The extended methodology is applied in the reactor design for chemical absorption of CO2 as an example for complex multiphase reaction systems with severe mass transfer limitation. An accurate model which is also numerically suitable for optimization has been set up and validated with pilot plant data from literature. Optimal temperature profiles which result from balancing the different temperature-dependent phenomena are identified for cases with different inlet conditions, and tailor-made heat control strategies are shown for these cases. The potential of the developments in improving mass transfer rates by, e.g., structural design or solvent design has been quantified. This model-based design methodology is generally applicable to different multiphase reaction systems with severe mass transfer limitation.
Keywords: Reactor design; Multiphase system; Mass transfer; Carbon dioxide; Chemical absorption; Process intensification

Role of CO in the Water-Induced Formation of Cobalt Oxide in a High Conversion Fischer-Tropsch Environment - Wolf, Moritz; Mutuma, Bridget; Coville, Neil; Fischer, Nico; Claeys, Michael (ACS Catalysis, 2018)
Keywords: carbon monoxide; Fischer-Tropsch synthesis; magnetometer; cobalt catalyst; deactivation; oxidation; water

Ru-Doped Wells–Dawson Polyoxometalate as Efficient Catalyst for Glycerol Hydrogenolysis to Propanediols - Modvig, Amalie; Kumpidet, Chiraphat; Riisager, Anders; Albert, Jakob (Materials, 2019)
Keywords: Wells-Dawson polyoxometalate; ruthenium; characterization; hydrogenolysis; glycerol

Scale-Bridging 3D Analysis of Micro-/Macroporous Zeolite Particles Using X-Ray Nano-Tomography and Electron Tomography - Apeleo Zubiri, Benjamin; Weissenberger, Tobias; Przybilla, Thomas; Wirth, Janis; Englisch, Silvan; Drobek, Dominik; Schwieger, Wilhelm; Spiecker, Erdmann (Cambridge University Press, 2019)

Scale-Bridging 3D Analysis of Micro-/Macroporous Zeolite Particles Using X-Ray Nano-Tomography and Electron Tomography - Apeleo Zubiri, Benjamin; Weissenberger, Tobias; Przybilla, Thomas; Wirth, Janis; Englisch, Silvan; Drobek, Dominik; Schwieger, Wilhelm; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

Scale-up of the Synthesis of Zeolitic Imidazolate Framework ZIF-4 - Hovestadt, Maximilian; Vargas Schmitz, Jürgen; Weissenberger, Tobias; Reif, Florian; Kaspereit, Malte; Schwieger, Wilhelm; Hartmann, Martin (Chemie Ingenieur Technik, 2017)
A new synthesis route for the zeolitic imidazolate framework ZIF-4 is reported. About 200 g of ZIF-4 are prepared by sonothermal synthesis from ZnO at room temperature. The ZIF-4 prepared by sonothermal synthesis is comparable to the ZIF-4 synthesized by the pathway reported in literature with respect to the powder X-ray diffraction pattern, particle size, and separation potential for olefin-paraffin gas mixtures. Moreover, the separation potential of ZIF-4 is compared to commercial adsorbents like carbon molecular sieves and zeolites.
Keywords: Adsorption; Ethylen; Porosity; Ultrasound-assisted synthesis

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

SCR and NO oxidation over Fe-ZSM-5 - The influence of the Fe content - Ellmers, Inga; Velez, Roxana Perez; Bentrup, Ursula; Schwieger, Wilhelm; Brückner, Angelika; Gruenert, Wolfgang (Catalysis Today, 2015)
Fe-ZSM-5 catalysts (Si/Alin ZSM-5-14) were prepared by different routes and used for an investigation of relations between normalized reaction rates (rates per Fe atom present) and Fe content in reactions relevant for NO abatement by selective catalytic reduction (SCR) with NH3: standard SCR, fast SCR, and NO oxidation. Samples were characterized by XRD, ex situ UV-vis and EPR spectroscopy. In standard SCR, normalized reaction rates increased with Fe content to a maximum around 0.5 wt.% (Fe/Al approximate to 0.07) and decreased at further growing Fe loading. This suggests the existence of Fe sites of different activity, which we identify with isolated Fe3+ sites (on alpha and/or beta cation positions, lower activity) and Fe3+ in small oligomeric structures (higher activity) on the basis of our characterization data and recent results from operando-EPR experiments (Perez Velez et al., 2014). The decay with further increasing Fe loading is assigned to Fe being included in more aggregated structures. Normalized reaction rates of NO oxidation to NO2 decrease from very small Fe contents on, which indicates that NO oxidation is catalyzed by a small minority of Fe sites, most likely by a variety of isolated sites, in strong contrast to standard SCR. Normalized reaction rates for fast SCR are difficult to establish due to complexity and high rate of the reaction. The results suggest, however, that fast SCR proceeds on a small minority of Fe sites as well, in agreement with our recent operando EPR and Moessbauer studies (Perez Velez et al., 2014). Fast SCR proceeds also in absence of Fe, but rates are inferior and easily exceeded even by contributions arising from Fe impurities usually present in technical zeolites. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: DeNO(x); Fe-ZSM-5; Active sites; Standard SCR; Fast SCR; NO oxidation

Screening of catalysts for the catalytic cracking of lignite - Seitz, Mathias; Nowak, Sascha; Welscher, Julia; Zimmermann, Jens; Nägler, Thomas; Stam-Creutz, Timo; Frank, Willy; Schwieger, Wilhelm (Chemie Ingenieur Technik, 2013)
Different processes were developed in the past to use lignite for chemical production. One of them is pyrolysis. In this work a new approach was investigated where the catalyst comes in contact directly with the lignite. Aliphatic components of the lignite can be cracked and olefins and aromatics can be formed. A catalyst screening shows that zeolites can be used for this purpose. A suitable catalyst with similar behavior can be crystallized on a carrier to improve the separation from coke residues. © 2013 Wiley-VCH Verlag GmbH & Co. KGaA.
Keywords: Catalysis; Hydrocarbon; Lignite; Pyrolysis; Zeolite

Screening of Ionic Liquid/H2O Working Pairs for Application in Low Temperature Driven Sorption Heat Pump Systems - Popp, Sabine; Bösmann, Andreas; Woelfel, Rene; Wasserscheid, Peter (ACS Sustainable Chemistry & Engineering, 2015)
Due to the known corrosion and crystallization issues of LiBr/H2O, the state-of-the-art working pair in sorption heat pump (SHP) systems, research into alternative working pairs is of high practical relevance. We have studied a wide range of ionic liquids (ILs) for this application in order to find potential new systems with enhanced performance. The screening was conducted with a focus on vapor pressure measurements of, in total, 74 examined working pairs. As common vapor liquid-equilibrium measurements are very precise but rather time-consuming, we developed a new setup allowing a fast relative determination of humidities with very small sample volumes for screening purposes. By this method we identified seventeen IL/H2O working pairs fulfilling the technical relevant criterion of a water vapor pressure p(H2O) <= 10 mbar at T = 308 K with an IL content of less than 80 wt % (wm < 0.8). Further evaluation of these candidates with respect to their thermal stability and viscosity allowed us to identify [MMIM][HCOO]/H2O, [MIVIIM][OAc]/H2O, [M.MININC2H5COO]/H2O, [Me4N][HCOO]/H2O, [Me4N][OAc]/ H2O and [Me4N] [C2H5COO]/H2O as the most promising IL/H2O systems for a possible application in SHP systems.
Keywords: Ionic liquid; Sorption heat pump; Vapor pressure; Thermal stability

Screening of Supported Ionic Liquid Phase (SILP) catalysts for the very low temperature water–gas-shift reaction - Werner, Sebastian; Szesni, Normen; Bittermann, Agnes; Schneider, Martin; Härter, Peter; Haumann, Marco; Wasserscheid, Peter (Applied Catalysis A-General, 2010)
Screening of transition metal complexes typically involves elaborative experiments in batch reactors in organic solvents under non-steady-state conditions. In contrast, screening of immobilized catalysts in a fixed-bed continuous gas-phase reactor enables highly efficient and precise investigations on activity and stability under steady-state. In this work we present a technique to immobilize numerous homogeneous transition metal complexes (Ru, Ir, Os, Fe, Cu, Mo, Pd Re, Rh) in the ionic liquid [BMMIM][OTf] on the highly porous support Silica 100 using the Supported Ionic Liquid Phase (SILP) technology. All prepared SILP catalysts were investigated in the water–gas shift reaction (WGSR) in a continuously operated fixed-bed reactor at temperatures between 120 and 160 °C and ambient pressure. Best activities and stabilities were found for ruthenium-based systems.

Seasonal storage and alternative carriers: A flexible hydrogen supply chain model - Reuß, Markus; Grube, Thomas; Robinius, Martin; Preuster, Patrick; Wasserscheid, Peter; Stolten, Detlef (Applied Energy, 2017)
Keywords: FCEV; Hydrogen; Hydrogen infrastructure; LOHC; Renewable energies; Seasonal storage

Selecting an Appropriate Computational Platform for Supporting the Development of New Catalyst Carriers - Zeiser, Thomas; Hager, Georg; Wellein, Gerhard; Inayat, Amer; Schwieger, Wilhelm; Heidig, Tobias; Freund, Hannsjörg (Innovatives Supercomputing in Deutschland : inSiDE, 2009)
UnivIS-Import:2015-03-09:Pub.2009.tech.IMMD.phleir._selec

Selection of entrainers in the 1-hexene/n-hexane system with a limited solubility - Lei, Zhigang; Arlt, Wolfgang; Wasserscheid, Peter (Fluid Phase Equilibria, 2007)
Vapor-liquid equilibria (VLE) have been measured for five 1-hexene/n-hexane/ionic liquid systems and 1-hexene/n-hexane/NMP (N-methyl-2-pyrrolidone) system with a headspace-gas chromatography (HSGC) apparatus at 333.15 K. The ionic liquids investigated were 1,3-dimethylimidazolium tetrafluoroborate [CMIM][BF], 1-butyl-3-methylimidazolium tetrafluoroborate [CMIM][BF], 1-methyl-3-octylimidazolium tetrafluoroborate [CMIM][BF], 1,3-dimethylimidazolium dicyanamide [CMIM][N(CN)] and 1-octylquinolinium bis(trifluoromethylsulfonyl)amide [CChin][BTA]. It was found that at low feeding concentration of 1-hexene and n-hexane, the separation ability of ionic liquids is in the order of [CMIM][BF] > [CMIM][BF] ≈ [CMIM][N(CN)] > [CMIM][BF] > [CChin][BTA], which is consistent with the priori prediction of the COSMO-RS (conductor-like screening model for real solvents) model. But at high feeding concentration, the separation ability of ionic liquids is in the order of [CMIM][BF] < [CMIM][BF] ≈ [CMIM][N(CN)] < [CMIM][BF] < [CChin][BTA]. The liquid demixing effect should be taken into account. The activity coefficients of 1-hexene and n-hexane at infinite dilution calculated with the COSMO-RS model were correlated using the NRTL, Wilson and UNIQUAC model. In this work the predictive results from the COSMO-RS model and UNIFAC model for the 1-hexene/n-hexane and 1-hexene/n-hexane/NMP systems were compared. The UNIFAC model is one of the most important academic contributions by Prof. Jürgen Gmehling. © 2006 Elsevier B.V. All rights reserved.
Keywords: 1-Hexene/n-hexane; COSMO-RS model; Ionic liquids; Selectivity; UNIFAC model; Vapor-liquid equilibria (VLE)

Selective catalytic conversion of biobased carbohydrates to formic acid using molecular oxygen - Woelfel, Rene; Taccardi, Nicola; Bösmann, Andreas; Wasserscheid, Peter (Green Chemistry, 2011)
A new and straightforward method to transform carbohydrate-based biomass to formic acid (FA) by oxidation with molecular oxygen in aqueous solution using a Keggin-type H5PV2Mo10O40 polyoxometalate as catalyst is presented. Several water-soluble carbohydrates were fully and selectively converted to formic acid and CO2 under very mild conditions. It is worth noting, even complex biomass mixtures, such as poplar wood sawdust, were transformed to formic acid, giving 19 wt% yield (11% based on the carbon atoms in the feedstock) under non-optimized conditions.

Selective catalytic hydrogenation of biomass derived furans to secondary alcohols using Pt/polyoxometalate catalysts under mild reaction conditions - Sherbi, Magdy; Stuckart, Maria; Albert, Jakob (Biofuels Bioproducts & Biorefining-Biofpr, 2021)
Promising bifunctional catalyst systems composed of platinum and polyoxometalates (POMs) were applied successfully for the selective catalytic hydrogenation of 2,5-dimethylfuran (DMF) to 2-hexanol under mild conditions. Pt(acac)2 was found to be the most active Pt precursor for the ring opening of DMF, and the Keggin-type POM K3[PW12O40] was identified as the most promoting acidic support for 2-hexanol formation at 80 °C and 10 bar H2 pressure using n-decane as a carrier liquid. It was revealed that modifications in the synthetic procedure of the Pt/K3[PW12O40] catalytic system allowed its catalytic performance to be enhanced. Thus, a higher yield of 2-hexanol (72.5%) was achieved compared to that (49%) obtained using a commercial Pt/C catalyst with the same Pt loading. The Wells–Dawson-type POM containing catalyst Pt/K6[α-P2W18O62] was found to be selective for 2-hexanon formation (56.4% yield) under identical reaction conditions. Furthermore, furan and 2-methylfuran were also selectively hydrogenated to 1-butanol (59.7% yield) and 1/2-pentanol (44.3% yield), respectively, under the applied reaction conditions. Moreover, using analytical tools like N2-physisorption, NH3-TPD, inductively coupled plasma optical emission spectroscopy (ICP-OES), CO chemisorption, and transmission electron microscopy (TEM), revealed that the higher total acid site density of the K3[PW12O40] enhances C=O hydrogenation and overcomes the rate-limiting step of 2-hexanone hydrogenation to 2-hexanol. This demonstrates the high performance of the bi-functional catalyst system Pt/K3[PW12O40] towards ring opening of various furans and the very high selectivity towards alcohol formation. This approach opens new interesting valorization pathways for several furanic compounds with respect to sustainable alcohol formation. © 2021 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.
CRIS-Team Scopus Importer:2021-06-11
Keywords: 2; 5-dimethylfuran; 2-hexanol; alcohol formation; polyoxometalates; ring opening; selective catalytic hydrogenation

Selective catalytic oxidation of humins to low-chain carboxylic acids with tailor-made polyoxometalate catalysts - Maerten, Stephanie; Voß, Dorothea; Liauw, Marcel; Albert, Jakob (ChemistrySelect, 2017)
For the first time, a selective catalytic conversion of thermally induced side products (humins) from biomass valorization to short-chain carboxylic acids like formic acid and acetic acid is reported. Very interestingly, we found that homogeneous polyoxometalate catalysts could selectively oxidize humins from sugar-derived levulinic acid production to formic acid and acetic acid under very mild conditions in a simple monophasic aqueous approach. This green and sustainable process offers a very cost-effective and sustainable way for the conversion of undesired humins and benefits from its low reaction temperature (90-120 °C) and its tunable product distribution. By variation of process parameters and chemical composition of the POM structures, we could control both product selectivity and humin conversion. Furthermore, catalyst recycling over three batches has been successfully carried out.

Selective laser sintering of zeolite filled polypropylene composites: Processing and properties of bulk adsorbents - Wudy, Katrin; Hinze, Moritz; Ranft, Florian; Drummer, Dietmar; Schwieger, Wilhelm (Journal of Materials Processing Technology, 2017)
UnivIS-Import:2017-07-10:Pub.2017.tech.FT.FT-KT.select
Keywords: Additive manufacturing; Composite materials; Polypropylene; Selective laser sintering; Water adsorption; Zeolite

Selective oxidation of complex, water-insoluble biomass to formic acid using additives as reaction accelerators - Albert, Jakob; Woelfel, Rene; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2012)
The oxidation of complex, water-insoluble biomass to formic acid is reported using a Keggin-type polyoxometalate (H5PV2Mo10O40) as the homogeneous catalyst, oxygen as the oxidant, water as the solvent and p-toluenesulfonic acid as the best additive. The reaction proceeds at 90 degrees C and 30 bar O-2 and transforms feedstock like wood, waste paper, or even cyanobacteria to formic acid and CO2 as the sole products. The reaction obtains up to 53% yield in formic acid for xylan as the feedstock within 24 h. Besides the role of the additive as a reaction promoter, the formic acid isolation and the recycling of catalyst and additive are demonstrated.

Selective oxidation of cyclohexanol to cyclohexanone in the ionic liquid 1-octyl-3-methylimidazolium chloride - Chen, Long; Zhou, Teng; Chen, Lifang; Ye, Yinmei; Qi, Zhiwen; Freund, Hannsjörg; Sundmacher, Kai (Chemical Communications, 2011)
Ionic liquid (IL) 1-octyl-3-methylimidazolium chloride was found to effectively intensify cyclohexanol oxidation and resulted in 100% conversion of cyclohexanol with 100% selectivity to cyclohexanone using hydrogen peroxide as an oxidant and WO(3) as a catalyst. The effect of the IL as a solvent is discussed with the support of COSMO-RS theory.

Selective oxidation of lignocellulosic biomass to formic acid and high-grade cellulose with tailor-made polyoxometalate catalysts - Albert, Jakob (Faraday Discussions, 2017)
The main goal of this project was to identify and to optimize tailor-made polyoxometalate catalysts for a fractionated oxidation of lignocellulosic biomass (i.e. wood and residues from sugar or paper industries) to produce formic acid (FA) and high-grade cellulose for further processing i.e. in white biotechnology to bio-ethanol. Homogeneous vanadium precursor like sodium metavanadate and vanadyl sulfate as well as Keggin-type polyoxometalates (POMs) and more exotic structures like Anderson-, Wells-Dawson and Lindqvist type POMs have been screened for the desired catalytic performance. The most promising behaviour was found using the Lindqvist-type POM K5V3W3O19 showing for the first time in literature a selective oxidation of solely hemicellulose and lignin to formic acid while the cellulose fraction was untrapped. However, this could be only a first step for the project goal as little product yields could be achieved.
EAM Import::2019-03-13

Selectivity enhancement in the catalytic hydrogenation of propionitrile using ionic liquid multiphase reaction systems - Obert, Katharina; Roth, Daniel; Ehrig, Martin; Schönweiz, Andreas; Assenbaum, Daniel; Lange, Harald; Wasserscheid, Peter (Applied Catalysis A-General, 2009)
A new ionic liquid based, multiphase reaction system was investigated for the catalytic hydrogenation of propionitrile. The reaction system under investigation consisted of a solid heterogeneous Ru-catalyst (Ru on carbon), two liquid phases and the hydrogen gas-phase. By using two liquid phases in the reactor – of which one was an ionic liquid – it was possible to improve significantly the selectivity for the formation of propylamine by suppressing consecutive reactions to dipropylamine and tripropylamine. This enhanced selectivity resulted either from the protonation of the primary formed amine (in case of the Brønsted acidic ionic liquids dimethylcyclohexylammonium hydrogensulfate and 1-butylimidazolium hydrogensulfate) or from the extraction of the primary amine into the organic phase (in case of a 1-ethyl-3-methylimidazolium ethylsulfate/1,2,4-trichlorobenzene biphasic system).

Sensing alterations of the local environment of 3d, 4d, and 4f central ions in polyoxopalladates with soft X-ray magnetic dichroisms - Schmitz-Antoniak, Carolin; Izarova, Natalya; Stuckart, Maria; Smekhova, Alevtina; Schmitz, Detlef; Shams, S. Fatemeh; Siemensmeyer, Konrad; Giesen, Margret; Koegerler, Paul (Journal of Magnetism and Magnetic Materials, 2020)
Polyoxopalladates hosting 3d, 4d or 4f central ions form a new class of molecular materials with well-defined, tunable morphology and ions coordination to be considered as model systems for basic research. We investigated the isotropic X-ray absorption near-edge structure (XANES), X-ray magnetic circular dichroism (XMCD), and X-ray magnetic linear dichroism (XMLD) to monitor the influence of symmetry changes on electronic and magnetic properties. After a brief introductory review about recent results on 3d and 4d transition metal ions, we (i) show that a change of the coordination symmetry from cubic eightfold (tetrahedral) to sixfold (octahedral) reduces the magnetic moment of Co2+ significantly and (ii) investigate whether axial distortions can modify the 4f states of trivalent lanthanide ions. While for Gd3+ there is no effect visible within experimental uncertainties, changes were observed for Dy3+ and Ho3+. The results are compared to atomic multiples calculations including the intraatomic spin-dipole term < T-z >. Furthermore, several experimental pitfalls are discussed that may lead to misinterpretation of X-ray absorption data but can be excluded in the present study.
CRIS-Team WoS Importer:2020-10-16

Sensitivity Analysis and Parameter Optimization for the Fractionative Catalytic Conversion of Lignocellulosic Biomass in the Polyoxometalate-lonosolv Concept - Bukowski, Anna; Schnepf, Kristin; Wesinger, Stefanie; Brandt-Talbot, Agnieszka; Albert, Jakob (ACS Sustainable Chemistry & Engineering, 2022)
The recently developed polyoxometalate (POM)-ionosolv concept offers an interesting strategy to generate two valuable product streams from lignocellulosic biomass, a solid cellulose-rich pulp and short-chain carboxylic acids like formic acid and acetic acid in a simple and cost-efficient manner. This study aimed to find optimum parameters for the two steps of the transformation by performing a sensitivity analysis on the initial ionosolv fractionation step as well as kinetic investigations of the following POM-catalyzed oxidation step. The results were transferred to the POM-ionosolv concept to find the overall process optimum. Beech wood was used as an industrially relevant substrate for ionosolv fractionation with the low-cost ionic liquid triethylammonium sulfate, [TEA][HSO4], and the HPA-5 [H8PV5Mo7O40] POM catalyst for the oxidation of the dissolved components in an oxygen atmosphere. As the most seminal finding, we defined optimum conditions of 125 degrees C, 1200 rpm, 30 bar oxygen, and 24 h reaction time in ionic liquid containing 70% water, achieving 72% xylose extraction from beech wood, which resulted in a 39% formic acid yield. We suggest that the fractionation and catalytic conversion are carried out at different water contents for maximum conversion efficiency for each step.
CRIS-Team WoS Importer:2022-07-08
Keywords: Lignocellulose; Fractionation; Ionic liquid; Polyoxometalate; Formic acid; Cellulose

Sequential Template Decomposition to Adjust the Performance of Imperfect Zeolite BEA Membranes - Reuß, Stephanie; Reif, Benjamin; Sanwald, Dirk; Schwieger, Wilhelm; Kaspereit, Malte; Singh, Puyam S.; Al-Thabaiti, Shaeel A.; Basahel, Sulaiman N.; Mokhtar, Mohamed; Obaid, Abdullah Y.; Alyoubi, Abdulrahman O. (Chemie Ingenieur Technik, 2019)
Zeolite membranes offer superior thermal, chemical, and mechanical stability compared to polymeric membranes. However, it is still a challenge to prepare completely defect-free membranes without any intercrystalline voids, which is necessary for gas separation processes. In this study zeolite beta (*BEA) membranes on stainless-steel supports were prepared by applying the multiple in situ crystallization technique. The membranes were used as a model system to systematically study the decomposition of the organic structure directing agent tetraethylammoniumhydroxide (TEA-OH). It was evaluated if the organic decomposition products of TEA-OH can be used for enhancing the membranes selectivity. Post-treatment experiments have been carried out to adjust surface properties and pore size dimensions in the zeolitic membrane layer. The results show that membranes calcined at lower temperatures exhibit a higher gas selectivity.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Gas separation; Template decomposition; Zeolite BEA membrane

Shifting the equilibrium of methanol synthesis from CO2 by in situ absorption using ionic liquid media - Reichert, Jenny; Maerten, Stephanie; Meltzer, Katharina; Tremel, Alexander; Baldauf, Manfred; Wasserscheid, Peter; Albert, Jakob (Sustainable Energy & Fuels, 2019)

Shining light on low-temperature methanol aqueous-phase reforming using homogeneous Ru-pincer complexes – operando Raman-GC studies - Strobel, Vinzent; Schuster, Julian; Bräuer, Andreas; Vogt, Lydia; Junge, Henrik; Haumann, Marco (Reaction Chemistry & Engineering, 2017)

Shrinking core like fluid solid reactions-A dispersion model accounting for fluid phase volume change and solid phase particle size distributions - Knorr, Tilman; Kaiser, Markus; Glenk, Friedrich; Etzold, Bastian (Chemical Engineering Science, 2012)
A mathematical model is derived for the shrinking core like conversion of solids in a reacting fluid. As a technical example for this type of reaction the model is used to evaluate kinetic experiments on the production of carbide-derived carbon from silicon carbide. Therefore the simultaneous influence of reaction as well as diffusion is combined with the residence time behaviour of the reactor (tubular reactor), the non-constant gas phase volume over the extent of reaction and the particle size distribution of the solid substrate. The derived model is validated for accuracy against known solutions of boarder cases (e.g. shrinking core model of a single sphere, fluid phase volume change without dispersion or shrinking core and limitation by reactant feed).
EAM Import::2019-03-13

Silica monoliths with hierarchical porosity obtained from porous glasses - Inayat, Alexandra; Reinhardt, Björn; Uhlig, Hans; Einicke, Wolf-Dietrich; Enke, Dirk (Chemical Society Reviews, 2013)
This review deals with “classical” porous glasses which are prepared by physical phase separation of alkali borosilicate glasses of suitable composition in combination with selective leaching. The resulting materials are characterized by a controllable pore size in the nanometer range, high mechanical, thermal and chemical stability and an adjustable macroscopic shape, which enables manufacturing of glass monoliths with various geometries. As a result of their formation, porous glasses obtained from physical phase separation exhibit a monomodal pore structure. There are only a few examples in the literature for the synthesis of hierarchically porous glasses. This review covers several synthesis strategies for the introduction of hierarchy into “classical” porous glass monoliths, including sintering and fusion of alkali borosilicate initial glasses as well as partial or complete pseudomorphic transformation of porous glasses into zeolites or ordered mesoporous material

Silicon Carbide Supported Liquid Phase (SLP) Hydroformylation Catalysis – Effective Reaction Kinetics from Continuous Gas-phase Operation - Schörner, Markus; Mitländer, Kerstin; Wolf, Moritz; Franke, Robert; Haumann, Marco (ChemCatChem, 2022)
The hydroformylation reaction is one of the most important applications of homogeneous catalysis on an industrial scale with worldwide production capacities exceeding 15 Mio tons per year. Efficient catalyst immobilization becomes mandatory for such large-scale processes. In this work, a supported liquid phase (SLP)-type catalyst on a silicon carbide support material was applied in the continuous Rh-bpp (bpp=biphephos) catalyzed gas-phase hydroformylation of but-1-ene. A parameter variation was carried out in the pressure range from 0.5 to 3.0 bara for but-1-ene, 0.5 to 5 bara for H2, 0.5 to 5 bara for CO, and in the temperature range from 90 to 125 °C. Activation energies were determined for the individual reactions showing a shift in activation energy most significantly for the hydroformylation to n-pentanal for temperatures of 110 °C and above. For all substrates the effective reaction orders were calculated and employed in a power-law rate model giving good agreement of measured and modeled data within a ±20 % error margin. Similar results were obtained using a microkinetic model.
CRIS-Team Scopus Importer:2022-06-03
Keywords: diphosphite ligand; hydroformylation; immobilization; rhodium; supported catalysts

SILP and SCILL catalysis - Haumann, Marco; Wasserscheid, Peter (Royal Society of Chemistry, 2014)

Silver-containing bioactive glasses for tissue engineering applications - Boccaccini, Aldo R.; Diba, Mani (Elsevier Ltd, 2014)
Bioactive glasses have shown promising results for tissue engineering applications. Specific metallic ions can be used for doping these materials to induce enhanced biological performance. Silver is an element well-known for its antibacterial properties. This chapter present an overview of Ag-doped bioactive glasses including their synthesis, properties and applications in tissue engineering. Moreover, the reported effects of Ag-doping on the properties of bioactive glasses are discussed. © 2014 Elsevier Ltd. All rights reserved.
Keywords: Antibacterial materials; Bioactive glass; Biodegradable materials; Silver; Tissue engineering

Simple and recyclable ionic liquid based system for the selective decomposition of formic acid to hydrogen and carbon dioxide - Berger, Markus; Assenbaum, Daniel; Taccardi, Nicola; Spiecker, Erdmann; Wasserscheid, Peter (Green Chemistry, 2011)
Exploitation of hydrogen as an energy carrier requires the development of systems for its storage and delivery. Formic acid has been proposed as valuable hydrogen carrier compound, due to its relatively high hydrogen content (53 g L-1), the latter being easily and cleanly released in catalytic reactions under mild conditions (HCOOH → H_2 + CO_2). Ionic liquids are interesting solvents for homogeneous catalyzed formic acid decomposition systems as their extremely low volatility avoids solvent contamination of the produced hydrogen stream. In this paper an outstandingly simple, robust and active catalyst system is presented, namely RuCl_3 dissolved in 1-ethyl-2,3-dimethylimidazolium acetate (RuCl_3/[EMMIM][OAc]). This system proved to be fully recyclable over 10 times. Turnover frequencies (TOF) of 150 h-1 and 850 h-1 were obtained at 80 °C and 120 °C, respectively.

Simulation of One-Stage Dimethyl Ether Synthesis over a Core-Shell Catalyst - Ding, Wenjin; Klumpp, Michael; Lee, Seungcheol; Reuß, Stephanie; Al-Thabaiti, Shaeel A.; Pfeifer, Peter; Schwieger, Wilhelm; Dittmeyer, Roland (Chemie Ingenieur Technik, 2015)
A spherical microsized core-shell catalyst (CuO/ZnO/Al2O3@H-ZSM-5) was synthesized for direct dimethyl ether synthesis from syngas in a micro packed bed reactor. To assist in the preparation and optimization of the core-shell catalyst, a 1D heterogeneous model was developed to simulate diffusion and reactions within the catalyst particles. Using the data obtained from the tubular reactor, kinetic parameters for the catalyst were determined first. Furthermore, simulation showed that thickness and activity of shell have significant effect on the catalytic performance of the core-shell catalyst.
Keywords: Core-shell catalyst; Heterogeneous model; Surface diffusion model; Zeolite H-ZSM-5

Simultaneous design of the optimal reaction and process concept for multiphase systems - Hentschel, Benjamin; Peschel, Andreas; Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering Science, 2014)
In complex chemical processes optimizing the reactor with respect to a stand-alone reactor performance criterium such as product selectivity does not necessarily yield the best process-wide reaction concept. Especially in case of multiphase reaction systems, which often involve complex reaction networks, nonideal phase behavior and multiple recycles, reactor and process have to be optimized simultaneously since the reactor affects the separation units and vice versa. In order to derive the process-wide optimal reaction concept in combination with optimal process parameters, a systematic optimization procedure based on a large scale optimization problem constrained by a system of differential algebraic equations (DAE) is presented. The optimization problem contains a detailed model of the reaction section, a process model describing the other units of the process, and models for operational and fixed costs. The solution of the optimization is a set of process parameters and optimal profiles of heat and material fluxes over the reaction coordinate which minimize the production costs. The method is exemplified on the rhodium catalyzed hydroformylation of 1-dodecene in a thermomorphic solvent system. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reactor design; Process design; Simultaneous optimization; Multiphase systems; Hydroformylation; Process economics

Size and structure effects controlling the stability of the liquid organic hydrogen carrier dodecahydro- N -ethylcarbazole during dehydrogenation over pt model catalysts - Amende, Maximilian; Gleichweit, Christoph; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Koch, Marcus; Obesser, Katharina; Papp, Christian; Wasserscheid, Peter; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry Letters, 2014)
Hydrogen can be stored conveniently using so-called liquid organic hydrogen carriers (LOHCs), for example, N-ethylcarbazole (NEC), which can be reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H-NEC). In this study, we focus on the dealkylation of H-NEC, an undesired side reaction, which competes with dehydrogenation. The structural sensivity of dealkylation was studied by high-resolution X-ray photoelectron spectroscopy (HR-XPS) on AlO-supported Pt model catalysts and Pt(111) single crystals. We show that the morphology of the Pt deposit strongly influences LOHC degradation via C-N bond breakage. On smaller, defect-rich Pt particles, the onset of dealkylation is shifted by 90 K to lower temperatures as compared to large, well-shaped particles and well-ordered Pt(111). We attribute these effects to a reduced activation barrier for C-N bond breakage at low-coordinated Pt sites, which are abundant on small Pt aggregates but are rare on large particles and single crystal surfaces. © 2014 American Chemical Society.

Size-controlled PtNi nanoparticles as highly efficient catalyst for hydrodechlorination reactions - Munoz, Macarena; Ponce, Sebastian; Zhang, Guirong; Etzold, Bastian (Applied Catalysis B-Environmental, 2016)
The application of size-controlled PtNi nanoparticles (NPs) as catalyst on the aqueous-phase hydrodechlorination (HDC) of 4-chlorophenol (4-CP) under ambient conditions (25 °C, 1 atm) has been investigated. NPs were synthesized as a co-reduction of both metals following a solvothermal method which allowed a proper control of the PtNi alloyed NP size in the range of 4.4–12.0 nm. To make the active sites of the nanoalloy accessible, the stabilizer poly(N-vinyl-2-pyrrolidone) was removed by washing of the NPs with H2O2/H2SO4. Evaluating the NP structure/composition influence on the activity, a clear synergic effect between Pt and Ni was found. In this sense, complete conversion of 4-CP was achieved in 1 h reaction time with the bimetallic NPs whereas only 70% was reached with the monometallic Pt counterpart (NP size = 12 nm, [Pt] = 80 mg L-1, [4-CP]0 = 78 extgreekmmol L-1). That effect could be related to the higher resistance of PtNi nanoalloy against chlorine poisoning compared to the monometallic Pt. In fact, PtNi NPs showed a remarkable stability and negligible deactivation even after storing the catalyst one month in the reaction mixture, whereas for the monometallic Pt fully deactivation resulted. The structure-sensitivity of HDC with PtNi nanocatalysts was finally confirmed as the catalytic performance was clearly dependent on the size. A volcano plot like behaviour was obtained, being 5.5 nm the optimum size. PtNi-5.5 led to the complete conversion of 4-CP in 15 min at a HDC rate of 3.12 L min-1 gPt-1.
EAM Import::2019-03-13

Size dependent stability of cobalt nanoparticles on silica under high conversion Fischer-Tropsch environment - Wolf, Moritz; Kotzé, H.; Fischer, Nico; Claeys, Michael (Faraday Discussions, 2017)

Slurry Phase Hydrogenation of CO2 to Methanol Using Supported In2O3 Catalysts as Promising Approach for Chemical Energy Storage - Schühle, Patrick; Reichenberger, Sven; Marzun, Galina; Albert, Jakob (Chemie Ingenieur Technik, 2020)
A promising approach for chemical energy storage from fluctuating renewable electricity is methanol synthesis from CO2 and hydrogen in a slurry reactor concept, due to efficient heat storage and easy reactor control. In combination with a promising In2O3/ZrO2 catalyst and mineral oil as carrier liquid, efficient methanol production under a wide range of changing process conditions is shown for the first time. A maximum methanol productivity of 2.1 gMeOHgIn−1h−1 and multiple recycling stability of the catalyst and the carrier liquid was achieved, showing no significant decrease in methanol yields.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Carbon dioxide; Chemical energy storage; Indium catalyst; Methanol; Slurry reaction

Solid oxide fuel cell operating on liquid organic hydrogen carrier-based hydrogen – making full use of heat integration potentials - Preuster, Patrick; Fang, Qingping; Peters, Roland; Deja, Robert; Van Nhu Nguyen,; Blum, Ludger; Stolten, Detlef; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2018)
Our contribution demonstrates the technological potential of coupling Liquid Organic Hydrogen Carrier (LOHC)-based hydrogen storage and hydrogen-based Solid Oxide Fuel Cell (SOFC) operation. As SOFC operation creates waste heat at a temperature level of more than 600 °C, clever heat transfer from the SOFC operation to the LOHC dehydrogenation process is possible and results in an overall efficiency of 45% (electric output of SOFC vs. lower heating value of LOHC-bound hydrogen). Moreover, we demonstrate that LOHC vapour does not harm the operational stability of a typical 150 W SOFC short stack. By operating the stack with LOHC-saturated hydrogen, operation times of more than 10 years have been simulated without noticeable degradation of SOFC performance.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Future energy systems; Heat integration; Hydrogen storage; LOHC; Off-grid energy supply; SOFC

Solid-State NMR Spectroscopic Investigation of TiO2 Grown on Silica Nanoparticles by Solution Atomic Layer Deposition - Ding, Fei; Tavera Méndez, Cindy Ly; Grass, Jan Paul; Crisp, Ryan; Barr, Maissa; Wisser, Dorothea (Advanced Materials Interfaces, 2023)
Atomic layer deposition in solution (sALD) is just emerging as a technology for the preparation of thin films. Unlike ALD from the gas phase, it allows for mild reaction conditions in a solvent phase and at room temperature, thus decreasing the energy requirements of the process and widening the range of accessible precursor molecules. In this work, the deposition of thin films of titania on silica is investigated using titanium(IV) isopropoxide (TTIP) and water as precursors, which are alternatingly brought into contact with the support in a home-built plug flow reactor. The mechanism of covalent grafting of the precursor to the surface, subsequent hydrolysis, and reaction to a layer of titania are investigated in detail using magic angle spinning (MAS) solid-state nuclear magnetic resonance (NMR) spectroscopy. TTIP preferentially reacts with Q2 groups of condensed silica. 2D solid-state NMR spectra allow to clearly show the successful grafting of this compound to the support by the appearance of a characteristic signal at −107 ppm, which is tentatively attributed to silicon nuclei in a Si-O-Ti bond, and to reveal the presence of titanol groups on the emerging TiO2 film.
CRIS-Team Scopus Importer:2023-05-26
Keywords: silica; solid-state NMR spectroscopy; solution atomic layer deposition; titania

Solid-state structures of double-long-chain imidazolium ionic liquids: Influence of anion shape on cation geometry and crystal packing - Wang, Xinjiao; Vogel, Carola; Heinemann, Frank Wilhelm; Wasserscheid, Peter; Meyer, Karsten (Crystal Growth & Design, 2011)
The syntheses and solid-state structures of a series of imidazolium (IM) salt-based, double C alkyl chain functionalized ionic liquids, namely, [CCIM] [A], where the anion A is I , I, I, N(CN) , C(CN), B(CN), or SbF, are reported. All compounds were fully characterized by CHN elemental analysis, H and C NMR spectroscopy, and X-ray diffraction studies on single crystals. The molecular structure of the IM [CCIM] cation, as found in the individual crystal packing arrangements, is discussed in relation to the different anions used for crystallization. Depending on the geometry of the counteranions used (linear, bent, planar, and spherical), different molecular structures of the IM cations (rod-, V-, and U-shaped) resulted. The crystal packing in the solid-state structure is examined on the basis of a Hirshfeld surface analysis and is discussed in terms of polar and nonpolar regions. © 2011 American Chemical Society.

Solubility Studies of Sodium Azide in Liquid Ammonia by in situ Ultrasonic Velocity Measurement - Baser, Hasan-Hüseyin; Schwieger, Wilhelm; Freitag, Detlef; Steigerwald, Thomas; Schlücker, Eberhard (Chemical Engineering & Technology, 2017)
Ultrasonic velocity measurement data has been established as a simple and convenient tool to determine different thermodynamic properties of liquids and solutions. Such measurements were carried out in situ to determine the solubility of NaN in liquid ammonia within a defined temperature range. Different mixtures of NaN in ammonia were prepared and the ultrasonic velocities of these mixtures were measured within this temperature range in order to compile calibration curves. Further, these calibration curves were used to calculate the solubility in a saturated solution.
Keywords: Ammonia; Sodium azide; Solubility; Ultrasonic velocity measurement

Solvent-Free Biginelli Reactions Catalyzed by Hierarchical Zeolite Utilizing a Ball Mill Technique: A Green Sustainable Process - Shahid, Ameen; Ahmed, Nesreen S. I.; Saleh, Tamer; Al-Thabaiti, Shaeel A.; Basahel, S.A.; Schwieger, Wilhelm; Mokhtar, Mohammed (Catalysts, 2017)
A sustainable, green one-pot process for the synthesis of dihydropyrimidinones (DHPMs) derivatives by a three-component reaction of beta-ketoester derivatives, aldehyde and urea or thiourea over the alkali-treated H-ZSM-5 zeolite under ball-milling was developed. Isolation of the product with ethyl acetate shadowed by vanishing of solvent was applied. The hierachical zeolite catalyst (MFI27_6) showed high yield (86%-96%) of DHPMs in a very short time (10-30 min). The recyclability of the catalyst for the subsequent reactions was examined in four subsequent runs. The catalyst was shown to be robust without a detectable reduction in catalytic activity, and high yields of products showed the efficient protocol of the Biginelli reactions.
Keywords: hierarchical; MFI27; Biginelli; dihydropyrimidinones; ball mill

Solvent-free transformation of spray coated ZnO layers to ZIF-8 membranes - Reif, Benjamin; Somboonvong, Jan; Fabisch, Florian; Kaspereit, Malte; Hartmann, Martin; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2019)
Keywords: Vapor-solid reaction; ZIF-8 membrane; Solvent-free; Spray-coating; ZnO

Spectroscopic and electrochemical characterization of heteropoly acids for their optimized application in selective biomass oxidation to formic acid - Albert, Jakob; Lüders, Daniela; Bösmann, Andreas; Guldi, Dirk Michael; Wasserscheid, Peter (Green Chemistry, 2014)
Different Keggin-type polyoxometalates have been synthesized and characterized in order to identify optimized homogeneous catalysts for the selective oxidation of biomass to formic acid (FA) using oxygen as an oxidant and p-toluenesulfonic acid as an additive. Applying the optimized polyoxometalate catalyst system H[PVMoO ] (HPA-5), a total FA-yield (with respect to carbon in the biogenic feedstock) of 60% for glucose within 8 h reaction time and 28% for cellulose within 24 h reaction time could be achieved. The transformation is characterized by its mild reaction temperature, its excellent selectivity to FA in the liquid product phase and its applicability to a very wide range of biogenic raw materials including non-edible biopolymers and complex biogenic mixtures. © 2014 The Royal Society of Chemistry.

Spectroscopic Observation and Molecular Dynamics Simulation of Ga Surface Segregation in Liquid Pd-Ga Alloys - Grabau, Mathias; Erhard, Jannis; Taccardi, Nicola; Krick Calderon, Sandra; Wasserscheid, Peter; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2017)
Liquid binary Pd-Ga alloys with low Pd contents of 0.8, 1.8, and 4.7at% of Pd were examined as a function of sample temperature in ultra-high vacuum by using angle-resolved XPS. Upon cooling from 750 to 400K, a pronounced temperature-dependence of the Pd concentration in the liquid phase was observed, which was explained by the transition from the pure liquid phase to a two-phase system, consisting of a solid Ga5Pd phase and a Pd-depleted liquid Pd-Ga alloy. In the liquid Pd-Ga alloy, Pd is always depleted from the topmost interface layer, as deduced from angle-resolved XPS at 0 and 80 degrees emission, independent of temperature and Pd concentration. This observation is interpreted as an inhomogeneous depth distribution function of Pd, that is, the segregation of Ga to the surface of the liquid phase. The results of a DFT-based molecular dynamics simulation (MD) independently show interfacial stratification of Ga and an inhomogeneous Pd distribution along the surface normal. The evaluation of the experimental data with a rigid layer model based on the MD calculations leads to excellent agreement with the simulation.
Keywords: DFT MD; gallium; liquid-metal catalysis; palladium; XPS

Spectroscopy on supported ionic liquids. - Schulz, Peter (Wiley-VCH Verlag GmbH & Co. KGaA, 2014)
A review. This article discusses the IR spectroscopy, X-ray diffraction and NMR spectroscopy on supported ionic liqs. [on SciFinder(R)]
Keywords: supported ionic liq spectroscopy review

SPIONs functionalized with small peptides for binding of lipopolysaccharide, a pathophysiologically relevant microbial product. - Karawacka, Weronika; Janko, Christina; Unterweger, Harald; Mühlberger, Marina; Lyer, Stefan; Taccardi, Nicola; Mokhir, Andriy; Jira, Wolfgang; Peukert, Wolfgang; Boccaccini, Aldo R.; Kolot, Mikhail; Strauss, Richard; et al. (Colloids and Surfaces B-Biointerfaces, 2018)
Systemic inflammation such as sepsis represents an acute life-threatening condition, to which often no timely remedy can be found. A promising strategy may be to functionalize magnetic nanoparticles with specific peptides, derived from the binding motives of agglutinating salivary proteins, that allow immobilization of pathogens. In this work, superparamagnetic iron oxide nanoparticles with stable polycondensed aminoalkylsilane layer were developed, to which the heterobifunctional linkers N-succinimidyl 3-(2-pyridyldithio)-propanoate (SDPD) and N-succinimidyl bromoacetate (SBA) were bound. These linkers were further chemoselectively reacted with the thiol group of singularly present cysteines of selected peptides. The resulting functional nanoparticles underwent a detailed physicochemical characterization. The biocompatibility of the primarily coated aminoalkylsilane particles was also investigated. To test the pathogen-binding efficacy of the particles, the lipopolysaccharide-immobilization capacity of the peptide-coated particles was compared with free peptides. Here, one particle-bound peptide species succeeded in capturing 90% of the toxin, whereas the degree of immobilization of the toxin with a system that varied in the sequence of the peptide dropped to 35%. With these promising results, we hope to develop extracorporeal magnetic clearance systems for removing pathogens from the human body in order to accelerate diagnosis and alleviate acute disease conditions such as sepsis.

Spray-coatable ionogels based on silane-ionic liquids for low voltage, flexible, electrolyte-gated organic transistors - Thiemann, Stefan; Sachnov, Swetlana; Gruber, Mathias; Gannott, Florentina; Spallek, Stefanie; Schweiger, Manuel; Krückel, Johannes; Kaschta, Joachim; Spiecker, Erdmann; Wasserscheid, Peter; Zaumseil, Jana (Journal of Materials Chemistry C, 2014)
We introduce a new type of silane-based ionogels that are produced by gelation of the ionic liquid 3-methyl-1-(3-(triethoxysilyl)propyl)-imidazolium bis(trifluoromethylsulfonyl)imide ([(EtO)3SiPMIM][TFSI]) with tetramethylorthosilane and formic acid. In the obtained ionogels the cations are involved in the network formation while the anions can move freely. The ionogels show advantageous properties for application in flexible electronics, such as low modulus, solution processability and high specific capacitance. Spray-coated ionogels were used as high capacitance gate dielectrics for organic (poly[3-hexylthiophene], P3HT) electrolyte-gated transistors (EGTs) that operated at very low voltages (<2 V) with high on/off ratios in air over weeks. Devices fabricated on polymer foil remained functional during repeated bending cycles with strains up to 2.3%.

Stability of a Bifunctional Cu-Based Core@Zeolite Shell Catalyst for Dimethyl Ether Synthesis Under Redox Conditions Studied by Environmental Transmission Electron Microscopy and In Situ X-Ray Ptychography - Baier, S.; Damsgaard, S.D.; Klumpp, Michael; Reinhardt, J.; Sheppard, T.; Balogh, Z.; Kasama, T.; Benzi, F.; Wagner, J.B.; Schwieger, Wilhelm; Schroer, C.G.; Grunwaldt, J.D. (Microscopy and Microanalysis, 2017)
When using bifunctional core@shell catalysts, the stability of both the shell and core-shell interface is crucial for catalytic applications. In the present study, we elucidate the stability of a CuO/ZnO/Al2O3@ZSM-5 core@shell material, used for one-stage synthesis of dimethyl ether from synthesis gas. The catalyst stability was studied in a hierarchical manner by complementary environmental transmission electron microscopy (ETEM), scanning electron microscopy (SEM) and in situ hard X-ray ptychography with a specially designed in situ cell. Both reductive activation and reoxidation were applied. The core-shell interface was found to be stable during reducing and oxidizing treatment at 250 degrees C as observed by ETEM and in situ X-ray ptychography, although strong changes occurred in the core on a 10 nm scale due to the reduction of copper oxide to metallic copper particles. At 350 degrees C, in situ X-ray ptychography indicated the occurrence of structural changes also on the mu m scale, i.e. the core material and parts of the shell undergo restructuring. Nevertheless, the crucial core-shell interface required for full bifunctionality appeared to remain stable. This study demonstrates the potential of these correlative in situ microscopy techniques for hierarchically designed catalysts.
Keywords: core-shell catalyst; dimethyl ether; correlative imaging; ETEM; X-ray microscopy

Stable and Selective Dehydrogenation of Methylcyclohexane using Supported Catalytically Active Liquid Metal Solutions – Ga52Pt/SiO2 SCALMS - Oshin, Sebastian; Nair, Sharanya; Taccardi, Nicola; Wolf, Moritz; Soegaard, Alexander; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2020)
The use of gallium-rich, Supported Catalytically Active Liquid Metal Solution (SCALMS) is a promising new concept to achieve catalysis with atomically dispersed active metal atoms. Expanding our previous work on short alkane dehydrogenation, we present here the application of SCALMS for the dehydrogenation of methylcyclohexane (MCH) to toluene (TOL) using a Ga52Pt alloy (liquid under reaction conditions) supported on silica. Cycloalkane dehydrogenation catalysis has attracted great attention recently in the context of hydrogen storage concepts using liquid organic hydrogen carrier (LOHC) systems. The system under investigation showed high activity and stable conversion of MCH at 450 °C and atmospheric pressure for more than 75 h time-on-stream (XMCH=15 %) with stable toluene selectivity (STOL) of 85 %. Compared to commercially available Pt/SiO2, the SCALMS system resulted in higher yields and robustness. Baseline experiments with Pt-free Ga/SiO2 under identical conditions revealed the decisive influence of Pt dissolved in the liquid Ga matrix.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Alloys; dehydrogenation; gallium; methylcyclohexane; platinum; supported catalysts

Stable Immobilization of Size-Controlled Bimetallic Nanoparticles in Photonic Crystal Fiber Microreactor - Ponce, Sebastian; Munoz, Macarena; Cubillas, Ana M.; Euser, Tijmen G.; Zhang, Gui-Rong; Russell, Philip St. J.; Wasserscheid, Peter; Etzold, Bastian J.M. (Chemie Ingenieur Technik, 2018)
The possibility of immobilizing ex situ-synthesized colloidal bimetallic nanoparticles (NPs) of well-defined characteristics inside hollow core photonic crystal fiber (HC-PCF) microreactors is demonstrated. With the developed method, PtNi clusters remain strongly attached to the fiber core and can be used as active catalysts for the hydrogenation of an azobenzene dye. The study revealed that optical transmission exhibits a size-dependent behavior, i.e., smaller NPs bring in less optical signal loss. Sufficient light transmission was achieved for all particle sizes. Furthermore, with these catalytic PCF microreactors, kinetic data can be obtained with a much lower amount of precious metals compared to a conventional batch reactor, opening a new pathway for in situ catalyst screening.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Heterogeneous catalysis; In situ UV-vis spectroscopy; Microreactors; Photonic crystal fibers; PtNi nanoparticles

Storage of hydrogen. - Wasserscheid, Peter; Assenbaum, Daniel; Taccardi, Nicola (2009)
The invention concerns a reaction system for decompg. ammonia into hydrogen and nitrogen, contg. a catalyst. The catalyst is present in dissolved form in the reaction system and the reaction system contains an ionic liq., whereby the catalyst is present dissolved or suspended in the ionic liq. Alternatively the catalyst can be present in solid form in the reaction system and the reaction system contains an ionic liq., which uses the catalyst. [on SciFinder(R)]
Keywords: hydrogen storage

Strategies for Low-Temperature Liquid Organic Hydrogen Carrier Dehydrogenation - Müller, Karsten; Skeledzic, Tanja; Wasserscheid, Peter (Energy & Fuels, 2021)
Liquid organic hydrogen carriers (LOHCs) store hydrogen by covalent bonds in a safe and dense manner. Recovery of hydrogen is realized by an endothermal dehydrogenation reaction. Theoretically, its heat demand could be covered by waste heat, e.g., from a fuel cell. However, to facilitate this, it is crucial to increase the temperature level of polymer electrolyte membrane fuel cells and lower the temperature level of the dehydrogenation reaction. In this study, strategies for releasing hydrogen from LOHCs at low temperatures are presented and evaluated. Thereby, the focus is on approaches for overcoming limitations by the reaction equilibrium. We see three main options: (i) dehydrogenation at a low pressure, (ii) dilution of hydrogen with an inert gas, and (iii) reactive distillation. These options are examined, particularly regarding their suitability for integrating waste heat, e.g., from fuel cells. Low-pressure dehydrogenation and reactive distillation show the highest potential for realizing efficient low-Temperature hydrogen release.
CRIS-Team Scopus Importer:2021-07-02

Structural Analysis of Liquid Metal Catalysts in Porous Silica Utilizing Nano-CT and Analytical Transmission Electron Microscopy - Wirth, Janis; Englisch, Silvan; Wiktor, Christian; Taccardi, Nicola; Apeleo Zubiri, Benjamin; Wasserscheid, Peter; Spiecker, Erdmann (Cambridge University Press, 2019)

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica - Peters, Britta; Stein, Johanna; Klingl, Stefan; Sander, Nathalie; Sandmann, Achim; Taccardi, Nicola; Sticht, Heinrich; Gerlach, Roman; Muller, Yves; Hensel, Michael (PLoS Pathogens, 2017)

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica - Peters, Britta; Stein, Johanna; Klingl, Stefan; Sander, Nathalie; Sandmann, Achim; Taccardi, Nicola; Sticht, Heinrich; Gerlach, Roman G.; Muller, Yves; Hensel, Michael (PLoS Pathogens, 2017)

Structured catalysts for the direct synthesis of dimethyl ether from synthesis gas: A comparison of core@shell versus hybrid catalyst configuration - Baracchini, Giulia; Machoke, Albert; Klumpp, Michael; Wen, Ruoxi; Arnold, Patrick; Schwieger, Wilhelm; Dittmeyer, Roland (Catalysis Today, 2019)
The direct synthesis of dimethyl ether (DME) from synthesis gas via methanol as an intermediate is a promising process for realizing a decentralized, small-scale Power-to-X concept. The efficient realization of this coupled process depends to a large extent on the appropriate catalyst configuration, i.e. the combination of the catalyst for methanol formation with the one for the subsequent dehydration step. In this work, two catalyst configurations were compared in terms of CO-conversion and DME-selectivity using modelling and experiments. Catalysts for methanol formation (Cu/ZnO/Al2O3, CZA) and dehydration (Zeolite H-ZSM-5, Z) prepared via flame spray pyrolysis and hydrothermal synthesis, respectively, were combined in the form of hybrid pellets (CZA&Z) and CZA-core@zeolite-shell (CZA@Z) particles. During the synthesis of the CZA@Z system, alteration of the CZA core in terms of CuO-reducibility and activity in methanol synthesis were found after individual steps of calcination and hydrothermal shell synthesis. In contrast, the preparation of the CZA&Z system presents an easy and tunable method with promising catalytic properties in terms of CO-conversion and DME-selectivity, once the proper mass ratio of the two catalysts was set. From modelling, for the same CZA/Z ratio in general higher CO-conversion was found for the CZA&Z system as compared to the CZA@Z, while the latter system shows higher DME-selectivity.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Core@shell; CuO/ZnO/Al; Dimethyl ether; Flame spray pyrolysis; Hybrid catalyst; Hydrothermal synthesis

Structure Formation in an Ionic Liquid Wetting Layer: A Combined STM, IRAS, DFT and MD Study of [C2C1Im][OTf] on Au(111) - Bühlmeyer, Hanna; Hauner, Jonas; Eschenbacher, Roman; Steffen, Julien; Trzeciak, Simon; Taccardi, Nicola; Görling, Andreas; Zahn, Dirk; Wasserscheid, Peter; Libuda, Jörg (Chemistry - A European Journal, 2023)
In a solid catalyst with ionic liquid layer (SCILL), ionic liquid (IL) coatings are used to improve the selectivity of noble metal catalysts. To understand the origins of this selectivity control, we performed model studies by surface science methods in ultrahigh vacuum (UHV). We investigated the growth and thermal stability of ultrathin IL films by infrared reflection absorption spectroscopy (IRAS). We combined these experiments with scanning tunneling microscopy (STM) to obtain information on the orientation of the ions, the interactions with the surface, the intermolecular interactions, and the structure formation. Additionally, we performed DFT calculations and molecular dynamics (MD) simulations to interpret the experimental data. We studied the IL 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C2C1Im][OTf] on Au(111) surfaces. We observe a weakly bound multilayer of [C2C1Im][OTf], which is stable up to 390 K, while the monolayer desorbs at ∼450 K. [C2C1Im][OTf] preferentially adsorbs at the step edges and elbows of the herringbone reconstruction of Au(111). The anion adsorbs via the SO3 group with the molecular axis perpendicular to the surface. At low coverage, the [C2C1Im][OTf] crystallizes in a glass-like 2D phase with short-range order. At higher coverage, we observe a phase transition to a 6-membered ring structure with long-range order.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Au(111); SCILL; infrared reflection absorption spectroscopy; ionic liquids; scanning tunneling microscopy

Structure-Property Relations in Ionic Liquids: 1,2,3-Trimethyl-imidazolium and 1,2,3-Trimethyl-benzimidazolium bis-(trifluorsulfonyl)imide - Zaitsau, Dzmitry H.; Yermalayeu, Andrei V.; Schick, Christoph; Emel'Yanenko, Vladimir N.; Verevkin, Sergey P.; Samarov, Artemiy A.; Schlenk, Stefan; Wasserscheid, Peter (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2013)
Vaporization enthalpies for a pairs of the ionic liquids (ILs) 1,2,3-trimethyl-imidazollum and 1,2,3-trimethyl-benzimidazolium bistrifluorsulfonylimide and the corresponding molecular liquids 1,2-dimethyl-imidazole and 1,2-dimethyl-benzimidazole were determined using a quartz crystal microbalance method and TGA (for ILs) and the transpiration method (for molecular compounds). Differences in vaporization enthalpies in molecular and ionic liquids are discussed in context of structure-property relations. For Supplementary Material see online version.
Keywords: Ionic Liquids; Imidazoles; Benzimidazoles; Quartz-Crystal Microbalance; TGA; Transpiration Method; Vapor Pressure; Enthalpy of Vaporization; Structure-Property Relations

Substituting fossil-based with bio-based chemicals: the case of limonene as a greener pore expander for micellar templated silica - Sultan, Umair; Städtke, Katrin; Göpfert, Andreas; Lemmen, Daniel; Metwali, Ezzeldin; Maiti, Santanu; Schlumberger, Carola; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Vogel, Nicolas; Unruh, Tobias; et al. (RSC Sustainability, 2023)
Porous materials are widely used in applications such as adsorption, catalysis and separation. The use of expander molecules is a versatile route to enlarge the mesopore size in micellar templated mesoporous silica materials. Typical expanders used for this purpose are fossil-based organic molecules such as trimethylbenzene (TMB). In the course of making such syntheses greener and more sustainable, it is highly desirable to substitute such fossil-based chemicals with renewable ones. Here, we show that bio-based limonene can be used as an alternative expander molecule for the synthesis of large-pore templated silica. On the basis of electron microscopy, nitrogen physisorption and small angle X-ray scattering we show that the substitution of TMB by limonene leads to very similar material characteristics, reaching mean mesopore diameters of 17-19 nm. A comparative life-cycle assessment demonstrates the reduced environmental impact of limonene production from citrus peel waste compared to TMB production, supporting the call for more applications of renewable chemicals, ideally from waste-streams, also for the production of porous materials.
CRIS-Team Scopus Importer:2023-10-06

Sugar acid production on gold nanoparticles in slurry reactor: Kinetics, solubility and modelling - Worgul, Bernadette; Freites Aguilera, Adriana; Vergat-Lemercier, Camille; Eränen, Kari; Simakova, Olga; Held, Hendrik; Freund, Hannsjörg; Yu. Murzin, Dmitry; Salmi, Tapio (Chemical Engineering Science, 2022)
Sugar acids obtained by oxidation of sugars are very valuable molecules which are used as chelating agents, binders as well as ingredients in pharmaceuticals. Arabinonic acid was prepared by oxidation of arabinose on gold nanoparticles deposited on an aluminium oxide carrier. A systematic reaction kinetic study was conducted to reveal the influence of oxygen partial pressure and pH on reaction rate and product selectivity. Experiments were carried out in a laboratory-scale semi-batch reactor which was operated at 70 °C and oxygen partial pressures 0.125–1.0 atm. The pH of the aqueous sugar solution was 6–8. Oxygen was continuously flowing through the semibatch slurry reactor and the pH was kept constant by adding NaOH during the experiments. The oxygen solubility in the reaction mixture was determined in separate experiments. A reaction mechanism was proposed for the formation of arabinonic acid (main product) and arabinolactone (intermediate by-product). The surface reaction of competitively adsorbed arabinose and oxygen was assumed to be rate determining for the arabinose consumption. For the formation of arabinonic acid from arabinolactone, the rate determining step was presumed to be the reaction between arabinolactone and sodium hydroxide. The reactor was described with the perfect backmixing model and the component mass balances were solved numerically during the estimation of kinetic parameters by nonlinear regression analysis. The kinetic model gives new insights in the reaction mechanism and described the experimental data very well. The model has potential for application in the oxidation of other monomeric sugars, too.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Gold catalyst; Kinetics; Lactone; Modelling; Oxygen solubility; Semibatch reactor; Sugar; Sugar acid

Supported homogeneous catalyst makes its own liquid phase - Kaftan, Andre; Schönweiz, Andreas; Nikiforidis, Ioannis; Hieringer, Wolfgang; Dyballa, Katrin M.; Franke, Robert; Görling, Andreas; Libuda, Jörg; Wasserscheid, Peter; Laurin, Mathias; Haumann, Marco (Journal of Catalysis, 2015)
2,2'-((3,3'-di-tert-butyl-5,5'-dimethoxy-[1,1'-biphenylj-2,2'-diyl)-bis(oxy))bis(4,4,5,5-tetraphenyl-1,3,2-dioxaphospholane) modified rhodium complexes molecularly adsorbed onto porous silica powder show surprisingly high activity and regioselectivity in the gas-phase hydroformylation of propene to but-anal, with no sign of deactivation. Operando IR investigations combined with density functional theory calculations confirm a side reaction: the aldol condensation of the butanal products. These heavier by-products accumulate inside the pores of the catalytic material. IR and gas chromatography show a direct relation between formation of enones, products of the aldol condensation, performance, and stability of the catalytic system. This demonstrates that the aldol condensation products generated in situ act as a solvent providing an ideal environment to the impregnated homogeneous catalyst. (c) 2014 Elsevier Inc. All rights reserved.
Keywords: Hydroformylation; Supported homogeneous catalysis; Operando spectroscopy; Infrared spectroscopy; Density functional theory; Silicon dioxide; Rhodium

Supported ionic liquid phase (SILP) catalyzed hydroformylation of 1-butene in a gradient-free loop reactor - Haumann, Marco; Jakuttis, Michael; Werner, Sebastian; Wasserscheid, Peter (Journal of Catalysis, 2009)
The supported ionic liquid phase (SILP) catalysis technology was applied to gas-phase hydroformylation of 1-butene using sulfoxantphos 1 modified rhodium complexes. Kinetic experiments were performed in a fixed bed reactor and compared to a gradient-free gas-phase loop reactor (Berty type). The influence of substrate concentration, temperature and syngas pressure was determined. Data from fixed bed and Berty reactor were found to be in good agreement with respect to activation energy and reaction order. Ex-situ NMR studies of fresh and used SILP catalysts confirmed that the ligand remained intact after prolonged time on stream.

Supported ionic liquid phase (SILP) materials for removal of hazardous gas compounds - efficient and irreversible NH3 adsorption - Kohler, Florian; Popp, Sabine; Klefer, Heiko; Eckle, Ilsebill; Schrage, Christian; Böhringer, Bertram; Roth, Daniel; Haumann, Marco; Wasserscheid, Peter (Green Chemistry, 2014)
Novel supported ionic liquid phase (SILP) gas purification materials have been developed to remove ammonia irreversibly from an ambient gas flow of nitrogen (1000 ppm NH3 in N-2, wet and dry). In the applied SILP materials, thin films of imidazolium based ionic liquids and ionic solutions of metal complexes, namely [C(8)C(1)lm][NTf2], [C(8)C(1)lm][NTf2]/Cu(NTf2)(2), [C(8)C(1)lm][NTf2]/Co(NTf2)(2) and [C(n)C(1)lm]Cl/CuCl2 (n = 2, 4, 8), were dispersed onto the large surface area of polymer-based spherical activated carbon supports. For the [C(n)C(1)lm]Cl/CuCl2 (n = 2, 4, 8) based SILP materials the use of a humid gas flow significantly enhances NH3 absorption as demonstrated by a clear increase of breakthrough times. The irreversibility of the ammonia sorption and the broadband capability (e.g. Cl-2, H2S and cyclohexane) of the prepared SILP absorber materials are reported and compared to typical standards for gas purification adsorber materials (ABEK regulations).

Supported ionic liquids on non-porous and porous inorganic materials-A topical review - Selvam, Thangaraj; Machoke, Albert; Schwieger, Wilhelm (Applied Catalysis A-General, 2012)
A topical review of the use of non-porous and porous inorganic materials as supports for the immobilization of ILs and their catalytic applications is given. The basic principles and the supports that are being used in various concepts emerging from supported ionic liquids (SILs) including supported ionic liquid films (SILFs), supported ionic liquid catalysis/catalysts (SILC/SILCAs), solid catalysts with ILs (SCILs), solid catalysts with IL layer (SCILL), supported IL nanoparticles (SILnPs) and supported ionic liquid phase (SILP) catalysts (SILPC) are first discussed. In addition, we provide a comprehensive review of the SILs concept dealing with inorganic supports, such as layered silicates, porous glass, zeolites, mesoporous (MCM) and PMO (periodic mesoporous organosilica) materials; and their applications. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ionic liquids; Supported ionic liquids; Inorganic supports; Non-porous and porous materials

Supported liquid catalysts. - Riisager, Anders; Fehrmann, Rasmus; Wasserscheid, Peter (Handbook of Heterogeneous Catalysis, 2008)
A review; supported liq. catalysts are discussed. [on SciFinder(R)]
Keywords: review supported liq catalyst

Supported liquid metals - A new class of robust dehydrogenation catalysts - Taccardi, Nicola; Grabau, Mathias; Debuschewltz, Jonas; Distaso, Monica; Brandl, Marco; Hock, Rainer; Maier, Florian; Papp, Christian; Erhard, Jannis; Neiß, Christian; Peukert, Wolfgang; Görling, Andreas; et al. (12th Natural Gas Conversion Symposium 2019, 2019)
CRIS-Team Scopus Importer:2019-12-10

Supraparticles on beads for supported catalytically active liquid metal solutions - the SCALMS suprabead concept - Zimmermann, Thomas; Madubuko, Nnamdi; Groppe, Philipp; Raczka, Theodor; Dünninger, Nils; Taccardi, Nicola; Carl, Simon; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Wasserscheid, Peter; Mandel, Karl; Haumann, Marco; et al. (Materials Horizons, 2023)
A novel GaPt-based supported catalytically active liquid metal solution (SCALMS) material is developed by exploiting the suprabead concept: Supraparticles, i.e. micrometer-sized particles composed of nanoparticles assembled by spray-drying, are bonded to millimeter-sized beads. The suprabeads combine macroscale size with catalytic properties of nanoscale GaPt particles entrapped in their silica framework.
Created from Fastlane, Scopus look-up

Surface and texture properties of mesoporous silica materials modified by silicon-organic compounds containing quaternary amino groups for their application in base-catalyzed reactions - Borodina, E.; Karpov, S. I.; Selemenev, V. F.; Schwieger, Wilhelm; Maracke, S.; Froeba, M.; Roessner, F. (Microporous and Mesoporous Materials, 2015)
The synthesis of organic-inorganic composite materials (OICM) was performed by the surface modification of mesoporous silica material (MM) type MCM-41 by N-((trimethoxysilyl)propyl)-N,N,N-trimethylammonium chloride (TMTMAC). The application of diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, X-ray diffraction (XRD), N-2 adsorption/desorption and thermogravimetric analysis (TGA) showed that the distribution of grafted TMTMAC strongly depended on polarity and nature of solvent used for grafting. For water a clustering of TMTMAC resulted in a pore blockage. Methanol was identified to be the most suitable solvent to obtain a low loading and more homogeneous distribution of aminosilanes. Thermogravimetric analysis showed the composites were thermally stable up to 180 degrees C. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Mesoporous silica materials; Surface modification; Quaternary ammonium groups; Knoevenagel condensation

Surface behavior of low-temperature molten salt mixtures during the transition from liquid to solid - Bhuin, Radha Gobinda; Schreiber, Patrick; Heller, Bettina; Scheuermeyer, Marlene; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Molecular Liquids, 2019)
We report on surface investigations of cesium and tetraphenylphosphonium bis(trifluoromethylsulfonyl)imide (Cs[Tf2N], [PPh4][Tf2N]) molten salts and their mixtures. Depending on composition, these ionic compounds combine low melting points with exceptionally high thermal stability, and thus, exhibit considerably enlarged thermal operation windows compared to conventional ionic liquids. To elucidate their liquid-solid transition behavior in the near-surface region, temperature-dependent angle-resolved X-ray photoelectron spectroscopy (ARXPS) investigations were performed using our unique laboratory electron spectrometer DASSA ("Dual Analyzer System for Surface Analysis"), dedicated for investigations of macroscopic liquid samples. We followed temperature-induced changes in bulk and surface composition within the first nanometers of the neat salt melts and of Cs[Tf2N]: (PPh4][Tf2N]= 3 : 1 and 1 : 3 mixtures. In the mixtures, pronounced surface enrichment of Cs+ on expense of the bulky [PPne ions was found in the liquid state at temperatures close to the liquid-solid transition. In the solid state of Cs[Tf2N]-rich mixtures, [PPH4](+) completely vanishes from the near-surface region probed by XPS. (C) 2018 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
CRIS-Team WoS Importer:2019-02-27

Surface characterization of functionalized imidazolium-based ionic liquids - Kolbeck, Claudia; Killian, Manuela; Maier, Florian; Paape, Natalia; Wasserscheid, Peter; Steinrück, Hans-Peter (Langmuir, 2008)
The surface composition of oligo(ethylene glycol) ether functionalized bis(trifluoromethylsulfonyl)imide ionic liquids has been studied by means of X-ray photoelectron spectroscopy (XPS). For [Me(EG)MIM] [TfN], [Et(EG)MIM]-[TfN], and [Me(EG)MIM][Tf N], which vary by the number of ethylene glycol (EG) units (from 1 to 3), we have shown that the stoichiometry of the surface near region is in excellent agreement with the bulk stoichiometry, which confirms the high purity of the ionic liquid samples investigated and rules out pronounced surface orientation effects. This has been deduced from the experimental observation that the angle-resolved XP spectra of all elements present in the IL anions and cations (C, N, O, F, S) show identical signals in the bulk and surfaces sensitive geometry, i.e., at 0° and 70° emission angle, respectively. The relative intensity ratios of all elements were found to be in nearly perfect agreement with the nominal values for the individual ILs. In contrast to these findings, we identified surfaceactive impurities in [Me(EG)MIM]I, which is the starting material for the final anion exchange step to synthesize [Me(EG)MIM][Tf2N]. Sputtering of the surface led to a depletion of this layer, which however recovered with time. The buildup of this contamination is attributed to a surface enrichment of a minor bulk contamination that shows surface activity in the iodide melt. © 2008 American Chemical Society.

Surface enrichment and depletion effects of ions dissolved in an ionic liquid: An X-ray photoelectron spectroscopy study - Maier, Florian; Gottfried, Michael; Rossa, Jürgen; Gerhard, Dirk; Schulz, Peter; Schwieger, Wilhelm; Wasserscheid, Peter; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2006)
(Graph Presented) Surfaces of ionic liquids: Angle-dependent X-ray photoelectron spectroscopy (XPS) shows that the surface composition of a solution of [Pt(NH)]Cl in the ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate ([EMIM][EtOSO]) deviates considerably from the bulk composition. The [Pt-(NH) ] cation is enriched on the surface at the expense of the [EMIM] cation (see picture), while the Cl anion is depleted to below the XPS detection limit. © 2006 Wiley-VCH Verlag GmbH & Co. KGaA.

Surface enrichment of Pt in Ga2O3 films grown on liquid Pt/Ga alloys - Grabau, Mathias; Krick Calderon, Sandra; Rietzler, Florian; Niedermaier, Inga; Taccardi, Nicola; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2016)
The formation of surface GaO films on liquid samples of Ga, and Pt-Ga alloys with 0.7 and 1.8 at.% Pt was examined using near-ambient pressure (NAP) X-ray photoelectron spectroscopy (XPS). Thickness, composition and growth of the oxide films were deduced as a function of temperature and Pt content of the alloys, in ultra-high vacuum and at oxygen pressures of 3 × 10, 3 × 10 and 1 mbar. We examined oxide layers up to a thickness of 37 Å. Different growth modes were found for oxidation at low and high pressures. The formed GaO oxide films showed an increased Pt content, while the pristine GaPt alloy showed a surface depletion of Pt at the examined temperatures. Upon growth of GaO on Pt/Ga alloys a linear increase of Pt content was observed, due to the incorporation of 3.6 at.% Pt in the GaO. The Pt content in GaO, at the examined temperatures and bulk Pt concentrations is found to be independent of pressure, temperature and the nominal Pt content of the metallic alloy.
Keywords: Bimetallic catalysts; Gallium oxide; NAP XPS; Pt/Ga alloys

Surface-functionalized ionic liquid crystal-supported ionic liquid phase materials: Ionic liquid crystals in mesopores - Kohler, Florian; Morain, Bruno; Weiß, Alexander; Laurin, Mathias; Libuda, Jörg; Wagner, Valentin; Melcher, Berthold Ulrich; Wang, Xinjiao; Meyer, Karsten; Wasserscheid, Peter (ChemPhysChem, 2011)
The influence of confinement on the ionic liquid crystal (ILC) [C C Im][OTf] is studied using differential scanning calorimetry (DSC), polarized optical microscopy (POM), and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The ILC studied is supported on Si-based powders and glasses with pore sizes ranging from 11 to 50 nm. The temperature of the solid-to-liquid-crystalline phase transition seems mostly unaffected by the confinement, whereas the temperature of the liquid-crystalline-to-liquid phase transition is depressed for smaller pore sizes. A contact layer with a thickness in the order of 2 nm is identified. The contact layer exhibits a phase transition at a temperature 30 K lower than the solid-to-liquid-crystalline phase transition observed for the neat ILC. For applications within the "supported ionic liquid phase (SILP)" concept, the experiments show that in pores of diameter 50 nm a pore filling of α>0.4 is sufficient to reproduce the phase transitions of the neat ILC. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Surface Reactions of Dicyclohexylmethane on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Höfert, Oliver; Xu, Tao; Späth, Florian; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2015)
We investigated the surface reaction of the liquid organic hydrogen carrier dicydohexylmethane (DCHM) on Pt(111) in ultrahigh vacuum by high-resolution X-ray photoelectron spectroscopy, temperature-programmed desorption, near-edge X-ray absorption fine structure, and infrared reflection absorption spectroscopy. Additionally, the hydrogen-lean molecule diphenylmethane and the relevant molecular fragments of DCHM, methylcyclohexane, and toluene were studied to elucidate the reaction steps of DCHM. We find dehydrogenation of DCHM in the range of 200-260 K, to form a double-sided pi-allylic species coadsorbed with hydrogen. Subsequently, similar to 30% of the molecules desorb, and for similar to 70%, one of the pi-allyls reacts to a phenyl group between 260 and 330 K, accompanied by associative hydrogen desorption. Above 360 K, the second pi-allylic species is dehydrogenated to a phenyl ring. This is accompanied by C-H bond scission at the methylene group, which is an unwanted decomposition step in the hydrogen storage cycle, as it alters the original hydrogen carrier DCHM. Above 450 K, we find further decomposition steps which we assign to C-H abstraction at the phenyl rings.

Surface science and model catalysis with ionic liquid-modified materials - Steinrück, Hans-Peter; Libuda, Jörg; Wasserscheid, Peter; Cremer, Till; Kolbeck, Claudia; Laurin, Mathias; Maier, Florian; Sobota, Marek; Schulz, Peter; Stark, Michael Werner (Advanced Materials, 2011)
Materials making use of thin ionic liquid (IL) films as support-modifying functional layer open up a variety of new possibilities in heterogeneous catalysis, which range from the tailoring of gas-surface interactions to the immobilization of molecularly defined reactive sites. The present report reviews recent progress towards an understanding of "supported ionic liquid phase (SILP)" and "solid catalysts with ionic liquid layer (SCILL)" materials at the microscopic level, using a surface science and model catalysis type of approach. Thin film IL systems can be prepared not only ex-situ, but also in-situ under ultrahigh vacuum (UHV) conditions using atomically well-defined surfaces as substrates, for example by physical vapor deposition (PVD). Due to their low vapor pressure, these systems can be studied in UHV using the full spectrum of surface science techniques. We discuss general strategies and considerations of this approach and exemplify the information available from complementary methods, specifically photoelectron spectroscopy and surface vibrational spectroscopy. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Surface Tension and Viscosity of Binary Mixtures of the Fluorinated and Non-fluorinated Ionic Liquids [PFBMIm][PF6] and [C4C1Im][PF6] by the Pendant Drop Method and Surface Light Scattering - Koller, Thomas Manfred; Lenahan, Frances; Schmidt, Patrick; Klein, Tobias; Mehler, Julian; Maier, Florian; Rausch, Michael Heinrich; Wasserscheid, Peter; Steinrück, Hans-Peter; Fröba, Andreas Paul (International Journal of Thermophysics, 2020)
Mixtures of fluorinated and non-fluorinated ionic liquids (ILs) show a distinct structural organization in the bulk and at the surface. To understand how such microscopic effects influence the macroscopic bulk and surface properties of IL mixtures, knowledge of corresponding thermophysical properties including viscosity and surface tension is required yet lacking. With the intention of investigating surface enrichment effects of the fluorinated IL [PFBMIm][PF6] (3-methyl-1-(3,3,4,4,4-pentafluorobutyl)imidazolium hexafluorophosphate) in mixtures with the structurally similar, non-fluorinated IL [C4C1Im][PF6] (1-butyl-3-methylimidazolium hexafluorophosphate) observed with angle-resolved X-ray photoelectron spectroscopy (ARXPS), the pendant drop method and surface light scattering (SLS) were applied in the present study to determine surface tension and dynamic viscosity between (293 and 368) K. By adding small amounts of [PFBMIm][PF6] up to 9 mol %, a distinct increase in the viscosity and decrease in the surface tension of the mixtures relative to the properties of pure [C4C1Im][PF6] was found. This behavior reflects the nanosegregated structure in the bulk and at the surface of the binary IL mixtures. Using the results about the pronounced surface enrichment of the fluorinated chain of [PFBMIm][PF6] quantified by ARXPS, a linear mixing rule for the surface tension of the IL mixtures based on the surface tensions of the pure ILs and the surface concentration of their most surface-active groups is suggested.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Ionic liquids; Mixtures; Pendant drop method; Surface light scattering; Surface tension; Viscosity

Surface Tension of Tricyanomethanide- and Tetracyanoborate-Based lmidazolium Ionic Liquids by Using the Pendant Drop Method - Koller, Thomas Manfred; Rausch, Michael Heinrich; Pohako-Esko, Kaija; Wasserscheid, Peter; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2015)
The surface tension of nine tricyanomethanide ([C(CN)(3)](-))- and tetracyanoborate ([B(CN)(4)](-))-based ionic liquids (ILs) carrying a homologous series of the 1-alkyl-3-methylimidazolium ([alkyl-MIM](+)) cations [EMLM](+) (ethyl), [BMIM](+) (butyl), [HMIM](+) (hexyl), [OMIM](+) (octyl), and [DMIM](+) (decyl) was measured with the pendant drop method in the temperature range between (283 and 353) K at atmospheric pressure with an estimated uncertainty of 2 % (k = 2). For the probed ILs, the surface tension decreases with increasing temperature and increasing alkyl chain length of the cation. Smaller values for the [B(CN)(4)](-)-based ILs compared to the [C(CN)(3)](-)-based ILs having the same cation were observed. The measured surface tensions agree with the limited number of experimental data found in the literature for the two IL families. A simple prediction based on the surface tension measured at 293 K and the temperature dependence of density showed good agreement with the measured temperature-dependent data. In comparison to other [alkyl-MIM](+)-based ILs with anions of varying molecular size, the fairly large surface tensions of the ILs investigated in this study could be attributed to the strong charge delocalization in their relatively small anions.

Surfactant-free synthesis of monodisperse cobalt oxide nanoparticles of tunable size and oxidation state developed by factorial design - Wolf, Moritz; Fischer, Nico; Claeys, Michael (Materials Chemistry and Physics, 2018)
Keywords: Cobalt oxide; Monodisperse; Experimental design; Sol-gel; Size control

Switchable Catalytic Polyoxometalate-Based Systems for Biomass Conversion to Carboxylic Acids - Voß, Dorothea; Dietrich, Regina; Stuckart, Maria; Albert, Jakob (ACS Omega, 2020)
We present the Keggin-type polyoxometalate H6[PV3Mo9O40] as a switchable catalyst being able to catalyze the transformation of both glucose and glyceraldehyde to formic acid (42%) and lactic acid (40%), respectively, within 1 h reaction time by simply changing the reaction atmosphere at 160 °C from oxygen to nitrogen in one reactor setup. In detail, we report the influence of different gas atmospheres and reaction temperatures on various vanadium-containing catalysts in the selective transformation of several biogenic substrates to carboxylic acids with a special emphasis on reaction pathways and switchability of the catalyst systems. All investigations were carried out in parallel using either an oxygen or a nitrogen atmosphere of 20 bar performing time-resolved experiments between 0.25 and 5 h and a temperature variation from 160 to 200 °C. Furthermore, a catalyst and a substrate variation led to the reaction system consisting of glyceraldehyde and the Keggin-type polyoxometalates (POM) H6[PV3Mo9O40] as the best switchable reaction system under the applied conditions. This study shows interesting potential for using both Keggin-type and Lindqvist-type POMs as switchable catalysts for selective biomass conversion to platform chemicals.
CRIS-Team Scopus Importer:2020-08-14

Synergistic effect of mesoporous metal oxides and PtO2 nanoparticles in aerobic oxidation of ethanol and ionic liquid induced acetaldehyde selectivity - Bingwa, Ndzondelelo; Ndolomingo, Matumuene Joe; Noh, Ji Hyang; Antonels, Nathan Charles; Carleschi, Emanuela; Doyle, Bryan P.; Haumann, Marco; Meijboom, Reinout (Molecular Catalysis, 2020)
We report on the catalytic performance of mesoporous metal oxides (MMOs) as catalysts and as potential supports for platinum (Pt) nanoparticles in aerobic oxidation of ethanol. Synthesis of MMOs was achieved through the hard-template method and the resulting MMOs resembled the 3-D structure of the templating KIT-6. The Pt nanoparticles were templated and stabilized using poly(amidoamide), PAMAM, dendrimer to achieve dendrimer-encapsulated Pt nanoparticles (Pt-DENs) with an average size of 3.5 ± 0.4 nm. All the components of the catalysts (Pt-DENs and MMOs) were first characterized separately and thereafter, followed the preparation of MMO-immobilized Pt nanoparticles. Upon characterization of the MMO-immobilized Pt nanoparticles, the Pt nanoparticle size increased as determined from hydrogen-chemisorption and organothiol-adsorption technique. Furthermore, X-ray photoelectron spectroscopy (XPS) revealed that Pt has an oxidation state of 4+ after removal of the dendrimer at 550 °C signifying an oxide state (PtO2). The hydrogen temperature-programmed reduction (H2-TPR) revealed a change in electronic structure of MMOs as reduction peaks shifted to lower temperatures upon immobilization of PtO2 nanoparticles. This change in electronic structure of the mesoporous metal oxides upon immobilization of PtO2 nanoparticles is found to be one of the reasons for enhanced catalytic activity. Improved selectivity towards acetaldehyde was induced by introduction of an ionic liquid layer in a solid catalyst with ionic liquid layer, SCILL concept. Furthermore, the amount of ionic liquid coating plays a pivotal role in impacting selectivity and has an impact in the reaction turnover frequency.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Adsorption; Ethanol oxidation; Ionic liquid; Mesoporous metal oxides; Platinum nanoparticles

Synthese mikroporöser Kohlenstoffschäume für katalytische Anwendungen - Glenk, Friedrich; Schirmer, Matthias; Gütlein, Stefan; Etzold, Bastian (Chemie Ingenieur Technik, 2010)
Mikroporöse Kohlenstoffschäume wurden über die Chlorierung von Carbiden zur Verwendung als strukturierte Katalysatorträger hergestellt. Die selbsttragenden Strukturen zeigten eine enge Mikroporenverteilung, welche Formselektivität induzieren können. Die Eignung dieser Materialien als Katalysatorträger wurde durch Nassimprägnierung von Pulver mit Platin und die Verwendung in einer Modellhydrierung von Olefinen getestet. Es ist anzunehmen, dass die Ergebnisse der Nassimprägnierung und Hydrierung auf Kohlenstoffschaumstrukturen übertragbar sind.
EAM Import::2019-03-12

Synthese und Charakterisierung von kronenetherstabilisierten Platin(IV)-Komplexen mit Aminosäureliganden - Steinborn, Dirk; Gravenhorst, Olaf; Junicke, H.; Heinemann, Frank Wilhelm (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 1998)

Synthesis and Catalytic Performance of Aluminium-containing Mesoporous, Spherical Silica Particles - Weissenberger, Tobias; Machoke, Albert; Kolle, Joel M.; Avadhut, Yamini; Hartmann, Martin; Schwieger, Wilhelm (Chemie Ingenieur Technik, 2021)
A one-pot synthesis of aluminium-containing mesoporous silica particles (Al-MSPs) utilizing polyvinyl alcohol (PVA) as steric stabilization agent is reported. PVA prevents particle agglomeration even when the ionic aluminium source is present in the synthesis mixture. Silicon and aluminium sources were utilised completely, resulting in high yield and easy adjustment of the Si/Al ratio. The Al-MSPs showed a spherical morphology, high surface area and were active for the liquid-phase Beckmann rearrangement of cyclohexanone to caprolactam.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Alumina; Beckmann rearrangement; Mesoporous particles; Silica

Synthesis and characterisation of hierarchically structured titanium silicalite-1 zeolites with large intracrystalline macropores - Weissenberger, Tobias; Leonhardt, Rainer; Apeleo Zubiri, Benjamin; Pitínová-Štekrová, Martina; Sheppard, Thomas L; Reiprich, Bastian; Bauer, Jürgen; Dotzel, Ralf; Kahnt, Maik; Schropp, Andreas; Schroer, Christian G; Grunwaldt, J.D.; et al. (Chemistry - A European Journal, 2019)
We report the successful synthesis of hierarchically structured titanium silicalite-1 (TS-1) with large intracrystalline macropores by steam-assisted crystallisation of mesoporous silica particles. The macropore topology was imaged in 3D using electron tomography and synchrotron radiation-based ptychographic X-ray computed tomography, revealing interconnected macropores within the crystals accounting for about 30 % of the particle volume. The study of the macropore formation mechanism revealed that the mesoporous silica particles act as a sacrificial macropore template during the synthesis. Silicon to titanium ratio of the macroporous TS-1 samples was successfully tuned from 100 to 44. The hierarchically structured TS-1 exhibited high activity in the liquid phase epoxidation of 2-octene with hydrogen peroxide. The hierarchically structured TS-1 surpassed a conventional nano-sized TS-1 sample in terms of alkene conversion and showed comparable selectivity to the epoxide. The flexible synthesis route described here can be used to prepare hierarchical zeolites with improved mass transport properties for other selective oxidation reactions. <br

Synthesis and characterization of chiral ionic liquids based on quinine, L-proline and L-valine for enantiomeric recognition - Sintra, Tânia E.; Gantman, Mikhail; Ventura, Sónia P.M.; Coutinho, João A.P.; Wasserscheid, Peter; Schulz, Peter (Journal of Molecular Liquids, 2019)
The separation of enantiomers remains a major challenge for the pharmaceutical industry. In this work, eight chiral ionic liquids (CILs) directly derived from the ‘chiral pool’ were synthesized and characterized in order to develop enantioselective systems, for the chiral resolution. According to their chiral cations, three different groups of CILs were prepared, namely based on quinine, L-proline and L-valine, and their enantiomeric recognition ability evaluated. For that purpose the diastereomeric interactions between a racemic mixture of Mosher's acid sodium salt and each CIL were studied using 19 F NMR spectroscopy. The remarkable chemical shift dispersion induced by some CILs demonstrates their potential application in chiral resolution. Additionally the optical rotation, thermophysical properties and ecotoxicity against the marine bacteria Aliivibrio fischeri of these chiral ionic liquids were addressed.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Chiral ionic liquids; Chiral resolution; Ecotoxicity; Enantioselectivity; Mosher's acid; Thermophysical properties

Synthesis and characterization of manganese containing mesoporous bioactive glass nanoparticles for biomedical applications - Nawaz, Qaisar; Ur Rehman, Muhammad Atiq; Burkovski, Andreas; Schmidt, Jochen; Shahid, Ameen; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2018)
Mesoporous bioactive glass (BG) nanoparticles based in the system: SiO2–P2O5-CaO-MnO were synthesized via a modified Stöber process at various concentrations of Mn (0-7 mol%). The synthesized manganese-doped BG nanoparticles were characterized in terms of morphology, composition, in vitro bioactivity and antibacterial activity. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET) analysis confirmed that the particles had spherical morphology (mean particle size: 110 nm) with disordered mesoporous structure. Energy dispersive X-ray spectroscopy (EDX) confirmed the presence of Mn, Ca, Si and P in the synthesized Mn-doped BG particles. Moreover, X-ray diffraction (XRD) analysis has shown that Mn has been incorporated into the amorphous silica network (bioactive glass). More over, it was found that manganese-doped BG particles form apatite crystals upon being immersed in simulated body fluid (SBF). Inductively coupled plasma atomic emission spectroscopy (ICP-OES) measurements confirmed that Mn is released in a sustained mannerBacillus subtilis , Pseudomonas aeruginosaaeruginosa Staphylococcus aureus . The multifunctional BG nanoparticles for bone tissue engineering. The results indicate that the incorporation of Mn into the bioactive glass network is effective. and <br

Synthesis and characterization of manganese containing mesoporous bioactive glass nanoparticles for biomedical applications - Nawaz, Qaisar; Ur Rehman, Muhammad Atiq; Burkovski, Andreas; Schmidt, Jochen; Beltran, Ana M.; Shahid, Ameen; Alber, Nina K.; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2018)
Mesoporous bioactive glass (BG) nanoparticles based in the system: SiO2-P2O5-CaO-MnO were synthesized via a modified Stober process at various concentrations of Mn (0-7 mol %). The synthesized manganese-doped BG nanoparticles were characterized in terms of morphology, composition, in vitro bioactivity and antibacterial activity. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET) analysis confirmed that the particles had spherical morphology (mean particle size: 110 nm) with disordered mesoporous structure. Energy dispersive X-ray spectroscopy (EDX) confirmed the presence of Mn, Ca, Si and P in the synthesized Mn-doped BG particles. Moreover, X-ray diffraction (XRD) analysis showed that Mn has been incorporated in the amorphous silica network (bioactive glass). Moreover, it was found that manganese-doped BG particles form apatite crystals upon immersion in simulated body fluid (SBF). Inductively coupled plasma atomic emission spectroscopy (ICP-OES) measurements confirmed that Mn is released in a sustained manner, which provided antibacterial effect against Bacillus subtilis, Pseudomonas aeruginosa and Staphylococcus aureus. The results indicate that the incorporation of Mn in the bioactive glass network is an effective strategy to develop novel multifunctional BG nanoparticles for bone tissue engineering.

Synthesis and Properties of Organic Hexahalocerate(III) Salts - Pohako-Esko, Kaija; Wehner, Tobias; Schulz, Peter; Heinemann, Frank Wilhelm; Müller-Buschbaum, Klaus; Wasserscheid, Peter (European Journal of Inorganic Chemistry, 2016)
A series of hexahalocerate(III) salts with the general formula [cation](3)[CeHal(6)] have been prepared by dissolving anhydrous cerium trihalides in imidazolium halide ionic liquids. Complexes with different anions, [CeCl6](3-), [CeBr6](3-) and [CeBr3Cl3](3-), were synthesized and their cationic alkyl chains were varied. To confirm the structures of the prepared salts, X-ray crystallography was used to characterize [BMIM](3)[CeCl6]. Two different crystal structures were found: [BMIM](3)[CeCl6] and the linear coordination polymer [BMIM](x)[Ce(mu-Cl)(2)Cl-2(EtOH)(2)](x) containing coordinated solvent. All the synthesized compounds were characterized by DSC and TGA. The influence of the cationic and anionic structures on the melting points and decomposition temperatures is discussed. Furthermore, the Ce-containing salts [BMIM](3)[CeHal(6)] show interesting photoluminescence properties: intense Ce3+-based 5d-4f-centred emission from the soft UV-B region to the border of visible light is observed that is driven both by direct excitation of Ce3+ as well as by a sensitizer effect of the [BMIM](+) cation.
Keywords: Ionic liquids; Luminescence; Lanthanides; Cerium; Halides

SYNTHESIS AND PROPERTIES OF Sn-CONTAINING MAGADIITE - Supronowicz, Wojciech; Roessner, Frank; Schwieger, Wilhelm; Meilikhov, Mikhail; Esken, Daniel (Clays and Clay Minerals, 2012)
Hydrothermal syntheses of the magadiite, a layered silicate structure, were conducted in the presence of a heteroatom source (SnCl(4)(-)5H(2)O) with the intention of investigating its influence on the resulting material, as well as the possibility of isomorphous replacement of Si by Sn atoms in the above-mentioned structure. For comparison, unmodified magadiite, Al-containing magadiite, and impregnated magadiite were synthesized. The magadiite structure was identified for samples with Sn/Si ratios up to 0.015. Synthetic methods applied to Sn-modified materials were found to be unsuitable for the introduction of Al. The characterization methods used were X-ray diffraction, temperature-programmed reduction, and Si-29 magic angle spinning nuclear magnetic resonance and these revealed the substitution of Si by Sn in the silica layers. No additional acid centers on the surfaces of the modified samples were detected, suggesting the presence of the desired four-coordinate Sn in the silica layers.
Keywords: H-2-TPR; Magadiite; Si-29 MAS NMR; Textural Properties; Tin Silicate; XRD

Synthesis and Red/Ox Reversibility of a Novel Copper‐Iron‐Aluminum Spinel Precursor for Low‐Temperature Water‐Gas‐Shift Reaction - Heinlein, Maximilian; Franken, Tanja (Chemie Ingenieur Technik, 2022)

Synthesis, characterisation and water-gas shift activity of nano-particulate mixed-metal (Al, Ti) cobalt oxides - Wolf, Moritz; Roberts, Stephen J.; Marquart, Wijnand; Olivier, Ezra J.; Luchters, Niels T. J.; Gibson, Emma K.; Catlow, C. Richard A.; Neethling, Jan H.; Fischer, Nico; Claeys, Michael (Dalton Transactions, 2019)
The formation of mixed-metal cobalt oxides, representing potential metal-support compounds for cobalt-based catalysts, has been observed at high conversion levels in the Fischer-Tropsch synthesis over metal oxide-supported cobalt catalysts. An often observed increase in the carbon dioxide selectivity at Fischer-Tropsch conversion levels above 80% has been suggested to be associated to the formation of water-gas shift active oxidic cobalt species. Mixed-metal cobalt oxides, namely cobalt aluminate and cobalt titanate, were therefore synthesised and tested for potential catalytic activity in the water-gas shift reaction. We present a preparation route for amorphous mixed-metal oxides via thermal treatment of metal precursors in benzyl alcohol. Calcination of the as prepared nanoparticles results in highly crystalline phases. The nano-particulate mixed-metal cobalt oxides were thoroughly analysed by means of X-ray diffraction, Raman spectroscopy, temperature-programmed reduction, X-ray absorption near edge structure spectroscopy, extended X-ray absorption fine structure, and high-resolution scanning transmission electron microscopy. This complementary characterisation of the synthesised materials allows for a distinct identification of the phases and their properties. The cobalt aluminate prepared has a cobalt-rich composition (Co1+xAl2-xO4) with a homogeneous atomic distribution throughout the nano-particulate structures, while the perovskite-type cobalt titanate (CoTiO3) features cobalt-lean smaller particles associated with larger ones with an increased concentration of cobalt. The cobalt aluminate prepared showed no water-gas shift activity in the medium-shift temperature range, while the cobalt titanate sample catalysed the conversion of water and carbon monoxide to hydrogen and carbon dioxide after an extended activation period. However, this perovskite underwent vast restructuring forming metallic cobalt, a known catalyst for the water-gas shift reaction at temperatures exceeding typical conditions for the cobalt-based Fischer-Tropsch synthesis, and anatase-TiO2. The partial reduction of the mixed-metal oxide and segregation was identified by means of post-run characterisation using X-ray diffraction, Raman spectroscopy, and transmission electron microscopy energy-dispersive spectrometry.
CRIS-Team WoS Importer:2019-10-04

Synthesis of carbon core–shell pore structures and their performance as supercapacitors - Ariyanto, Ariyanto; Dyatkin, Boris; Zhang, Guirong; Kern, Andreas; Gogotsi, Yury; Etzold, Bastian (Microporous and Mesoporous Materials, 2015)
High-power supercapacitors require excellent electrolyte mobility within the pore network and high electrical conductivity for maximum capacitance and efficiency. Achieving high power typically requires sacrificing energy densities, as the latter demands a high specific surface area and narrow porosity that impedes ion transport. We present a novel solution for this optimization problem: a nanostructured core-shell carbonaceous material that exhibits a microporous carbon core surrounded by a mesoporous, graphitic shell. Our tunable synthesis parameters yielded a structure that features either a sharp or a gradual transition between the core and shell sections. Electrochemical supercapacitor testing using organic electrolyte revealed that these novel core-shell materials outperform carbons with homogeneous pore structures. The hybrid core-shell materials showed a combination of good capacitance retention, typical for the carbon present in the shell and high specific capacitance, typical for the core material. These materials achieved power densities in excess of 40 kW kg-1 at energy densities reaching 27 Wh kg-1.
EAM Import::2019-03-12

Synthesis of copper-containing bioactive glass nanoparticles using a modified Stöber method for biomedical applications - Zheng, Kai; Dai, Xinyi; Lu, Miao; Hueser, Norbert; Taccardi, Nicola; Boccaccini, Aldo R. (Colloids and Surfaces B-Biointerfaces, 2017)
Keywords: Apatite formation; Bioactive glass nanoparticles; Copper; Ion release; Stöber method

Synthesis of Large Platelets of Egyptian Blue via Pseudomorphosis after NaRUB-18 - Loch, Patrick; Martin, Thomas; Grüner, Michael; Kaupp, Günther; Schwieger, Wilhelm; Breu, Josef (Zeitschrift für Anorganische und Allgemeine Chemie, 2020)
A colored platy substrate with appreciable aspect ratio can improve the hiding power while extending the color range of pearlescent pigments. One of the oldest synthetic pigments, Egyptian blue, possesses a layered structure and a platy morphology, making it a promising colored substrate for pearlescent pigments, which derives its blue color from CuII. Unfortunately, existing synthesis routes are either not technically benign or lack the natural platy morphology. Here, we introduce a new synthesis route starting with large, square-shaped platelets of a synthetic layered sodium silicate (NaRUB-18). As evidenced by Rietveld refinement and scanning electron microscopy, NaRUB-18 can be converted with conservation of this attractive morphology (pseudomorphosis) into Egyptian blue.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Egyptian blue; Layered silicic acid; NaRUB-18; Solid state synthesis: Pseudomorphosis

Synthesis of methanol by hydrogenolysis of biobased methyl formate using highly stable and active Cu-spinel catalysts in slurry and gas phase reactions - Haagen, Vera; Iser, Jakob; Schörner, Markus; Weber, Dennis; Franken, Tanja; Wasserscheid, Peter; Schühle, Patrick (Green Chemistry, 2023)
This contribution deals with a new atom efficient two-stage production route for green methanol (MeOH) from biomass that includes biomass conversion to methyl formate (MF)/formic acid (FA) mixtures followed by hydrogenolysis to MeOH. Herein, we focus on the hydrogenolysis step and propose a materials solution to the problem of catalyst corrosion by the acidic MF/FA mixture formed in the previous biomass oxidation step. We show that Cu0.9Al2O4 spinel materials are very effective hydrogenolysis catalysts for the conversion of MA/FA mixtures to MeOH. Compared to commercial catalysts such as CuO/Cr2O3, the spinel material does not contain hazardous chromium compounds or require them during synthesis. Furthermore, this spinel catalyst shows much lower corrosion than known commercial hydrogenolysis catalysts. By using reactive frontal chromatography, nitrogen sorption, IR-ATR and XRD measurements we show, that CuO/MgO/ZnO/Al2O3 and CuO/Cr2O3 suffer from leaching of copper and chromium in the presence of FA due to the formation of mobile metal formate species. In contrast, the strongly fixed nature of copper in the highly ordered crystal structure of our Cu0.9Al2O4 spinel type catalyst leads to exceptional stability in the presence of FA and in continuous hydrogenolysis experiments for more than 110 h time-on-stream.<br

Synthesis of Microporous Carbon Foams as Catalyst Supports - Glenk, Friedrich; Knorr, Tilman; Schirmer, Matthias; Gütlein, Stefan; Etzold, Bastian (Chemical Engineering & Technology, 2010)
Microporous carbon foams were synthesized as structured catalyst supports by the carbide-derived carbon (CDC) method. The self-supporting foams showed a narrow pore size distribution which seems to induce shape-selective effects during reactions. The applicability of these materials as supports for active metals was tested in a hydrogenation reaction of different olefins with a CDC powder wet impregnated with platinum
EAM Import::2019-03-12
Keywords: Carbide-derived carbon; CDC method; Foams; Microporous carbon; CARBIDE-DERIVED CARBONS; HYDROGEN STORAGE; ACTIVATED CARBON; MONOLITHS; NITROBENZENE; POROSITY; REACTOR

Synthesis of multilamellar MFI-type zeolites under static conditions: The role of gel composition on their properties - Machoke, Albert; Knoke, I. Y.; Lopez-Orozco, S.; Schmiele, Martin; Selvam, Thangaraj; Marthala, Venkata; Spiecker, Erdmann; Unruh, Tobias; Hartmann, Martin; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2014)
The formation of multilamellar MFI-type zeolite has been studied systematically by investigating the crystallization kinetics and the influence of different synthesis parameters under static conditions. Depending on the template amount and alkalinity, multilamellar MFI-type zeolites with different degrees of purity were obtained. In accordance with X-ray diffraction, SAXS and SEM results, highly crystalline multilamellar MFI-type zeolites were obtained within 4 days of crystallization time. Depending on the Si/Al ratio of the synthesis gel, different crystallization rates, textural properties and product morphologies were observed. <br
Keywords: Hierarchical zeolites; Static conditions; ZSM-5; Multilamellar MFI; Nanosheets of MFI

Synthesis of multilamellar MFI-type zeolites under static conditions: The role of gel composition on their properties - Machoke, Albert; Knoke, I. Y.; Lopez-Orozco, S.; Schmiele, Martin; Selvam, Thangaraj; Marthala, V. R. R.; Spiecker, E.; Unruh, Tobias; Hartmann, Martin; Schwieger, Wilhelm; Hartmann, Martin; Spiecker, Erdmann (Microporous and Mesoporous Materials, 2014)
The formation of multilamellar MFI-type zeolite has been studied systematically by investigating the crystallization kinetics and the influence of different synthesis parameters under static conditions. Depending on the template amount and alkalinity, multilamellar MFI-type zeolites with different degrees of purity were obtained. In accordance with X-ray diffraction, SAXS and SEM results, highly crystalline multilamellar MFI-type zeolites were obtained within 4 days of crystallization time. Depending on the Si/Al ratio of the synthesis gel, different crystallization rates, textural properties and product morphologies were observed. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Nanosheets of MFI; Multilamellar MFI; Hierarchical zeolites; ZSM-5; Static conditions

Synthesis of silver nanoparticle necklaces without explicit addition of reducing or templating agents - Hanisch, Mathias; Mackovic, Mirza; Taccardi, Nicola; Spiecker, Erdmann; Klupp Taylor, Robin (Chemical Communications, 2012)
Here we report that silver nanoparticle necklaces can be readily formed by treatment of colloidal silica with ammoniacal silver complex solution followed by washing, deposition and ageing. We investigate the morphology of the produced materials and elucidate the key variables that influence this promising new approach to one-dimensional nanostructuring. © The Royal Society of Chemistry 201
Keywords: templating; agent; nano; particle

Synthesis of silver nanoparticles in melts of amphiphilic polyesters - Vasylyev, Serhiy; Damm, Cornelia; Segets, Doris; Hanisch, Mathias; Taccardi, Nicola; Wasserscheid, Peter; Peukert, Wolfgang (Nanotechnology, 2013)
The current work presents a one-step procedure for the synthesis of amphiphilic silver nanoparticles suitable for production of silver-filled polymeric materials. This solvent free synthesis via reduction of Tollens' reagent as silver precursor in melts of amphiphilic polyesters consisting of hydrophilic poly(ethylene glycol) blocks and hydrophobic alkyl chains allows the production of silver nanoparticles without any by-product formation. This makes them especially interesting for the production of medical devices with antimicrobial properties. In this article the influences of the chain length of the hydrophobic block in the amphiphilic polyesters and the process temperature on the particle size distribution (PSD) and the stability of the particles against agglomeration are discussed. According to the results of spectroscopic and viscosimetric investigations the silver precursor is reduced to elemental silver nanoparticles by a single electron transfer process from the poly(ethylene glycol) chain to the silver ion.

Synthesis of the novel MOF hcp UiO-66 employing ionic liquids as a linker precursor - Ermer, Matthias; Mehler, Julian; Kriesten, Martin; Avadhut, Yamini; Schulz, Peter; Hartmann, Martin (Dalton Transactions, 2018)
By using a terephthalate containing ionic liquid, a new metal-organic framework, hcp UiO-66, comprising (Zr12O8(OH)(14)) double clusters and terephthalate ligands has been synthesized. The hydrothermal synthesis of hcp UiO-66 might help to establish metal-organic frameworks for industrial scale applications.

Synthesis of the zeolitic imidazolate framework ZIF-4 from the ionic liquid 1-butyl-3-methylimidazolium imidazolate - Hovestadt, Maximilian; Schwegler, Johannes; Schulz, Peter; Hartmann, Martin (Journal of Chemical Physics, 2018)
A new synthesis route for the zeolitic imidazolate framework ZIF-4 using imidazolium imidazolate is reported. Additionally, the ionic liquid-derived material is compared to conventional ZIF-4 with respect to the powder X-ray diffraction pattern pattern, nitrogen uptake, particle size, and separation potential for olefin/paraffin gas mixtures. Higher synthesis yields were obtained, and the different particle size affected the performance in the separation of ethane and ethylene. Published by AIP Publishing.

Synthesis of ZIF-11-Effect of water residues in the solvent onto the phase transition from ZIF-11 to ZIF-7-III - Reif, Benjamin; Fabisch, Florian; Hovestadt, Maximilian; Hartmann, Martin; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2017)
The syntheses of MOFs and ZIFs are often accompanied by the formation of unwanted byproducts. Also for the ZIF-11 synthesis in N,N-Diethylformamide (DEF), phase impurities have been reported. In this systematic study, water residues in the reaction mixture could be identified as one major reason for the formation of the phase impurity ZIF-7-Ill within the ZIF-11 synthesis. The parameters 'crystallinity' and 'phase index' were introduced to quantify the phase transition. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: ZIF-11 synthesis; Phase transition; ZIF-7-III

Synthesis of ZIF-11 – Influence of the synthesis parameters on the phase purity - Hartmann, Martin; Reif, Benjamin; Paula, Carolin; Fabisch, Florian; Hartmann, Martin; Kaspereit, Malte; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2019)
The synthesis of ZIF-11 in N,N-Diethylformamide (DEF) at varying reaction temperatures, times and different molar compositions of the reaction mixture was investigated in detail in order to identify ranges of the formation of phase-pure ZIF-11. Since it is known that water in the solvent DEF leads to the formation of the phase impurity ZIF-7-III during the ZIF-11 synthesis, all reactions were carried out in DEF exhibiting water contents below 0.1 wt%. The variations of the molar ratio of substrates Zn:bIm:DEF = 1:x:y as well as the synthesis temperature and time revealed a number of phase transitions within the ZIF-11 synthesis. Highly crystalline ZIF-11 was obtained for a molar ratio Zn:bIm:DEF of 1:15:1400 already after 3 h of reaction at 60 degrees C and 100 degrees C. Depending on the reaction vessel, the water content of the solvent as well as the temperature, ZIF-11 transformed to the dense phase ZIF-7-III within different reaction times. It was concluded that ZIF-11 represents a metastable reaction product. SEM images of the samples obtained after different synthesis times showed that ZIF-il undergoes successive dissolution-recrystallization cycles in combination with heterogeneous nucleation. For a reduced amount of solvent, the formation of ZIF-11 proceeded faster, but ZIF-11 with lower maximum relative crystallinity was formed. For lower ratios of solvent to zinc, the time range of stable ZIF-11 formation was smaller as compared to higher solvent amounts. The variations of the ratio of zinc to the linker benzimidazole showed that ZIF-11 formation was slower for lower molar ratios, e.g. 1:2:1400 and 1:4:1400. ZIF-11 with the highest relative crystallinity and a pore volume of 0.43 cm(3) g(-1) was formed after 3-12 h of reaction at molar ratios Zn:bIm:DEF of 1:8:1400 and 1:12:1400. Another phase transition was observed for synthesis times of 6-96 h for a molar ratio of 1:2:1400. Under those conditions, an unidentified layered crystalline product was found and similarities to the layered ZIF-L were identified.
Keywords: Phase transition; ZIF-11 synthesis; Parameter variation; Phase purity; ZIF-7-III

Synthesis of ZIF-11 Membranes: The Influence of Preparation Technique and Support Type - Reif, Benjamin; Somboonvong, Jan; Hartmann, Martin; Kaspereit, Malte; Schwieger, Wilhelm (Membranes, 2021)
Due to its structural features, ZIF-11 is one of the most interesting materials for gas separation applications. Herein, we report a systematic study on the synthesis of ZIF-11 as a supported membrane. For this, we adapted optimized conditions for the ZIF-11 powder synthesis, identified in our previous works, to form ZIF layers on symmetric and asymmetric stainless-steel and asymmetric alpha-Al2O3 supports. Different techniques were investigated for the challenging layer formation, namely, in situ crystallization (ISC), multiple in situ crystallization (MISC), and the seeding and secondary growth (SSG) method. It was possible to deposit ZIF-11 on different supports by ISC and MISC, although it was difficult to obtain complete layers. SSG, in turn, was more effective in forming dense and well-intergrown ZIF-11 layers. This agrees well with the generally accepted fact that seeding considerably facilitates layer formation. Systematic studies of both individual steps of SSG (seeding and secondary growth) led to a basic understanding of layer formation of ZIF-11 on the different supports. The best membranes prepared by rub seeding and secondary growth achieved Knudsen selectivity. Improved gas separation performance is expected if the formation of defects can be avoided.
CRIS-Team WoS Importer:2021-08-06
Keywords: ZIF-11 membrane; seeding and secondary growth; multiple in crystallization

System and method for utilizing hydrogen. - Arlt, Wolfgang; Bösmann, Andreas; Preuster, Patrick; Wasserscheid, Peter (2015)
The system for utilizing hydrogen comprises a transfer hydrogenation device that includes a transfer hydrogenation unit for hydrogenating a material to be hydrogenated, and a hydrogen supplying device for supplying hydrogen for the transfer hydrogenation device. The hydrogen supplying device allows hydrogen to be supplied in a bound form for the transfer hydrogenation device and is provided with a loading unit for loading a carrier medium with hydrogen. [on SciFinder(R)]
Keywords: system utilizing hydrogen

Systematic Experimental Investigations and Modeling of the Heat Transfer in Additively Manufactured Periodic Open Cellular Structures with Diamond Unit Cell - Littwin, Giulia; Röder, Susanne; Freund, Hannsjörg (Industrial & Engineering Chemistry Research, 2021)
Additively manufactured periodic open cellular structures (POCS) represent a new class of structured catalyst carriers due to their favorable characteristics such as high specific surface area, low pressure drop, and remarkable heat transport properties. The periodic, well-defined, and reproducible geometry makes systematic investigations and geometric optimization possible. For a detailed optimization, models for the description of the transport characteristics of POCS are necessary. Besides the geometric parameters of the unit cell, the unit-cell geometry itself has a major effect on the dispersive thermal conductivity. POCS based on the diamond unit cell show a superior dynamic thermal conductivity in comparison to cubic structures and are therefore examined in detail. From the measurement results and the corresponding model parameters, influences of the geometric parameters of the structures are found. This leads to new design correlations for the heat transport in POCS. With this, a model-based optimization of POCS for a specific application, such as strongly exothermic reactions, is possible.
CRIS-Team Scopus Importer:2021-05-14

Tailored catalyst pellet specification for improved fixed-bed transport characteristics: A shortcut method for the model-based reactor design - Pietschak, Alexander; Kaiser, Markus; Freund, Hannsjörg (Chemical Engineering Research & Design, 2018)
tTo improve the transport characteristics of a catalytic fixed-bed via optimal design of catalystpellet specifications such as the pellet diameter it is necessary to account for all physico-chemical phenomena influenced by the pellet. For the approximative description of thetransport phenomena on the catalyst pellet scale a new shortcut method is developed inthis work. It enables a generalized and system independent treatment of the aforementionedprocesses and can be applied to arbitrary reaction networks and reaction kinetic models.Based on linearization and decoupling of the pellet balance equations the method yields ananalytical solution. This allows for model-based design of the reactor-catalyst system viadynamic optimization at reduced computational costs as the use of complex heterogeneousmodels is avoided. In order to ensure accurate predictions of the method, regions with highcatalyst utilization are targeted. To indicate the potential of improved bed transport characteristics, the shortcut method isapplied to the reactor-catalyst system for ethylene oxide synthesis. The system is optimizedin terms of reducing the pressure drop while meeting other reactor performance constraints.The pressure drop could be reduced by more than 60%. The shortcut method is validatedusing a rigorous stand-alone model of the catalyst pellet.
Keywords: Reactor optimization; Thiele modulus; Fixed-bed reactors; Process intensification; Catalyst pellet design

Tailored monolith supports for improved ultra-low temperature water-gas shift reaction - Portela, Raquel; Wolf, Patrick; Marinkovic, Jakob M.; Serrano-Lotina, Ana; Riisager, Anders; Haumann, Marco (Reaction Chemistry & Engineering, 2021)
Supported ionic liquid-phase (SILP) particulate catalysts consisting of Ru-complexes dissolved in an ionic liquid that is dispersed on a gamma-alumina porous substrate facilitate the water-gas shift (WGS) reaction at ultra-low temperatures. In this work, a screening of different ceramic support materials was performed to design a suitable monolithic support to disperse the SILP system with the objective of scaling up the WGS process efficiently. gamma-Alumina-rich channeled monoliths were developed with the use of natural clays as binders (10 wt% bentonite and 20 wt% sepiolite) with the following properties: i) high volume of mesopores to maximize the catalyst loading and successfully immobilize the ionic liquid-catalyst system via capillary forces, ii) mechanical resistance to withstand the impregnation process and the reaction operating conditions, and iii) surface chemistry compatible with a highly active and selective phase for WGS. The developed monolithic-SILP catalyst demonstrated high stability and long-term WGS performance at 130 degrees C with an average steady-state CO conversion of around 30% after 190 h time-on-stream (TOS) and a conversion of 23% after 320 h TOS. Interestingly, the catalyst activity proved essentially unaffected by variation in the water partial pressure during operation due to accumulation of water in the monolith, thus making the system highly durable.
CRIS-Team WoS Importer:2021-08-27

Techno-economic analysis for the synthesis of liquid and gaseous fuels based on hydrogen production via electrolysis - Tremel, Alexander; Wasserscheid, Peter; Baldauf, Manfred; Hammer, Thomas (International Journal of Hydrogen Energy, 2015)
The production of hydrogen from renewable sources by water electrolysis can be coupled to a downstream chemical synthesis. This enables the production of liquid fuels or chemical raw materials that can be used in today's infrastructure. However, it is not clear which synthesis technology fits best to the novel boundary conditions for chemical plants (e.g. small scale, flexible operation). In order to identify the most promising syntheses, different one-stage synthesis systems are evaluated in terms of technology, economics and acceptance. The analysis gives in all cases production costs that are significantly above today's market prices. Fischer-Tropsch (FT) synthesis routes are expected to have a higher public acceptance compared to the other technologies due to the high product similarity to conventional energy carriers (diesel, crude oil). The economic feasibility of synthetic natural gas (SNG) production suffers from the low product price of natural gas as a benchmark, but its technical score is high. Methanol production is identified as the synthesis technology that achieves the highest overall score. The analysis shows that not only techno-economic parameters, but also parameters representing the public acceptance like the fit to the existing infrastructure, have to be considered to identify appropriate technologies that may play a role in future energy systems. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electrolysis; Hydrogen utilization; Hydrogen storage; Chemical synthesis; Synthetic fuel

Temperature Dependence of the Non-Stokesian Charge Transport in Binary Blends of Ionic Liquids - Wachter, Philipp; Zistler, Markus; Schreiner, Christian; Fleischmann, Matthias; Gerhard, Dirk; Wasserscheid, Peter; Barthel, Joseph; Gores, Heiner J. (Journal of Chemical and Engineering Data, 2009)
A comprehensive characterization of an ionic liquid based electrolyte for dye-sensitized solar cells (DSSC) was performed by determination of triiodide diffusion coefficients, viscosities, specific conductivities, and densities. The observed non-Stokesian transport behavior was ensured by determination of triiodide diffusion coefficients with two independent methods, steady-state cyclic voltammetry at ultramicroelectrodes, and polarization measurements at thin layer cells. The electrolyte, consisting of 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF_4]), 1-methyl-3-propylimidazolium iodide ([MPIM][I]), and iodine, was examined at fixed iodine concentration over a broad mixing range with varying ionic liquid molar ratio and over a broad temperature range as well. The triiodide diffusion coefficients and the specific conductivity increase with decreasing [MPIM][I] mole fraction or increasing temperature, caused by decreasing electrolyte viscosity. The Einstein-Stokes ratios strongly increase with increasing [MPIM][I] mole fraction and viscosity and thus do not obey the Einstein-Stokes equation. The magnitude of this strong non-Stokesian behavior decreases with increasing temperature. Additional non-Stokesian behavior was found for [MPIM][I]-rich blends since for these blends the Einstein-Stokes ratios strongly decrease at increasing temperatures and simultaneously decreasing viscosity.

Temperature-dependent surface-enrichment effects of imidazolium-based ionic liquids - Kolbeck, Claudia; Deyko, Alexey; Matsuda, Takashi; Kohler, Florian; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2013)
We present the first systematic study of the influence of temperature on the degree of surface enrichment of 1-alkyl-3-methylimidazolium-based ionic liquids (ILs). Using angle-resolved X-ray photoelectron spectroscopy, we demonstrate that the degree of surface enrichment strongly decreases with increasing temperature for all the studied ILs. For ILs with the same cation, but different anions, [CCIm]Br, [CC Im][TfO] and [CCIm][TfN], no significant differences of the temperature-induced partial loss of surface enrichment are found. Measurements for [CCIm][TfO], [CCIm][TfO] and [CCIm][TfO] indicate a small effect of the chain length. For [CC Im][TfO], a continuous decrease of alkyl surface enrichment is found with increasing temperature, with no abrupt changes at the phase-transition temperature from the smectic A to the isotropic phase, indicating that the surface enrichment is not affected by this phase transition. Loss of order! The surface enrichment of the alkyl chains of five imidazolium-based ionic liquids (ILs) at the liquid/vacuum interface is studied as a function of temperature by angle-resolved X-ray photoelectron spectroscopy; both the anion and the alkyl chain length at the cation are varied. At room temperature, the alkyl chains are enriched at the outer surface. Upon increasing the temperature, the degree of surface enrichment decreases. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Temperature independent description of water adsorption on zeotypes showing a type V adsorption isotherm - Kohler, Tobias; Hinze, Moritz; Müller, Karsten; Schwieger, Wilhelm (Energy, 2017)
New adsorbents like aluminumphosphates (AIPO's) and siliconaluminumphosphates (SAPO's) show high potential for adsorption based heat transformation processes. These adsorbents show IUPAC type V adsorption behavior with the adsorptive water. To model heat transformation processes it is important to describe the adsorption equilibrium independent of temperature. Many groups in this research field use the potential theory by Polanyi to model the adsorption process. However, the classical potential theory is not suited to describe type V adsorption behavior. This work presents an adaption of the potential theory, which enables the temperature independent modeling of the adsorption of water on zeotypes showing a type V adsorption characteristic. The adaption is based on a corrected adsorption enthalpy and consequently on a more valid description of the desorption pressure. The adaption could be verified through our own experiments on ALPO-18, SAPO-18 and TAPSO-34 adsorbents, as well as with isotherms for ALPO-5 from literature, measured at different temperatures using water as adsorptive. The results show that the presented adaption is able to describe the adsorption equilibrium independent of temperature and therefore enables modeling of adsorption based heat transformation processes with the potential theory of adsorption. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Adsorption refrigeration; Energy density; Efficiency; Characteristic curve; SAPO-18; TAPSO-34; Water adsorption

The 2-Propanol Fuel Cell: A Review from the Perspective of a Hydrogen Energy Economy - Brodt, Matthew; Mueller, Karsten; Kerres, Jochen; Katsounaros, Ioannis; Mayrhofer, Karl; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon (Energy Technology, 2021)
The 2-propanol fuel cell has been shown to hold several key advantages over the more established methanol fuel cell, including a comparably high real open-circuit voltage, reduced fuel crossover through a Nafion membrane and a benign toxicological fuel profile. In addition, while the highly selective partial oxidation of 2-propanol to acetone in a fuel cell (rather than the more typical complete combustion of organic fuels to CO2) has been viewed as a disadvantage in the past, recent work has shown that the 2-propanol/acetone couple is compatible with traditional hydrocarbon liquid organic hydrogen carrier (LOHC) systems though transfer hydrogenation. With this approach, a disadvantage of hydrogen LOHC logistics—the steep energy cost of dehydrogenation that must be provided during energy-lean times—can be largely avoided. This LOHC compatibility along with the potential for high fuel-cell performance could place the 2-propanol fuel cell (also referred to as the direct isopropanol fuel cell or DIFC) in a position to enable a hydrogen energy economy while avoiding the drawbacks of molecular hydrogen transport and storage. In this Review, the purpose is to ascertain the state-of-the-art of DIFCs—an understudied yet promising research area with unique advantages and challenges.
CRIS-Team Scopus Importer:2021-07-30
Keywords: 2-propanol fuel cells; direct isopropanol fuel cells; liquid organic hydrogen carriers

The Buoy Effect: Surface Enrichment of a Pt Complex in IL Solution by Ligand Design - Hemmeter, Daniel; Kremitzl, Daniel; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2023)
The targeted enrichment of a Pt complex with an ionic liquid (IL)-derived ligand system in IL solution is demonstrated by using angle-resolved X-ray photoelectron spectroscopy. When the ligand system is complemented with fluorinated side chains, the complex accumulates strongly at the IL/gas interface, while in an equivalent solution of a complex without these substituents no such effect could be observed. This buoy-like behavior induces strong population of the complex at the outermost molecular layer close to surface saturation, which was studied over a range from 5 to 30 %mol. The surface enrichment was found to be most efficient at the lowest concentration, which is particularly favorable for catalytic applications such as supported ionic-liquid-phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-01-20
Keywords: catalysis; ionic liquids; surface analysis; surface enrichment; X-ray photoelectron spectroscopy (XPS)

The Helmholtz Energy Alliance "Energy Efficient Multiphase Chemical Processes" - Hampel, Uwe; Dittmeyer, Roland; Patyk, Andreas; Wetzel, Thomas; Lange, Ruediger; Freund, Hannsjörg; Schwieger, Wilhelm; Grünewald, Marcus; Schlüter, Michael; Petasch, Uwe (Chemie Ingenieur Technik, 2013)
Energy efficiency is an essential building block of a sustainable economy and an indispensable prerequisite for achieving current international climate goals. The Energy Alliance "Energy efficient multiphase chemical processes" funded by the Helmholtz Association combines expertise and research activities in the field of chemical process engineering with the objective to further develop design tools, numerical and experimental techniques as well as new measurement techniques for increased efficiency of chemical multiphase processes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Energy efficiency; Multiphase flow; Reactors

The Power of Technological Innovation - Franke, Jörg; Wasserscheid, Peter; Ihne, Thorsten; Lamp, Peter; Guldner, Jürgen; Zipse, Oliver (Road to Net Zero, 2023)
Achieving the urgent need for rapid decarbonization to meet the 1.5 °C target requires disruptive technological change. In the automotive industry, technological progress is closely linked to improved sustainability, and sustainability goals drive the need for technological innovation. However, new technologies in the mobility sector are fraught with uncertainties that challenge both original equipment manufacturers (OEMs) and their stakeholders, such as suppliers, customers, and policy-makers. Therefore, this chapter focuses on the technical, economic, and environmental evaluation of alternative powertrain concepts and the management of uncertainties associated with emerging technological innovation as part of the broader transition to net zero. Electric mobility plays a central role in the sustainability transition and is characterized by a high degree of variance. Battery electric vehicles (BEVs) are expected to dominate private transport in the future due to their greenhouse gas and pollutant-free operation and high efficiency. In addition to charging infrastructure, the technical challenges currently lie primarily in cell chemistry and power electronics. Advances in battery technology and infrastructure electrification will help eliminate the range problem in the future. Another important future fuel is hydrogen. One application is the fuel cell vehicle, which combines the advantages of a chemical energy carrier with high gravimetric energy density with those of an electrical energy converter. Hydrogen also plays an important role as an energy carrier for specific energy supply processes in manufacturing processes and simplifies the transport of regeneratively generated energy. In addition, hybrid vehicles are a transitional technology, and alternative fuel internal combustion engines can contribute to the decarbonization of the existing fleet and to specific applications. This chapter assesses the performance of alternative powertrains; highlights the interrelationship between powertrain systems, energy ecosystems, and sustainability goals; and identifies future research directions for electric and hydrogen mobilit
Keywords: Electromobility; Hydrogen mobility; Alternative powertrains; Energy ecosystem; Battery technology; Charging technology

The Prospect of Hydrogen Storage Using Liquid Organic Hydrogen Carriers - Modisha, Phillimon M.; Ouma, Cecil N.M.; Garidzirai, Rudaviro; Wasserscheid, Peter; Bessarabov, Dmitri (Energy & Fuels, 2019)
Reducing CO 2 emissions is an urgent global priority. The enforcement of a CO 2 tax, stringent regulations, and investment in renewables are some of the mitigation strategies currently in place. For a smooth transition to renewable energy, the energy storage issue must be addressed decisively. Hydrogen is regarded as a clean energy carrier; however, its low density at ambient conditions makes its storage challenging. The storage of hydrogen in liquid organic hydrogen carriers (LOHC) systems has numerous advantages over conventional storage systems. Most importantly, hydrogen storage and transport in the form of LOHC systems enables the use of the existing infrastructure for fuel. From a thermodynamic point of view, hydrogen storage in LOHC systems requires an exothermic hydrogenation step and an endothermic dehydrogenation step. Interestingly, hydrogenation and dehydrogenation can be carried out at the same temperature level. Under high hydrogen pressures (typically above 20 bar as provided from electrolysis or methane reforming), LOHC charging occurs and catalytic hydrogenation takes place. Under low hydrogen pressures (typically below 5 bar), hydrogen release from the LOHC system takes place. Hydrogen release from charged LOHC systems is always in conflict between highly power-dense hydrogen production and LOHC stability over many charging/discharging cycles. We therefore discuss the role of different catalyst materials on hydrogen productivity and LOHC stability. The use of density functional theory techniques to determine adsorption energies and to identify rate-determining steps in the LOHC conversion processes is also described. Furthermore, the performance of a LOHC dehydrogenation unit is strongly dependent on the applied reactor configuration. Industrial implementation of the LOHC technology has started but is still in an early stage. Related to this, we have identified promising application scenarios for the South African energy market.
CRIS-Team Scopus Importer:2019-05-09

Thermal collapse and hierarchy of polymorphs in a faujasite-type zeolite and its analogous melt-quenched glass - Palenta, Theresia; Fuhrmann, Sindy; Greaves, G. Neville; Schwieger, Wilhelm; Wondraczek, Lothar (Journal of Chemical Physics, 2015)
We examine the route of structural collapse and re-crystallization of faujasite-type (Na, K)-LSX zeolite. As the first step, a rather stable amorphous high density phase HDA(collapse) is generated through an order-disorder transition from the original zeolite via a low density phase LDA(collapse), at around 790 degrees C. We find that the overall amorphization is driven by an increase in the bond angle distribution within T-O-T and a change in ring statistics to 6-membered TO4 (T = Si4+, Al3+) rings at the expense of 4-membered rings. The HDA(amorph) transforms into crystalline nepheline, though, through an intermediate metastable carnegieite phase. In comparison, the melt-derived glass of similar composition, HDA(MQ), crystallizes directly into the nepheline phase without the occurrence of intermediate carnegieite. This is attributed to the higher structural order of the faujasite-derived HDA(collapse) which prefers the re-crystallization into the highly symmetric carnegieite phase before transformation into nepheline with lower symmetry. (C) 2015 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution 3.0 Unported License.

Thermal collapse of SAPO-34 molecular sieve towards a perfect glass - Wondraczek, Lothar; Gao, Guojun; Moencke, Doris; Selvam, Thangaraj; Kuhnt, Andreas; Schwieger, Wilhelm; Palles, Dimitrios; Kamitsos, Efstratios I. (Journal of Non-Crystalline Solids, 2013)
Controlled collapse of a silicoaluminophosphate molecular sieve CHA-type SAPO-34 by thermal aging was studied in a multi-method approach. Structural changes and the mechanism of order-disorder-order transitions during collapse were followed for varying annealing conditions between 1000 and 1100 degrees C. Collapse of SAPO-34 occurs via the formation of an intermediate amorphous state by the loss of long-range order but preservation to a high degree of short-range order and macroscopic morphology. This intermediate amorphous state with low entropy may be classified as a "perfect glass". Prolonged aging in the collapse regime results in the precipitation of crystalline AlPO4 while the SiO2 species initially remain in an amorphous phase. Further increasing the aging temperature leads to virtually complete recrystallization and, ultimately, melting. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Zeolite; SAPO-34; Collapse; Recrystallization; Thermal aging

THERMAL CONDUCTIVITY OF BIOMORPHIC POROUS SIC BASED CERAMICS - Popovska, Nadejda; Alkhateeb, Emad; Kugler, Tanja; Fröba, Andreas Paul; Leipertz, Alfred (14th International Heat Transfer Conference, 2010)
Biomorphic porous SiC composite ceramics were produced by chemical vapor infiltration and reaction (CVI-R) technique using paper preforms as template. The thermal conductivity of four samples with different composition and microstructure was investigated: a) C-template b) C-SiC, c) C-SiC-Si3N4 and d) SiC coated with a thin layer of TiO2. The SiC-Si3N4 composite ceramic showed enhanced oxidation resistance compared to single phase SiC. However; a key property for the application of these materials at high temperatures is their thermal conductivity. The later was determined experimentally at defined temperatures in the range 298-373K with a laser flash apparatus. It was found that the thermal conductivity of the porous ceramic composites increases in the following order: C-template < C-SiC < C-SiC-Si3N4 < SiC-TiO2. The results were interpreted in regard to the porosity and the microstructure of the ceramics.
Keywords: united

Thermal Conductivity of Hydrocarbon Liquid Organic Hydrogen Carrier Systems: Measurement and Prediction - Bioucas, Francisco; Piszko, Maximilian; Kerscher, Manuel; Preuster, Patrick; Rausch, Michael Heinrich; Koller, Thomas Manfred; Wasserscheid, Peter; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2020)
In this study, the thermal conductivity of diphenylmethane, benzyltoluene, and dibenzyltoluene and their fully hydrogenated counterparts relevant in the context of the liquid organic hydrogen carrier (LOHC) technology was investigated. For the determination of the thermal conductivity between 298.15 and 323.15 K at atmospheric pressure with an expanded uncertainty of 5% (k = 2), a steady-state guarded parallel-plate instrument was used. To discuss the thermal conductivity over a broader temperature range, measurements were also performed for the density of the pure LOHCs and binary mixtures of diphenylmethane and dicyclohexylmethane between 293.15 and 363.15 K by vibrating tube densimetry as well as for the thermal diffusivity and the Fick diffusion coefficient of binary mixtures of diphenylmethane or dicyclohexylmethane with dissolved hydrogen between 323 and 573 K and pressures between 2.7 and 6.2 MPa by dynamic light scattering (DLS). In general, the measured thermal conductivities of the compounds under investigation decrease with increasing temperature and molar mass and with the degree of hydrogenation. For mixtures of diphenylmethane and dicyclohexylmethane, the concentration dependency of the thermal conductivity shows a distinct nonideal behavior. Based on the measured thermal conductivities of the present pure substances and reference data from the literature for selected cyclic hydrocarbons, a prediction method for the thermal conductivity of such systems could be developed, which requires the molar mass and density as sole input parameters. This correlation represents the thermal conductivity of the selected dehydrogenated and hydrogenated substances and of the studied binary mixture between 298 K and their normal boiling temperature, typically within 5%. By comparison with the thermal conductivity data for diphenylmethane and dicyclohexylmethane deduced from the measurement results for thermal diffusivity and density and from literature data for the specific heat, it was found that the prediction method also allows for a reliable estimation of the thermal conductivity of LOHCs up to a temperature of 573 K, which is the relevant temperature range for hydrogen release from the hydrogenated LOHC compounds.
CRIS-Team Scopus Importer:2020-10-16

Thermal Conductivity of Ionic Liquids: Measurement and Prediction - Fröba, Andreas Paul; Rausch, Michael Heinrich; Krzeminski, Kamil; Assenbaum, Daniel; Wasserscheid, Peter; Leipertz, Alfred (International Journal of Thermophysics, 2010)
This study reports thermal-conductivity data for a series of [EMIM] (1-ethyl-3-methylimidazolium)-based ionic liquids (ILs) having the anions [NTf2] (bis(trifluoromethylsulfonyl)imide), [OAc] (acetate), [N(CN)2] (dicyanimide), [C(CN)3] (tricyanomethide), [MeOHPO2] (methylphosphonate), [EtSO4] (ethylsulfate), or [OcSO4] (octylsulfate), and in addition for ILs with the [NTf2]-anion having the cations [HMIM] (1-hexyl-3-methylimidazolium), [OMA] (methyltrioctylammonium), or [BBIM] (1,3-dibutylimidazolium). Measurements were performed in the temperature range between (273.15 and 333.15) K by a stationary guarded parallelplate instrument with a total measurement uncertainty of 3%(k = 2). For all ILs, the temperature dependence of the thermal conductivity can well be represented by a linear temperature dependence of the thermal conductivity can well be represented by a linear equation. While for the [NTf2]-based ILs, a slight increase of the thermal conductivity with increasingmolar mass of the cation is found at a given temperature, the [EMIM]based ILs show a pronounced, approximately linear decrease with increasing molar mass of the different probed anions. Based on the experimental data obtained in this study, a simple relationship between the thermal conductivity,molar mass, and density is proposed for the prediction of the thermal-conductivity data of ILs. For this, also densities were measured for [EMIM][OAc], [EMIM][C(CN)3], and [HMIM][NTf2]. Themean absolute percentage deviation of all thermal-conductivity data for ILs found in the literature from the proposed prediction is about 7 %. This result represents a convenient simplification in the acquisition of thermal conductivity information for the enormous amount of structurally different IL cation/anion combinations available.

Thermal conductivity of porous SiC composite ceramics derived from paper precursor - Popovska, Nadejda; Alkhateeb, Emad; Fröba, Andreas Paul; Leipertz, Alfred (Ceramics International, 2010)
Biomorphic porous SiC composite ceramics were produced by chemical vapor infiltration and reaction (CVI-R) technique using paper precursor as template. The thermal conductivity of four samples with different composition and microstructure was investigated: (a) C-template, (b) C-SiC, (c) C-SiC-Si3N4 and (d) SiC coated with a thin layer of TiO2. The SiC-Si3N4 composite ceramic showed enhanced oxidation resistance compared to single phase SiC. However, a key property for the application of these materials at high temperatures is their thermal conductivity. The later was determined experimentally at defined temperatures in the range 293-373 K with a laser flash apparatus. It was found that the thermal conductivity of the porous ceramic composites increases in the following order: C-template < C-SiC < C-SiC-Si3N4 < SiC-TiO2. The results were interpreted in regard to the porosity and the microstructure of the ceramics. (C) 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Porosity; Thermal conductivity; Thermal applications; Biomorphic SiC ceramics

Thermal decomposition, gas phase hydration and liquid phase reconstruction in the system Mg/Al hydrotalcite/mixed oxide: A comparative study - Mokhtar, M.; Inayat, Alexandra; Ofili, Ifeanyi Jimmy; Schwieger, Wilhelm (Applied Clay Science, 2010)
The thermal decomposition of a synthetic Mg/Al hydrotalcite and the subsequent hydration of the calcined products in the presence of water vapor at 30 degrees C were studied by in situ XRD. A comparative study between the gas phase hydration and reconstruction of calcined hydrotalcite in Na(2)CO(3) solution at 25 and 70 degrees C was investigated. TG coupled to a mass spectrometer was used to study the thermal behaviour of synthetic hydrotalcite. SEM images were taken to show the layering and size of crystals. Thermal decomposition of hydrotalcite led to the formation of a dehydrated intermediate phase at 200 degrees C. followed by crystalline MgO formation at 450 degrees C. Hydration of calcined hydrotalcite in H(2)O/N(2) resulted in the formation of broad pattems of the meixnerite phase after 2 h. This phase retained its structure even after 52 h exposure to water vapor. Reconstruction of the calcined products in carbonated water at 25 and 70 degrees C resulted in intensified patterns of the hydrotalcite phase. Due to the different structural and compositional properties of the layered products obtained by different chemical reactions of the mixed oxide phase a clarification of nomenclature for all phase transforming steps is proposed. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Hydrotalcites; Hydration; Rehydration; Reconstruction; In-situ XRD

Thermal Energy - Sources, Recovery, and Applications - Shah, Yatish (CRC Press, 2018)
The book details sources of thermal energy, methods of capture, and applications. It describes the basics of thermal energy, including measuring thermal energy, laws of thermodynamics that govern its use and transformation, modes of thermal energy, conventional processes, devices and materials, and the methods by which it is transferred. It covers 8 sources of thermal energy: combustion, fusion (solar) fission (nuclear), geothermal, microwave, plasma, waste heat, and thermal energy storage. In each case, the methods of production and capture and its uses are described in detail. It also discusses novel processes and devices used to improve transfer and transformation processe

Thermally Induced Growth of ZnO Nanocrystals on Mixed Metal Oxide Surfaces - Inayat, Alexandra; Makky, Ayman; Giraldo, Jose; Kuhnt, Andreas; Busse, Corinna; Schwieger, Wilhelm (Chemistry - A European Journal, 2014)
An in situ method for the growth of ZnO nanocrystals on Zn/Al mixed metal oxide (MMO) surfaces is presented. The key to this method is the thermal treatment of Zn/Al layered double hydroxides (Zn/Al LDHs) in the presence of nitrate anions, which results in partial demixing of the LDH/MMO structure and the subsequent crystallization of ZnO crystals on the surface of the forming MMO layers. In a first experimental series, thermal treatment of Zn/Al LDHs with different fractions of nitrate and carbonate in the interlayer space was examined by thermogravimetry coupled with mass spectrometry (TG-MS) and in situ XRD. In a second experimental series, Zn/Al LDHs with only carbonate in the interlayer space were thermally treated in the presence of different amounts of an external nitrate source (NH4NO3). All obtained Zn/Al MMO samples were analysed by electron microscopy, nitrogen physisorption and powder X-ray diffraction. The gas phase formed during nitrate decomposition turned out to be responsible for the formation of crystalline ZnO nanoparticles. Accordingly, both interlayer nitrate and the presence of ammonium nitrate led to the formation of supported ZnO nanocrystals with mean diameters between 100 and 400 nm, and both methods offer the possibility to tailor the amount and size of the ZnO crystals by means of the amount of nitrate.
Keywords: layered compounds; mixed metal oxides; nanoparticles; nitrogen oxides; zinc

Thermally stable bis(trifluoromethylsulfonyl)imide salts and their mixtures - Scheuermeyer, Marlene; Kusche, Matthias Manfred; Agel, Friederike; Schreiber, Patrick; Maier, Florian; Steinrück, Hans-Peter; Davis, James H.; Heym, Florian; Jess, Andreas; Wasserscheid, Peter (New Journal of Chemistry, 2016)
We show that both tetraphenylphosphonium bis(trifluoromethylsulfonyl)imide ([PPh4][NTf2]) and Cs[NTf2] are low melting salts of exceptionally high and also very similar thermal stability. This similarity indicates that the thermal stability is dominated by the anion. Moreover, eutectic mixtures of [PPh4][NTf2] and Cs[NTf2] with melting points below 100 degrees C are presented. Surface analysis of the latter in the liquid state reveals a surprising depletion of (PPh4](+) ions from the surface.

Thermal stability studies of zeolites A and X synthesized from South African coal fly ash - Musyoka, Nicholas M.; Petrik, Leslie F.; Hums, Eric; Kuhnt, Andreas; Schwieger, Wilhelm (Research on Chemical Intermediates, 2015)
The thermal stability of zeolites A and X synthesized from coal fly ash was studied by evaluation of TGA-DTA curves obtained on increasing the temperature and by in-situ temperature-programmed XRD analysis. It was found that zeolites A and X were both stable up to approximately 800 A degrees C and retained their characteristic diffraction peaks up to 440 A degrees C, meaning the crystal structure was still stable. Of particular interest was that zeolite X, which has a unique hierarchical morphology, was thermally stable and was, hence, suitable for applications requiring elevated temperatures, for example catalysis and pollution control.
Keywords: Zeolites; Fly ash; Thermal stability; In-situ XRD

Thermochemical and Structural Studies of New Chiral and Achiral Long Alkyl Chain Functionalized Imidazolinium Ionic Liquids - Seidl, Vera; Sternberg, Michelle; Heinemann, Frank Wilhelm; Schmiele, Martin; Unruh, Tobias; Wasserscheid, Peter; Meyer, Karsten (Crystal Growth and Design, 2021)
Adding to the versatile class of ionic liquids (ILs), an entirely new series of imidazolinium-based ionic liquids is reported herein, offering chirality and important thermal characteristics, such as polymorphism, glass transition, and plastic crystalline behavior. An efficient and general procedure for the preparation of long N,N′-alkyl chain-substituted compounds with either saturated (s) or chiral (c) cyclohexyl (cyC6)-substituted imidazolium (Im) backbones, namely, [C12C12RsIm][A] (A = Br-, [BF4]-, [ClO4]-, [PF6]- R = H, Me, iPr) and [C12C12cIm-cyC6][A] (A = Br-, I-, [I3]-, [BF4]-, [ClO4]-, [PF6]-, [SbF6]-, [BPh4]-), was developed, and the novel compounds were studied by thermochemical methods (DSC, TGA), X-ray diffraction in the small angle regime (SAXS), single-crystal X-ray diffraction (SC-XRD), and specific rotation analysis.
CRIS-Team Scopus Importer:2021-10-29

Thermochemical Properties and Dehydrogenation Thermodynamics of Indole Derivates - Konnova, Maria E.; Li, Shao; Bösmann, Andreas; Müller, Karsten; Wasserscheid, Peter; Andreeva, Irina V.; Turovtzev, V. V.; Zaitsau, Dzmitry H.; Pimerzin, Aleksey A.; Verevkin, Sergey P. (Industrial & Engineering Chemistry Research, 2020)
Indole and methylindole are heterocyclic aromatics, which can be hydrogenated and used for hydrogen storage. A huge advantage of heterocyclic components compared to homocyclic aromatics is the lower enthalpy of reaction for hydrogen release by dehydrogenation. In this study, thermochemical properties of indole and 2-methylindole and its partially and fully hydrogenated derivatives have been determined. Hydrogenation of indoles is a two-step reaction, which is highly influenced by reaction thermodynamics. High precision combustion calorimetry was used to measure enthalpies of formation of indole derivatives. The gas-phase enthalpies of formation were derived with the help of vapor pressure measurements. The high-level quantum-chemical methods were used to establish consistency of the experimental data. The standard molar thermodynamic functions of formation (enthalpy, entropy, and Gibbs energy) of indole derivatives were derived. The results showed that the partially hydrogenated species, 2-methylindoline, tends to dehydrogenate easily under hydrogen release conditions. Thus, indoline is only expected in trace amounts in the respective reaction mixture.
CRIS-Team Scopus Importer:2020-12-04

Thermochemical properties of 6,7-benzindole and its perhydrogenated derivative: A model component for liquid organic hydrogen carriers - Kondratev, Stanislav O.; Zaitsau, Dzmitry H.; Vostrikov, Sergey V.; Li, Shao; Bösmann, Andreas; Wasserscheid, Peter; Müller, Karsten; Verevkin, Sergey P. (Fuel, 2022)
Liquid Organic Hydrogen Carriers are substances that store hydrogen by reversible hydrogenation of aromatic compounds. A major advantage is the fact that they enable the safe and dense storage of large amounts of hydrogen. Nitrogen-containing heterocycles, particularly with five-membered rings, have demonstrated the advantage of lower heats of reaction for dehydrogenation compared to homocyclic systems. In this work, 6,7-benzindole and its hydrogenated form, dodecahydro-6,7–benzindole, have been analyzed regarding their thermodynamic properties. The results have been obtained via high-precision combustion calorimetry and accompanied by quantum-chemical calculations to validate the results. The enthalpy of reaction for dehydrogenation has been determined as ΔrHmo(gas) = +348.9 ± 3.5 kJ·mol−1 in the gas phase and ΔrHmo(liq) = +325.7 ± 3.7 kJ·mol−1 in the liquid phase (ΔrHmo(gas) = +58.2 ± 0.6 kJ·molH2–1 and ΔrHmo(liq) = +54.3 ± 0.6 kJ·molH2–1, respectively). This reaction enthalpy is similar to values for other heterocyclic systems like indole and about 11 kJ·molH2–1 lower than that of homocyclic systems, such as perhydro dibenzyl toluene. As a consequence, it can be expected that the temperature needed thermodynamically to enable hydrogen release from dodecahydro-6,7–benzindole will be lower than for the dehydrogenation of perhydro dibenzyl toluene.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Enthalpies of phase transitions; Enthalpy of combustion; Enthalpy of formation; LOHC; Structure–property relationships; Vapor pressure

Thermochemical properties of benzyltoluenes and their hydro- and perhydro-derivatives as key components of a liquid organic hydrogen carrier system - Verevkin, Sergey P.; Vostrikov, Sergey V.; Leinweber, Anatol; Wasserscheid, Peter; Müller, Karsten (Fuel, 2023)
Benzyltoluenes can be utilized for hydrogen storage through reversible hydrogenation in form of pure regioisomers or as isomeric mixture. For the design of the process and in-depth understanding of the reaction, knowledge about the thermochemical properties of the different chemical species is mandatory. This work aims at providing data on relevant thermochemical properties such as vapor pressure, enthalpy of vaporization and enthalpy of formation for benzyltoluenes and their hydro- and perhydro-derivatives forming the respective liquid organic hydrogen carrier (LOHC) system. Combustion calorimetry has been utilized to determine enthalpy of reaction and high-level quantum chemical methods have been applied for validation. It has been found that the different steps of the reaction and reactions of different isomers are similar as expected, but there are still clear differences. For instance, enthalpy of reaction is higher for the hydrogenation of the meta isomer than for the other two isomers. Hydrogenation of the first ring is more exothermal than hydrogenation of the second ring and hydrogenation of the less substituted ring is more exothermal than hydrogenation of the higher substituted ring. These findings shed new light on kinetic observations, which so far have only been explained by steric effects.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Enthalpy of formation; Enthalpy of vaporization; LOHC; Quantum-chemical calculations; Vapor pressure measurements

Thermodynamic Analysis of Chemical Hydrogen Storage: Energetics of Liquid Organic Hydrogen Carrier Systems Based on Methyl-Substituted Indoles - Vostrikov, Sergey V.; Samarov, Artemiy A.; Turovtsev, Vladimir V.; Wasserscheid, Peter; Müller, Karsten; Verevkin, Sergey P. (Materials, 2023)
Liquid organic hydrogen carriers can store hydrogen in a safe and dense form through covalent bonds. Hydrogen uptake and release are realized by catalytic hydrogenation and dehydrogenation, respectively. Indoles have been demonstrated to be interesting candidates for this task. The enthalpy of reaction is a crucial parameter in this regard as it determines not only the heat demand for hydrogen release, but also the reaction equilibrium at given conditions. In this work, a combination of experimental measurements, quantum chemical methods and a group-additivity approach has been applied to obtain a consistent dataset on the enthalpies of formation of different methylated indole derivatives and their hydrogenated counterparts. The results show a namable influence of the number and position of methyl groups on the enthalpy of reaction. The enthalpy of reaction of the overall hydrogenation reaction varies in the range of up to 18.2 kJ·mol−1 (corresponding to 4.6 kJ·mol(H2)−1). The widest range of enthalpy of reaction data for different methyl indoles has been observed for the last step (hydrogenation for the last double bond in the five-membered ring). Here a difference of up to 7.3 kJ·mol(H2)−1 between the highest and the lowest value was found.
CRIS-Team Scopus Importer:2023-04-28
Keywords: enthalpy of formation; enthalpy of vaporization; quantum chemical calculations; structure–property relationships; vapor pressure

Thermodynamic Analysis of lsomerization Equilibria of Chlorotoluenes and Dichlorobenzenes in a Biphasic Reaction Systems Containing Highly Acidic Chloroaluminate Melts - Verevkin, Sergey P.; Meßner, Julia; Emel'Yanenko, Vladimir N.; Gantman, Mikhail; Schulz, Peter; Wasserscheid, Peter (Journal of Physical Chemistry B, 2016)
Thermodynamics and kinetics of the isomerization of chlorotoluenes and dichlorobenzene to the technically desired meta-isomers have been studied in the presence of highly acidic chloroaluminate melts with alkali metal and organic imidazolium cations. Enthalpies of four isomerization processes in reacting systems of chlorotoluenes and dichlorobenzene were obtained from temperature dependencies of the corresponding equilibrium constants in the liquid phase. Experimental reaction enthalpies, enthalpies of vaporization, and absolute vapor pressures of chlorotoluenes and dichlorobenzene have been used for the validation of quantum-chemical methods to predict thermodynamic functions of the four reactions under study successfully. Values of the standard Gibbs energies of formation, standard enthalpies and entropies of formation of chlorotoluenes and dichlorobenzenes in the liquid and in the gas phase have been derived. These values allow optimization of liquidliquid biphasic manufacturing technologies for halogen-substituted benzenes.

Thermodynamic assessment of the stability of bulk and nanoparticulate cobalt and nickel during dry and steam reforming of methane - Wolf, Moritz (RSC Advances, 2021)
The high reaction temperatures during steam and dry reforming of methane inevitably entail catalyst deactivation. Evaluation of the feasibility or potentially relevant mechanisms at play is of utmost importance to develop highly active and stable catalysts. Herein, various oxidation reactions of bulk-sized nickel and cobalt to the corresponding metal oxide or in the presence of a metal oxide carrier are evaluated thermodynamically and linked to approximated conditions during methane reforming. In particular cobalt aluminate, as well as cobalt or nickel titanates are likely to form. As oxidation to bulk-sized metal oxide is unlikely, a thermodynamic analysis of metallic nanoparticles was performed to calculate the size dependent stability against oxidation to nickel oxide or cobalt oxide in water and carbon dioxide-rich environments. The calculations indicate that nickel nanoparticles >3 nm and cobalt nanoparticles >10 nm are expected to withstand oxidation during steam and dry reforming of methane with stoichiometric feed compositions and methane conversion levels >10% at temperatures up to 1100 and 900 °C, respectively. Lastly, the reduced thermal stability of nanoparticles due to melting point suppression was assessed, leading to similar recommendations concerning minimum particle sizes. This journal is
CRIS-Team Scopus Importer:2021-06-11

Thermodynamics of Chemical Hydrogen Storage: Are Sterically Hindered and Overcrowded Molecules More Effective? - Verevkin, Sergey P.; Samarov, Artemiy A.; Turovtsev, Vladimir V.; Vostrikov, Sergey V.; Wasserscheid, Peter; Müller, Karsten (Applied Sciences, 2023)
Homocyclic aromatics with different degrees of alkylation have been investigated so far as Liquid Organic Hydrogen Carriers (LOHC). A low enthalpy of reaction for the dehydrogenation reaction is generally considered beneficial. Values available for crowded, multi-alkylated aromatics, such as hexamethyl benzene, indicate that these substances could be utilized efficiently as LOHCs. However, no clear trend can be identified in the existing data. The aim of this study is to provide a consistent and comprehensive data set on this substance class to evaluate if multi-alkylation is indeed beneficial. For this purpose, own and literature results from experimental methods such as combustion calorimetry and the transpiration method for measuring the enthalpy of vaporisation were combined with quantum chemical approaches to obtain a validated, consistent data set. This comprehensive study reveals that the positive effect on enthalpy of reaction for dehydrogenation is comparatively weak. A slightly lower enthalpy of reaction is actually observed for crowded alkylbenzenes, but it is most likely not sufficient to reach a significant decrease in temperature for hydrogen release. Nevertheless, the results are of high importance for the further development of LOHC systems with optimal structural motifs.
CRIS-Team Scopus Importer:2023-02-03
Keywords: alkylbenzenes; enthalpy of formation; enthalpy of vaporisation; LOHC; quantum-chemical calculations; structure–property correlation; vapour pressure

Thermodynamics of imidazolium based ionic liquids with cyano containing anions - Zaitsau, Dzmitry H.; Pohako-Esko, Kaija; Arlt, Soeren; Emel'Yanenko, Vladimir N.; Schulz, Peter; Wasserscheid, Peter; Schulz, Axel; Verevkin, Sergey P. (Journal of Molecular Liquids, 2017)
Thermochemical investigation of the series of 1-alkyl-3-methylimidazolium ionic liquids with B(CN)(4) and PF2(CN)(4) anions is presented. Absolute vapor pressures and vaporization enthalpies have been measured by using quartz-crystal microbalance. Gas-phase enthalpies of formation of ILs were calculated by using the high-level quantum-chemical method G(3)MP(2). From a combination of experimental and theoretical results, the enthalpy of formation of aqueous B(CN)(4) ion was derived for the first time. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Ionic liquid; Vapor pressure; Enthalpy of vaporization; Enthalpy of formation

Thermodynamics of Reversible Hydrogen Storage: Are Methoxy-Substituted Aromatics better through Oxygen Functionality? - Samarov, Artemiy A.; Müller, Karsten; Wasserscheid, Peter; Verevkin, Sergey P. (Chemical Engineering & Technology, 2024)
An attractive option for the storage of hydrogen is the reversible hydrogenation of an aromatic substance, a so-called liquid organic hydrogen carrier. For hydrogen release, it is desirable to find substances with low enthalpies of reaction for dehydrogenation. It has been demonstrated that substitution, e.g., with methyl groups, on the ring can have a positive effect in this regard. In this study, thermochemical properties of methoxy-substituted pyridines and quinolines and their respective hydrogenated counterparts have been analyzed from a thermodynamic point of view. Combustion calorimetry has been utilized to measure the enthalpy of formation and the transpiration method for determining the vapor pressure. Additionally, high-level quantum-chemical approaches have been applied to obtain caloric data in the gas phase, which provide a basis for comparison and evaluation of the experimental data. The results reveal two main effects of methoxy substitution. First, oxygenated substituents like methoxy groups have stronger effect on the Gibbs energy of reaction and thus the temperature needed thermodynamically for hydrogen release than methyl groups. Second, the effect is highly depending on the position of the substitution on the ring. Particularly methoxy groups close to a N heteroatom can have a significant positive effect, which might enable hydrogen release at equilibrium temperatures more than 50 K lower than for their unsubstituted analogue.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Enthalpy of formation; Enthalpy of vaporization; Liquid organic hydrogen carrier; Quantum-chemical calculations; Structure-property correlation

Thermophysical properties of diphenylmethane and dicyclohexylmethane as a reference liquid organic hydrogen carrier system from experiments and molecular simulations - Kerscher, Manuel; Klein, Tobias; Schulz, Peter; Veroutis, Emmanouil; Dürr, Stefan; Preuster, Patrick; Koller, Thomas Manfred; Rausch, Michael Heinrich; Economou, Ioannis G.; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2020)
This work contributes to the characterization of the liquid organic hydrogen carrier (LOHC) system diphenylmethane/dicyclohexylmethane by the experimental determination and molecular simulation of the thermophysical properties of the dehydrogenated and fully hydrogenated compounds in a process-relevant temperature range of up to 623 K. Liquid density, liquid viscosity, surface tension and liquid self-diffusion coefficient data measured by vibrating-tube densimeters, surface light scattering, rotational viscometry and NMR spectroscopy are correlated and compared with available literature data which are mostly restricted to temperatures below 473 K. Furthermore, it is demonstrated that an L-OPLS force field (FF) modified in the present study outperforms commonly used FFs from literature in predicting the thermophysical properties of both substances by equilibrium molecular dynamics simulations.<br
Keywords: Density; Equilibrium molecular dynamics simulations; Experiment; Liquid organic hydrogen carriers; Surface tension; Viscosity

Thermophysical Properties of Homologous Tetracyanoborate-Based Ionic Liquids Using Experiments and Molecular Dynamics Simulations - Koller, Thomas Manfred; Ramos, Javier; Schulz, Peter; Economou, Ioannis G.; Rausch, Michael Heinrich; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2017)
Thermophysical properties of low-viscosity ionic liquids (ILs) based on the tetracyanoborate ([B(CN)(4)](-)) anion carrying a homologous series of 1-alkyl-3-methylimidazolium ([AMIM](+)) cations [EMIM](+) (ethyl), [BMIM](butyl), [HMIIVI](+) (hexyl), [OMIM]F (octyl), and [DMIM](+) (decyl) were investigated by experimental methods and molecular-dynamics (MD) simulations at atmospheric pressure and various temperatures. Spectroscopic methods based on nuclear magnetic resonance and surface light scattering were applied to measure the ion self-diffusion coefficients-and dynamic viscosity, respectively. In terms of MD simulations, a nonpolaritable molecular model for [EMIM] [B(CN)4] developed by optimization to experimental data was transferred to the other homologous ILs. For the appropriate description of the inter- and tntratnolecular interactions, precise and approximate force fields (FFs) were tested regarding their transferability within the homologous IL series, aiming at reducing the computational effort in molecular simulations. It is shown that at comparable simulated and, experimental densities, the calculated and measured data for viscosity and self-diffusion coefficients of the Its agree well mostly-within combined uncertainties, but deviate stronger for longer-chained ILs using an overly coarse FF model. For the [B(CN)(4)](-)based ILs studied, a comparison with literature data, the influence of varying alkyl-chain length in the cation on their Structural and thermophysical properties, and a correlation between self-diffusivity and viscosity are discussed.

Thermophysical properties of imidazolium tricyanomethanide ionic liquids: experiments and molecular simulation - Zubeir, Lawien F.; Rocha, Marisa A. A.; Vergadou, Niki; Weggemans, Wilko M. A.; Peristeras, Loukas D.; Schulz, Peter; Economou, Ioannis G.; Kroon, Maaike C. (Physical Chemistry Chemical Physics, 2016)
The low-viscous tricyanomethanide ([TCM](-))-based ionic liquids (ILs) are gaining increasing interest as attractive fluids for a variety of industrial applications. The thermophysical properties (density, viscosity, surface tension, electrical conductivity and self-diffusion coefficient) of the 1-alkyl-3-methylimidazolium tricyanomethanide [C(n)mim][TCM] (n = 2, 4 and 6-8) IL series were experimentally measured over the temperature range from 288 to 363 K. Moreover, a classical force field optimized for the imidazolium-based [TCM](-) ILs was used to calculate their thermodynamic, structural and transport properties (density, surface tension, self-diffusion coefficients, viscosity) in the temperature range from 300 to 366 K. The predictions were directly compared against the experimental measurements. The effects of anion and alkyl chain length on the structure and thermophysical properties have been evaluated. In cyano-based ILs, the density decreases with increasing molar mass, in contrast to the behavior of the fluorinated anions, being in agreement with the literature. The contribution per -CH2- group to the increase of the viscosity presents the following sequence: [PF6](-) > [BF4](-) > [Tf2N](-) > [DCA](-) > [TCB](-) > [TCM](-). [TCM](-)-based ILs show lower viscosity than dicyanamide ([DCA](-))- and tetracyanoborate ([TCB](-))-based ILs, while the latter two exhibit a crossover which depends both on temperature and the alkyl chain length of the cation. The surface tension of the investigated ILs decreases with increasing alkyl chain length. [C(2)mim][TCM] shows an outlier behavior compared to other members of the homologous series. The surface enthalpies and surface entropies for all the studied systems have been calculated based on the experimentally determined surface tensions. The relationship between molar conductivity and viscosity was analyzed using the Walden rule. The experimentally determined self-diffusion coefficients of the cations are in good agreement with the molecular simulation predictions, in which a decrease of the self-diffusion of the cations with increasing alkyl chain length is observed with a simultaneous increase in viscosity and for the longer alkyl lengths the anion becomes more mobile than the cation.

Thermophysical properties of the energy carrier methanol under the influence of dissolved hydrogen - Kerscher, Manuel; Jander, Julius Hans; Luther, Fabian; Schühle, Patrick; Richter, Markus; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2023)
Keywords: Isochoric-saturation method; Methanol; Chemical hydrogen storage; Dynamic light scattering; Raman spectroscopy; Thermophysical properties

Thermophysical Properties of the Ionic Liquids [EMIM][B(CN)(4)] and [HMIM][B(CN)(4)] - Koller, Thomas Manfred; Rausch, Michael Heinrich; Ramos, Javier; Schulz, Peter; Wasserscheid, Peter; Economou, Ioannis G.; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2013)
In the present study, the thermophysical properties of the tetracyanoborate-based ionic liquids (ILs) 1-ethyl-3-methylimidazolium tetracyanoborate ([EMIM][B(CN)(4)]) and 1-hexyl-3-methylimidazolium tetracyanoborate ([HMIM][B(CN)(4)]) obtained by both experimental methods and molecular dynamics (MD) simulations are presented. Conventional experimental techniques were applied for the determination of refractive index, density, interfacial tension, and self-diffusion coefficients for [HMIM][B(CN)(4)] at atmospheric pressure in the temperature range from 283.15 to 363.15 K. In addition, surface light scattering (SLS) experiments provided accurate viscosity and interfacial tension data. As no complete molecular parametrization was available for the MD simulations of [HMIM][B(CN)(4)], our recently developed united-atom force field for [EMIM] [B(CN)(4)] was partially transferred to the homologous IL [HMIM][B(CN)(4)]. Deviations between our simulated and experimental data for the equilibrium properties are less than +/- 0.3% in the case of density and less than +/- 8% in the case of interfacial tension for both ILs. Furthermore, the calculated and measured data for the transport properties viscosity and self-diffusion coefficient are in good agreement, with deviations of less than +/- 30% over the whole temperature range. In addition to a comparison with the literature, the influence of varying cation chain length on thermophysical properties of [EMIM] [B(CN)(4)] and [HMIM][B(CN)(4)] is discussed.

Thermophysical properties of the liquid organic hydrogen carrier system based on diphenylmethane with the byproducts fluorene or perhydrofluorene - Kerscher, Manuel; Jander, Julius Hans; Cui, Junwei; Wasserscheid, Peter; Rausch, Michael Heinrich; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2023)
Keywords: Fluorene; Liquid organic hydrogen carrier; Density; Diphenylmethane; Surface tension; Viscosity

The role of the C2 position in interionic interactions of imidazolium based ionic liquids: a vibrational and NMR spectroscopic study - Noack, Kristina; Schulz, Peter; Paape, Natalia; Kiefer, Johannes; Wasserscheid, Peter; Leipertz, Alfred (Physical Chemistry Chemical Physics, 2010)
Methylation of the C2 position of 1,3-dialkylimidazolium based ionic liquids disrupts the predominant hydrogen-bonding interaction between cation and anion leading to unexpected changes of the physicochemical properties. We found the viscosity of 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide [C2C1C1Im][Tf2N], for example, to be about three times higher than that of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C2C1Im][Tf2N]. In order to explain these macroscopic changes upon methylation we investigated the vibrational as well as the magnetic resonance structure of [Tf2N]- salts involving the cations 1-ethyl-3-methylimidazolium [C2C1Im]+, 1-ethyl-2,3-dimethylimidazolium [C2C1C1Im]+, 1-butyl-3-methylimidazolium [C4C1Im]+, and 1-butyl-2,3-dimethylimidazolium [C4C1C1Im]+ by means of Fourier-transform infrared (FTIR), Raman and 13C NMR as well as 1H NMR spectroscopy aiming a better microscopic understanding of the cation–anion interaction. To reveal the impact of methylating the C2 position and changing the alkyl side chain length of the imidazolium a detailed assignment of the individual peaks is followed by a comparative discussion of the spectral features also considering already published work. Our spectroscopic findings deduce electron density changes leading to changes in the position and strength of interionic interactions and reduced configurational variations. Both facts are represented on a macroscopic level by the viscosity and melting point. Therefore changes on a macroscopic level clearly express molecular alterations which in turn can be observed using spectroscopic methods as Raman, IR and NMR.

The urea method for the direct synthesis of ZnAl layered double hydroxides with nitrate as the interlayer anion - Inayat, Alexandra; Klumpp, Michael; Schwieger, Wilhelm (Applied Clay Science, 2011)
ZnAl layered double hydroxides (LDHs) with nitrate as the charge balancing anion in the interlayer space were synthesized by precipitation from homogeneous solution using urea hydrolysis. The composition of the synthesis mixture and the synthesis time were varied in order to identify the parameters, which control if nitrate or carbonate will be the interlayer anion. Especially, the addition of ammonium nitrate turned out to be an effective tool for the synthesis of nitrate containing ZnAl LDHs independent from the synthesis time. Results are mainly based on powder X-ray diffraction measurements of the obtained samples. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Layered double hydroxides; Hydrotalcite-like materials; Synthesis of nitrate form; Urea method; Precipitation from homogeneous solution; XRD pattern

Three-dimensional and quantitative reconstruction of non-accessible internal porosity in hematite nanoreactors using 360 degrees electron tomography - Distaso, Monica; Apeleo Zubiri, Benjamin; Mohtasebi, Amirmasoud; Inayat, Alexandra; Dudak, Michal; Koci, Petr; Butz, Benjamin; Klupp Taylor, Robin; Schwieger, Wilhelm; Spiecker, Erdmann; Peukert, Wolfgang (Microporous and Mesoporous Materials, 2017)
In the current paper, mesocrystals are used as effective precursors to design nanoreactors with different kinds of enclosed porosity. The thermal treatment of hematite mesocrystalline nanoparticles is investigated as a post-processing tool for the engineering of internal organization of hierarchical structures. The porosity of starting materials and of particles thermally treated at different temperatures is investigated by transmission electron microscopy, nitrogen sorption and 360 degrees electron tomography. Virtual Capillary Condensation and Maximum Sphere Inscription are used as independent approaches for the quantitative assessment of internal porosity. The combination of experimental evidences and simulations provides a deep understanding of the internal topology of nanoreactors upon thermal treatment of mesocrystalline particles. This new design strategy may pave the way for exploring the use of the post treated mesocrystals as carriers to encapsulate materials for optoelectronic applications. (C) 2017 Elsevier Inc. All rights reserve
Keywords: Mesocrystals; Inorganic hollow nanoparticles; Compartmentalization; Encapsulation

Three Steps, Two Enzymes, One Pot, but a Multitude of Nanocompartments: Combined Cycles of Kinetic Resolutions and Re-racemization with Incompatible Biocatalysts - Golombek, Florian; Haumann, Marco; Knoll, Matthias; Fröba, Andreas Paul; Castiglione, Kathrin (ACS Omega, 2021)
Deracemizations are clearly preferable to kinetic resolutions in the production of chiral molecules from racemates, as they allow up to 100% chemical and optical yield. Here we present a new process route for multienzymatic deracemizations that is relevant for reaction systems with incompatible reaction conditions of the biocatalysts. This often applies to combinations of lipases used for stereoselective acylation and solvent-sensitive racemases. By encapsulating a model racemase in polymeric vesicles, it was protected from inactivation by the organic solvent up to phase proportions of 99%. As high yields in the lipase reaction required either water proportions well below 1% or racemase-denaturating acyl donor concentrations, a one-pot reaction was implemented through the sequential use of lipase and racemase-containing nanocompartments. This strategy allowed us to perform two kinetic resolutions with intermittent re-racemization in one pot yielding 72% (0.72 mM after 120 h) of an enantiopure product.
CRIS-Team Scopus Importer:2021-11-26

Timing of calcium nitrate addition affects morphology, dispersity and composition of bioactive glass nanoparticles - Zheng, Kai; Taccardi, Nicola; Maria Beltran, Ana; Sui, Baiyan; Zhou, Tian; Marthala, Venkata; Hartmann, Martin; Boccaccini, Aldo R. (RSC Advances, 2016)
Bioactive glass nanoparticles (BGN) are promising materials for a number of biomedical applications. Many parameters related to the synthesis of BGN using sol-gel methods can affect their characteristics. In this study, the influence of timing of calcium nitrate (calcium precursor) addition during processing on BGN characteristics was investigated. The results showed that the addition timing could affect the morphology, dispersity and composition of BGN. With delayed addition of calcium nitrate, larger, more regular and better dispersed BGN could be synthesized while the gap between nominal and actual compositions of BGN was widened. However, the addition timing had no significant influence on structural characteristics, as BGN with different addition-timing of calcium nitrate exhibited similar infrared spectra and amorphous nature. The results also suggested that monodispersed BGN could be synthesized by carefully controlling the addition of calcium nitrate. The synthesized monodispersed BGN could release Si and Ca ions continuously for up to at least 14 days. They also showed in vitro bioactivity and non-cytotoxicity towards rat bone marrow-derived mesenchymal stem cells (rBMSCs). In conclusion, the timing of calcium precursor addition is an essential parameter to be considered when producing BGN which should exhibit monodisperse characteristics for biomedical applications.

Titanium carbide-derived carbon as a novel support for platinum catalysts in direct methanol fuel cell application - Schlange, Alicja; Dos Santos, Antonio Rodolfo; Hasse, Benjamin; Etzold, Bastian; Kunz, Ulrich; Turek, Thomas (Journal of Power Sources, 2012)
The improvement of direct methanol fuel cells (DMFCs) requires the development of highly active catalysts. Carbide-derived carbon (CDC) is a new class of carbon materials which are produced via selective extraction of the non-carbon compounds from metal carbides. Nanoporous carbon with a surface area of 906 m2 g-1 and mean pore size of 3.4 nm was produced in consequence of chlorinating pure titanium carbide. This material was oxidatively treated to create the nucleation sites for the metal precursor. An increase of oxygen content in the carbon sample was observed after the functionalization step. The CDC material was subsequently loaded with 18.62 wt.% platinum, with an average particle size of 1.16 nm, by wet impregnation and chemical reduction. As a result, an enhanced electrochemical activity towards oxygen reduction was observed. The maximum power density of 50.16 mW cm-2 was achieved and is subsequently 18% higher than the value measured for commercial platinum catalyst (20 wt.% Pt) on activated carbon. This increase can be attributed to good catalyst dispersion, high surface area and small platinum cluster sizes, thus, confirming the potential of carbide-derived carbon supported catalysts for DMFC applications.
EAM Import::2019-03-13

Titanium-supported W-containing PEO layers enriched with Mn or Zn in oxidative desulfurization and the zwitterionic liquid effect - Bryzhin, A. A.; Tarkhanova, I. G.; Gantman, Mikhail; Rudnev, V. S.; Vasilyeva, M. S.; Lukiyanchuk, I. V. (Surface & Coatings Technology, 2020)
Titanium-supported oxide layers of W, W + Zn and W + Mn, formed by plasma electrolytic oxidation, were established to catalyze the peroxide oxidation of thiophene. The most active compositions based on Zn-W-containing PEO layers were also tested in the oxidation of a number of organosulfur compounds and diesel fuel desulfurization. Preliminary covering the samples by zwitterionic liquid (ZIL) made it possible to achieve residual sulfur content as low as 6 ppm. The change in the morphology and composition of samples with and without ZIL was studied during catalytic tests. It was found that ZIL reduces the etching of the sample surfaces when interacting with the reaction medium.
CRIS-Team Scopus Importer:2020-04-28
Keywords: MnWO; Oxidative desulfurization; Plasma electrolytic oxidation; Surface behavior; Titanium-supported catalysts; Zwitterionic liquid effect

Top-down vs. bottom-up synthesis of Ga–based supported catalytically active liquid metal solutions (SCALMS) for the dehydrogenation of isobutane - Raman, Narayanan; Söllner, Jakob; Madubuko, Nnamdi; Nair, Sharanya; Taccardi, Nicola; Thommes, Matthias; Haumann, Marco; Wasserscheid, Peter (Chemical Engineering Journal, 2023)
Supported catalytically active liquid metal solutions (SCALMS) catalysts consist of a liquid metal solution of an active metal (e.g., Pd, Rh, Pt, Ni) in a low melting metal (e.g., Ga, In, Sn) deposited on a porous support material. In the current study, we extend and optimize the recently developed top-down synthesis protocol (ultrasonication of gallium metal) to prepare GaPd, GaRh and GaPt SCALMS systems. We compare the morphological differences in the obtained catalyst materials achieved between this approach and the more traditional bottom-up synthesis protocol (in situ thermal decomposition of triethylamino-gallane complex) using electron microscopy. Moreover, the spatial distribution of the catalytically active material in the porous alumina support is evaluated using high resolution argon physisorption measurements. Both techniques strongly indicate that the bottom-up approach leads to a high degree of pore penetration while the gallium droplets are largely on the outer surface in case of the top-down method. Changes to the surface chemistry of the support were also investigated by means of NH3/CO2 temperature programmed desorption. All catalytic systems synthesized by the two synthesis methods, i.e., GaPd, GaRh and GaPt, were tested in a quartz, fixed-bed tubular reactor for isobutane dehydrogenation. All SCALMS materials, irrespective of their individual synthesis protocol, were significantly more active than their pure metal counterparts. The SCALMS catalyst prepared using the bottom-up approach showed initial productivity of 407 gbutenes molM–1 min−1, 832 gbutenes molM–1 min−1, and 963 gbutenes molM–1 min−1 for the GaPd, GaRh and GaPt respectively. These values represent more than twice the initial activity obtained with the top-down synthesized counterparts. This activity difference can be explained by the analytically determined difference in liquid metal droplet size distribution.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Coking; Dehydrogenation; Gallium; Liquid metal; SCALMS; Supported catalyst

Toward Highly Dispersed Mesoporous Bioactive Glass Nanoparticles With High Cu Concentration Using Cu/Ascorbic Acid Complex as Precursor - Zheng, Kai; Kang, Jeonil; Rutkowski, Bogdan; Gaweda, Magdalena; Zhang, Jue; Wang, You; Founier, Niklas; Sitarz, Maciej; Taccardi, Nicola; Boccaccini, Aldo R. (Frontiers in Chemistry, 2019)
Copper (Cu) ions have a variety of advantageous biological functionalities, such as proangiogenic and bactericidal activities. Given the intrinsic biodegradability and biocompatibility, silicate-based mesoporous bioactive glass nanoparticles (MBGNs) are considered as promising platforms for the delivery of Cu ions. However, effective incorporation of Cu into MBGNs still faces challenges, e.g., particle aggregation, the formation of insoluble crystalline Cu-based nanoparticles, and a low loading amount of Cu. We report a novel method to synthesize chemically homogenous and highly dispersed Cu-containing MBGNs (Cu-MBGNs) with tunable Cu concentration by using ascorbic acid/Cu complexes as the precursor of Cu in a microemulsion-assisted sol-gel approach. Cu-MBGNs exhibited a sphere-like shape with a particle size between 100 and 300 nm while their pore size varied from 2 to 10 nm. The inclusion of Cu, regardless of the incorporated concentration, did not significantly affect the morphology of particles. ICP-AES results indicated that the concentration of Cu in the particles could be conveniently tuned from 0 to similar to 6 mol% by controlling the amount of ascorbic acid/Cu complexes added, while the formation of crystalline Cu-based nanoparticles was avoided. The amorphous feature of Cu-MBGNs was proved by XRD, while the predominant oxidation state of Cu was evidenced to be Cu2+ by XPS. The incorporation of Cu did not inhibit the apatite-forming ability (bioactivity) of the particles in contact with simulated body fluid. Cu-MBGNs exhibited the capability of releasing Cu, Si, and Ca ions over time in the physiological fluid. The concentration of released Cu ions could be controlled by selecting specific Cu-MBGNs of different Cu contents. The dissolution products of most Cu-MBGNs at the dosage of 1, 0.1, and 0.01 mg/mL did not exhibit cytotoxicity, while only 7Cu-MBGN was cytotoxic at the dosage of 1 mg/mL. This study provided a feasible strategy to synthesize highly dispersed amorphous Cu-MBGNs with high Cu concentrations for biomedical applications. The particles exhibit great potential as building blocks for developing composite 3D scaffolds, coatings, and drug carriers, particularly when a large amount of particles incorporated may compromise the properties of (polymer) matrix materials while a relatively high concentration of released Cu ions is still required.
CRIS-Team WoS Importer:2019-08-02

Toward ionic-liquid-based model catalysis: Growth, orientation, conformation, and interaction mechanism of the [Tf2N]- anion in [BMIM][Tf2N] thin films on a well-ordered alumina surface - Sobota, Marek; Nikiforidis, Ioannis; Hieringer, Wolfgang; Paape, Natalia; Happel, Markus; Steinrück, Hans-Peter; Görling, Andreas; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Langmuir, 2010)
Aiming at a better understanding of the interaction of ionic liquid (IL) thin films with oxide supports, we have performed a model study under ultrahigh vacuum (UHV) conditions. We apply infrared reflection absorption spectroscopy (IRAS) in combination with density functional theory (DFT). Thin films of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][Tf N] are grown on an atomically flat, well-ordered alumina film on NiAl(110) using a novel UHV-compatible evaporator. Time-resolved IRAS measured during the growth and subsequent thermal desorption points toward reversible molecular adsorption and desorption. There was no indication of decomposition. The vibrational bands are assigned with the help of DFT calculations. Strong relative intensity changes in individual [TfN] bands are observed in the monolayer region. This indicates pronounced orientation effects for the anion. The adsorption geometry of [TfN] is determined on the basis of a detailed comparison with DFT. The results suggest that [TfN] anions adopt a cis conformation in the submonolayer region. They adsorb in a slightly tilted orientation with respect to the surface, mainly interacting with the support via the sulfonyl groups. © 2010 American Chemical Society.

Towards a greener synthesis of dianhydrohexitol esters - Städtke, Katrin; Göpfert, Andreas; Inayat, Alexandra (Green Chemistry, 2023)
Esterification is an important reaction mechanism for the conversion of many bio-based molecules. In this work, we study the esterification of bio-based diols isosorbide and isomannide with different short-chain organic acids via two well-established esterification routes. Route 1 is Fischer esterification, i.e. it is catalytic and uses an organic acid as a reaction partner. Route 2 uses a more reactive acid anhydride instead of free acids, and therefore, it is faster and does not require a catalyst and entraining agent. A comparative cradle-to-gate life cycle assessment was conducted to identify the ecological advantages and disadvantages of each esterification route in order to conclude on their greenness and identify points for future improvement. It was found that Route 1 consumes around 30% less energy for the production of the reactants and auxiliaries compared to Route 2. However, Route 2 requires only 10% of the energy for the esterification process because of the much shorter reaction time (3 h) than that of Route 1 (30 h). Since the current global energy source mix is largely fossil-based, impacts related to emissions from energy production dominate the ecological impacts of both routes and scale with the total energy demand. Therefore, Route 2 is currently the greener one in most impact categories (global warming, fossil depletion and human toxicity potential) with the exception of a high water depletion potential (WDP), which is related to the acid anhydride production. If in future only renewable energy from sun, wind and water was used for ester production, both esterification routes would be much greener. With the current global energy mix, the greenness of Route 1 could be enhanced if the reaction time could be shortened, a well reusable catalyst could be found and if the recycling rate of the entrainer and excess acid could be further increased or their amount generally reduced.
CRIS-Team Scopus Importer:2023-09-08

Towards a methodology for the systematic analysis and design of efficient chemical processes Part 1. From unit operations to elementary process functions - Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering and Processing, 2008)
For this purpose, we decompose the chemical process into so-called functional modules that fulfill specific tasks in the course of the process. The functional modules itself can be further decomposed and represented by a linear combination of elementary process functions. These are basis vectors in thermodynamic state space. Within this theoretical framework we can individually examine possible process routes and identify resistances in individual process steps. This allows us to analyze and propose possible options for the intensification of the considered chemical process. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Process intensification; Process route; Process analysis; Process design; Process synthesis; Unit operation; History of chemical engineering; Optimization; Flux; Resistance; State space

Towards a molecular understanding of cation-anion interactions-Probing the electronic structure of imidazolium ionic liquids by NMR spectroscopy, X-ray photoelectron spectroscopy and theoretical calculations - Cremer, Till; Kolbeck, Claudia; Lovelock, Kevin; Paape, Natalia; Woelfel, Rene; Schulz, Peter; Wasserscheid, Peter; Weber, Henry; Thar, Jens; Kirchner, Barbara; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2010)
Ten [CCIm] (1-methyl-3- octylimidazolium)-based ionic liquids with anions Cl, Br , I, [NO], [BF] , [TfO], [PF], [Tf N], [PfN], and [FAP] (TfO = trifluoromethylsulfonate, TfN = bis(trifluoromethylsulfonyl) imide, PfN = bis(pentafluoroethylsulfonyl)imide, FAP = tris-(pentafluoroethyl)trifluorophosphate) and two [CC CIm] (1,2-dimethyl-3-octylimidazolium)-based ionic liquids with anions Br and [TfN] were investigated by using X-ray photoelectron spectroscopy (XPS), NMR spectroscopy and theoretical calculations. WhileH NMR spectroscopy is found to probe very specifically the strongest hydrogen-bond interaction between the hydrogen attached to the C position and the anion, a comparative XPS study provides first direct experimental evidence for cation-anion charge-transfer phenomena in ionic liquids as a function of the ionic liquid's anion. These charge-transfer effects are found to be surprisingly similar for [CCIm] and [CCC Im] salts of the same anion, which in combination with theoretical calculations leads to the conclusion that hydrogen bonding and charge transfer occur independently from each other, but are both more pronounced for small and more strongly coordinating anions, and are greatly reduced in the case of large and weakly coordinating anions. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Towards an efficient liquid organic hydrogen carrier fuel cell concept - Sievi, Gabriel; Geburtig, Denise; Skeledzic, Tanja; Bösmann, Andreas; Preuster, Patrick; Brummel, Olaf; Waidhas, Fabian; Montero, María A.; Khanipourmehrin, Peyman; Katsounaros, Ioannis; Libuda, Jörg; Mayrhofer, Karl; et al. (Energy and Environmental Science, 2019)
The high temperature required for hydrogen release from Liquid Organic Hydrogen Carrier (LOHC) systems has been considered in the past as the main drawback of this otherwise highly attractive and fully infrastructure-compatible form of chemical hydrogen storage. According to the state-of-the art, the production of electrical energy from LOHC-bound hydrogen, e.g. from perhydro-dibenzyltoluene (H18-DBT), requires provision of the dehydrogenation enthalpy (e.g. 65 kJ mol-1 (H2) for H18-DBT) at a temperature level of 300 °C followed by purification of the released hydrogen for subsequent fuel cell operation. Here, we demonstrate that a combination of a heterogeneously catalysed transfer hydrogenation from H18-DBT to acetone and fuel cell operation with the resulting 2-propanol as a fuel, allows for an electrification of LOHC-bound hydrogen in high efficiency (>50%) and at surprisingly mild conditions (temperatures below 200 °C). Most importantly, our proposed new sequence does not require an external heat input as the transfer hydrogenation from H18-DBT to acetone is almost thermoneutral. In the PEMFC operation with 2-propanol, the endothermal proton release at the anode is compensated by the exothermic formation of water. Ideally the proposed sequence does not form and consume molecular H2 at any point which adds a very appealing safety feature to this way of producing electricity from LOHC-bound hydrogen, e.g. for applications on mobile platforms.
CRIS-Team Scopus Importer:2019-07-23

Towards X-ray in-situ visualization of ammonothermal crystal growth of nitrides - Schimmel, Saskia; Künecke, Ulrike; Baser, Hasan-Hüseyin; Steigerwald, Thomas; Hertweck, Benjamin; Alt, Nicolas; Schlücker, Eberhard; Schwieger, Wilhelm; Wellmann, Peter (Physica Status Solidi (C) Current Topics in Solid State Physics, 2014)
In-situ X-ray visualization of hydrothermal growth of silicalite- 1 is applied as an intermediate step for developing X-ray in-situ visualization techniques for ammonothermal growth of nitride materials. In-situ X-ray imaging of silicalite-1 crystals grown by the bulk material dissolution technique (Shimizu and Hamada, Angew. Chem., Int. Ed. 38, 2725 (1999) [1]) is demonstrated using a stainless steel autoclave equipped with ceramic aluminium oxide windows. Processes in the reaction medium such as local density changes are also visualized. The transferability of the technique to ammonothermal growth of nitrides is evaluated. Furthermore, the applicability of windowless autoclaves for X-ray in-situ monitoring of ammonothermal crystal growth of nitrides is investigated. (C) 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: in-situ X-ray imaging; ammonothermal crystal growth; GaN; nitrides

Traceable Quantitative Risk Assessment Applied to Investment Decision for Local Backups - Weiß, Steffen; Tielemann, Michael; Meyer-Wegener, Klaus (Proc. 3rd Int. Conf on ARES, 2008)
Most organizations have critical data, i.e. customer data or large databases. If these data are lost, organization's existence is in danger. As a consequence, backups for the systems are produced. However, some data are stored only on the computers of employees. These data are usually less critical, but their value cannot be neglected. At DATEV eG in Nuremberg, the question has risen whether it is economically justified to install backup mechanisms for these data. To answer this question, we first present a model to perform an assessment. With the help of this model, we calculate the expected annual cost of repair employees' computers and data including all side effects. Finally the break-even point in cost-efficiency is computed for the example of DATEV eG. © 2008 IEEE.
UnivIS-Import:2015-07-08:Pub.2008.tech.IMMD.IMMD6.tracea

Transesterification of methylsulfate and ethylsulfate ionic liquids - an environmentally benign way to synthesize long-chain and functionalized alkylsulfate ionic liquids - Himmler, Simone; van Hal, Roy; Schulz, Peter; Wasserscheid, Peter; et al. (Green Chemistry, 2006)
A new environmentally friendly method to synthesize long-chain and functionalized alkylsulfate ionic liqs. is reported. The two-step synthesis comprises the synthesis of a methylsulfate or ethylsulfate ionic liq. by direct alkylation in the first step. In the second step, this intermediate is transformed in a transesterification reaction, using different functionalized and non-functionalized alcs., to the corresponding new alkylsulfate melts. The entire reaction sequence is halide-free and liberates methanol or ethanol as the only byproducts. Moreover, it is carried out in a solvent-free manner and scale-up is straight forward. [on SciFinder(R)]
Keywords: alkylsulfate ionic liq prepn

Transfer of Individual Micro- and Nanoparticles for High-Precision 3D Analysis Using 360° Electron Tomography - Przybilla, Thomas; Apeleo Zubiri, Benjamin; Maria Beltran, Ana; Butz, Benjamin; Machoke, Albert; Inayat, Alexandra; Distaso, Monica; Peukert, Wolfgang; Schwieger, Wilhelm; Spiecker, Erdmann (Small Methods, 2017)
A versatile approach is demonstrated, providing a general routine for an extensive and advanced 3D characterization of individually selected micro- and nanoparticles, enabling the combination of complementary and scale-bridging techniques. Quintessential to the method is the transfer of individual particles onto tailored tips using a conventional scanning electron microscope equipped with a suitable micromanipulator. The method enables a damage- and contamination-free preparation of freestanding particles. This is of significant importance for applications addressing the measurement of structural, physical, and chemical properties of specifically selected particles, such as 360° electron tomography, atom probe tomography, nano X-ray tomography, or optical near-field measurements. In this context, the method is demonstrated for 360° electron tomography of micro-/macroporous zeolite particles with sizes in the micrometer range and mesoporous alpha-hematite nanoparticles exhibiting sizes of 50–100 nm, including detailed pre- and post-characterization on the nanoscal
Keywords: 360 degrees electron tomography; dual-beam SEM/FIB; micromanipulation; pick and place; sample preparation

Transformation of porous glasses into MCM-41 containing geometric bodies - Uhlig, Hans; Gimpel, Marie-Luise; Inayat, Alexandra; Glaeser, Roger; Schwieger, Wilhelm; Einicke, Wolf-Dietrich; Enke, Dirk (Microporous and Mesoporous Materials, 2013)
During the transformation the primary pore walls were found to swell into the initial pore space, which is caused by bulk density differences between the non-porous glass walls and the template containing MCM-41 material. A pore volume above 1.0 cm(3)/g and pore diameters above 60 nm were found to be prerequirements for a pseudomorphic transformation of the porous glasses into MCM-41. Furthermore, a complete transformation was only possible for glasses exhibiting sufficiently high surface area, which was not the case for very large pore diameters of around 390 nm. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Pseudomorphic transformation; Controlled pore glass; Porous glass; Hierarchy; MCM-41

Transition metal carbonyl catalysts with ionic liquids for water gas shift reaction under mild conditions. - Szesni, Normen; Wasserscheid, Peter; Fischer, Richard; Haumann, Marco; Werner, Sebastian; Kaiser, Melanie (2011)
Water gas shift reaction catalysts for reaction under mild conditions use a solid support contg. an active catalyst, an ionic liq., and a co-activator, in which the active catalyst is a metal carbonyl of general formulas [M(CO)x(L)yClz], in which M = Cr, Mo, W, Ru, Fe, Co, Rh, Ir, Mn, Re, Ni, Pd, Pt, Cu, Ag, Au, or Zn; x = 0-6, y = 0-4, z = 1-6, and n = 1, 2, 3, 4, or >4; L is a monodentate or oligodentate donor ligand (e.g., amines, phosphanes, phosphite, arsanes, stibanes, or heterocyclic systems, such as pyridine, bipyridine, phenanthroline, or N-heterocyclic carbene ligands). The ionic liq. is of general structure [A]n+[Y],sup.n- (n = 1 or 2), in which Y is an org. or inorg. anion, and A is an onium cation, such as quaternary ammonium, quaternary phosphonium, sulfonium, guanidinium, imidazolium, pyridinium, pyrazolium, and 1,3,5-triazolium. [on SciFinder(R)]
Keywords: water gas shift catalyst ionic liq; supported ionic liq catalyst water gas shift; metal carbonyl water gas shift catalyst

Transition metal catalysis in ionic liquids. - Wasserscheid, Peter (Handbook of Green Chemistry, 2010)
A review was given focusing on the addnl. green chem. aspects that arise from the use of a catalytic transition metal in an ionic liq. reaction mixt. It took into account that catalytically active metals can be present in an ionic liq. as homogeneously dissolved metal-ligand complexes, as nanoclusters/nanoparticles or as part of a classical heterogeneous catalyst that forms a suspension with the ionic liq. [on SciFinder(R)]
Keywords: review transition metal catalysis ionic liq

Transition metal catalysis in ionic liquids. - Wasserscheid, Peter; Schulz, Peter (Ionic Liquids in Synthesis, 2008)
A review; transition metal catalysis in ionic liqs. is discussed. [on SciFinder(R)]
Keywords: review transition metal catalysis ionic liq

Transition of TiO2 nanotubes to nanopores for electrolytes with very low water contents - Wei, Wei; Hauser, Christina; Wei, Wei; Berger, Steffen; Hauser, Christina; Meyer, Karsten; Yang, Mingjun; Schmuki, Patrik (Electrochemistry Communications, 2010)
Over the past decade, the electrochemical formation of self-organized nanotube layers in dilute fluoride containing electrolytes has been studied intensively. In the present work, we show that by anodization of Ti in similar electrolytes but containing only very low water contents, the formation of ordered TiO nanoporous structures can be observed. I.e., the water content in the electrolyte is the critical factor that decides whether self-ordered oxide tubes or pores are formed. This supports the concept that tube formation originates from ordered porous oxide by a "pore-wall- splitting" mechanism. © 2010 Elsevier B.V. All rights reserved.

Transition-state effects of ionic liquids in substitution reactions of Pt-II complexes - Weber, Christian; Puchta, Ralph; van Eikema Hommes, Nico; Wasserscheid, Peter; van Eldik, Rudi (Angewandte Chemie International Edition, 2005)
Keywords: density functional calculations; ionic liquids; kinetics; platinum; reaction mechanisms

Trimerization and tetramerization of ethylene in continuous gas-phase reaction using a Cr-based supported liquid phase catalyst - Müller, Tobias; Dixon, John Thomas; Haumann, Marco; Wasserscheid, Peter (Reaction Chemistry & Engineering, 2019)
Homogeneous Cr-PNP tri- and tetramerization catalysts were dissolved together with the co-catalyst MAO in the high-boiling, non-polar, aliphatic hydrocarbon perhydro-dibenzyltoluene (H18-DBT). The solution was then dispersed onto different high surface area supports. The resulting solid materials were tested in the gas-phase selective oligomerization of ethylene at 43 °C and pressures between 1 and 14 bar. Low activities were observed at ambient pressure. At ethylene pressures of higher than 3 bar the formed 1-hexene and 1-octene condensed inside the porous system, thereby facilitating the dissolution and redistribution of the Cr-PNP catalyst. Further studies were conducted at pressures up to 35 bar at which a change in the primary reaction selectivity from 1-hexene to 1-octene could be observed. Such a selectivity switch is in accordance with previously reported mechanistic and kinetic studies.
CRIS-Team Scopus Importer:2019-05-28

Tunable Photocatalytic Activity of PEO-Stabilized ZnO-Polyoxometalate Nanostructures in Aqueous Solution - Bernhardt, Sarah; Düring, Jasmin; Haschke, Sandra; Barr, Maissa; Stiegler, Lisa; Schühle, Patrick; Bachmann, Julien; Hirsch, Andreas; Gröhn, Franziska (Advanced Materials Interfaces, 2021)
The photocatalytic activity and selectivity of novel binary and ternary composite nanostructures from polyethylene oxide-stabilized zinc oxide (PEO-ZnO) with and without polyoxometalate (H-4[Si(W3O10)(4)], POM) are determined in aqueous solution under UV-light. Mono- and di-COOH-end-functionalized PEO polymers are used as surface modifiers, influencing the morphology and stability of the ZnO nanoparticles being synthesized in water. POM acts as an additional versatile photocatalytically active building block resulting in a ternary hybrid structure with tunable photocatalytic activity. Catalytic selectivity is demonstrated by studying photocatalytic dye degradations as model reactions, where the chemical backbone of the dyes and their charge turn out to be the basis for the selectivity. All samples are characterized with dynamic light scattering, transmission electron microscopy, scanning electron microscopy, light microscopy, and zeta-potential measurements. With the functionalized PEOs, large ZnO clusters consisting of leaves are formed while 2-[2-(2-methoxyethoxy) ethoxy] acetic acid (TODA) yields ZnO flower-like structures.
CRIS-Team WoS Importer:2021-07-09

Tuning catalyst performance in the SILP-catalyzed gas-phase hydroformylation of but-1-ene by choice of the ionic liquid - Schörner, Markus; Schönweiz, Andreas; Vignesh, Stefanie; Mokrushina, Liudmila; Thommes, Matthias; Franke, Robert; Haumann, Marco (Journal of Ionic Liquids, 2023)
For the industrially relevant hydroformylation of but‑1-ene the concept of supported ionic liquid phase (SILP) has been applied previously. In this work, we have studied the influence of the type of ionic liquid (imidazolium and phosphonium based cations, various anions) on the solubility of the three reagents but‑1-ene, carbon monoxide and hydrogen. For the olefin, the predicted solubility values were determined using the COSMO-RS software tool. These data were compared to the experimentally determined values. A correlation between the predicted solubility and the observed activity within similar ILs could be observed. The highest activity could be obtained with the IL [N1888][NTf2]. A variation of the olefin chain length supported the observed correlation between solubility and activity. With increasing chain length, the activity of the SILP catalyst also increased. For the undesired consecutive reaction leading to aldols it was found that the substrate solubility does not significantly influence the activity or hydrocarbon accumulation under the used reaction conditions. The anion had a more pronounced effect on the accumulation of aldols, with hydrophilic Cl− and [EtOSO3]− showing lowest accumulation as well as aldol formation activity, while [NTf2]− showed highest values for both accumulation and formation activity. It was shown that the Kamlet-Taft-parameter β is a suitable value to be correlated with activity and accumulation for different ILs.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Aldol condensation; Hydroformylation; Kamlet-Taft-parameter; Rhodium; Solubility; Supported ionic liquid phase (SILP)

Tuning Hierarchical ZSM-5 Zeolite for Both Gas- And Liquid-Phase Biorefining - Zhao, Shufang; Wang, Wei David; Wang, Lizhuo; Schwieger, Wilhelm; Wang, Wei; Huang, Jun (ACS Catalysis, 2020)
A hierarchical ZSM-5 zeolite with an adjustable mesoporous size is required for many chemical processes including the biorefining of big biomass compounds. In this research, a simple and high-efficiency hard template method has been successfully developed by adopting carbon nanoparticles obtained from carbonation of polyethylene oxide and urea. The abundant -C-O-C- groups on the surface of carbon nanoparticles provide the high hydrophilicity (from -C-O-C- to -C-O-H) in the alkaline synthetic gel solution, which promotes the synthesis of hierarchical ZSM-5 zeolite and the aluminum condensation in the silica framework to improve the Brønsted acidity. The as-synthesized hierarchical zeolites exhibited two sets of channel systems: micropores (∼0.55 nm) are from the MFI framework network, and mesopores (∼12.5 and ∼34.5 nm) result from carbon nanoparticles of 10-40 nm in size, respectively. The hierarchical ZSM-5 with minimized extraframework aluminum species showed catalytic performance with high ethanol conversion (100%) and high stability (lifetime above 30 h) in the ethanol to olefins conversion. Importantly, the diffusion efficiency in ZSM-5 with mesoporous size was remarkably improved, compared to the catalyst with mesoporous size ∼12.5 nm. As the benzylation of mesitylene with benzyl alcohol, the ZSM-5 (∼34.5 nm) sample showed the highest conversion in benzyl alcohol (82.0%) and selectivity in 2-benzyl-1,3,5-trimethylbenzene (74.3%).
CRIS-Team Scopus Importer:2020-02-07
Keywords: benzylation; Brønsted acidity; carbon particles; ethanol dehydration; hierarchical ZSM-5 zeolites

Two-Step Reactive Distillation Process for Cyclohexanol Production from Cyclohexene - Katariya, Amit; Freund, Hannsjörg; Sundmacher, Kai (Industrial & Engineering Chemistry Research, 2009)
The present work deals with a novel and attractive alternative process route for the production of cyclohexanol by indirect hydration of cyclohexene using reactive distillation. The proposed two-step process comprises the esterification of cyclohexene with formic acid followed by the hydrolysis of the formed ester. The principle feasibility of this new process has recently been proved by means of residue curve analysis [Steyer et al. Ind. Eng. Chem. Res 2008, 47, 9581-9587]. In the present contribution, detailed equilibrium stage simulations are performed to identify the optimum design and operating conditions for the coupled reactive distillation column scheme. The simulations reveal that it is possible to achieve almost complete conversion of cyclohexene to cyclohexanol with a comparatively low amount of catalyst. To the best of our knowledge, this is the first time that Such all outstanding performance of a process for the production of cyclohexanol is reported

UiO-66 and hcp UiO-66 Catalysts Synthesized from Ionic Liquids as Linker Precursors - Ermer, Matthias; Mehler, Julian; Rosenberger, Björn; Fischer, Marcus; Schulz, Peter; Hartmann, Martin (ChemistryOpen, 2020)
Using ionic liquids (ILs) as linker precursors, the well-known metal-organic framework (MOF) UiO-66 (Universitetet i Oslo) and the recently reported MOF hcp UiO-66 (hexagonal closed packed) have been successfully synthesized and characterized. The advantage of the applied novel synthesis approach is an economically and environmentally benign work-up procedure, due to the better solubility of the IL. Additionally, the reactivity of the terephthalate anions is increased compared to terephthalic acid, resulting in faster MOF formation with an increased amount of defects in the MOF structure. In order to explore to the influence of defects on the catalytic performance, the cyclisation of citronellal to isopulegol was employed as test reaction. The activity of hcp UiO-66 and fcc UiO-66 (face centered cubic) is improved compared to other MOF or zeolite based catalysts, while the selectivity is similar.
Keywords: UiO-66; metal-organic frameworks; ionic liquids; US damping; citronellal cyclization

Ultra-Low Concentration Monitoring of Catalytic Reactions in Photonic Crystal Fiber - Cubillas, Ana Maria; Schmidt, Matthias; Scharrer, Michael; Euser, Tijmen G.; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (Chemistry - A European Journal, 2012)
Photonic crystal fibers as microreactors: Photonic crystal fibers can be used as microreactors (see figure). As an example, the illustration shows the difference in size between a 10cm cuvette (left), and a photonic crystal fiber (right; not to scale).

Ultra-Low-Temperature Water-Gas Shift Catalysis using Supported Ionic Liquid Phase (SILP) Materials - Werner, Sebastian; Szesni, Normen; Kaiser, Melanie; Fischer, Richard; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2010)
SILP inside the eye of your mind: A new class of water–gas shift catalyst system that outperforms commercial shift catalysts under ultra-low-temperature real gas conditions (T<160 °C) has been developed. The new catalysts consist of [RuCl2(CO)32] dissolved in a chloride ionic liquid and dispersed on a porous basic support using the SILP approach. Its robustness and recyclability make it highly attractive for industrial hydrogen production.

Ultra-low temperature water-gas shift reaction catalyzed by homogeneous Ru-complexes in a membrane reactor - membrane development and proof of concept - Logemann, Morten; Wolf, Patrick; Loipersböck, Jürgen; Schrade, Alexander; Wessling, Matthias; Haumann, Marco (Catalysis: Science and Technology, 2021)
A monolithic membrane reactor combining the supported ionic liquid-phase (SILP) catalyzed ultra-low temperature water-gas shift reaction (WGSR) within situproduct removal is presented. The SILP catalyst consists of the transition metal complex [Ru(CO)3Cl2]2homogeneously dissolved in 1-butyl-2,3-dimethylimidazolium chloride [C4C1C1Im]Cl and supported on alumina pellets. These Ru-SILP pellets are deposited inside the channels of a silicon carbide monolith. The resulting monolithic catalyst is very active and stable in the WGSR in the temperature range between 120 and 160 °C, thereby making full use of the high equilibrium conversion at these conditions. A facilitated transport membrane was coated onto the smooth outside of the SiC monolith to allow preferential removal of CO2compared to H2. The proof of this concept has been shown under industrially relevant conditions using a biogas feed. These results demonstrate, for the first time, the combination of homogeneous SILP catalyzed WGSR with enhancedin situremoval of one of the products (here: CO2)viafacilitated transport membrane separation.
CRIS-Team Scopus Importer:2021-03-19

Ultrasonic monitoring of zeolite A and Metal Organic Frameworks (MOFs) formations: A comparative study - Baser, Hasan-Hüseyin; Schwieger, Wilhelm (Studies in Surface Science and Catalysis, 2008)
We present in this work the use of ultrasonic attenuation (US-Attenuation) as a real-time, in-situ diagnostic tool for monitoring the crystallization of zeolites and MOFs. The results of this examination were analyzed with Avrami kinetic model. The reaction order (n) for the crystallization of CuBTC was found to be 0.91 while for that of zeolite A was 3.32.
Keywords: Zeolite Synthesis; MOF; Kinetic; Ultrasonic Attenuation

Ultrasonic Monitoring of Zeolite Synthesis in Real-time - Schwieger, Wilhelm; Schmachtl, M.; Kim, T. J.; Grill, W.; Herrmann, Ralph; Scharf, Oliver (Ultrasonics, 2000)
Variations of the phase and amplitude of a transmitted ultrasonic wave package were monitored in real time during the synthesis of zeolite A and zeolite X. For both materials, characteristic changes of the measured attenuation and the sound velocity of ultrasonic waves traveling in the reaction fluid were observed, correlating with the processes of gel formation and zeolite crystallization, respectively. Aging effects of the reaction fluids are demonstrated. The observation of the onset of the zeolite crystallization was verified with ex-situ X-ray diffraction (XRD) measurements.
UnivIS-Import:2015-03-09:Pub.2000.tech.ITC.LTCIR.ultras

Ultrasound Measurement as a Tool for in Situ Determination of Filling Degree Under Extreme Conditions - Schwieger, Wilhelm; Baser, Hasan-Hüseyin (Ammonothermal Synthesis and Crystal Growth of Nitrides, 2021)
Ammonothermal syntheses require high pressures and temperatures to realize the supercritical conditions. For this a special autoclave technology is required, which places special demands on both the material and the geometrical design. Characteristics are thick walls, high weight, opaque, narrow interior. Therefore the exact determination of initial weights and in particular filling degrees of liquids, which are liquid only under pressure, becomes difficult. In this section, we are going to compare three methods (i) pumping time measurement, (ii) determination by weighing and (iii) ultrasound for adjusting and/or determining the ammonia filling degree of ammonia in an autoclave are presented and the advantages and disadvantages of the individual methods are compared. In addition it is important to have the Ammonia amount very precise to describe the all the concentrations in the autoclave, even under the ammothermal conditions.
CRIS-Team Scopus Importer:2021-03-05

Underlying core-shell colloidal nanostructure for Beta zeolite membrane formation - Singh, Puyam S.; Aswal, Vinod K.; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2021)
Optimal design of Beta zeolite membrane of a three-dimensional 12-ring interconnected channel system can be vital for environmentally sustainable industrial separation application. A faster route of crystal growth from colloidal solution resulted to formation of poly (nanocrystalline) zeolite Beta membrane. The present SANS study probed the underlying functional diversity of core-shell precursor nanoparticle depending on form and structure factor towards the crystal growth for Beta membrane formation. The data clearly distinguished nanoscale structural arrangements of the synthesis solution before the hydrothermal heat treatment, during the induction and nucleation periods. Initially, shells consisting of organic template, reactive Al species and other dissolved ions surrounded the colloidal silica nanoparticles. Some of the silica cores sizes reduced while the shell thicknesses increased resulting to a heterogeneous colloidal solution system consisting of particles of different core-shell dimensions. The evolution of extra-small core and extra-large shell in the heterogeneous system may be nucleating particles as confirmed by XRD pattern corresponding of zeolite Beta. Deposition of such nucleating particles over the support might led to the formation of Beta zeolite membrane. The SANS profile of the solutions further showed that the nucleating particles were more readily deposited over the zeolite-seeded support than the non-seeded support.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Beta zeolite; Membrane; Nanoscale scattering; Nucleation; Precursor nanoparticle

Understanding the Buoy Effect of Surface-Enriched Pt Complexes in Ionic Liquids: A Combined ARXPS and Pendant Drop Study** - Hemmeter, Daniel; Paap, Ulrike; Wellnhofer, Nicolas; Gezmis, Emine; Kremitzl, Daniel; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2023)
Recently, we demonstrated that Pt catalyst complexes dissolved in the ionic liquid (IL) [C4C1Im][PF6] can be deliberately enriched at the IL surface by introducing perfluorinated substituents, which act like buoys dragging the metal complex towards the surface. Herein, we extend our previous angle-resolved X-ray photoelectron spectroscopy (ARXPS) studies at complex concentrations between 30 and 5 %mol down to 1 %mol and present complementary surface tension pendant drop (PD) measurements under ultraclean vacuum conditions. This combination allows for connecting the microscopic information on the IL/gas interface derived from ARXPS with the macroscopic property surface tension. The surface enrichment of the Pt complexes is found to be most pronounced at 1 %mol. It also displays a strong temperature dependence, which was not observed for 5 %mol and above, where the surface is already saturated with the complex. The surface enrichment deduced from ARXPS is also reflected by the pronounced decrease in surface tension with increasing concentration of the catalyst. We furthermore observe by ARXPS and PD a much stronger surface affinity of the buoy-complex as compared to the free ligands in solution. Our results are highly interesting for an optimum design of IL-based catalyst systems with large contact areas to the surrounding reactant/product phase, such as in supported IL phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-11-10
Keywords: homogeneous catalysis; ionic liquids; surface enrichment; surface tension; X-ray photoelectron spectroscopy (XPS)

Unraveling Structural Details in Ga-Pd SCALMS Systems Using Correlative Nano-CT, 360° Electron Tomography and Analytical TEM - Wirth, Janis; Englisch, Silvan; Drobek, Dominik; Apeleo Zubiri, Benjamin; Wu, Mingjian; Taccardi, Nicola; Raman, Narayanan; Wasserscheid, Peter; Spiecker, Erdmann (Catalysts, 2021)
We present a comprehensive structural and analytical characterization of the highly promising supported catalytically active liquid metal solutions (SCALMS) system. This novel catalyst shows excellent performance for alkane dehydrogenation, especially in terms of resistance to coking. SCALMS consists of a porous support containing catalytically active low-melting alloy particles (e.g., Ga-Pd) featuring a complex structure, which are liquid at reaction temperature. High-resolution 3D characterization at various length scales is required to reveal the complex pore morphology and catalytically active sites’ location. Nano X-ray computed tomography (nano-CT) in combination with electron tomography (ET) enables nondestructive and scale-bridging 3D materials research. We developed and applied a correlative approach using nano-CT, 360°-ET and analytical transmission electron microscopy (TEM) to decipher the morphology, distribution and chemical composition of the Ga-Pd droplets of the SCALMS system over several length scales. Utilizing ET-based segmentations of nano-CT reconstructions, we are able to reliably reveal the homogenous porous support network with embedded Ga-Pd droplets featuring a nonhomogenous elemental distribution of Ga and Pd. In contrast, large Ga-Pd droplets with a high Ga/Pd ratio are located on the surface of SCALMS primary particles, whereas the droplet size and the Ga/Pd ratio decreases while advancing into the porous volume. Our studies reveal new findings about the complex structure of SCALMS which are required to understand its superior catalytic performance. Furthermore, advancements in lab-based nano-CT imaging are presented by extending the field of view (FOV) of a single experiment via a multiple region-of-interest (ROI) stitching approach. <
Keywords: supported catalytically active liquid metal solutions (SCALMS); catalysis; nano-CT; electron tomography; X-ray microscopy; electron microscopy

Untersuchungen zur atmosphärischen Plasmapolymerisation metallorganischer Funktionsschichten für die Energietechnik - Ntourmas, Felix (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

Uptake and release characteristics of serotonin hydrochloride by natural Cuban zeolite containing clinoptilolite and mordenite - Grass, Jan-Paul; Pals, Ulrike; Inayat, Alexandra; Schwieger, Wilhelm; Hartmann, Martin; Dathe, Wilfried (Scientific Reports, 2021)
Serotonin (5-HT) plays an important role in human physiology. An excess of this native regulator within the human gut can be partially controlled by orally consuming zeolite. Therefore, this study focuses on the kinetics of the uptake and release of serotonin hydrochloride (5-HT-hc) by natural Cuban zeolite containing clinoptilolite and mordenite at different pH levels using UV-Vis spectroscopy. 5-HT-hc is stable under the following investigated experimental conditions: incubation temperature of 36 degrees C; and at a pH of 5, 7, and 9. Independent of the zeolite framework, the 5-HT-hc is adsorbed without changing its molecular structure. The uptake and release of 5-HT-hc were not correlated to the textural properties of these aluminosilicates. The investigated zeolites adsorbed 5-HT-hc at about 14 mg per gram zeolite with no large differences observed between different samples. Release studies of 5-HT-hc-loaded zeolite revealed that the 5-HT-hc is strongly bound to the zeolite, and independent of the pH value and zeolite framework only up to 12.7% was released into the water.
CRIS-Team WoS Importer:2021-08-06

Use of a catalyst composition for olefin metathesis in the gas phase and procedure for the olefin metathesis in the gas phase. - Szesni, Normen; Müller, Stephan; Fischer, Richard; Wasserscheid, Peter; Haumann, Marco; Öchsner, Eva; Loekman, Soebiakto; Demin, Arthur (2010)
Highly efficient catalyst compns. for olefin metathesis such as manuf. of ethylene and 1-butene from propylene in the gas phase consist of ionic liqs. contg. dissolved catalysts and supported on inorg. compds. [on SciFinder(R)]
Keywords: inorg compd supported ionic liq catalyst soln olefin metathesis; ethylene butene manuf propylene metathesis reaction catalyst

Vacuum Surface Science Meets Heterogeneous Catalysis: Dehydrogenation of a Liquid Organic Hydrogen Carrier in the Liquid State - Matsuda, Takashi; Taccardi, Nicola; Schwegler, Johannes; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2015)
Ultrahigh vacuum (UHV) surface science techniques are used to study the heterogeneous catalytic dehydrogenation of a liquid organic hydrogen carrier in its liquid state close to the conditions of real catalysis. For this purpose, perhydrocarbazole (PH), otherwise volatile under UHV, is covalently linked as functional group to an imidazolium cation, forming a non-volatile ionic liquid (IL). The catalysed dehydrogenation of the PH unit as a function of temperature is investigated for a Pt foil covered by a macroscopically thick PH-IL film and for Pd particles suspended in the PH-IL film, and for PH-IL on Au as inert support. X-ray photoelectron spectroscopy and thermal desorption spectroscopy allows us to follow in situ the catalysed transition of perhydrocarbazole to carbazole at technical reaction temperatures. The data demonstrate the crucial role of the Pt and Pd catalysts in order to shift the dehydrogenation temperature below the critical temperature of thermal decomposition.
Keywords: heterogeneous catalysis; ionic liquids; liquid organic hydrogen carrier; surface science; x-ray photoelectron spectroscopy

Vanadium pentoxide/carbide-derived carbon core-shell hybrid particles for high performance electrochemical energy storage - Zeiger, Marco; Ariyanto, Teguh; Krüner, Benjamin; Peter, Nicolas J.; Fleischmann, Simon; Etzold, Bastian; Presser, Volker (Journal of Materials Chemistry A, 2016)
A novel, two step synthesis is presented combining the formation of carbide-derived carbon (CDC) and redox-active vanadium pentoxide (V2O5) in a core-shell manner using solely vanadium carbide (VC) as the precursor. In a first step, the outer part of VC particles is transformed to nanoporous CDC owing to the in situ formation of chlorine gas from NiCl2 at 700 °C. In a second step, the remaining VC core is calcined in synthetic air to obtain V2O5/CDC core-shell particles. Materials characterization by means of electron microscopy, Raman spectroscopy, and X-ray diffraction clearly demonstrates the partial transformation from VC to CDC, as well as the successive oxidation to V2O5/CDC core-shell particles. Electrochemical performance was tested in organic 1 M LiClO4 in acetonitrile using half- and asymmetric full-cell configuration. High specific capacities of 420 mA h g-1 (normalized to V2O5) and 310 mA h g-1 (normalized to V2O5/CDC) were achieved. The unique nanotextured core-shell architecture enables high power retention with ultrafast charging and discharging, achieving more than 100 mA h g-1 at 5 A g-1 (rate of 12C). Asymmetric cell design with CDC on the positive polarization side leads to a high specific energy of up to 80 W h kg-1 with a superior retention of more than 80% over 10000 cycles and an overall energy efficiency of up to 80% at low rates.
CRIS-Team Scopus Importer:2023-08-15

Vapor Pressure of water in mixtures with hydrophilic ionic liquids - A contribution to the design of processes for drying of gases by absorption in ionic liquids - Heym, F.; Haber, J.; Korth, W.; Etzold, Bastian; Jess, A. (Chemical Engineering & Technology, 2010)
The low water vapor pressures of mixtures of water with the ionic liquids (ILs), [EMIM][EtSO4] and [BEIM][EtSO4], indicate that a process of gas dehydration by absorption in ILs might be an alternative to the classical absorption process with triethylene glycol (TEG). The activity coefficient for an infinite dilution of water in the IL (xIL → 1), which should be low for efficient dehydration, is only about 0.2 for [EMIM][EtSO4] compared to 0.6 for triethylene glycol. In contrast to TEG, losses by evaporation are excluded with ILs as solvents, because they have a negligible vapor pressure. The number of separation stages needed for the absorption in the IL and for the subsequent regeneration of the water-loaded IL is small, about six and eight, respectively. IL regeneration can be achieved by distillation of water out of the IL (e.g., at 120 °C) and stripping with ambient air, which is not possible in the case of TEG (chemical attack by O2). The low water vapor pressure of mixtures of water with ILs indicates that a process of gas dehydration by absorption in ILs might be an alternative to classical absorption processes. Losses by evaporation are excluded. The number of separation stages needed for this process is small. The IL-regeneration can be achieved by stripping with ambient air. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Absorption; Activity coefficient; Gas dehydration; Ionic liquid; Stripping

Viscosities, Vapor Pressures, and Excess Enthalpies of Choline Lactate + Water, Choline Glycolate + Water, and Choline Methanesulfonate + Water Systems. - Constantinescu, Dana; Schaber, Karlheinz; Agel, Friederike; Klingele, Marco H.; Schubert, Thomas J. S. (Journal of Chemical and Engineering Data, 2007)
This research has been focused on viscosities, vapor-liq. equil. (VLE), and heat of mixing measurements for water with the following choline-based ionic liqs.: choline lactate, choline glycolate, and choline methanesulfonate. Isothermal vapor-liq. equil. were measured by means of a static VLE app. at (303.15, 313.15, and 323.15) K. The exptl. VLE data were correlated using the NRTL and UNIQUAC models, and the root-mean-square deviations are given. Furthermore, the molar excess enthalpies of water + choline glycolate and water + choline lactate ionic liq. systems have been performed at T = (303.15, 315.15, and 323.15) K using a differential scanning calorimeter. The results were fitted to a Redlich-Kister equation to det. the fitting parameters and the mean relative deviations. Viscosities of the binary aq. systems with choline glycolate and choline lactate have been measured at 293.15 K. [on SciFinder(R)]
Keywords: choline salt water binary mixt viscosity excess enthalpy VLE

Viscosity and Surface Tension of Fluorene and Perhydrofluorene Close to 0.1 MPa up to 573 K - Cui, Junwei; Kerscher, Manuel; Jander, Julius Hans; Rüde, Timo; Schulz, Peter; Wasserscheid, Peter; Rausch, Michael Heinrich; Koller, Thomas Manfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2022)
In the present study, the liquid viscosity and surface tension of fluorene (H0-F) and its fully hydrogenated counterpart perhydrofluorene (H12-F), representing process-relevant byproducts of the liquid organic hydrogen carrier (LOHC) system based on diphenylmethane and dicyclohexylmethane and potentially interesting LOHC compounds by themselves, were determined close to 0.1 MPa using different experimental methods. Besides surface light scattering (SLS) allowing for a simultaneous access to both properties up to 573 K, conventional methods in the form of capillary viscometry and pendant-drop tensiometry were applied up to (473 and 523) K, respectively. Furthermore, the liquid density of H12-F was measured by vibrating-tube densimetry from (283 to 473) K. While agreement of the viscosity and surface tension results obtained by SLS and the conventional methods is found in the case of H12-F, this is not given for H0-F, especially with respect to its surface tension, which seems to be caused by SLS-specific effects. H0-F exhibiting a melting point of about 384 K shows larger values for density, surface tension, and viscosity compared to H12-F being liquid at 283 K. The latter compound features stereoisomerism which appears to have a pronounced effect on the thermophysical properties. This could be deduced by comparison with the very limited amount of experimental data for the fluorene-based substances that are available in the literature so far. The extension of the thermophysical property database for H0-F and H12-F under process-relevant conditions can be useful for future studies, particularly in the field of chemical hydrogen storage.
CRIS-Team WoS Importer:2022-09-30

Viscosity, Interfacial Tension, Density, and Refractive Index of Ionic Liquids [EMIM][MeSO3], [EMIM][MeOHPO2], [EMIM][OcSO(4)], and [BBIM][NTf2] in Dependence on Temperature at Atmospheric Pressure - Hasse, Benjamin; Lehmann, Julia; Assenbaum, Daniel; Wasserscheid, Peter; Leipertz, Alfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2009)
This work represents a continuation of former investigations, where viscosity, interfacial tension, density, and refractive index of ionic liquids (ILs) [EMIM][EtSO4] (1-ethyl-3-methylimidazolium ethylsulfate), [EMIM][NTf2] (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide), [EMIM][N(CN)(2)] (1-ethyl-3-methylimidazolium dicyanamide), and [OMA][NTf2)] (trioctylmethylammonium bis(trifluoromethylsulfonyl)imide) were studied. Here, the ILs [EMIM][MeSO3] (1-ethyl-3-methylimidazolium methanesulfonate), [EMIM][MeOHPO2] (1-ethyl-3-methylimidazolium methylphosphonate), [EMIM][OcSO(4)] (1-ethyl-3-methylimidazolium octylsulfate), and [BBIM][NTf2] (1-butyl-3-butylimidazolium bis(trifluoromethylsulfonyl)imide) were investigated again both by conventional techniques and by surface light scattering (SLS). An Abbe refractometer was used for the measurement of the refractive index in the range of (283.15 to 313.15) K with an expanded uncertainty (k = 2) of about 0.0005. The density was measured between (273.15 and 313.15) K with a vibrating tube densimeter and an expanded uncertainty (k = 2) of about 0.02%. The interfacial tension was obtained from the pendant drop technique at a temperature of 293.15 K with an expanded uncertainty (k = 2) of 1%. On the basis of this datum and the temperature dependence of density, the interfacial tension for all relevant temperatures was estimated via an appropriate prediction model. For the ILs studied within this work, at a first-order approximation, the quantity directly accessible by SLS was the ratio of dynamic viscosity to surface tension. Combining the results from SLS with values for density and interfacial tension from conventional methods, the dynamic viscosity could be obtained from (273.15 to 333.15) K with an estimated expanded uncertainty (k = 2) of less than 3%. Besides a comparison with the literature, the major aim of this work was to point out the influence of variations of the anion on thermophysical properties of [EMIM](+)-based ILs. In addition, the effect of different cations was studied in ILs with the [NTf2](-) anion. ILs with equal cations and similar anions can still exhibit different properties, which is interpreted with relevant molecular interactions.

Viscosity, Interfacial Tension, Self-Diffusion Coefficient, Density, and Refractive Index of the Ionic Liquid 1-Ethyl-3-methylimidazolium Tetracyanoborate as a Function of Temperature at Atmospheric Pressure. - Koller, Thomas Manfred; Rausch, Michael Heinrich; Schulz, Peter; Berger, Markus; Wasserscheid, Peter; Economou, Ioannis G.; Leipertz, Alfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2012)
Thermophys. properties of the ionic liq. (IL) [EMIM][B(CN)4] (1-ethyl-3-methylimidazolium tetracyanoborate) were investigated both by conventional techniques and by surface light scattering (SLS) at atm. pressure. The d. was measured between (283.15 and 363.15) K with a vibrating U-tube densimeter. An Abbe refractometer was used for the measurement of the refractive index in the range from (283.15 to 313.15) K. Self-diffusion coeffs. for the cation and anion were measured by NMR spectroscopy from (273.15 to 318.15) K. The interfacial tension was obtained from the pendant drop technique at 297.04 K. Based on this datum and the temp. dependence of d., the interfacial tension for all relevant temps. was estd. via an appropriate prediction model. For the IL studied within the present work, the quantity directly accessible by SLS at low temps. was the ratio of dynamic viscosity to interfacial tension. Combining the results from SLS with the d. and interfacial tension data obtained from conventional methods, the dynamic viscosity could be detd. from (283.15 to 303.15) K. For higher temps., SLS measurements combined with the results for d. allowed the simultaneous detn. of dynamic viscosity and interfacial tension from (313.15 to 363.15) K. Besides a comparison with literature data for [EMIM][B(CN)4], the influence of variation of the anion in [EMIM]-based ILs on thermophys. properties is discussed. It could be shown that the thermophys. properties of [EMIM][B(CN)4] are mainly affected by the distinct charge delocalization in the anion. [on SciFinder(R)]
Keywords: viscosity interfacial tension diffusion density refractive index ethylmethylimidazolium tetracyanoborate

Viscosity, surface tension, and density of binary mixtures of the liquid organic hydrogen carrier diphenylmethane with benzophenone - Kerscher, Manuel; Jander, Julius Hans; Cui, Junwei; Martin, Max; Wolf, Moritz; Preuster, Patrick; Rausch, Michael Heinrich; Wasserscheid, Peter; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
The liquid organic hydrogen carrier (LOHC) diphenylmethane may react to benzophenone in the presence of air, especially at elevated temperatures. Therefore, information about the influence of benzophenone added to diphenylmethane on process-relevant thermophysical properties is required. In the present contribution, the liquid viscosity, surface tension, and liquid density of binary mixtures of diphenylmethane with benzophenone are determined between (283 and 573) K using complementary experimental methods. Investigations on the surface tension by the pendant-drop method and surface light scattering indicate molecular orientation effects of benzophenone at the vapor-liquid interface. With increasing benzophenone content, an increase in density, surface tension, and especially viscosity is found. For the latter property, a distinct change in the temperature dependence is observed at the transition from the liquid to the supercooled liquid state. Furthermore, water dissolved in benzophenone causes changes within 15% and 3% relative to the viscosity and surface tension of benzophenone, respectively.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Benzophenone; Density; Diphenylmethane; Liquid organic hydrogen carrier; Surface tension; Viscosity

Viscosity, surface tension, and density of the liquid organic hydrogen carrier system based on diphenylmethane, biphenyl, and benzophenone - Jander, Julius Hans; Kerscher, Manuel; Cui, Junwei; Wicklein, Johannes; Rüde, Timo; Preuster, Patrick; Rausch, Michael Heinrich; Wasserscheid, Peter; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
Keywords: Biphenyl; Liquid organic hydrogen carrier; Surface tension; Diphenylmethane; Eutectic mixture; Viscosity

Visually Based Characterization of the Incipient Particle Motion in Regular Substrates: From Laminar to Turbulent Conditions - Rodríguez Agudo, José; Han, Jiwon; Park, Jinyoung; Kwon, Sinyoung; Loekman, Soebiakto; Luzi, Giovanni; Lindenberger, Christoph; Delgado, Antonio; Wierschem, Andreas (Journal of Visualized Experiments, 2018)
Two different experimental methods for determining the threshold of particle motion as a function of geometrical properties of the bed from laminar to turbulent flow conditions are presented. For that purpose, the incipient motion of a single bead is studied on regular substrates that consist of a monolayer of fixed spheres of uniform size that are regularly arranged in triangular and quadratic symmetries. The threshold is characterized by the critical Shields number. The criterion for the onset of motion is defined as the displacement from the original equilibrium position to the neighboring one. The displacement and the mode of motion are identified with an imaging system. The laminar flow is induced using a rotational rheometer with a parallel disk configuration. The shear Reynolds number remains below 1. The turbulent flow is induced in a low-speed wind tunnel with open jet test section. The air velocity is regulated with a frequency converter on the blower fan. The velocity profile is measured with a hot wire probe connected to a hot film anemometer. The shear Reynolds number ranges between 40 and 150. The logarithmic velocity law and the modified wall law presented by Rotta are used to infer the shear velocity from the experimental data. The latter is of special interest when the mobile bead is partially exposed to the turbulent flow in the so-called hydraulically transitional flow regime. The shear stress is estimated at onset of motion. Some illustrative results showing the strong impact of the angle of repose, and the exposure of the bead to shear flow are represented in both regimes.
Keywords: Granular Flow; Particle/Fluid Flow; Sediment Transport; Incipient Motion

Volatility of molten salts [Ph4P][NTf2] and Cs[NTf2] - Zaitsau, Dzmitry H.; Gantman, Mikhail; Schulz, Peter; Wasserscheid, Peter; Verevkin, Sergey P. (ChemistryOpen, 2020)
The two ionic compounds [Ph4P][NTf2] and Cs[NTf2] were qualified to be suitable liquid materials for different high temperature applications. Development and optimization of these application techniques require knowledge of the thermodynamic properties of vaporization. Vapor pressures and vaporization enthalpies have been measured by using quartz-crystal microbalance. Solubility parameters and miscibility of ionic liquids in practically relevant solvents were assessed.
CRIS-Team Scopus Importer:2020-12-25
Keywords: ionic liquids; solubility; thermal stability; vapor pressure; vaporization enthalpy

Wasserstoff, chemisch gespeichert - Papp, Christian; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter (Nachrichten aus der Chemie, 2014)
Ein Ansatz, Energie chemisch zu speichern, sind flüssige organische Wasserstoffträger. Die Oberflächenforschung leistet Beiträge zum mechanistischen Verständnis der katalytischen Wasserstofffreisetzung und zieht Schlussfolgerungen für die praktische Anwendung solcher Techniken.

Wasserstofflogistik: flüssige organische Wasserstoffträger: Die flüssige Pfandflasche für unsere Energie - Geißelbrecht, Michael; Auer, Franziska; Kiermaier, Stephan; Wasserscheid, Peter (Chemie in Unserer Zeit, 2023)
Liquid Organic Hydrogen Carriers (LOHCs) represent a promising alternative for the storage and transport of the green energy carrier hydrogen. Compared to conventional methods, such as compression and liquefaction, the LOHC technology offers advantages in terms of safety and loss-free storage at comparable volumetric energy density. Due to reversible chemical bonding of the hydrogen in the LOHC fluid, the latter can be regarded as a liquid returnable bottle. The storage and release take place in each case via a chemical reaction. In this article, various application scenarios of the LOHC technology and related current projects are presented. In summary, it can be stated that the supply of buildings with electricity and heat can be realised by combining LOHC dehydrogenation and a solid oxide fuel cell (SOFC). The climate-neutral supply of industrial parks can be improved by integrating a seasonal LOHC storage system into an existing heating network. The coupling with a combined heat and power plant enables the use of all heat flows and a high storage efficiency. In addition, the LOHC technology can contribute to the realisation of safe, cheap and emission-free rail transport on non-electrified lines. In contrast to the use of gaseous hydrogen as fuel, the existing infrastructure for diesel can be further used for refuelling trains with the liquid LOHC storage medium.
CRIS-Team Scopus Importer:2023-10-20

Water-induced deactivation of cobalt-based Fischer–Tropsch catalysts - Wolf, Moritz; Fischer, Nico; Claeys, Michael (Nature Catalysis, 2020)
CRIS-Team Scopus Importer:2020-11-27

Water-Induced Formation of Cobalt-Support Compounds under Simulated High Conversion Fischer-Tropsch Environment - Wolf, Moritz; Gibson, Emma K.; Olivier, Ezra J.; Neethling, Jan H.; Catlow, C. Richard A.; Fischer, Nico; Claeys, Michael (ACS Catalysis, 2019)
Herein we present a comparative study on the water-induced formation of metal-support compounds from metallic cobalt in a simulated high conversion Fischer-Tropsch environment. Literature on the deactivation of supported cobalt catalysts via oxidation to cobalt(II) oxide or cobalt-support compounds is contradictory due to a lack of use in suitable model catalysts and insufficient direct characterization of the metallic cobalt phase under reaction conditions. The particular carrier materials stabilize the active cobalt nanoparticles, but also dictate the likelihood of the formation of nonactive cobalt-support compounds. In this study, well-defined cobalt nanoparticles of 5 nm were deposited on alumina, silica, and three titania carriers. The stability of the reduced nanoparticles against water-rich H-2 atmospheres during exposure to simulated high Fischer-Tropsch conversion levels was monitored in an in situ magnetometer. Co/SiO2 was shown to be the most stable model catalyst, while various Co/TiO2 model systems readily formed large amounts of cobalt-support compounds at low ratios of the Fischer-Tropsch product H2O to reactant H-2 or even during the preceding reduction of the oxidic precursor. Co/Al2O3 displayed a surprisingly high stability at industrially relevant conditions, in contradiction to thermodynamic predictions. However, cobalt aluminate forms at increased concentrations of water. The existence of hard-to-reduce metal-support compounds in the spent catalysts was confirmed and characterized by means of X-ray absorption near edge structure spectroscopy and high-resolution scanning transmission electron microscopy of the exposed and passivated model catalysts.
CRIS-Team WoS Importer:2019-06-28

Wet milling of H-ZSM-5 zeolite and its effects on direct oxidation of benzene to phenol - Gopalakrishnan, Saiprasath; Yada, S.; Münch, Jörg; Selvam, Thangaraj; Schwieger, Wilhelm; Sommer, Marc; Peukert, Wolfgang (Applied Catalysis A-General, 2007)
The direct oxidation of benzene to phenol with NO over ZSM-5 catalysts suffers from the problem of rapid catalyst deactivation mainly due to the secondary transformation of phenol into heavier hydrocarbon compounds leading to the catalyst coking. In order to investigate the deactivation behavior of the ZSM-5 catalysts during this reaction, a comparative study was performed over ZSM-5 catalysts having different crystal sizes. The original catalyst was milled to two different periods of time to obtain catalysts having various crystal sizes. The original and the milled catalysts were tested for the benzene to phenol reaction to get an insight into the effect of crystal size on the catalyst deactivation. There was a decrease in catalyst deactivation with a decrease in crystal size. An indirect dependence of catalyst deactivation with total acidity was observed. © 2007 Elsevier B.V. All rights reserved.
Keywords: Benzene oxidation; Crystal size; Microreactor; Nitrous oxide; Phenol; ZSM-5

Wetting Behavior and Support Interactions in Imidazolium-Based Supported Ionic Liquid Phase Materials-A Systematic Study by Solid-State Nuclear Magnetic Resonance Spectroscopy - Frosch, Matthias; Tavera Méndez, Cindy Ly; Koch, Angela Barbara; Schörner, Markus; Haumann, Marco; Hartmann, Martin; Wisser, Dorothea (Journal of Physical Chemistry C, 2023)
Supported ionic liquid phase (SILP) catalysts are an extremely promising class of materials that combine advantageous concepts from both homogeneous and heterogeneous catalysis. Optimized SILP catalysts should exhibit a thin, homogeneous, and continuous film of the ionic liquid (IL) to avoid pore blocking and to ensure a good accessibility of the catalyst. Yet, the interactions between the IL and the support, which determine the formation of such a film, are still poorly understood. We investigate here in a systematic way the deposition of three imidazolium-based ILs on silica supports with different surface areas and morphologies using 1H magic angle spinning solid-state nuclear magnetic resonance spectroscopy. We demonstrate that the point of complete surface wetting can be determined by the disappearance of the 1H resonance of isolated silanol groups and that this point depends both on the textural properties of the support material and the chemical properties of the IL.1H chemical shifts also provide valuable insight into hydrogen bonding interactions within the IL and between the IL and the support. They indicate cleavage of the anion-cation hydrogen bonds upon IL deposition and the formation of new hydrogen bonds with the silica surface.
CRIS-Team WoS Importer:2023-05-26

Wilhelm Keim (1934-2018) - Schueth, Ferdi; Wasserscheid, Peter (Angewandte Chemie International Edition, 2019)
Wilhelm "Willi" Keim, professor emeritus at the RWTH Aachen University, passed away on September 30, 2018. Keim was best known for his role in developing the Shell higher olefins process (SHOP), and also made pioneering contributions to the areas of liquid-liquid biphasic catalysis, and green and sustainable chemistry.
CRIS-Team Scopus Importer:2019-05-02

Wilkinson-type catalysts in ionic liquids for hydrogenation of small alkenes: understanding and improving catalyst stability - Kratzer, Eva; Schötz, Simon; Maisel, Sven; Blaumeiser, Dominik; Khan Antara, Sharmin; Ewald, Leon; Dotzel, Daniel; Haumann, Marco; Görling, Andreas; Korth, Wolfgang; Jess, Andreas; Retzer, Tanja (Catalysis: Science and Technology, 2023)
In this work, we apply supported ionic liquid phase (SILP) catalysts to hydrogenate 1-alkenes in a continuous fixed-bed reactor. SILP catalyts were prepared using the ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C4C1Im][NTf2] and tris(triphenylphosphine)rhodium(i) chloride [RhCl(PPh3)3] as a dissolved catalyst. Under isothermal conditions, we observe an increase in activity related to restructuring of the catalyst via formation of supported metal nanoparticles (NPs). Combined in situ infrared spectroscopic and theoretical studies show that NP formation is a step-wise process including the sequential loss of ligands and formation of isolated, supported Rh+-ions as intermediates. To stabilize the highly selective homogeneous catalyst, we systematically vary the experimental conditions (co-feeding of CO) and catalyst design (application of strongly binding CO or chelating xantphos ligand). This knowledge-driven approach results in a stabilization of the molecular Rh complex under hydrogenation conditions.
CRIS-Team Scopus Importer:2023-03-24

Zeolite/aluminum composite adsorbents for application in adsorption refrigeration - Bauer, J.; Herrmann, R.; Mittelbach, W.; Schwieger, Wilhelm; et al. (International Journal of Energy Research, 2009)
Thermally driven adsorption refrigerators, which transform available low-temperature waste heat (from processes, engines, solar radiation, district heat) into useful cooling energy, are a very promising and green technology to reduce the demand for primary energy. To improve their refrigeration performance, new zeolite/aluminum composite adsorbents with optimized sorption and heat transfer properties were prepared following the partial support transformation technique. A direct and binderless contact between the closed zeolite layer and the metal could be established which enables best thermal diffusivity. It is shown by measurements of thermal sorption capacities and kinetics on planar samples and on coated heat exchangers that this causes best sorption performance combined with high mechanical stability.
EAM Import::2019-03-12

Zeolite-Coated Porous Arrays: A Novel Strategy for Enzyme Encapsulation - Marthala, Venkata; Friedrich, Mona; Zhou, Zhou; Distaso, Monica; Reuß, Stephanie; Al-Thabaiti, Shaeel A.; Peukert, Wolfgang; Schwieger, Wilhelm; Hartmann, Martin (Advanced Functional Materials, 2015)
Zeolite Beta-coated stainless steel supports with gradient porosity are employed as filter-panels for lipase encapsulation. Enzyme encapsulation on the stainless steel porous discs is achieved via vacuum infiltration. Subsequently, two lipase-encapsulated zeolite Beta-coated stainless steel discs are attached using an adhesive. The zeolite Beta layer on the stainless steel discs largely prevents lipase leaching in comparison to the stainless steel discs without a zeolite layer. The activity of the lipase-encapsulated, attached zeolite Beta-coated stainless steel porous discs depends on the thickness of the zeolite Beta layer. It is shown that the biocatalytic performance of the lipase-encapsulated, attached zeolite Beta-coated stainless steel supports with a zeolite Beta layer thickness of ≈0.7–1 μm is better than the lipase-encapsulated, attached zeolite Beta-coated stainless steel supports with a zeolite Beta layer thickness of ≈2–3 μm in the lipase-catalyzed transesterification of vinyl propionate with 1-butanol using n-hexane as solvent.

Zeolitic Materials with Hierarchical Porous Structures - Lopez Orozco, Sofia; Inayat, Amer; Schwab, Andreas; Selvam, Thangaraj; Schwieger, Wilhelm (Advanced Materials, 2011)
During the past several years, different kinds of hierarchical structured zeolitic materials have been synthesized due to their highly attractive properties, such as superior mass/heat transfer characteristics, lower restriction of the diffusion of reactants in the mesopores, and low pressure drop. Our contribution provides general information regarding types and preparation methods of hierarchical zeolitic materials and their relative advantages and disadvantages. Thereafter, recent advances in the preparation and characterization of hierarchical zeolitic structures within the crystallites by post-synthetic treatment methods, such as dealumination or desilication; and structured devices by in situ and ex situ zeolite coatings on open-cellular ceramic foams as (non-reactive as well as reactive) supports are highlighted. Specific advantages of using hierarchical zeolitic catalysts/structures in selected catalytic reactions, such as benzene to phenol (BTOP) and methanol to olefins (MTO) are presented.

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu](4) by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu](4) building blocks with O-3 in ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu](4) and [C(2)C(1)Im][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu](4) was analyzed between 300 and 4000 cm(-1) based on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu](4) in [C(2)C(1)Im][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10(-6) mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [C(2)C(1)Im][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of O-3 to [C(2)C(1)Im](+) and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu](4)/[C(2)C(1)Im][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [C(2)C(1)Im][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [C(2)C(1)Im][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [C(2)C(1)Im][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu]4 by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu]“building blocks” with Oin ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu]and [CCIm][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu]was analyzed between 300 and 4000 cmbased on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu]in [CCIm][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [CCIm][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of Oto [CCIm]and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu]/[CCIm][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [CCIm][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [CCIm][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [CCIm][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science

ZnO quantum dots modified bioactive glass nanoparticles with pH-sensitive release of Zn ions, fluorescence, antibacterial and osteogenic properties - Zheng, Kai; Lu, Miao; Rutkowski, Bogdan; Dai, Xinyi; Yang, Yuyun; Taccardi, Nicola; Stachewicz, Urszula; Czyrska-Filemonowicz, Aleksandra; Hueser, Norbert; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2016)

Zur Struktur und Konstitution von Dichloro(tetraalkylcyclobutadien)platin(II)-Komplexen - Steinborn, Dirk; Gerisch, M.; Heinemann, Frank Wilhelm; Scholz, Judith; Schenzel, K. (Zeitschrift für Anorganische und Allgemeine Chemie, 1995)

Zwitterionic clusters with dianion core produced by electrospray ionisation of Brønsted acidic ionic liquids - Li, Jing; Nye, Leanne; Schulz, Peter; Wasserscheid, Peter; Ivanovic-Burmazovic, Ivana; Drewello, Thomas; Wei, Wei (Physical Chemistry Chemical Physics, 2012)
New Brønsted acidic ionic liquids (BAILs) are prepared by treating zwitterions, which are composed of an imidazolium cation and a sulfonate anion, with an alkanedisulfonic acid. Acidification of the zwitterions produces the cation and deprotonation of the alkanedisulfonic acid forms the anion of the new BAILs. Direct laser desorption/ionisation (LDI), matrix-assisted LDI (MALDI) and electrospray ionisation (ESI) are employed to transfer ions into the gas-phase for detection by mass spectrometry and for dissociation studies by tandem mass spectrometry. The components of the BAILs are confirmed by LDI and MALDI by the detection of the respective cation and anion and by ESI by the observation of the cation and the dianion. A prominent feature of ESI is the formation of aggregates (cluster ions). Positively charged cluster ions are formally composed of multiple zwitterions plus one additional proton. In the negative-ion mode the clusters also incorporate the zwitterions which are, however, linked with the alkanedisulfonate dianion. In collision-induced dissociations (CID), the cationic aggregates show the evaporation of zwitterions until the protonated zwitterion is reached. Similarly, the cluster dianions release zwitterions until the free alkane disulfonate dianion is reached. However, the 1:1 adduct of dianion and zwitterion also displays proton transfer and Coulomb explosion into the mono-protonated disulfonic mono-anion and an imidazole-based carbene with sulfonate mono-anion. © 2012 the Owner Societies.

Zwitterionic Hydrobromic Acid Carriers for the Synthesis of 2-Bromopropionic Acid from Lactide - Kehrer, Matthias; Mehler, Julian; Taccardi, Nicola; Nagengast, Jens; Kadar, Julian; Collias, Dimitris; Dziezok, Peter; Wasserscheid, Peter; Albert, Jakob (ChemSusChem, 2018)
A convenient and highly efficient way of synthesizing 2‐bromopropionic acid (2‐BrPA) from lactide is presented. The procedure uses ionic liquids obtained from the addition of HBr to ammonium‐based zwitterions as the solvent and bromination agent. The buffered HBr acidity, high polarity, and charge stabilizing character of the ionic liquid (IL) enable the synthesis of 2‐BrPA with excellent selectivity. The best results are obtained with an imidazolium‐based IL, that is, 1‐(4‐butanesulfonic acid)‐3‐methylimidazolium bromide ([MIMBS]Br). The HBr loading and water content of the IL are crucial parameters for the bromination reaction. The formed 2‐BrPA product can be selectively isolated by extraction from the IL, and the unconverted substrate remains in the [MIMBS]Br IL for the next run. Successful recycling of the IL over four cycles is demonstrated.
Keywords: bromination; ionic liquids; lactide; renewable resources; zwitterions